Food Insecurity, Race and Ethnicity, and Cognitive Function Among United States Older Adults. - Wang, Haowei; El-Abbadi, Naglaa (The Journal of Nutrition, 2024)
BACKGROUND: Cognitive impairment and dementia are severe public health issues in aging populations, which can be exacerbated by insufficient or unhealthy dietary intake. Food (in)security status is linked to cognitive function among older adults, but the relationship is complex and can vary by sociodemographic characteristics. OBJECTIVE: This article aimed to investigate the association between food insecurity and cognitive function among United States older adults and explore potential variations by race and ethnicity groups. METHODS: We prospectively examined changes in cognitive function and incidence of cognitive impairment alongside the presence of self-reported food insecurity among older adults of different racial and ethnic groups. Data were from the 2012-2018 Health and Retirement Study (HRS) and the 2013 Health Care and Nutrition Study (HCNS), including N = 6,638 United States adults aged 50 years and older. Food insecurity was measured by a self-reported United States Household Food Security Survey Module, and cognitive function was assessed by the modified version of the Telephone Interview for Cognitive Status. RESULTS: Results showed that 17% of United States older adults reported food insecurity in the 2013 HCNS. Compared with food secure older adults, those reporting food insecurity experienced worsened cognitive functioning over time (B = -0.63, p < .001), and they were more likely to have onset of cognitive impairment (OR= 1.46, p < .001) in the 6-y observation. Compared with non-Hispanic White older adults, being non-Hispanic Black, non-Hispanic Other, or Hispanic was associated with 2.96, 2.09, or 1.26 odds (p < .001) of cognitive impairment (2012-2018), respectively. Older adults of racial and ethnic minority groups also had higher risks of experiencing the double burden of cognitive impairment alongside food insecurity compared with non-Hispanic White older adults. CONCLUSION: Findings underscore racial and ethnic structural disparities in food security and cognitive health in the United States aging population.
Keywords: Aged; Cognition; Cognitive Dysfunction; ethnicity; Food insecurity; Food Supply; Humans; Middle Aged; Minority Groups; Racial Groups; United States

Food Security and Health Outcomes following Gray Divorce. - Zhao, Hang; Andreyeva, Tatiana; Sun, Xiaohan (Nutrients, 2024)
The study evaluates the immediate and long-term consequences of gray divorce (i.e., marital dissolution after age 50) for the food security, depression, and disability of older Americans. Staggered Difference-in-Difference models were fitted to a nationally representative longitudinal sample of adults aged ≥ 50 years from the Health and Retirement Study, 1998-2018. Food insecurity and disability increase in the year of gray divorce and remain significantly elevated for up to six years or more following the event, consistent with the chronic strain model of gray divorce. Gray divorce has particularly adverse consequences for the food security of older women, while no gender differences were observed for disability. Increasing trends in gray divorce have important negative implications for food security and health of older Americans, particularly women, who appear to be less prepared to financially withstand a marital collapse in older age. Targeted policies to provide nutrition assistance and support in reemployment might be necessary to reduce the burden of food insecurity in the wake of gray divorce among women.
Keywords: Adult; Aged; Divorce; Female; Food security; Food Supply; Humans; Marriage; Outcome Assessment, Health Care; Retirement; United States

Perceived neighborhood disorder and type 2 diabetes disparities in Hispanic, Black, and White Americans. - Yu, Min Ying; Velasquez, Alfredo J; Campos, Belinda; Robinette, Jennifer W (Frontiers in Public Health, 2024)
INTRODUCTION: Approximately 32 million Americans have type 2 diabetes, and that number continues to grow. Higher prevalence rates are observed among certain subgroups, including members of marginalized racial/ethnic groups as well as residents of disordered neighborhoods (i.e., those with more trash and vandalism). Institutionalized discriminatory practices have resulted in disproportionate representation of marginalized racial/ethnic groups in disordered neighborhoods compared to non-Hispanic Whites. These neighborhood disparities may partially contribute to health disparities, given that signs of neighborhood disorder often relate to a general withdrawal from the neighborhood, minimizing opportunities for both physical and social engagement. Yet, research suggests variability across racial/ethnic groups both in reporting rates of neighborhood disorder and in the extent to which neighborhood disorder is interpreted as posing a threat to health and well-being. METHODS: Using 2016-2018 Health and Retirement Study data (n = 10,419, mean age = 67 years), a representative sample of older US adults, this study examined the possibility of racial/ethnic differences in associations between perceived neighborhood disorder and type 2 diabetes risk. Participants reported their perceptions of neighborhood disorder and type 2 diabetes status. Weighted logistic regression models predicted type 2 diabetes risk by perceived neighborhood disorder, race/ethnicity, and their interaction. RESULTS: Non-Hispanic Blacks and Hispanics had higher type 2 diabetes risk; these two groups also reported more disorder in their neighborhoods compared to non-Hispanic Whites. Perceiving more neighborhood disorder was associated with increased type 2 diabetes risk, but the interaction between race/ethnicity and disorder was not significant. DISCUSSION: Findings from the current study suggest that the negative effects of perceiving neighborhood disorder, a neighborhood-level stressor, extend to increased type 2 diabetes risk.
Keywords: Adult; Aged; Diabetes Mellitus, Type 2; ethnicity; Hispanic or Latino; Humans; Middle Aged; United States; White; White People

Personality traits and the risk of urinary incontinence: Evidence from three longitudinal samples. - Stephan, Yannick; Sutin, Angelina R; Terracciano, Antonio (International Journal of Geriatric Psychiatry, 2024)
OBJECTIVE: Urinary incontinence (UI) is a common condition with a substantial negative impact on older adults' quality of life. This study examines whether individual differences in behavioral, cognitive, and emotional traits assessed by the five major dimensions of personality are related to the risk of concurrent and incident UI. METHODS: Participants were older women and men (N > 26,000) from the Midlife in the United States Survey, the Health and Retirement Study, and the English Longitudinal Study of Aging. In each cohort, personality traits (measured with the Midlife Development Inventory) and demographic (age, sex, education, and race), clinical (body mass index, diabetes, blood pressure), and behavioral (smoking) factors were assessed at baseline. UI was assessed at baseline and again 8-20 years later. Results for each cohort were combined in random-effect meta-analyses. RESULTS: Consistently across cohorts, higher neuroticism and lower conscientiousness were related to a higher risk of concurrent and incident UI. To a lesser extent, extraversion, openness, and agreeableness were also related to lower risk of concurrent and incident UI. BMI, diabetes, blood pressure, and smoking partially accounted for these associations. There was little evidence that age or sex moderated the associations. CONCLUSIONS: The present study provides novel, robust, and replicable evidence linking personality traits to UI. The higher vulnerability for UI for individuals who score higher on neuroticism and lower on conscientiousness is consistent with findings for other multifactorial geriatric syndromes. Personality traits can help identify individuals at risk and may help contextualize the clinical presentation of comorbid emotional, cognitive, and behavioral symptoms.
Keywords: Aged; Diabetes Mellitus; Female; Humans; Longitudinal Studies; Male; Neuroticism; Personality; Personality Disorders; Personality Inventory; Quality of Life; United States

The Potential of Informal Care for Self-Perceptions of Aging Among Older Community-Dwelling Adults: Longitudinal Findings From the Health and Retirement Study. - Zwar, Larissa; König, Hans-Helmut; Hajek, André (Journal of Applied Gerontology, Series B, Psychological Sciences and social sciences, 2024)
OBJECTIVES: This is the first study to analyze, whether receipt of (informal) care with (instrumental) activities of daily living (IADL/ADL) is associated with (positive and negative) self-perceptions of aging among community-dwelling older adults; and whether chronological age moderates these associations, using a longitudinal design. METHODS: Longitudinal data of the Health and Retirement Study in the United States was used. The sample was composed of up to 9,198 observations of community-dwelling adults aged ≥50 years pooled over 6 waves (2008-2018). Receiving care at all and the amount of care received with (I)ADL were analyzed in association with positive and negative attitudes towards own aging (ATOA; 8-item modified Philadelphia Geriatric Center Morale Scale, positive and negative subscore). Adjusted fixed effects regression analyses with robust standard errors were calculated. RESULTS: Transitioning into receipt of care with any (I)ADL was associated with lower positive ATOA but not with any change in negative ATOA. Chronological age moderated the association between receipt of informal care, primarily with IADL, and negative ATOA. More negative ATOA was found among care recipients between 50 and 64 years but less among care recipients aged ≥80 years. DISCUSSION: Receiving any form of informal care was associated with an increase in internalized ageism, in particular among adults aged 50 to 64 years, but a decrease among those aged ≥80 years. Psycho-educative measures are recommended for adults with care needs to prevent a loss of positive self-perceptions of aging, and reduce the danger to their healthy aging, with the receipt of care.
Keywords: Activities of Daily Living; Aged; Humans; Independent Living; Longitudinal Studies; Patient Care; Retirement; Self Concept; United States

The Prevalence of Cognitive Impairment Among Medicare Beneficiaries Who Use Outpatient Physical Therapy. - Miller, Matthew J; Cenzer, Irena; Barnes, Deborah E; Kelley, Amy S; Covinsky, Kenneth E (Physical Therapy, 2024)
OBJECTIVE: The objective of this study was to estimate the prevalence of cognitive impairment (including cognitive impairment no dementia [CIND] and dementia) among Medicare fee-for-service beneficiaries who used outpatient physical therapy and to estimate the prevalence of cognitive impairment by measures that are relevant to rehabilitation practice. METHODS: This cross-sectional analysis included 730 Medicare fee-for-service beneficiaries in the 2016 wave of the Health and Retirement Study with claims for outpatient physical therapy. Cognitive status, our primary variable of interest, was categorized as normal, CIND, or dementia using a validated approach, and population prevalence of cognitive impairment (CIND and dementia) was estimated by sociodemographic variables and Charlson comorbidity index score. Age-, gender- (man/woman), race-/ethnicity-adjusted population prevalence of CIND and dementia were also calculated for walking difficulty severity, presence of significant pain, self-reported fall history, moderate-vigorous physical activity (MVPA) ≤1×/week, and sleep disturbance frequency using multinomial logistic regression. RESULTS: Among Medicare beneficiaries with outpatient physical therapist claims, the prevalence of any cognitive impairment was 20.3% (CIND:15.2%, dementia:5.1%). Cognitive impairment was more prevalent among those who were older, Black, had lower education attainment, or higher Charlson comorbidity index scores. The adjusted population prevalence of cognitive impairment among those who reported difficulty walking across the room was 29.8%, difficulty walking 1 block was 25.9%, difficulty walking several blocks was 20.8%, and no difficulty walking was 16.3%. Additionally, prevalence of cognitive impairment among those with MVPA ≤1×/week was 27.1% and MVPA >1×/week was 14.1%. Cognitive impairment prevalence did not vary by significant pain, self-reported fall history, or sleep disturbance. CONCLUSION: One in 5 older adults who use outpatient physical therapist services have cognitive impairment. Furthermore, cognitive impairment is more common in older physical therapist patients who report worse physical function and less physical activity. IMPACT: Physical therapists should consider cognitive screening for vulnerable older adults to inform tailoring of clinical practice toward a patient's ability to remember and process rehabilitation recommendations.
Keywords: Aged; Cognitive Dysfunction; Cross-Sectional Studies; Dementia; Female; Humans; Male; Medicare; Mobility Limitation; Outpatients; pain; Physical Therapy Modalities; Prevalence; United States

Purposeful and purposeless aging: Structural issues for sense of purpose and their implications for predicting life outcomes. - Pfund, Gabrielle N; Olaru, Gabriel; Allemand, Mathias; Hill, Patrick L (Developmental Psychology, 2024)
Despite the value of sense of purpose during older adulthood, this construct often declines with age. With some older adults reconsidering the relevance of purpose later in life, the measurement of purpose may suffer from variance issues with age. The current study investigated whether sense of purpose functions similarly across ages and evaluated if the predictive power of purpose on mental, physical, cognitive, and financial outcomes changes when accounting for a less age-affected measurement structure. Utilizing data from two nationwide panel studies (Health and Retirement Study: = 14,481; Midlife in the United States: = 4,030), the current study conducted local structural equation modeling and found two factors for the positively and negatively valenced purpose items in the Purpose in Life subscale (Ryff, 1989), deemed the purposeful and purposeless factor. These factors become less associated with each other at higher ages. When reproducing past findings with this two-factor structure, the current study found that the purposeful and purposeless factors predicted these outcomes in the same direction as would be suggested by past research, but the magnitude of these effects differed for some outcomes. The discussion focuses on the implications of what this means for our understanding of sense of purpose across the lifespan. (PsycInfo Database Record (c) 2024 APA, all rights reserved).
Keywords: Aged; Aging; Humans; Longevity; Retirement; United States

Residential greenspace and major depression among older adults living in urban and suburban areas with different climates across the United States. - Fossa, Alan J; D'Souza, Jennifer; Bergmans, Rachel; Zivin, Kara; Adar, Sara D (Environmental Research, 2024)
BACKGROUND AND AIM: Residential greenspace could alleviate depression - a leading cause of disability. Fewer studies of depression and greenspace have considered major depression, and, to our knowledge, none have considered how climate, which determines vegetation abundance and type, may change the impacts of greenspace. Our aim was to investigate whether residential greenspace is associated with major depression among older adults and explore effect modification by climate. METHODS: We used biennial interviews between 2008 and 2016 from the Health and Retirement Study. We calculated greenness within walking distance of home addresses as the maximum NDVI for the year of each participant interview averaged within a 1 km buffer. Reflecting clinical criteria, a score of ≥5 on the CIDI-SF indicated major depression in the preceding 12-months. We characterized climate using Köppen-Geiger classifications. To estimate prevalence ratios, we used Poisson regression. Our models adjusted for sociodemographic characteristics, geography, annual sunshine, and bluespace. RESULTS: The 21,611 eligible participants were 65 ± 10 years old on average, 55% female, 81% White, 12% Black, 10% Hispanic/Latino, and 31% had at least a 4-year college degree. The 12-month prevalence of a major depression was 8%. In adjusted models, more residential greenspace was associated with a lower prevalence of major depression (prevalence ratio per IQR, 0.91; 95% CI, 0.84 to 0.98). There was evidence of effect modification by climate (P forinteraction, 0.062). We observed stronger associations in tropical (prevalence ratio per IQR 0.69; 95% CI, 0.47 to 1.01) and cold (prevalence ratio per IQR, 0.83; 95% CI, 0.74 to 0.93) climates compared to arid (prevalence ratio per IQR 0.99; 95% CI, 0.90 to 1.09) and temperate (prevalence ratio per IQR 0.98; 95% CI, 0.86 to 1.11) climates. CONCLUSIONS: Residential greenspace may help reduce major depression. However, climate may influence how people benefit from greenspace.
Keywords: Aged; depression; Depressive Disorder, Major; Environmental Exposure; Female; Humans; Male; Mental Health; Middle Aged; Parks, Recreational; United States

Return Migration and Disability by Life Course Stage of Return: Evidence Against the Salmon Bias. - Sheftel, Mara Getz (The Journals of Gerontology, Series B, Psychological Sciences and Social Sciences, 2024)
OBJECTIVES: Life course theory points to unique characteristics among older immigrants that may differentiate older age return migration from return at younger ages in terms of health. To investigate how the health of returnees may differ by age-at-return, this analysis compares disability between 3 groups of Mexican adults with a history of migration to the United States: those who return to Mexico before age 50, those who return at 50 and older, and those who remain in the United States at age 50 and older. METHODS: Data from two nationally representative data sets, the U.S. Health and Retirement Study and the Mexican Health and Aging Study, are combined to create a data set representing Mexicans 50 and older with a history of migration to the United States. Adopting a life course perspective, activity of daily living (ADL) difficulty is compared by return status and age-at-return to account for differential selection into return by life stage. RESULTS: Mexican immigrants who remain in the United States past age 50 have a higher probability of at least 1 ADL compared to those who return to Mexico, regardless of life course timing of return. The immigrant disadvantage persists after adjusting for differences in demographic, childhood, and adult characteristics between groups. DISCUSSION: These findings are noteworthy because they stand in opposition to hypotheses based on life course and health-selective return migration theories and because they mean that Mexican immigrants remaining in the United States into midlife and older adulthood may be vulnerable to heightened prevalence of disability.
Keywords: Disabled Persons; Emigrants and Immigrants; Emigration and Immigration; Humans; Life Change Events; Mexican Americans; Mexico; Middle Aged; North American People; United States

Variation in Home Healthcare Use by Dementia Status Among a National Cohort of Older Adults. - Burgdorf, Julia G; Ornstein, Katherine A; Liu, Bian; Leff, Bruce; Brody, Abraham A; McDonough, Catherine; Ritchie, Christine S (Journals of Gerontology. Series A Biological Sciences and Medical Sciences, 2024)
BACKGROUND: Medicare-funded home healthcare (HHC) delivers skilled nursing, therapy, and related services through visits to the patient's home. Nearly one-third (31%) of HHC patients have diagnosed dementia, but little is currently known regarding how HHC utilization and care delivery differ for persons living with dementia (PLwD). METHODS: We drew on linked 2012-2018 Health and Retirement Study and Medicare claims for a national cohort of 1 940 community-living older adults. We described differences in HHC admission, length of stay, and referral source by patient dementia status and used weighted, multivariable logistic and negative binomial models to estimate the relationship between dementia and HHC visit type and intensity while adjusting for sociodemographic characteristics, health and functional status, and geographic/community factors. RESULTS: PLwD had twice the odds of using HHC during a 2-year observation period, compared to those without dementia (odds ratio [OR]: 2.03; p < .001). They were more likely to be referred to HHC without a preceding hospitalization (49.4% vs 32.1%; p < .001) and incurred a greater number of HHC episodes (1.4 vs 1.0; p < .001) and a longer median HHC length of stay (55.8 days vs 40.0 days; p < .001). Among post-acute HHC patients, PLwD had twice the odds of receiving social work services (unadjusted odds ratio [aOR]: 2.15; p = .008) and 3 times the odds of receiving speech-language pathology services (aOR: 2.92; p = .002). CONCLUSIONS: Findings highlight HHC's importance as a care setting for community-living PLwD and indicate the need to identify care delivery patterns associated with positive outcomes for PLwD and design tailored HHC clinical pathways for this patient subpopulation.
Keywords: Aged; Delivery of Health Care; Dementia; Home Care Services; Hospitalization; Humans; Medicare; United States

Adverse Childhood Experiences, Social Isolation, Job Strain, and Cardiovascular Disease Mortality in U.S. Older Employees. - Matthews, Timothy A; Li, Jian (Medicina (Kaunas), 2023)
Stress is a key driver of cardiovascular disease (CVD), yet the contribution of psychosocial stressors to the development of CVD has not been systematically examined in United States (U.S.) populations. The objective of this study was to assess prospective associations of adverse childhood experiences (ACEs), social isolation, and job strain with CVD mortality. Data were from the large, nationally representative, population-based Health and Retirement Study (HRS). ACEs, social isolation and job strain were assessed using validated survey instruments at baseline between 2006-2008, and death information was followed up through 2018. Cox proportional hazards regression models were used to examine prospective associations of ACEs, social isolation, and job strain with CVD mortality among 4046 older employees free from CVD at baseline. During 42,149 person-years of follow-up time, 59 death cases of CVD were reported. After adjustment for covariates, ACEs and job strain were significantly associated with increased risk of CVD mortality (aHR and 95% CI = 3.67 [1.59, 8.48] and 2.24 [1.21, 4.11], respectively), whereas social isolation demonstrated an inflated but nonsignificant association (aHR and 95% CI = 1.62 [0.72, 3.66]). These findings highlight the role of psychosocial exposures as novel and clinically relevant risk factors for CVD.
Keywords: Adverse Childhood Experiences; Cardiovascular Diseases; Humans; Risk Factors; social isolation; Surveys and Questionnaires; United States

[Analysis of healthy life expectancy and related socioeconomic influencing factors among the middle-aged and elderly in China, the United States, and the European Union]. - Hou, X D; Luo, Y N; Jin, Y Z; Zheng, Z J (Zhonghua Liu Xing Bing Xue Za Zhi, 2023)
To calculate and compare the healthy life expectancy (HLE) of the middle-aged and elderly in China, the United States, and developing and developed countries in the European Union(EU) and analyze the impact of socioeconomic factors on HLE in different countries or regions. Four surveys from 2010 to 2019 were brought into the research. The data were collected from the China Health and Retirement Longitudinal Study, Health and Retirement Study, and the Survey of Health, Ageing and Retirement in Europe. Developed and developing countries in the EU were divided into two groups for calculation. Education level, total family wealth, and work retirement status were selected to measure socioeconomic status, and activities of daily living were used as health status indicators. We used the multi-state life cycle table method to calculate the transition probability between different health states and estimate life expectancy and HLE. A total of 69 544 samples were included in the study. In terms of age, the middle-aged and elderly in the United States and developed countries of the EU have higher HLE in all age groups. In terms of gender, only Chinese women have lower HLE than men. Regarding socioeconomic factors, the middle-aged and elderly with higher education levels and total family wealth level have higher HLE. In China, working seniors have higher HLE, while for USA women and developed countries of the EU, retired or unemployed seniors have higher HLE. Demographic and socioeconomic factors impact HLE in different countries or regions. China should pay more attention to the health of women and the middle-aged and elderly retired with lower education and less total family wealth.
Keywords: Activities of Daily Living; Aged; China; European Union; Female; Healthy life expectancy; Humans; Longitudinal Studies; Male; Middle Aged; Socioeconomic factors; United States

Association between perceived risk of Alzheimer's disease and related dementias and cognitive function among U.S. older adults. - Wang, Nan; Xu, Hanzhang; West, Jessica S; Østbye, Truls; Wu, Bei; Xian, Ying; Dupre, Matthew E (Arch Gerontol Geriatr, 2023)
INTRODUCTION: The aim of the study was to assess factors associated with the perceived risk of developing Alzheimer's disease and related dementias (ADRD) and how the perceived risk of ADRD was related to cognitive function. METHODS: We conducted a retrospective cohort study using 5 waves of data from the Health and Retirement Study (2012-2022) that included adults aged 65 years or older with no previous diagnosis of ADRD at baseline. Cognitive function was measured at baseline and over time using a summary score that included immediate/delayed word recall, serial 7's test, objective naming test, backwards counting, recall of the current date, and naming the president/vice-president (range = 0-35). Perceived risk of developing ADRD was categorized at baseline as "definitely not" (0% probability), "unlikely" (1-49%), "uncertain" (50%), and "more than likely" (>50-100%). Additional baseline measures included participants' sociodemographic background, psychosocial resources, health behaviors, physiological status, and healthcare utilization. RESULTS: Of 1457 respondents (median age 74 [IQR = 69-80] and 59.8% women), individuals who perceived that they were "more than likely" to develop ADRD had more depressive symptoms and were more likely to be hospitalized in the past two years than individuals who indicated that it was "unlikely" they would develop ADRD. Alternatively, respondnets who perceived that they would "definitely not" develop ADRD were more likely to be non-Hispanic Black, less educated, and have lower income than individuals who indicated it was "unlikely" they would develop ADRD. Respondents who reported their risks of developing ADRD as "more than likely" (β = -2.10, P < 0.001) and "definitely not" (β = -1.50, P < 0.001) had the lowest levels of cognitive function; and the associations were explained in part by their socioeconomic, psychosocial, and health status. CONCLUSIONS: Perceived risk of developing ADRD is associated with cognitive function. The (dis)concordance between individuals' perceived risk of ADRD and their cognitive function has important implications for increasing public awareness and developing interventions to prevent ADRD.
Keywords: Alzheimer's disease; cognitive function; Dementia; Older Adults; United States

Associations between diagnosis with stroke, comorbidities, and activity of daily living among older adults in the United State - Suebsarn Ruksakulpiwat; Wendie Zhou; Lalipat Phianhasin; Chitchanok Benjasirisan; Saeideh Salehizadeh; Limin Wang; Joachim G. Voss (2023)
Background Stroke is the leading cause of mortality. This study aimed to investigate the association between stroke, comorbidities, and activity of daily living (ADL) among older adults in the United States. Methods Participants were 1165 older adults aged 60 and older from two waves (2016 and 2018) of the Health and Retirement Study who had a stroke. Descriptive statistics were used to describe demographic information and comorbidities. Logistic regressions and multiple regression analyses were used to determine associations between stroke, comorbidities, and ADL. Results The mean age was 75.32 ± 9.5 years, and 55.6% were female. An adjusted analysis shows that older stroke adults living with diabetes as comorbidity are significantly associated with difficulty in dressing, walking, bedding, and toileting. Moreover, depression was significantly associated with difficulty in dressing, walking, bathing, eating, and bedding. At the same time, heart conditions and hypertension as comorbidity were rarely associated with difficulty in ADL. After adjusting for age and sex, heart condition and depression are significantly associated with seeing a doctor for stroke (odds ratio [OR]: 0.66; 95% confidence interval [CI]: 0.49–0.91; p = 0.01) and stroke therapy (OR: 0.46; 95% CI: 0.25–0.84; p = 0.01). Finally, stroke problem (unstandardized β [B] = 0.58, p = 0.017) and stroke therapy (B = 1.42, p < 0.001) significantly predict a lower level of independence. Conclusion This study could benefit healthcare professionals in developing further interventions to improve older stroke adults' lives, especially those with a high level of dependence.
Keywords: Older Adults; Stroke; United States

Biological expressions of early life trauma in the immune system of older adults. - Noppert, Grace A; Duchowny, Kate A; Stebbins, Rebecca; Aiello, Allison E; Dowd, Jennifer B; Clarke, Philippa (PLoS One, 2023)
BACKGROUND: Poor immune function is associated with increased risk for a number of age-related diseases, however, little is known about the impact of early life trauma on immune function in late-life. METHODS: Using nationally representative data from the Health and Retirement Study (n = 5,823), we examined the association between experiencing parental/caregiver death or separation before age 16 and four indicators of immune function in late-life: C-reactive Protein (CRP), Interleukin-6 (IL-6), soluble Tumor Necrosis Factor (sTNFR), and Immunoglobulin G (IgG) response to cytomegalovirus (CMV). We also examined racial/ethnic differences. FINDINGS: Individuals that identified as racial/ethnic minorities were more likely to experience parental/caregiver loss and parental separation in early life compared to Non-Hispanic Whites, and had poorer immune function in late-life. We found consistent associations between experiencing parental/caregiver loss and separation and poor immune function measured by CMV IgG levels and IL-6 across all racial/ethnic subgroups. For example, among Non-Hispanic Blacks, those that experienced parental/caregiver death before age 16 had a 26% increase in CMV IgG antibodies in late-life (β = 1.26; 95% CI: 1.17, 1.34) compared to a 3% increase in CMV antibodies among Non-Hispanic Whites (β = 1.03; 95% CI: 0.99, 1.07) controlling for age, gender, and parental education. INTERPRETATION: Our results suggest a durable association between experiencing early life trauma and immune health in late-life, and that structural forces may shape the ways in which these relationships unfold over the life course.
Keywords: Adolescent; Aged; Cytomegalovirus Infections; Humans; Immune System; Immunoglobulin G; Interleukin-6; United States; White

Breast and prostate cancer screening rates by cognitive status in US older adults. - Schoenborn, Nancy L; Cidav, Tom; Boyd, Cynthia M; Pollack, Craig E; Sekhon, Vishaldeep Kaur; Yasar, Sevil (J Am Geriatr Soc, 2023)
INTRODUCTION: For most older adults with dementia, the short-term harms and burdens of routine cancer screening likely outweigh the delayed benefits. We aimed to provide a more updated assessment of the extent that US older adults with dementia receive breast and prostate cancer screenings. METHODS: Using the Health and Retirement Study (HRS) Wave 12 (2014-2015) linked to Medicare, we examine rates of breast and prostate cancer screenings in adults 65+ years by cognitive status. We used claims data to identify eligibility for screening and receipt of screening. We used a validated method using HRS data to define cognitive status. RESULTS: The analytic sample included 2439 women in the breast cancer screening cohort and 1846 men in the prostate cancer screening cohort. Average ages were 76.8 years for women and 75.6 years for men, with 9.0% and 7.6% with dementia in each cohort, respectively. Among women with dementia, 12.3% were screened for breast cancer. When stratified by age, 10.6% of those 75+ and have dementia were screened for breast cancer. When stratified by predicted life expectancy, 10.4% of those with predicted life expectancy of <10 years and have dementia were screened for breast cancer. Among men with dementia, 33.9% were screened for prostate cancer. When stratified by age, 30.9% of those 75+ and have dementia were screened for prostate cancer. When stratified by predicted life expectancy, 34.4% of those with predicted life expectancy of <10 years and have dementia were screened for prostate cancer. Using multivariable logistic regression, dementia was associated with lower odds of receiving breast cancer screening (OR 0.36, 95% CI 0.23-0.57) and prostate cancer screening (OR 0.58, 95% CI 0.36-0.96). DISCUSSION: Our results suggest potential over-screening in older adults with dementia. Better supporting dementia patients and caregivers to make informed cancer screening decisions is critical.
Keywords: Aged; Breast Neoplasms; Cognition; Dementia; Early Detection of Cancer; Humans; Male; Mass Screening; Medicare; Prostate-Specific Antigen; Prostatic Neoplasms; United States

Changes in Self-Perceptions of Aging Among Black and White Older Adults: The Role of Volunteering. - Huo, Meng; Kim, Kyungmin; Haghighat, Misha D (J Gerontol B Psychol Sci Soc Sci, 2023)
OBJECTIVES: Given the health consequences of self-perceptions of aging (SPA), understanding how SPA change among Black and White older adults may shed light on racial disparities in late-life health. The current study is the first to assess whether Black older adults exhibit less favorable patterns of change in SPA than White older adults. We also tested whether the salubrious effect of volunteering on SPA would be particularly salient among Black older adults. METHODS: A pooled sample of adults aged 50+ (N = 10,183; Black: n = 1,672, White: n = 8,511) from the Health and Retirement Study rated positive and negative SPA once every 4 years across 3 waves (2008/2010, 2012/2014, and 2016/2018). We assessed participants' reports on volunteering status in each wave. RESULTS: Growth curve models revealed that positive SPA decreased over time whereas negative SPA increased. Black older adults reported more positive and less negative SPA at baseline and flatter time-related changes than their White counterparts. We found that volunteering was significantly associated with more positive and less negative SPA across waves, but this effect was only evident in White older adults. DISCUSSION: Findings revealed vulnerabilities in White older adults as they experience and perceive age-related changes but also identified volunteering as a way to uniquely protect them. More research is needed to refine our understanding of racial disparities in the United States and help tailor interventions intended to maximize benefits to older adults from diverse backgrounds.
Keywords: Aged; Aging; Black People; Humans; Racial Groups; Self Concept; United States; White

Comparison of sex differences in cognitive function in older adults between high- and middle-income countries and the role of education: a population-based multicohort study. - Bloomberg, Mikaela; Dugravot, Aline; Sommerlad, Andrew; Kivimäki, Mika; Singh-Manoux, Archana; Sabia, Séverine (Age Ageing, 2023)
BACKGROUND: The extent to which education explains variations in sex differences in cognitive function between countries at different levels of economic development is unknown. We examined the role of education in sex differences in four cognitive domains in high- and middle-income countries. METHODS: Analyses were based on 70,846 participants, aged 60 years and older, in cohort studies from a high-income (United States) and four middle-income countries (Mexico, Brazil, China, and India). We used weighted linear models to allow nationally-representative comparisons of sex differences in orientation, memory, attention, and fluency using the United States as the reference, before and after adjustment for education, and after stratification by education. RESULTS: Females had lower levels of education than males in all countries, particularly in India. Before adjustment for education, sex differences in orientation and attention in all middle-income countries, memory in Brazil, China, and India, and fluency in India were less favourable to females than in the United States (P < 0.010). For example, females outperformed males in memory in the United States (mean difference [male-female scores] = -0.26 standard deviations [95% CI -0.30, -0.22]) but not in China (0.15 [0.09, 0.21]) or India (0.16 [0.13, 0.19]). Adjustment for education attenuated these sex differences. In analyses stratified by education, there were minimal sex differences in the high education group in all countries. CONCLUSION: Education contributes to larger female disadvantages in cognitive function at older ages in middle-income countries compared with the United States. Gender equity in education is an important target to reduce sex disparities in cognitive function globally.
Keywords: Aged; Cognition; Developing Countries; Educational Status; Female; Humans; Income; Male; Middle Aged; Sex Characteristics; United States

The Construction of a Multidomain Risk Model of Alzheimer's Disease and Related Dementias. - Akushevich, Igor; Yashkin, Arseniy; Ukraintseva, Svetlana; Yashin, Anatoliy I; Kravchenko, Julia (Journal of Alzheimer's Disease : JAD, 2023)
BACKGROUND: Alzheimer's disease (AD) and related dementia (ADRD) risk is affected by multiple dependent risk factors; however, there is no consensus about their relative impact in the development of these disorders. OBJECTIVE: To rank the effects of potentially dependent risk factors and identify an optimal parsimonious set of measures for predicting AD/ADRD risk from a larger pool of potentially correlated predictors. METHODS: We used diagnosis record, survey, and genetic data from the Health and Retirement Study to assess the relative predictive strength of AD/ADRD risk factors spanning several domains: comorbidities, demographics/socioeconomics, health-related behavior, genetics, and environmental exposure. A modified stepwise-AIC-best-subset blanket algorithm was then used to select an optimal set of predictors. RESULTS: The final predictive model was reduced to 10 features for AD and 19 for ADRD; concordance statistics were about 0.85 for one-year and 0.70 for ten-year follow-up. Depression, arterial hypertension, traumatic brain injury, cerebrovascular diseases, and the APOE4 proxy SNP rs769449 had the strongest individual associations with AD/ADRD risk. AD/ADRD risk-related co-morbidities provide predictive power on par with key genetic vulnerabilities. CONCLUSION: Results confirm the consensus that circulatory diseases are the main comorbidities associated with AD/ADRD risk and show that clinical diagnosis records outperform comparable self-reported measures in predicting AD/ADRD risk. Model construction algorithms combined with modern data allows researchers to conserve power (especially in the study of disparities where disadvantaged groups are often grossly underrepresented) while accounting for a high proportion of AD/ADRD-risk-related population heterogeneity stemming from multiple domains.
Keywords: Alzheimer disease; Comorbidity; Dementia; Humans; Hypertension; Medicare; United States

Contributions of neighborhood social environment and air pollution exposure to Black-White disparities in epigenetic aging. - Yannatos, Isabel; Stites, Shana; Brown, Rebecca T; McMillan, Corey T (PLoS One, 2023)
Racial disparities in many aging-related health outcomes are persistent and pervasive among older Americans, reflecting accelerated biological aging for Black Americans compared to White, known as weathering. Environmental determinants that contribute to weathering are poorly understood. Having a higher biological age, measured by DNA methylation (DNAm), than chronological age is robustly associated with worse age-related outcomes and higher social adversity. We hypothesize that individual socioeconomic status (SES), neighborhood social environment, and air pollution exposures contribute to racial disparities in DNAm aging according to GrimAge and Dunedin Pace of Aging methylation (DPoAm). We perform retrospective cross-sectional analyses among 2,960 non-Hispanic participants (82% White, 18% Black) in the Health and Retirement Study whose 2016 DNAm age is linked to survey responses and geographic data. DNAm aging is defined as the residual after regressing DNAm age on chronological age. We observe Black individuals have significantly accelerated DNAm aging on average compared to White individuals according to GrimAge (239%) and DPoAm (238%). We implement multivariable linear regression models and threefold decomposition to identify exposures that contribute to this disparity. Exposure measures include individual-level SES, census-tract-level socioeconomic deprivation and air pollution (fine particulate matter, nitrogen dioxide, and ozone), and perceived neighborhood social and physical disorder. Race and gender are included as covariates. Regression and decomposition results show that individual-level SES is strongly associated with and accounts for a large portion of the disparity in both GrimAge and DPoAm aging. Higher neighborhood deprivation for Black participants significantly contributes to the disparity in GrimAge aging. Black participants are more vulnerable to fine particulate matter exposure for DPoAm, perhaps due to individual- and neighborhood-level SES, which may contribute to the disparity in DPoAm aging. DNAm aging may play a role in the environment "getting under the skin", contributing to age-related health disparities between older Black and White Americans.
Keywords: Aged; Aging; Air Pollution; Black or African American; Cross-Sectional Studies; Epigenesis, Genetic; Humans; Particulate Matter; Retrospective Studies; Social Environment; United States; White

Dementia Attributable Healthcare Utilizations in the Caribbean versus United States. - Li, Jing; Weiss, Jordan; Rajadhyaksha, Ashish; Acosta, Daisy (Journal of Alzheimers Disease: JAD, 2023)
BACKGROUND: Despite the high burden of Alzheimer's disease and other dementias among the Hispanic population worldwide, little is known about how dementia affects healthcare utilizations among this population outside of the US, in particular among those in the Caribbean region. OBJECTIVE: This study examines healthcare utilization associated with Alzheimer's disease and other dementias among older adults in the Caribbean as compared to the US. METHODS: We conducted harmonized analyses of two population-based surveys, the 10/66 Dementia Group Research data collected in Dominican Republic, Cuba, and Puerto Rico, and the US-based Health and Retirement Study. We examined changes in hospital nights and physician visits in response to incident and ongoing dementias. RESULTS: Incident dementia significantly increased the risk of hospitalization and number of hospital nights in both populations. Ongoing dementia increased the risk of hospitalization and hospital nights in the US, with imprecise estimates for the Caribbean. The number of physician visits was elevated in the US but not in the Caribbean. CONCLUSIONS: The concentration of increased healthcare utilization on hospital care and among patients with incident dementia suggests an opportunity for improved outpatient management of new and existing dementia patients in the Caribbean.
Keywords: Aged; Alzheimer disease; Delivery of Health Care; ethnicity; Humans; Patient Acceptance of Health Care; Puerto Rico; United States

Dementia Attributable Healthcare Utilizations in the Caribbean versus United States. - Li, Jing; Weiss, Jordan; Rajadhyaksha, Ashish; Acosta, Daisy; Harrati, Amal; Jiménez Velázquez, Ivonne Z; Liu, Mao-Mei; Guerra, Jorge J Llibre; Rodriguez, Juan de Jesús Llibre; Dow, William H (Journal of Alzheimers Disease: JAD, 2023)
BACKGROUND: Despite the high burden of Alzheimer's disease and other dementias among the Hispanic population worldwide, little is known about how dementia affects healthcare utilizations among this population outside of the US, in particular among those in the Caribbean region. OBJECTIVE: This study examines healthcare utilization associated with Alzheimer's disease and other dementias among older adults in the Caribbean as compared to the US. METHODS: We conducted harmonized analyses of two population-based surveys, the 10/66 Dementia Group Research data collected in Dominican Republic, Cuba, and Puerto Rico, and the US-based Health and Retirement Study. We examined changes in hospital nights and physician visits in response to incident and ongoing dementias. RESULTS: Incident dementia significantly increased the risk of hospitalization and number of hospital nights in both populations. Ongoing dementia increased the risk of hospitalization and hospital nights in the US, with imprecise estimates for the Caribbean. The number of physician visits was elevated in the US but not in the Caribbean. CONCLUSIONS: The concentration of increased healthcare utilization on hospital care and among patients with incident dementia suggests an opportunity for improved outpatient management of new and existing dementia patients in the Caribbean.
Keywords: Aged; Alzheimer disease; Delivery of Health Care; ethnicity; Humans; Patient Acceptance of Health Care; Puerto Rico; United States

Disparities in advance care planning among older US immigrants. - Mindo-Panusis, Dallas; Sudore, Rebecca L; Cenzer, Irena; Smith, Alexander K; Kotwal, Ashwin A (J Am Geriatr Soc, 2023)
BACKGROUND: Despite known racial disparities in advance care planning (ACP), little is known about ACP disparities experienced by US immigrants. METHODS: We used data from the 2016 wave of the Health and Retirement Study. We defined ACP engagement as self-reported end-of-life (EOL) discussions, designation of a power of attorney (DPOA), documented living will, or "any" of the three behaviors. Immigration status was determined by respondent-reported birth outside the United States. Time in the United States was calculated by subtracting the year of arrival in the United States from the survey year of 2016. We used multivariable logistic regression to estimate the association between ACP engagement and immigration status and the relationship of acculturation to ACP engagement, adjusting for sociodemographics, religiosity, and life expectancy. RESULTS: Of the total cohort (N = 9928), 10% were immigrants; 45% of immigrants identified as Hispanic. After adjustment, immigrants had significantly lower adjusted probability of any ACP engagement (immigrants: 74% vs. US-born: 83%, p < 0.001), EOL discussions (67% vs. 77%, p < 0.001), DPOA designation (50% vs. 59%, p = 0.001) and living will documentation (50% vs. 56%, p = 0.03). Among immigrants, each year in the United States was associated with a 4% increase in the odds of any ACP engagement (aOR 1.04, 95% CI 1.03-1.06), ranging from 36% engaged 10 years after immigration to 78% after 70 years. CONCLUSION: ACP engagement was lower for US immigrants compared to US-born older adults, particularly for those that recently immigrated. Future studies should explore strategies to reduce disparities in ACP and the unique ACP needs among different immigrant populations.
Keywords: care planning; Disparities; Immigrants; United States

Does education moderate gender disparities in later-life memory function? A cross-national comparison of harmonized cognitive assessment protocols in the United States and India. - Westrick, Ashly C; Avila-Rieger, Justina; Gross, Alden L; Hohman, Timothy; Vonk, Jet M J; Zahodne, Laura B; Lindsay C Kobayashi (Alzheimers Dement, 2023)
INTRODUCTION: We compared gender disparities in later-life memory, overall and by education, in India and the United States (US). METHODS: Data (N = 7443) were from harmonized cognitive assessment protocols (HCAPs) in the Longitudinal Aging Study of India-Diagnostic Assessment of Dementia (LASI-DAD; N = 4096; 2017-19) and US Health and Retirement Study HCAP (HRS-HCAP; N = 3347; 2016-17). We derived harmonized memory factors from each study using confirmatory factor analysis. We used multivariable-adjusted linear regression to compare gender disparities in memory function between countries, overall and by education. RESULTS: In the United States, older women had better memory than older men (0.28 SD-unit difference; 95% CI: 0.22, 0.35). In India, older women had worse memory than older men (-0.15 SD-unit difference; 95% CI: -0.20, -0.10), which attenuated with increasing education and literacy. CONCLUSION: We observed gender disparities in memory in India that were not present in the United States, and which dissipated with education and literacy.
Keywords: Education; gender disparities; India; memory function; United States

Examining racial and ethnic differences in disability among older adults: A polysocial score approach. - Tang, Junhan; Chen, Ying; Liu, Hua; Wu, Chenkai (Maturitas, 2023)
OBJECTIVES: Racial and ethnic disparities in disability in activities of daily living (ADL) continue to be a public concern. We evaluated whether the polysocial score approach could provide a more comprehensive method for modifying racial and ethnic differences in such disability. STUDY DESIGN: Cohort study. MAIN OUTCOME MEASURES: We included 5833 participants from the Health and Retirement Study, who were aged 65 years or more and were initially free of ADL disability. We considered six ADLs: bathing, eating, using the toilet, dressing, walking across a room, and getting in/out of bed. We included 20 social factors spanning economic stability, neighborhood and physical environment, education, community and social context, and health system. We used forward stepwise logistic regression to derive a polysocial score for ADL disability. We created a polysocial score using 12 social factors and categorized the score as low (0-19), intermediate (20-30), and high (31+). We used multivariable logistic regression to estimate the incident risk of ADL disability and examine additive interactions between race/ethnicity and polysocial score. RESULTS: A higher polysocial score is associated with a lower incidence of ADL disability among older adults in the United States. We found additive interactions between race/ethnicity and polysocial score categories. In the low polysocial score category, White and Black/Hispanic participants had a 18.5 % and 24.4 % risk of ADL disability, respectively. Among White participants, the risk of ADL disability decreased to 14.1 % and 12.1 % in the intermediate and high polysocial score categories, respectively; among Black/Hispanic participants, those in the intermediate and high categories had a 11.9 % and 8.7 % risk of ADL disability, respectively. CONCLUSIONS: The polysocial score approach provides a new opportunity for explaining racial/ethnic disparities in functional capacity among older adults.
Keywords: Activities of Daily Living; Aged; Cohort Studies; Disabled Persons; ethnicity; Health Status Disparities; Humans; Racial Groups; United States

Expected and diagnosed rates of mild cognitive impairment and dementia in the U.S. Medicare population: observational analysis. - Mattke, Soeren; Jun, Hankyung; Chen, Emily; Liu, Ying; Becker, Andrew; Wallick, Christopher (Alzheimers Res Ther, 2023)
BACKGROUND: With the emergence of disease-modifying Alzheimer's treatments, timely detection of early-stage disease is more important than ever, as the treatment will not be indicated for later stages. Contemporary population-level data for detection rates of mild cognitive impairment (MCI), the stage at which treatment would ideally start, are lacking, and detection rates for dementia are only available for subsets of the Medicare population. We sought to compare documented diagnosis rates of MCI and dementia in the full Medicare population with expected rates based on a predictive model. METHODS: We performed an observational analysis of Medicare beneficiaries aged 65 and older with a near-continuous enrollment over a 3-year observation window or until death using 100% of the Medicare fee-for-service or Medicare Advantage Plans beneficiaries from 2015 to 2019. Actual diagnoses for MCI and dementia were derived from ICD-10 codes documented in those data. We used the 2000-2016 data of the Health and Retirement Study to develop a prediction model for expected diagnoses for the included population. The ratios between actually diagnosed cases of MCI and dementia over number of cases expected, the observed over expected ratio, reflects the detection rate. RESULTS: Although detection rates for MCI cases increased from 2015 to 2019 (0.062 to 0.079), the results mean that 7.4 of 8 million (92%) expected MCI cases remained undiagnosed. The detection rate for MCI was 0.039 and 0.048 in Black and Hispanic beneficiaries, respectively, compared with 0.098 in non-Hispanic White beneficiaries. Individuals dually eligible for Medicare and Medicaid had lower estimated detection rates than their Medicare-only counterparts for MCI (0.056 vs 0.085). Dementia was diagnosed more frequently than expected (1.086 to 1.104) from 2015 to 2019, mostly in non-Hispanic White beneficiaries (1.367) compared with 0.696 in Black beneficiaries and 0.758 in Hispanic beneficiaries. CONCLUSIONS: These results highlight the need to increase the overall detection rates of MCI and of dementia particularly in socioeconomically disadvantaged groups.
Keywords: cognitive impairment; Medicare; United States

Exposure to Family Member Deaths Across the Life Course for Hispanic Individuals. - Donnelly, Rachel; Garcia, Michael A; Cha, Hyungmin; Hummer, Robert A; Umberson, Debra (Demography, 2023)
The present study documents differences in exposure to family member deaths among foreign-born and U.S.-born Hispanic individuals compared with non-Hispanic Black and non-Hispanic White individuals. We use data from the Health and Retirement Study (HRS; 1992-2016, ages 51+; N = 23,228) and the National Longitudinal Study of Adolescent to Adult Health (Add Health; Waves I-V, ages 12-43; N = 11,088) to estimate the risk of exposure to the death of a mother, father, spouse, sibling, and child across the life course. HRS results show more inequities in exposure to family deaths compared with Add Health results, suggesting differences by age or birth cohort. Compared with non-Hispanic Whites, U.S.-born Hispanic individuals in the HRS have a higher risk of experiencing a child's death throughout adulthood and a sibling's death in later life; the latter is explained by larger sibship size, indicating a greater lifetime risk of bereavement experiences. The higher risk of parental death during childhood for U.S.-born and foreign-born Hispanic individuals is explained by covariates (e.g., lower levels of educational attainment). Hispanic individuals generally have a lower risk of family deaths than non-Hispanic Black individuals, but at times a higher risk of exposure relative to non-Hispanic White individuals.
Keywords: Adolescent; Adult; Child; Death; Family; Hispanic or Latino; Humans; Life Change Events; Longitudinal Studies; Middle Aged; United States; White; Young Adult

From financial wealth shocks to ill-health: Allostatic load and overload. - French, Declan (Health Econ, 2023)
A number of studies have associated financial wealth changes with health-related outcomes arguing that the effect is due to psychological distress and is immediate. In this paper, I examine this relationship for cumulative shocks to the financial wealth of American retirees using the allostatic load model of pathways from stress to poor health. Wealth shocks are identified from Health and Retirement Study reports of stock ownership along with significant negative discontinuities in high-frequency S&P500 index data. I find that a one standard deviation increase in cumulative shocks over two years increases the probability of elevated blood pressure by 9.5%, increases waist circumference by 1.2% and the cholesterol ratio by 6.1% for those whose wealth is all in shares. My findings suggest that the combined effect of random shocks to financial wealth over time is salient for health outcomes. This is consistent with the allostatic load model in which repeated activation of stress responses leads to cumulative wear and tear on the body.
Keywords: Allostasis; Cholesterol; Humans; Retirement; Stress, Psychological; United States

Geographic Patterns of Dementia in the United States: Variation by Place of Residence, Place of Birth, and Subpopulation. - Zacher, Meghan; Brady, Samantha; Short, Susan E (J Gerontol B Psychol Sci Soc Sci, 2023)
OBJECTIVES: The prevalence of dementia varies geographically in the United States. However, the extent to which this variation reflects contemporary place-based experiences versus embodied exposures from earlier in the life course remains unclear, and little is known regarding the intersection of place and subpopulation. This study therefore evaluates whether and how risk for assessed dementia varies by place of residence and birth, overall and by race/ethnicity and education. METHODS: We pool data from the 2000-2016 waves of the Health and Retirement Study, a nationally representative panel survey of older U.S. adults (n=96,848 observations). We estimate the standardized prevalence of dementia by Census division of residence and birth. We then fit logistic regression models of dementia on region of residence and birth, adjusting for sociodemographic characteristics, and examine interactions between region and subpopulation. RESULTS: The standardized prevalence of dementia ranges from 7.1% to 13.6% by division of residence and from 6.6% to 14.7% by division of birth, with rates highest throughout the South and lowest in the Northeast and Midwest. In models accounting for region of residence, region of birth, and sociodemographic covariates, Southern birth remains significantly associated with dementia. Adverse relationships between Southern residence or birth and dementia are generally largest for Black and less educated older adults. As a result, sociodemographic disparities in predicted probabilities of dementia are largest for those residing or born in the South. DISCUSSION: The sociospatial patterning of dementia suggests its development is a lifelong process involving cumulated and heterogeneous lived experiences embedded in place.
Keywords: Dementia; geographic patterns; United States

Immigrant Wealth Stratification and Return Migration: The Case of Mexican Immigrants in the United States During the Twentieth Century. - Sheftel, Mara Getz (Demography, 2023)
Considerable wealth stratification exists between U.S.-born and foreign-born populations (Campbell and Kaufman 2006), with low wealth attainment documented among Mexican immigrants (Hao 2007). High rates of Mexican return migration (Azose and Raftery 2019) suggest that nonrandom selection into return migration on wealth is a potential driver of stratification. Existing theories do not conclusively predict asset accumulation among returnees versus stayers, and empirical research on return migration and wealth stratification is scarce. Combining data from the 2000 U.S. Health and Retirement Study and the 2001 Mexican Health and Aging Study to create a novel data set representing all Mexicans aged 50 and older with a history of migration to the United States and adopting a life course perspective, I find that return migration at younger and older ages is associated with higher wealth accumulation and might be a way to maximize assets at older ages. Thus, return migration may contribute to nativity-based wealth stratification in the United States. The study's findings point to the greater financial risks for new cohorts of immigrants aging in place, suggest caution in interpreting wealth stratification as a measure of mobility, and inform theories about the links between return migration and wealth across the life course.
Keywords: Aged; Aging; Emigrants and Immigrants; Emigration and Immigration; Humans; Income; Independent Living; Mexican Americans; Mexico; Middle Aged; United States

Inequalities in Retirement Life Span in the United States. - Shi, Jiaxin; Dudel, Christian; Monden, Christiaan; van Raalte, Alyson (J Gerontol B Psychol Sci Soc Sci, 2023)
OBJECTIVES: The length of retirement life may be highly unequal due to persistent and significant discrepancies in old-age mortality. This study assesses gender and educational differences in the average retirement life span and the variation in retirement life span, taking into account individual labor force exit and reentry dynamics. METHODS: We used longitudinal data from the Health and Retirement Study from 1996 to 2016, focusing on respondents aged 50 and older (N = 32,228). Multistate life tables were estimated using discrete-time event history models. The average retirement life span, as well as absolute and relative variation in retirement life span, were calculated analytically. RESULTS: Among women, we found a persistent educational gradient in average retirement life span over the whole period studied; among men, the relationship between education and retirement expectancy differed across periods. Women and the lower-educated had higher absolute variation in retirement life span than men and the higher-educated-yet these relationships were reversed when examined by relative variation. DISCUSSION: Our multistate approach provides an accurate and comprehensive picture of the retirement life span of older Americans over the past two decades. Such findings should be considered in high-level discussions on Social Security. Potential reforms such as raising the eligibility age or cutting benefits may have unexpected implications for different social groups due to their differential effects on retirement initiation and reentry dynamics.
Keywords: Aged; Educational Status; Employment; Female; Humans; Life Expectancy; Life Tables; Longevity; Male; Middle Aged; Retirement; United States

Inequality in housing transitions during cognitive decline. - Mawhorter, Sarah L; Wilkie, Rachel Z; Jennifer A Ailshire (PLoS One, 2023)
Independent living can become challenging for people experiencing cognitive decline. With reduced functioning and greater care needs, many people with dementia (PWD) may need to move to another home with better safety features, move to live closer to or with relatives who can provide care, or enter a nursing home. Housing plays a key role in supporting quality of life for both PWD and their caregivers, so the ability to move when needed is crucial for their well-being. Yet the substantial costs of moving, housing, and care mean that PWD with limited financial resources may be unable to afford moving, exacerbating inequalities between more and less advantaged PWD. Emerging qualitative research considers the housing choices of PWD and their caregivers, yet little is known on a broader scale about the housing transitions PWD actually make over the course of cognitive decline. Prior quantitative research focuses specifically on nursing home admissions; questions remain about how often PWD move to another home or move in with relatives. This study investigates socioeconomic and racial/ethnic disparities in the timing and type of housing transitions among PWD in the United States, using Health and Retirement study data from 2002 through 2016. We find that over half of PWD move in the years around dementia onset (28% move once, and 28% move twice or more) while 44% remain in place. Examining various types of moves, 35% move to another home, 32% move into nursing homes, and 11% move in with relatives. We find disparities by educational attainment and race/ethnicity: more advantaged PWD are more likely to move to another home and more likely to enter a nursing home than less advantaged groups. This highlights the importance of providing support for PWD and their families to transition into different living arrangements as their housing needs change.
Keywords: Caregivers; Cognitive Dysfunction; Dementia; Housing; Humans; Nursing homes; Quality of Life; United States

Life-Sustaining Treatments Among Medicare Beneficiaries with and without Dementia at the End of Life. - Zhu, Yingying; Olchanski, Natalia; Cohen, Joshua T; Freund, Karen M; Jessica Faul; Fillit, Howard M; Neumann, Peter J; Lin, Pei-Jung (Journal of Alzheimer's Disease : JAD, 2023)
BACKGROUND: Older adults with dementia including Alzheimer's disease may have difficulty communicating their treatment preferences and thus may receive intensive end-of-life (EOL) care that confers limited benefits. OBJECTIVE: This study compared the use of life-sustaining interventions during the last 90 days of life among Medicare beneficiaries with and without dementia. METHODS: This cohort study utilized population-based national survey data from the 2000-2016 Health and Retirement Study linked with Medicare and Medicaid claims. Our sample included Medicare fee-for-service beneficiaries aged 65 years or older deceased between 2000 and 2016. The main outcome was receipt of any life-sustaining interventions during the last 90 days of life, including mechanical ventilation, tracheostomy, tube feeding, and cardiopulmonary resuscitation. We used logistic regression, stratified by nursing home use, to examine dementia status (no dementia, non-advanced dementia, advanced dementia) and patient characteristics associated with receiving those interventions. RESULTS: Community dwellers with dementia were more likely than those without dementia to receive life-sustaining treatments in their last 90 days of life (advanced dementia: OR = 1.83 [1.42-2.35]; non-advanced dementia: OR = 1.16 [1.01-1.32]). Advance care planning was associated with lower odds of receiving life-sustaining treatments in the community (OR = 0.84 [0.74-0.96]) and in nursing homes (OR = 0.68 [0.53-0.86]). More beneficiaries with advanced dementia received interventions discordant with their EOL treatment preferences. CONCLUSIONS: Community dwellers with advanced dementia were more likely to receive life-sustaining treatments at the end of life and such treatments may be discordant with their EOL wishes. Enhancing advance care planning and patient-physician communication may improve EOL care quality for persons with dementia.
Keywords: Aged; Alzheimer disease; Cohort Studies; Death; Humans; Medicare; Terminal Care; United States

Measurement differences in the assessment of functional limitations for cognitive impairment classification across geographic locations. - Nichols, Emma; Ng, Derek K; Hayat, Shabina; Kenneth M. Langa; Lee, Jinkook; Steptoe, Andrew; Deal, Jennifer A; Gross, Alden L (Alzheimers Dement, 2023)
INTRODUCTION: The measurement of dementia in cross-national contexts relies on the assessment of functional limitations. We aimed to evaluate the performance of survey items on functional limitations across culturally diverse geographic settings. METHODS: We used data from the Harmonized Cognitive Assessment Protocol Surveys (HCAP) in five countries (total N = 11,250) to quantify associations between items on functional limitations and cognitive impairment. RESULTS: Many items performed better in the United States and England compared to South Africa, India, and Mexico. Items on the Community Screening Instrument for Dementia (CSID) had the least variability across countries (SD = 0.73 vs. 0.92 [Blessed] and 0.98 [Jorm IQCODE]), but also the weakest associations with cognitive impairment (median odds ratio [OR] = 2.23 vs. 3.01 [Blessed] and 2.75 [Jorm IQCODE]). DISCUSSION: Differences in cultural norms for reporting functional limitations likely influences performance of items on functional limitations and may affect the interpretation of results from substantive studies. HIGHLIGHTS: There was substantial cross-country variation in item performance. Items from the Community Screening Instrument for Dementia (CSID) had less cross-country variability but lower performance. There was more variability in performance of instrumental activities of daily living (IADL) compared to activities of daily living (ADL) items. Variability in cultural expectations of older adults should be taken into account. Results highlight the need for novel approaches to assessing functional limitations.
Keywords: Activities of Daily Living; Aged; Cognitive Dysfunction; Dementia; England; Humans; Surveys and Questionnaires; United States

Measures of Aging Biology in Saliva and Blood as Novel Biomarkers for Stroke and Heart Disease in Older Adults. - Waziry, Reem; Gu, Yian; Boehme, Amelia K; Williams, Olajide A (Neurology, 2023)
BACKGROUND AND OBJECTIVES: The role of aging biology as a novel risk factor and biomarker for vascular outcomes in different accessible body tissues such as saliva and blood remain unclear. We aimed to (1) assess the role of aging biology as a risk factor of stroke and heart disease among individuals of same chronologic age and sex and (2) compare aging biology biomarkers measured in different accessible body tissues as novel biomarkers for stroke and heart disease in older adults. METHODS: This study included individuals who consented for blood and saliva draw in the Venous Blood Substudy and Telomere Length Study of the Health and Retirement Study (HRS). The HRS is a population-based, nationally representative longitudinal survey of individuals aged 50 years and older in the United States. Saliva-based measures included telomere length. Blood-based measures included DNA methylation and physiology biomarkers. Propensity scores-matched analyses and Cox regression models were conducted. RESULTS: This study included individuals aged 50 years and older, who consented for blood (N = 9,934) and saliva (N = 5,808) draw in the HRS. Blood-based biomarkers of aging biology showed strong associations with incident stroke as follows: compared with the lowest tertile of blood-based biomarkers of aging, biologically older individuals had significantly higher risk of stroke based on DNA methylation Grim Age clock (adjusted hazard ratio [aHR] = 2.64, 95% CI 1.90-3.66, < 0.001) and Physiology-based Phenotypic Age clock (aHR = 1.75, 95% CI 1.27-2.42, < 0.001). In secondary analysis, biologically older individuals had increased risk of heart disease as follows: DNA methylation Grim Age clock (aHR = 1.77, 95% CI 1.49-2.11, < 0.001) and Physiology-based Phenotypic Age clock (aHR = 1.61, 95% CI 1.36-1.90, < 0.001). DISCUSSION: Compared with saliva-based telomere length, blood-based aging physiology and some DNA methylation biomarkers are strongly associated with vascular disorders including stroke and are more precise and sensitive biomarkers of aging. Saliva-based telomere length and blood-based DNA methylation and physiology biomarkers likely represent different aspects of biological aging and accordingly vary in their precision as novel biomarkers for optimal vascular health.
Keywords: Aged; Aging; Biology; Biomarkers; DNA Methylation; Heart Diseases; Humans; Middle Aged; Saliva; Stroke; United States

Occupational characteristics and epigenetic aging among older adults in the United States. - Andrasfay, Theresa; Crimmins, Eileen (Epigenetics, 2023)
Occupational characteristics have been studied as risk factors for several age-related diseases and are thought to impact the ageing process, although there has been limited empirical work demonstrating an association between adverse occupational characteristics and accelerated ageing and this prior work has yielded mixed results. We used the 2010 and 2016 waves of the Health and Retirement Study ( = 1,251) to examine the association between occupation categories and self-reported working conditions of American adults at midlife and their subsequent epigenetic ageing as measured through five epigenetic clocks: PCHorvath, PCHannum, PCPhenoAge, PCGrimAge, and DunedinPACE. We found that individuals working in sales/clerical, service, and manual work show evidence of epigenetic age acceleration compared to those working in managerial/professional jobs and that the associations were stronger with second- and third-generation clocks. Individuals reporting high stress and high physical effort at work showed evidence of epigenetic age acceleration only on PCGrimAge and DunedinPACE. Most of these associations were attenuated after adjustment for race/ethnicity, educational attainment, and lifestyle-related risk factors. Sales/clerical work remained significantly associated with PCHorvath and PCHannum, while service work remained significantly associated with PCGrimAge. The results suggest that manual work and occupational physical activity may appear to be risk factors for epigenetic age acceleration through their associations with socioeconomic status, while stress at work may be a risk factor for epigenetic age acceleration through its associations with health behaviours outside of work. Additional work is needed to understand when in the life course and the specific mechanisms through which these associations occur.
Keywords: Aged; Aging; DNA Methylation; Epigenesis, Genetic; ethnicity; Humans; United States

Out-of-Pocket Health Care Spending at Older Ages: Do Caregiving Arrangements Matter? - Friedman, Esther M; Beach, Scott R; Schulz, Richard (J Appl Gerontol, 2023)
Identifying the correlates of out-of-pocket (OOP) health care spending is an important step for ensuring the financial security of older adults. Whether or not someone has a family member providing assistance is one such factor that could be associated with OOP spending. If family caregivers facilitate better health, health care spending could be reduced. On the other hand, costs would be higher if family members facilitate more (or more costly) care for loved ones. This paper explores the relationship between caregiving arrangements and OOP spending using data from 5045 individuals in the 2000-2016 Health and Retirement Study with Medicare coverage and caregiving needs. We do not find a relationship between family caregiving and OOP health care costs, overall. However, among those with Medicare HMO insurance, having a family caregiver is associated with more spending than having no helper. This is mainly due to differences in spending on prescription medications.
Keywords: Aged; Delivery of Health Care; Health Expenditures; Humans; Medicare; Middle Aged; United States

Parental Death Across the Life Course, Social Isolation, and Health in Later Life: Racial/Ethnic Disadvantage in the U.S. - Donnelly, Rachel; Lin, Zhiyong; Umberson, Debra (Social Forces, 2023)
Bereavement is a risk factor for poor health, yet prior research has not considered how exposure to parental death across the life course may contribute to lasting social isolation and, in turn, poor health among older adults. Moreover, prior research often fails to consider the racial context of bereavement in the United States wherein Black and Hispanic Americans are much more likely than White Americans to experience parental death earlier in life. The present study uses longitudinal data from the Health and Retirement Study (HRS; 1998–2016) to consider linkages of parental death, social isolation, and health (self-rated health, functional limitations) for Black, Hispanic, and White older adults. Findings suggest that exposure to parental death is associated with higher levels of isolation, greater odds of fair/poor self-rated health, and greater odds of functional limitations in later life. Moreover, social isolation partially explains associations between parental bereavement and later-life health. These patterns persist net of psychological distress—an additional psychosocial response to bereavement. Racial inequities in bereavement are central to disadvantage: Black and Hispanic adults are more likely to experience a parent’s death earlier in the life course, and this differential exposure to parental death in childhood or young adulthood has implications for racial and ethnic inequities in social isolation and health throughout life.
Keywords: health; later life; parental death; racial disadvantage; social isolation; United States

Personality and Risk of Incident Stroke in 6 Prospective Studies. - Stephan, Yannick; Sutin, Angelina R; Luchetti, Martina; Aschwanden, Damaris; Terracciano, Antonio (Stroke, 2023)
BACKGROUND: A large literature has examined a broad range of factors associated with increased risk of stroke. Few studies, however, have examined the association between personality and stroke. The present study adopted a systematic approach using a multi-cohort design to examine the associations between 5-Factor Model personality traits (neuroticism, extraversion, openness, agreeableness, and conscientiousness) and incident stroke using data from 6 large longitudinal samples of adults. METHODS: Participants (age range: 16-104 years old, N=58 105) were from the MIDUS (Midlife in the United States) Study, the HRS (Health and Retirement Study), The US (Understanding Society) study, the WLS (Wisconsin Longitudinal Study), the NHATS (National Health and Aging Trends Study), and the LISS (Longitudinal Internet Studies for the Social Sciences). Personality traits, demographic factors, clinical and behavioral risk factors were assessed at baseline; stroke incidence was tracked over 7 to 20 years follow-up. RESULTS: Meta-analyses indicated that higher neuroticism was related to a higher risk of incident stroke (hazard ratio, 1.15 [95% CI, 1.10-1.20]; <0.001), whereas higher conscientiousness was protective (HR, 0.89 [95% CI, 0.85-0.93]; <0.001). Additional meta-analyses indicated that BMI, diabetes, blood pressure, physical inactivity, and smoking as additional covariates partially accounted for these associations. Extraversion, openness, and agreeableness were unrelated to stroke incidence. CONCLUSIONS: Similar to other cardiovascular and neurological conditions, higher neuroticism is a risk factor for stroke incidence, whereas higher conscientiousness is a protective factor.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Humans; Longitudinal Studies; Middle Aged; Neuroticism; Personality; Prospective Studies; Stroke; United States; Young Adult

Physical Disability, Psychological Resilience and COVID-related Changes in Depressive Symptoms among U.S. Older Adults. - Li, Miao; Luo, Ye (J Gerontol B Psychol Sci Soc Sci, 2023)
OBJECTIVES: This study pursued three goals: (1) to determine how depressive symptoms among U.S. older adults changed in 2018-2020, a period transitioning to the first wave of COVID pandemic, compared to in pre-pandemic periods, (2) to determine whether physical disability predicts change in depressive symptoms in 2018-2020, and (3) to assess whether psychological resilience moderates the association between physical disability and change in depressive symptoms in 2018-2020. METHODS: Based on biennial longitudinal data of the Health and Retirement Study from 2010 to 2020, we used a before-after design and latent change score model to examine whether depressive symptoms change in 2018-2020 represents a continuation or departure from the overall trend of between-wave changes in 2010-2018. We also used physical disability in 2018 and psychological resilience in 2016-2018 to predict depressive symptoms change score in 2018-2020. RESULTS: In contrast to the relatively stable between-wave change trend in 2010-2018, there was an abrupt elevation in the latent change score of depressive symptoms in 2018-2020, which was primarily driven by increased affective symptoms (e.g., depressed mood, loneliness, unhappiness, and sadness). Increase in depressive symptoms in 2018-2020 was associated positively with physical disability but negatively with psychological resilience. Moderation effect of psychological resilience, however, was not significant. DISCUSSION: Our findings reveal heavier COVID-related mental health burden for older adults with physical disabilities and the potential benefits of enhancing individual psychological resilience. They also suggest that health interventions addressing the COVID impacts need to particularly focus on the affective aspects of depressive symptoms.
Keywords: COVID-19; Depressive symptoms; Older Adults; Physical disability; United States

Predictors of food insecurity among older adults before and during COVID-19 in the United States. - Nicklett, Emily Joy; Cheng, Greta Jianjia; Morris, Zachary A (Front Public Health, 2023)
BACKGROUND: The COVID-19 pandemic has strained the health and wellbeing of older adult populations through increased morbidity, mortality, and social exclusion. However, the impact of COVID-19 on the health of older adults through food security has received relatively little attention, despite the strong impact of diet quality on the health and longevity of older adults. OBJECTIVE: The objective of this study was to identify sociodemographic and socioeconomic predictors of self-reported food insecurity before and early in the COVID-19 pandemic among community-dwelling older adults in the United States. METHODS: Using longitudinal data from the Health and Retirement Study, a nationally representative sample of middle-aged and older adults in the United States, we examined the associations between sociodemographic and socioeconomic predictors of self-reported food insecurity between 2018 ( = 2,413) and June 2020 ( = 2,216) using population-weighted multivariate logistic regression models. RESULTS: The prevalence of food insecurity doubled among participants from 2018 (4.83%) to June 2020 (9.54%). In 2018, non-Hispanic Black and rural residents were more likely to report food insecurity, while individuals with higher education and greater wealth were less likely to report food insecurity in adjusted models. In June 2020, those who were relatively younger, not working due to a disability, and renting were more likely to report food insecurity. Those with an increased number of functional limitations, a recent onset of a work-limiting disability, and those who were no longer homeowners experienced an elevated longitudinal risk for food insecurity. CONCLUSION: Future research should examine effective policies and interventions to address the disproportionate impacts of COVID-19 on populations at a heightened risk of experiencing food insecurity.
Keywords: Aged; COVID-19; diet; Food insecurity; Food Supply; Humans; Middle Aged; Pandemics; United States

Prevalence and Trends of Handgrip Strength Asymmetry in the United States. - McGrath, Ryan; Lang, Justin J; Clark, Brian C; Cawthon, Peggy M; Black, Kennedy; Kieser, Jacob; Fraser, Brooklyn J; Tomkinson, Grant R (Adv Geriatr Med Res, 2023)
BACKGROUND: Strength asymmetries are a type of muscle function impairment that is associated with several health conditions. However, the prevalence of these asymmetries among adults from the United States remains unknown. We sought to estimate the prevalence and trends of handgrip strength (HGS) asymmetry in American adults. METHODS: The unweighted analytic sample included 23,056 persons aged at least 50-years with information on HGS for both hands from the 2006-2016 waves of the Health and Retirement Study. A handgrip dynamometer measured HGS, with the highest recorded values for each hand used to calculate asymmetry. Persons were categorized into the following asymmetry severity categories: (1) >10%, (2) >20.0%, and (3) >30.0%. Survey weights were used to generate nationally-representative asymmetry estimates. RESULTS: Overall, there were no statistically significant trends in HGS asymmetry categories over time. The prevalence of HGS asymmetry in the 2014-2016 wave was 53.4% (CI: 52.2-54.4), 26.0% (CI: 25.0-26.9), and 11.7% (CI: 10.9-12.3) for asymmetry at >10%, >20%, and >30%, respectively. HGS asymmetry was generally higher in older Americans compared to middle-aged adults at each wave. In the 2014-2016 wave, >30% asymmetry prevalence was 13.7% (CI: 12.7-14.6) in females and 9.3% (CI: 8.4-10.2) in males. Some differences in asymmetry prevalence by race and ethnicity were observed. CONCLUSIONS: The prevalence of asymmetry was generally high, especially in women and older adults. Ongoing surveillance of strength asymmetry will help monitor trends in muscle dysfunction, guide screening for disablement, identify subpopulations at risk for asymmetry, and inform relevant interventions.
Keywords: Handgrip strength; United States

Prevalence and Trends of Weakness Among Middle-Aged and Older Adults in the United States. - McGrath, Ryan; FitzSimmons, Samantha; Andrew, Sarah; Black, Kennedy; Bradley, Adam; Christensen, Bryan K; Collins, Kyle; Klawitter, Lukus; Kieser, Jacob; Langford, Matthew; Orr, Megan; Hackney, Kyle J (Journal of strength and conditioning research, 2023)
McGrath, R, FitzSimmons, S, Andrew, S, Black, K, Bradley, A, Christensen, BK, Collins, K, Klawitter, L, Kieser, J, Langford, M, Orr, M, and Hackney, KJ. Prevalence and trends of weakness among middle-aged and older adults in the United States. J Strength Cond Res 37(12): 2484-2490, 2023-Muscle weakness, which is often determined with low handgrip strength (HGS), is associated with several adverse health conditions; however, the prevalence and trends of weakness in the United States is not well-understood. We sought to estimate the prevalence and trends of weakness in Americans aged at least 50 years. The total unweighted analytic sample included 22,895 Americans from the 2006-2016 waves of the Health and Retirement Study. Handgrip strength was measured with a handgrip dynamometer. Men with weakness were below at least one of the absolute or normalized (body mass, body mass index) cut points: <35.5 kg, <0.45 kg/kg, <1.05 kg/kg/m 2 . The presence of any weakness in women was also identified as being below one of the absolute or normalized HGS cut points: <20.0 kg, <0.34 kg/kg, or <0.79 kg/kg/m 2 . There was an increasing trend in the prevalence of any weakness over time ( p < 0.001). The prevalence of weakness was 45.1% (95% confidence interval [CI]: 44.0-46.0) in the 2006-2008 waves and 52.6% (CI: 51.5-53.7) in the 2014-2016 waves. Weakness prevalence was higher for older (≥65 years) Americans (64.2%; CI: 62.8-65.5) compared with middle-aged (50-64 years) Americans (42.2%; CI: 40.6-43.8) in the 2014-2016 waves. Moreover, the prevalence of weakness in the 2014-2016 waves was generally higher in women (54.5%; CI: 53.1-55.9) than in men (50.4%; CI: 48.7-52.0). Differences existed in weakness prevalence across races and ethnicities. The findings from our investigation suggest that the prevalence of weakness is overall pronounced and increasing in Americans. Efforts for mitigating and better operationalizing weakness will elevate in importance as our older American population grows.
Keywords: Aged; Body Mass Index; Female; Hand Strength; Humans; Male; Middle Aged; Muscle Weakness; Prevalence; Retirement; United States

Prevalence and Trends of Weakness Among Middle-Aged and Older Adults in the United States. - McGrath, Ryan; FitzSimmons, Samantha; Andrew, Sarah; Black, Kennedy (Journal of strength and conditioning research, 2023)
McGrath, R, FitzSimmons, S, Andrew, S, Black, K, Bradley, A, Christensen, BK, Collins, K, Klawitter, L, Kieser, J, Langford, M, Orr, M, and Hackney, KJ. Prevalence and trends of weakness among middle-aged and older adults in the United States. J Strength Cond Res 37(12): 2484-2490, 2023-Muscle weakness, which is often determined with low handgrip strength (HGS), is associated with several adverse health conditions; however, the prevalence and trends of weakness in the United States is not well-understood. We sought to estimate the prevalence and trends of weakness in Americans aged at least 50 years. The total unweighted analytic sample included 22,895 Americans from the 2006-2016 waves of the Health and Retirement Study. Handgrip strength was measured with a handgrip dynamometer. Men with weakness were below at least one of the absolute or normalized (body mass, body mass index) cut points: <35.5 kg, <0.45 kg/kg, <1.05 kg/kg/m 2 . The presence of any weakness in women was also identified as being below one of the absolute or normalized HGS cut points: <20.0 kg, <0.34 kg/kg, or <0.79 kg/kg/m 2 . There was an increasing trend in the prevalence of any weakness over time ( p < 0.001). The prevalence of weakness was 45.1% (95% confidence interval [CI]: 44.0-46.0) in the 2006-2008 waves and 52.6% (CI: 51.5-53.7) in the 2014-2016 waves. Weakness prevalence was higher for older (≥65 years) Americans (64.2%; CI: 62.8-65.5) compared with middle-aged (50-64 years) Americans (42.2%; CI: 40.6-43.8) in the 2014-2016 waves. Moreover, the prevalence of weakness in the 2014-2016 waves was generally higher in women (54.5%; CI: 53.1-55.9) than in men (50.4%; CI: 48.7-52.0). Differences existed in weakness prevalence across races and ethnicities. The findings from our investigation suggest that the prevalence of weakness is overall pronounced and increasing in Americans. Efforts for mitigating and better operationalizing weakness will elevate in importance as our older American population grows.
Keywords: Aged; Body Mass Index; Female; Hand Strength; Humans; Male; Middle Aged; Muscle Weakness; Prevalence; Retirement; United States

Propensity Scores in Health Disparities Research: The Example of Cognitive Aging and the Hispanic Paradox. - Kezios, Katrina L; Zimmerman, Scott C; Zhang, Adina; Calonico, Sebastian; Jawadekar, Neal; Glymour, M Maria; Zeki Al Hazzouri, Adina (Epidemiology, 2023)
BACKGROUND: Individuals of Mexican ancestry in the United States experience substantial socioeconomic disadvantages compared with non-Hispanic white individuals; however, some studies show these groups have similar dementia risk. Evaluating whether migration selection factors (e.g., education) associated with risk of Alzheimer disease and related dementia (ADRD) explain this paradoxical finding presents statistical challenges. Intercorrelation of risk factors, common with social determinants, could make certain covariate patterns very likely or unlikely to occur for particular groups, which complicates their comparison. Propensity score (PS) methods could be leveraged here to diagnose nonoverlap and help balance exposure groups. METHODS: We compare conventional and PS-based methods to examine differences in cognitive trajectories between foreign-born Mexican American, US-born Mexican American, and US-born non-Hispanic white individuals in the Health and Retirement Study (1994-2018). We examined cognition using a global measure. We estimated trajectories of cognitive decline from linear mixed models adjusted for migration selection factors also associated with ADRD risk conventionally or with inverse probability weighting. We also employed PS trimming and match weighting. RESULTS: In the full sample, where PS overlap was poor, unadjusted analyses showed both Mexican ancestry groups had worse baseline cognitive scores but similar or slower rates of decline compared with non-Hispanic white adults; adjusted findings were similar, regardless of method. Focusing analyses on populations where PS overlap was improved (PS trimming and match weighting) did not alter conclusions. CONCLUSIONS: Attempting to equalize groups on migration selection and ADRD risk factors did not explain paradoxical findings for Mexican ancestry groups in our study.
Keywords: Adult; cognitive aging; Hispanic or Latino; Humans; Mexican Americans; Propensity Score; Risk Factors; United States

Racial and Ethnic Disparities in Health Care Use and Access Associated With Loss of Medicaid Supplemental Insurance Eligibility Above the Federal Poverty Level. - Roberts, Eric T; Kwon, Youngmin; Hames, Alexandra G; McWilliams, J Michael; Ayanian, John Z; Tipirneni, Renuka (JAMA Intern Med, 2023)
IMPORTANCE: Medicaid supplemental insurance covers most cost sharing in Medicare. Among low-income Medicare beneficiaries, the loss of Medicaid eligibility above this program's income eligibility threshold (100% of federal poverty level [FPL]) may exacerbate racial and ethnic disparities in Medicare beneficiaries' ability to afford care. OBJECTIVE: To examine whether exceeding the income threshold for Medicaid, which results in an abrupt loss of Medicaid eligibility, is associated with greater racial and ethnic disparities in access to and use of care. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study used a regression discontinuity design to assess differences in access to and use of care associated with exceeding the income threshold for Medicaid eligibility. We analyzed Medicare beneficiaries with incomes 0% to 200% of FPL from the 2008 to 2018 biennial waves of the Health and Retirement Study linked to Medicare administrative data. To identify racial and ethnic disparities associated with the loss of Medicaid eligibility, we compared discontinuities in outcomes among Black and Hispanic beneficiaries (n = 2885) and White beneficiaries (n = 5259). Analyses were conducted between January 1, 2022, and October 1, 2022. MAIN OUTCOME MEASURES: Patient-reported difficulty accessing care due to cost and outpatient service use, medication fills, and hospitalizations measured from Medicare administrative data. RESULTS: This cross-sectional study included 8144 participants (38 805 person-years), who when weighted represented 151 282 957 person-years in the community-dwelling population of Medicare beneficiaries aged 50 years and older and incomes less than 200% FPL. In the weighted sample, the mean (SD) age was 75.4 (9.4) years, 66.1% of beneficiaries were women, 14.8% were non-Hispanic Black, 13.6% were Hispanic, and 71.6% were White. Findings suggest that exceeding the Medicaid eligibility threshold was associated with a 43.8 percentage point (pp) (95% CI, 37.8-49.8) lower probability of Medicaid enrollment among Black and Hispanic Medicare beneficiaries and a 31.0 pp (95% CI, 25.4-36.6) lower probability of Medicaid enrollment among White beneficiaries. Among Black and Hispanic beneficiaries, exceeding the threshold was associated with increased cost-related barriers to care (discontinuity: 5.7 pp; 95% CI, 2.0-9.4), lower outpatient use (-6.3 services per person-year; 95% CI, -10.4 to -2.2), and fewer medication fills (-6.9 fills per person-year; 95% CI, -11.4 to -2.5), but it was not associated with a statistically significant discontinuity in hospitalizations. Discontinuities in these outcomes were smaller or nonsignificant among White beneficiaries. Consequently, exceeding the threshold was associated with widened disparities, including greater reductions in outpatient service use (disparity: -6.2 services per person-year; 95% CI, -11.7 to -0.6; P = .03) and medication fills (disparity: -7.2 fills per person-year; 95% CI, -13.4 to -1.0; P = .02) among Black and Hispanic vs White beneficiaries. CONCLUSIONS AND RELEVANCE: This cross-sectional study found that loss of eligibility for Medicaid supplemental insurance above the federal poverty level, which increases cost sharing in Medicare, was associated with increased racial and ethnic health care disparities among low-income Medicare beneficiaries. Expanding eligibility for Medicaid supplemental insurance may narrow these disparities.
Keywords: Aged; Cross-Sectional Studies; Female; Healthcare Disparities; Humans; Male; Medicaid; Medicare; Middle Aged; Poverty; United States

Self-Rated Health and Mortality: Moderation by Purpose in Life. - Friedman, Elliot M; Teas, Elizabeth (Int J Environ Res Public Health, 2023)
Poor self-rated health consistently predicts reduced longevity, even when objective disease conditions and risk factors are considered. Purpose in life is also a reliable predictor of diverse health outcomes, including greater longevity. Given prior work in which we showed that purpose in life moderated the association between chronic conditions and health-related biological factors, the aim of the current study was to examine the role of purpose in life in moderating the relationship between subjective health and mortality. We also examined potential differences in these associations by race/ethnicity. Data were from two large national longitudinal studies-the Health and Retirement Study (HRS) and the Midlife in the United States (MIDUS) study-with a 12- to 14-year follow-up period for mortality estimates. Results of logistic regression analyses showed that purpose in life and self-rated health were both significantly positively associated with longevity, and that purpose in life significantly moderated the relationship between self-rated health and mortality. Stratified analyses showed similar results across all racial/ethnic groups, with the exception of Black MIDUS participants. These results suggest that greater purpose in life may provide a buffer against the greater probability of mortality associated with poor subjective health.
Keywords: ethnicity; Humans; Longevity; Longitudinal Studies; Mortality; Racial Groups; United States; White

Ten-year cross-sectional and longitudinal assessment and factors associated with unfavourable self-rated oral health in older adults in the United States. - Tembhe, Amrita; Preisser, John S; Batorsky, Anna; Weintraub, Jane A (Gerodontology, 2023)
OBJECTIVE: To investigate the association of demographic and socio-economic characteristics with self-reported oral health (SROH) among older adults who participated in the Health and Retirement Study (HRS) in 2008, 2018, or both, and to describe temporal changes. METHODS: Data were from the University of Michigan's Health and Retirement Study (HRS), a nationally representative longitudinal survey of Americans aged 51 and older. Responses from participants who completed the Core HRS survey and Dental Module (DM) in 2008 (n = 1310), 2018 (n = 1330), and the "common group" at both timepoints (n = 559) were analysed. Using the common group, the outcome measure was 2018 self-rated oral health (Favourable vs Unfavourable). Potential explanatory variables included 2008 self-rated oral health (SROH), sociodemographic, and dental utilisation-related factors. Survey logistic regression analysis was used to identify factors that were associated with unfavourable 2018 SROH in 2018. RESULTS: Unfavourable SROH prevalence was 28.5% and 31.6% in 2008 and 2018, respectively. Among the common, longitudinal group, the unfavourable prevalence remained the same, 26.1% at both timepoints. A positive association was seen between 2018 unfavourable SROH and baseline variables of 2008 unfavourable SROH, male gender, less education, and lower levels of wealth. CONCLUSIONS: Over a quarter of participants reported unfavourable SROH. There was little change in SROH during this period. Sociodemographic factors influence the SROH of the older population. Policies and programs to promote and protect the oral health of older adults should be designed and implemented to reduce social inequalities and improve the SROH of disadvantaged older adults.
Keywords: Older Adults; Oral Health; United States

Trajectories of self-reported hearing and their associations with cognition: evidence from the United Kingdom and United States of America. - Matthews, Katey; Dawes, Piers; Elliot, Rebecca; Pendleton, Neil; Tampubolon, Gindo; Maharani, Asri (Age Ageing, 2023)
OBJECTIVE: This study aimed to investigate the relationships between trajectories of change in self-reported hearing over eight years with subsequent effects on cognition, measured using episodic memory. METHODS: Data were drawn from 5 waves (2008-2016) of the English Longitudinal Study of England (ELSA) and the Health and Retirement Study (HRS), involving 4,875 individuals aged 50+ at the baseline in ELSA and 6,365 in HRS. The latent growth curve modelling was used to identify trajectories of hearing over eight years, and linear regression models were performed to investigate the relationship between hearing trajectory memberships and episodic memory scores, controlling for confounding factors. RESULTS: Five trajectories of hearing (stable very good, stable fair, poor to fair/good, good to fair, and very good to good) were retained in each study. Individuals whose hearing remains suboptimal and those whose hearing deteriorates within suboptimal levels throughout eight years have significantly poorer episodic memory scores at follow-up than those with stable very good hearing. Conversely, individuals whose hearing declines but is within an optimal category at baseline do not see significantly poorer episodic memory scores than those with consistently optimal hearing. There was no significant relationship between individuals whose hearing improved from suboptimal baseline levels to optimal by follow-up and memory in ELSA. However, analysis using HRS data shows a significant improvement for this trajectory group (-1.260, P < 0.001). CONCLUSIONS: Either stable fair or deterioration in hearing is associated with worse cognitive function, both stable good or improving hearing is associated with better cognitive function specifically episodic memory.
Keywords: Cognition; hearing; Humans; Longitudinal Studies; Memory, Episodic; Self Report; United Kingdom; United States

Understanding Alzheimer's disease in the context of aging: Findings from applications of stochastic process models to the Health and Retirement Study. - Arbeev, Konstantin G; Bagley, Olivia; Yashkin, Arseniy P; Duan, Hongzhe; Akushevich, Igor; Ukraintseva, Svetlana V; Yashin, Anatoliy I (Mech Ageing Dev, 2023)
There is growing literature on applications of biodemographic models, including stochastic process models (SPM), to studying regularities of age dynamics of biological variables in relation to aging and disease development. Alzheimer's disease (AD) is especially good candidate for SPM applications because age is a major risk factor for this heterogeneous complex trait. However, such applications are largely lacking. This paper starts filling this gap and applies SPM to data on onset of AD and longitudinal trajectories of body mass index (BMI) constructed from the Health and Retirement Study surveys and Medicare-linked data. We found that APOE e4 carriers are less robust to deviations of trajectories of BMI from the optimal levels compared to non-carriers. We also observed age-related decline in adaptive response (resilience) related to deviations of BMI from optimal levels as well as APOE- and age-dependence in other components related to variability of BMI around the mean allostatic values and accumulation of allostatic load. SPM applications thus allow revealing novel connections between age, genetic factors and longitudinal trajectories of risk factors in the context of AD and aging creating new opportunities for understanding AD development, forecasting trends in AD incidence and prevalence in populations, and studying disparities in those.
Keywords: Aged; Aging; Alzheimer disease; Apolipoproteins E; Humans; Medicare; Retirement; United States

Use of Advance Directives in US Veterans and Non-Veterans: Findings from the Decedents of the Health and Retirement Study 1992-2014. - TUNG, HO-JUI; Yeh, Ming-Chin (Healthcare (Basel), 2023)
Evidence shows that older patients with advance directives such as a living will, or durable power of attorney for healthcare, are more likely to receive care consistent with their preferences at the end of life. Less is known about the use of advance directives between veteran and non-veteran older Americans. Using data from the decedents of a longitudinal survey, we explore whether there is a difference in having an established advance directive between the veteran and non-veteran decedents. Data were taken from the Harmonized End of Life data sets, a linked collection of variables derived from the Health and Retirement Study (HRS) Exit Interview. Only male decedents were included in the current analysis (N = 4828). The dependent variable, having an established advance directive, was measured by asking the proxy, "whether the deceased respondent ever provided written instructions about the treatment or care he/she wanted to receive during the final days of his/her life" and "whether the deceased respondent had a Durable Power of Attorney for healthcare?" A "yes" to either of the two items was counted as having an advance directive. The independent variable, veteran status, was determined by asking participants, "Have you ever served in the active military of the United States?" at their first HRS core interview. Logistic regression was used to predict the likelihood of having an established advance directive. While there was no difference in having an advance directive between male veteran and non-veteran decedents during the earlier follow-up period (from 1992 to 2003), male veterans who died during the second half of the study period (from 2004 to 2014) were more likely to have an established advance directive than their non-veteran counterparts (OR = 1.24, < 0.05). Other factors positively associated with having an established advance directive include dying at older ages, higher educational attainment, needing assistance in activities of daily living and being bedridden three months before death, while Black decedents and those who were married were less likely to have an advance directive in place. Our findings suggest male veterans were more likely to have an established advance directive, an indicator for better end-of-life care, than their non-veteran counterparts. This observed difference coincides with a time when the Veterans Health Administration (VHA) increased its investment in end-of-life care. More studies are needed to confirm if this higher utilization of advance directives and care planning among veterans can be attributed to the improved access and quality of end-of-life care in the VHA system.
Keywords: Advance directives; United States; Veterans

Associations Between Satisfaction With Aging and Health and Well-being Outcomes Among Older US Adults. - Julia S Nakamura; Hong, Joanna H; Jacqui Smith; William J. Chopik; Chen, Ying; Tyler J VanderWeele; Eric S Kim (JAMA Network Open, 2022)
Importance: Researchers and policy makers are expanding the focus from risk factors of disease to seek potentially modifiable health factors that enhance people's health and well-being. Understanding if and to what degree aging satisfaction (one's beliefs about their own aging) is associated with a range of health and well-being outcomes aligns with the interests of older adults, researchers, health systems, and politicians. Objectives: To evaluate associations between changes in aging satisfaction and 35 subsequent health and well-being outcomes. Design, Setting, and Participants: This cohort study used data from the Health and Retirement Study, a national, diverse, and longitudinal sample of 13 752 US adults older than 50 years, to evaluate if changes in aging satisfaction (between combined cohorts from 2008 and 2010 and 4 years later, in 2012 and 2014) were subsequently associated with 35 indicators of physical, behavioral, and psychosocial health and well-being in 2016 and 2018. Statistical analysis was conducted from July 24, 2020, to November 6, 2021. Exposure: Aging satisfaction. Main Outcomes and Measures: A total of 35 physical (eg, stroke), behavioral (eg, sleep problems), and psychosocial (eg, depression) outcomes were evaluated using multiple linear and generalized linear regression models. Data from all participants, irrespective of how their levels of aging satisfaction changed from the prebaseline to baseline waves, were incorporated into the overall estimate, which was conditional on prior satisfaction. Results: During the 4-year follow-up period, participants (N = 13 752; 8120 women [59%]; mean [SD] age, 65 [10] years; median age, 64 years [IQR, 56-72 years]; 7507 of 11 824 married [64%]) in the highest (vs lowest) quartile of aging satisfaction had improved physical health (eg, 43% reduced risk of mortality [risk ratio, 0.57; 95% CI, 0.46-0.71]), better health behaviors (eg, 23% increased likelihood of frequent physical activity [risk ratio, 1.23; 95% CI, 1.12-1.34]), and improved psychosocial well-being (eg, higher positive affect [β = 0.51; 95% CI, 0.44-0.58] and lower loneliness [β = -0.41; 95% CI, -0.48 to -0.33]), conditional on prebaseline aging satisfaction. Conclusions and Relevance: This study suggests that higher aging satisfaction is associated with improved subsequent health and well-being. These findings highlight potential outcomes if scalable aging satisfaction interventions were developed and deployed at scale; they also inform the efforts of policy makers and interventionists who aim to enhance specific health and well-being outcomes. Aging satisfaction may be an important target for future interventions aiming to improve later-life health and well-being.
Keywords: Aged; Aging; Female; Health Behavior; Humans; Male; Middle Aged; Personal Satisfaction; United States

Dietary Supplement Use in Middle-aged and Older Adults. - Tan, E C K; Eshetie, T C; Gray, S L; Marcum, Z A (The Journal of Nutrition, Health & Aging, 2022)
OBJECTIVES: Despite limited evidence of clinical benefits, dietary supplement use is increasingly common among older adults. The aim of this study was to characterise the prevalence of dietary supplement use in a national sample of community-dwelling middle-aged and older adults and investigate factors associated with its use. DESIGN/SETTING/PARTICIPANTS: This was a cross-sectional study using data from the Health and Retirement Study (HRS), a biennial, nationally representative survey of individuals aged 50 years and older in the United States. This study combined data from the 2013/14 Health Care and Nutrition Survey (HCNS) and 2012 Core Survey. MEASUREMENTS: The primary outcome was the use of any dietary supplement at least once a week. Secondary outcomes were the use of multivitamins and specific vitamin and supplement types. Multivariable regression models were used to identify factors associated with any dietary supplement use. RESULTS: A total of 6045 participants (weighted n = 71,268,015) were included in the final analytical sample (mean age 67.7 years, 59.3% female). Of these, 84.6% (n=60,292,704) were regular dietary supplement users, with participants taking a mean of 3.2±0.1 different dietary supplements and 41.9% taking four or more. Multivitamins were the most common, used by 57.5% (n=41,147,146) of participants. Other commonly used dietary supplements were vitamin D, fish oil, calcium, vitamin C, and vitamin B12. Older age (75+ years), female sex, higher education, daily alcohol use, vigorous physical activity, regular medication use, and arthritis were associated with higher odds of dietary supplement use. CONCLUSIONS: In this sample of middle-aged and older Americans, more than 4 out of 5 used a dietary supplement. Certain demographic, behavioural, and clinical factors were associated with their use. Given the lack of evidence for improving health outcomes, our findings suggest potential overuse of dietary supplements in people over the age of 50.
Keywords: Animals; Cross-Sectional Studies; Dietary Supplements; Female; Male; Nutrition Surveys; Nutritional Status; United States; Vitamins

Investigating Racial and Ethnic Disparities in the Provision of Workplace Accommodations in the United States - Debra L. Brucker; Megan Henly; Andrew Houtenville (University of Michigan, 2022)
This study used data from a nationally representative survey that follows people 50 and older over time (the Health and Retirement Study) to test whether the receipt of workplace accommodations by persons with work limitations varies by race/ethnicity. Workplace accommodations can include changes to time (allowing more breaks, allowing different arrival or departure times, or shortening the workday), provision of equipment/assistance (getting someone to help, getting special equipment, arranging special transportation), and changes to work (changing the job, helping to learn new job skills). We found that 85% of persons with work limitations identified a need for workplace accommodations, but only 32% actually received accommodations. While our preliminary analyses suggested some differences by race/ethnicity in the likelihood of receiving accommodations, when we also considered other factors (age, gender, education, organizational size, and physical nature of an occupation), these differences by race did not hold. Organizational size was a critical factor, however, as persons working for organizations that employed 100 or more people were significantly more likely to receive accommodations. This finding suggests that smaller employers may benefit from training or other supports to increase the availability of workplace accommodations. Workers with disabilities might also benefit from increased education offered by vocational rehabilitation agencies, workforce development programs, and other similar organizations on how to make requests for and implement reasonable accommodations.
Keywords: Racial and ethnic disparities; United States; workplace accommodations

The positive impact of informal spousal caregiving on the physical activity of older adults. - Zan, Hua; Shin, Su Hyun (Front Public Health, 2022)
INTRODUCTION: Although physical activity (PA) is crucial for health, the literature is mixed about how individuals' PA decisions are affected by their spouses. To fill this gap, we examined the extent to which providing care for one spouse affects the PA of the other spouse among those aged 50 or older in the United States. METHODS: We analyzed 9,173 older adults living with their spouses or partners from the 2004 to 2016 waves of the Health and Retirement Study. To identify the causal effect of spousal caregiving on the PA of older adults, we estimated individual-fixed effects models using a two-stage least squared instrumental variable approach with spousal falls as our instrument. We also estimated the models by splitting the sample by gender and race/ethnicity to identify heterogeneous impacts of spousal caregiving on PA decisions among subgroups. RESULTS: We found that a one percentage point increase in the probability of providing care to spouses led to an increase in the probability of initiating moderate or vigorous PA (MVPA) by 0.34-0.52 percentage points. This effect was salient, especially among female and non-Hispanic white older adults. DISCUSSION: Caregiving experience might provide opportunities to learn about caregiving burdens and trigger an emotional response about the salience of an event (i.e., they need care in the future). Older caregivers might start MVPA in an effort to improve or maintain their health and avoid burdening their families for caregiving in the future. This study demonstrated spousal influence on PA. Instead of delivering PA-promotion information (e.g., the harm of sedentary lifestyle and benefits of regular PA) to individuals, risk communication and education efforts on PA promotion might be more effective considering the family context. Family events such as health shocks or the emergence of caregiving needs from family members provide windows of opportunities for intervening. Subgroup differences should also be considered in targeted interventions.
Keywords: Aged; Caregivers; Female; Humans; Retirement; Spouses; United States

Projecting the chronic disease burden among the adult population in the United States using a multi-state population model. - Ansah, John P; Chiu, Chi-Tsun (Front Public Health, 2022)
INTRODUCTION: As the United States population ages, the adult population with chronic diseases is expected to increase. Exploring credible, evidence-based projections of the future burden of chronic diseases is fundamental to understanding the likely impact of established and emerging interventions on the incidence and prevalence of chronic disease. Projections of chronic disease often involve cross-sectional data that fails to account for the transition of individuals across different health states. Thus, this research aims to address this gap by projecting the number of adult Americans with chronic disease based on empirically estimated age, gender, and race-specific transition rates across predetermined health states. METHODS: We developed a multi-state population model that disaggregates the adult population in the United States into three health states, i.e., (a) healthy, (b) one chronic condition, and (c) multimorbidity. Data from the 1998 to 2018 Health and Retirement Study was used to estimate age, gender, and race-specific transition rates across the three health states, as input to the multi-state population model to project future chronic disease burden. RESULTS: The number of people in the United States aged 50 years and older will increase by 61.11% from 137.25 million in 2020 to 221.13 million in 2050. Of the population 50 years and older, the number with at least one chronic disease is estimated to increase by 99.5% from 71.522 million in 2020 to 142.66 million by 2050. At the same time, those with multimorbidity are projected to increase 91.16% from 7.8304 million in 2020 to 14.968 million in 2050. By race by 2050, 64.6% of non-Hispanic whites will likely have one or more chronic conditions, while for non-Hispanic black, 61.47%, and Hispanic and other races 64.5%. CONCLUSION: The evidence-based projections provide the foundation for policymakers to explore the impact of interventions on targeted population groups and plan for the health workforce required to provide adequate care for current and future individuals with chronic diseases.
Keywords: Adult; Aged; Chronic disease; Cross-Sectional Studies; ethnicity; Hispanic or Latino; Humans; Middle Aged; United States; White People

Trends in the Use of Residential Settings Among Older Adults. - Toth, Matt; Palmer, Lauren; Lawren E. Bercaw; Voltmer, Helena; Sarita Karon (The Journals of Gerontology: Series B, 2022)
OBJECTIVES: As the U.S. population ages, the prevalence of disability and functional limitations, and demand for long-term services and supports (LTSS), will increase. This study identified the distribution of older adults across different residential settings, and how their health characteristics have changed over time. METHODS: A cross-sectional analysis of older adults residing in traditional housing, community-based residential facilities (CBRFs), and nursing facilities using 3 data sources: the Medicare Current Beneficiary Survey (MCBS), 2008 and 2013; the Health and Retirement Study (HRS), 2008 and 2014; and the National Health and Aging Trends Study, 2011 and 2015. We calculated the age-standardized prevalence of older adults by setting, functional limitations, and comorbidities and tested for health characteristics changes relative to the baseline year (2002). RESULTS: The proportion of older adults in traditional housing increased over time, relative to baseline (p < .05), while the proportion of older adults in CBRFs was unchanged. The proportion of nursing facility residents declined from 2002 to 2013 in the MCBS (p < .05). The prevalence of dementia and functional limitations among traditional housing residents increased, relative to the baseline year in the HRS and MCBS (p < .05). DISCUSSION: The proportion of older adults residing in traditional housing is increasing, while the nursing facility population is decreasing. This change may not be due to better health; rather, older adults may be relying on noninstitutional LTSS.
Keywords: Activities of Daily Living; Aged; Comorbidity; Cross-Sectional Studies; Dementia; Female; Health Status Disparities; Health Transition; Homes for the Aged; Humans; Independent Living; Male; Medicare; Nursing homes; United States

Peripheral edema: A common and persistent health problem for older Americans. - Besharat, Soroush; Grol-Prokopczyk, Hanna; Gao, Shan; Feng, Changyong; Akwaa, Frank; Gewandter, Jennifer S (PLoS One, 2021)
Peripheral edema (i.e., lower limb swelling) can cause pain, weakness, and limited range of motion. However, few studies have examined its prevalence in the U.S. or its association with demographics, comorbidities, activity, or mobility. This study used data from the Health and Retirement Study, a nationally representative longitudinal survey of U.S. adults (age 51+/ N = 19,988 for 2016), to evaluate time trends and correlates of peripheral edema using weighted descriptive statistics and logistic regressions, respectively. Peripheral edema was assessed with the question "Have you had… // Persistent swelling in your feet or ankles?" The weighted prevalence of edema among older U.S. adults was 19% to 20% between 2000 and 2016. Peripheral edema was associated with older age, female sex, non-white race, low wealth, obesity, diabetes, hypertension, pain, low activity levels, and mobility limitations (odds ratios ranging from 1.2-5.6; p-values ≤0.001). This study provides the first estimates of national prevalence and correlates of peripheral edema among older Americans. Peripheral edema is common and strongly associated with comorbidities, pain, low activity levels, and mobility limitations, and disproportionately affects poorer and minority groups. Peripheral edema should be a focus of future research in order to develop novel and cost-effective interventions.
Keywords: Aged; Aged, 80 and over; Cross-Sectional Studies; Edema; ethnicity; Female; Follow-Up Studies; Humans; Longitudinal Studies; Lower Extremity; Male; Middle Aged; Mobility Limitation; Prognosis; Surveys and Questionnaires; United States

Long-term decline in intergenerational mobility in the United States since the 1850s. - Song, Xi; Massey, Catherine G; Rolf, Karen A; Ferrie, Joseph P; Rothbaum, Jonathan L; Xie, Yu (Proc Natl Acad Sci U S A, 2020)
We make use of newly available data that include roughly 5 million linked household and population records from 1850 to 2015 to document long-term trends in intergenerational social mobility in the United States. Intergenerational mobility declined substantially over the past 150 y, but more slowly than previously thought. Intergenerational occupational rank-rank correlations increased from less than 0.17 to as high as 0.32, but most of this change occurred to Americans born before 1900. After controlling for the relatively high mobility of persons from farm origins, we find that intergenerational social mobility has been remarkably stable. In contrast with relative stability in rank-based measures of mobility, absolute mobility for the nonfarm population-the fraction of offspring whose occupational ranks are higher than those of their parents-increased for birth cohorts born prior to 1900 and has fallen for those born after 1940.
Keywords: Censuses; Family Characteristics; Female; History, 19th Century; History, 20th Century; Humans; Income; Intergenerational Relations; Male; Parents; social mobility; Socioeconomic factors; United States

Population structure and pharmacogenomic risk stratification in the United States. - Nagar, Shashwat Deepali; Conley, Andrew B; Jordan, I King (BMC Biology, 2020)
BACKGROUND: Pharmacogenomic (PGx) variants mediate how individuals respond to medication, and response differences among racial/ethnic groups have been attributed to patterns of PGx diversity. We hypothesized that genetic ancestry (GA) would provide higher resolution for stratifying PGx risk, since it serves as a more reliable surrogate for genetic diversity than self-identified race/ethnicity (SIRE), which includes a substantial social component. We analyzed a cohort of 8628 individuals from the United States (US), for whom we had both SIRE information and whole genome genotypes, with a focus on the three largest SIRE groups in the US: White, Black (African-American), and Hispanic (Latino). Our approach to the question of PGx risk stratification entailed the integration of two distinct methodologies: population genetics and evidence-based medicine. This integrated approach allowed us to consider the clinical implications for the observed patterns of PGx variation found within and between population groups. RESULTS: Whole genome genotypes were used to characterize individuals' continental ancestry fractions-European, African, and Native American-and individuals were grouped according to their GA profiles. SIRE and GA groups were found to be highly concordant. Continental ancestry predicts individuals' SIRE with > 96% accuracy, and accordingly, GA provides only a marginal increase in resolution for PGx risk stratification. In light of the concordance between SIRE and GA, taken together with the fact that information on SIRE is readily available to clinicians, we evaluated PGx variation between SIRE groups to explore the potential clinical utility of race and ethnicity. PGx variants are highly diverged compared to the genomic background; 82 variants show significant frequency differences among SIRE groups, and genome-wide patterns of PGx variation are almost entirely concordant with SIRE. The vast majority of PGx variation is found within rather than between groups, a well-established fact for almost all genetic variants, which is often taken to argue against the clinical utility of population stratification. Nevertheless, analysis of highly differentiated PGx variants illustrates how SIRE partitions PGx variation based on groups' characteristic ancestry patterns. These cases underscore the extent to which SIRE carries clinically valuable information for stratifying PGx risk among populations, albeit with less utility for predicting individual-level PGx alleles (genotypes), supporting the concept of population pharmacogenomics. CONCLUSIONS: Perhaps most interestingly, we show that individuals who identify as Black or Hispanic stand to gain far more from the consideration of race/ethnicity in treatment decisions than individuals from the majority White population.
Keywords: Ethnic Groups; Genetics, Population; Genome, Human; Genotype; Humans; Pharmacogenetics; Risk Assessment; United States

Reducing cross-wave variability in survey measures of household wealth - Michael D Hurd; Erik Meijer; Moldoff, Michael; Susann Rohwedder (Journal of Economic and Social Measurement, 2020)
Survey measures of household wealth often incorporate measurement error. The resulting excess variability in the first difference in wealth makes meaningful statistical inference difficult on changes in household-level wealth. We study the effects of two methods intended to reduce this problem: Asset verification confronts respondents with large discrepancies between wealth reports from the current wave and from the previous wave. Cross-wave imputation uses adjacent wave information in the imputation procedures for missing data. In the U.S. Health and Retirement Study, the corrections from asset verification substantially reduced wave-To-wave changes in wealth. The cross-wave imputations also reduced variation, but to a lesser extent. © 2019-IOS Press and the authors. All rights reserved.
Keywords: household income; Panel data; social structure; survey design; United States

Relationship between smoking status and muscle strength in the United States older adults. - Wiener, R Constance; Findley, Patricia A; Shen, Chan; Dwibedi, Nilanjana; Sambamoorthi, Usha (Epidemiology and Health, 2020)
OBJECTIVES: Muscle strength in older adults is associated with greater physical ability. Identifying interventions to maintain muscle strength can therefore improve quality of life. The purpose of this study was to evaluate whether current or former smoking status is associated with a decrease in muscle strength in older adults. METHODS: Data from the Health and Retirement Study from 2012-2014 were analyzed with regard to maximum dominant hand grip strength, maximum overall hand grip strength, and smoking status (current, former, or never). Unadjusted linear regression was conducted. Other factors known to be related to strength were included in the adjusted linear regression analyses. RESULTS: For maximum grip strength, the regression coefficient was 4.91 for current smoking (standard error [SE], 0.58; p<0.001), 3.58 for former smoking (SE, 0.43; p<0.001), and 28.12 for never smoking (SE, 0.34). Fully adjusted linear regression on the relationship between dominant hand grip strength and smoking did not yield a significant result. The factors significantly associated with dominant hand grip strength were male sex, younger age, a race/ethnicity of non-Hispanic White or non-Hispanic Black, higher income, morbidity of ≤1 condition, no pain, and moderate or vigorous exercise more than once a week. CONCLUSIONS: Muscle strength in older adults was not associated with smoking status in the adjusted analysis.
Keywords: Aged; Aged, 80 and over; Female; Hand Strength; Humans; Male; Middle Aged; Muscle Strength; Smoking; United States

Aging in the USA: Similarities and disparities across time and space - Ana Lucia Abeliansky; Devin Erel; Holger Strulik (University of Goettingen (Gottingen), 2019)
We study biological aging of elderly U.S. Americans born 1904-1966. We use thirteen waves of the Health and Retirement Study and construct a health deﬁcit index as the number of health deﬁcits present in a person measured relative to the number of potential deﬁcits. We ﬁnd that, on average, Americans develop 5 percent more health deﬁcits per year, that men age slightly faster than women, and that, at any age above 50, Caucasians display signiﬁcantly less health deﬁcits than African Americans. We also document a steady time trend of health improvements. For each year of later birth, health deﬁcits decline on average by about 1 percent. This health trend is about the same across regions and for men and women, but signiﬁcantly lower for African Americans compared to Caucasians. In non-linear regressions, we ﬁnd that regional diﬀerences in aging follow a particular regularity, akin to the compensation eﬀect of mortality. Health deﬁcits converge for men and women and across American regions and suggest a life span of the American population of about 97 years.
Keywords: Aging; health; health deﬁcit index; United States

Cognitive Performance Among Older Persons in Japan and the United States - Saito, Yasuhiko; Jung K Kim; Davarian, Shieva; Hagedorn, Aaron; Eileen M. Crimmins (Journal of the American Geriatrics Society, 2019)
OBJECTIVE To compare cognitive performance among Japanese and American persons, aged 68 years and older, using two nationally representative studies and to examine whether differences can be explained by differences in the distribution of risk factors or in their association with cognitive performance. DESIGN Nationally representative studies with harmonized collection of data on cognitive functioning. SETTING Nihon University Japanese Longitudinal Study of Aging and the US Health and Retirement Study. PARTICIPANTS A total of 1953 Japanese adults and 2959 US adults, aged 68 years or older. MEASUREMENTS Episodic memory and arithmetic working memory are measured using immediate and delayed word recall and serial 7s. RESULTS Americans have higher scores on episodic memory than Japanese people (0.72 points on a 20-point scale); however, when education is controlled, American and Japanese people did not differ. Level of working memory was higher in Japan (0.36 on a 5-point scale) than in the United States, and the effect of education on working memory was stronger among Americans than Japanese people. There are no differences over the age of 85 years. CONCLUSION Even with large differences in educational attainment and a strong effect of education on cognitive functioning, the overall differences in cognitive functioning between the United States and Japan are modest. Differences in health appear to have little effect on national differences in cognition.
Keywords: cognitive performance; Education; Japan; Nihon University Japanese Longitudinal Study of Aging; United States

Food deserts and diet-related health outcomes of the elderly - Fitzpatrick, Katie; Nadia Greenhalgh-Stanley; Michele Ver Ploeg (Food Policy, 2019)
It is hypothesized that residents of neighborhoods with limited access to affordable and nutritious food face greater barriers to eating a healthy diet, which may in turn, result in worse health outcomes for them. Low-income elderly in urban areas may be uniquely affected by these so-called “food deserts” due to limited transportation options, strong attachments to local neighborhoods, fixed incomes, physical limitations in food shopping and meal preparation, and chronic health problems. Using the 2006, 2010, and 2014 waves of the Health and Retirement Study (HRS), the association between the food environment of elderly individuals living in urban Census tracts and their diet-related health was examined. Within urban areas, we find little evidence that food deserts negatively impact the health of lower income elderly individuals. Policies to address the needs of elderly residents of food deserts should be narrowly targeted and carefully justified.
Keywords: Diet-related disease; Elderly; Food access; Food desert; United States

How Does Employment-Based Insurance Coverage Relate to Health After Early Retirement? - Ben Lennox Kail (J Gerontol B Psychol Sci Soc Sci, 2019)
Keywords: Activities of Daily Living; Age Factors; Aged; depression; Employment; Female; Health Benefit Plans, Employee; Humans; Male; Middle Aged; Retirement; United States

One-Year Mortality After Dialysis Initiation Among Older Adults. - Melissa W Wachterman; O'Hare, Ann M; Rahman, Omari-Khalid; Karl A Lorenz; Edward R Marcantonio; Alicante, Gabrielle K; Amy Kelley (JAMA Intern Med, 2019)
This cohort study examines the incidence of mortality 1 year after the start of hemodialysis in patients 65 years and older.
Keywords: Aged; Aged, 80 and over; Female; Humans; Male; Renal Dialysis; United States

Racial disparities and temporal trends in dementia misdiagnosis risk in the United States - Kan Z Gianattasio; Prather, C.; M. Maria Glymour; Ciarleglio, A.; Melinda C Power (Alzheimer's and Dementia: Translational Research and Clinical Interventions, 2019)
Introduction: Systematic disparities in misdiagnosis of dementia across racial/ethnic groups have implications for health disparities. We compared the risk of dementia under- and overdiagnosis in clinical settings across racial/ethnic groups from 2000 to 2010. Methods: We linked fee-for-service Medicare claims to participants aged ≥70 from the nationally representative Health and Retirement Study. We classified dementia status using an algorithm with similar sensitivity and specificity across racial/ethnic groups and assigned clinical dementia diagnosis status using ICD-9-CM codes from Medicare claims. Multinomial logit models were used to estimate relative risks of clinical under- and overdiagnosis between groups and over time. Results: Non-Hispanic blacks had roughly double the risk of underdiagnosis as non-Hispanic whites. While primary analyses suggested a shrinking disparity over time, this was not robust to sensitivity analyses or adjustment for covariates. Risk of overdiagnosis increased over time in both groups. Discussion: Our results suggest that efforts to reduce racial disparities in underdiagnosis are warranted. © 2019 The Authors
Keywords: Aged; algorithm; ancestry group; Article; Black person; Caucasian; Dementia; diagnostic error; ethnic group; Female; health disparity; human; ICD-9-CM; major clinical study; Male; Medicare; priority journal; Retirement; risk factor; sensitivity analysis; Sensitivity and Specificity; United States

Wealth and the health of older Black women in the United States - Sharma, A. (Health promotion international, 2019)
Public health scholars and policy-makers are concerned that the United States continues to experience unmanageable health care costs while struggling with issues surrounding access and equity. To addresses these and other key issues, the National Academy of Medicine held a public symposium, Vital Directions for Health and Health Care: A National Conversation during September 2016, with the goal of identifying clear priorities for high-value health care and improved well-being. One important area was addressing social determinants of health. This article contributes to this objective by investigating the impact of wealth on older Black women's health. Employing the 2008/2010 waves of the RAND Health and Retirement Study on a sample of 906 older Black women, this panel study examined self-assessed health ratings of very good/good/fair/poor within a relaxed random effects framework, thereby controlling for both (i) observed and (ii) unobserved individual-level heterogeneity. This analysis did not find a statistically significant association with wealth despite a difference of approximately $75 000 in its valuation from very good to poor health. This also occurred after wealth was (i) readjusted for outliers and (ii) reformulated as negative, no change or positive change from 2008. This finding suggests that wealth may not play as integral a role. However, the outcome was significant for earnings and education, particularly higher levels of education. Scholars should further this inquiry to better understand how earnings/education/wealth operate as social determinants of health for minority populations. © The Author(s) 2018. Published by Oxford University Press. All rights reserved. For permissions, please email: journals.permissions@oup.com.
Keywords: Adult; Article; Education; Female; human; human experiment; human tissue; major clinical study; panel study; Policy; Population Health; Retirement; Social determinants of health; United States; Wellbeing; Women's Health

Antecedents of Gray Divorce: A Life Course Perspective. - Lin, I-Fen; Susan L. Brown; Matthew R Wright; Anna M Hammersmith (J Gerontol B Psychol Sci Soc Sci, 2018)
Objectives: Increasingly, older adults are experiencing divorce, yet little is known about the risk factors associated with divorce after age 50 (termed "gray divorce"). Guided by a life course perspective, our study examined whether key later life turning points are related to gray divorce. Method: We used data from the 1998-2012 Health and Retirement Study to conduct a prospective, couple-level discrete-time event history analysis of the antecedents of gray divorce. Our models incorporated key turning points (empty nest, retirement, and poor health) as well as demographic characteristics and economic resources. Results: Contrary to our expectations, the onset of an empty nest, the wife's or husband's retirement, and the wife's or husband's chronic conditions were unrelated to the likelihood of gray divorce. Rather, factors traditionally associated with divorce among younger adults were also salient for older adults. Marital duration, marital quality, home ownership, and wealth were negatively related to the risk of gray divorce. Discussion: Gray divorce is especially likely to occur among couples who are socially and economically disadvantaged, raising new questions about the consequences of gray divorce for individual health and well-being.
Keywords: Age Factors; Divorce; Female; Humans; Interviews as Topic; Male; Marriage; Middle Aged; Prospective Studies; Retirement; Risk Factors; Socioeconomic factors; Spouses; United States

Are coresidence and nursing homes substitutes? Evidence from Medicaid spend-down provisions. - Corina D Mommaerts (J Health Econ, 2018)
This paper measures the extent to which the price of nursing home care affects a potential substitute living arrangement: coresidence with adult children. Exploiting variation in state Medicaid income "spend-down" provisions over time, I find that living in a state with a spend-down provision decreases the prevalence of coresidence with adult children by 1-4 percentage points for single elderly individuals, with a corresponding increase in the use of nursing home care. These findings suggest that changes in Medicaid eligibility for long-term care benefits could have large impacts on living arrangements, care utilization patterns, and Medicaid expenditures.
Keywords: Adult children; Aged; Aged, 80 and over; Female; Health Expenditures; Homes for the Aged; Humans; Long-term Care; Male; Medicaid; Nursing homes; Residence Characteristics; United States

Arthritis, Depression, and Falls Among Community-Dwelling Older Adults: Evidence From the Health and Retirement Study. - Lien Quach; Jeffrey A Burr (J Appl Gerontol, 2018)
The aims of this study were to examine the association between different types of arthritis and falls and to investigate whether clinically significant depression symptoms (CSDS) moderate these relationships. The study used nationally representative data from the 2008 Health and Retirement Study ( n = 7,715, M age = 75, 62% female, and 90% White). Among the respondents, 42% experienced at least one fall during the previous 2 years. About one third had some form of arthritis: 22% osteoarthritis (OA), 4.8% rheumatoid arthritis (RA), 2.3% both OA and RA, and 7.9% with other arthritis types. About one fifth of respondents had CSDS. OA and CSDS are associated with the odds of falling (17% and 29%, respectively), adjusting for socio-demographic characteristics, lifestyle, health conditions, and psychiatric medications. There was no statistically significant interaction between types of arthritis and CSDS. Health care providers should pay attention to managing arthritis, especially OA, and CSDS to prevent falls among older adults.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Arthritis, Rheumatoid; Comorbidity; depression; Female; Health Surveys; Humans; Independent Living; Male; Osteoarthritis; United States

Early Origins of Adult Cancer Risk Among Men and Women: Influence of Childhood Misfortune? - Blakelee R Kemp; Kenneth F Ferraro; Patricia M Morton; Sarah A Mustillo (J Aging Health, 2018)
OBJECTIVE: To examine the effect of five childhood misfortune domains-parental behavior, socioeconomic status, infectious diseases, chronic diseases, and impairments-on all-site and selected site-specific cancer prevalence and all-site cancer incidence. METHOD: Panel data from the Health and Retirement Study (2004-2012) were used to investigate cancer risk among adults above the age of 50. RESULTS: Risky parental behavior and impairment in childhood were associated with higher odds of all-site cancer prevalence, and childhood chronic disease was associated with prostate cancer, even after adjusting for adult health and socioeconomic factors. Moreover, having one infectious disease in childhood lowered the odds of colon cancer. Cancer trends varied by race and ethnicity, most notably, higher prostate cancer prevalence among Black men and lower all-site cancer among Hispanic adults. DISCUSSION: These findings underscore the importance of examining multiple domains of misfortune because the type and amount of misfortune influence cancer risk in different ways.
Keywords: African Americans; Aged; Child; Female; Hispanic Americans; Humans; Incidence; Male; Middle Aged; Neoplasms; Parents; Prevalence; Risk Assessment; Risk Factors; Social Class; Social Conditions; Socioeconomic factors; United States

Educational and Gender Differences in Health Behavior Changes After a Gateway Diagnosis. - Elaine M Hernandez; Rachel Margolis; Robert A Hummer (J Aging Health, 2018)
OBJECTIVE: Hypertension represents a gateway diagnosis to more serious health problems that occur as people age. We examine educational differences in three health behavior changes people often make after receiving this diagnosis in middle or older age, and test whether these educational differences depend on (a) the complexity of the health behavior change and (b) gender. METHOD: We use data from the Health and Retirement Study and conduct logistic regression analysis to examine the likelihood of modifying health behaviors post diagnosis. RESULTS: We find educational differences in three behavior changes-antihypertensive medication use, smoking cessation, and physical activity initiation-after a hypertension diagnosis. These educational differences in health behaviors were stronger among women compared with men. DISCUSSION: Upon receiving a hypertension diagnosis, education is a more important predictor of behavior changes for women compared with men, which may help explain gender differences in the socioeconomic gradient in health in the United States.
Keywords: Aged; Attitude to Health; Educational Status; Exercise; Female; Health Behavior; Humans; Hypertension; Male; Middle Aged; Retirement; Sex Factors; Smoking cessation; United States

The Effects of Medicare Part D on Health Outcomes of Newly Covered Medicare Beneficiaries. - Diebold, Jeffrey (J Gerontol B Psychol Sci Soc Sci, 2018)
OBJECTIVES: To estimate the impact of Medicare Part D on cost-related prescription nonadherence and health outcomes among the newly covered medicare beneficiaries. METHOD: Difference-in-differences analyses of data from a balanced panel of Medicare beneficiaries observed in each wave of the Health and Retirement Study from 2000 to 2010 were carried out. The differences in the pre- and post-Part D changes in these outcomes are calculated for previously uncovered Part D enrollees and a comparison group of previously covered Medicare beneficiaries. RESULTS: The results from this analysis indicate that Part D reduced cost-related nonadherence rates among the newly covered by 7 percentage points and that this decline was sustained through 2010. Part D was also associated with a 5 percentage points increase in the likelihood that a newly covered enrollee reported to be in good or better health and a 4-percentage point decline in the likelihood of being diagnosed with high blood pressure. These improvements were also sustained through 2010 but were only evident among those newly covered beneficiaries who remained enrolled in a Part D plan through 2010. However, there is insufficient evidence to conclude that Part D improved the blood pressure of newly covered, hypertensive beneficiaries. DISCUSSION: Part D has had a sustained impact on cost-related nonadherence rates and the health status of newly covered beneficiaries. However, the change in health status is conditional on remaining enrolled in a Part D plan over time.
Keywords: Aged; Female; Health Status; Humans; Hypertension; Male; Medicare Part D; Medication Adherence; Models, Statistical; United States

Later Life Marital Dissolution and Repartnership Status: A National Portrait. - Susan L. Brown; Lin, I-Fen; Anna M Hammersmith; Matthew R Wright (J Gerontol B Psychol Sci Soc Sci, 2018)
OBJECTIVES: Our study compares two types of later life marital dissolution that occur after age 50-divorce and widowhood-and their associations with repartnership status (i.e., remarried, cohabiting, or unpartnered). METHOD: We used data from the Health and Retirement Study to provide a portrait of later life divorce and widowhood for women and men. Next, we tested whether marital dissolution type is related to women's and men's repartnered status, distinguishing among remarrieds, cohabitors, and unpartnereds, net of key sociodemographic indicators. RESULTS: Divorcees are more often repartnered through either remarriage or cohabitation than are widoweds. This gap persists among women net of an array of sociodemographic factors. For men, the differential is reduced to nonsignificance with the inclusion of these factors. DISCUSSION: Later life marital dissolution increasingly occurs through divorce rather than widowhood, and divorce is more often followed by repartnership. The results from this study suggest that gerontological research should not solely focus on widowhood but also should pay attention to divorce and repartnering during later life.
Keywords: Age Factors; Aged; Aged, 80 and over; Divorce; Female; Humans; Longitudinal Studies; Male; Marriage; Middle Aged; Socioeconomic factors; Spouses; United States; Widowhood

A Longitudinal Assessment of Perceived Discrimination and Maladaptive Expressions of Anger Among Older Adults: Does Subjective Social Power Buffer the Association? - Lee, Yeonjung; Bierman, Alex (The Journals of Gerontology: Series B, 2018)
Objectives: We examine whether perceived discrimination in older adults is associated with external conflict (anger-out) and internally directed anger (anger-in), as well as how subjective social power-as indicated by a sense of personal control and subjective social status-modifies these associations while holistically controlling for time-stable confounds and the five major dimensions of personality. Method: The 2006 and 2008 psychosocial subsamples of the Health and Retirement Study were combined to create baseline observations, and the 2010 and 2012 waves were combined to create follow-up observations. Responses were analyzed with random-effects models that adjust for repeated observations and fixed-effects models that additionally control for all time-stable confounds. Results: Discrimination was significantly associated with anger-in and anger-out. Fixed-effects models and controls for personality reduced these associations by more than 60%, although they remained significant. Measures of subjective social power weaken associations with anger-out but not anger-in. Discussion: The mental health consequences of perceived discrimination for older adults may be over-estimated if time-stable confounds and personality are not taken into account. Subjective social power can protect victims of discrimination from reactions that may escalate conflict, but not from internalized anger that is likely to be wearing and cause further health problems.
Keywords: African Americans; Aged; Anger; European Continental Ancestry Group; Female; Hispanic Americans; Humans; Longitudinal Studies; Male; Personality Inventory; Power, Psychological; Prejudice; Racism; United States

Medicare Part D Implementation and Associated Health Impact Among Older Adults in the United States. - Chen, Cheng-Chia; Hsien-Chang Lin; Seo, Dong-Chul (Int J Health Serv, 2018)
This study examined the effect of Medicare (Part D) implementation on health outcomes among U.S. older adults. Study participants were initially extracted from the 2004-2008 Health and Retirement Study (HRS). Data from respondents who further participated in the HRS 2005-2007 Prescription Drug Study were analyzed (N = 746). This was a retrospective pre-post design with a treatment and a control group. The difference-in-differences approach with panel ordered logistic regressions was used to examine the Part D effect on three patient health outcomes before and after the implementation, controlling for patient sociodemographic characteristics. People with continuous Part D enrollment from 2006-2008 were less likely to have a worse self-rated health than those who were not enrolled in Part D (odds ratio [OR] = 0.48; p < .05). A higher Charlson Comorbidity Index score was associated with a higher likelihood of having worse self-rated overall health, worse mental health, and worse activities of daily living impairment (ORs = 1.12, 1.17, and 1.36, respectively; all ps < .001). The Part D implementation appears to have a positive effect on older adults' overall health outcomes. A decrease in out-of-pocket cost for health care may encourage older adults to utilize more needed medications, which in turn helped maintain better health.
Keywords: Aged; Health Services for the Aged; Humans; Medicare Part D; United States

The Potential Effects of Obesity on Social Security Claiming Behavior and Retirement Benefits. - Michael D Hurd; James P Smith; Julie M Zissimopoulos (J Gerontol B Psychol Sci Soc Sci, 2018)
OBJECTIVES: Obesity prevalence among Americans has increased for nearly three decades. We explore the relationship between the rise in obesity and Social Security retirement benefit claiming, a decision impacting nearly all aging Americans. Specifically, we investigate whether obesity can affect individuals' decision to claim benefits early, a choice that has important implications for financial security in retirement, particularly for those with lower socioeconomic status (SES). METHOD: We use a microsimulation model called MINT6 (Modeling Income in the Near Term, version 6) to demonstrate the potential effects of obesity on subjective life expectancy and claiming behavior. We impute obesity status using data from the National Health and Nutrition Examination Survey (NHANES), which describes the distribution of obesity prevalence within the United States by gender, poverty status, and race/ethnicity. RESULTS: We find that the rise in obesity and the consequent incidence of obesity-related diseases may lead some individuals to make claiming decisions that lead to lower monthly and lifetime Social Security retirement benefits. Further, we find that the potential economic impact of this decision is larger for those with lower SES. DISCUSSION: We present a behavioral perspective by addressing the potential effects that obesity can have on individuals' retirement decisions and their resulting Social Security retirement benefits.
Keywords: Aged; Female; Humans; Life Expectancy; Male; Obesity; Pensions; Poverty; Social Class; Social Security; United States

State-level estimation of diabetes and prediabetes prevalence: Combining national and local survey data and clinical data. - David A Marker; Mardon, Russ; Jenkins, Frank; Campione, Joanne; Nooney, Jennifer; Li, Jane; Saydeh, Sharon; Zhang, Xuanping; Shrestha, Sundar; Deborah B. Rolka (Statistics in Medicine, 2018)
Many statisticians and policy researchers are interested in using data generated through the normal delivery of health care services, rather than carefully designed and implemented population-representative surveys, to estimate disease prevalence. These larger databases allow for the estimation of smaller geographies, for example, states, at potentially lower expense. However, these health care records frequently do not cover all of the population of interest and may not collect some covariates that are important for accurate estimation. In a recent paper, the authors have described how to adjust for the incomplete coverage of administrative claims data and electronic health records at the state or local level. This article illustrates how to adjust and combine multiple data sets, namely, national surveys, state-level surveys, claims data, and electronic health record data, to improve estimates of diabetes and prediabetes prevalence, along with the estimates of the method's accuracy. We demonstrate and validate the method using data from three jurisdictions (Alabama, California, and New York City). This method can be applied more generally to other areas and other data sources.
Keywords: Bias; California; Diabetes Mellitus; Electronic Health Records; Health Surveys; Humans; Insurance Claim Review; New York City; Nutrition Surveys; Prediabetic State; Prevalence; Statistics as Topic; United States

Are Changes in Self-Rated Health Associated With Memory Decline in Older Adults? - Bendayan, Rebecca; Andrea M Piccinin; Scott M Hofer; Muniz, Graciela (J Aging Health, 2017)
OBJECTIVE: The association between patterns of change in self-rated health (SRH) and memory trajectories in older adults was examined using a systematic approach. METHOD: Data from the Health and Retirement Study ( n = 6,016) and the English Longitudinal Study of Ageing ( n = 734) were analyzed. Individuals were grouped into five categories according to their pattern of change in SRH over 8 years: stable excellent/very good/good, stable fair/poor, improvement, decline, and fluctuating pattern without a trend. Memory was measured using immediate and delayed recall tests. Kruskal-Wallis, chi-squares tests, and linear mixed models were used to examine the association. RESULTS: Different rates of decline in memory can be identified in the different patterns of change in SRH. Those who had a stable excellent/very good/good pattern had the slowest rate of decline. DISCUSSION: Our findings suggest that SRH status and patterns of change could be used as a marker of cognitive decline in prevention screening programs.
Keywords: Aged; Cross-Sectional Studies; Diagnostic Self Evaluation; Female; Humans; Longitudinal Studies; Male; Memory Disorders; Self Report; United States

Associations Between Arthritis and Change in Physical Function in U.S. Retirees. - Nancy A. Baker; Kamil E Barbour; Charles G Helmick; Matthew M. Zack; Soham Al Snih (J Gerontol A Biol Sci Med Sci, 2017)
BACKGROUND: The aims of this study were to determine among retirees: the associations of arthritis with limitations in physical functions, and whether these associations changed differently with age for those with arthritis versus without arthritis. METHODS: We identified retirees from the Health and Retirement Study, a nationally representative longitudinal panel study of U.S. adults ≥51 years old. We calculated incidence density ratios (IDRs) using Poisson regression modeling with generalized estimating equations to estimate the associations between arthritis and limitations in four physical function measures (large muscle tasks, mobility, activities of daily living, and instrumental activities of daily living) adjusting for age, sex, race/ethnicity, marital status, education, total household income, depression, obesity, smoking, chronic conditions, physical activity, and cohort status. We examined interaction effects between arthritis and age to determine if the rate of change in physical function differed by arthritis status across age. RESULTS: Over 8 years (2004-2012), significantly more retirees with arthritis had limitations with large muscle tasks (IDR 2.1: 95% confidence interval 1.6, 2.8), mobility (IDR 1.6: 1.2, 2.2), activities of daily living (IDR 2.2: 1.0, 4.7), and instrumental activities of daily living (IDR 3.7: 1.9, 7.4) than retirees without arthritis. Retirees with arthritis did not develop limitations in mobility, activities of daily living, and instrumental activities of daily living at a different rate as they aged compared to those without arthritis. CONCLUSIONS: Arthritis was associated with a greater prevalence of physical function limitations. Preventing limitations caused by arthritis is a key strategy to prevent disability in retirees.
Keywords: Activities of Daily Living; Age Factors; Aged; Arthritis; Case-Control Studies; Female; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Muscle Strength; Retirement; United States

Associations between community-level disaster exposure and individual-level changes in disability and risk of death for older Americans. - Samuel L. Brilleman; Wolfe, Rory; Moreno-Betancur, Margarita; Anne E Sales; Kenneth M. Langa; Yun Li; Elizabeth L. Daugher Biddison; Rubinson, Lewis; Theodore J Iwashyna (Soc Sci Med, 2017)
Disasters occur frequently in the United States (US) and their impact on acute morbidity, mortality and short-term increased health needs has been well described. However, barring mental health, little is known about the medium or longer-term health impacts of disasters. This study sought to determine if there is an association between community-level disaster exposure and individual-level changes in disability and/or the risk of death for older Americans. Using the US Federal Emergency Management Agency's database of disaster declarations, 602 disasters occurred between August 1998 and December 2010 and were characterized by their presence, intensity, duration and type. Repeated measurements of a disability score (based on activities of daily living) and dates of death were observed between January 2000 and November 2010 for 18,102 American individuals aged 50-89 years, who were participating in the national longitudinal Health and Retirement Study. Longitudinal (disability) and time-to-event (death) data were modelled simultaneously using a 'joint modelling' approach. There was no evidence of an association between community-level disaster exposure and individual-level changes in disability or the risk of death. Our results suggest that future research should focus on individual-level disaster exposures, moderate to severe disaster events, or higher-risk groups of individuals.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Community Participation; Continental Population Groups; Disabled Persons; Disaster Planning; Disasters; Female; Humans; Income; Longitudinal Studies; Male; Middle Aged; Mortality; United States

Body weight status and telomere length in U.S. middle-aged and older adults. - An, Ruopeng; Yan, Hai (Obes Res Clin Pract, 2017)
OBJECTIVE: Telomere length has been proposed as a biomarker of biological aging. This study examined the relationship between body weight status and telomere length in U.S. middle-aged and older adults. METHODS: Nationally representative data (N=2749) came from the Health and Retirement Study. Linear regressions were performed to examine the relationship between baseline body weight status reported in 1992 and telomere length measured in 2008 in the overall sample and by sex and racial/ethnic groups, adjusted for individual characteristics. RESULTS: Baseline overweight (25kg/m≤body mass index [BMI]<30kg/m) and obesity (BMI≥30kg/m) status positively predicted telomere length 17 years later. Compared with their normal weight counterparts, telomere length ratio was on average 0.062 (95% confidence interval=0.016, 0.109) and 0.125 (0.048, 0.202) larger among overweight and obese adults, respectively. In comparison to women and racial/ethnic minorities, the estimated positive associations between overweight and obesity status and telomere length were more salient among men and non-Hispanic whites, respectively. CONCLUSIONS: The positive association between body weight status and telomere length found in this study was opposite to what existing biological model predicts, and could partially relate to the nonlinear relationship between body weight status and telomere length across age cohorts, and/or the lack of reliability of BMI as an indicator for adiposity in the older population. Large-scale longitudinal studies with baseline telomere length measures are warranted to replicate this study finding and explore the potential heterogeneous relationship between body weight status and telomere length.
Keywords: Aged; Aging; Body Mass Index; Body Weight; ethnicity; Female; Humans; Linear Models; Male; Middle Aged; Obesity; Overweight; Racial Groups; Risk Factors; Sex Factors; Telomere; Telomere Shortening; United States; White People

Caregiver stressors and depressive symptoms among older husbands and wives in the United States. - Kim, Min Hee; Ruth E Dunkle; Amanda J Lehning; Shen, Huei-Wern; Sheila Feld; Angela K Perone (J Women Aging, 2017)
Framed by Pearlin's Stress Process Model, this study prospectively examines the effects of primary stress factors reflecting the duration, amount, and type of care on the depressive symptoms of spousal caregivers over a2-year period, and whether the effects of stressors differ between husbands and wives. Data are from the 2004 and 2006 waves of the Health and Retirement Study and we included community-dwelling respondents providing activities of daily life (ADL) and/or instrumental activities of daily life (IADL) help to their spouses/partners (N = 774). Results from multivariate regression models indicate that none of the primary stressors were associated with depressive symptoms. However, wives providing only personal care had significantly more depressive symptoms than wives providing only instrumental care, while husbands providing different types of care showed no such differences. To illuminate strategies for reducing the higher distress experienced by wife caregivers engaged in personal care assistance, further studies are needed incorporating couples' relational dynamics and gendered experiences in personal care.
Keywords: Activities of Daily Living; Aged; Caregivers; depression; Female; Humans; Independent Living; Longitudinal Studies; Male; Middle Aged; Multivariate Analysis; Prospective Studies; Regression Analysis; Sex Factors; Spouses; Stress, Psychological; United States

A Comparison of the Prevalence of Dementia in the United States in 2000 and 2012. - Kenneth M. Langa; Eric B Larson; Eileen M. Crimmins; Jessica Faul; Deborah A Levine; Mohammed U Kabeto; David R Weir (JAMA Intern Med, 2017)
Importance: The aging of the US population is expected to lead to a large increase in the number of adults with dementia, but some recent studies in the United States and other high-income countries suggest that the age-specific risk of dementia may have declined over the past 25 years. Clarifying current and future population trends in dementia prevalence and risk has important implications for patients, families, and government programs. Objective: To compare the prevalence of dementia in the United States in 2000 and 2012. Design, Setting, and Participants: We used data from the Health and Retirement Study (HRS), a nationally representative, population-based longitudinal survey of individuals in the United States 65 years or older from the 2000 (n = 10 546) and 2012 (n = 10 511) waves of the HRS. Main Outcomes and Measures: Dementia was identified in each year using HRS cognitive measures and validated methods for classifying self-respondents, as well as those represented by a proxy. Logistic regression was used to identify socioeconomic and health variables associated with change in dementia prevalence between 2000 and 2012. Results: The study cohorts had an average age of 75.0 years (95% CI, 74.8-75.2 years) in 2000 and 74.8 years (95% CI, 74.5-75.1 years) in 2012 (P = .24); 58.4% (95% CI, 57.3%-59.4%) of the 2000 cohort was female compared with 56.3% (95% CI, 55.5%-57.0%) of the 2012 cohort (P < .001). Dementia prevalence among those 65 years or older decreased from 11.6% (95% CI, 10.7%-12.7%) in 2000 to 8.8% (95% CI, 8.2%-9.4%) (8.6% with age- and sex-standardization) in 2012 (P < .001). More years of education was associated with a lower risk for dementia, and average years of education increased significantly (from 11.8 years [95% CI, 11.6-11.9 years] to 12.7 years [95% CI, 12.6-12.9 years]; P < .001) between 2000 and 2012. The decline in dementia prevalence occurred even though there was a significant age- and sex-adjusted increase between years in the cardiovascular risk profile (eg, prevalence of hypertension, diabetes, and obesity) among older US adults. Conclusions and Relevance: The prevalence of dementia in the United States declined significantly between 2000 and 2012. An increase in educational attainment was associated with some of the decline in dementia prevalence, but the full set of social, behavioral, and medical factors contributing to the decline is still uncertain. Continued monitoring of trends in dementia incidence and prevalence will be important for better gauging the full future societal impact of dementia as the number of older adults increases in the decades ahead.
Keywords: Aged; Dementia; Female; Humans; Male; Prevalence; Risk Factors; United States

The Costs of Fall-Related Injuries among Older Adults: Annual Per-Faller, Service Component, and Patient Out-of-Pocket Costs. - Geoffrey J Hoffman; Hays, Ron D; Martin F Shapiro; Steven P Wallace; Susan L Ettner (Health Serv Res, 2017)
OBJECTIVE: To estimate expenditures for fall-related injuries (FRIs) among older Medicare beneficiaries. DATA SOURCES: The 2007-2009 Medicare claims and 2008 Health and Retirement Study (HRS) data for 5,497 (228 FRI and 5,269 non-FRI) beneficiaries. STUDY DESIGN: FRIs were indicated by inpatient/outpatient ICD-9 diagnostic codes for fractures, trauma, dislocations, and by e-codes. A pre-post comparison group design was used to estimate the differential change in pre-post expenditures for the FRI relative to the non-FRI cohort (FRI expenditures). Out-of-pocket (OOP) costs, service category total annual FRI-related Medicare expenditures, expenditures related to the type of initial FRI treatment (inpatient, ED, outpatient), and the risk of persistently high expenditures (4th quartile for each post-FRI quarter) were estimated. PRINCIPAL FINDINGS: Estimated FRI expenditures were $9,389 (95 percent CI: $5,969-$12,808). Inpatient, physician/outpatient, skilled nursing facility, and home health comprised 31, 18, 39, and 12 percent of the total. OOP costs were $1,363.0 (95 percent CI: $889-$1,837). Expenditures for FRIs initially treated in inpatient/ED/outpatient settings were $21,424/$6,142/$8,622. The FRI cohort had a 64 percent increased risk of persistently high expenditures. Total Medicare expenditures were $13 billion (95 percent CI: $9-$18 billion). CONCLUSIONS: FRIs are associated with substantial, persistent Medicare expenditures. Cost-effectiveness of multifactorial falls prevention programs should be assessed using these expenditure estimates.
Keywords: Accidental Falls; Age Factors; Aged; Aged, 80 and over; Female; Financing, Personal; Health Expenditures; Health Services; Humans; Male; Medicare; Models, Econometric; Sex Factors; Socioeconomic factors; United States; Wounds and Injuries

Do Regular Cholesterol Screenings Lead to Lower Cholesterol Levels and Better Health Behaviors for All? Spotlight on Middle-Aged and Older Adults in the United States. - Choi, Yool; Lee, Hyo Jung (J Aging Health, 2017)
OBJECTIVE: This study investigates how the causal effects of cholesterol screening differ by likelihood of using this preventive care service in terms of accessibility gaps and effects on health-related outcomes across groups with advantaged and disadvantaged backgrounds. METHOD: We use propensity score matching to analyze a nationally representative sample using data from 2008, 2010, and 2012 waves of the Health and Retirement Study ( N = 3,907). RESULTS: We find that respondents who are least likely to get their cholesterol tested benefit most from the use of cholesterol screening when they do use it, while its effects are smallest for those who are most likely to use this service. DISCUSSION: Understanding the heterogeneous effects of preventive health service has important policy implications, particularly in terms of how to maximize the public health benefits of preventive care.
Keywords: Aged; Aged, 80 and over; Cholesterol; Female; Health Behavior; Humans; Longitudinal Studies; Male; Mass Screening; Middle Aged; Preventive Health Services; United States

Effects of receipt of Social Security retirement benefits on older women's employment. - Gillen, Martie; Claudia J Heath (J Women Aging, 2017)
Labor force participation of women has declined since 1999; however, labor force participation of women 62+ has increased. The 2000-2006 waves of Health and Retirement Study (HRS) data, the initial years of the continuing upward trajectory, were used to test the effects of receipt of Social Security retirement benefits on older women's employment. The models tested: (a) the effect of receipt of Social Security retirement benefits on whether employed; and (b) for women receiving Social Security retirement benefits, the effect of age elected receipt of benefits on whether employed. Both models included the effects of human capital characteristics and income sources. Receipt of Social Security benefits, pension income, and current age reduced the likelihood of employment; while educational level, good to excellent health, and nonmarried marital status increased the likelihood of employment. The older the woman was when she elected Social Security benefits, the more likely she was to be employed.
Keywords: Aged; Employment; Female; Humans; Middle Aged; Retirement; Social Security; United States; Women's Health; Women, Working

Emergency Preparedness of Persons Over 50 Years Old: Further Results From the Health and Retirement Study. - Timothy S Killian; Zola K Moon; McNeill, Charleen; Garrison, Betsy; Moxley, Shari (Disaster Med Public Health Prep, 2017)
OBJECTIVE: This article conceptualized emergency preparedness as a complex, multidimensional construct and empirically examined an array of sociodemographic, motivation, and barrier variables as predictors of levels of emergency preparedness. METHODS: The authors used the 2010 wave of the Health and Retirement Study's emergency preparedness module to focus on persons 50 years old and older in the United States by use of logistic regression models and reconsidered a previous analysis. RESULTS: The models demonstrated 3 key findings: (1) a lack of preparedness is widespread across virtually all sociodemographic variables and regions of the country; (2) an authoritative voice, in the role of health care personnel, was a strong predictor of preparedness; and (3) previous experience in helping others in a disaster predisposes individuals to be better prepared. Analyses also suggest the need for caution in creating simple summative indexes and the need for further research into appropriate measures of preparedness. CONCLUSION: This population of older persons was generally not well prepared for emergencies, and this lack of preparedness was widespread across social, demographic, and economic groups in the United States. Findings with implications for policy and outreach include the importance of health care providers discussing preparedness and the use of experienced peers for outreach. (Disaster Med Public Health Preparedness. 2017;11:80-89).
Keywords: Aged; Aged, 80 and over; Attitude to Health; Civil Defense; Equipment and Supplies; Female; Help-Seeking Behavior; Humans; Male; Middle Aged; Retirement; United States; Vulnerable Populations

Financial Care for Older Adults With Dementia. - Pan, Xi; Lee, Yeonjung; Dye, Cheryl; Laurie Theriot Roley (Int J Aging Hum Dev, 2017)
This article describes an examination of the sociodemographic characteristics of adult children, particularly Baby Boomer caregivers, who provide financial care to older parents with dementia. The sample including 1,011adult children dementia caregivers aged 50 to 64 years is selected from a nationally representative sample in the 2010 Health and Retirement Study. Exact logistic regression revealed that race, provision of financial assistance to caregiver children, and the number of their children are significantly associated with financial caregiving of parents. Non-White caregivers are more likely to provide financial care to their parents or parents-in-law with dementia; those who have more children and provide financial assistance to their children are less likely to provide financial care to parents with dementia. The current findings present valuable new information on the sociodemographic characteristics of adult children who provide financial assistance to parents with dementia and inform research, programs, and services on dementia caregiving.
Keywords: Adult children; Aged; Aged, 80 and over; Dementia; Female; Humans; Male; Middle Aged; United States

Foundations of Activity of Daily Living Trajectories of Older Americans. - Linda G Martin; Zachary Zimmer; Jinkook Lee (J Gerontol B Psychol Sci Soc Sci, 2017)
OBJECTIVES: The disablement process can be viewed conceptually as a progression from disease to impairment to functional limitation and finally disability (frequently operationalized as activity limitation). This article assesses the extent to which early phases of the process are associated with individual-level disability trajectories by age. METHOD: We use data from seven waves of the Health and Retirement Study, 1998 to 2010, to investigate for individuals aged 65-84 years how baseline sociodemographic characteristics and self-reported disease, pain, and functional limitation (physical, cognitive, or sensory) are related to the dynamics of limitations in activities of daily living (ADLs). Our modeling approach jointly estimates multiperiod trajectories of ADL limitation and mortality and yields estimates of the number of, shapes of, and factors associated with the most common trajectories. RESULTS: Individual probability of ADL limitation can best be described by three common trajectories. In comparison with disease, pain, and functional limitation, sociodemographic characteristics have weak associations with trajectory group membership. Notably, neither sex nor education is strongly associated with group membership in multivariate models. DISCUSSION: The analysis confirms the importance of the early phases of the disablement process and their relationships with subsequent trajectories of activity limitation.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Chronic pain; cognitive aging; Disability Evaluation; disease progression; Female; Humans; Individuality; Male; Middle Aged; Socioeconomic factors; Statistics as Topic; United States

Glycated haemoglobin (HbA1c), diabetes and trajectories of change in episodic memory performance. - Pappas, Colleen; Andel, Ross; Frank J Infurna; Seetharaman, Shyam (J Epidemiol Community Health, 2017)
BACKGROUND: As the ageing population grows, it is important to identify strategies to moderate cognitive ageing. OBJECTIVE: We examined glycated haemoglobin (HbA1c) and diabetes in relation to level and change in episodic memory in older adults with and without diabetes. METHODS: Data from 4419 older adults with (n=950) and without (n=3469) diabetes participating in a nationally representative longitudinal panel study (the Health and Retirement Study) were examined. Average baseline age was 72.66 years and 58% were women. HbA1c was measured in 2006 and episodic memory was measured using immediate and delayed list recall over 4 biennial waves between 2006 and 2012. Growth curve models were used to assess trajectories of episodic memory change. RESULTS: In growth curve models adjusted for age, sex, education, race, depressive symptoms and waist circumference, higher HbA1c levels and having diabetes were associated with poorer baseline episodic memory (p=0.036 and <0.001, respectively) and greater episodic memory decline (p=0.006 and 0.004, respectively). The effect of HbA1c on episodic memory decline was smaller than the effect of age. The results were stronger for women than men and were not modified by age or race. When the main analyses were estimated for those with and without diabetes separately, HbA1c was significantly linked to change in episodic memory only among those with diabetes. CONCLUSIONS: Higher HbA1c and diabetes were both associated with declines in episodic memory, with this relationship further exacerbated by having diabetes and elevated HbA1c. HbA1c appeared more important for episodic memory performance among women than men.
Keywords: Aged; cognitive aging; Demography; Diabetes Mellitus; Female; Glycated Hemoglobin A; Humans; Longitudinal Studies; Male; Memory, Episodic; Risk Factors; Sex Factors; United States

Healthy Aging in the Context of Educational Disadvantage: The Role of "Ordinary Magic". - Sara J McLaughlin (J Aging Health, 2017)
OBJECTIVE: The objective of this study is to examine the correlates of healthy aging in the context of educational disadvantage and the extent to which identified correlates are shared with the wider, more educationally advantaged population. METHOD: Data are from the 2012 Health and Retirement Study. The analytic sample included 17,484 self-respondents ≥50 years of age. Educational disadvantage was defined as having less than a high school diploma. Using logistic regression, healthy aging was regressed on demographic, early-life, and health-related factors by educational status. RESULTS: Among educationally disadvantaged adults, demographic characteristics (e.g., age), health practices (e.g., physical activity), and the presence of health conditions were independently correlated with healthy aging. With few exceptions, correlates of healthy aging were similar among educationally advantaged and disadvantaged adults. DISCUSSION: Ordinary factors are associated with healthy aging among adults without a high school diploma, suggesting that healthy aging is possible for larger numbers of adults aging in the context of educational disadvantage.
Keywords: Aged; Aged, 80 and over; Educational Status; Female; Health Behavior; healthy aging; Humans; Logistic Models; Male; Middle Aged; Social Class; United States

Hierarchy and Speed of Loss in Physical Functioning: A Comparison Across Older U.S. and English Men and Women. - Bendayan, Rebecca; Cooper, Rachel; Elizabeth G Wloch; Scott M Hofer; Andrea M Piccinin; Graciela Muñiz Terrera (J Gerontol A Biol Sci Med Sci, 2017)
Background: We aimed to identify the hierarchy of rates of decline in 16 physical functioning measures in U.S. and English samples, using a systematic and integrative coordinated data analysis approach. Methods: The U.S. sample consisted of 13,612 Health and Retirement Study participants, and the English sample consisted of 5,301 English Longitudinal Study of Ageing participants. Functional loss was ascertained using self-reported difficulties performing 6 activities of daily living and 10 mobility tasks. The variables were standardized, rates of decline were computed, and mean rates of decline were ranked. Mann-Whitney U tests were performed to compare rates of decline between studies. Results: In both studies, the rates of decline followed a similar pattern; difficulty with eating was the activity that showed the slowest decline and climbing several flights of stairs and stooping, kneeling, or crouching the fastest declines. There were statistical differences in the speed of decline in all 16 measures between countries. American women had steeper declines in 10 of the measures than English women. Similar differences were found between American and English men. Conclusions: Reporting difficulties climbing several flights of stairs without resting, and stooping, kneeling, or crouching are the first indicators of functional loss reported in both populations.
Keywords: Activities of Daily Living; Aged; Aging; Cross-Cultural Comparison; Disability Evaluation; Female; Geriatric Assessment; Health Status Disparities; Humans; Longitudinal Studies; Male; Middle Aged; Mobility Limitation; Self Report; Statistics, Nonparametric; United Kingdom; United States

Home and community-based service and other senior service use: Prevalence and characteristics in a national sample. - Amanda Sonnega; Kristen N Robinson; Helen G Levy (Home Health Care Serv Q, 2017)
We report on the use of home and community-based services (HCBS) and other senior services and factors affecting utilization of both among Americans over age 60 in the Health and Retirement Study (HRS). Those using HCBS were more likely to be older, single, Black, lower income, receiving Medicaid, and in worse health. Past use of less traditional senior services, such as exercise classes and help with tax preparation, were found to be associated with current use of HCBS. These findings suggest use of less traditional senior services may serve as a "gateway" to HCBS that can help keep older adults living in the community.
Keywords: Aged; Aged, 80 and over; Community Health Services; Female; Home Care Services; Humans; Logistic Models; Longitudinal Studies; Male; Middle Aged; Prevalence; Senior Centers; United States

Honest Labor Bears a Lovely Face: Will Late-Life Unemployment Impact Health and Satisfaction in Retirement? - Maren W Voss; Wendy Church Birmingham; Lori Wadsworth; Wei Chen; Bounsanga, Jerry; Gu, Yushan; Hung, Man (J Occup Environ Med, 2017)
OBJECTIVE: Unemployment among older adults during recessionary cycles has been tied to early retirement decisions and negative health outcomes. This study explored episodes of unemployment experienced between age 50 and retirement as predictors of retirement age and health outcomes. METHODS: A total of 1540 participants from the U.S. Health and Retirement Study aged 50 years and older who transitioned from workforce to retirement were analyzed with descriptive statistics and multiple regression controlling for unemployment, demographics, and health status. RESULTS: Late-life unemployment significantly related to earlier retirement age and lowered life satisfaction, independent of income effects. We found no main effect for late-life unemployment on physical health status. CONCLUSIONS: Potential improvements in future life satisfaction might be gained if job search obstacles are removed for older unemployed adults, reducing reliance on involuntary early retirement as an income source.
Keywords: Age Factors; Aged; Chronic disease; depression; Female; Health Status; Health Surveys; Humans; Male; Mental Health; Middle Aged; Personal Satisfaction; Retirement; Unemployment; United States; Work

Identifying Older Adults with Serious Illness: A Critical Step toward Improving the Value of Health Care. - Amy Kelley; Kenneth E Covinsky; Rebecca Jean Gorges; McKendrick, Karen; Bollens-Lund, Evan; R Sean Morrison; Christine S Ritchie (Health Serv Res, 2017)
OBJECTIVE: To create and test three prospective, increasingly restrictive definitions of serious illness. DATA SOURCES: Health and Retirement Study, 2000-2012. STUDY DESIGN: We evaluated subjects' 1-year outcomes from the interview date when they first met each definition: (A) one or more severe medical conditions (Condition) and/or receiving assistance with activities of daily living (Functional Limitation); (B) Condition and/or Functional Limitation and hospital admission in the last 12 months and/or residing in a nursing home (Utilization); and (C) Condition and Functional Limitation and Utilization. Definitions are increasingly restrictive, but not mutually exclusive. DATA COLLECTION: Of 11,577 eligible subjects, 5,297 met definition A; 3,151 definition B; and 1,447 definition C. PRINCIPAL FINDINGS: One-year outcomes were as follows: hospitalization 33 percent (A), 44 percent (B), 47 percent (C); total average Medicare costs $20,566 (A), $26,349 (B), and $30,828 (C); and mortality 13 percent (A), 19 percent (B), 28 percent (C). In comparison, among those meeting no definition, 12 percent had hospitalizations, total Medicare costs averaged $7,789, and 2 percent died. CONCLUSIONS: Prospective identification of older adults with serious illness is feasible using clinically accessible criteria and may be a critical step toward improving health care value. These definitions may aid clinicians and health systems in targeting patients who could benefit from additional services.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Critical Illness; Early Diagnosis; Female; Health Care Costs; Hospitalization; Humans; Male; Medicare; Nursing homes; Prospective Studies; Quality Improvement; United States

Identifying Specific Combinations of Multimorbidity that Contribute to Health Care Resource Utilization: An Analytic Approach. - Nicholas K Schiltz; David F Warner; Jiayang Sun; Paul M Bakaki; Avi Dor; Charles W Given; Kurt C Stange; Siran M Koroukian (Med Care, 2017)
BACKGROUND: Multimorbidity affects the majority of elderly adults and is associated with higher health costs and utilization, but how specific patterns of morbidity influence resource use is less understood. OBJECTIVE: The objective was to identify specific combinations of chronic conditions, functional limitations, and geriatric syndromes associated with direct medical costs and inpatient utilization. DESIGN: Retrospective cohort study using the Health and Retirement Study (2008-2010) linked to Medicare claims. Analysis used machine-learning techniques: classification and regression trees and random forest. SUBJECTS: A population-based sample of 5771 Medicare-enrolled adults aged 65 and older in the United States. MEASURES: Main covariates: self-reported chronic conditions (measured as none, mild, or severe), geriatric syndromes, and functional limitations. Secondary covariates: demographic, social, economic, behavioral, and health status measures. OUTCOMES: Medicare expenditures in the top quartile and inpatient utilization. RESULTS: Median annual expenditures were $4354, and 41% were hospitalized within 2 years. The tree model shows some notable combinations: 64% of those with self-rated poor health plus activities of daily living and instrumental activities of daily living disabilities had expenditures in the top quartile. Inpatient utilization was highest (70%) in those aged 77-83 with mild to severe heart disease plus mild to severe diabetes. Functional limitations were more important than many chronic diseases in explaining resource use. CONCLUSIONS: The multimorbid population is heterogeneous and there is considerable variation in how specific combinations of morbidity influence resource use. Modeling the conjoint effects of chronic conditions, functional limitations, and geriatric syndromes can advance understanding of groups at greatest risk and inform targeted tailored interventions aimed at cost containment.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Comorbidity; Female; Health Behavior; Health Expenditures; Health Status; Humans; Machine learning; Male; Medicare; Retrospective Studies; Self Report; Socioeconomic factors; United States

The Impact of Medicare Part D on Emergency Department Visits. - Padmaja Ayyagari; Dan M. Shane; George L Wehby (Health Economics, 2017)
The Medicare Part D program introduced prescription drug coverage for seniors in 2006. We examine the impact of this program on the use of emergency department (ED) care. Using a difference-in-differences model, we find declines in the number of ED visits for non-emergency care but not for emergency care, suggesting that Part D may have led to better management of health and reduced unnecessary use of EDs. Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: Aged; Delivery of Health Care; Emergency Service, Hospital; Female; Humans; Insurance Coverage; Insurance, Health; Male; Medicare Part D; Middle Aged; prescription drugs; Surveys and Questionnaires; United States

The Influence of the Transportation Environment on Driving Reduction and Cessation. - Jonathon M Vivoda; Steven G Heeringa; Amy J Schulz; Grengs, Joe; Cathleen M. Connell (Gerontologist, 2017)
Purpose of the Study: Driving is by far the most common mode of transportation in the United States, but driving ability is known to decline as people experience age-related functional declines. Some older adults respond to such declines by self-limiting their driving to situations with a low perceived risk of crashing, and many people eventually stop driving completely. Previous research has largely focused on individual and interpersonal predictors of driving reduction and cessation (DRC). The purpose of this study was to assess the influence of the transportation environment on DRC. Design and Methods: Data were combined from the Health and Retirement Study, the Urban Mobility Scorecard, and StreetMap North America (GIS data). Longitudinal survival analysis techniques were used to analyze seven waves of data spanning a 12-year period. Results: As roadway density and congestion increased in the environment, the odds of DRC also increased, even after controlling for individual and interpersonal predictors. Other predictors of DRC included demographics, relationship status, health, and household size. Implications: The current study identified an association between the transportation environment and DRC. Future research is needed to determine whether a causal link can be established. If so, modifications to the physical environment (e.g., creating livable communities with goods and services in close proximity) could reduce driving distances in order to improve older drivers' ability to remain engaged in life. In addition, older individuals who wish to age in place should consider how their local transportation environment may affect their quality of life.
Keywords: Aged; Aging; Automobile Driving; environment; Family Characteristics; Female; Geographic Information Systems; Health Status; Humans; Longitudinal Studies; Male; Marital Status; Risk; Survival Analysis; Transportation; United States

A Longitudinal Analysis of Site of Death: The Effects of Continuous Enrollment in Medicare Advantage Versus Conventional Medicare. - Elizabeth Edmiston Chen; Edward Alan Miller (Res Aging, 2017)
This study assessed the odds of dying in hospital associated with enrollment in Medicare Advantage (M-A) versus conventional Medicare Fee-for-Service (M-FFS). Data were derived from the 2008 and 2010 waves of the Health and Retirement Study ( n = 1,030). The sample consisted of elderly Medicare beneficiaries who died in 2008-2010 (34% died in hospital, and 66% died at home, in long-term senior care, a hospice facility, or other setting). Logistic regression estimated the odds of dying in hospital for those continuously enrolled in M-A from 2008 until death compared to those continuously enrolled in M-FFS and those switching between the two plans. Results indicate that decedents continuously enrolled in M-A had 43% lower odds of dying in hospital compared to those continuously enrolled in M-FFS. Financial incentives in M-A contracts may reduce the odds of dying in hospital.
Keywords: Aged; Aged, 80 and over; Decision making; Fee-for-Service Plans; Female; health policy; Hospices; Hospital Mortality; Humans; Longitudinal Studies; Male; Medicare Part C; Terminal Care; United States

Mental health and breast cancer screening utilization among older Hispanic women. - Tamara J. Cadet; Berrett-Abebe, Julie; Stewart, Kathleen (J Women Aging, 2017)
Considerable racial and ethnic differences exist in the way the burden of cancer is experienced in the United States for older Hispanic women. This study utilized data from the 2008 wave of the Health and Retirement Study to investigate the mental health factors associated with older Hispanic women's participation in breast cancer screening services. Logistic regression models were used. Findings indicated that anxiety and positive affect were associated with a greater likelihood of participating in breast cancer screening. Despite ongoing national conversations, evidence indicates there is agreement that underserved women need to be screened, particularly the older Hispanic population.
Keywords: Affect; Aged; Anxiety; Breast Neoplasms; Early Detection of Cancer; Female; Hispanic Americans; Humans; Logistic Models; Middle Aged; Motivation; Patient Acceptance of Health Care; United States; Vulnerable Populations

Neighborhood age structure and cognitive function in a nationally-representative sample of older adults in the U.S. - Esther M Friedman; Regina A Shih; Mary E Slaughter; Margaret M Weden; Kathleen A. Cagney (Soc Sci Med, 2017)
Recent evidence suggests that living in a neighborhood with a greater percentage of older adults is associated with better individual health, including lower depression, better self-rated health, and a decreased risk of overall mortality. However, much of the work to date suffers from four limitations. First, none of the U.S.-based studies examine the association at the national level. Second, no studies have examined three important hypothesized mechanisms - neighborhood socioeconomic status and neighborhood social and physical characteristics - which are significantly correlated with both neighborhood age structure and health. Third, no U.S. study has longitudinally examined cognitive health trajectories. We build on this literature by examining nine years of nationally-representative data from the Health and Retirement Study (2002-2010) on men and women aged 51 and over linked with Census data to examine the relationship between the percentage of adults 65 and older in a neighborhood and individual cognitive health trajectories. Our results indicate that living in a neighborhood with a greater percentage of older adults is related to better individual cognition at baseline but we did not find any significant association with cognitive decline. We also explored potential mediators including neighborhood socioeconomic status, perceived neighborhood cohesion and perceived neighborhood physical disorder. We did not find evidence that neighborhood socioeconomic status explains this relationship; however, there is suggestive evidence that perceived cohesion and disorder may explain some of the association between age structure and cognition. Although more work is needed to identify the precise mechanisms, this work may suggest a potential contextual target for public health interventions to prevent cognitive impairment.
Keywords: Aged; Aged, 80 and over; Aging; Cognition; Female; Health Status; Humans; Interpersonal Relations; Male; Residence Characteristics; Social Support; Socioeconomic factors; United States

Older Adults With Three Generations of Kin: Prevalence, Correlates, and Transfers. - Rachel Margolis; Wright, Laura (J Gerontol B Psychol Sci Soc Sci, 2017)
OBJECTIVES: We document the prevalence and sociodemographic correlates of older adults with three generations of living kin and examine the patterns of transfers among this group compared with those with fewer generations of kin available. METHOD: We use the Health and Retirement Study (1998-2010) to estimate kin availability and intergenerational transfers among respondents in their 50s, 60s, and 70s. RESULTS: It is far more common for older adults to have aging parents, children, and grandchildren than to have just two generations of kin (parents and children). Forty percent of adults in their 50s, 30% of those in their 60s, and 7.5% of those in their 70s have three generations of kin available. Hispanics and the least educated are more likely to have this generational configuration. The vast majority provides financial or in-kind transfers to at least one generation, and a large minority provides support to both older and younger generations. DISCUSSION: Although there has been much concern about the strains among those sandwiched between parents and children, it is far more common among older adults to also have grandchildren, and many of these adults are transferring resources both upward and downward to multiple generations.
Keywords: Aged; Black or African American; Family; Family Characteristics; Female; Hispanic or Latino; Humans; Intergenerational Relations; Male; Middle Aged; Resource Allocation; Social Support; Surveys and Questionnaires; United States; White People

Out-of-Pocket Spending and Financial Burden Among Medicare Beneficiaries With Cancer. - Amol K Narang; Lauren Hersch Nicholas (JAMA Oncol, 2017)
Importance: Medicare beneficiaries with cancer are at risk for financial hardship given increasingly expensive cancer care and significant cost sharing by beneficiaries. Objectives: To measure out-of-pocket (OOP) costs incurred by Medicare beneficiaries with cancer and identify which factors and services contribute to high OOP costs. Design, Setting, and Participants: We prospectively collected survey data from 18 166 community-dwelling Medicare beneficiaries, including 1409 individuals who were diagnosed with cancer during the study period, who participated in the January 1, 2002, to December 31, 2012, waves of the Health and Retirement Study, a nationally representative panel study of US residents older than 50 years. Data analysis was performed from July 1, 2014, to June 30, 2015. Main Outcomes and Measures: Out-of-pocket medical spending and financial burden (OOP expenditures divided by total household income). Results: Among the 1409 participants (median age, 73 years [interquartile range, 69-79 years]; 46.4% female and 53.6% male) diagnosed with cancer during the study period, the type of supplementary insurance was significantly associated with mean annual OOP costs incurred after a cancer diagnosis ($2116 among those insured by Medicaid, $2367 among those insured by the Veterans Health Administration, $5976 among those insured by a Medicare health maintenance organization, $5492 among those with employer-sponsored insurance, $5670 among those with Medigap insurance coverage, and $8115 among those insured by traditional fee-for-service Medicare but without supplemental insurance coverage). A new diagnosis of cancer or common chronic noncancer condition was associated with increased odds of incurring costs in the highest decile of OOP expenditures (cancer: adjusted odds ratio, 1.86; 95% CI, 1.55-2.23; P < .001; chronic noncancer condition: adjusted odds ratio, 1.82; 95% CI, 1.69-1.97; P < .001). Beneficiaries with a new cancer diagnosis and Medicare alone incurred OOP expenditures that were a mean of 23.7% of their household income; 10% of these beneficiaries incurred OOP expenditures that were 63.1% of their household income. Among the 10% of beneficiaries with cancer who incurred the highest OOP costs, hospitalization contributed to 41.6% of total OOP costs. Conclusions and Relevance: Medicare beneficiaries without supplemental insurance incur significant OOP costs following a diagnosis of cancer. Costs associated with hospitalization may be a primary contributor to these high OOP costs. Medicare reform proposals that restructure the benefit design for hospital-based services and incorporate an OOP maximum may help alleviate financial burden, as can interventions that reduce hospitalization in this population.
Keywords: Aged; Cost of Illness; Female; Financing, Personal; Health Expenditures; Humans; Income; Insurance, Health; Male; Medicare; Neoplasms; Prospective Studies; Social Class; United States

Perceived weight discrimination mediates the prospective relation between obesity and depressive symptoms in U.S. and U.K. adults. - Robinson, Eric; Angelina R Sutin; Daly, Michael (Health Psychol, 2017)
OBJECTIVE: Obesity has been shown to increase risk of depression. Persons with obesity experience discrimination because of their body weight. Across 3 studies, we tested for the first time whether experiencing (perceived) weight-based discrimination explains why obesity is prospectively associated with increases in depressive symptoms. METHOD: Data from 3 studies, including the English Longitudinal Study of Ageing (2008/2009-2012/2013), the Health and Retirement Study (2006/2008-2010/2012), and Midlife in the United States (1995/1996-2004/2005), were used to examine associations between obesity, perceived weight discrimination, and depressive symptoms among 20,286 U.S. and U.K. adults. RESULTS: Across all 3 studies, Class II and III obesity were reliably associated with increases in depressive symptoms from baseline to follow-up. Perceived weight-based discrimination predicted increases in depressive symptoms over time and mediated the prospective association between obesity and depressive symptoms in all 3 studies. Persons with Class II and III obesity were more likely to report experiencing weight-based discrimination, and this explained approximately 31% of the obesity-related increase in depressive symptoms on average across the 3 studies. CONCLUSION: In U.S. and U.K. samples, the prospective association between obesity (defined using body mass index) and increases in depressive symptoms in adulthood may in part be explained by perceived weight discrimination. (PsycINFO Database Record
Keywords: Adult; Aged; Body Weight; depression; Female; Humans; Longitudinal Studies; Male; Middle Aged; Obesity; Prejudice; Prospective Studies; United Kingdom; United States; Young Adult

Positive Self-Perceptions of Aging and Lower Rate of Overnight Hospitalization in the US Population Over Age 50. - Jennifer K Sun; Eric S Kim; Jacqui Smith (Psychosom Med, 2017)
OBJECTIVE: The aging of the baby boomer generation has led to an unprecedented rise in the number of US adults reaching old age, prompting an urgent call for innovative and cost-effective ways to address the increasing health care needs of the aging population. Studying the role of psychosocial factors on health care use could offer insight into how to minimize hospitalizations among older adults. METHODS: We use prospective data from a subsample of 4735 participants (mean [standard deviation] age = 69 [8.79] years, 61% women) from the Health and Retirement Study, a nationally representative study of US adults over age 50, to examine the association between self-perceptions of aging (SPA) and self-reported overnight hospitalizations after adjusting for a comprehensive list of sociodemographic, health-related, and behavioral factors. RESULTS: Over the 4-year follow-up period, there were a total of 5196 overnight hospitalizations, and 44% of the sample reported being hospitalized overnight at least once. After adjusting for sociodemographic factors, each standard deviation increase in positive SPA was associated with a lower rate of overnight hospitalization (incidence rate ratio = 0.75; 95% confidence interval = 0.71-0.80, p < .001). After dividing respondents into quartiles of SPA, we observed a dose-response relationship with individuals in higher quartiles showing increasingly lower rates of overnight hospitalization. CONCLUSIONS: Positive self-perceptions of aging are associated with a lower rate of hospitalization among older adults over a 4-year period. Future research should examine the factors that contribute to older adults' SPA and explore the pathways through which attitudes toward aging influence the use of health care resources.
Keywords: Aged; Aging; Female; Follow-Up Studies; Hospitalization; Humans; Male; Middle Aged; Self Concept; United States

Receipt of Caregiving and Fall Risk in US Community-dwelling Older Adults. - Geoffrey J Hoffman; Hays, Ron D; Steven P Wallace; Martin F Shapiro; Yakusheva, Olga; Susan L Ettner (Med Care, 2017)
BACKGROUND: Falls and fall-related injuries (FRI) are common and costly occurrences among older adults living in the community, with increased risk for those with physical and cognitive limitations. Caregivers provide support for older adults with physical functioning limitations, which are associated with fall risk. DESIGN: Using the 2004-2012 waves of the Health and Retirement Study, we examined whether receipt of low (0-13 weekly hours) and high levels (≥14 weekly hours) of informal care or any formal care is associated with lower risk of falls and FRIs among community-dwelling older adults. We additionally tested whether serious physical functioning (≥3 activities of daily living) or cognitive limitations moderated this relationship. RESULTS: Caregiving receipt categories were jointly significant in predicting noninjurious falls (P=0.03) but not FRIs (P=0.30). High levels of informal care category (P=0.001) and formal care (P<0.001) had stronger associations with reduced fall risk relative to low levels of informal care. Among individuals with ≥3 activities of daily living, fall risks were reduced by 21% for those receiving high levels of informal care; additionally, FRIs were reduced by 42% and 58% for those receiving high levels of informal care and any formal care. High levels of informal care receipt were also associated with a 54% FRI risk reduction among the cognitively impaired. CONCLUSIONS: Fall risk reductions among older adults occurred predominantly among those with significant physical and cognitive limitations. Accordingly, policy efforts involving fall prevention should target populations with increased physical functioning and cognitive limitations. They should also reduce financial barriers to informal and formal caregiving.
Keywords: Accidental Falls; Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Female; Geriatric Assessment; Humans; Independent Living; Longitudinal Studies; Male; Middle Aged; Risk Assessment; Risk Factors; United States

The relationship between family support; pain and depression in elderly with arthritis. - Hung, Man; Bounsanga, Jerry; Maren W Voss; Anthony B. Crum; Wei Chen; Wendy Church Birmingham (Psychol Health Med, 2017)
The prevalence and chronic nature of arthritis make it the most common cause of disability among U.S.A adults. Family support reduces the negative impact of chronic conditions generally but its role in pain and depression for arthritic conditions is not well understood. A total of 844 males (35.0%) and 1567 females (65.0%) with arthritic conditions (n = 2411) were drawn from the 2012 Health and Retirement Study to examine the effect of family support on pain and depressive symptoms. Using regression analysis and controlling for age, ethnicity, gender, marital/educational status and employment/income, physical function/disability status, pain and antidepressant medications, and other clinical indicators of chronic health conditions, we examined the effects of family support (spouse, children, other) on pain and depression levels. Results indicated that depressive symptoms decreased significantly with strong family and spousal support (p < .05). Pain decreased as support levels increased, but was non-statistically significant. This study provides new insights into the relationship between family support, pain, and depression for individuals with arthritis. Future longitudinal studies are needed to evaluate family support and relationships over a wider spectrum of demographics.
Keywords: Aged; Aged, 80 and over; Aging; Arthralgia; Arthritis; depression; Family; Female; Humans; Male; Middle Aged; Social Support; United States

Smoking Response to Health and Medical Spending Changes and the Role of Insurance. - Marti, Joachim; Michael R. Richards (Health Econ, 2017)
Severe health shocks provide new information about one's personal health and have been shown to influence smoking behaviors. In this paper, we suggest that they may also convey information about the hard to predict financial consequences of illnesses. Relevant financial risk information is idiosyncratic and unavailable to the consumer preceding illness, and the information search costs are high. However, new and salient information about the health as well as financial consequences of smoking after a health shock may impact smoking responses. Using variation in the timing of health shocks and two features of the US health care system (uninsured spells and aging into the Medicare program at 65), we test for heterogeneity in the post-shock smoking decision according to plausibly exogenous changes in financial risk exposure to medical spending. We also explore the relationship between smoking and the evolution of out-of-pocket costs. Individuals experiencing a cardiovascular health shock during an uninsured spell have more than twice the cessation effect of those receiving the illness while insured. For those uninsured prior to age 65 years, experiencing a cardiovascular shock post Medicare eligibility completely offsets the cessation effect. We also find that older adults' medical spending changes separate from health shocks influence their smoking behavior. Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: Cardiovascular Diseases; Female; Health Behavior; Health Expenditures; Health Surveys; Humans; Insurance, Health; Male; Medically Uninsured; Medicare; Middle Aged; Risk Factors; Smoking; Socioeconomic factors; United States

Social Activities, Incident Cardiovascular Disease, and Mortality. - Sae Hwang Han; Jane Tavares; Evans, Molly; Jane S Saczynski; Jeffrey A Burr (J Aging Health, 2017)
OBJECTIVE: This study examined the relationships between social activities, incident cardiovascular disease (CVD), and non-CVD mortality among older adults in the United States. METHOD: Data from the Health and Retirement Study (2006-2010) were employed. Two measures of social engagement, volunteering and informal helping, along with two measures of social participation, attendance at religious services and social group meetings, were included. Mediation models for health behaviors were estimated. RESULTS: Multinomial logistic regression models demonstrated that volunteering provided the most consistent results in terms of a lower risk of incident CVD and mortality. Furthermore, volunteering at higher time commitments is related to lower CVD incidence and death; informally helping others at a modest time commitment is related to lower risk of death only. Health behaviors mediated the relationships. Social participation was not related to either CVD or mortality. DISCUSSION: Social activity is a modifiable behavior that may be considered a potential health intervention.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Humans; Incidence; Leisure activities; Logistic Models; Male; Middle Aged; Retirement; United States

Social Capital and Unretirement: Exploring the Bonding, Bridging, and Linking Aspects of Social Relationships. - Guillermo Ernest Gonzales; Nowell, William Benjamin (Res Aging, 2017)
Working longer is an important area of research given extended life expectancy, shortfalls of retirement income, desires to remain socially engaged, and solvency concerns of social insurance programs. The purpose of this longitudinal population-based study of older adults is to examine how different types of social resources (social bonding, bridging, and linking) relate to returning to work after retirement. Data were drawn from the Health and Retirement Study of fully retired older adults aged 62+ in 1998 ( N = 8,334) and followed to 2008. After controlling for a comprehensive set of fixed and time-varying covariates, findings suggest that social bridging (informal volunteering) and social linking (formal volunteering, partnered with an employed spouse) were strongly and positively related to returning to work (Hazard Ratio [HR]: 1.49, p < .001; HR: 1.58, p < .0001; and HR: 1.75, p < .0001, respectively). Social bonding resources were not significantly associated with returning to work. Implications for social policy are discussed.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Cross-Sectional Studies; Employment; Female; Humans; Longitudinal Studies; Male; Middle Aged; Retirement; Social capital; United States

Successful Aging as the Intersection of Individual Resources, Age, Environment, and Experiences of Well-being in Daily Activities. - Shannon T. Mejia; Lindsay H Ryan; Gonzalez, Richard; Jacqui Smith (J Gerontol B Psychol Sci Soc Sci, 2017)
Objective: We conceptualize successful aging as a cumulative index of individual resources (the absence of disease and disability, high cognitive and physical functioning, social embeddedness) in the service of successful aging outcomes (global well-being, experienced well-being, and vital status), and conditioned by age, social structure, and environment. Method: The study used baseline and follow-up data from the 2008-2014 waves of the Health and Retirement Study (N = 17,230; age = 51-101). Linear, multilevel, and logistic models compared individual resources at baseline as independent, cumulative, and binary predictors of outcomes 4 years later. Results: Individual resources were unequally distributed across age group and social structures (education, wealth, race, gender) and had a cumulative effect on all successful aging outcomes. For experienced well-being, individual resources were most important at midlife and for groups with lower education. Person-environment congruence (social cohesion, city satisfaction) was associated with all successful aging outcomes and conditioned the effect of individual resources on experienced well-being. Discussion: A cumulative index allows for gradations in resources that can be compensated for by external factors such as person-environment congruence. This index could guide policy and interventions to enhance resources in vulnerable subgroups and diminish inequalities in successful aging outcomes.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Aging; environment; Female; Follow-Up Studies; Health Status; Humans; Male; Middle Aged; Personal Satisfaction; Social Support; United States

Successful Aging in the Context of the Disablement Process: Working and Volunteering as Moderators on the Association Between Chronic Conditions and Subsequent Functional Limitations. - Ben Lennox Kail; Dawn C Carr (J Gerontol B Psychol Sci Soc Sci, 2017)
Objectives : This study evaluated the successful aging model by assessing the impact of two forms of productive engagement-working and volunteering-as potential interventions in the process of disablement. Method : The Health and Retirement Study was used to (a) estimate two-stage selection equations of (i) currently working part time and full time and (ii) currently volunteering less than 100 hours and volunteering 100 hours or more per year (net of chronic health problems) and (b) assess whether, net of selection, working, and volunteering moderate the association between chronic conditions and subsequent functional limitations. Results : Chronic conditions were associated with elevated levels of subsequent functional limitations, whereas both working and volunteering were associated with lower levels of subsequent functional limitations. Moreover, workers and volunteers of less than 100 hours per year experienced a reduction in the association of chronic conditions on subsequent functional limitations. Discussion : This research highlights the role of productive engagement as a key element in successful aging. Not only do work and volunteering have direct associations with health outcomes themselves, but they also act as potential interventions in the process of disablement by attenuating the way in which chronic conditions are translated into subsequent functional limitations. This suggests that (a) future research should apply successful aging models to health processes as well as health outcomes and (b) policy makers should support social institutions that foster late-life productive engagement.
Keywords: Aged; Aged, 80 and over; Aging; Disabled Persons; Employment; Female; Humans; Male; United States; Volunteers

Telomere Length Among Older U.S. Adults: Differences by Race/Ethnicity, Gender, and Age. - Lauren L Brown; Belinda L Needham; Jennifer A Ailshire (J Aging Health, 2017)
OBJECTIVE: We examine race/ethnic, gender, and age differences in telomere length (TL) within a diverse, nationally representative sample of older adults. METHOD: Data come from 5,228 White, Black, and Hispanic respondents aged 54+ in the 2008 Health and Retirement Study. TL was assayed from saliva using quantitative polymerase chain reaction (qPCR) by comparing telomere sequence copy number with a single gene copy number (T/S ratio). Linear regression was used to examine TL by race/ethnicity, gender, and age adjusting for social, economic, and health characteristics. RESULTS: Women had longer TL than men (p < .05). Blacks ( p < .05) and Hispanics ( p < .10) had longer TL than Whites. Black women and men had the longest TL relative to other groups ( p < .05), while White men had the shortest TL ( p < .05). Black women and Hispanic men showed greater differences in TL with age. DISCUSSION: Findings indicate social patterns in TL by race/ethnicity, gender, and age among older adults do not reflect differences observed in most population health outcomes.
Keywords: Aged; Aging; Biomarkers; Female; Health Status Disparities; Humans; Interviews as Topic; Male; Minority Groups; Qualitative Research; Telomere; United States

African Ancestry, Social Factors, and Hypertension Among Non-Hispanic Blacks in the Health and Retirement Study. - Jessica R Marden; Stefan Walter; Jay S Kaufman; M. Maria Glymour (Biodemography Soc Biol, 2016)
The biomedical literature contains much speculation about possible genetic explanations for the large and persistent black-white disparities in hypertension, but profound social inequalities are also hypothesized to contribute to this outcome. Our goal is to evaluate whether socioeconomic status (SES) differences provide a plausible mechanism for associations between African ancestry and hypertension in a U.S. cohort of older non-Hispanic blacks. We included only non-Hispanic black participants (N = 998) from the Health and Retirement Study who provided genetic data. We estimated percent African ancestry based on 84,075 independent single nucleotide polymorphisms using ADMIXTURE V1.23, imposing K = 4 ancestral populations, and categorized into quartiles. Hypertension status was self-reported in the year 2000. We used linear probability models (adjusted for age, sex, and southern birth) to predict prevalent hypertension with African ancestry quartile, before and after accounting for a small set of SES measures. Respondents with the highest quartile of African ancestry had 8 percentage points' (RD = 0.081; 95% CI: -0.001, 0.164) higher prevalence of hypertension compared to the lowest quartile. Adjustment for childhood disadvantage, education, income, and wealth explained over one-third (RD = 0.050; 95% CI: -0.034, 0.135) of the disparity. Explanations for the residual disparity remain unspecified and may include other indicators of SES or diet, lifestyle, and psychosocial mechanisms.
Keywords: African Americans; Aged; Female; Health Status Disparities; Humans; Hypertension; Life Style; Male; Middle Aged; Prevalence; Risk Factors; Socioeconomic factors; United States

Age Differences in the Association Between Body Mass Index Class and Annualized Medicare Expenditures. - Daniel O. Clark; Kathleen A Lane; Ambuehl, Roberta; Tu, Wanzhu; Chiung-Ju Liu; Kathleen T. Unroe; Christopher M. Callahan (J Aging Health, 2016)
OBJECTIVE: The aim of the study is to assess the relationship between body mass index (BMI) class and Medicare claims among young-old (65-69), old (70-74), and old-old (75+) adults over a 10-year period. METHOD: We assessed costs by BMI class and age group among 9,300 respondents to the 1998 Health and Retirement Study (HRS) with linked 1998-2008 Medicare claims data. BMI was classified as normal (18.5-24.9), overweight (25-29.9), mild obesity (30-34.9), or severe obesity (35 or above). RESULTS: Annualized total Medicare claims adjusted for age, gender, ethnicity, education, and smoking history were 109% greater for severely obese young-old adults in comparison with normal weight young-old adults (US$9,751 vs. US$4,663). Total annualized claim differences between the normal weight and severely obese in the old and old-old groups were not statistically significant. DISCUSSION: Excess Medicare expenditures related to obesity may be concentrated among severely obese young-old adults. Preventing severe obesity among middle and older aged adults may have large cost implications for society.
Keywords: Age Factors; Aged; Body Mass Index; Female; Health Expenditures; Humans; Male; Medicare; Obesity; United States

Antidepressant use and functional limitations in U.S. older adults. - An, Ruopeng; Lu, Lingyun (J Psychosom Res, 2016)
OBJECTIVE: The upsurge in prevalence and long-term use of antidepressants among older adults might have profound health implications beyond depressive symptom management. This study examined the relationship between antidepressant use and functional limitation onset in U.S. older adults. METHODS: Study sample came from 2006 and 2008 waves of the Health and Retirement Study, in combination with data from 2005 and 2007 Prescription Drug Study. Self-reported antidepressant use was identified based on the therapeutic classification of Cerner Multum's Lexicon. Functional limitations were classified into those pertaining to physical mobility, large muscle function, activities of daily living, gross motor function, fine motor function, and instrumental activities of daily living. Cox proportional hazard models were performed to assess the effects of antidepressant use on future functional limitation onset by limitation category, antidepressant type, and length of use, adjusted by depression status and other individual characteristics. RESULTS: Antidepressant use for one year and longer was associated with an increase in the risk of functional limitation by 8% (95% confidence interval=4%-12%), whereas the relationship between antidepressant use less than a year and function limitation was statistically nonsignificant. Antidepressant use was associated with an increase in the risk of functional limitation by 8% (3%-13%) among currently nondepressed participants but not currently depressed participants. CONCLUSION: Long-term antidepressant use in older adults should be prudently evaluated and regularly monitored to reduce the risk of functional limitation. Future research is warranted to examine the health consequences of extended and/or off-label antidepressant use in absence of depressive symptoms.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Antidepressive Agents; depression; Drug Utilization; Female; Health Surveys; Humans; Longitudinal Studies; Male; Mobility Limitation; Muscle, Skeletal; Prevalence; Risk Factors; Socioeconomic factors; United States

Are self-reported neighbourhood characteristics associated with onset of functional limitations in older adults with or without memory impairment? - Thu T Nguyen; Rist, Pamela M; M. Maria Glymour (J Epidemiol Community Health, 2016)
BACKGROUND: Neighbourhood resources may preserve functional independence in older adults, but little is known about whether benefits differ for individuals with normal and impaired memory. We evaluated the extent to which neighbourhood context was related to onset of instrumental and basic activities of daily living (I/ADL) limitations and whether relationships were modified by memory impairment. METHODS: Health and Retirement Study participants 50+ years of age without baseline I/ADL limitations (n=8726 for IADL and n=8345 for ADL models) were interviewed biennially for up to 8 years. Self-reported neighbourhood characteristics were scaled from 0 (worst) to 1 (best). Memory, assessed by direct and proxy cognitive assessments, was dichotomised at the 20th centile. We used pooled logistic regression models, adjusted for demographics and individual characteristics. RESULTS: Low neighbourhood physical disorder (OR=0.51 (95% CI: 0.37 to 0.69)), high social cohesion (OR=0.46 (0.34 to 0.62)), and high safety (OR=0.59 (0.46 to 0.76)) were associated with reduced incidence of IADL limitations. These neighbourhood characteristics were also associated with lower incidence of ADL limitations (disorder OR=0.59 (0.43 to 0.81)); social cohesion OR=0.60 (0.45 to 0.81)); safety OR=0.74 (0.58 to 0.93)). High social ties were not related to ADLs (OR=1.01(0.80 to 1.28)) or IADLs (OR=0.93(0.74 to 1.17)). The benefits of these neighbourhood characteristics for ADLs were similar among those with and without memory impairment but primarily observed among those without memory impairment for IADLs. CONCLUSIONS: Older adults living in neighbourhoods with low physical disorder, high social cohesion and high safety experience lower incidence of IADL and ADL limitations. Memory status modified the estimated effects of neighbourhood characteristics on IADL but not ADL limitations.
Keywords: Activities of Daily Living; Aged; Female; Humans; Independent Living; Interviews as Topic; Longitudinal Studies; Male; Memory Disorders; Middle Aged; Mobility Limitation; Residence Characteristics; Risk Factors; United States

Association of a Genetic Risk Score With Body Mass Index Across Different Birth Cohorts. - Stefan Walter; Mejía-Guevara, Iván; Estrada, Karol; Sze Y Liu; M. Maria Glymour (JAMA, 2016)
IMPORTANCE: Many genetic variants are associated with body mass index (BMI). Associations may have changed with the 20th century obesity epidemic and may differ for black vs white individuals. OBJECTIVE: Using birth cohort as an indicator for exposure to obesogenic environment, to evaluate whether genetic predisposition to higher BMI has a larger magnitude of association among adults from more recent birth cohorts, who were exposed to the obesity epidemic at younger ages. DESIGN, SETTING, AND PARTICIPANTS: Observational study of 8788 adults in the US national Health and Retirement Study who were aged 50 years and older, born between 1900 and 1958, with as many as 12 BMI assessments from 1992 to 2014. EXPOSURES: A multilocus genetic risk score for BMI (GRS-BMI), calculated as the weighted sum of alleles of 29 single nucleotide polymorphisms associated with BMI, with weights equal to the published per-allele effects. The GRS-BMI represents how much each person's BMI is expected to differ, based on genetic background (with respect to these 29 loci), from the BMI of a sample member with median genetic risk. The median-centered GRS-BMI ranged from -1.68 to 2.01. MAIN OUTCOMES AND MEASURES: BMI based on self-reported height and weight. RESULTS: GRS-BMI was significantly associated with BMI among white participants (n = 7482; mean age at first assessment, 59 years; 3373 [45%] were men; P <.001) and among black participants (n = 1306; mean age at first assessment, 57 years; 505 [39%] were men; P <.001) but accounted for 0.99% of variation in BMI among white participants and 1.37% among black participants. In multilevel models accounting for age, the magnitude of associations of GRS-BMI with BMI were larger for more recent birth cohorts. For example, among white participants, each unit higher GRS-BMI was associated with a difference in BMI of 1.37 (95% CI, 0.93 to 1.80) if born after 1943, and 0.17 (95% CI, -0.55 to 0.89) if born before 1924 (P = .006). For black participants, each unit higher GRS-BMI was associated with a difference in BMI of 3.70 (95% CI, 2.42 to 4.97) if born after 1943, and 1.44 (95% CI, -1.40 to 4.29) if born before 1924. CONCLUSIONS AND RELEVANCE: For participants born between 1900 and 1958, the magnitude of association between BMI and a genetic risk score for BMI was larger among persons born in later cohorts. This suggests that associations of known genetic variants with BMI may be modified by obesogenic environments.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Aged, 80 and over; Alleles; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Multilocus Sequence Typing; Obesity; Polymorphism, Single Nucleotide; Risk Factors; United States

Association of retirement age with mortality: a population-based longitudinal study among older adults in the USA. - Wu, Chenkai; Michelle C Odden; Gwenith G Fisher; Stawski, Robert S (J Epidemiol Community Health, 2016)
BACKGROUND: Retirement is an important transitional process in later life. Despite a large body of research examining the impacts of health on retirement, questions still remain regarding the association of retirement age with survival. We aimed to examine the association between retirement age and mortality among healthy and unhealthy retirees and to investigate whether sociodemographic factors modified this association. METHODS: On the basis of the Health and Retirement Study, 2956 participants who were working at baseline (1992) and completely retired during the follow-up period from 1992 to 2010 were included. Healthy retirees (n=1934) were defined as individuals who self-reported health was not an important reason to retire. The association of retirement age with all-cause mortality was analysed using the Cox model. Sociodemographic effect modifiers of the relation were examined. RESULTS: Over the study period, 234 healthy and 262 unhealthy retirees died. Among healthy retirees, a 1-year older age at retirement was associated with an 11% lower risk of all-cause mortality (95% CI 8% to 15%), independent of a wide range of sociodemographic, lifestyle and health confounders. Similarly, unhealthy retirees (n=1022) had a lower all-cause mortality risk when retiring later (HR 0.91, 95% CI 0.88 to 0.94). None of the sociodemographic factors were found to modify the association of retirement age with all-cause mortality. CONCLUSIONS: Early retirement may be a risk factor for mortality and prolonged working life may provide survival benefits among US adults.
Keywords: Adult; Aged; Female; Health Status; Humans; Life Expectancy; Life Style; Longitudinal Studies; Male; Middle Aged; Mortality, Premature; Retirement; Risk Factors; United States

Associations between health literacy and preventive health behaviors among older adults: findings from the health and retirement study. - Dena M. Fernandez; Janet L. Larson; Brian J Zikmund-Fisher (BMC Public Health, 2016)
BACKGROUND: While the association between inadequate health literacy and adverse health outcomes has been well documented, less is known about the impact of health literacy on health perceptions, such as perceptions of control over health, and preventive health behaviors. METHODS: We identified a subsample of participants (N = 707) from the Health and Retirement Study (HRS), a nationally representative sample of older adults, who participated in health literacy testing. Self-reported health literacy was measured with a literacy screening question, and objective health literacy with a summed score of items from the Test of Functional Health Literacy. We compared answers on these items to those related to participation in health behaviors such as cancer screening, exercise, and tobacco use, as well as self-referencing health beliefs. RESULTS: In logistic regression models adjusted for gender, education, race, and age, participants with adequate self-reported health literacy (compared to poorer levels of health literacy) had greater odds of participation in mammography within the last 2 years (Odds ratio [OR] = 2.215, p = 0.01) and participation in moderate exercise two or more times per week (OR = 1.512, p = 0.03). Participants with adequate objective health literacy had reduced odds of participation in monthly breast self-exams (OR = 0.369, p = 0.004) and reduced odds of current tobacco use (OR = 0.456, p = 0.03). In adjusted linear regression analyses, self-reported health literacy made a small but significant contribution to explaining perceived control of health (β 0.151, p = <0.001) and perceived social standing (β 0.112, p = 0.002). CONCLUSION: In a subsample of older adult participants of the HRS, measures of health literacy were positively related to several health promoting behaviors and health-related beliefs and non-use of breast self-exams, a screening behavior of questionable benefit. These relationships varied however, between self-reported and objectively-measured health literacy. Further investigation into the specific mechanisms that lead higher literacy people to pursue health promoting actions appears clearly warranted.
Keywords: Aged; Aged, 80 and over; Female; Health Behavior; Health Knowledge, Attitudes, Practice; Health Literacy; Health Promotion; Humans; Logistic Models; Male; Middle Aged; Odds Ratio; Preventive Health Services; Regression Analysis; Retirement; United States

Associations of childhood adversity and adulthood trauma with C-reactive protein: A cross-sectional population-based study. - Joy E. Lin; Thomas C Neylan; Elissa S Epel; O Donovan, Aoife (Brain Behav Immun, 2016)
Mounting evidence highlights specific forms of psychological stress as risk factors for ill health. Particularly strong evidence indicates that childhood adversity and adulthood trauma exposure increase risk for physical and psychiatric disorders, and there is emerging evidence that inflammation may play a key role in these relationships. In a population-based sample from the Health and Retirement Study (n=11,198, mean age 69 ± 10), we examine whether childhood adversity, adulthood trauma, and the interaction between them are associated with elevated levels of the systemic inflammatory marker high sensitivity C-reactive protein (hsCRP). All models were adjusted for age, gender, race, education, and year of data collection, as well as other possible confounds in follow-up sensitivity analyses. In our sample, 67% of individuals had experienced at least one traumatic event during adulthood, and those with childhood adversity were almost three times as likely to have experienced trauma as an adult. Childhood adversities and adulthood traumas were independently associated with elevated levels of hsCRP (β=0.03, p=0.01 and β=0.05, p<0.001, respectively). Those who had experienced both types of stress had higher levels of hsCRP than those with adulthood trauma alone, Estimate=-0.06, 95% CI [-0.003, -0.12], p=0.04, but not compared to those with childhood adversity alone, Estimate=-0.06, 95% CI [0.03, -0.16], p=0.19. There was no interaction between childhood and adulthood trauma exposure. To our knowledge, this is the first study to examine adulthood trauma exposure and inflammation in a large population-based sample, and the first to explore the interaction of childhood adversity and adulthood trauma with inflammation. Our study demonstrates the prevalence of trauma-related inflammation in the general population and suggests that childhood adversity and adulthood trauma are independently associated with elevated inflammation.
Keywords: Aged; Biomarkers; C-reactive protein; Cross-Sectional Studies; Female; Humans; Inflammation; Longitudinal Studies; Male; Mental Disorders; Middle Aged; Prevalence; Risk Factors; Socioeconomic factors; Stress, Psychological; Trauma and Stressor Related Disorders; United States

Changes in Depressive Symptoms among Older Adults with Multiple Chronic Conditions: Role of Positive and Negative Social Support. - Ahn, SangNam; Kim, Seonghoon; Zhang, Hongmei (Int J Environ Res Public Health, 2016)
Depression severely affects older adults in the United States. As part of the social environment, significant social support was suggested to ameliorate depression among older adults. We investigate how varying forms of social support moderate depressive symptomatology among older adults with multiple chronic conditions (MCC). Data were analyzed using a sample of 11,400 adults, aged 65 years or older, from the 2006-2012 Health and Retirement Study. The current study investigated the moderating effects of positive or negative social support from spouse, children, other family, and friends on the association between MCC and depression. A linear mixed model with repeated measures was used to estimate the effect of MCC on depression and its interactions with positive and negative social support in explaining depression among older adults. Varying forms of social support played different moderating roles in depressive symptomatology among older adults with MCC. Positive spousal support significantly weakened the deleterious effect of MCC on depression. Conversely, all negative social support from spouse, children, other family, and friends significantly strengthened the deleterious effect of MCC on depression. Minimizing negative social support and maximizing positive spousal support can reduce depression caused by MCC and lead to successful aging among older adults.
Keywords: Aged; Aged, 80 and over; Aging; depression; Family; Female; Friends; Humans; Male; Multiple Chronic Conditions; Social Support; United States

Changes in Visual Function in the Elderly Population in the United States: 1995-2010. - Chen, Yiqun; Hahn, Paul; Frank A Sloan (Ophthalmic Epidemiol, 2016)
PURPOSE: To document recent trends in visual function among the United States population aged 70+ years and investigate how the trends can be explained by inter-temporal changes in: (1) population sociodemographic characteristics, and chronic disease prevalence, including eye diseases (compositional changes); and (2) effects of the above factors on visual function (structural changes). METHODS: Data from the 1995 Asset and Health Dynamics among the Oldest Old (AHEAD) and the 2010 Health and Retirement Study (HRS) were merged with Medicare Part B claims in the interview years and the 2 previous years. Decomposition analysis was performed. Respondents from both studies were aged 70+ years. The outcome measure was respondent self-reported visual function on a 6-point scale (from 6 = blind to 1 = excellent). RESULTS: Overall, visual function improved from slightly worse than good (3.14) in 1995 to slightly better than good (2.98) in 2010. A decline in adverse effects of aging on vision was found. Among the compositional changes were higher educational attainment leading to improved vision, and higher prevalence of such diseases as diabetes mellitus, which tended to lower visual function. However, compared to compositional changes, structural changes were far more important, including decreased adverse effects of aging, diabetes mellitus (when not controlling for eye diseases), and diagnosed glaucoma. CONCLUSION: Although the US population has aged and is expected to age further, visual function improved among elderly persons, especially among persons 80+ years, likely reflecting a favorable role of structural changes identified in this study in mitigating the adverse effect of ongoing aging on vision.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Chronic disease; Cross-Sectional Studies; Female; Humans; Male; Medicare Part B; Prevalence; Self Report; Socioeconomic factors; United States; Visual Acuity; Visually Impaired Persons

Cigarette Taxes and Older Adult Smoking: Evidence from the Health and Retirement Study. - Johanna Catherine Maclean; Asia Sikora Kessler; Donald S. Kenkel (Health Econ, 2016)
In this study, we use the Health and Retirement Study to test whether older adult smokers, defined as those 50 years and older, respond to cigarette tax increases. Our preferred specifications show that older adult smokers respond modestly to tax increases: a $1.00 (131.6%) tax increase leads to a 3.8-5.2% reduction in cigarettes smoked per day (implied tax elasticity = -0.03 to -0.04). We identify heterogeneity in tax elasticity across demographic groups as defined by sex, race/ethnicity, education, and marital status and by smoking intensity and level of addictive stock. These findings have implications for public health policy implementation in an aging population.
Keywords: Age Factors; Aged; Consumer Behavior; Female; Humans; Longitudinal Studies; Male; Middle Aged; Regression Analysis; Smoking; Taxes; Tobacco Products; United States

Claims-based Identification Methods and the Cost of Fall-related Injuries Among US Older Adults. - Geoffrey J Hoffman; Hays, Ron D; Martin F Shapiro; Steven P Wallace; Susan L Ettner (Med Care, 2016)
OBJECTIVES: Compare expenditures of fall-related injuries (FRIs) using several methods to identify FRIs in administrative claims data. RESEARCH DESIGN: Using 2007-2009 Medicare claims and 2008 Health and Retirement Survey data, FRIs were identified using external-cause-of-injury (e-codes 880/881/882/884/885/888) only, e-codes plus a broad set of primary diagnosis codes, and a newer approach using e-codes and diagnostic and procedural codes. Linear regression models adjusted for sociodemographic, health, and geographic characteristics were used to estimate per-FRI, service component, patient cost share, expenditures by type of initial FRI treatment (inpatient, emergency department only, outpatient), and total annual FRI-related Medicare expenditures. SUBJECTS: The analysis included 5497 community-dwelling adults ≥65 (228 FRI, 5269 non-FRI individuals) with continuous Medicare coverage and alive during the 24-month study. RESULTS: The 3 FRI identification methods produced differing distributions of index FRI type and varying estimated expenditures: $12,171 [95% confidence interval (CI), $4662-$19,680], $5648 (95% CI, $3819-$7476), and $9388 (95% CI, $5969-$12,808). In all models, most spending occurred in hospital, outpatient, and skilled nursing facility (SNF) settings, but greater proportions of SNF and outpatient spending were observed with commonly used FRI identification methods. Patient cost-sharing was estimated at $691-$1900 across the 3 methods. Inpatient-treated index FRIs were more expensive than emergency department and outpatient-treated FRIs across all methods, but were substantially higher when identifying FRI using only e-codes. Estimated total FRI-related Medicare expenditures were highly variable across methods. CONCLUSIONS: FRIs are costly, with implications for Medicare and its beneficiaries. However, expenditure estimates vary considerably based on the method used to identify FRIs.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Cross-Over Studies; Female; Humans; Insurance Claim Review; Male; Medicare; United States; Wounds and Injuries

Combat exposure, social relationships, and subjective well-being among middle-aged and older Veterans. - Mai See Yang; Jeffrey A Burr (Aging Ment Health, 2016)
OBJECTIVES: This study described the association of subjective well-being with combat exposure and social relationships among middle-aged and older Veteran men in the USA. The stress-buffering hypothesis, which predicts social relationships may moderate the association between combat exposure and subjective well-being, was also examined. METHOD: Data from the 2008 Health and Retirement Study (N = 2961) were used to estimate logistic regression models, focusing on three measures of subjective well-being: depression, life satisfaction, and self-reported health. RESULTS: In the fully adjusted models, there were no statistically significant relationships between combat exposure and the three indicators of subjective well-being. However, compared to Veterans who had lower scores on the social relationship index, Veterans who had higher scores were less likely to be depressed and less likely to report poor or fair health. Veterans who had higher scores on the social relationships index reported higher levels of life satisfaction than those Veterans who had lower scores. There was no evidence for a social relationships buffering effect. CONCLUSION: The results of this study demonstrated that combat exposure did not have a long-term relationship with subjective well-being. Longitudinal research designs with more comprehensive indicators of combat exposure may help researchers better understand some of the underlying complexity of this relationship. Complementary research with samples of women Veterans, as well as samples of Hispanic, and non-Black, non-White Veterans, is also needed.
Keywords: Aged; Combat Disorders; depression; Health Status; Humans; Interpersonal Relations; Male; Middle Aged; Personal Satisfaction; United States; Veterans

Combinations of Chronic Conditions, Functional Limitations, and Geriatric Syndromes that Predict Health Outcomes. - Siran M Koroukian; Nicholas K Schiltz; David F Warner; Jiayang Sun; Paul M Bakaki; Kathleen A Smyth; Kurt C Stange; Charles W Given (J Gen Intern Med, 2016)
BACKGROUND: The strategic framework on multiple chronic conditions released by the US Department of Health and Human Services calls for identifying homogeneous subgroups of older adults to effectively target interventions aimed at improving their health. OBJECTIVE: We aimed to identify combinations of chronic conditions, functional limitations, and geriatric syndromes that predict poor health outcomes. DESIGN, SETTING AND PARTICIPANTS Data from the 2010-2012 Health and Retirement Study provided a representative sample of U.S. adults 50 years of age or older (n = 16,640). MAIN MEASURES: Outcomes were: Self-reported fair/poor health, self-rated worse health at 2 years, and 2-year mortality. The main independent variables included self-reported chronic conditions, functional limitations, and geriatric syndromes. We conducted tree-based classification and regression analysis to identify the most salient combinations of variables to predict outcomes. KEY RESULTS: Twenty-nine percent and 23 % of respondents reported fair/poor health and self-rated worse health at 2 years, respectively, and 5 % died in 2 years. The top combinations of conditions identified through our tree analysis for the three different outcome measures (and percent respondents with the outcome) were: a) for fair/poor health status: difficulty walking several blocks, depressive symptoms, and severe pain (> 80 %); b) for self-rated worse health at 2 years: 68.5 years of age or older, difficulty walking several blocks and being in fair/poor health (60 %); and c) for 2-year mortality: 80.5 years of age or older, and presenting with limitations in both ADLs and IADLs (> 40 %). CONCLUSIONS: Rather than chronic conditions, functional limitations and/or geriatric syndromes were the most prominent conditions in predicting health outcomes. These findings imply that accounting for chronic conditions alone may be less informative than also accounting for the co-occurrence of functional limitations and geriatric syndromes, as the latter conditions appear to drive health outcomes in older individuals.
Keywords: Activities of Daily Living; Age Distribution; Aged; Aged, 80 and over; Chronic disease; Comorbidity; Female; Geriatric Assessment; Health Status; Health Status Indicators; Humans; Longitudinal Studies; Male; Middle Aged; Mobility Limitation; Prognosis; Risk Factors; Self Report; Sex Distribution; Socioeconomic factors; Syndrome; United States

Comparing Alternative Effect Decomposition Methods: The Role of Literacy in Mediating Educational Effects on Mortality. - Thu T Nguyen; Eric J. Tchetgen Tchetgen; Ichiro Kawachi; Stephen E. Gilman; Stefan Walter; M. Maria Glymour (Epidemiology, 2016)
BACKGROUND: Inverse odds ratio weighting, a newly proposed tool to evaluate mediation in exposure-disease associations, may be valuable for a host of research questions, but little is known about its performance in real data. We compare this approach to a more conventional Baron and Kenny type of decomposition on an additive hazards scale to estimate total, direct, and indirect effects using the example of the role of literacy in mediating the effects of education on mortality. METHODS: Health and Retirement Study participants born in the United States between 1900 and 1947 were interviewed biennially for up to 12 years (N = 17,054). Literacy was measured with a brief vocabulary assessment. Decomposition estimates were derived based on Aalen additive hazards models. RESULTS: A 1 standard deviation difference in educational attainment (3 years) was associated with 6.7 fewer deaths per 1000 person-years (β = -6.7, 95% confidence interval [CI]: -7.9, -5.4). Of this decrease, 1.3 fewer deaths (β = -1.3, 95% CI: -4.0, 1.2) were attributed to the literacy pathway (natural indirect), representing 19% of the total effect. Baron and Kenny estimates were consistent with inverse odds ratio weighting estimates but were less variable (natural indirect effect: -1.2 [95% CI: -1.7, -0.69], representing 18% of total effect). CONCLUSION: In a cohort of older Americans, literacy partially mediated the effect of education on mortality. See Video Abstract at http://links.lww.com/EDE/B78.
Keywords: Aged; Aged, 80 and over; Educational Status; Female; Humans; Literacy; Longitudinal Studies; Male; Middle Aged; Mortality; Odds Ratio; Proportional Hazards Models; United States

A Comparison of Educational Differences on Physical Health, Mortality, and Healthy Life Expectancy in Japan and the United States. - Chi-Tsun Chiu; Mark D Hayward; Saito, Yasuhiko (J Aging Health, 2016)
OBJECTIVE: This study examined the educational gradient of health and mortality between two long-lived populations: Japan and the United States. METHOD: This analysis is based on the Nihon University Japanese Longitudinal Study of Aging and the Health and Retirement Study to compare educational gradients in multiple aspects of population health-life expectancy with/without disability, functional limitations, or chronic diseases, using prevalence-based Sullivan life tables. RESULTS: Our results show that education coefficients from physical health and mortality models are similar for both Japan and American populations, and older Japanese have better mortality and health profiles. DISCUSSION: Japan's compulsory national health service system since April 1961 and living arrangements with adult children may play an important role for its superior health profile compared with that of the United States.
Keywords: Activities of Daily Living; Age Distribution; Aged; Cause of Death; Cross-Cultural Comparison; Educational Status; Employment; Family Characteristics; Female; Health Status; Health Surveys; Healthy Lifestyle; Humans; Japan; Life Expectancy; Life Tables; Longitudinal Studies; Male; Middle Aged; Regression Analysis; Retirement; Sex Distribution; United States

Comparison of hypertension healthcare outcomes among older people in the USA and England. - Alan Marshall; James Nazroo; Feeney, Kevin; Jinkook Lee; Vanhoutte, Bram; Pendleton, Neil (J Epidemiol Community Health, 2016)
BACKGROUND: The USA and England have very different health systems. Comparing hypertension care outcomes in each country enables an evaluation of the effectiveness of each system. METHOD: The English Longitudinal Study of Ageing and the Health and Retirement Survey are used to compare the prevalence of controlled, uncontrolled and undiagnosed hypertension within the hypertensive population (diagnosed or measured within the survey data used) aged 50 years and above in the USA and in England. RESULTS: Controlled hypertension is more prevalent within the hypertensive population in the USA (age 50-64: 0.53 (0.50 to 0.57) and age 65+: 0.51 (0.49 to 0.53)) than in England (age 50-64: 0.45 (0.42 to 0.48) and age 65+: 0.42 (0.40 to 0.45)). This difference is driven by lower undiagnosed hypertension in the USA (age 50-64: 0.18 (0.15-0.21) and age 65+: 0.13 (0.12 to 0.14)) relative to England (age 50-64: 0.26 (0.24 to 0.29) and age 65+: 0.22 (0.20 to 0.24)). The prevalence of uncontrolled hypertension within the hypertensive population is very similar in the USA (age 50-64: 0.29 (0.26 to 0.32) and age 65+: 0.36 (0.34 to 0.38)) and England (age 50-64: 0.29 (0.26 to 0.32) and age 65+: 0.36 (0.34 to 0.39)). Hypertension care outcomes are comparable across US insurance categories. In both countries, undiagnosed hypertension is positively correlated with wealth (ages 50-64). Uncontrolled hypertension declines with rising wealth in the USA. CONCLUSIONS: Different diagnostic practices are likely to drive the cross-country differences in undiagnosed hypertension. US government health systems perform at least as well as private healthcare and are more equitable in the distribution of care outcomes. Higher undiagnosed hypertension among the affluent may reflect less frequent medical contact.
Keywords: Aged; Aging; Antihypertensive Agents; Blood pressure; Cross-Sectional Studies; Delivery of Health Care; England; Female; Health Surveys; Humans; Hypertension; Logistic Models; Longitudinal Studies; Male; Middle Aged; Outcome and Process Assessment, Health Care; Prevalence; Quality of Life; Socioeconomic factors; United States

Compression of disability between two birth cohorts of US adults with diabetes, 1992-2012: a prospective longitudinal analysis. - Barbara H. Bardenheier; Ji Lin; Zhuo, Xiaohui; Mohammed K. Ali; Theodore J Thompson; Yiling J. Cheng; Edward W Gregg (Lancet Diabetes Endocrinol, 2016)
BACKGROUND: The life expectancy of the average American with diabetes has increased, but the quality of health and functioning during those extra years are unknown. We aimed to investigate the net effect of recent trends in diabetes incidence, disability, and mortality on the average age of disability onset and the number of healthy and disabled years lived by adults with and without diabetes in the USA. We assessed whether disability expanded or was compressed in the population with diabetes and compared the findings with those for the population without diabetes in two consecutive US birth cohorts aged 50-70 years. METHODS: In this prospective longitudinal analysis, we analysed data for two cohorts of US adults aged 50-70 years from the Health and Retirement Study, including 1367 people with diabetes and 11 414 without diabetes. We assessed incident disability, remission from disability, and mortality between population-based cohort 1 (born 1931-41, follow-up 1992-2002) and cohort 2 (born 1942-47, follow up 2002-12). Disability was defined by mobility loss, difficulty with one or more instrumental activities of daily living, and difficulty with one or more activities of daily living. We entered age-specific probabilities representing the two birth cohorts into a five-state Markov model to estimate the number of years of disabled and disability-free life and life-years lost by age 70 years. FINDINGS: In people with diabetes, compared with cohort 1 (n=1067), cohort 2 (n=300) had more disability-free and total years of life, later onset of disability, and fewer disabled years. Simulations of the Markov models suggest that in men with diabetes aged 50 years, this difference between cohorts amounted to a 0·8-2·3 year delay in disability across the three metrics (mobility, 63·0 [95% CI 62·3-63·6] to 64·8 [63·6-65·7], p=0·01; instrumental activities of daily living, 63·5 [63·0-64·0] to 64·3 [63·0-65·3], p=0·24; activities of daily living, 62·7 [62·1-63·3] to 65·0 [63·5-65·9], p<0·0001) and 1·3 fewer life-years lost (ie, fewer remaining life-years up to age 70 years; from 2·8 [2·5-3·2] to 1·5 [1·3-1·9]; p<0·0001 for all three measures of disability). Among women with diabetes aged 50 years, this difference between cohorts amounted to a 1·1-2·3 year delay in disability across the three metrics (mobility, 61·3 [95% CI 60·5-62·1] to 63·2 [61·5-64·5], p=0·0416; instrumental activities of daily living, 63·0 [62·4-63·7] to 64·1 [62·7-65·2], p=0·16; activities of daily living, 62·3 [61·6-63·0] to 64·6 [63·1-65·6], p<0·0001) and 0·8 fewer life-years lost by age 70 years (1·9 [1·7-2·2] to 1·1 [0·9-1·5]; p<0·0001 for all three measures of disability). Parallel improvements were gained between cohorts of adults without diabetes (cohort 1, n=8687; cohort 2, n=2727); within both cohorts, those without diabetes had significantly more disability-free years than those with diabetes (p<0·0001 for all comparisons). INTERPRETATION: Irrespective of diabetes status, US adults saw a compression of disability and gains in disability-free life-years. The decrease in disability onset due to primary prevention of diabetes could play an important part in achieving longer disability-free life-years. FUNDING: US Department of Health & Human Services and the US Centers for Disease Control and Prevention.
Keywords: Activities of Daily Living; Aged; Diabetes Mellitus; Disabled Persons; Female; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Prospective Studies; United States

C-reactive protein level partially mediates the relationship between moderate alcohol use and frailty: the Health and Retirement Study. - Mona Shah; Daniel Paulson (Age Ageing, 2016)
BACKGROUND: frailty is an indicator of late-life decline marked by higher rates of disability and healthcare utilisation. Research has linked health benefits with moderate alcohol use, including frailty risk reduction. Past work suggests inflammation, measured by C-reactive protein (CRP), as one candidate mechanism for this effect. OBJECTIVE: this study aims to elucidate a possible mechanism - CRP modulation - by which moderate alcohol consumption may protect against frailty. METHODS: a cross-sectional study using data from the 2008 wave of the Health and Retirement Study (HRS) conducted by the University of Michigan. The HRS is a cohort study on health, retirement and aging on adults aged 50 and older living in the USA. A final sample of 3,229 stroke-free participants, over the age of 65 years and with complete data, was identified from the 2008 wave. Alcohol use was measured via self-report. Frailty was measured using the Paulson-Lichtenberg Frailty Index. CRP was collected through the HRS protocol. RESULTS: results from structural equation modelling support the hypothesised model that moderate alcohol use is associated with less frailty and lower CRP levels. Furthermore, the indirect relationship from moderate alcohol use to frailty through CRP was statistically significant. CONCLUSIONS: overall findings suggest that inflammation measured by CRP is one mechanism by which moderate alcohol use may confer protective effects for frailty. These findings inform future research relating alcohol use and frailty, and suggest inflammation as a possible mechanism in the relationship between moderate alcohol use and other beneficial health outcomes.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Alcohol Drinking; Biomarkers; C-reactive protein; Cross-Sectional Studies; Female; Frail Elderly; Frailty; Geriatric Assessment; Humans; Inflammation Mediators; Male; Protective factors; Risk Factors; United States

Depressed Mood in Middle-Aged and Older Adults in Europe and the United States: A Comparative Study Using Anchoring Vignettes. - Ramin Mojtabai (J Aging Health, 2016)
OBJECTIVE: To compare self-ratings of depressed mood in middle-aged and older adults in the United States and nine European countries after adjustment by anchoring vignettes. METHOD: Samples were drawn from three large surveys of middle-aged and older adults: the U.S. Health and Retirement Study, the English Longitudinal Study of Aging (ELSA), and the Survey of Health, Ageing and Retirement in Europe. Self-ratings of depressed mood were compared across countries before and after adjustment by anchoring vignettes depicting cases with different levels of depressed mood. RESULTS: Compared with Europeans as a group, Americans rated both the cases presented in the vignettes and themselves as more depressed. However, after adjustment by vignette ratings, Americans appeared to be less depressed than their counterparts in all but two European countries. DISCUSSION: Cultural differences in mental health norms reflected in vignette rating may partly explain between-country differences in self-reported depressive symptoms and perhaps other psychiatric complaints.
Keywords: Aged; Cross-Cultural Comparison; depression; Europe; Female; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; United States

The determinants of presenteeism: a comprehensive investigation of stress-related factors at work, health, and individual factors among the aging workforce. - Tianan Yang; Zhu, Mingjing; Xiyao Xie (J Occup Health, 2016)
OBJECTIVES: The aim of this study was to identify the determinants of presenteeism, taking health and individual factors into account. METHODS: A quantitative analysis applying structural equation modelling analysis was conducted on the basis of secondary data from the Health and Retirement Survey (2008 wave), which measured presenteeism and its determinants. RESULTS: Stress-related factors at work (β =-0.35, p<0.001), individual factors (α =-0.27, p<0.001), and health (β =0.24, p<0.001) were significantly related to presenteeism. Individual factors were found to be directly correlated with stress-related factors at work (β =0.22, p<0.001). Significant indirect effects between stress-related factors at work and presenteeism (Sobel z=-6.61; p<0.001) and between individual factors and presenteeism (Sobel z=-4.42; p<0.001), which were mediated by health, were also found. Overall, the final model accounted for 37% (R(2)=0.37) of the variance in presenteeism. CONCLUSIONS: Our study indicates some important and practical guidelines for employers to avoid the burdens of stress-related presenteeism among their employees. These findings could help select target factors in the design and implementation of effective presenteeism interventions in the aging working population.
Keywords: Age Factors; Aged; Aging; Female; Health Surveys; Humans; Male; Middle Aged; Occupational Diseases; Presenteeism; Stress, Psychological; United States; Workplace

Differences Among Older Adults in the Types of Dental Services Used in the United States. - Richard J. Manski; Jody Schimmel Hyde; Haiyan Chen; John F Moeller (Inquiry, 2016)
The purpose of this article is to explore differences in the socioeconomic, demographic characteristics of older adults in the United States with respect to their use of different types of dental care services. The 2008 Health and Retirement Study (HRS) collected information about patterns of dental care use and oral health from individuals aged 55 years and older in the United States. We analyze these data and explore patterns of service use by key characteristics before modeling the relationship between service use type and those characteristics. The most commonly used service category was fillings, inlays, or bonding, reported by 43.6% of those with any utilization. Just over one third of those with any utilization reported a visit for a crown, implant, or prosthesis, and one quarter reported a gum treatment or tooth extraction. The strongest consistent predictors of use type are denture, dentate, and oral health status along with dental insurance coverage and wealth. Our results provide insights into the need for public policies to address inequalities in access to dental services among an older US population. Our findings show that lower income, less wealthy elderly with poor oral health are more likely to not use any dental services rather than using only preventive dental care, and that cost prevents most non-users who say they need dental care from going to the dentist. These results suggest a serious access problem and one that ultimately produces even worse oral health and expensive major procedures for this population in the future.
Keywords: Aged; Dental Care; Female; Humans; Insurance, Dental; Male; Middle Aged; Surveys and Questionnaires; United States

Disparity in dental attendance among older adult populations: a comparative analysis across selected European countries and the USA. - Richard J. Manski; John F Moeller; Haiyan Chen; Widstrom, Eeva; Listl, Stefan (Int Dent J, 2016)
BACKGROUND: The current study addresses the extent to which diversity in dental attendance across population subgroups exists within and between the USA and selected European countries. METHOD: The analyses relied on 2006/2007 data from the Survey of Health, Ageing and Retirement in Europe (SHARE) and 2004-2006 data from the Health and Retirement Study (HRS) in the USA for respondents≥51 years of age. Logistic regression models were estimated to identify impacts of dental-care coverage, and of oral and general health status, on dental-care use. RESULTS: We were unable to discern significant differences in dental attendance across population subgroups in countries with and without social health insurance, between the USA and European countries, and between European countries classified according to social welfare regime. Patterns of diverse dental use were found, but they did not appear predominately in countries classified according to welfare state regime or according to the presence or absence of social health insurance. CONCLUSIONS: The findings of this study suggest that income and education have a stronger, and more persistent, correlation with dental use than the correlation between dental insurance and dental use across European countries. We conclude that: (i) higher overall rates of coverage in most European countries, compared with relatively lower rates in the USA, contribute to this finding; and that (ii) policies targeted to improving the income of older persons and their awareness of the importance of oral health care in both Europe and the USA can contribute to improving the use of dental services.
Keywords: Aged; Aged, 80 and over; Demography; Dental Care; Europe; Female; Humans; Insurance Coverage; Interviews as Topic; Male; Middle Aged; Oral Health; Patient Acceptance of Health Care; United States

Dispositional Optimism and Incidence of Cognitive Impairment in Older Adults. - Katerina A B Gawronski; Eric S Kim; Kenneth M. Langa; Laura D Kubzansky (Psychosom Med, 2016)
OBJECTIVE: Higher levels of optimism have been linked with positive health behaviors, biological processes, and health conditions that are potentially protective against cognitive impairment in older adults. However, the association between optimism and cognitive impairment has not been directly investigated. We examined whether optimism is associated with incident cognitive impairment in older adults. METHODS: Data are from the Health and Retirement Study. Optimism was measured by using the Life Orientation Test-R and cognitive impairment with a modified version of the Telephone Interview for Cognitive Status derived from the Mini-Mental State Examination. Using multiple logistic regression models, we prospectively assessed whether optimism was associated with incident cognitive impairment in 4624 adults 65 years and older during a 4-year period. RESULTS: Among participants, 312 women and 190 men developed cognitive impairment during the 4-year follow-up. Higher optimism was associated with decreased risk of incident cognitive impairment. When adjusted for sociodemographic factors, each standard deviation increase in optimism was associated with reduced odds (odds ratio [OR] = 0.70, 95% confidence interval [CI] = 0.61-0.81) of becoming cognitively impaired. A dose-response relationship was observed. Compared with those with the lowest levels of optimism, people with moderate levels had somewhat reduced odds of cognitive impairment (OR = 0.78, 95% CI = 0.59-1.03), whereas people with the highest levels had the lowest odds of cognitive impairment (OR = 0.52, 95% CI = 0.36-0.74). These associations remained after adjusting for health behaviors, biological factors, and psychological covariates that could either confound the association of interest or serve on the pathway. CONCLUSIONS: Optimism was prospectively associated with a reduced likelihood of becoming cognitively impaired. If these results are replicated, the data suggest that potentially modifiable aspects of positive psychological functioning such as optimism play an important role in maintaining cognitive functioning.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Female; Humans; Incidence; Male; Optimism; Protective factors; United States

Does the Relationship of the Proxy to the Target Person Affect the Concordance between Survey Reports and Medicare Claims Measures of Health Services Use? - George L Wehby; Michael P Jones; Fred A Ullrich; Yiyue Lou; Frederic D Wolinsky (Health Serv Res, 2016)
OBJECTIVES: To compare concordance of survey reports of health service use versus claims data between self respondents and spousal and nonspousal relative proxies. DATA SOURCES: 1995-2010 data from the Survey on Assets and Health Dynamics among the Oldest Old and 1993-2010 Medicare claims for 3,229 individuals (13,488 person-years). STUDY DESIGN: Regression models with individual fixed effects were estimated for discordance of any hospitalizations and outpatient surgery and for the numbers of under- and over-reported physician visits. PRINCIPAL FINDINGS: Spousal proxies were similar to self respondents on discordance. Nonspousal proxies, particularly daughters/daughters-in-law and sons/sons-in-law, had less discordance, mainly due to reduced under-reporting. CONCLUSIONS: Survey reports of health services use from nonspousal relatives are more consistent with Medicare claims than spousal proxies and self respondents.
Keywords: Ambulatory Surgical Procedures; Female; Hospitalization; Humans; Insurance Claim Review; Male; Medicare; Patient Acceptance of Health Care; Proxy; Self Report; Socioeconomic factors; Spouses; United States

Functional health decline before and after retirement: A longitudinal analysis of the Health and Retirement Study. - Sander K. R. van Zon; Bültmann, Ute; Reijneveld, Sijmen A; Carlos F. Mendes de Leon (Soc Sci Med, 2016)
OBJECTIVES: The aims of this study are to examine the pattern of pre- and post-retirement changes in functional health and to examine the degree to which socioeconomic position (SEP) modifies pre- and post-retirement changes in functional health. METHOD: This longitudinal study was conducted using data from the Health and Retirement Study from 1992 to 2012. Piecewise linear regression analyses with generalised estimating equations were used to calculate trajectories of limitations in mobility and large muscle functions before and after retirement spanning a time period of 16 years. Interaction terms of three indicators of SEP with time before and after retirement were examined to investigate the modifying effect of SEP on changes in functional health before and after retirement. RESULTS: Average levels of limitations in mobility and large muscle functions increased significantly in the years prior to retirement. This increase slowed down after retirement, most prominently for limitations in large muscle functions. Higher SEP was associated with a slower increase of functional limitations prior to retirement. After retirement, a less clear pattern was found as only wealth modified the increase of limitations in mobility functions. DISCUSSION: Prevention of functional decline in older working adults may be essential in achieving longer and healthier working lives. Such strategies may have to give special consideration to lower SEP adults, as they tend to experience functional health declines prior to retirement at a greater rate than higher SEP adults.
Keywords: Aged; Aging; Female; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Regression Analysis; Retirement; Social Class; United States

Functional status in older women diagnosed with pelvic organ prolapse. - Tatiana V D Sanses; Nicholas K Schiltz; Bruna M. Couri; Sangeeta T Mahajan; Holly E Richter; David F Warner; Jack M. Guralnik; Siran M Koroukian (Am J Obstet Gynecol, 2016)
BACKGROUND: Functional status plays an important role in the comprehensive characterization of older adults. Functional limitations are associated with an increased risk of adverse treatment outcomes, but there are limited data on the prevalence of functional limitations in older women with pelvic floor disorders. OBJECTIVE: The aim of the study was to describe the prevalence of functional limitations based on health status in older women with pelvic organ prolapse (POP). STUDY DESIGN: This pooled, cross-sectional study utilized data from the linked Health and Retirement Study and Medicare files from 1992 through 2008. The analysis included 890 women age ≥65 years with POP. We assessed self-reported functional status, categorized in strength, upper and lower body mobility, activities of daily living (ADL), and instrumental ADL (IADL) domains. Functional limitations were evaluated and stratified by respondents self-reported general health status. Descriptive statistics were used to compare categorical and continuous variables, and logistic regression was used to measure differences in the odds of functional limitation by increasing age. RESULTS: The prevalence of functional limitations was 76.2% in strength, 44.9% in upper and 65.8% in lower body mobility, 4.5% in ADL, and 13.6% in IADL. Limitations were more prevalent in women with poor or fair health status than in women with good health status, including 91.5% vs 69.9% in strength, 72.9% vs 33.5% in upper and 88.0% vs 56.8% in lower body mobility, 11.6% vs 0.9% in ADL, and 30.6% vs 6.7% in IADL; all P < .01. The odds of all functional limitations also increased significantly with advancing age. CONCLUSION: Functional limitations, especially in strength and body mobility domains, are highly prevalent in older women with POP, particularly in those with poor or fair self-reported health status. Future research is necessary to evaluate if functional status affects clinical outcomes in pelvic reconstructive and gynecologic surgery and whether it should be routinely assessed in clinical decision-making when treating older women with POP.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cross-Sectional Studies; Female; Health Status; Health Surveys; Humans; Medicare; Middle Aged; Mobility Limitation; Muscle Strength; Pelvic Organ Prolapse; United States; Upper Extremity

Functioning, Forgetting, or Failing Health: Which Factors Are Associated With a Community-Based Move Among Older Adults? - Esther M Friedman; Margaret M Weden; Regina A Shih; Stephanie Kovalchik; Singh, Reema; José J Escarce (J Gerontol B Psychol Sci Soc Sci, 2016)
OBJECTIVE: To examine whether the health and functioning of middle-aged and older adults are associated with an increased likelihood of community-based moves. METHOD: Biennial data from adults aged 51 and older in the Health and Retirement Study (HRS) and discrete-time survival models were used to assess the likelihood of community-based moves from 2000 to 2010 as a function of 11 measures of health and functioning. RESULTS: Respondents diagnosed with heart disease, stroke, hypertension, lung disease, and psychiatric problems were more likely to move during the study period than those with no such diagnosis. Changes in activities of daily living and instrumental activities of daily living functioning, cognitive impairment, and falls were also related to a greater likelihood of moving during the study period. Cancer and diabetes were not related to overall moves, although diabetes was associated with an increased likelihood of local moves. For the most part, it was longstanding not recent diagnoses that were significantly related to the likelihood of moving. DISCUSSION: Although some health conditions precipitate moves among middle-aged and older adults, others do not. This work has important implications for understanding the role of different aspects of health and functioning in the likelihood of migration among older adults.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; Female; Health Status; Health Surveys; Humans; Male; Middle Aged; Population Dynamics; Residence Characteristics; United States

A Genetic Network Associated With Stress Resistance, Longevity, and Cancer in Humans. - Morgan E. Levine; Eileen M. Crimmins (J Gerontol A Biol Sci Med Sci, 2016)
Human longevity and diseases are likely influenced by multiple interacting genes within a few biologically conserved pathways. Using long-lived smokers as a phenotype (n = 90)-a group whose survival may signify innate resilience-we conducted a genome-wide association study comparing them to smokers at ages 52-69 (n = 730). These results were used to conduct a functional interaction network and pathway analysis, to identify single nucleotide polymorphisms that collectively related to smokers' longevity. We identified a set of 215 single nucleotide polymorphisms (all of which had p <5×10(-3) in the genome-wide association study) that were located within genes making-up a functional interaction network. These single nucleotide polymorphisms were then used to create a weighted polygenic risk score that, using an independent validation sample of nonsmokers (N = 6,447), was found to be significantly associated with a 22% increase in the likelihood of being aged 90-99 (n = 253) and an over threefold increase in the likelihood of being a centenarian (n = 4), compared with being at ages 52-79 (n = 4,900). Additionally, the polygenic risk score was also associated with an 11% reduction in cancer prevalence over up to 18 years (odds ratio: 0.89, p = .011). Overall, using a unique phenotype and incorporating prior knowledge of biological networks, this study identified a set of single nucleotide polymorphisms that together appear to be important for human aging, stress resistance, cancer, and longevity.
Keywords: Aged; Aged, 80 and over; Aging; Alleles; Case-Control Studies; Gene Regulatory Networks; Genome-Wide Association Study; Genotype; Humans; Longevity; Longitudinal Studies; Middle Aged; Neoplasms; Phenotype; Polymorphism, Single Nucleotide; Smoking; Stress, Physiological; United States

Health Effects of Short-Term Fluctuations in Macroeconomic Conditions: The Case of Hypertension for Older Americans. - Marco Angrisani; Jinkook Lee (Health Econ, 2016)
We investigate the health effects of short-term macroeconomic fluctuations as described by changes in unemployment rate, house, and stock market price indexes. The 'Great Recession' provides the opportunity to conduct this analysis as it involved contemporaneous shocks to the labor, housing, and stock markets. Using panel data from the Health and Retirement Study over the period 2004-2010, we relate changes in hypertension status to changes in state-level unemployment rate and house prices and to changes in stock market prices. We consider hypertension, a disease related to stress and of high prevalence among older adults, that has received little attention in the literature linking macroeconomic conditions to individual health. Our analysis exploits self-reports of hypertension diagnosis as well as directly measured blood pressure readings. Using both measures, we find that the likelihood of developing hypertension is negatively related to changes in house prices. Also, decreasing house prices lower the probability of stopping hypertension medication treatment for individuals previously diagnosed with the condition. We do not observe significant associations between hypertension and either changes in unemployment rate or stock market prices. We document heterogeneity in the estimated health effects of the recession by gender, education, asset ownership, and work status. Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: Aged; Commerce; Economic Recession; Female; Health Status; Humans; Hypertension; Longitudinal Studies; Male; Middle Aged; Socioeconomic factors; Stress, Psychological; Surveys and Questionnaires; Unemployment; United States

Instrumental variable approaches to identifying the causal effect of educational attainment on dementia risk. - Thu T Nguyen; Eric J. Tchetgen Tchetgen; Ichiro Kawachi; Stephen E. Gilman; Stefan Walter; Sze Y Liu; Jennifer J Manly; M. Maria Glymour (Ann Epidemiol, 2016)
PURPOSE: Education is an established correlate of cognitive status in older adulthood, but whether expanding educational opportunities would improve cognitive functioning remains unclear given limitations of prior studies for causal inference. Therefore, we conducted instrumental variable (IV) analyses of the association between education and dementia risk, using for the first time in this area, genetic variants as instruments as well as state-level school policies. METHODS: IV analyses in the Health and Retirement Study cohort (1998-2010) used two sets of instruments: (1) a genetic risk score constructed from three single-nucleotide polymorphisms (SNPs; n = 7981); and (2) compulsory schooling laws (CSLs) and state school characteristics (term length, student teacher ratios, and expenditures; n = 10,955). RESULTS: Using the genetic risk score as an IV, there was a 1.1% reduction in dementia risk per year of schooling (95% confidence interval, -2.4 to 0.02). Leveraging compulsory schooling laws and state school characteristics as IVs, there was a substantially larger protective effect (-9.5%; 95% confidence interval, -14.8 to -4.2). Analyses evaluating the plausibility of the IV assumptions indicated estimates derived from analyses relying on CSLs provide the best estimates of the causal effect of education. CONCLUSIONS: IV analyses suggest education is protective against risk of dementia in older adulthood.
Keywords: Aged; Aged, 80 and over; Dementia; Education, Nonprofessional; Educational Status; Female; Genetic Predisposition to Disease; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; Polymorphism, Single Nucleotide; Protective factors; Risk Factors; Schools; United States

Job Strain as a Risk Factor for Incident Diabetes Mellitus in Middle and Older Age U.S. Workers. - Mutambudzi, Miriam; Javed, Zulqarnain (J Gerontol B Psychol Sci Soc Sci, 2016)
OBJECTIVES: The current study examined the relationship between the 4 quadrants of the job strain model and incident diabetes in U.S. working adults 50 years and older. METHODS: This study used longitudinal data from the 2006-2012 waves of the Health and Retirement Study (n = 1,396). Kaplan-Meier survival curves and Cox proportional hazard regression models were used to examine whether job strain significantly predicted diabetes incidence. RESULTS: Participants in high strain and passive jobs had significantly higher risk of diabetes relative to those in low strain jobs. In the univariate survival curves, significantly higher risk of diabetes was observed in men working in passive jobs. After adjustment for relevant covariates, participants in high strain (hazard ratio [HR] = 1.73, 95% confidence interval [CI] = 1.09-2.75) and passive (HR = 1.66, 95% CI = 1.01-2.73) jobs had a significantly increased risk of diabetes. Among adults 65 years and older, high strain and passive jobs were associated with an approximately fourfold increased risk of incident diabetes. DISCUSSION: High strain and passive occupations which represent low control over work are associated with increased risk of diabetes incidence among older workers. More research is required to better understand how psychosocial work factors impact health in aging workers. Further, research should continue to explore gender differences in effects of job strain on diabetes.
Keywords: Aged; Aging; Diabetes Mellitus; Female; Humans; Kaplan-Meier Estimate; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Stress, Psychological; United States; Work

Lagged Associations of Metropolitan Statistical Area- and State-Level Income Inequality with Cognitive Function: The Health and Retirement Study. - Kim, Daniel; Griffin, Beth Ann; Mohammed U Kabeto; José J Escarce; Kenneth M. Langa; Regina A Shih (PLoS One, 2016)
PURPOSE: Much variation in individual-level cognitive function in late life remains unexplained, with little exploration of area-level/contextual factors to date. Income inequality is a contextual factor that may plausibly influence cognitive function. METHODS: In a nationally-representative cohort of older Americans from the Health and Retirement Study, we examined state- and metropolitan statistical area (MSA)-level income inequality as predictors of individual-level cognitive function measured by the 27-point Telephone Interview for Cognitive Status (TICS-m) scale. We modeled latency periods of 8-20 years, and controlled for state-/metropolitan statistical area (MSA)-level and individual-level factors. RESULTS: Higher MSA-level income inequality predicted lower cognitive function 16-18 years later. Using a 16-year lag, living in a MSA in the highest income inequality quartile predicted a 0.9-point lower TICS-m score (β = -0.86; 95% CI = -1.41, -0.31), roughly equivalent to the magnitude associated with five years of aging. We observed no associations for state-level income inequality. The findings were robust to sensitivity analyses using propensity score methods. CONCLUSIONS: Among older Americans, MSA-level income inequality appears to influence cognitive function nearly two decades later. Policies reducing income inequality levels within cities may help address the growing burden of declining cognitive function among older populations within the United States.
Keywords: Cities; Cognition; Female; health; Humans; Income; Interviews as Topic; Linear Models; Male; Middle Aged; Multivariate Analysis; Residence Characteristics; Retirement; Socioeconomic factors; Statistics as Topic; Telephone; United States

Late mortality after sepsis: propensity matched cohort study. - Hallie C Prescott; Osterholzer, John J; Kenneth M. Langa; Angus, Derek C; Theodore J Iwashyna (BMJ, 2016)
OBJECTIVES:  To determine whether late mortality after sepsis is driven predominantly by pre-existing comorbid disease or is the result of sepsis itself. DEIGN:  Observational cohort study. SETTING:  US Health and Retirement Study. PARTICIPANTS:  960 patients aged ≥65 (1998-2010) with fee-for-service Medicare coverage who were admitted to hospital with sepsis. Patients were matched to 777 adults not currently in hospital, 788 patients admitted with non-sepsis infection, and 504 patients admitted with acute sterile inflammatory conditions. MAIN OUTCOME MEASURES:  Late (31 days to two years) mortality and odds of death at various intervals. RESULTS:  Sepsis was associated with a 22.1% (95% confidence interval 17.5% to 26.7%) absolute increase in late mortality relative to adults not in hospital, a 10.4% (5.4% to 15.4%) absolute increase relative to patients admitted with non-sepsis infection, and a 16.2% (10.2% to 22.2%) absolute increase relative to patients admitted with sterile inflammatory conditions (P<0.001 for each comparison). Mortality remained higher for at least two years relative to adults not in hospital. CONCLUSIONS:  More than one in five patients who survives sepsis has a late death not explained by health status before sepsis.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cause of Death; Female; Hospital Mortality; Hospitalization; Humans; Longitudinal Studies; Male; Medicare; Propensity Score; Prospective Studies; Sepsis; Time Factors; United States

Life Course Pathways to Racial Disparities in Cognitive Impairment among Older Americans. - Zhang, Zhenmei; Mark D Hayward; Yu, Yan-Liang (J Health Soc Behav, 2016)
Blacks are especially hard hit by cognitive impairment at older ages compared to whites. Here, we take advantage of the Health and Retirement Study (1998-2010) to assess how this racial divide in cognitive impairment is associated with the racial stratification of life course exposures and resources over a 12-year period among 8,946 non-Hispanic whites and blacks ages 65 and older in 1998. We find that blacks suffer from a higher risk of moderate/severe cognitive impairment at baseline and during the follow-up. Blacks are also more likely to report childhood adversity and to have grown up in the segregated South, and these early-life adversities put blacks at a significantly higher risk of cognitive impairment. Adulthood socioeconomic status is strongly associated with the risk of cognitive impairment, net of childhood conditions. However, racial disparities in cognitive impairment, though substantially reduced, are not eliminated when controlling for these life course factors.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; European Continental Ancestry Group; Female; Health Status Disparities; Humans; Male; Neuropsychological tests; Risk Factors; Severity of Illness Index; United States

Life Expectancy With and Without Pain in the U.S. Elderly Population. - Zachary Zimmer; Rubin, Sara (J Gerontol A Biol Sci Med Sci, 2016)
BACKGROUND: This study contributes to dialogue on quality versus quantity of life by examining years older persons can expect to live in various states of pain. METHODS: Data from seven waves of the Health and Retirement Study; N = 26,896; age 55+. Estimations using the Interpolative Markov Chain approach apply probability transitions to multistate life table functions. Two estimates are interpreted: (i) population-based, which provide population averages aggregated across baseline states and (ii) status-based, which provide independent estimates by baseline state. Age- and sex-specific years with no pain, milder nonlimiting, and severe or limiting pain are reported as is percent of life in states of pain. RESULTS: Females have higher life expectancy than males but similar expectations of pain-free life. Total life expectancy varies only slightly by baseline pain states but pain-free life expectancy varies greatly. For example, an 85-year-old female pain-free at baseline expects 7.04 more years, 5.28 being pain-free. An 85-year-old female with severe pain at baseline expects 6.42 years with only 2.66 pain-free. Percent of life with pain decreases by age for those pain-free at baseline and increases for those with pain at baseline. CONCLUSION: Pain is moderately associated with quantity of or total life but substantially and importantly associated with quality of or pain-free life.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Disabled Persons; Female; Health Status Indicators; Humans; Incidence; Life Expectancy; Life Tables; Male; Middle Aged; pain; Quality of Life; Risk Factors; Surveys and Questionnaires; United States

Lifespan adversity and later adulthood telomere length in the nationally representative US Health and Retirement Study. - Puterman, Eli; Gemmill, Alison; Karasek, Deborah; David R Weir; Nancy E Adler; Aric A Prather; Elissa S Epel (Proc Natl Acad Sci U S A, 2016)
Stress over the lifespan is thought to promote accelerated aging and early disease. Telomere length is a marker of cell aging that appears to be one mediator of this relationship. Telomere length is associated with early adversity and with chronic stressors in adulthood in many studies. Although cumulative lifespan adversity should have bigger impacts than single events, it is also possible that adversity in childhood has larger effects on later life health than adult stressors, as suggested by models of biological embedding in early life. No studies have examined the individual vs. cumulative effects of childhood and adulthood adversities on adult telomere length. Here, we examined the relationship between cumulative childhood and adulthood adversity, adding up a range of severe financial, traumatic, and social exposures, as well as comparing them to each other, in relation to salivary telomere length. We examined 4,598 men and women from the US Health and Retirement Study. Single adversities tended to have nonsignificant relations with telomere length. In adjusted models, lifetime cumulative adversity predicted 6% greater odds of shorter telomere length. This result was mainly due to childhood adversity. In adjusted models for cumulative childhood adversity, the occurrence of each additional childhood event predicted 11% increased odds of having short telomeres. This result appeared mainly because of social/traumatic exposures rather than financial exposures. This study suggests that the shadow of childhood adversity may reach far into later adulthood in part through cellular aging.
Keywords: Aged; Aged, 80 and over; Cellular Senescence; Female; Humans; Longevity; Male; Middle Aged; Multivariate Analysis; Odds Ratio; Public Health Surveillance; Risk Factors; Stress, Psychological; Telomere; Telomere Shortening; United States

The Long-Term Benefits of Increased Aspirin Use by At-Risk Americans Aged 50 and Older. - David B. Agus; Gaudette, Étienne; Dana P Goldman; Messali, Andrew (PLoS One, 2016)
BACKGROUND: The usefulness of aspirin to defend against cardiovascular disease in both primary and secondary settings is well recognized by the medical profession. Multiple studies also have found that daily aspirin significantly reduces cancer incidence and mortality. Despite these proven health benefits, aspirin use remains low among populations targeted by cardiovascular prevention guidelines. This article seeks to determine the long-term economic and population-health impact of broader use of aspirin by older Americans at higher risk for cardiovascular disease. METHODS AND FINDINGS: We employ the Future Elderly Model, a dynamic microsimulation that follows Americans aged 50 and older, to project their lifetime health and spending under the status quo and in various scenarios of expanded aspirin use. The model is based primarily on data from the Health and Retirement Study, a large, representative, national survey that has been ongoing for more than two decades. Outcomes are chosen to provide a broad perspective of the individual and societal impacts of the interventions and include: heart disease, stroke, cancer, life expectancy, quality-adjusted life expectancy, disability-free life expectancy, and medical costs. Eligibility for increased aspirin use in simulations is based on the 2011-2012 questionnaire on preventive aspirin use of the National Health and Nutrition Examination Survey. These data reveal a large unmet need for daily aspirin, with over 40% of men and 10% of women aged 50 to 79 presenting high cardiovascular risk but not taking aspirin. We estimate that increased use by high-risk older Americans would improve national life expectancy at age 50 by 0.28 years (95% CI 0.08-0.50) and would add 900,000 people (95% CI 300,000-1,400,000) to the American population by 2036. After valuing the quality-adjusted life-years appropriately, Americans could expect $692 billion (95% CI 345-975) in net health benefits over that period. CONCLUSIONS: Expanded use of aspirin by older Americans with elevated risk of cardiovascular disease could generate substantial population health benefits over the next twenty years and do so very cost-effectively.
Keywords: Aged; Aged, 80 and over; Anti-Inflammatory Agents, Non-Steroidal; Aspirin; Cardiovascular Diseases; Female; Humans; Incidence; Life Expectancy; Male; Middle Aged; Nutrition Surveys; Primary Prevention; Quality-Adjusted Life Years; Risk Assessment; United States

Marital history and survival after a heart attack. - Matthew E Dupre; Nelson, Alicia (Soc Sci Med, 2016)
Heart disease is the leading cause of death in the United States and nearly one million Americans will have a heart attack this year. Although the risks associated with a heart attack are well established, we know surprisingly little about how marital factors contribute to survival in adults afflicted with heart disease. This study uses a life course perspective and longitudinal data from the Health and Retirement Study to examine how various dimensions of marital life influence survival in U.S. older adults who suffered a heart attack (n = 2197). We found that adults who were never married (odds ratio [OR] = 1.73), currently divorced (OR = 1.70), or widowed (OR = 1.34) were at significantly greater risk of dying after a heart attack than adults who were continuously married; and the risks were not uniform over time. We also found that the risk of dying increased by 12% for every additional marital loss and decreased by 7% for every one-tenth increase in the proportion of years married. After accounting for more than a dozen socioeconomic, psychosocial, behavioral, and physiological factors, we found that current marital status remained the most robust indicator of survival following a heart attack. The implications of the findings are discussed in the context of life course inequalities in chronic disease and directions for future research.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Divorce; Female; Humans; Male; Marital Status; Myocardial Infarction; Prospective Studies; Retrospective Studies; Single Person; Spouses; Survivors; United States; Widowhood

Methodological Aspects of Subjective Life Expectancy: Effects of Culture-Specific Reporting Heterogeneity Among Older Adults in the United States. - Lee, Sunghee; Jacqui Smith (The Journals of Gerontology: Series B, 2016)
OBJECTIVES: Subjective life expectancy (SLE) has been suggested as a predictor of mortality and mortality-related behaviors. Although critical for culturally diverse societies, these findings do not consider cross-cultural methodological comparability. Culture-specific reporting heterogeneity is a well-known phenomenon introducing biases, and research on this issue with SLE is not established. METHOD: Using data from the Health and Retirement Study, we examined reporting heterogeneity in SLE focusing on item nonresponse, focal points, and reports over time for five ethnic-cultural groups: non-Hispanic Whites, non-Hispanic Blacks, non-Hispanic other races, English-interviewed Hispanics, and Spanish-interviewed Hispanics. RESULTS: On item nonresponse, Spanish-interviewed Hispanics said, "I don't know," to SLE significantly more than any other groups. Nearly half of the respondents chose 0, 50, or 100, making them focal points. However, the focal points differed: 50 for Whites, 100 for Blacks, and 0 for Spanish-interviewed Hispanics. The relationship of SLE measured at two time points was higher for Whites than minorities. Moreover, those who said "I don't know" to SLE showed higher subsequent mortality than those who gave an answer. SLE was not a significant mortality predictor for Hispanics. DISCUSSION: Overall, SLE is not free from culture-specific reporting heterogeneity. This warrants further research about its culture-relevant measurement mechanisms.
Keywords: Aged; Aged, 80 and over; Bias; Cross-Cultural Comparison; Cross-Sectional Studies; Diagnostic Self Evaluation; Ethnic Groups; Female; Frail Elderly; Humans; Language; Life Expectancy; Longitudinal Studies; Male; Middle Aged; Self Report; United States

Multimorbidity is associated with anxiety in older adults in the Health and Retirement Study. - Christine E Gould; Ruth O'Hara; Mary K. Goldstein; Sherry A. Beaudreau (Int J Geriatr Psychiatry, 2016)
OBJECTIVES: The present study determined whether the number of medical conditions was associated with increased occurrence of anxiety and whether triads of medical conditions were associated with anxiety in a nationally representative sample of older Americans. We determined whether multimorbidity findings were unique to anxiety as compared with depressive symptoms. METHODS: A sample of 4219 participants (65 years or older) completed anxiety and depression measures in the Health and Retirement Study 2006 wave. The logistic regression models' outcome was elevated anxiety (≥12 on five-item Beck Anxiety Inventory) or depressive symptoms (≥12 on eight-item Center for Epidemiological Studies Depression Scale). The predictor variable was a tally of seven self-report of doctor-diagnosed conditions: arthritis, cancer, diabetes, heart conditions, high blood pressure, lung disease, and stroke. Analyses were adjusted for age, gender, and depressive or anxiety symptoms. Associations among elevated anxiety or depressive symptoms and 35 triads of medical conditions were examined using Bonferroni corrected chi-square analyses. RESULTS: Three or more medical conditions conferred a 2.30-fold increase in elevated anxiety (95% confidence interval: 1.44-4.01). Twenty triads were associated with elevated anxiety as compared with 13 associated with depressive symptoms. Six of seven medical conditions, with the exception being stroke, were present in the majority of triads. CONCLUSION: Number of medical conditions and specific conditions are associated with increased occurrence of elevated anxiety. Compared with elevated depressive symptoms, anxiety is associated with greater multimorbidity. As anxiety and depression cause significant morbidity, it may be beneficial to consider these mental health symptoms when evaluating older adults with multimorbidity. Published 2016. This article is a U.S. Government work and is in the public domain in the USA.
Keywords: Aged; Aged, 80 and over; Anxiety Disorders; Chronic disease; Depressive Disorder; Female; Humans; Logistic Models; Male; multimorbidity; Retirement; United States

Neuroimaging overuse is more common in Medicare compared with the VA. - James F. Burke; Eve A Kerr; Ryan J McCammon; Holleman, Rob; Kenneth M. Langa; Brian C. Callaghan (Neurology, 2016)
OBJECTIVE: To inform initiatives to reduce overuse, we compared neuroimaging appropriateness in a large Medicare cohort with a Department of Veterans Affairs (VA) cohort. METHODS: Separate retrospective cohorts were established in Medicare and in VA for headache and neuropathy from 2004 to 2011. The Medicare cohorts included all patients enrolled in the Health and Retirement Study (HRS) with linked Medicare claims (HRS-Medicare; n = 1,244 for headache and 998 for neuropathy). The VA cohorts included all patients receiving services in the VA (n = 93,755 for headache and 183,642 for neuropathy). Inclusion criteria were age over 65 years and an outpatient visit for incident neuropathy or a primary headache. Neuroimaging use was measured with Current Procedural Terminology codes and potential overuse was defined using published criteria for use with administrative data. Increasingly specific appropriateness criteria excluded nontarget conditions for which neuroimaging may be appropriate. RESULTS: For both peripheral neuropathy and headache, potentially inappropriate imaging was more common in HRS-Medicare compared with the VA. Forty-nine percentage of all headache patients received neuroimaging in HRS-Medicare compared with 22.1% in the VA (p < 0.001) and differences persist when analyzing more specific definitions of overuse. A total of 23.7% of all HRS-Medicare incident neuropathy patients received neuroimaging compared with 9.0% in the VA (p < 0.001), and the difference persisted after excluding nontarget conditions. CONCLUSIONS: Overuse of neuroimaging is likely less common in the VA than in a Medicare population. Better understanding the reasons for the more selective use of neuroimaging in the VA could help inform future initiatives to reduce overuse of diagnostic testing.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Female; Headache Disorders, Primary; Humans; Male; Medicare; Neuroimaging; Peripheral Nervous System Diseases; United States; United States Department of Veterans Affairs; Unnecessary Procedures

One-Year Mortality After Hip Fracture: Development and Validation of a Prognostic Index. - Irena Cenzer; Victoria L. Tang; W John Boscardin; Christine S Ritchie; Margaret Wallhagen; Espaldon, Roxanne; Kenneth E Covinsky (J Am Geriatr Soc, 2016)
OBJECTIVES: To develop a prediction index for 1-year mortality after hip fracture in older adults that includes predictors from a wide range of domains. DESIGN: Retrospective cohort study. SETTINGS: Health and Retirement Study (HRS). PARTICIPANTS: HRS participants who experienced hip fracture between 1992 and 2010 as identified according to Medicare claims data (N = 857). MEASUREMENTS: Outcome measure was death within 1 year of hip fracture. Predictor measures were participant demographic characteristics, socioeconomic status, social support, health, geriatric symptoms, and function. Variables independently associated with 1-year mortality were identified, and best-subsets regression was used to identify the final model. The selected variables were weighted to create a risk index. The index was internally validated using bootstrapping to estimate model optimism. RESULTS: Mean age at time of hip fracture was 84, and 76% of the participants were women. There were 235 deaths (27%) during the 1-year follow up. Five predictors of mortality were included in the final model: aged 90 and older (2 points), male sex (2 points), congestive heart failure (2 points), difficulty preparing meals (2 points), and not being able to drive (1 point). The point scores of the index were associated with 1-year mortality, with 0 points predicting 10% risk and 7 to 9 points predicting 66% risk. The c-statistic for the final model was 0.73, with an estimated optimism penalty of 0.01, indicating very little evidence of overfitting. CONCLUSION: The prognostic index combines demographic, comorbidity, and function variables and can be used to differentiate between individuals at low and high risk of 1-year mortality after hip fracture.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cause of Death; Cohort Studies; Comorbidity; Disability Evaluation; Female; Hip Fractures; Humans; Incidence; Longitudinal Studies; Male; Prognosis; Retrospective Studies; Risk Assessment; Survival Analysis; United States

Physical and/or Cognitive Impairment, Out-of-Pocket Spending, and Medicaid Entry among Older Adults. - Willink, Amber; Davis, Karen; Schoen, Cathy; Jennifer L. Wolff (J Urban Health, 2016)
While Medicare provides health insurance coverage for those over 65 years of age, many still are underinsured, experiencing substantial out-of-pocket costs for covered and non-covered services as a proportion of their income. Using the Health and Retirement Study (HRS), this study found that being underinsured is a significant predictor of entering into Medicaid coverage over a 16-year period. The rate of entering Medicaid was almost twice as high for those who were underinsured and with physical and/or cognitive impairment than those who were not, while supplemental health insurance reduced the rate of entering Medicaid by 30 %. Providing more comprehensive coverage through the traditional Medicare program, including a ceiling on out-of-pocket expenditures or targeted support for those with physical or cognitive impairment, could postpone becoming covered by Medicaid and yield savings in Medicaid.
Keywords: Aged; Cognitive Dysfunction; Delivery of Health Care; Disabled Persons; Eligibility Determination; Female; Financing, Personal; Humans; Insurance Coverage; Insurance, Health; Male; Medicaid; Middle Aged; United States

A pilot study among older adults of the concordance between their self-reports to a health survey and spousal proxy reports on their behalf. - Frederic D Wolinsky; Ayres, Lioness; Michael P Jones; Yiyue Lou; George L Wehby; Fred A Ullrich (BMC Health Serv Res, 2016)
BACKGROUND: Proxy respondents are frequently used in health surveys, and the proxy is most often the spouse. Longstanding concerns linger, however, about the validity of using spousal proxies, especially for older adults. The purpose of this pilot study was to evaluate the concordance between self-reports and spousal proxy reports to a standard health survey in a small convenience sample of older married couples. METHODS: We used the Seniors Together in Aging Research (STAR) volunteer registry at the University of Iowa to identify and consent a cross-sectional, convenience sample of 28 married husband and wife couples. Private, personal interviews with each member of the married couple using a detailed health survey based on the 2012 Health and Retirement Study (HRS) instrument were conducted using computer assisted personal interviewing software. Within couples, each wife completed the health survey first for herself and then for her husband, and each husband completed the health survey first for himself and then for his wife. The health survey topics included health ratings, health conditions, mobility, instrumental activities of daily living (IADLs), health services use, and preventative services. Percent of agreement and prevalence and bias adjusted kappa statistics (PABAKs) were used to evaluate concordance. RESULTS: PABAK coefficients indicated moderate to excellent concordance (PABAKs >0.60) for most of the IADL, health condition, hospitalization, surgery, preventative service, and mobility questions, but only slight to fair concordance (PABAKs = -0.21 to 0.60) for health ratings, and physician and dental visits. CONCLUSIONS: These results do not allay longstanding concerns about the validity of routinely using spousal proxies in health surveys to obtain health ratings or the number of physician and dental visits among older adults. Further research is needed in a nationally representative sample of older couples in which each wife completes the health survey first for herself and then for her husband, each husband completes the health survey first for himself and then for his wife, and both spouses' Medicare claims are linked to their health survey responses to determine not just the concordance between spousal reports, but the concordance of those survey responses to the medical record.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Epidemiologic Methods; Female; Health Status; Hospitalization; Humans; Iowa; Male; Medicare; Middle Aged; Patient Acceptance of Health Care; Physicians; Proxy; Spouses; United States

Predictors of bone mineral density testing among older women on Medicare. - Yiyue Lou; Edmonds, S. W.; Michael P Jones; Fred A Ullrich; George L Wehby; Cram, P.; Frederic D Wolinsky (Osteoporos Int, 2016)
Although dual-energy X-ray absorptiometry (DXA) is recommended for all women ≥65 and is covered by Medicare, 40 % of women on Medicare report never having had a DXA. In a longitudinal cohort of 3492 women followed for two decades, we identified several risk factors that should be targeted to improve DXA testing rates. INTRODUCTION: DXA is used to measure bone mineral density, screen for osteoporosis, and assess fracture risk. DXA is recommended for all women ≥65 years old. Although Medicare covers DXA every 24 months for women, about 40 % report never having had a DXA test, and little is known from prospective cohort studies about which subgroups of women have low use rates and should be targeted for interventions. Our objective was to identify predictors of DXA use in a nationally representative cohort of women on Medicare. METHODS: We used baseline and biennial follow-up survey data (1993-2012) for 3492 women ≥70 years old from the nationally representative closed cohort known as the Survey on Assets and Health Dynamics among the Oldest Old (AHEAD). The survey data for these women were then linked to their Medicare claims (1991-2012), yielding 17,345 person years of observation. DXA tests were identified from the Medicare claims, and Cox proportional hazard regression models were used with both fixed and time-dependent predictors from the survey interviews including demographic characteristics, socioeconomic factors, health status, health habits, and the living environment. RESULTS: DXA use was positively associated with being Hispanic American, better cognition, higher income, having arthritis, using other preventative services, and living in Florida or other southern states. DXA use was negatively associated with age, being African-American, being overweight or obese, having mobility limitations, and smoking. CONCLUSIONS: Interventions to increase DXA use should target the characteristics that were observed here to be negatively associated with such screening.
Keywords: Absorptiometry, Photon; Aged; Bone density; Delivery of Health Care; Female; Humans; Medicare; Osteoporosis; Prospective Studies; United States

Prescription drug coverage and chronic pain. - Padmaja Ayyagari (Int J Health Econ Manag, 2016)
Chronic pain is one of the most common chronic conditions affecting more than 50 % of older adults. While pain management can be quite complex, prescription drugs are the most commonly used treatment modality. In this study, I examine whether increased access to prescription drugs due to the introduction of the Medicare Part D program in 2006 led to better management of pain among the elderly. While prior work has identified increases in the utilization of analgesics due to the introduction of Medicare Part D, the extent to which this increase in drug use actually improved the well-being of older adults is not known. Using data from the Health and Retirement Study, I employ a difference-in-differences strategy that compares pre versus post 2006 changes in pain related outcomes between Medicare eligible persons and a younger ineligible group. I find that Medicare Part D significantly reduced pain related activity limitations among a sample of older adults who report being troubled by pain.
Keywords: Analgesics; Chronic pain; Humans; Insurance Coverage; Medicare Part D; prescription drugs; Retirement; United States

Prevalence and Outcomes of Breathlessness in Older Adults: A National Population Study. - David C. Currow; Amy P Abernethy; Miriam J Johnson; Yinghui Miao; W John Boscardin; Christine S Ritchie (J Am Geriatr Soc, 2016)
OBJECTIVES: To determine the prevalence and outcomes of breathlessness in older Americans. SETTING: Community-dwelling older adults. PARTICIPANTS: Individuals aged 70 and older in the nationally representative Health and Retirement Study (2008, follow-up through 2012) (N = 3,671; mean age 78). MEASUREMENTS: Breathlessness was assessed by asking the question, "How often do you become short of breath while awake?" Responses of often or sometimes were considered to represent a level of breathlessness sufficient to warrant clinical attention. The prevalence of breathlessness is described overall and in subpopulations, then rates of associated symptoms, well-being, and health services use of participants who were breathless are compared with rates of those who were not. The risk of decline in activities of daily living (ADLs) and death through 2012 was estimated by creating a multivariable Cox proportional hazards model, adjusting for age, sex, race and ethnicity, and education. RESULTS: Twenty-five percent of participants reported breathlessness. The prevalence of breathlessness was higher in certain subpopulations: chronic lung disease (63%), multimorbidity (≥2 chronic conditions) (45%), current smokers (38%), heart disease (36%), obesity (body mass index ≥30.0 kg/m ) (33%), and education less than high school (32%). Breathlessness was associated with higher rates of depression, anxiety, and severe fatigue; lower ratings of well-being; and higher rates of clinic and emergency department visits and hospitalizations (all P < .001). Breathlessness predicted ADL decline over 5 years (adjusted hazard ratio (aHR) = 1.43, 95% confidence interval (CI) = 1.22-1.68) and death (aHR 1.62, 95% CI = 1.32-2.02). CONCLUSION: One in four adults aged 70 and older in the United States experiences breathlessness, which is associated with lack of well-being, greater health services use, and a 40% greater risk of worsened function and 60% greater risk of death over the next 5 years.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Anxiety; Chronic disease; Comorbidity; depression; Dyspnea; Female; Geriatric Assessment; Hospitalization; Humans; Male; Prevalence; Proportional Hazards Models; Risk Assessment; Risk Factors; Symptom Assessment; United States

Prevalence of weakness and its relationship with limitations based on the Foundations for the National Institutes for Health project: data from the Health and Retirement Study. - John A. Batsis; Cassandra M Germain; Elizabeth Vasquez; Bartels, S. J. (Eur J Clin Nutr, 2016)
BACKGROUND/OBJECTIVES: The objectives of this study were to determine the prevalence of muscle weakness using the two 2014 Foundation for the National Institutes of Health (FNIH) Sarcopenia Project criteria and its relationship with physical limitations, basic activities of daily living (ADL) and instrumental ADL. SUBJECTS/METHODS: We performed a cross-sectional analysis of community-dwelling adults from the Health and Retirement Study 2006-2008 and identified a subsample of 5092 adults aged ⩾60 years with grip strength (GS) data. Self-reported physical limitations, basic ADL and instrumental ADL were assessed. Criteria for GS (men<26 kg; women <16 kg) and GS adjusted for body mass index (GS/BMI; men <1.0; women <0.56) were applied to the sample. We determined the prevalence of muscle weakness in each sex. Multivariable logistic regression was used to calculate the association of physical limitations, basic ADL and instrument ADL with weakness definitions in each sex. RESULTS: Mean age was 72.1 years (54.9% female). Mean GS was 38.3 and 22.9 kg and mean BMI was 29 kg/m, respectively, in men and women. Weakness prevalence using GS and GS:BMI definitions were 7.8 and 15.2 (P<0.001), respectively, in men and 11.4 and 13.3% (P=0.04) in women. Overall prevalence of physical limitations, basic ADL limitations and instrumental ADL limitations was 52.9, 28.1 and 35.9%, respectively. In those with weakness, prevalence of physical limitations, basic ADL and instrumental ADL was 78.5, 42.3 and 65.3%, respectively, using the GS definition, and 79.7, 40.7 and 58.8%, respectively, using the GS/BMI definition. GS and the GS/BMI definitions of weakness were strongly associated with physical limitations (odds ratio (OR) 2.19 (95% confidence interval (CI): (1.67-2.87)) and 2.52 (2.01-3.17)), basic ADL (OR 1.59 (1.22-2.07) and 1.66 (1.32-2.07)) and instrumental ADLs (OR 1.98 (1.28-2.54) and 1.78 (1.44-2.20)). CONCLUSIONS: The new FNIH guidelines for weakness are associated with higher prevalence of physical limitations, basic ADL impairments and instrumental ADL impairments as compared with individuals without weakness.
Keywords: Activities of Daily Living; Aged; Aging; Cross-Sectional Studies; Databases, Factual; Female; Humans; Male; Middle Aged; Muscle Weakness; National Institutes of Health (U.S.); Retirement; sarcopenia; Surveys and Questionnaires; United States

The Protective Effects of Religiosity on Depression: A 2-Year Prospective Study. - Corina R Ronneberg; Edward Alan Miller; Dugan, Elizabeth; Frank Porell (Gerontologist, 2016)
PURPOSE OF THE STUDY: Approximately 20% of older adults are diagnosed with depression in the United States. Extant research suggests that engagement in religious activity, or religiosity, may serve as a protective factor against depression. This prospective study examines whether religiosity protects against depression and/or aids in recovery. DESIGN AND METHODS: Study data are drawn from the 2006 and 2008 waves of the Health and Retirement Study. The sample consists of 1,992 depressed and 5,740 nondepressed older adults (mean age = 68.12 years), at baseline (2006), for an overall sample size of 7,732. Logistic regressions analyzed the relationship between organizational (service attendance), nonorganizational (private prayer), and intrinsic measures of religiosity and depression onset (in the baseline nondepressed group) and depression recovery (in the baseline depressed group) at follow-up (2008), controlling for other baseline factors. RESULTS: Religiosity was found to both protect against and help individuals recover from depression. Individuals not depressed at baseline remained nondepressed 2 years later if they frequently attended religious services, whereas those depressed at baseline were less likely to be depressed at follow-up if they more frequently engaged in private prayer. IMPLICATIONS: Findings suggest that both organizational and nonorganizational forms of religiosity affect depression outcomes in different circumstances (i.e., onset and recovery, respectively). Important strategies to prevent and relieve depression among older adults may include improving access and transportation to places of worship among those interested in attending services and facilitating discussions about religious activities and beliefs with clinicians.
Keywords: Adult; Aged; Aging; depression; Depressive Disorder; Female; Health Surveys; Humans; Male; Middle Aged; Prospective Studies; Religion; Religion and Psychology; Social Support; Spirituality; United States

Racial and ethnic differences in cognitive function among older adults in the USA. - Díaz-Venegas, Carlos; Brian Downer; Kenneth M. Langa; Rebeca Wong (International Journal of Geriatric Psychiatry, 2016)
OBJECTIVE: Examine differences in cognition between Hispanic, non-Hispanic black (NHB), and non-Hispanic white (NHW) older adults in the United States. DATA/METHODS: The final sample includes 18 982 participants aged 51 or older who received a modified version of the Telephone Interview for Cognitive Status during the 2010 Health and Retirement Study follow-up. Ordinary least squares will be used to examine differences in overall cognition according to race/ethnicity. RESULTS: Hispanics and NHB had lower cognition than NHW for all age groups (51-59, 60-69, 70-79, 80+). Hispanics had higher cognition than NHB for all age groups but these differences were all within one point. The lower cognition among NHB compared to NHW remained significant after controlling for age, gender, and education, whereas the differences in cognition between Hispanics and NHW were no longer significant after controlling for these covariates. Cognitive scores increased with greater educational attainment for all race/ethnic groups, but Hispanics exhibited the least benefit. DISCUSSION: Our results highlight the role of education in race/ethnic differences in cognitive function during old age. Education seems beneficial for cognition in old age for all race/ethnic groups, but Hispanics appear to receive a lower benefit compared to other race/ethnic groups. Further research is needed on the racial and ethnic differences in the pathways of the benefits of educational attainment for late-life cognitive function. Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: African Americans; Aged; Aged, 80 and over; Cognition; Ethnic Groups; European Continental Ancestry Group; Female; Hispanic Americans; Humans; Male; Middle Aged; United States

Racial and Ethnic Differences in End-of-Life Medicare Expenditures. - Byhoff, Elena; Tamara B Harris; Kenneth M. Langa; Theodore J Iwashyna (Journal of the American Geriatrics Society, 2016)
OBJECTIVES: To determine to what extent demographic, social support, socioeconomic, geographic, medical, and End-of-Life (EOL) planning factors explain racial and ethnic variation in Medicare spending during the last 6 months of life. DESIGN: Retrospective cohort study. SETTING: Health and Retirement Study (HRS). PARTICIPANTS: Decedents who participated in HRS between 1998 and 2012 and previously consented to survey linkage with Medicare claims (N = 7,105). MEASUREMENTS: Total Medicare expenditures in the last 180 days of life according to race and ethnicity, controlling for demographic factors, social supports, geography, illness burden, and EOL planning factors, including presence of advance directives, discussion of EOL treatment preferences, and whether death had been expected. RESULTS: The analysis included 5,548 (78.1%) non-Hispanic white, 1,030 (14.5%) non-Hispanic black, and 331 (4.7%) Hispanic adults and 196 (2.8%) adults of other race or ethnicity. Unadjusted results suggest that average EOL Medicare expenditures were $13,522 (35%, P < .001) more for black decedents and $16,341 (42%, P < .001) more for Hispanics than for whites. Controlling for demographic, socioeconomic, geographic, medical, and EOL-specific factors, the Medicare expenditure difference between groups fell to $8,047 (22%, P < .001) more for black and $6,855 (19%, P < .001) more for Hispanic decedents than expenditures for non-Hispanic whites. The expenditure differences between groups remained statistically significant in all models. CONCLUSION: Individuals-level factors, including EOL planning factors do not fully explain racial and ethnic differences in Medicare spending in the last 6 months of life. Future research should focus on broader systemic, organizational, and provider-level factors to explain these differences.
Keywords: African Continental Ancestry Group; Aged; Aged, 80 and over; Cohort Studies; Comorbidity; Cross-Cultural Comparison; Ethnic Groups; European Continental Ancestry Group; Female; Health Care Surveys; Health Expenditures; Hispanic Americans; Humans; Life Support Care; Longitudinal Studies; Male; Medicare; Rate Setting and Review; Social Support; Socioeconomic factors; Terminal Care; United States

Racial and Socioeconomic Variation in Genetic Markers of Telomere Length: A Cross-Sectional Study of U.S. Older Adults. - Hamad, Rita; Tuljapurkar, Shripad; David Rehkopf (EBioMedicine, 2016)
BACKGROUND: Shorter telomere length (TL) has been associated with stress and adverse socioeconomic conditions, yet U.S. blacks have longer TL than whites. The role of genetic versus environmental factors in explaining TL by race and socioeconomic position (SEP) remains unclear. METHODS: We used data from the U.S. Health and Retirement Study (N=11,934) to test the hypothesis that there are differences in TL-associated SNPs by race and SEP. We constructed a TL polygenic risk score (PRS) and examined its association with race/ethnicity, educational attainment, assets, gender, and age. RESULTS: U.S. blacks were more likely to have a lower PRS for TL, as were older individuals and men. Racial differences in TL were statistically accounted for when controlling for population structure using genetic principal components. The GWAS-derived SNPs for TL, however, may not have consistent associations with TL across different racial/ethnic groups. CONCLUSIONS: This study showed that associations of race/ethnicity with TL differed when accounting for population stratification. The role of race/ethnicity for TL remains uncertain, however, as the genetic determinants of TL may differ by race/ethnicity. Future GWAS samples should include racially diverse participants to allow for better characterization of the determinants of TL in human populations.
Keywords: Age Factors; Aged; Aged, 80 and over; Alleles; Cross-Sectional Studies; Ethnic Groups; Female; Gene Frequency; Genetic Markers; Genome-Wide Association Study; Geriatric Assessment; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Population Surveillance; Socioeconomic factors; Telomere Homeostasis; United States

The relationship between childhood poverty, military service, and later life depression among men: Evidence from the Health and Retirement Study. - Bareis, Natalie; Briana Mezuk (J Affect Disord, 2016)
BACKGROUND: Childhood poverty has been associated with depression in adulthood, but whether this relationship extends to later life major depression (MD) or is modified by military service is unclear. METHODS: Data come from the Health and Retirement Study (HRS) 2010 wave, a longitudinal, nationally representative study of older adults. Men with data on military service and childhood poverty were included (N=6330). Childhood poverty was assessed by four indicators (i.e., parental unemployment, residential instability) experienced before age 16. Military service was categorized as veteran versus civilian, and during draft versus all-volunteer (after 1973) eras. Past year MD was defined by the Composite International Diagnostic Inventory. RESULTS: Four in ten men ever served, with 13.7% in the all-volunteer military. Approximately 12% of civilians, 8% draft era and 24% all-volunteer era veterans had MD. Childhood poverty was associated with higher odds of MD (Odds Ratio (OR): 2.38, 95% Confidence Interval (CI): 1.32-4.32) and higher odds of military service (OR: 2.58, 95% CI: 1.58-4.21). Military service was marginally associated with MD (OR: 1.28, 95% CI: 0.98-1.68) and did not moderate the association between childhood poverty and MD. LIMITATIONS: Self-report data is subject to recall bias. The HRS did not assess childhood physical and emotional abuse, or military combat exposure. CONCLUSIONS: Men raised in poverty had greater odds of draft and all-volunteer military service. Early-life experiences, independent of military service, appear associated with greater odds of MD. Assessing childhood poverty in service members may identify risk for depression in later life.
Keywords: Adult Survivors of Child Adverse Events; Aged; Depressive Disorder, Major; Female; Health Surveys; Humans; Life Change Events; Male; Middle Aged; Military Personnel; Odds Ratio; Poverty; Self Report; United States; Veterans

Relationship between marijuana and other illicit drug use and depression/suicidal thoughts among late middle-aged and older adults. - Namkee G Choi; DiNitto, Diana M; Marti, C Nathan; Bryan Y Choi (Int Psychogeriatr, 2016)
BACKGROUND: Despite growing numbers of older-adult illicit drug users, research on this topic is rare. This study examined the relationship between marijuana and/or other illicit drug use and major depressive episode (MDE) and serious suicidal thoughts among those aged 50+ years in the USA. METHODS: The public use files of the 2008 to 2012 US National Survey on Drug Use and Health (NSDUH) provided data on 29,634 individuals aged 50+ years. Logistic regression analysis was used to test hypothesized associations between past-year marijuana and/or other illicit drug use and MDE and serious suicidal thoughts. RESULTS: Nearly 6% of the 50+ years age group reported past-year marijuana and/or other illicit drug use. Compared to non-users of any illicit drug, the odds of past-year MDE among those who used marijuana only, other illicit drugs only, and marijuana and other illicit drugs were 1.54 (95% CI = 1.17-2.03), 2.75 (95% CI = 1.75-4.33), and 2.12 (95% CI = 1.45-3.09), respectively. Those who used marijuana and other drugs also had higher odds (2.44, 95% CI = 1.58-3.77) of suicidal thoughts than non-users of any illicit drug. However, among users of any illicit drug, no difference was found among users of marijuana only, marijuana and other illicit drugs, and other illicit drugs only. Among marijuana users, marijuana use frequency was a significant correlate of suicidal thoughts only among those with MDE. CONCLUSIONS: Health and mental health (MH) service providers should pay close attention to the potential reciprocal effects of marijuana and other illicit drug use and MDE and suicidal thoughts among late middle-aged and older adults.
Keywords: Age Distribution; Aged; Cannabis; Cross-Sectional Studies; depression; Depressive Disorder, Major; Female; Health Surveys; Humans; Illicit Drugs; Male; Marijuana Abuse; Marijuana Smoking; Middle Aged; Regression Analysis; Self Report; Substance-Related Disorders; Suicidal Ideation; Suicide, Attempted; United States

Self-reported herpes zoster, pain, and health care seeking in the Health and Retirement Study: implications for interpretation of health care-based studies. - Hales, Craig M; Harpaz, Rafael; Bialek, Stephanie R (Ann Epidemiol, 2016)
PURPOSE: To describe self-reported herpes zoster (HZ) and explore factors that could impact interpretation of results from health care-based HZ studies. METHODS: We performed logistic regression using data from the 2008 Health and Retirement Study (HRS) to evaluate risk factors for having a history of HZ and experiencing severe HZ pain, and predictors for seeking health care for HZ. RESULTS: Among 14,564 respondents aged ≥55 years, women were more likely than men to report a history of HZ (15.7% vs. 11.6%, P < .01). Blacks (6.4% vs. 14.7% in whites, P < .01) and respondents with less than a high school diploma (12.2% vs.14.2% in respondents with at least a high school diploma, P = .01) were less likely to report a history of HZ. Women, blacks, Hispanics, and those with less than a high school diploma were more likely to report severe HZ pain. Most (91.1%) respondents sought health care for HZ; Hispanics (64.2% vs. 92.1% in whites, P < .001) and those with recurrent HZ were less likely to seek health care for HZ, whereas those with severe pain were more likely (95.4% vs. 87.9% in those without severe pain, P < .01). CONCLUSIONS: HRS provides a new platform for studies of HZ, one which allowed us to uncover issues that warrant particular attention when interpreting results of health care-based studies.
Keywords: Age Factors; Aged; Aged, 80 and over; Cross-Sectional Studies; Female; Health Surveys; Herpes Zoster; Humans; Independent Living; Logistic Models; Male; Middle Aged; Outcome Assessment, Health Care; pain; Pain Measurement; Patient Acceptance of Health Care; Reproducibility of Results; Retirement; Risk Assessment; Self Report; Severity of Illness Index; Sex Factors; Treatment Outcome; United States

Spousal Characteristics and Older Adults' Hospice Use: Understanding Disparities in End-of-Life Care. - Katherine A Ornstein; Melissa D. Aldridge; Christine A Mair; Rebecca Jean Gorges; Albert L Siu; Amy Kelley (J Palliat Med, 2016)
BACKGROUND: Hospice use has been shown to benefit quality of life for patients with terminal illness and their families, with further evidence of cost savings for Medicare and other payers. While disparities in hospice use by patient diagnosis, race, and region are well documented and attention to the role of family members in end-of-life decision-making is increasing, the influence of spousal characteristics on the decision to use hospice is unknown. OBJECTIVES: To determine the association between spousal characteristics and hospice use. DESIGN: We used data from the Health and Retirement Study (HRS), a prospective cohort study, linked to the Dartmouth Atlas of Health Care and Medicare claims. SETTING: National study of 1567 decedents who were married or partnered at the time of death (2000-2011). MEASURES: Hospice use at least 1 day in the last year of life as measured via Medicare claims data. Spousal factors (e.g., education and health status) measured via survey. RESULTS: In multivariate models controlling for patient factors and regional variation, spouses with lower educational attainment than their deceased spouse had decreased likelihood of hospice use (odds ratio [OR] = 0.58; 95% confidence interval [CI] = 0.40-0.82). Health of the spouse was not significantly associated with likelihood of decedent hospice use in adjusted models. IMPLICATIONS: Although the health of the surviving spouse was not associated with hospice use, their educational level was a predictor of hospice use. Spousal and family characteristics, including educational attainment, should be examined further in relation to disparities in hospice use. Efforts to increase access to high-quality end-of-life care for individuals with serious illness must also address the needs and concerns of caregivers and family.
Keywords: Hospice Care; Hospices; Humans; Medicare; Prospective Studies; Quality of Life; Terminal Care; United States

Spousal labor market effects from government health insurance: Evidence from a veterans affairs expansion. - Melissa A. Boyle; Joanna N Lahey (J Health Econ, 2016)
Measuring the total impact of health insurance receipt on household labor supply is important in an era of increased access to publicly provided and subsidized insurance. Although government expansion of health insurance to older workers leads to direct labor supply reductions for recipients, there may be spillover effects on the labor supply of uncovered spouses. While the most basic model predicts a decrease in overall household work hours, financial incentives such as credit constraints, target income levels, and the need for own health insurance suggest that spousal labor supply might increase. In contrast, complementarities of spousal leisure would predict a decrease in labor supply for both spouses. Utilizing a mid-1990s expansion of health insurance for U.S. veterans, we provide evidence on the effects of public insurance availability on the labor supply of spouses. Using data from the Current Population Survey and Health and Retirement Study, we employ a difference-in-differences strategy to compare the labor market behavior of the wives of older male veterans and non-veterans before and after the VA health benefits expansion. Although husbands' labor supply decreases, wives' labor supply increases, suggesting that financial incentives dominate complementarities of spousal leisure. This effect is strongest for wives with lower education levels and lower levels of household wealth and those who were not previously employed full-time. These findings have implications for government programs such as Medicare and Social Security and the Affordable Care Act.
Keywords: Employment; Female; Government Programs; Humans; Insurance, Health; Male; Middle Aged; Spouses; Surveys and Questionnaires; United States; Veterans

Telomere length and health outcomes: A two-sample genetic instrumental variables analysis. - Hamad, Rita; Stefan Walter; David Rehkopf (Exp Gerontol, 2016)
OBJECTIVE: Previous studies linking telomere length (TL) and health have been largely associational. We apply genetic instrumental variables (IV) analysis, also known as Mendelian randomization, to test the hypothesis that shorter TL leads to poorer health. This method reduces bias from reverse causation or confounding. METHODS: We used two approaches in this study that rely on two separate data sources: (1) individual-level data from the Health and Retirement Study (HRS) (N=3734), and (2) coefficients from genome-wide association studies (GWAS). We employed two-sample genetic IV analyses, constructing a polygenic risk score (PRS) of TL-associated single nucleotide polymorphisms. The first approach examined the association of the PRS with nine individual health outcomes in HRS. The second approach took advantage of estimates available in GWAS databases to estimate the impact of TL on five health outcomes using an inverse variance-weighted meta-analytic technique. RESULTS: Using individual-level data, shorter TL was marginally statistically significantly associated with decreased risk of stroke and increased risk of heart disease. Using the meta-analytic approach, shorter TL was associated with increased risk of coronary artery disease (OR 1.02 per 100 base pairs, 95%CI: 1.00, 1.03). DISCUSSION: With the exception of a small contribution to heart disease, our findings suggest that TL may be a marker of disease rather than a cause. They also demonstrate the utility of the inverse variance-weighted meta-analytic approach when examining small effect sizes.
Keywords: Aged; Aging; Coronary Artery Disease; Databases, Factual; Female; Humans; Longitudinal Studies; Male; Middle Aged; Molecular Epidemiology; Polymorphism, Single Nucleotide; Self Report; Telomere; Telomere Homeostasis; United States

Ten-Year Prevalence and Incidence of Urinary Incontinence in Older Women: A Longitudinal Analysis of the Health and Retirement Study. - Erekson, Elisabeth A; Cong, Xiangyu; Mary K Townsend; Ciarleglio, Maria M (J Am Geriatr Soc, 2016)
OBJECTIVES: To measure the incidence of urinary incontinence (UI) over 10 years in older women who did not report UI at baseline in 1998, to estimate the prevalence of female UI according to severity and type, and to explore potential risk factors for development of UI. DESIGN: Secondary analysis of a prospective cohort. SETTING: Health and Retirement Study. PARTICIPANTS: Women participating in the Health and Retirement Study between 1998 and 2008 who did not have UI at baseline (1998). MEASUREMENTS: UI was defined as an answer of "yes" to the question, "During the last 12 months, have you lost any amount of urine beyond your control?" UI was characterized according to severity (according to the Sandvik Severity Index) and type (according to International Continence Society definitions) at each biennial follow-up between 1998 and 2008. RESULTS: In 1998, 5,552 women aged 51 to 74 reported no UI. The cumulative incidence of UI in older women was 37.2% (95% confidence interval (CI)=36.0-38.5%). The most common incontinence type at the first report of leakage was mixed UI (49.1%, 95% CI=46.5-51.7%), and women commonly reported their symptoms at first leakage as moderate to severe (46.4%, 95% CI=43.8-49.0%). CONCLUSION: Development of UI in older women was common and tended to result in mixed type and moderate to severe symptoms.
Keywords: Aged; Female; Humans; Incidence; Longitudinal Studies; Prevalence; Prospective Studies; Surveys and Questionnaires; United States; Urinary incontinence

Using an Alzheimer Disease Polygenic Risk Score to Predict Memory Decline in Black and White Americans Over 14 Years of Follow-up. - Jessica R Marden; Elizabeth R Mayeda; Stefan Walter; Vivot, Alexandre; Tchetgen Tchetgen, Eric J; Ichiro Kawachi; M. Maria Glymour (Alzheimer Dis Assoc Disord, 2016)
Evidence on whether genetic predictors of Alzheimer disease (AD) also predict memory decline is inconsistent, and limited data are available for African ancestry populations. For 8253 non-Hispanic white (NHW) and non-Hispanic black (NHB) Health and Retirement Study participants with memory scores measured 1 to 8 times between 1998 and 2012 (average baseline age=62), we calculated weighted polygenic risk scores [AD Genetic Risk Score (AD-GRS)] using the top 22 AD-associated loci, and an alternative score excluding apolipoprotein E (APOE) (AD-GRSexAPOE). We used generalized linear models with AD-GRS-by-age and AD-GRS-by-age interactions (age centered at 70) to predict memory decline. Average NHB decline was 26% faster than NHW decline (P<0.001). Among NHW, 10% higher AD-GRS predicted faster memory decline (linear β=-0.058 unit decrease over 10 y; 95% confidence interval,-0.074 to -0.043). AD-GRSexAPOE also predicted faster decline for NHW, although less strongly. Among NHB, AD-GRS predicted faster memory decline (linear β=-0.050; 95% confidence interval, -0.106 to 0.006), but AD-GRSexAPOE did not. Our nonsignificant estimate among NHB may reflect insufficient statistical power or a misspecified AD-GRS among NHB as an overwhelming majority of genome-wide association studies are conducted in NHW. A polygenic score based on previously identified AD loci predicts memory loss in US blacks and whites.
Keywords: Alzheimer disease; Black or African American; ethnicity; Female; Follow-Up Studies; Genome-Wide Association Study; Humans; Male; Memory Disorders; Middle Aged; Risk Factors; United States; White People

Validating a summary measure of weight history for modeling the health consequences of obesity. - Andrew C. Stokes; Ni, Yu (Ann Epidemiol, 2016)
PURPOSE: Data on weight history may enhance the predictive validity of epidemiologic models of the health risks of obesity, but collecting such data is often not feasible. In this study, we investigate the validity of a summary measure of weight history. METHODS: We evaluated the quality of reporting of maximum weight in a sample of adults aged 50-84 years using data from the Health and Retirement Study. Recalled max body mass index (BMI, measured in kilogram per square meter) based on recalled weight in 2004 was compared with calculated max BMI based on self-reported weight collected biennially between 1992 and 2004. Logistic regression was used to assess similarity between the measures in predicting prevalent conditions. RESULTS: The correlation coefficient between recalled and calculated max weight in the overall sample was 0.95. Recalled max BMI value was within three BMI units of the calculated value 91.4% of the time. The proportions of individuals with obese I (BMI: 30.0-34.9), obese II (BMI: 35.0-39.9), and obese III (BMI: 40.0 and above) were 28.8%, 12.7%, and 6.6% using recalled values compared with 27.1%, 10.5%, and 4.9% using calculated values. In multivariate analyses, the two BMI measures similarly predicted disease prevalence across a number of chronic conditions. CONCLUSIONS: Recalled max BMI was strongly correlated with max BMI calculated over the 12-year period before recall, suggesting that this measure can serve as a reliable summary measure of recent weight status.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Body Weight; Chronic disease; Female; Health Surveys; Humans; Logistic Models; Longitudinal Studies; Male; Middle Aged; Obesity; Self Report; United States

Volunteering Is Associated with Lower Risk of Cognitive Impairment. - Frank J Infurna; Morris A Okun; Kevin J. Grimm (J Am Geriatr Soc, 2016)
OBJECTIVES: To examine whether psychosocial factors that can be a target for interventions, such as volunteering, are associated with risk of cognitive impairment. DESIGN: Health and Retirement Study (HRS) data from 1998 to 2012, a nationally representative longitudinal panel survey of older adults assessed every 2 years, were used. SETTING: The HRS interviews participants aged 50 and older across the contiguous United States. PARTICIPANTS: Individuals aged 60 and older in 1998 (N = 13,262). MEASUREMENTS: Personal interviews were conducted with respondents to assess presence of cognitive impairment, measured using a composite across cognitive measures. RESULTS: Volunteering at the initial assessment and volunteering regularly over time independently decreased the risk of cognitive impairment over 14 years, and these findings were maintained independent of known risk factors for cognitive impairment. Greater risk of onset of cognitive impairment was associated with being older, being female, being nonwhite, having fewer years of education, and reporting more depressive symptoms. CONCLUSION: Consistent civic engagement in old age is associated with lower risk of cognitive impairment and provides impetus for interventions to protect against the onset of cognitive impairment. Given the increasing number of baby boomers entering old age, the findings support the public health benefits of volunteering and the potential role of geriatricians, who can promote volunteering by incorporating "prescriptions to volunteer" into their patient care.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Female; Geriatric Assessment; Health Surveys; Humans; Interviews as Topic; Male; Middle Aged; Risk Factors; United States; Volunteers

Work-Family Trajectories and the Higher Cardiovascular Risk of American Women Relative to Women in 13 European Countries. - van Hedel, Karen; Mejía-Guevara, Iván; Mauricio Avendano; Erika L. Sabbath; Lisa F Berkman; Johan P Mackenbach; van Lenthe, Frank J (Am J Public Health, 2016)
OBJECTIVES: To investigate whether less-healthy work-family life histories contribute to the higher cardiovascular disease prevalence in older American compared with European women. METHODS: We used sequence analysis to identify distinct work-family typologies for women born between 1935 and 1956 in the United States and 13 European countries. Data came from the US Health and Retirement Study (1992-2006) and the Survey of Health, Aging, and Retirement in Europe (2004-2009). RESULTS: Work-family typologies were similarly distributed in the United States and Europe. Being a lone working mother predicted a higher risk of heart disease, stroke, and smoking among American women, and smoking for European women. Lone working motherhood was more common and had a marginally stronger association with stroke in the United States than in Europe. Simulations indicated that the higher stroke risk among American women would only be marginally reduced if American women had experienced the same work-family trajectories as European women. CONCLUSIONS: Combining work and lone motherhood was more common in the United States, but differences in work-family trajectories explained only a small fraction of the higher cardiovascular risk of American relative to European women.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Computer Simulation; Europe; Female; Humans; Middle Aged; Obesity; Single Parent; Smoking; Socioeconomic factors; United States; Women, Working; Young Adult

Adherence to diabetes guidelines for screening, physical activity and medication and onset of complications and death. - Chen, Yiqun; Frank A Sloan; Arseniy P Yashkin (J Diabetes Complications, 2015)
AIMS: Analyze relationships between adherence to guidelines for diabetes care - regular screening; physical activity; and medication - and diabetes complications and mortality. METHODS: Outcomes were onset of congestive heart failure (CHF), stroke, renal failure, moderate complications of lower extremities, lower-limb amputation, proliferative diabetic retinopathy (PDR), and mortality during follow-up. Participants were persons aged 65+ in the Health and Retirement Study (HRS) 2003 Diabetes Study and had Medicare claims in follow-up period (2004-8). RESULTS: Adherence to screening recommendations decreased risks of developing CHF (odds ratio (OR)=0.83; 95% confidence interval (CI): 0.72-0.96), stroke (OR=0.80; 95% CI: 0.68-0.94); renal failure (OR=0. 82; 95% CI: 0.71-0.95); and death (OR=0.86; 95% CI: 0.74-0.99). Adherence to physical activity recommendation reduced risks of stroke (OR=0.64; 95% CI: 0.45-0.90), renal failure (OR=0.71; 95% CI: 0.52-0.97), moderate lower-extremity complications (OR=0.71; 95% CI: 0.51-0.99), having a lower limb amputation (OR=0.31, 95% CI: 0.11-0.85), and death (OR=0.56, 95% CI: 0.41-0.77). Medication adherence was associated with lower risks of PDR (OR=0.35, 95% CI: 0.13-0.93). CONCLUSIONS: Adherence to screening, physical activity and medication guidelines was associated with lower risks of diabetes complications and death. Relative importance of adherence differed among outcome measures.
Keywords: Aged; Aged, 80 and over; Combined Modality Therapy; Diabetes Complications; Diabetes Mellitus; Early Diagnosis; Female; Health Promotion; Health Surveys; Humans; Hypoglycemic Agents; Longitudinal Studies; Male; Mass Screening; Medicare Part A; Medicare Part B; Medication Adherence; Motor Activity; Patient Compliance; Practice Guidelines as Topic; Risk; United States

Antidepressant Use and Cognitive Decline: The Health and Retirement Study. - Jane S Saczynski; Allison B Rosen; Ryan J McCammon; Zivin, Kara; Susan E. Andrade; Kenneth M. Langa; Sandeep Vijan; Paul A Pirraglia; Becky A. Briesacher (Am J Med, 2015)
BACKGROUND: Depression is associated with cognitive impairment and dementia, but whether treatment for depression with antidepressants reduces the risk for cognitive decline is unclear. We assessed the association between antidepressant use and cognitive decline over 6 years. METHODS: Participants were 3714 adults aged 50 years or more who were enrolled in the nationally representative Health and Retirement Study and had self-reported antidepressant use. Depressive symptoms were assessed using the 8-item Center for Epidemiologic Studies Depression Scale. Cognitive function was assessed at 4 time points (2004, 2006, 2008, 2010) using a validated 27-point scale. Change in cognitive function over the 6-year follow-up period was examined using linear growth models, adjusted for demographics, depressive symptoms, comorbidities, functional limitations, and antidepressant anticholinergic activity load. RESULTS: At baseline, cognitive function did not differ significantly between the 445 (12.1%) participants taking antidepressants and those not taking antidepressants (mean, 14.9%; 95% confidence interval, 14.3-15.4 vs mean, 15.1%; 95% confidence interval, 14.9-15.3). During the 6-year follow up period, cognition declined in both users and nonusers of antidepressants, ranging from -1.4 change in mean score in those with high depressive symptoms and taking antidepressants to -0.5 change in mean score in those with high depressive symptoms and not taking antidepressants. In adjusted models, cognition declined in people taking antidepressants at the same rate as those not taking antidepressants. Results remained consistent across different levels of baseline cognitive function, age, and duration of antidepressant use (prolonged vs short-term). CONCLUSIONS: Antidepressant use did not modify the course of 6-year cognitive change in this nationally representative sample.
Keywords: Age Distribution; Aged; Aged, 80 and over; Antidepressive Agents; Cognition; Cross-Sectional Studies; Depressive Disorder; Female; Follow-Up Studies; Geriatric Assessment; Humans; Incidence; Male; Middle Aged; Reference Values; Risk Assessment; Sex Distribution; Surveys and Questionnaires; United States

The association of depression, cognitive impairment without dementia, and dementia with risk of ischemic stroke: a cohort study. - Dimitry S Davydow; Deborah A Levine; Zivin, Kara; Wayne J Katon; Kenneth M. Langa (Psychosom Med, 2015)
OBJECTIVE: To determine if depression, cognitive impairment without dementia (CIND), and/or dementia are each independently associated with risk of ischemic stroke and to identify characteristics that could modify these associations. METHODS: This retrospective-cohort study examined a population-based sample of 7031 Americans older than 50 years participating in the Health and Retirement Study (1998-2008) who consented to have their interviews linked to their Medicare claims. The eight-item Center for Epidemiologic Studies Depression Scale and/or International Classification of Disease, Ninth Revision, Clinical Modification (ICD-9-CM) depression diagnoses were used to identify baseline depression. The Modified Telephone Interview for Cognitive Status and/or ICD-9-CM dementia diagnoses were used to identify baseline CIND or dementia. Hospitalizations for ischemic stroke were identified via ICD-9-CM diagnoses. RESULTS: After adjusting for demographics, medical comorbidities, and health-risk behaviors, CIND alone (odds ratio [OR] = 1.37, 95% confidence interval [CI] = 1.11-1.69) and co-occurring depression and CIND (OR = 1.65, 95% CI = 1.24-2.18) were independently associated with increased odds of ischemic stroke. Depression alone was not associated with odds of ischemic stroke (OR = 1.11, 95% CI = 0.88-1.40) in unadjusted analyses. Neither dementia alone (OR = 1.09, 95% CI = 0.82-1.45) nor co-occurring depression and dementia (OR = 1.25, 95% CI = 0.89-1.76) were associated with odds of ischemic stroke after adjusting for demographics. CONCLUSIONS: CIND and co-occurring depression and CIND are independently associated with increased risk of ischemic stroke. Individuals with co-occurring depression and CIND represent a high-risk group that may benefit from targeted interventions to prevent stroke.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Dementia; depression; Female; Humans; Male; Middle Aged; Psychiatric Status Rating Scales; Retrospective Studies; Risk Factors; Stroke; United States

Becoming centenarians: disease and functioning trajectories of older US Adults as they survive to 100. - Jennifer A Ailshire; Hiram Beltrán-Sánchez; Eileen M. Crimmins (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: Little is known about the health and functioning of individuals who become centenarians in the years prior to reaching age 100. We examined long-term trajectories of disease, disability, and cognitive function in a sample of U.S. centenarians to determine how their aging experience differs from their nonsurviving cohort counterparts, and if there is heterogeneity in the aging experience of centenarians. METHODS: Data are from the 1993-2010 waves of the nationally representative Health and Retirement Study. Among those who had the potential to become centenarians, we identified 1,045 respondents who died before reaching age 100 and 96 who survived to their 100th birthday. Respondents, or their proxies, reported on diagnosis of six major diseases (hypertension, heart disease, lung disease, stroke, cancer, and diabetes), limitations in activities of daily living, and cognitive function. RESULTS: As they age to 100, centenarians are generally healthier than nonsurviving members of their cohort, and a number of individuals who become centenarians reach 100 with no self-reported diseases or functional impairments. About 23% of centenarians reached age 100 with no major chronic disease and approximately the same number had no disability (18%). Over half (55%) reached 100 without cognitive impairment. Disease and functioning trajectories of centenarians differ by sex, education, and marital status. CONCLUSIONS: While some centenarians have poor health and functioning upon reaching age 100, others are able to achieve exceptional longevity in relatively good health and without loss of functioning. This study underscores the importance of examining variation in the growing centenarian population.
Keywords: Activities of Daily Living; Aged, 80 and over; Aging; Chronic disease; Cognition; Disability Evaluation; Educational Status; Female; Geriatric Assessment; Health Status; Health Surveys; Humans; Longevity; Longitudinal Studies; Male; Marital Status; Prospective Studies; Sex Factors; United States

The burden of health care costs for patients with dementia in the last 5 years of life. - Amy Kelley; Kathleen McGarry; Rebecca Jean Gorges; Jonathan S Skinner (Ann Intern Med, 2015)
BACKGROUND: Common diseases, particularly dementia, have large social costs for the U.S. population. However, less is known about the end-of-life costs of specific diseases and the associated financial risk for individual households. OBJECTIVE: To examine social costs and financial risks faced by Medicare beneficiaries 5 years before death. DESIGN: Retrospective cohort. SETTING: The HRS (Health and Retirement Study). PARTICIPANTS: Medicare fee-for-service beneficiaries, aged 70 years or older, who died between 2005 and 2010 (n = 1702), stratified into 4 groups: persons with a high probability of dementia or those who died because of heart disease, cancer, or other causes. MEASUREMENTS: Total social costs and their components, including Medicare, Medicaid, private insurance, out-of-pocket spending, and informal care, measured over the last 5 years of life; and out-of-pocket spending as a proportion of household wealth. RESULTS: Average total cost per decedent with dementia ($287 038) was significantly greater than that of those who died of heart disease ($175 136), cancer ($173 383), or other causes ($197 286) (P < 0.001). Although Medicare expenditures were similar across groups, average out-of-pocket spending for patients with dementia ($61 522) was 81% higher than that for patients without dementia ($34 068); a similar pattern held for informal care. Out-of-pocket spending for the dementia group (median, $36 919) represented 32% of wealth measured 5 years before death compared with 11% for the nondementia group (P < 0.001). This proportion was greater for black persons (84%), persons with less than a high school education (48%), and unmarried or widowed women (58%). LIMITATION: Imputed Medicaid, private insurance, and informal care costs. CONCLUSION: Health care expenditures among persons with dementia were substantially larger than those for other diseases, and many of the expenses were uncovered (uninsured). This places a large financial burden on families, and these burdens are particularly pronounced among the demographic groups that are least prepared for financial risk. PRIMARY FUNDING SOURCE: National Institute on Aging.
Keywords: Aged; Aged, 80 and over; Cost of Illness; Dementia; Female; Health Expenditures; Humans; Insurance, Health; Male; Medicaid; Medicare; Retrospective Studies; Socioeconomic factors; Terminal Care; United States

Cognitive function and the concordance between survey reports and Medicare claims in a nationally representative cohort of older adults. - Frederic D Wolinsky; Michael P Jones; Fred A Ullrich; Yiyue Lou; George L Wehby (Med Care, 2015)
BACKGROUND: While age-related cognitive decline may affect all stages in the response process--comprehension, retrieval, judgment, response selection, and response reporting--the associations between objective cognitive tests and the agreement between self-reports and Medicare claims has not been assessed. We evaluate those associations using the Survey on Assets and Health Dynamics among the Oldest Old (AHEAD). METHODS: Eight waves of reinterviews (1995-2010) were linked to Medicare claims for 3661 self-respondents yielding 12,313 person-period observations. Cognitive function was measured by 2 episodic memory tests (immediate and delayed recall of 10 words) and 1 mental status test (backward counting, dates, and names). Survey reports on 12 diseases and 4 health services were mapped to Medicare claims to derive counts of concordant reports, underreports, and overreports, as were the numbers of hospital episodes and physician visits. GEE negative binomial and logistic regression models were used. RESULTS: Better mental status was associated with more concordant reporting and less underreporting on disease history and the number of hospital episodes. Better mental status and delayed word recall were associated with more concordant reporting and less underreporting on health services use. Better delayed recall was significantly associated with less underreporting on the number of physician visits. These associations were not appreciably altered by adjustment for demographic characteristics, socioeconomic status, self-rated health, or secular trends. CONCLUSION: We recommend that future surveys of older adults include an objective measure of mental status (rather than memory), especially when those survey reports cannot be verified by access to Medicare claims or chart review.
Keywords: Aged; Aging; Cognition Disorders; Data collection; Female; Humans; Insurance Claim Review; Male; Medicare; Mental Health; Psychiatric Status Rating Scales; Self Report; United States

Comorbidity and functional trajectories from midlife to old age: the Health and Retirement Study. - Stenholm, Sari; Westerlund, Hugo; Head, Jenny; Hyde, Martin; Ichiro Kawachi; Pentti, Jaana; Mika Kivimäki; Vahtera, Jussi (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: The number of diseases and physical functioning difficulties tend to increase with age. The aim of this study was to examine the trajectories of physical functioning across age groups and whether the trajectories differ according to disease status in different population subgroups. METHODS: Repeat data from a nationally representative population sample, the Health and Retirement Study, was used. Participants were 10,709 men and 13,477 women aged 60-107 years at baseline with biennial surveys from 1992 to 2010. Average length of follow-up was 10.3 years ranging from 0 to 18 years. Disease status and physical functioning was asked about at all study phases and 10 items were summed to obtain a physical functioning score (0-10). RESULTS: Age modified the relationship between number of chronic diseases and physical functioning with older participants having more physical functioning difficulties with increasing number of diseases. An average 70-year-old participant with no diseases had 0.89 (95% CI: 0.85-0.93) physical functioning difficulties, with one disease 1.72 (95% CI: 1.69-1.76) difficulties, with two diseases 2.57 (95% CI: 2.52-2.62) difficulties, and with three or more diseases 3.82 (95% CI: 3.76-3.88) difficulties. Of the individual diseases memory-related diseases, stroke, pulmonary diseases, and arthritis were associated with significantly higher physical functioning difficulties compared with other diseases. CONCLUSIONS: Comorbidity is associated with greater burden of physical functioning difficulties. Of the studied diseases, memory-related diseases, stroke, pulmonary diseases, and arthritis alone or in combination limit most physical functioning.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Chronic disease; Comorbidity; Female; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Retirement; Socioeconomic factors; United States

Cross-National Differences in Disability Among Elders: Transitions in Disability in Mexico and the United States. - Kerstin Gerst; Rebeca Wong; Alejandra Michaels-Obregon; Alberto Palloni (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: Little is known about how exposure to a combination of infectious and chronic conditions throughout the lifecourse could impact disability in old age. This paper compares 2 cohorts of adults who have aged under very different country contexts by contrasting disability transitions among elders in Mexico with elders in the United States. METHODS: Data comes from the Mexican Health and Aging Study (MHAS) and the U.S. Health and Retirement Study (HRS). Estimated probabilities of 2-year transitions among disability states and mortality are presented for adults aged 50 and older. RESULTS: The levels of disability prevalence and 2 year transitions are consistent with a higher rate of disability for the United States compared to Mexico. In 2-year transitions, the U.S. sample was more likely to transition to a disabled state or increase the number of disabilities than the Mexican counterparts, while Mexicans are more likely to move out of disability or reduce the number of disabilities reported. DISCUSSION: The findings suggest that the current rate of disability in old age is lower for a less developed country compared with a developed society. We discuss implications, possible explanations, and likely future scenarios.
Keywords: Aged; Aged, 80 and over; Aging; Cross-Cultural Comparison; Disabled Persons; Female; Humans; Male; Mexico; Middle Aged; Mortality; Prevalence; United States

Dental use and expenditures for older uninsured Americans: the simulated impact of expanded coverage. - Richard J. Manski; John F Moeller; Haiyan Chen; Jody Schimmel; John V Pepper; Patricia A St Clair (Health Serv Res, 2015)
OBJECTIVE: To determine if providing dental insurance to older Americans would close the current gaps in dental use and expenditure between insured and uninsured older Americans. DATA SOURCES/STUDY SETTING: We used data from the 2008 Health and Retirement Survey (HRS) supplemented by data from the 2006 Medical Expenditure Panel Survey (MEPS). STUDY DESIGN: We compared the simulated dental use and expenditures rates of newly insured persons against the corresponding rates for those previously insured. DATA COLLECTION/EXTRACTION METHODS: The HRS is a nationally representative survey administered by the Institute for Social Research (ISR). The MEPS is a nationally representative household survey sponsored by the Agency for Healthcare Research and Quality (AHRQ). PRINCIPAL FINDINGS: We found that expanding dental coverage to older uninsured Americans would close previous gaps in dental use and expense between uninsured and insured noninstitutionalized Americans 55 years and older. CONCLUSIONS: Providing dental coverage to previously uninsured older adults would produce estimated monthly costs net of markups for administrative costs that comport closely to current market rates. Estimates also suggest that the total cost of providing dental coverage targeted specifically to nonusers of dental care may be less than similar costs for prior users.
Keywords: Aged; Dental Health Services; Female; Health Expenditures; Humans; Insurance, Dental; Male; Medically Uninsured; Middle Aged; Surveys and Questionnaires; United States

Disability Trajectories at the End of Life: A "Countdown" Model. - Douglas A. Wolf; Vicki A Freedman; Jan I Ondrich; Christopher L Seplaki; Brenda C Spillman (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: Studies of late-life disablement typically address the role of advancing age as a factor in developing disability, and in some cases have pointed out the importance of time to death (TTD) in understanding changes in functioning. However, few studies have addressed both factors simultaneously, and none have dealt satisfactorily with the problem of missing data on TTD in panel studies. METHODS: We fit latent-class trajectory models of disablement using data from the Health and Retirement Study. Among survivors (~20% of the sample), TTD is unknown, producing a missing-data problem. We use an auxiliary regression equation to impute TTD and employ multiple imputation techniques to obtain final parameter estimates and standard errors. RESULTS: Our best-fitting model has 3 latent classes. In all 3 classes, the probability of having a disability increases with nearness to death; however, in only 2 of the 3 classes is age associated with disability. We find gender, race, and educational differences in class-membership probabilities. DISCUSSION: The model reveals a complex pattern of age- and time-dependent heterogeneity in late-life disablement. The techniques developed here could be applied to other phenomena known to depend on TTD, such as cognitive change, weight loss, and health care spending.
Keywords: Aged; Aged, 80 and over; Aging; Death; Disabled Persons; Female; Humans; Male; Time Factors; United States

Disease incidence and mortality among older Americans and Europeans. - Sole-Auro, Aida; Pierre-Carl Michaud; Michael D Hurd; Eileen M. Crimmins (Demography, 2015)
Recent research has shown a widening gap in life expectancy at age 50 between the United States and Europe as well as large differences in the prevalence of diseases at older ages. Little is known about the processes determining international differences in the prevalence of chronic diseases. Higher prevalence of disease could result from either higher incidence or longer disease-specific survival. This article uses comparable longitudinal data from 2004 and 2006 for populations aged 50 to 79 from the United States and from a selected group of European countries to examine age-specific differences in prevalence and incidence of heart disease, stroke, lung disease, diabetes, hypertension, and cancer as well as mortality associated with each disease. Not surprisingly, we find that Americans have higher disease prevalence. For heart disease, diabetes, and cancer, incidence is lower in Europe when we control for sociodemographic and health behavior differences in risk, and these differences explain much of the prevalence gap at older ages. On the other hand, incidence is higher in Europe for lung disease and not different between Europe and the United States for hypertension and stroke. Our findings do not suggest a survival advantage conditional on disease in Europe compared with the United States. Therefore, the origin of the higher disease prevalence at older ages in the United States is to be found in higher prevalence earlier in the life course and, for some conditions, higher incidence between ages 50 and 79.
Keywords: Age Distribution; Aged; Chronic disease; Europe; Health Behavior; Humans; Incidence; Middle Aged; Neoplasms; Prevalence; Risk Factors; Sex Distribution; Socioeconomic factors; United States

Effects of Co-Worker and Supervisor Support on Job Stress and Presenteeism in an Aging Workforce: A Structural Equation Modelling Approach. - Tianan Yang; Shen, Yu-Ming; Zhu, Mingjing; Liu, Yuanling; Deng, Jianwei; Chen, Qian; See, Lai-Chu (Int J Environ Res Public Health, 2015)
We examined the effects of co-worker and supervisor support on job stress and presenteeism in an aging workforce. Structural equation modelling was used to evaluate data from the 2010 wave of the Health and Retirement Survey in the United States (n = 1649). The level of presenteeism was low and the level of job stress was moderate among aging US workers. SEM revealed that co-worker support and supervisor support were strongly correlated (β = 0.67; p < 0.001). Job stress had a significant direct positive effect on presenteeism (β = 0.30; p < 0.001). Co-worker support had a significant direct negative effect on job stress (β = -0.10; p < 0.001) and presenteeism (β = -0.11; p < 0.001). Supervisor support had a significant direct negative effect on job stress (β = -0.40; p < 0.001) but not presenteeism. The findings suggest that presenteeism is reduced by increased respect and concern for employee stress at the workplace, by necessary support at work from colleagues and employers, and by the presence of comfortable interpersonal relationships among colleagues and between employers and employees.
Keywords: Aged; Cross-Sectional Studies; Female; Health Surveys; Humans; Interpersonal Relations; Male; Middle Aged; Models, Statistical; Occupational Health; Population Dynamics; Presenteeism; Social Support; Stress, Psychological; United States

The effects of income on mental health: evidence from the social security notch. - Ezra Golberstein (J Ment Health Policy Econ, 2015)
BACKGROUND: Mental health is a key component of overall wellbeing and mental disorders are relatively common, including among older adults. Yet the causal effect of income on mental health status among older adults is poorly understood. AIMS: This paper considers the effects of a major source of transfer income, Social Security retirement benefits, on the mental health of older adults. METHODS: The Social Security benefit "Notch" is as a large, permanent, and exogenous shock to Social Security income in retirement. The "Notch" is used to identify the causal effect of Social Security income on mental health among older ages using data from the AHEAD cohort of the Health and Retirement Study. RESULTS: We find that increases in Social Security income significantly improve mental health status and the likelihood of a psychiatric diagnosis for women, but not for men. DISCUSSION: The effects of income on mental health for older women are statistically significant and meaningful in magnitude. While this is one of the only studies to use plausibly exogenous variation in household income to identify the effect of income on mental health, a limitation of this work is that the results only directly pertain to lower-education households. IMPLICATIONS: Public policy proposals that alter retirement benefits for the elderly may have important effects on the mental health of older adults.
Keywords: Age Factors; Aged; Aged, 80 and over; Female; Humans; Income; Male; Mental Health; Models, Econometric; Retirement; Sex Factors; Social Security; Socioeconomic factors; United States

Explaining Disability Trends in the U.S. Elderly and Near-Elderly Population. - Chen, Yiqun; Frank A Sloan (Health Serv Res, 2015)
OBJECTIVE: To examine disability trends among U.S. near-elderly and elderly persons and explain observed trends. DATA SOURCE: 1996-2010 waves of the Health and Retirement Study. STUDY DESIGN: We first examined trends in Activities of Daily Living and Instrumental Activities of Daily Living limitations, and large muscle, mobility, gross motor, and fine motor indexes. Then we used decomposition analysis to estimate contributions of changes in sociodemographic composition, self-reported chronic disease prevalence and health behaviors, and changes in disabling effects of these factors to disability changes between 1996 and 2010. PRINCIPAL FINDINGS: Disability generally increased or was unchanged. Increased trends were more apparent for near-elderly than elderly persons. Sociodemographic shifts tended to reduce disability, but their favorable effects were largely offset by increased self-reported chronic disease prevalence. Changes in smoking and heavy drinking prevalence had relatively minor effects on disability trends. Increased obesity rates generated sizable effects on lower-body functioning changes. Disabling effects of self-reported chronic diseases often declined, and educational attainment became a stronger influence in preventing disability. CONCLUSIONS: Such unfavorable trends as increased chronic disease prevalence and higher obesity rates offset or outweighed the favorable effects with the result that disability remained unchanged or increased.
Keywords: Activities of Daily Living; Age Distribution; Aged; Aged, 80 and over; Alcohol Drinking; Chronic disease; Disabled Persons; Female; Health Behavior; Health Surveys; Humans; Male; Middle Aged; Mobility Limitation; Obesity; Prevalence; Sex Distribution; Smoking; Socioeconomic factors; United States

Factors associated with cognitive evaluations in the United States. - Vikas Kotagal; Kenneth M. Langa; Brenda L Plassman; Gwenith G Fisher; Bruno J Giordani; Robert B Wallace; James F. Burke; David C Steffens; Mohammed U Kabeto; Roger L. Albin; Norman L Foster (Neurology, 2015)
OBJECTIVE: We aimed to explore factors associated with clinical evaluations for cognitive impairment among older residents of the United States. METHODS: Two hundred ninety-seven of 845 subjects in the Aging, Demographics, and Memory Study (ADAMS), a nationally representative community-based cohort study, met criteria for dementia after a detailed in-person study examination. Informants for these subjects reported whether or not they had ever received a clinical cognitive evaluation outside of the context of ADAMS. Among subjects with dementia, we evaluated demographic, socioeconomic, and clinical factors associated with an informant-reported clinical cognitive evaluation using bivariate analyses and multivariable logistic regression. RESULTS: Of the 297 participants with dementia in ADAMS, 55.2% (representing about 1.8 million elderly Americans in 2002) reported no history of a clinical cognitive evaluation by a physician. In a multivariable logistic regression model (n = 297) controlling for demographics, physical function measures, and dementia severity, marital status (odds ratio for currently married: 2.63 [95% confidence interval: 1.10-6.35]) was the only significant independent predictor of receiving a clinical cognitive evaluation among subjects with study-confirmed dementia. CONCLUSIONS: Many elderly individuals with dementia do not receive clinical cognitive evaluations. The likelihood of receiving a clinical cognitive evaluation in elderly individuals with dementia associates with certain patient-specific factors, particularly severity of cognitive impairment and current marital status.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Cohort Studies; Dementia; Female; Humans; Logistic Models; Male; Marital Status; Multivariate Analysis; Neuropsychological tests; Severity of Illness Index; United States

Financing Long-Term Services And Supports: Options Reflect Trade-Offs For Older Americans And Federal Spending. - Melissa Favreault; Gleckman, Howard; Richard W. Johnson (Health Affairs (Project Hope), 2015)
About half of older Americans will need a high level of assistance with routine activities for a prolonged period of time. This help is commonly referred to as long-term services and supports (LTSS). Under current policies, these individuals will fund roughly half of their paid care out of pocket. Partly as a result of high costs and uncertainty, relatively few people purchase private long-term care insurance or save sufficiently to fully finance LTSS; many will eventually turn to Medicaid for help. To show how policy changes could expand insurance's role in financing these needs, we modeled several new insurance options. Specifically, we looked at a front-end-only benefit that provides coverage relatively early in the period of disability but caps benefits, a back-end benefit with no lifetime limit, and a combined comprehensive benefit. We modeled mandatory and voluntary versions of each option, and subsidized and unsubsidized versions of each voluntary option. We identified important differences among the alternatives, highlighting relevant trade-offs that policy makers can consider in evaluating proposals. If the primary goal is to significantly increase insurance coverage, the mandatory options would be more successful than the voluntary versions. If the major aim is to reduce Medicaid costs, the comprehensive and back-end mandatory options would be most beneficial.
Keywords: Aged; Financing; Government; Humans; Insurance; Insurance Coverage; Long-term Care; Medicaid; Middle Aged; Policy Making; United States

Functional impairment and hospital readmission in Medicare seniors. - S. Ryan Greysen; Irena Cenzer; Andrew D. Auerbach; Kenneth E Covinsky (JAMA Intern Med, 2015)
IMPORTANCE: Medicare currently penalizes hospitals for high readmission rates for seniors but does not account for common age-related syndromes, such as functional impairment. OBJECTIVE: To assess the effects of functional impairment on Medicare hospital readmissions given the high prevalence of functional impairments in community-dwelling seniors. DESIGN, SETTING, AND PARTICIPANTS: We created a nationally representative cohort of 7854 community-dwelling seniors in the Health and Retirement Study, with 22,289 Medicare hospitalizations from January 1, 2000, through December 31, 2010. MAIN OUTCOMES AND MEASURES: Outcome was 30-day readmission assessed by Medicare claims. The main predictor was functional impairment determined from the Health and Retirement Study interview preceding hospitalization, stratified into the following 5 levels: no functional impairments, difficulty with 1 or more instrumental activities of daily living, difficulty with 1 or more activities of daily living (ADL), dependency (need for help) in 1 to 2 ADLs, and dependency in 3 or more ADLs. Adjustment variables included age, race/ethnicity, sex, annual income, net worth, comorbid conditions (Elixhauser score from Medicare claims), and prior admission. We performed multivariable logistic regression to adjust for clustering at the patient level to characterize the association of functional impairments and readmission. RESULTS: Patients had a mean (SD) age of 78.5 (7.7) years (range, 65-105 years); 58.4% were female, 84.9% were white, 89.6% reported 3 or more comorbidities, and 86.0% had 1 or more hospitalizations in the previous year. Overall, 48.3% had some level of functional impairment before admission, and 15.5% of hospitalizations were followed by readmission within 30 days. We found a progressive increase in the adjusted risk of readmission as the degree of functional impairment increased: 13.5% with no functional impairment, 14.3% with difficulty with 1 or more instrumental activities of daily living (odds ratio [OR], 1.06; 95% CI, 0.94-1.20), 14.4% with difficulty with 1 or more ADL (OR, 1.08; 95% CI, 0.96-1.21), 16.5% with dependency in 1 to 2 ADLs (OR, 1.26; 95% CI, 1.11-1.44), and 18.2% with dependency in 3 or more ADLs (OR, 1.42; 95% CI, 1.20-1.69). Subanalysis restricted to patients admitted with conditions targeted by Medicare (ie, heart failure, myocardial infarction, and pneumonia) revealed a parallel trend with larger effects for the most impaired (16.9% readmission rate for no impairment vs 25.7% for dependency in 3 or more ADLs [OR, 1.70; 95% CI, 1.04-2.78]). CONCLUSIONS AND RELEVANCE: Functional impairment is associated with increased risk of 30-day all-cause hospital readmission in Medicare seniors, especially those admitted for heart failure, myocardial infarction, or pneumonia. Functional impairment may be an important but underaddressed factor in preventing readmissions for Medicare seniors.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Cohort Studies; Comorbidity; Female; Heart Failure; Humans; Income; Logistic Models; Male; Medicare; Myocardial Infarction; Patient Readmission; Pneumonia; Risk Assessment; Risk Factors; Sex Factors; United States

Gender Differences in Institutional Long-Term Care Transitions. - Mudrazija, Stipica; Thomeer, Mieke Beth; Jacqueline L. Angel (Womens Health Issues, 2015)
INTRODUCTION: This study investigates the relationship between gender, the likelihood of discharge from institutional long-term care (LTC) facilities, and post-discharge living arrangements, highlighting sociodemographic, health, socioeconomic, and family characteristics. METHODS: We use the Health and Retirement Study to examine individuals age 65 and older admitted to LTC facilities between 2000 and 2010 (n = 3,351). We examine discharge patterns using survival analyses that account for the competing risk of death and estimate the probabilities of post-discharge living arrangements using multinomial logistic regression models. RESULTS: Women are more likely than men to be discharged from LTC facilities during the first year of stay. Women are more likely to live alone or with kin after discharge, whereas men are more likely to live with a spouse or transfer to another institution. Gender differences in the availability and use of family support may partly account for the gender disparity of LTC discharge and post-discharge living arrangements. CONCLUSION: Our findings suggest that women and men follow distinct pathways after LTC discharge. As local and federal efforts begin to place more emphasis on the transition from LTC facilities to prior communities (e.g., transitional care initiatives under the Patient Protection and Affordable Care Act), policymakers should take these gender differences into account in the design of community transition programs.
Keywords: Aged; Aged, 80 and over; Continuity of Patient Care; Family Characteristics; Female; Geriatric Assessment; Home Care Services; Humans; Length of Stay; Logistic Models; Long-term Care; Male; Marital Status; Middle Aged; Nursing homes; Patient Discharge; Residence Characteristics; Sex Characteristics; United States

Greater Perceived Age Discrimination in England than the United States: Results from HRS and ELSA. - Rippon, Isla; Zaninotto, Paola; Andrew Steptoe (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: We examined cross-national differences in perceptions of age discrimination in England and the United States. Under the premise that the United States has had age discrimination legislation in place for considerably longer than England, we hypothesized that perceptions of age discrimination would be lower in the United States. METHODS: We analyzed data from two nationally representative studies of aging, the U.S. Health and Retirement Study (n = 4,818) and the English Longitudinal Study of Ageing (n = 7,478). Respondents aged 52 years and older who attributed any experiences of discrimination to their age were treated as cases of perceived age discrimination. We used multivariable logistic regression to estimate the odds ratios of experiencing perceived age discrimination in relation to selected sociodemographic factors. RESULTS: Perceptions of age discrimination were significantly higher in England than the United States, with 34.8% of men and women in England reporting age discrimination compared with 29.1% in the United States. Associations between perceived age discrimination and older age and lower levels of household wealth were observed in both countries, but we found differences between England and the United States in the relationship between perceived age discrimination and education. DISCUSSION: Our study revealed that levels of perceived age discrimination are lower in the United States than England and are less socially patterned. This suggests that differing social and political circumstances in the two countries may have an important role to play.
Keywords: Aged; Aged, 80 and over; Ageism; England; Female; Humans; Longitudinal Studies; Male; Middle Aged; Perception; Surveys and Questionnaires; United States

Harmonizing Measures of Cognitive Performance Across International Surveys of Aging Using Item Response Theory. - Kitty S. Chan; Alden L Gross; Liliana E Pezzin; Jason Brandt; Judith D Kasper (J Aging Health, 2015)
OBJECTIVE: To harmonize measures of cognitive performance using item response theory (IRT) across two international aging studies. METHOD: Data for persons ≥65 years from the Health and Retirement Study (HRS, N = 9,471) and the English Longitudinal Study of Aging (ELSA, N = 5,444). Cognitive performance measures varied (HRS fielded 25, ELSA 13); 9 were in common. Measurement precision was examined for IRT scores based on (a) common items, (b) common items adjusted for differential item functioning (DIF), and (c) DIF-adjusted all items. RESULTS: Three common items (day of date, immediate word recall, and delayed word recall) demonstrated DIF by survey. Adding survey-specific items improved precision but mainly for HRS respondents at lower cognitive levels. DISCUSSION: IRT offers a feasible strategy for harmonizing cognitive performance measures across other surveys and for other multi-item constructs of interest in studies of aging. Practical implications depend on sample distribution and the difficulty mix of in-common and survey-specific items.
Keywords: Aged; Aged, 80 and over; Aging; Cognition; Female; Humans; Internationality; Longitudinal Studies; Male; Psychological Theory; Reproducibility of Results; Surveys and Questionnaires; United Kingdom; United States

Health literacy and the digital divide among older Americans. - Helen G Levy; Alexander T Janke; Kenneth M. Langa (J Gen Intern Med, 2015)
BACKGROUND: Among the requirements for meaningful use of electronic medical records (EMRs) is that patients must be able to interact online with information from their records. However, many older Americans may be unprepared to do this, particularly those with low levels of health literacy. OBJECTIVE: The purpose of the study was to quantify the relationship between health literacy and use of the Internet for obtaining health information among Americans aged 65 and older. DESIGN: We performed retrospective analysis of 2009 and 2010 data from the Health and Retirement Study, a longitudinal survey of a nationally representative sample of older Americans. PARTICIPANTS: Subjects were community-dwelling adults aged 65 years and older (824 individuals in the general population and 1,584 Internet users). MAIN MEASURES: Our analysis included measures of regular use of the Internet for any purpose and use of the Internet to obtain health or medical information; health literacy was measured using the Rapid Estimate of Adult Literacy in Medicine-Revised (REALM-R) and self-reported confidence filling out medical forms. KEY RESULTS: Only 9.7% of elderly individuals with low health literacy used the Internet to obtain health information, compared with 31.9% of those with adequate health literacy. This gradient persisted after controlling for sociodemographic characteristics, health status, and general cognitive ability. The gradient arose both because individuals with low health literacy were less likely to use the Internet at all (OR = 0.36 [95% CI 0.24 to 0.54]) and because, among those who did use the Internet, individuals with low health literacy were less likely to use it to get health or medical information (OR = 0.60 [95% CI 0.47 to 0.77]). CONCLUSION: Low health literacy is associated with significantly less use of the Internet for health information among Americans aged 65 and older. Web-based health interventions targeting older adults must address barriers to substantive use by individuals with low health literacy, or risk exacerbating the digital divide.
Keywords: Age Factors; Aged; Aged, 80 and over; Cohort Studies; Digital Divide; Female; Health Literacy; Humans; Internet; Male; Prospective Studies; Retrospective Studies; Surveys and Questionnaires; United States

Historical improvements in well-being do not hold in late life: Birth- and death-year cohorts in the United States and Germany. - Hülür, Gizem; Ram, Nilam; Denis Gerstorf (Dev Psychol, 2015)
One key objective of life span research is to examine how individual development is shaped by the historical time people live in. Secular trends favoring later-born cohorts on fluid cognitive abilities have been widely documented, but findings are mixed for well-being. It remains an open question whether secular increases in well-being seen in earlier phases of life also manifest in the last years of life. To examine this possibility, we made use of longitudinal data obtained from the mid-1980s until the late 2000s in 2 large national samples in the United States (Health and Retirement Study [HRS]) and Germany (German Socio-Economic Panel [SOEP]). We operationally defined historical time from 2 complementary perspectives: birth-year cohorts based on the years in which people were born (earlier: 1930s vs. later: 1940s) and death-year cohorts based on the years in which people died (earlier: 1990s vs. later: 2000s). To control for relevant covariates, we used case-matched groups based on age (at death) and education and covaried for gender, health, and number of observations. Results from both countries revealed that well-being in old age was indeed developing at higher levels among later-born cohorts. However, for later-deceased cohorts, no evidence for secular increases in well-being was found. To the contrary, later-dying SOEP participants reported lower levels of well-being at age 75 and 2 years prior to death and experienced steeper late-life declines. Our results suggest that secular increases in well-being observed in old age do not manifest in late life, where "manufactured" survival may be exacerbating age- and mortality-related declines.
Keywords: Aged; Aging; Cohort Effect; depression; Epidemiologic Research Design; Female; Germany; Health Status; Health Surveys; Humans; Longitudinal Studies; Male; Propensity Score; United States

Hospitalization Type and Subsequent Severe Sepsis. - Hallie C Prescott; Dickson, R. P.; Mary A M Rogers; Kenneth M. Langa; Lwashyna, T. J. (Am J Respir Crit Care Med, 2015)
RATIONALE: Hospitalization is associated with microbiome perturbation (dysbiosis), and this perturbation is more severe in patients treated with antimicrobials. OBJECTIVES: To evaluate whether hospitalizations known to be associated with periods of microbiome perturbation are associated with increased risk of severe sepsis after hospital discharge. METHODS: We studied participants in the U.S. Health and Retirement Study with linked Medicare claims (1998-2010). We measured whether three hospitalization types associated with increasing severity of probable dysbiosis (non-infection-related hospitalization, infection-related hospitalization, and hospitalization with Clostridium difficile infection [CDI]) were associated with increasing risk for severe sepsis in the 90 days after hospital discharge. We used two study designs: the first was a longitudinal design with between-person comparisons and the second was a self-controlled case series design using within-person comparison. MEASUREMENTS AND MAIN RESULTS: We identified 43,095 hospitalizations among 10,996 Health and Retirement Study-Medicare participants. In the 90 days following non-infection-related hospitalization, infection-related hospitalization, and hospitalization with CDI, adjusted probabilities of subsequent admission for severe sepsis were 4.1% (95% confidence interval [CI], 3.8-4.4%), 7.1% (95% CI, 6.6-7.6%), and 10.7% (95% CI, 7.7-13.8%), respectively. The incidence rate ratio (IRR) of severe sepsis was 3.3-fold greater during the 90 days after hospitalizations than during other observation periods. The IRR was 30% greater after an infection-related hospitalization versus a non-infection-related hospitalization. The IRR was 70% greater after a hospitalization with CDI than an infection-related hospitalization without CDI. CONCLUSIONS: There is a strong dose-response relationship between events known to result in dysbiosis and subsequent severe sepsis hospitalization that is not present for rehospitalization for nonsepsis diagnoses.
Keywords: Aged; Aged, 80 and over; Anti-Bacterial Agents; Clostridioides difficile; Dysbiosis; Enterocolitis, Pseudomembranous; Female; Hospitalization; Humans; Incidence; Information Storage and Retrieval; Longitudinal Studies; Male; Medicare; Patient Readmission; Retrospective Studies; Risk Factors; Sepsis; United States

How do race and Hispanic ethnicity affect nursing home admission? Evidence from the Health and Retirement Study. - Thomeer, Mieke Beth; Mudrazija, Stipica; Jacqueline L. Angel (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: This study investigates how health- and disability-based need factors and enabling factors (e.g., socioeconomic and family-based resources) relate to nursing home admission among 3 different racial and ethnic groups. METHOD: We use Cox proportional hazard models to estimate differences in nursing home admission for non-Hispanic whites, non-Hispanic blacks, and Hispanics from 1998 to 2010 in the Health and Retirement Study (N = 18,952). RESULTS: Racial-ethnic differences in nursing home admission are magnified after controlling for health- and disability-based need factors and enabling factors. Additionally, the degree to which specific factors contribute to risk of nursing home admission varies significantly across racial-ethnic groups. DISCUSSION: Our findings indicate that substantial racial and ethnic variations in nursing home admission continue to exist and that Hispanic use is particularly low. We argue that these differences may demonstrate a significant underuse of nursing homes for racial and ethnic minorities. Alternatively, they could signify different preferences for nursing home care, perhaps due to unmeasured cultural factors or structural obstacles.
Keywords: Activities of Daily Living; African Continental Ancestry Group; Disability Evaluation; European Continental Ancestry Group; Hispanic Americans; Homes for the Aged; Humans; Nursing homes; Proportional Hazards Models; Socioeconomic factors; United States

Incident Diabetes and Mobility Limitations: Reducing Bias Through Risk-set Matching. - Ezra I. Fishman (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: Increased prevalence of diabetes in the U.S. population could contribute substantially to increases in disability at older ages. Previous studies have examined the association between prevalent diabetes and various impairments and disabilities. Methods considering incident, rather than prevalent, diabetes as the exposure of interest can reduce bias in estimates of these associations. METHODS: Risk-set matching, a type of propensity score matching meant to handle time-varying exposures, was used to estimate the relationship between incident diabetes and mobility limitations among adults in the Health and Retirement Study. This approach ensures that covariates precede diabetes onset rather than follow it. RESULTS: Individuals who were diagnosed with diabetes during the study period accumulated more subsequent mobility limitations than were accumulated by matched controls. Among observationally similar pairs of individuals, those who developed diabetes reported an average of 24.9% more mobility limitations at study exit than those who did not. CONCLUSIONS: The magnitude of the relationship between diabetes and limitations estimated in this article is smaller than that presented in previous studies, but the method presented here is likely to provide a less-biased estimate of the association between diabetes and accumulation of mobility limitations.
Keywords: Bias; Diabetes Mellitus; Female; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Mobility Limitation; Propensity Score; Risk Assessment; Risk Factors; Socioeconomic factors; United States

Increase in Disability Prevalence Before Hip Fracture. - Irena Cenzer; W John Boscardin; Christine S Ritchie; Margaret Wallhagen; Kenneth E Covinsky (J Am Geriatr Soc, 2015)
OBJECTIVES: To establish the prevalence and correlates of disability during the 2 years before hip fracture. DESIGN: Data from participants who experienced hip fracture in the Health and Retirement Study (HRS) with hip fracture identified using linked Medicare claims. Each participant was interviewed at varying time points in the 2 years before hip fracture. Disability was defined as self-report of the need for assistance in any activity of daily living (walking across the room, eating, bathing, dressing, using the toilet, transferring). Based on the timing between interview and hip fracture, prevalence of disability was calculated in the cohort as a whole over the 2 years before hip fracture and in subgroups defined according to demographic and clinical characteristics. SETTING: The HRS is a nationally representative longitudinal study (1992-2010). PARTICIPANTS: HRS participants aged ≥65 with hip fracture (mean age at fracture 84, 77% female). RESULTS: The adjusted prevalence of disability was 20% (95% confidence interval (CI) = 14-25%) 2 years before hip fracture, with little change until approximately 10 months before fracture, when it started to rise, reaching 44% (95% CI = 33-55%) in the month before hip fracture. The prevalence of disability was highest in the last month before fracture for persons aged 85 and older (53%) and for those with dementia (60%). CONCLUSION: Care models for hip fracture need to consider not only the acute medical and surgical needs, but also the high level of need for supportive care and caregiver assistance that chronically disabled individuals require.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Dementia; Disability Evaluation; Disabled Persons; Educational Status; Female; Health Surveys; Hip Fractures; Humans; Income; Male; Mobility Limitation; Prevalence; United States

A Life Course Approach to Inequality: Examining Racial/Ethnic Differences in the Relationship between Early Life Socioeconomic Conditions and Adult Health Among Men. - Taylor W. Hargrove; Tyson H Brown (Ethn Dis, 2015)
OBJECTIVE: Previous research has documented a relationship between childhood socioeconomic conditions and adult health, but less is known about racial/ethnic differences in this relationship, particularly among men. This study utilizes a life course approach to investigate racial/ethnic differences in the relationships among early and later life socioeconomic circumstances and health in adulthood among men. DESIGN: Panel data from the Health and Retirement Study and growth curve models are used to examine group differences in the relationships among childhood and adult socioeconomic factors and age-trajectories of self-rated health among White, Black and Mexican American men aged 51-77 years (N=4147). RESULTS: Multiple measures of childhood socioeconomic status (SES) predict health in adulthood for White men, while significantly fewer measures of childhood SES predict health for Black and Mexican American men. Moreover, the health consequences of childhood SES diminish with age for Black and Mexican American men. The childhood SES-adult health relationship is largely explained by measures of adult SES for White men. CONCLUSIONS: The life course pathways linking childhood SES and adult health differ by race/ethnicity among men. Similar to arguments that the universality of the adult SES-health relationship should not be assumed, results from our study suggest that scholars should not assume that the significance and nature of the association between childhood SES and health in adulthood is similar across race/ethnicity among men.
Keywords: Adult; Aged; ethnicity; Humans; Life Change Events; Male; Men's health; Middle Aged; Racial Groups; Socioeconomic factors; United States

Lifespan and Healthspan: Past, Present, and Promise. - Eileen M. Crimmins (Gerontologist, 2015)
The past century was a period of increasing life expectancy throughout the age range. This resulted in more people living to old age and to spending more years at the older ages. It is likely that increases in life expectancy at older ages will continue, but life expectancy at birth is unlikely to reach levels above 95 unless there is a fundamental change in our ability to delay the aging process. We have yet to experience much compression of morbidity as the age of onset of most health problems has not increased markedly. In recent decades, there have been some reductions in the prevalence of physical disability and dementia. At the same time, the prevalence of disease has increased markedly, in large part due to treatment which extends life for those with disease. Compressing morbidity or increasing the relative healthspan will require "delaying aging" or delaying the physiological change that results in disease and disability. While moving to life expectancies above age 95 and compressing morbidity substantially may require significant scientific breakthroughs; significant improvement in health and increases in life expectancy in the United States could be achieved with behavioral, life style, and policy changes that reduce socioeconomic disparities and allow us to reach the levels of health and life expectancy achieved in peer societies.
Keywords: Aged; Aged, 80 and over; Aging; Disabled Persons; Humans; Life Expectancy; Socioeconomic factors; United States

The "long arm" of childhood health: linking childhood disability to late midlife mental health. - Kenzie Latham (Res Aging, 2015)
A growing body of research underscores the early origins of health in later life; however, relatively little is known about the relationship between childhood physical health and adult mental health. This research explores the relationship between childhood disability and depressive symptoms among a nationally representative sample of late midlife adults (N = 3,572). Using data from Waves 8-10 (2006-2010) of the Health and Retirement Study, a series of ordinary least squares regression models were created to assess the number of depressive symptoms. Childhood disability was significantly associated with higher levels of depressive symptoms; however, late midlife social and health factors accounted for differences between those with and without childhood disability. Late midlife physical health appeared to be a particularly salient mediator. Individuals who experience childhood disability may accumulate more physical impairment over the life course, thus experiencing worse mental health such as greater depressive symptoms in late midlife.
Keywords: Child; depression; Female; Health Status; Humans; Male; Middle Aged; Risk Factors; Surveys and Questionnaires; Time Factors; United States

Longitudinal patient-oriented outcomes in neuropathy: Importance of early detection and falls. - Brian C. Callaghan; Kevin Kerber; Kenneth M. Langa; Banerjee, Mousumi; Rodgers, Ann; Ryan J McCammon; James F. Burke; Eva L Feldman (Neurology, 2015)
OBJECTIVE: To evaluate longitudinal patient-oriented outcomes in peripheral neuropathy over a 14-year time period including time before and after diagnosis. METHODS: The 1996-2007 Health and Retirement Study (HRS)-Medicare Claims linked database identified incident peripheral neuropathy cases (ICD-9 codes) in patients ≥65 years. Using detailed demographic information from the HRS and Medicare claims, a propensity score method identified a matched control group without neuropathy. Patient-oriented outcomes, with an emphasis on self-reported falls, pain, and self-rated health (HRS interview), were determined before and after neuropathy diagnosis. Generalized estimating equations were used to assess differences in longitudinal outcomes between cases and controls. RESULTS: We identified 953 peripheral neuropathy cases and 953 propensity-matched controls. The mean (SD) age was 77.4 (6.7) years for cases, 76.9 (6.6) years for controls, and 42.1% had diabetes. Differences were detected in falls 3.0 years before neuropathy diagnosis (case vs control; 32% vs 25%, p = 0.008), 5.0 years for pain (36% vs 27%, p = 0.002), and 5.0 years for good to excellent self-rated health (61% vs 74%, p < 0.0001). Over time, the proportion of fallers increased more rapidly in neuropathy cases compared to controls (p = 0.002), but no differences in pain (p = 0.08) or self-rated health (p = 0.9) were observed. CONCLUSIONS: In older persons, differences in falls, pain, and self-rated health can be detected 3-5 years prior to peripheral neuropathy diagnosis, but only falls deteriorates more rapidly over time in neuropathy cases compared to controls. Interventions to improve early peripheral neuropathy detection are needed, and future clinical trials should incorporate falls as a key patient-oriented outcome.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Early Diagnosis; Female; Humans; International Classification of Diseases; Longitudinal Studies; Male; Medicare; Patient-Centered Care; Peripheral Nervous System Diseases; Treatment Outcome; United States

Measurement Invariance of Cognitive Abilities Across Ethnicity, Gender, and Time Among Older Americans. - A Nayena Blankson; John J McArdle (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: The aim of this research was to test the invariance of the cognitive variables in the Health and Retirement Study/Asset Health Dynamics Among the Oldest Old studies (HRS/AHEAD) across ethnicity, gender, and time. METHOD: Analyses were conducted using a selected subsample of the HRS/AHEAD data set. The cognitive performance tests measuring episodic memory and mental status were used, and invariance of a two-factor structure was tested using confirmatory factor analyses and multilevel modeling for longitudinal data. RESULTS: Results provided some support for "strict" factorial invariance of the episodic memory and mental status measures across ethnicity and gender. Further support of weak ("metric") measurement invariance was found across time. DISCUSSION: Results of the research further our understanding of invariance of the HRS/AHEAD cognitive ability measures. Further implications are discussed.
Keywords: Aged; Aged, 80 and over; Black People; Female; Hispanic or Latino; Humans; Male; Memory, Episodic; Mental Processes; Middle Aged; Neuropsychological tests; Psychometrics; Psychomotor Performance; Reproducibility of Results; Sex Factors; Time Factors; United States; White People

Multimorbidity redefined: prospective health outcomes and the cumulative effect of co-occurring conditions. - Siran M Koroukian; David F Warner; Owusu, Cynthia; Charles W Given (Prev Chronic Dis, 2015)
INTRODUCTION: Multimorbidity is common among middle-aged and older adults; however the prospective effects of multimorbidity on health outcomes (health status, major health decline, and mortality) have not been fully explored. This study addresses this gap in the literature. METHODS: We used self-reported data from the 2008 and 2010 Health and Retirement Study. Our study population included 13,232 adults aged 50 or older. Our measure of baseline multimorbidity in 2008 was based on the occurrence or co-occurrence of chronic conditions, functional limitations, and/or geriatric syndromes, as follows: MM0, no chronic conditions, functional limitations, or geriatric syndromes; MM1, occurrence (but no co-occurrence) of chronic conditions, functional limitations, or geriatric syndromes; MM2, co-occurrence of any 2 of chronic conditions, functional limitations, or geriatric syndromes; and MM3, co-occurrence of all 3 of chronic conditions, functional limitations, and geriatric syndromes. Outcomes in 2010 included fair or poor health status, major health decline, and mortality. RESULTS: All 3 outcomes were significantly associated with multimorbidity. Compared with MM0 (respectively for fair or poor health and major health decline), the adjusted odds ratios (AORs) and 95% confidence intervals were as follows: 2.61 (1.79-3.78) and 2.20 (1.42-3.41) for MM1; 7.49 (5.20-10.77) and 3.70 (2.40-5.71) for MM2; and 22.66 (15.64-32.83) and 4.72 (3.03-7.37) for MM3. Multimorbidity was also associated with mortality: an adult classified as MM3 was nearly 12 times (AOR, 11.87 [5.72-24.62]) as likely as an adult classified as MM0 to die within 2 years. CONCLUSION: Given the strong and significant association between multimorbidity and prospective health status, major health decline, and mortality, multimorbidity may be used - both in clinical practice and in research - to identify older adults with heightened vulnerability for adverse outcomes.
Keywords: Aged; Aged, 80 and over; Alcohol Drinking; Body Mass Index; Chronic disease; Cognition Disorders; Comorbidity; Cross-Sectional Studies; Data Interpretation, Statistical; ethnicity; Female; Health Status Indicators; Humans; Interviews as Topic; Male; Middle Aged; Mobility Limitation; Outcome Assessment, Health Care; Prospective Studies; Recurrence; Retirement; Self Report; Smoking; Social Class; Syndrome; United States; Vulnerable Populations

Polygenic risk, stressful life events and depressive symptoms in older adults: a polygenic score analysis. - Musliner, Katherine L.; Seiffudin, Fayaz; Judy, J. A.; Pirooznia, Mehdi; Goes, Fernando S.; Zandi, Peter P. (Psychol Med, 2015)
BACKGROUND: Previous studies suggest that the relationship between genetic risk and depression may be moderated by stressful life events (SLEs). The goal of this study was to assess whether SLEs moderate the association between polygenic risk of major depressive disorder (MDD) and depressive symptoms in older adults. METHOD: We used logistic and negative binomial regressions to assess the associations between polygenic risk, SLEs and depressive symptoms in a sample of 8761 participants from the Health and Retirement Study. Polygenic scores were derived from the Psychiatric Genomics Consortium genome-wide association study of MDD. SLEs were operationalized as a dichotomous variable indicating whether participants had experienced at least one stressful event during the previous 2 years. Depressive symptoms were measured using an eight-item Center for Epidemiologic Studies Depression Scale subscale and operationalized as both a dichotomous and a count variable. RESULTS: The odds of reporting four or more depressive symptoms were over twice as high among individuals who experienced at least one SLE (odds ratio 2.19, 95% confidence interval 1.86-2.58). Polygenic scores were significantly associated with depressive symptoms (β = 0.21, p ⩽ 0.0001), although the variance explained was modest (pseudo r 2 = 0.0095). None of the interaction terms for polygenic scores and SLEs was statistically significant. CONCLUSIONS: Polygenic risk and SLEs are robust, independent predictors of depressive symptoms in older adults. Consistent with an additive model, we found no evidence that SLEs moderated the association between common variant polygenic risk and depressive symptoms.
Keywords: depression; Depressive Disorder, Major; Female; Genetic Predisposition to Disease; Humans; Life Change Events; Male; Middle Aged; Multifactorial Inheritance; Odds Ratio; Risk Factors; United States

Prostate Cancer Screening Among American Indians and Alaska Natives: The Health and Retirement Survey, 1996-2008. - R. Turner Goins; Marc B Schure; Carolyn Noonan; Dedra S. Buchwald (Prev Chronic Dis, 2015)
INTRODUCTION: Among US men, prostate cancer is the leading malignancy diagnosed and the second leading cause of cancer death. Disparities in cancer screening rates exist between American Indians/Alaska Natives and other racial/ethnic groups. Our study objectives were to examine prostate screening at 5 time points over a 12-year period among American Indian/Alaska Native men aged 50 to 75 years, and to compare their screening rates to African American men and white men in the same age group. METHODS: We analyzed Health and Retirement Study data for 1996, 1998, 2000, 2004, and 2008. Prostate screening was measured by self-report of receipt of a prostate examination within the previous 2 years. Age-adjusted prevalence was estimated for each year. We used regression with generalized estimating equations to compare prostate screening prevalence by year and race. RESULTS: Our analytic sample included 119 American Indian/Alaska Native men (n = 333 observations), 1,359 African American men (n = 3,704 observations), and 8,226 white men (n = 24,292 observations). From 1996 to 2008, prostate screening rates changed for each group: from 57.0% to 55.7% among American Indians/Alaska Natives, from 62.0% to 71.2% among African Americans, and from 68.6% to 71.3% among whites. Although the disparity between whites and African Americans shrank over time, it was virtually unchanged between whites and American Indians/Alaska Natives. CONCLUSION: As of 2008, American Indians/Alaska Natives were less likely than African Americans and whites to report a prostate examination within the previous 2 years. Prevalence trends indicated a modest increase in prostate cancer screening among African Americans and whites, while rates remained substantially lower for American Indians/Alaska Natives.
Keywords: Aged; Alaska; Analysis of Variance; Black or African American; Health Behavior; Health Surveys; Healthcare Disparities; Humans; Indians, North American; Male; Mass Screening; Middle Aged; Prevalence; Prostatic Neoplasms; Regression Analysis; Retirement; Self Report; Surveys and Questionnaires; United States; White People

Race/Ethnic Differentials in the Health Consequences of Caring for Grandchildren for Grandparents. - Chen, Feinian; Christine A Mair; Bao, Luoman; Yang Claire Yang (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: The phenomenon of grandparents caring for grandchildren is disproportionately observed among different racial/ethnic groups in the United States. This study examines the influence of childcare provision on older adults' health trajectories in the United States with a particular focus on racial/ethnic differentials. METHOD: Analyzing nationally representative, longitudinal data on grandparents over the age of 50 from the Health and Retirement Study (1998-2010), we conduct growth curve analysis to examine the effect of living arrangements and caregiving intensity on older adults' health trajectories, measured by changing Frailty Index (FI) in race/ethnic subsamples. We use propensity score weighting to address the issue of potential nonrandom selection of grandparents into grandchild care. RESULTS: We find that some amount of caring for grandchildren is associated with a reduction of frailty for older adults, whereas coresidence with grandchildren results in health deterioration. For non-Hispanic black grandparents, living in a skipped generation household appears to be particularly detrimental to health. We also find that Hispanic grandparents fare better than non-Hispanic black grandparents despite a similar level of caregiving and rate of coresidence. Finally, financial and social resources assist in buffering some of the negative effects of coresidence on health (though this effect also differs by race/ethnicity). DISCUSSION: Our findings suggest that the health consequences of grandchild care are mixed across different racial/ethnic groups and are further shaped by individual characteristics as well as perhaps cultural context.
Keywords: Aged; Black People; Female; Frail Elderly; Health Status; Health Status Disparities; Hispanic or Latino; Humans; Intergenerational Relations; Longitudinal Studies; Male; Middle Aged; Parenting; Residence Characteristics; Socioeconomic factors; United States

A Research Note on Transitions in Out-of-Pocket Spending on Dental Services. - Richard J. Manski; John F Moeller; Haiyan Chen; Jody Schimmel Hyde; John V Pepper; Patricia A St Clair (Res Aging, 2015)
OBJECTIVE: We analyze correlates of the direction and magnitude of changes in out-of-pocket (OOP) payments for dental care by older Americans over a recent 4-year period. METHODS: We analyzed data from the 2006 and 2008 waves of the Health and Retirement Study. We estimated multinomial logistic models of the direction and linear regression models of the amounts of OOP changes over survey periods. RESULTS: Financial-based factors were more strongly associated with the direction and magnitude of changing self-payments for dental care than were health factors. DISCUSSION: Findings suggested that dental coverage, income, and wealth and changes in these financial factors were more strongly correlated with the persistence of and changes in OOP payments for dental care over time than were health status and changes in health status. The sensitivity to dental coverage changes should be considered as insurance and retirement policy reforms are deliberated.
Keywords: Aged; Aged, 80 and over; Dental Care; Female; Health Expenditures; Humans; Insurance, Dental; Longitudinal Studies; Male; Middle Aged; United States

Social Relationships, Gender, and Recovery From Mobility Limitation Among Older Americans. - Kenzie Latham; Philippa J Clarke; Gregory Pavela (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: Evidence suggests social relationships may be important facilitators for recovery from functional impairment, but the extant literature is limited in its measurement of social relationships including an over emphasis on filial social support and a paucity of nationally representative data. METHODS: Using data from Waves 4-9 (1998-2008) of the Health and Retirement Study (HRS), this research examines the association between social relationships and recovery from severe mobility limitation (i.e., difficulty walking one block or across the room) among older Americans. Using a more nuanced measure of recovery that includes complete and partial recovery, a series of discrete-time event history models with multiple competing recovery outcomes were estimated using multinomial logistic regression. RESULTS: Providing instrumental support to peers increased the odds of complete and partial recovery from severe mobility limitation, net of numerous social, and health factors. Having relatives living nearby decreased the odds of complete recovery, while being engaged in one's neighborhood increased the odds of partial recovery. The influence of partner status on partial and complete recovery varied by gender, whereby partnered men were more likely to experience recovery relative to partnered women. The effect of neighborhood engagement on partial recovery also varied by gender. Disengaged women were the least likely to experience partial recovery compared with any other group. DISCUSSION: The rehabilitative potential of social relationships has important policy implications. Interventions aimed at encouraging older adults with mobility limitation to be engaged in their neighborhoods and/or provide instrumental support to peers may improve functional health outcomes.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Family; Female; Humans; Interpersonal Relations; Male; Middle Aged; Mobility Limitation; Peer Group; Recovery of Function; Residence Characteristics; Sex Factors; Social Support; United States

Socioeconomic stratification and multidimensional health trajectories: evidence of convergence in later old age. - Xiao Xu; Jersey Liang; Joan M. Bennett; Anda Botoseneanu; Heather G. Allore (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: This research sought to examine socioeconomic stratification in the joint trajectories of physical, emotional, and cognitive functioning among older Americans and how it differs by age groups. METHODS: We used data from a nationally representative sample of 9,237 Americans age 65 or older from the Health and Retirement Study, who were observed biennially from 1998 to 2010. Joint trajectories of physical, emotional, and cognitive functioning were characterized using a group-based mixture model. We then applied multinomial logistic regression analysis to evaluate their linkages with socioeconomic status and how the linkages differ by age groups. RESULTS: We identified four distinct patterns of joint changes in physical, emotional, and cognitive functioning over time. Accounting for 29.3%, 23.5%, 24.5%, and 22.6% of the older Americans, respectively, these trajectory patterns characterized groups of individuals experiencing minimal to severe levels of impairment and deterioration. Lower education, income, and net worth were associated with trajectories featuring greater impairment or more rapid deterioration in these functional dimensions. Disparities based on education, however, attenuated in later old age, whereas health benefits associated with higher income and higher net worth persisted into advanced age. DISCUSSION: Distinct patterns of joint trajectories of physical, emotional, and cognitive functioning exist in old age. There were significant socioeconomic differences in the joint trajectories, with education-based inequality in health converging in later old age. Further research identifying strategies to alleviate the disproportionate burden of poor multidimensional health trajectories in lower socioeconomic groups is important.
Keywords: Aged; Aged, 80 and over; Aging; Cognition Disorders; Disabled Persons; Educational Status; Female; Health Status; Humans; Male; Social Class; United States

Substance-use coping and self-rated health among US middle-aged and older adults. - Pia M Mauro; Sarah L. Canham; Silvia S Martins; Adam P Spira (Addict Behav, 2015)
The prevalence of alcohol, drug, and tobacco use among US middle-aged and older adults is increasing. A subset of this population uses substances to cope with stress, but the characteristics of these individuals, and the association between substance-use coping and health outcomes remain unclear. We identified correlates of substance-use coping and measured its association with self-rated health in a community-based sample of adults aged 54-99 in the Health and Retirement Study (HRS). In the 2008 HRS, 1351 participants reported their frequency of prescription/other drug-, alcohol-, and cigarette-use coping with stress and reported self-rated health (excellent/very good, good, or fair/poor); 1201 of these participants also reported self-rated health in 2010. One in six participants frequently used substances to cope. The oldest participants were least likely to engage in frequent alcohol-use coping. Those with elevated depressive symptoms were more likely to frequently engage in cigarette- and prescription/other drug-use coping. In multivariable-adjusted analyses, participants who frequently used cigarettes (compared to participants who infrequently used cigarettes) to cope had 2.7 times (95% CI=1.1-6.7) the odds of poor (vs. excellent) self-rated health. Relative to participants who infrequently used prescription/other drugs to cope, participants who frequently used prescription/other drugs to cope had 2.4 times (95% CI=1.1-5.1) the odds of reporting poor self-rated health. The association between prescription/other drug-use coping in 2008 and self-rated health in 2010 was statistically significant (relative OR=3.5, 95% CI=1.7-7.2). Participants engaging in substance-use coping likely have particular demographic and clinical characteristics. Interventions to reduce substance-use coping may prevent adverse health outcomes.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Alcohol Drinking; depression; Female; Health Status; Humans; Male; Middle Aged; Smoking; Substance-Related Disorders; United States

Variation in the effects of family background and birth region on adult obesity: results of a prospective cohort study of a Great Depression-era American cohort. - Hui Zheng; Dmitry Tumin (BMC Public Health, 2015)
BACKGROUND: Studies have identified prenatal and early childhood conditions as important contributors to weight status in later life. To date, however, few studies have considered how weight status in adulthood is shaped by regional variation in early-life conditions, rather than the characteristics of the individual or their family. Furthermore, gender and life course differences in the salience of early life conditions to weight status remain unclear. This study investigates whether the effect of family background and birth region on adult obesity status varies by gender and over the life course. METHODS: We used data from a population-based cohort of 6,453 adults from the Health and Retirement Study, 1992-2008. Early life conditions were measured retrospectively at and after the baseline. Obesity was calculated from self-reported height and weight. Logistic models were used to estimate the net effects of family background and birth region on adulthood obesity risk after adjusting for socioeconomic factors and health behaviors measured in adulthood. Four economic and demographic data sets were used to further test the birthplace effect. RESULTS: At ages 50-61, mother's education and birth region were associated with women's obesity risk, but not men's. Each year's increase in mother's education significantly reduces the odds of being obese by 6% (OR = 0.94; 95% CI: 0.92, 0.97) among women, and this pattern persisted at ages 66-77. Women born in the Mountain region were least likely to be obese in late-middle age and late-life. Measures of per capita income and infant mortality rate in the birth region were also associated with the odds of obesity among women. CONCLUSIONS: Women's obesity status in adulthood is influenced by early childhood conditions, including regional conditions, while adulthood health risk factors may be more important for men's obesity risk. Biological and social mechanisms may account for the gender difference.
Keywords: Aged; Aged, 80 and over; Body Weight; Cohort Studies; ethnicity; Family Characteristics; Female; Health Behavior; Humans; Interviews as Topic; Logistic Models; Male; Middle Aged; Obesity; Prospective Studies; Qualitative Research; Retirement; Risk Factors; Socioeconomic factors; United States

Weight Discrimination and Risk of Mortality. - Angelina R Sutin; Yannick Stephan; Antonio Terracciano (Psychol Sci, 2015)
Discrimination based on weight is a stressful social experience linked to declines in physical and mental health. We examined whether this harmful association extends to risk of mortality. Participants in the Health and Retirement Study (HRS; N = 13,692) and the Midlife in the United States Study (MIDUS; N = 5,079) reported on perceived discriminatory experiences and attributed those experiences to a number of personal characteristics, including weight. Weight discrimination was associated with an increase in mortality risk of nearly 60% in both HRS participants (hazard ratio = 1.57, 95% confidence interval = [1.34, 1.84]) and MIDUS participants (hazard ratio = 1.59, 95% confidence interval = [1.09, 2.31]). This increased risk was not accounted for by common physical and psychological risk factors. The association between mortality and weight discrimination was generally stronger than that between mortality and other attributions for discrimination. In addition to its association with poor health outcomes, weight discrimination may shorten life expectancy.
Keywords: Adult; Aged; Female; Humans; Male; Mental Health; Middle Aged; Mortality; Overweight; Prejudice; Proportional Hazards Models; Social Discrimination; Stress, Psychological; Surveys and Questionnaires; United States

Chiropractic use in the Medicare population: prevalence, patterns, and associations with 1-year changes in health and satisfaction with care. - Paula A Weigel; Jason Hockenberry; Frederic D Wolinsky (J Manipulative Physiol Ther, 2014)
OBJECTIVE: The purpose of this study was to examine how chiropractic care compares to medical treatments on 1-year changes in self-reported function, health, and satisfaction with care measures in a representative sample of Medicare beneficiaries. METHODS: Logistic regression using generalized estimating equations is used to model the effect of chiropractic relative to medical care on decline in 5 functional measures and 2 measures of self-rated health among 12170 person-year observations. The same method is used to estimate the comparative effect of chiropractic on 6 satisfaction with care measures. Two analytic approaches are used, the first assuming no selection bias and the second using propensity score analyses to adjust for selection effects in the outcome models. RESULTS: The unadjusted models show that chiropractic is significantly protective against 1-year decline in activities of daily living, lifting, stooping, walking, self-rated health, and worsening health after 1 year. Persons using chiropractic are more satisfied with their follow-up care and with the information provided to them. In addition to the protective effects of chiropractic in the unadjusted model, the propensity score results indicate a significant protective effect of chiropractic against decline in reaching. CONCLUSION: This study provides evidence of a protective effect of chiropractic care against 1-year declines in functional and self-rated health among Medicare beneficiaries with spine conditions, and indications that chiropractic users have higher satisfaction with follow-up care and information provided about what is wrong with them.
Keywords: Aged; Aged, 80 and over; Female; Humans; Male; Manipulation, Chiropractic; Medicare; Patient Satisfaction; Time Factors; Treatment Outcome; United States

Cohort differences in the marriage-health relationship for midlife women. - Nicky J Newton; Lindsay H Ryan; Rachel T King; Jacqui Smith (Soc Sci Med, 2014)
The present study aimed to identify potential cohort differences in midlife women's self-reported functional limitations and chronic diseases. Additionally, we examined the relationship between marital status and health, comparing the health of divorced, widowed, and never married women with married women, and how this relationship differs by cohort. Using data from the Health and Retirement Study (HRS), we examined potential differences in the level of functional limitations and six chronic diseases in two age-matched cohorts of midlife women in the United States: Pre-Baby Boomers, born 1933-1942, N = 4574; and Early Baby Boomers, born 1947-1956, N = 2098. Linear and logistic regressions tested the marital status/health relationship, as well as cohort differences in this relationship, controlling for age, education, race, number of marriages, length of time in marital status, physical activity, and smoking status. We found that Early Baby Boom women had fewer functional limitations but higher risk of chronic disease diagnosis compared to Pre-Baby Boom women. In both cohorts, marriage was associated with lower disease risk and fewer functional limitations; however, never-married Early Baby Boom women had more functional limitations, as well as greater likelihood of lung disease than their Pre-Baby Boom counterparts (OR = 0.28). Results are discussed in terms of the stress model of marriage, and the association between historical context and cohort health (e.g., the influence of economic hardship vs. economic prosperity). Additionally, we discuss cohort differences in selection into marital status, particularly as they pertain to never-married women, and the relative impact of marital dissolution on physical health for the two cohorts of women.
Keywords: Age Factors; Aged; Chronic disease; Cohort Studies; Female; Health Status; Health Surveys; Humans; Marital Status; Marriage; Middle Aged; Mobility Limitation; Risk Factors; Socioeconomic factors; United States

Cohort Profile: the Health and Retirement Study (HRS). - Amanda Sonnega; Jessica Faul; Mary Beth Ofstedal; Kenneth M. Langa; John W R Phillips; David R Weir (Int J Epidemiol, 2014)
The Health and Retirement Study (HRS) is a nationally representative longitudinal survey of more than 37 000 individuals over age 50 in 23 000 households in the USA. The survey, which has been fielded every 2 years since 1992, was established to provide a national resource for data on the changing health and economic circumstances associated with ageing at both individual and population levels. Its multidisciplinary approach is focused on four broad topics-income and wealth; health, cognition and use of healthcare services; work and retirement; and family connections. HRS data are also linked at the individual level to administrative records from Social Security and Medicare, Veteran's Administration, the National Death Index and employer-provided pension plan information. Since 2006, data collection has expanded to include biomarkers and genetics as well as much greater depth in psychology and social context. This blend of economic, health and psychosocial information provides unprecedented potential to study increasingly complex questions about ageing and retirement. The HRS has been a leading force for rapid release of data while simultaneously protecting the confidentiality of respondents. Three categories of data-public, sensitive and restricted-can be accessed through procedures described on the HRS website (hrsonline.isr.umich.edu).
Keywords: Aged; Female; Genetic Predisposition to Disease; Health Status; Humans; Longitudinal Studies; Male; Mental Health; Middle Aged; Physical Fitness; Retirement; United States

Cumulative inequality and racial disparities in health: private insurance coverage and black/white differences in functional limitations. - Ben Lennox Kail; Miles G Taylor (J Gerontol B Psychol Sci Soc Sci, 2014)
OBJECTIVES: To test different forms of private insurance coverage as mediators for racial disparities in onset, persistent level, and acceleration of functional limitations among Medicare age-eligible Americans. METHOD: Data come from 7 waves of the Health and Retirement Study (1996-2008). Onset and progression latent growth models were used to estimate racial differences in onset, level, and growth of functional limitations among a sample of 5,755 people aged 65 and older in 1996. Employer-provided insurance, spousal insurance, and market insurance were next added to the model to test how differences in private insurance mediated the racial gap in physical limitations. RESULTS: In baseline models, African Americans had larger persistent level of limitations over time. Although employer-provided, spousal provided, and market insurances were directly associated with lower persistent levels of limitation, only differences in market insurance accounted for the racial disparities in persistent level of limitations. DISCUSSION: Results suggest private insurance is important for reducing functional limitations, but market insurance is an important mediator of the persistently larger level of limitations observed among African Americans.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Black or African American; Cross-Sectional Studies; Female; Health Status Disparities; Hispanic or Latino; Humans; Insurance Coverage; Insurance, Health; Longitudinal Studies; Male; Medicare; Socioeconomic factors; United States

Death certificates underestimate infections as proximal causes of death in the U.S. - Govindan, Sushant; Shapiro, Letitia; Kenneth M. Langa; Theodore J Iwashyna (PLoS One, 2014)
BACKGROUND: Death certificates are a primary data source for assessing the population burden of diseases; however, there are concerns regarding their accuracy. Diagnosis-Related Group (DRG) coding of a terminal hospitalization may provide an alternative view. We analyzed the rate and patterns of disagreement between death certificate data and hospital claims for patients who died during an inpatient hospitalization. METHODS: We studied respondents from the Health and Retirement Study (a nationally representative sample of older Americans who had an inpatient death documented in the linked Medicare claims from 1993-2007). Causes of death abstracted from death certificates were aggregated to the standard National Center for Health Statistics List of 50 Rankable Causes of Death. Centers for Medicare and Medicaid Services (CMS)-DRGs were manually aggregated into a parallel classification. We then compared the two systems via 2×2, focusing on concordance. Our primary analysis was agreement between the two data sources, assessed with percentages and Cohen's kappa statistic. RESULTS: 2074 inpatient deaths were included in our analysis. 36.6% of death certificate cause-of-death codes agreed with the reason for the terminal hospitalization in the Medicare claims at the broad category level; when re-classifying DRGs without clear alignment as agreements, the concordance only increased to 61%. Overall Kappa was 0.21, or "fair." Death certificates in this cohort redemonstrated the conventional top 3 causes of death as diseases of the heart, malignancy, and cerebrovascular disease. However, hospitalization claims data showed infections, diseases of the heart, and cerebrovascular disease as the most common diagnoses for the same terminal hospitalizations. CONCLUSION: There are significant differences between Medicare claims and death certificate data in assigning cause of death for inpatients. The importance of infections as proximal causes of death is underestimated by current death certificate-based strategies.
Keywords: Cause of Death; Death Certificates; Hospitalization; Humans; Infections; Medicare; United States

Dental usage under changing economic conditions. - Richard J. Manski; John F Moeller; Haiyan Chen; Jody Schimmel; Patricia A St Clair; John V Pepper (J Public Health Dent, 2014)
OBJECTIVE: The purpose of this article is to examine the relationship between changes in household finances (wealth and income) and changes in dental utilization at the onset of the recent recession in a population of older Americans. METHODS: Data from the Health and Retirement Study (HRS) were analyzed for U.S. individuals aged 51 years and older during the 2006 and 2008 waves of the HRS. We estimated logistic models of (a) starting and (b) stopping dental use between 2006 and 2008 survey periods as a function of changes in household wealth and income, controlling for other potentially confounding covariates. RESULTS: We found that only when household wealth falls by 50 percent or more were older adults less likely to seek dental care. Changes in household income and other changes in household wealth were not associated with changes in dental utilization among this population. CONCLUSIONS: Older Americans' dental care utilization appeared to be fairly resilient to changes in household finances; only when wealth fell by 50 percent or more did individuals decrease dental use. This finding might extend to other health-care services that are preventive, routine, and relatively inexpensive.
Keywords: Dental Health Services; Financing, Personal; Humans; Middle Aged; United States

Depression and risk of hospitalization for pneumonia in a cohort study of older Americans. - Dimitry S Davydow; Catherine L Hough; Zivin, Kara; Kenneth M. Langa; Wayne J Katon (J Psychosom Res, 2014)
OBJECTIVE: The aim of this study is to determine if depression is independently associated with risk of hospitalization for pneumonia after adjusting for demographics, medical comorbidity, health-risk behaviors, baseline cognition and functional impairments. METHODS: This secondary analysis of prospectively collected data examined a population-based sample of 6704 Health and Retirement Study (HRS) (1998-2008) participants>50years old who consented to have their interviews linked to their Medicare claims and were without a dementia diagnosis. The eight-item Center for Epidemiologic Studies Depression Scale and/or International Classification of Disease, Ninth Revision, Clinical Modification (ICD-9-CM) depression diagnoses were used to identify baseline depression. ICD-9-CM diagnoses were used to identify hospitalizations for which the principal discharge diagnosis was for bacterial or viral pneumonia. The odds of hospitalization for pneumonia for participants with depression relative to those without depression were estimated using logistic regression models. Population attributable fractions were calculated to determine the extent that hospitalizations for pneumonia could be attributable to depression. RESULTS: After adjusting for demographic characteristics, clinical factors, and health-risk behaviors, depression was independently associated with increased odds of hospitalization for pneumonia (odds ratio [OR]: 1.28, 95% confidence interval [95%CI]: 1.08, 1.53). This association persisted after adjusting for baseline cognition and functional impairments (OR: 1.24, 95%CI: 1.03, 1.50). In this cohort, 6% (95%CI: 2%, 10%) of hospitalizations for pneumonia were potentially attributable to depression. CONCLUSION: Depression is independently associated with increased odds of hospitalization for pneumonia. This study provides additional rationale for integrating mental health care into medical settings in order to improve outcomes for older adults.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Comorbidity; depression; Depressive Disorder; Female; Hospitalization; Humans; Logistic Models; Male; Middle Aged; Odds Ratio; Pneumonia; Risk Assessment; Risk Factors; United States

The disability burden associated with stroke emerges before stroke onset and differentially affects blacks: results from the health and retirement study cohort. - Benjamin D Capistrant; Nicte I Mejia; Sze Y Liu; Qianyi Wang; M. Maria Glymour (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND: Few longitudinal studies compare changes in instrumental activities of daily living (IADLs) among stroke-free adults to prospectively document IADL changes among adults who experience stroke. We contrast annual declines in IADL independence for older individuals who remain stroke free to those for individuals who experienced stroke. We also assess whether these patterns differ by sex, race, or Southern birthplace. METHODS: Health and Retirement Study participants who were stroke free in 1998 (n = 17,741) were followed through 2010 (average follow-up = 8.9 years) for self- or proxy-reported stroke. We used logistic regressions to compare annual changes in odds of self-reported independence in six IADLs among those who remained stroke free throughout follow-up (n = 15,888), those who survived a stroke (n = 1,412), and those who had a stroke and did not survive to participate in another interview (n = 442). We present models adjusted for demographic and socioeconomic covariates and also stratified on sex, race, and Southern birthplace. RESULTS: Compared with similar cohort members who remained stroke free, participants who developed stroke had faster declines in IADL independence and lower probability of IADL independence prior to stroke. After stroke, independence declined at an annual rate similar to those who did not have stroke. The black-white disparity in IADL independence narrowed poststroke. CONCLUSION: Racial differences in IADL independence are apparent long before stroke onset. Poststroke differences in IADL independence largely reflect prestroke disparities.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Black or African American; Cohort Studies; Disabled Persons; Female; Humans; Male; Prospective Studies; Stroke; United States; White People

Does duration of spousal caregiving affect risk of depression onset? Evidence from the Health and Retirement Study. - Benjamin D Capistrant; Lisa F Berkman; M. Maria Glymour (Am J Geriatr Psychiatry, 2014)
OBJECTIVES: To assess the association of current and long-term spousal caregiving with risk of depression in a nationally (U.S.) representative sample of older adults. METHODS: We studied married and depression-free Health and Retirement Study respondents aged 50 years and older (n = 9,420) at baseline from 2000 to 2010. Current (≥14 hours per week of help with instrumental/activities of daily living for a spouse in the most recent biennial survey) and long-term caregiving (care at two consecutive surveys) were used to predict onset of elevated depressive symptoms (≥3 on a modified Centers for Epidemiologic Studies Depression scale) with discrete-time hazards models and time-updated exposure and covariate information. RESULTS: Current caregiving was associated with significant elevations in risk of depression onset (hazard ratio: 1.64; Wald χ(2), 1 df: 28.34; p <0.0001). Effect estimates for long-term caregiving were similar (hazard ratio: 1.52, Wald χ(2), 1 df: 3.63; p = 0.06). CONCLUSIONS: Current spousal caregiving significantly predicted onset of depression; the association was not exacerbated by longer duration of caregiving.
Keywords: Aged; Caregivers; depression; Female; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; Retirement; Risk Factors; Spouses; Time Factors; United States

Factors influencing the use of intensive procedures at the end of life. - Evan C Tschirhart; Qingling Du; Amy Kelley (J Am Geriatr Soc, 2014)
OBJECTIVES: To examine individual and regional factors associated with the use of intensive medical procedures in the last 6 months of life. DESIGN: Retrospective cohort study. SETTING: The Health and Retirement Study (HRS), a longitudinal nationally representative cohort of older adults. PARTICIPANTS: HRS decedents aged 66 and older (N = 3,069). MEASUREMENTS: Multivariable logistic regression was used to evaluate associations between individual and regional factors and receipt of five intensive procedures: intubation and mechanical ventilation, tracheostomy, gastrostomy tube insertion, enteral and parenteral nutrition, or cardiopulmonary resuscitation in the last 6 months of life. RESULTS: Approximately 18% of subjects (n = 546) underwent at least one intensive procedure in the last 6 months of life. Characteristics significantly associated with lower odds of an intensive procedure included aged 85-94 (vs 65-74, adjusted odds ratio (AOR) = 0.67, 95% confidence interval (CI) = 0.51-0.90), Alzheimer's disease (AOR = 0.71, 95% CI = 0.54-0.94), cancer (AOR = 0.60, 95% CI = 0.43-0.85), nursing home residence (AOR = 0.70, 95% CI = 0.50-0.97), and having an advance directive (AOR = 0.71, 95% CI = 0.57-0.89). In contrast, living in a region with higher hospital care intensity (AOR = 2.16, 95% CI = 1.48-3.13) and black race (AOR = 2.02, 95% CI = 1.52-2.69) each doubled one's odds of undergoing an intensive procedure. CONCLUSION: Individual characteristics and regional practice patterns are important determinants of intensive procedure use in the last 6 months of life. The effect of nonclinical factors highlights the need to better align treatments with individual preferences.
Keywords: Advance directives; Aged; Aged, 80 and over; Alzheimer disease; Cause of Death; Chronic disease; Critical Care; Female; Homes for the Aged; Humans; Life Support Care; Logistic Models; Male; Multivariate Analysis; Neoplasms; Nursing homes; Odds Ratio; Terminal Care; United States; Utilization Review

Fine particulate matter air pollution and cognitive function among older US adults. - Jennifer A Ailshire; Eileen M. Crimmins (Am J Epidemiol, 2014)
Existing research on the adverse health effects of exposure to pollution has devoted relatively little attention to the potential impact of ambient air pollution on cognitive function in older adults. We examined the cross-sectional association between residential concentrations of particulate matter with aerodynamic diameter of 2.5 μm or less (PM2.5) and cognitive function in older adults. Using hierarchical linear modeling, we analyzed data from the 2004 Health and Retirement Study, a large, nationally representative sample of US adults aged 50 years or older. We linked participant data with 2000 US Census tract data and 2004 census tract-level annual average PM2.5 concentrations. Older adults living in areas with higher PM2.5 concentrations had worse cognitive function (β = -0.26, 95% confidence interval: -0.47, -0.05) even after adjustment for community- and individual-level social and economic characteristics. Results suggest that the association is strongest for the episodic memory component of cognitive function. This study adds to a growing body of research highlighting the importance of air pollution to cognitive function in older adults. Improving air quality in large metropolitan areas, where much of the aging US population resides, may be an important mechanism for reducing age-related cognitive decline.
Keywords: Aged; Aged, 80 and over; Cognition; Cognition Disorders; Cross-Sectional Studies; Female; Humans; Inhalation Exposure; Male; Memory, Episodic; Middle Aged; Neuropsychological tests; Particulate Matter; Socioeconomic factors; United States; Urban Population

Functional disability and cognitive impairment after hospitalization for myocardial infarction and stroke. - Deborah A Levine; Dimitry S Davydow; Catherine L Hough; Kenneth M. Langa; Mary A M Rogers; Theodore J Iwashyna (Circ Cardiovasc Qual Outcomes, 2014)
BACKGROUND: We assessed the acute and long-term effect of myocardial infarction (MI) and stroke on postevent functional disability and cognition while controlling for survivors' changes in functioning over the years before the event. METHODS AND RESULTS: Among participants in the nationally representative Health and Retirement Study with linked Medicare data (1998-2010), we determined within-person changes in functional limitations (basic and instrumental activities of daily living) and cognitive impairment after hospitalization for stroke (n=432) and MI (n=450), controlling for premorbid functioning using fixed-effects regression. In persons without baseline impairments, an acute MI yielded a mean acute increase of 0.41 functional limitations (95% confidence interval [CI], 0.18-0.63) with a linear increase of 0.14 limitations/year in the following decade. These increases were 0.65 limitations (95% CI, 0.07-1.23) and 0.27 limitations/year afterward for those with mild-to-moderate impairment at baseline. Stroke resulted in an acute increase of 2.07 (95% CI, 1.51-2.63) limitations because of the acute event and an increase of 0.15 limitations/year afterward for those unimpaired at baseline. There were 2.65 new limitations (95% CI, 1.86-3.44) and 0.19/year afterward for those with baseline mild-to-moderate impairment. Stroke hospitalization was associated with greater odds of moderate-to-severe cognitive impairment (odds ratio, 3.86; 95% CI, 2.10-7.11) at the time of the event, after adjustment for premorbid cognition but MI hospitalization was not. CONCLUSIONS: In this population-based cohort, most MI and stroke hospitalizations were associated with significant increases in functional disability at the time of the event and in the decade afterward. Survivors of MI and stroke warrant screening for functional disability over the long-term.
Keywords: Activities of Daily Living; Cognition; Cognition Disorders; Disability Evaluation; Disabled Persons; Female; Follow-Up Studies; Hospitalization; Humans; Incidence; Male; Middle Aged; Myocardial Infarction; Odds Ratio; Retrospective Studies; Stroke; Time Factors; United States

Genetic and educational assortative mating among US adults. - Benjamin W Domingue; Jason M. Fletcher; Dalton C Conley; Jason D Boardman (Proc Natl Acad Sci U S A, 2014)
Understanding the social and biological mechanisms that lead to homogamy (similar individuals marrying one another) has been a long-standing issue across many fields of scientific inquiry. Using a nationally representative sample of non-Hispanic white US adults from the Health and Retirement Study and information from 1.7 million single-nucleotide polymorphisms, we compare genetic similarity among married couples to noncoupled pairs in the population. We provide evidence for genetic assortative mating in this population but the strength of this association is substantially smaller than the strength of educational assortative mating in the same sample. Furthermore, genetic similarity explains at most 10% of the assortative mating by education levels. Results are replicated using comparable data from the Framingham Heart Study.
Keywords: Databases, Genetic; Educational Status; ethnicity; Female; Genome-Wide Association Study; Genotype; Humans; Male; Marriage; Metagenomics; Phenotype; Racial Groups; Sexual Behavior; Spouses; United States

Genetic susceptibility to accelerated cognitive decline in the US Health and Retirement Study. - Zhang, Chenan; Brandon L Pierce (Neurobiol Aging, 2014)
Age-related cognitive decline is a major public health concern facing a large segment of the US population. To identify genetic risk factors related to cognitive decline, we used nationally representative longitudinal data from the US Health and Retirement Study to conduct genome-wide association studies with 5765 participants of European ancestry, and 890 participants of African ancestry. Mixed effects models were used to derive cognitive decline phenotypes from data on repeated cognitive assessments and to perform single nucleotide polymorphism-based heritability estimation. We found 2 independent associations among European-Americans in the 19q13.32 region: rs769449 (APOE intron; p = 3.1 × 10(-20)) and rs115881343 (TOMM40 intron; p = 6.6 × 10(-11)). rs769449 was also associated with cognitive decline among African-Americans (p = 0.005), but rs115881343 was not. Cross-sectional cognitive function showed moderate heritability (15%-32%) across several age strata (50-59, 60-69, 70-79 years), but the cognitive decline heritability estimate was low (∼5%). These results indicate that despite multiple association signals for cognitive decline in the 19q13.32 region, inter-individual variation is likely influenced substantially by environmental factors.
Keywords: African Americans; Aged; Aged, 80 and over; Chromosomes, Human, Pair 9; Cognition; Cognition Disorders; Cross-Sectional Studies; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Membrane Transport Proteins; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; United States

Genomic assortative mating in marriages in the United States. - Guo, Guang; Wang, Lin; Hexuan Liu; Randall, Thomas (PLoS One, 2014)
Assortative mating in phenotype in human marriages has been widely observed. Using genome-wide genotype data from the Framingham Heart study (FHS; number of married couples = 989) and Health Retirement Survey (HRS; number of married couples = 3,474), this study investigates genomic assortative mating in human marriages. Two types of genomic marital correlations are calculated. The first is a correlation specific to a single married couple "averaged" over all available autosomal single-nucleotide polymorphism (SNPs). In FHS, the average married-couple correlation is 0.0018 with p = 3 × 10(-5); in HRS, it is 0.0017 with p = 7.13 × 10(-13). The marital correlation among the positively assorting SNPs is 0.001 (p = .0043) in FHS and 0.015 (p = 1.66 × 10(-24)) in HRS. The sizes of these estimates in FHS and HRS are consistent with what are suggested by the distribution of the allelic combination. The study also estimated SNP-specific correlation "averaged" over all married couples. Suggestive evidence is reported. Future studies need to consider a more general form of genomic assortment, in which different allelic forms in homologous genes and non-homologous genes result in the same phenotype.
Keywords: Data collection; Female; Genome, Human; Genomics; Genotype; Humans; Male; Marriage; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Reproduction; United States

Geographic variation in out-of-pocket expenditures of elderly Medicare beneficiaries. - Lena M. Chen; Edward C Norton; Kenneth M. Langa; Le, Sidney; Arnold M. Epstein (J Am Geriatr Soc, 2014)
OBJECTIVES: To examine whether out-of-pocket expenditures (OOPEs) exhibit the same geographic variation as Medicare claims, given wide variation in the costs of U.S. health care, but no information on how that translates into OOPEs or financial burden for older Americans. DESIGN: Retrospective cohort study. SETTING: Data from the Health and Retirement Study linked to Medicare claims. PARTICIPANTS: A nationally representative cohort of 4,657 noninstitutionalized, community-dwelling, fee-for-service elderly Medicare beneficiaries interviewed in 2006 and 2008. MEASUREMENTS: The primary predictor was per capita Medicare spending quintile according to hospital referral region. The primary outcome was a self-reported, validated measure of annual OOPEs excluding premiums. RESULTS: Mean and median adjusted per capita Medicare payments were $5,916 and $2,635, respectively; mean and median adjusted OOPEs were $1,525 and $779, respectively. Adjusted median Medicare payments were $3,474 in the highest cost quintile and $1,942 in the lowest cost quintile (ratio 1.79, P < .001 for difference). In contrast, adjusted median OOPEs were not higher in the highest than in the lowest Medicare cost quintile ($795 vs $764 for a Q5:Q1 ratio of 1.04, P = .42). The Q5:Q1 ratio was 1.48 for adjusted mean Medicare payments and 1.04 for adjusted mean OOPEs (both P < .001). CONCLUSION: Medicare payments vary widely between high- and low-cost regions, but OOPEs do not.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Female; Geography; Health Care Costs; Health Expenditures; Humans; Male; Medicare; Retrospective Studies; United States

The health effects of US unemployment insurance policy: does income from unemployment benefits prevent cardiovascular disease? - Stefan Walter; M. Maria Glymour; Mauricio Avendano (PLoS One, 2014)
OBJECTIVE: Previous studies suggest that unemployment predicts increased cardiovascular disease (CVD) risk, but whether unemployment insurance programs mitigate this risk has not been assessed. Exploiting US state variations in unemployment insurance benefit programs, we tested the hypothesis that more generous benefits reduce CVD risk. METHODS: Cohort data came from 16,108 participants in the Health and Retirement Study (HRS) aged 50-65 at baseline interviewed from 1992 to 2010. Data on first and recurrent CVD diagnosis assessed through biennial interviews were linked to the generosity of unemployment benefit programmes in each state and year. Using state fixed-effect models, we assessed whether state changes in the generosity of unemployment benefits predicted CVD risk. RESULTS: States with higher unemployment benefits had lower incidence of CVD, so that a 1% increase in benefits was associated with 18% lower odds of CVD (OR:0.82, 95%-CI:0.71-0.94). This association remained after introducing US census regional division fixed effects, but disappeared after introducing state fixed effects (OR:1.02, 95%-CI:0.79-1.31).This was consistent with the fact that unemployment was not associated with CVD risk in state-fixed effect models. CONCLUSION: Although states with more generous unemployment benefits had lower CVD incidence, this appeared to be due to confounding by state-level characteristics. Possible explanations are the lack of short-term effects of unemployment on CVD risk. Future studies should assess whether benefits at earlier stages of the life-course influence long-term risk of CVD.
Keywords: Aged; Cardiovascular Diseases; Female; Geography; Humans; Incidence; Insurance Benefits; Insurance, Health; Longitudinal Studies; Male; Middle Aged; Risk Factors; Unemployment; United States

Heterogeneity in healthy aging. - David J Lowsky; S Jay Olshansky; Bhattacharya, Jay; Dana P Goldman (J Gerontol A Biol Sci Med Sci, 2014)
For a surprisingly large segment of the older population, chronological age is not a relevant marker for understanding, measuring, or experiencing healthy aging. Using the 2003 Medical Expenditure Panel Survey and the 2004 Health and Retirement Study to examine the proportion of Americans exhibiting five markers of health and the variation in health-related quality of life across each of eight age groups, we find that a significant proportion of older Americans is healthy within every age group beginning at age 51, including among those aged 85+. For example, 48% of those aged 51-54 and 28% of those aged 85+ have excellent or very good self-reported health status; similarly, 89% of those aged 51-54 and 56% of those aged 85+ report no health-based limitations in work or housework. Also, health-related quality of life ranges widely within every age group, yet there is only a comparatively small variation in median quality of life across age groups, suggesting that older Americans today may be experiencing substantially different age-health trajectories than their predecessors. Patterns are similar for medical expenditures. Several policy implications are explored.
Keywords: Aged; Aged, 80 and over; Aging; Female; Health Status; Humans; Male; Middle Aged; Population Surveillance; Quality of Life; Retrospective Studies; United States

History of alcohol use disorders and risk of severe cognitive impairment: a 19-year prospective cohort study. - Kuźma, Elżbieta; David J Llewellyn; Kenneth M. Langa; Robert B Wallace; Iain A Lang (Am J Geriatr Psychiatry, 2014)
OBJECTIVE: To assess the effects of a history of alcohol use disorders (AUDs) on risk of severe cognitive and memory impairment in later life. METHODS: We studied the association between history of AUDs and the onset of severe cognitive and memory impairment in 6,542 middle-aged adults born 1931 through 1941 who participated in the Health and Retirement Study, a prospective nationally representative U.S. cohort. Participants were assessed at 1992 baseline and follow-up cognitive assessments were conducted biannually from 1996 through 2010. History of AUDs was identified using the three-item modified CAGE questionnaire. Cognitive outcomes were assessed using the 35-item modified Telephone Interview for Cognitive Status at last follow-up with incident severe cognitive impairment defined as a score ≤ 8, and incident severe memory impairment defined as a score ≤ 1 on a 20-item memory subscale. RESULTS: During up to 19 years of follow-up (mean: 16.7 years, standard deviation: 3.0, range: 3.5-19.1 years), 90 participants experienced severe cognitive impairment and 74 participants experienced severe memory impairment. History of AUDs more than doubled the odds of severe memory impairment (odds ratio [OR] = 2.21, 95% confidence interval [CI] = 1.27-3.85, t = 2.88, df = 52, p = 0.01). The association with severe cognitive impairment was statistically non-significant but in the same direction (OR = 1.80, 95% CI = 0.97-3.33, t = 1.92, df = 52, p = 0.06). CONCLUSION: Middle-aged adults with a history of AUDs have increased odds of developing severe memory impairment later in life. These results reinforce the need to consider the relationship between alcohol consumption and cognition from a multifactorial lifespan perspective.
Keywords: Alcohol-Related Disorders; Cognition Disorders; Diagnosis, Dual (Psychiatry); Female; Humans; Incidence; Male; Memory Disorders; Middle Aged; Prospective Studies; Risk Factors; United States

Identifying diabetics in Medicare claims and survey data: implications for health services research. - Joseph W Sakshaug; David R Weir; Lauren Hersch Nicholas (BMC Health Serv Res, 2014)
BACKGROUND: Diabetes health services research often utilizes secondary data sources, including survey self-report and Medicare claims, to identify and study the diabetic population, but disagreement exists between these two data sources. We assessed agreement between the Chronic Condition Warehouse diabetes algorithm for Medicare claims and self-report measures of diabetes. Differences in healthcare utilization outcomes under each diabetes definition were also explored. METHODS: Claims data from the Medicare Beneficiary Annual Summary File were linked to survey and blood data collected from the 2006 Health and Retirement Study. A Hemoglobin A1c reading, collected on 2,028 respondents, was used to reconcile discrepancies between the self-report and Medicare claims measures of diabetes. T-tests were used to assess differences in healthcare utilization outcomes for each diabetes measure. RESULTS: The Chronic Condition Warehouse (CCW) algorithm yielded a higher rate of diabetes than respondent self-reports (27.3 vs. 21.2, p < 0.05). A1c levels of discordant claims-based diabetics suggest that these patients are not diabetic, however, they have high rates of healthcare spending and utilization similar to diabetics. CONCLUSIONS: Concordance between A1c and self-reports was higher than for A1c and the CCW algorithm. Accuracy of self-reports was superior to the CCW algorithm. False positives in the claims data have similar utilization profiles to diabetics, suggesting minimal bias in some types of claims-based analyses, though researchers should consider sensitivity analysis across definitions for health services research.
Keywords: Aged; Aged, 80 and over; Algorithms; Diabetes Mellitus; Female; Glycated Hemoglobin; Health Services Research; Humans; Insurance Claim Review; Male; Medicare; Prevalence; United States

Increased 1-year healthcare use in survivors of severe sepsis. - Hallie C Prescott; Kenneth M. Langa; Liu, Vincent; Gabriel J. Escobar; Theodore J Iwashyna (Am J Respir Crit Care Med, 2014)
RATIONALE: Hospitalizations for severe sepsis are common, and a growing number of patients survive to hospital discharge. Nonetheless, little is known about survivors' post-discharge healthcare use. OBJECTIVES: To measure inpatient healthcare use of severe sepsis survivors compared with patients' own presepsis resource use and the resource use of survivors of otherwise similar nonsepsis hospitalizations. METHODS: This is an observational cohort study of survivors of severe sepsis and nonsepsis hospitalizations identified from participants in the Health and Retirement Study with linked Medicare claims, 1998-2005. We matched severe sepsis and nonsepsis hospitalizations by demographics, comorbidity burden, premorbid disability, hospitalization length, and intensive care use. MEASUREMENTS AND MAIN RESULTS: Using Medicare claims, we measured patients' use of inpatient facilities (hospitals, long-term acute care hospitals, and skilled nursing facilities) in the 2 years surrounding hospitalization. Severe sepsis survivors spent more days (median, 16 [interquartile range, 3-45] vs. 7 [0-29]; P < 0.001) and a higher proportion of days alive (median, 9.6% [interquartile range, 1.4-33.8%] vs. 1.9% [0.0-7.9%]; P < 0.001) admitted to facilities in the year after hospitalization, compared with the year prior. The increase in facility-days was similar for nonsepsis hospitalizations. However, the severe sepsis cohort experienced greater post-discharge mortality (44.2% [95% confidence interval, 41.3-47.2%] vs. 31.4% [95% confidence interval, 28.6-34.2%] at 1 year), a steeper decline in days spent at home (difference-in-differences, -38.6 d [95% confidence interval, -50.9 to 26.3]; P < 0.001), and a greater increase in the proportion of days alive spent in a facility (difference-in-differences, 5.4% [95% confidence interval, 2.8-8.1%]; P < 0.001). CONCLUSIONS: Healthcare use is markedly elevated after severe sepsis, and post-discharge management may be an opportunity to reduce resource use.
Keywords: Aged; Female; Health Facilities; Humans; Insurance Claim Review; Long-term Care; Male; Medical Record Linkage; Medicare; Mortality; Outcome Assessment, Health Care; Patient Readmission; Prospective Studies; Sepsis; Skilled Nursing Facilities; Survivors; United States

An investigation of activity profiles of older adults. - Morrow-Howell, Nancy; Putnam, Michelle; Lee, Yung Soo; Jennifer C. Greenfield; Inoue, Megumi; Chen, Huajuan (J Gerontol B Psychol Sci Soc Sci, 2014)
OBJECTIVES: In this study, we advance knowledge about activity engagement by considering many activities simultaneously to identify profiles of activity among older adults. Further, we use cross-sectional data to explore factors associated with activity profiles and prospective data to explore activity profiles and well-being outcomes. METHOD: We used the core survey data from the years 2008 and 2010, as well as the 2009 Health and Retirement Study Consumption and Activities Mail Survey (HRS CAMS). The HRS CAMS includes information on types and amounts of activities. We used factor analysis and latent class analysis to identify activity profiles and regression analyses to assess antecedents and outcomes associated with activity profiles. RESULTS: We identified 5 activity profiles: Low Activity, Moderate Activity, High Activity, Working, and Physically Active. These profiles varied in amount and type of activities. Demographic and health factors were related to profiles. Activity profiles were subsequently associated with self-rated health and depression symptoms. DISCUSSION: The use of a 5-level categorical activity profile variable may allow more complex analyses of activity that capture the "whole person." There is clearly a vulnerable group of low-activity individuals as well as a High Activity group that may represent the "active ageing" vision.
Keywords: Aged; Aged, 80 and over; Aging; Black or African American; Cohort Studies; Cross-Sectional Studies; Employment; Female; Florida; Health Surveys; Hispanic or Latino; Human Activities; Humans; Male; Middle Aged; Models, Psychological; Motor Activity; Prospective Studies; Regression Analysis; United States

Leveraging the health and retirement study to advance palliative care research. - Amy Kelley; Kenneth M. Langa; John G. Cagle; Katherine A Ornstein; Maria J Silveira; Lauren Hersch Nicholas; Kenneth E Covinsky; Christine S Ritchie (J Palliat Med, 2014)
BACKGROUND: The critical need to expand and develop the palliative care evidence base was recently highlighted by the Journal of Palliative Medicine's series of articles describing the Research Priorities in Geriatric Palliative Care. The Health and Retirement Study (HRS) is uniquely positioned to address many priority areas of palliative care research. This nationally representative, ongoing, longitudinal study collects detailed survey data every 2 years, including demographics, health and functional characteristics, information on family and caregivers, and personal finances, and also conducts a proxy interview after each subject's death. The HRS can also be linked with Medicare claims data and many other data sources, e.g., U.S. Census, Dartmouth Atlas of Health Care. SETTING: While the HRS offers innumerable research opportunities, these data are complex and limitations do exist. Therefore, we assembled an interdisciplinary group of investigators using the HRS for palliative care research to identify the key palliative care research gaps that may be amenable to study within the HRS and the strengths and weaknesses of the HRS for each of these topic areas. CONCLUSION: In this article we present the work of this group as a potential roadmap for investigators contemplating the use of HRS data for palliative care research.
Keywords: Aged; Caregivers; Evidence-Based Practice; Health Services Research; Health Surveys; Humans; Longitudinal Studies; Needs Assessment; Pain Management; Palliative care; Quality of Life; Retirement; Sociological Factors; United States

Life satisfaction and frequency of doctor visits. - Eric S Kim; Nansook Park; Jennifer K Sun; Jacqui Smith; Christopher Peterson (Psychosom Med, 2014)
OBJECTIVE: Identifying positive psychological factors that reduce health care use may lead to innovative efforts that help build a more sustainable and high-quality health care system. Prospective studies indicate that life satisfaction is associated with good health behaviors, enhanced health, and longer life, but little information about the association between life satisfaction and health care use is available. We tested whether higher life satisfaction was prospectively associated with fewer doctor visits. We also examined potential interactions between life satisfaction and health behaviors. METHODS: Participants were 6379 adults from the Health and Retirement Study, a prospective and nationally representative panel study of American adults older than 50 years. Participants were tracked for 4 years. We analyzed the data using a generalized linear model with a gamma distribution and log link. RESULTS: Higher life satisfaction was associated with fewer doctor visits. On a 6-point life satisfaction scale, each unit increase in life satisfaction was associated with an 11% decrease in doctor visits--after adjusting for sociodemographic factors (relative risk = 0.89, 95% confidence interval = 0.86-0.93). The most satisfied respondents (n = 1121; 17.58%) made 44% fewer doctor visits than did the least satisfied (n = 182; 2.85%). The association between higher life satisfaction and reduced doctor visits remained even after adjusting for baseline health and a wide range of sociodemographic, psychosocial, and health-related covariates (relative risk = 0.96, 95% confidence interval = 0.93-0.99). CONCLUSIONS: Higher life satisfaction is associated with fewer doctor visits, which may have important implications for reducing health care costs.
Keywords: Aged; Female; Health Behavior; Humans; Male; Middle Aged; Office Visits; Personal Satisfaction; Prospective Studies; United States

Longitudinal predictors of self-rated health and mortality in older adults. - Diane C Wagner; Jerome L Short (Prev Chronic Dis, 2014)
INTRODUCTION: Few studies have compared the effects of demographic, cognitive, and behavioral factors of health and mortality longitudinally. We examined predictors of self-rated health and mortality at 3 points, each 2 years apart, over 4 years. METHODS: We used data from the 2006 wave of the Health and Retirement Study and health and mortality indicators from 2006, 2008, and 2010. We analyzed data from 17,930 adults (aged 50-104 y) to examine predictors of self-rated health and data from a subgroup of 1,171 adults who died from 2006 through 2010 to examine predictors of mortality. RESULTS: Time 1 depression was the strongest predictor of self-rated health at all points, independent of age and education. Education, mild activities, body mass index, delayed word recall, and smoking were all associated with self-rated health at each point and predicted mortality. Delayed word recall mediated the relationships of mild activity with health and mortality. Bidirectional mediation was found for the effects of mild activity and depression on health. CONCLUSION: Medical professionals should consider screening for depression and memory difficulties in addition to conducting medical assessments. These assessments could lead to more effective biopsychosocial interventions to help older adults manage risks for mortality.
Keywords: Age Factors; Aged; Aged, 80 and over; Body Mass Index; Chronic disease; depression; Educational Status; Female; Health Behavior; Health Status Indicators; Humans; Longitudinal Studies; Male; Mental Recall; Middle Aged; Proportional Hazards Models; Psychometrics; Retirement; Self Report; Survival Analysis; United States

Mortality and cardiovascular disease among older live kidney donors. - P. P. Reese; R. D. Bloom; H. I. Feldman; Rosenbaum, P; Wang, W; P. Saynisch; Tarsi, N M; Mukherjee, N; Garg, A X; A. Mussell; J. Shults; Even-Shoshan, O; et al. (Am J Transplant, 2014)
Over the past two decades, live kidney donation by older individuals (≥55 years) has become more common. Given the strong associations of older age with cardiovascular disease (CVD), nephrectomy could make older donors vulnerable to death and cardiovascular events. We performed a cohort study among older live kidney donors who were matched to healthy older individuals in the Health and Retirement Study. The primary outcome was mortality ascertained through national death registries. Secondary outcomes ascertained among pairs with Medicare coverage included death or CVD ascertained through Medicare claims data. During the period from 1996 to 2006, there were 5717 older donors in the United States. We matched 3368 donors 1:1 to older healthy nondonors. Among donors and matched pairs, the mean age was 59 years; 41% were male and 7% were black race. In median follow-up of 7.8 years, mortality was not different between donors and matched pairs (p = 0.21). Among donors with Medicare, the combined outcome of death/CVD (p = 0.70) was also not different between donors and nondonors. In summary, carefully selected older kidney donors do not face a higher risk of death or CVD. These findings should be provided to older individuals considering live kidney donation.
Keywords: Age Factors; Aged; Cardiovascular Diseases; Female; Follow-Up Studies; Humans; Kidney Transplantation; Living Donors; Longitudinal Studies; Male; Medicare; Middle Aged; Nephrectomy; Quality of Life; Renal Insufficiency; Time Factors; Treatment Outcome; United States

Neuropsychiatric disorders and potentially preventable hospitalizations in a prospective cohort study of older Americans. - Dimitry S Davydow; Zivin, Kara; Wayne J Katon; Gregory M Pontone; Lydia Chwastiak; Kenneth M. Langa; Theodore J Iwashyna (J Gen Intern Med, 2014)
BACKGROUND: The relative contributions of depression, cognitive impairment without dementia (CIND), and dementia to the risk of potentially preventable hospitalizations in older adults are not well understood. OBJECTIVE(S): To determine if depression, CIND, and/or dementia are each independently associated with hospitalizations for ambulatory care-sensitive conditions (ACSCs) and rehospitalizations within 30 days after hospitalization for pneumonia, congestive heart failure (CHF), or myocardial infarction (MI). DESIGN: Prospective cohort study. PARTICIPANTS: Population-based sample of 7,031 Americans > 50 years old participating in the Health and Retirement Study (1998-2008). MAIN MEASURES: The eight-item Center for Epidemiologic Studies Depression Scale and/or International Classification of Disease, Ninth Revision, Clinical Modification (ICD-9-CM) depression diagnoses were used to identify baseline depression. The Modified Telephone Interview for Cognitive Status and/or ICD-9-CM dementia diagnoses were used to identify baseline CIND or dementia. Primary outcomes were time to hospitalization for an ACSC and presence of a hospitalization within 30 days after hospitalization for pneumonia, CHF, or MI. KEY RESULTS: All five categories of baseline neuropsychiatric disorder status were independently associated with increased risk of hospitalization for an ACSC (depression alone: Hazard Ratio [HR]: 1.33, 95% Confidence Interval [95%CI]: 1.18, 1.52; CIND alone: HR: 1.25, 95%CI: 1.10, 1.41; dementia alone: HR: 1.32, 95%CI: 1.12, 1.55; comorbid depression and CIND: HR: 1.43, 95%CI: 1.20, 1.69; comorbid depression and dementia: HR: 1.66, 95%CI: 1.38, 2.00). Depression (Odds Ratio [OR]: 1.37, 95%CI: 1.01, 1.84), comorbid depression and CIND (OR: 1.98, 95%CI: 1.40, 2.81), or comorbid depression and dementia (OR: 1.58, 95%CI: 1.06, 2.35) were independently associated with increased odds of rehospitalization within 30 days after hospitalization for pneumonia, CHF, or MI. CONCLUSIONS: Depression, CIND, and dementia are each independently associated with potentially preventable hospitalizations in older Americans. Older adults with comorbid depression and cognitive impairment represent a particularly at-risk group that could benefit from targeted interventions.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Cohort Studies; Dementia; depression; Female; Hospitalization; Humans; Male; Mental Disorders; Prospective Studies; Risk Factors; United States

Obesity and 1-year outcomes in older Americans with severe sepsis. - Hallie C Prescott; Virginia W Chang; James M. O'Brien Jr; Kenneth M. Langa; Theodore J Iwashyna (Crit Care Med, 2014)
OBJECTIVES: Although critical care physicians view obesity as an independent poor prognostic marker, growing evidence suggests that obesity is, instead, associated with improved mortality following ICU admission. However, this prior empirical work may be biased by preferential admission of obese patients to ICUs, and little is known about other patient-centered outcomes following critical illness. We sought to determine whether 1-year mortality, healthcare utilization, and functional outcomes following a severe sepsis hospitalization differ by body mass index. DESIGN: Observational cohort study. SETTING: U.S. hospitals. PATIENTS: We analyzed 1,404 severe sepsis hospitalizations (1999-2005) among Medicare beneficiaries enrolled in the nationally representative Health and Retirement Study, of which 597 (42.5%) were normal weight, 473 (33.7%) were overweight, and 334 (23.8%) were obese or severely obese, as assessed at their survey prior to acute illness. Underweight patients were excluded a priori. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Using Medicare claims, we identified severe sepsis hospitalizations and measured inpatient healthcare facility use and calculated total and itemized Medicare spending in the year following hospital discharge. Using the National Death Index, we determined mortality. We ascertained pre- and postmorbid functional status from survey data. Patients with greater body mass indexes experienced lower 1-year mortality compared with nonobese patients, and there was a dose-response relationship such that obese (odds ratio = 0.59; 95% CI, 0.39-0.88) and severely obese patients (odds ratio = 0.46; 95% CI, 0.26-0.80) had the lowest mortality. Total days in a healthcare facility and Medicare expenditures were greater for obese patients (p < 0.01 for both comparisons), but average daily utilization (p = 0.44) and Medicare spending were similar (p = 0.65) among normal, overweight, and obese survivors. Total function limitations following severe sepsis did not differ by body mass index category (p = 0.64). CONCLUSIONS: Obesity is associated with improved mortality among severe sepsis patients. Due to longer survival, obese sepsis survivors use more healthcare and result in higher Medicare spending in the year following hospitalization. Median daily healthcare utilization was similar across body mass index categories.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Comorbidity; Critical Illness; Delivery of Health Care; Female; Health Expenditures; Hospitalization; Humans; Male; Medicare; Middle Aged; Obesity; Sepsis; Survival Rate; Survivors; United States

Perceived neighbourhood social cohesion and myocardial infarction. - Eric S Kim; Armani M. Hawes; Jacqui Smith (J Epidemiol Community Health, 2014)
BACKGROUND: The main strategy for alleviating heart disease has been to target individuals and encourage them to change their health behaviours. Although important, emphasis on individuals has diverted focus and responsibility away from neighbourhood characteristics, which also strongly influence people's behaviours. Although a growing body of research has repeatedly demonstrated strong associations between neighbourhood characteristics and cardiovascular health, it has typically focused on negative neighbourhood characteristics. Only a few studies have examined the potential health enhancing effects of positive neighbourhood characteristics, such as perceived neighbourhood social cohesion. METHODS: Using multiple logistic regression models, we tested whether higher perceived neighbourhood social cohesion was associated with lower incidence of myocardial infarction. Prospective data from the Health and Retirement Study--a nationally representative panel study of American adults over the age of 50--were used to analyse 5276 participants with no history of heart disease. Respondents were tracked for 4 years and analyses adjusted for relevant sociodemographic, behavioural, biological and psychosocial factors. RESULTS: In a model that adjusted for age, gender, race, marital status, education and total wealth, each SD increase in perceived neighbourhood social cohesion was associated with a 22% reduced odds of myocardial infarction (OR=0.78, 95% CI 0.63 to 0.94. The association between perceived neighbourhood social cohesion and myocardial infarction remained even after adjusting for behavioural, biological and psychosocial covariates. CONCLUSIONS: Higher perceived neighbourhood social cohesion may have a protective effect against myocardial infarction.
Keywords: Aged; Aged, 80 and over; Confounding Factors, Epidemiologic; Female; Health Behavior; Health Status; Health Surveys; Humans; Incidence; Interviews as Topic; Male; Mental Health; Middle Aged; Multilevel Analysis; Myocardial Infarction; Perception; Prospective Studies; Protective factors; Residence Characteristics; Self Report; Social Environment; Socioeconomic factors; United States

Preparedness for natural disasters among older US adults: a nationwide survey. - Tala M. Al-rousan; Linda M. Rubenstein; Robert B Wallace (Am J Public Health, 2014)
OBJECTIVES: We sought to determine natural disaster preparedness levels among older US adults and assess factors that may adversely affect health and safety during such incidents. METHODS: We sampled adults aged 50 years or older (n = 1304) from the 2010 interview survey of the Health and Retirement Study. The survey gathered data on general demographic characteristics, disability status or functional limitations, and preparedness-related factors and behaviors. We calculated a general disaster preparedness score by using individual indicators to assess overall preparedness. RESULTS: Participant (n = 1304) mean age was 70 years (SD = 9.3). Only 34.3% reported participating in an educational program or reading materials about disaster preparation. Nearly 15% reported using electrically powered medical devices that might be at risk in a power outage. The preparedness score indicated that increasing age, physical disability, and lower educational attainment and income were independently and significantly associated with worse overall preparedness. CONCLUSIONS: Despite both greater vulnerability to disasters and continuous growth in the number of older US adults, many of the substantial problems discovered are remediable and require attention in the clinical, public health, and emergency management sectors of society.
Keywords: Aged; Aged, 80 and over; Disaster Planning; Female; Humans; Male; Middle Aged; Surveys and Questionnaires; United States

Prospective study of the association between dispositional optimism and incident heart failure. - Eric S Kim; Jacqui Smith; Laura D Kubzansky (Circ Heart Fail, 2014)
BACKGROUND: Although higher optimism has been linked with an array of positive health behaviors, biological processes, and cardiovascular outcomes, the relationship between optimism and heart failure has not been examined. In the United States, 80% of heart failures occur in adults aged 65+ years. Therefore, we examined whether higher optimism was linked with a reduced incidence of heart failure among older adults. METHODS AND RESULTS: Prospective data were from the Health and Retirement Study, a nationally representative study of older US adults. Our sample included 6808 participants who were followed for 4 years. Multiple logistic regression models were used to assess whether optimism was independently associated with incident heart failure. We adjusted for sociodemographic, behavioral, biological, and psychological covariates. Higher optimism was associated with a lower risk of incident heart failure during the follow-up period. In a model that adjusted for sociodemographic factors, each SD increase in optimism had an odds ratio of 0.74 (95% confidence interval, 0.63-0.85) for heart failure. Effects of optimism persisted even after adjusting for a wide range of covariates. There was also evidence of a dose-response relationship. As optimism increased, risk of developing heart failure decreased monotonically, with a 48% reduced odds among people with the highest versus lowest optimism. CONCLUSIONS: This is the first study to suggest that optimism is associated with a lower risk of heart failure. If future studies confirm these findings, they may be used to inform new strategies for preventing or delaying the onset of heart failure.
Keywords: Affect; Aged; Aged, 80 and over; Emotions; Female; Heart Failure; Humans; Incidence; Logistic Models; Male; Middle Aged; Outcome Assessment, Health Care; Prospective Studies; Retrospective Studies; Risk Factors; Socioeconomic factors; United States

Public beliefs and knowledge about risk and protective factors for Alzheimer's disease. - J Scott Roberts; Sara J McLaughlin; Cathleen M. Connell (Alzheimers Dement, 2014)
BACKGROUND: The purpose of this study was to assess public beliefs and knowledge about risk and protective factors for Alzheimer's disease (AD). METHODS: A brief survey module was added to the Health and Retirement Study, a longstanding national panel study of the U.S. population over the age of 50. RESULTS: Respondents were 1641 adults (mean age=64.4 years, 53.6% female, 81.7% White). Most (60.1%) indicated interest in learning their AD risk, with 29.4% expressing active worry. Many failed to recognize that medications to prevent AD are not available (39.1%) or that having an affected first-degree relative is associated with increased disease risk (32%). Many respondents believed that various actions (e.g., mental activity, eating a healthy diet) would be effective in reducing AD risk. CONCLUSION: Older and middle-aged adults are interested in their AD risk status and believe that steps can be taken to reduce disease risk. Tailored education efforts are needed to address potential misconceptions about risk and protective factors.
Keywords: Aged; Alzheimer disease; Female; Health Knowledge, Attitudes, Practice; Humans; Male; Middle Aged; Protective factors; United States

Question context and priming meaning of health: effect on differences in self-rated health between Hispanics and non-Hispanic Whites. - Lee, Sunghee; Schwarz, Norbert (Am J Public Health, 2014)
OBJECTIVES: We examined the implications of the current recommended data collection practice of placing self-rated health (SRH) before specific health-related questions (hence, without a health context) to remove potential context effects, between Hispanics and non-Hispanics. METHODS: We used 2 methodologically comparable surveys conducted in English and Spanish that asked SRH in different contexts: before and after specific health questions. Focusing on the elderly, we compared the influence of question contexts on SRH between Hispanics and non-Hispanics and between Spanish and English speakers. RESULTS: The question context influenced SRH reports of Spanish speakers (and Hispanics) significantly but not of English speakers (and non-Hispanics). Specifically, on SRH within a health context, Hispanics reported more positive health, decreasing the gap with non-Hispanic Whites by two thirds, and the measurement utility of SRH was improved through more consistent mortality prediction across ethnic and linguistic groups. CONCLUSIONS: Contrary to the current recommendation, asking SRH within a health context enhanced measurement utility. Studies using SRH may result in erroneous conclusions when one does not consider its question context.
Keywords: Aged; Female; Health Status; Health Surveys; Hispanic or Latino; Humans; Male; Middle Aged; Mortality; Self Report; United States; White People

Satisfaction with aging and use of preventive health services. - Eric S Kim; Kyle D Moored; Hannah L. Giasson; Jacqui Smith (Prev Med, 2014)
OBJECTIVE: Preventive health service use is relatively low among older age groups. We hypothesized that aging satisfaction would be associated with increased use of preventive health services four years later. METHOD: We conducted multiple logistic regression analyses on a sample of 6177 people from the Health and Retirement Study, a nationally representative study of U.S. adults over the age of 50 (M age=70.6; women n=3648; men n=2529). RESULTS: Aging satisfaction was not associated with obtaining flu shots. However, in fully-adjusted models, each standard deviation increase in aging satisfaction was associated with higher odds of reporting service use for cholesterol tests (OR=1.10, 95% CI=1.00-1.20). Further, women with higher aging satisfaction were more likely to obtain a mammogram/x-ray (OR=1.17, 95% CI=1.06-1.29) or Pap smear (OR=1.10, 95% CI=1.00-1.21). Among men, the odds of obtaining a prostate exam increased with higher aging satisfaction (OR=1.20 95% CI=1.09-1.34). CONCLUSION: These results suggest that aging satisfaction potentially influences preventive health service use after age 50.
Keywords: Aged; Aged, 80 and over; Aging; Chronic disease; Female; Health Behavior; Health Knowledge, Attitudes, Practice; Humans; Influenza Vaccines; Logistic Models; Male; Mammography; Middle Aged; Patient Acceptance of Health Care; Patient Satisfaction; Personal Satisfaction; Preventive Health Services; Prostatic Neoplasms; Surveys and Questionnaires; United States; Vaginal Smears

Self-rated health changes and oldest-old mortality. - Eric M Vogelsang (J Gerontol B Psychol Sci Soc Sci, 2014)
OBJECTIVES: This study explores how 2 measures of self-rated health (SRH) change are related to mortality among oldest-old adults. In doing so, it also considers how associations between SRH and mortality may depend on prior SRH. METHOD: Data come from the Asset and Health Dynamics survey--the oldest-old portion of the Health and Retirement Study-and follow 6,233 individuals across 13 years. I use parametric hazard models to examine relationships between death and 2 measures of short-term SRH change--a computed measure comparing SRH at time t-1 and t, and a respondent-provided retrospectively reported change. RESULTS: Respondents who demonstrate or report any SRH change between survey waves died at a greater rate than those with consistent SRH. After controlling for morbidity, individual characteristics, and SRH, those who changed SRH categories between survey waves and those who retrospectively reported an improvement in health continue to have a greater risk of death, when compared with those with no change. DISCUSSION: These findings suggest that the well-established associations between SRH status and mortality may understate the risk of death for oldest-old individuals with recent subjective health improvements.
Keywords: Aged; Aged, 80 and over; Diagnostic Self Evaluation; Female; Health Status; Humans; Longitudinal Studies; Male; Mortality; Proportional Hazards Models; Randomized Controlled Trials as Topic; Risk; United States

Short- and long-term associations between widowhood and mortality in the United States: longitudinal analyses. - J Robin Moon; M. Maria Glymour; Anusha M Vable; Sze Y Liu; S. V. Subramanian (J Public Health (Oxf), 2014)
BACKGROUND: Past research shows that spousal death results in elevated mortality risk for the surviving spouse. However, most prior studies have inadequately controlled for socioeconomic status (SES), and it is unclear whether this 'widowhood effect' persists over time. METHODS: Health and Retirement Study participants aged 50+ years and married in 1998 (n = 12 316) were followed through 2008 for widowhood status and mortality (2912 deaths). Discrete-time survival analysis was used to compare mortality for the widowed versus the married. RESULTS: Odds of mortality during the first 3 months post-widowhood were significantly higher than in the continuously married (odds ratio (OR) for men = 1.87, 95% CI: 1.27, 2.75; OR for women = 1.47, 95% CI: 0.96, 2.24) in models adjusted for age, gender, race and baseline SES (education, household wealth and household income), behavioral risk factors and co-morbidities. Twelve months following bereavement, men experienced borderline elevated mortality (OR = 1.16, 95% CI: 1.00, 1.35), whereas women did not (OR = 1.07, 95% CI: 0.90, 1.28), though the gender difference was non-significant. CONCLUSION: The 'widowhood effect' was not fully explained by adjusting for pre-widowhood SES and particularly elevated within the first few months after widowhood. These associations did not differ by sex.
Keywords: Bereavement; Female; Humans; Longitudinal Studies; Male; Middle Aged; Mortality; Risk Factors; Sex Factors; Socioeconomic factors; Time Factors; United States; Widowhood

Social relationships, leisure activity, and health in older adults. - Chang, Po-Ju; Linda A. Wray; Lin, Yeqiang (Health Psychol, 2014)
OBJECTIVE: Although the link between enhanced social relationships and better health has generally been well established, few studies have examined the role of leisure activity in this link. This study examined how leisure influences the link between social relationships and health in older age. METHOD: Using data from the 2006 and 2010 waves of the nationally representative U.S. Health and Retirement Study and structural equation modeling analyses, we examined data on 2,965 older participants to determine if leisure activities mediated the link between social relationships and health in 2010, controlling for race, education level, and health in 2006. RESULTS: The results demonstrated that leisure activities mediate the link between social relationships and health in these age groups. Perceptions of positive social relationships were associated with greater involvement in leisure activities, and greater involvement in leisure activities was associated with better health in older age. CONCLUSION: The contribution of leisure to health in these age groups is receiving increasing attention, and the results of this study add to the literature on this topic, by identifying the mediating effect of leisure activity on the link between social relationships and health. Future studies aimed at increasing leisure activity may contribute to improved health outcomes in older adults.
Keywords: Aged; Aged, 80 and over; Female; Health Status; Humans; Interpersonal Relations; Leisure activities; Longitudinal Studies; Male; Middle Aged; United States

Validation of a polygenic risk score for dementia in black and white individuals. - Jessica R Marden; Stefan Walter; Eric J. Tchetgen Tchetgen; Ichiro Kawachi; M. Maria Glymour (Brain Behav, 2014)
OBJECTIVE: To determine whether a polygenic risk score for Alzheimer's disease (AD) predicts dementia probability and memory functioning in non-Hispanic black (NHB) and non-Hispanic white (NHW) participants from a sample not used in previous genome-wide association studies. METHODS: Non-Hispanic white and NHB Health and Retirement Study (HRS) participants provided genetic information and either a composite memory score (n = 10,401) or a dementia probability score (n = 7690). Dementia probability score was estimated for participants' age 65+ from 2006 to 2010, while memory score was available for participants age 50+. We calculated AD genetic risk scores (AD-GRS) based on 10 polymorphisms confirmed to predict AD, weighting alleles by beta coefficients reported in AlzGene meta-analyses. We used pooled logistic regression to estimate the association of the AD-GRS with dementia probability and generalized linear models to estimate its effect on memory score. RESULTS: Each 0.10 unit change in the AD-GRS was associated with larger relative effects on dementia among NHW aged 65+ (OR = 2.22; 95% CI: 1.79, 2.74; P < 0.001) than NHB (OR=1.33; 95% CI: 1.00, 1.77; P = 0.047), although additive effect estimates were similar. Each 0.10 unit change in the AD-GRS was associated with a -0.07 (95% CI: -0.09, -0.05; P < 0.001) SD difference in memory score among NHW aged 50+, but no significant differences among NHB (β = -0.01; 95% CI: -0.04, 0.01; P = 0.546). [Correction added on 29 July 2014, after first online publication: confidence intervalshave been amended.] The estimated effect of the GRS was significantly smaller among NHB than NHW (P < 0.05) for both outcomes. CONCLUSION: This analysis provides evidence for differential relative effects of the GRS on dementia probability and memory score among NHW and NHB in a new, national data set.
Keywords: African Americans; Aged; Aged, 80 and over; Dementia; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Multifactorial Inheritance; Polymorphism, Genetic; Reproducibility of Results; Risk Assessment; Risk Factors; Surveys and Questionnaires; United States

Advance care planning and the quality of end-of-life care in older adults. - Bischoff, Kara E; Rebecca L. Sudore; Yinghui Miao; W John Boscardin; Alexander K Smith (J Am Geriatr Soc, 2013)
OBJECTIVES: To determine whether advance care planning influences quality of end-of-life care. DESIGN: In this observational cohort study, Medicare data and survey data from the Health and Retirement Study (HRS) were combined to determine whether advance care planning was associated with quality metrics. SETTING: The nationally representative HRS. PARTICIPANTS: Four thousand three hundred ninety-nine decedent subjects (mean age 82.6 at death, 55% women). MEASUREMENTS: Advance care planning (ACP) was defined as having an advance directive (AD), durable power of attorney (DPOA) or having discussed preferences for end-of-life care with a next of kin. Outcomes included previously reported quality metrics observed during the last month of life (rates of hospital admission, in-hospital death, >14 days in the hospital, intensive care unit admission, >1 emergency department visit, hospice admission, and length of hospice ≤ 3 days). RESULTS: Seventy-six percent of subjects engaged in ACP. Ninety-two percent of ADs stated a preference to prioritize comfort. After adjustment, subjects who engaged in ACP were less likely to die in a hospital (adjusted relative risk (aRR) = 0.87, 95% confidence interval (CI) = 0.80-0.94), more likely to be enrolled in hospice (aRR = 1.68, 95% CI = 1.43-1.97), and less likely to receive hospice for 3 days or less before death (aRR = 0.88, 95% CI = 0.85-0.91). Having an AD, a DPOA or an ACP discussion were each independently associated with a significant increase in hospice use (P < .01 for all). CONCLUSION: ACP was associated with improved quality of care at the end of life, including less in-hospital death and increased use of hospice. Having an AD, assigning a DPOA and conducting ACP discussions are all important elements of ACP.
Keywords: Adaptation, Psychological; Advance care planning; Aged, 80 and over; Female; Humans; Male; Quality of Life; Terminal Care; United States

The apolipoprotein E genotype predicts longitudinal transitions to mild cognitive impairment but not to Alzheimer's dementia: findings from a nationally representative study. - Brainerd, C. J.; V. F. Reyna; Ronald C Petersen; Glenn E Smith; Kenney, A. E.; C. J. Gross; Taub, E. S.; Brenda L Plassman; Gwenith G Fisher (Neuropsychology, 2013)
OBJECTIVE: The ε4 allele of the apolipoprotein E (APOE) genotype is the most widely accepted genetic risk factor for Alzheimer's dementia (AD), but findings on whether it is a risk factor for the AD prodrome, mild cognitive impairment (MCI), have been inconsistent. In a prospective longitudinal design, we investigated (a) whether transitions to MCI and other forms of neurocognitive impairment without dementia (CIND) are more frequent among normal ε4 carriers than among noncarriers and (b) whether subsequent transitions to AD from MCI and from other forms of CIND are more frequent among ε4 carriers than among noncarriers. METHOD: The frequency of the ε4 allele was studied in older adults (mean age > 70), who had participated in two or more waves of neuropsychological testing and diagnosis in the Aging, Demographics, and Memory Study (ADAMS) of the United States Department of Health and Human Services, National Institutes of Health, National Institute on Aging's Health and Retirement Study, conducted by the University of Michigan. The association between ε4 and longitudinal transitions to specific types of CIND and dementia can be determined with this data set. RESULTS: Epsilon 4 increased the rate of progression from normal functioning to MCI (58% of new diagnoses were carriers) but not to other forms of CIND. The rate of progression to AD from MCI or from other forms of CIND was not increased by ε4. CONCLUSIONS: The results support the hypothesis that ε4 is a risk factor for transitions from normal functioning to MCI but not for subsequent transitions to AD. In the ADAMS sample, the reason ε4 is elevated in AD individuals is because it is already elevated in MCI individuals, who are the primary source of new AD diagnoses.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Apolipoproteins E; Cognitive Dysfunction; disease progression; Female; Genetic Predisposition to Disease; Genetic Testing; Genotype; Humans; Logistic Models; Longitudinal Studies; Male; National Institutes of Health (U.S.); Neuropsychological tests; Risk Factors; United States

BMI change patterns and disability development of middle-aged adults with diabetes: a dual trajectory modeling approach. - Chiu, Ching-Ju; Linda A. Wray; Lu, Feng-hwa; Elizabeth A Beverly (J Gen Intern Med, 2013)
BACKGROUND: Few longitudinal studies have examined associations between body mass index (BMI) changes in adults with diabetes and the development of disability. OBJECTIVE: To investigate association patterns between BMI and disability in middle-aged adults with diabetes. DESIGN AND SETTING: Retrospective cohort design with data from the 1992-2006 Health and Retirement Study (HRS). A group-based joint trajectory method identified distinct BMI change trajectories and their link to subsequent disability trajectories. PARTICIPANTS: U.S. nationally representative adults aged 51-61 who reported a diagnosis of diabetes in the 1992 HRS (N = 1,064). MEASUREMENTS: BMI and self-reported disability score were the main variables. Sociodemographic, clinical, behavioral, and diabetes-related factors were also examined. RESULTS: Four distinct weight trajectories (stable normal weight, 28.7 %; stable overweight, 46.2 %; loss and regain obese, 18.0 %; weight cumulating morbidly obese, 7.1 %) and three disability trajectories (little or low increase, 34.4 %; moderate increase, 45.4 %; chronic high increase, 20.2 %) best characterized the long-term patterns of BMI and disability change in middle-aged adults with diabetes. Adults in stable normal weight had the highest probability of being in the little/low increase disability group; however, one in five adults in that group progressed into chronic high disability, a higher proportion compared to the stable overweight group. CONCLUSIONS: Although there were various ways in which the two trajectories were linked, the beneficial impacts of optimizing weight in adults with diabetes were supported. In addition, the complexity of diabetes control in those with relatively normal weight was highlighted from this study.
Keywords: Activities of Daily Living; Body Mass Index; Diabetes Mellitus, Type 2; Disability Evaluation; Disabled Persons; Female; Humans; Longitudinal Studies; Male; Middle Aged; Models, Statistical; Obesity; Obesity, Morbid; Overweight; Retrospective Studies; United States; Weight Gain; Weight Loss

Chiropractic use and changes in health among older medicare beneficiaries: a comparative effectiveness observational study. - Paula A Weigel; Jason Hockenberry; Suzanne E Bentler; Frederic D Wolinsky (J Manipulative Physiol Ther, 2013)
OBJECTIVE: The purpose of this study was to investigate the effect of chiropractic on 5 outcomes among Medicare beneficiaries: increased difficulties performing activities of daily living (ADLs), instrumental ADLs (IADLs), and lower body functions, as well as lower self-rated health and increased depressive symptoms. METHODS: Among all beneficiaries, we estimated the effect of chiropractic use on changes in health outcomes among those who used chiropractic compared with those who did not, and among beneficiaries with back conditions, we estimated the effect of chiropractic use relative to medical care, both during a 2- to 15-year period. Two analytic approaches were used--one assumed no selection bias, whereas the other adjusted for potential selection bias using propensity score methods. RESULTS: Among all beneficiaries, propensity score analyses indicated that chiropractic use led to comparable outcomes for ADLs, IADLs, and depressive symptoms, although there were increased risks associated with chiropractic for declines in lower body function and self-rated health. Propensity score analyses among beneficiaries with back conditions indicated that chiropractic use led to comparable outcomes for ADLs, IADLs, lower body function, and depressive symptoms, although there was an increased risk associated with chiropractic use for declines in self-rated health. CONCLUSION: The evidence in this study suggests that chiropractic treatment has comparable effects on functional outcomes when compared with medical treatment for all Medicare beneficiaries, but increased risk for declines in self-rated health among beneficiaries with back conditions.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Cohort Studies; Databases, Factual; Disability Evaluation; Female; Geriatric Assessment; Humans; Low Back Pain; Male; Manipulation, Chiropractic; Medicare; Mobility Limitation; Musculoskeletal Diseases; Patient Satisfaction; Quality of Life; Risk Assessment; Sex Factors; Treatment Outcome; United States

Cognition and take-up of subsidized drug benefits by Medicare beneficiaries. - Ifedayo Kuye; Richard G Frank; J. Michael McWilliams (JAMA Intern Med, 2013)
IMPORTANCE: Take-up of the Medicare Part D low-income subsidy (LIS) by eligible beneficiaries has been low despite the attractive drug coverage it offers at no cost to beneficiaries and outreach efforts by the Social Security Administration. OBJECTIVE: To examine the role of beneficiaries' cognitive abilities in explaining this puzzle. DESIGN AND SETTING: Analysis of survey data from the nationally representative Health and Retirement Study. PARTICIPANTS: Elderly Medicare beneficiaries who were likely eligible for the LIS, excluding Medicaid and Supplemental Security Income recipients who automatically receive the subsidy without applying. MAIN OUTCOMES AND MEASURES: Using survey assessments of overall cognition and numeracy from 2006 to 2010, we examined how cognitive abilities were associated with self-reported Part D enrollment, awareness of the LIS, and application for the LIS. We also compared out-of-pocket drug spending and premium costs between LIS-eligible beneficiaries who did and did not report receipt of the LIS. Analyses were adjusted for sociodemographic characteristics, household income and assets, health status, and presence of chronic conditions. RESULTS: Compared with LIS-eligible beneficiaries in the top quartile of overall cognition, those in the bottom quartile were significantly less likely to report Part D enrollment (adjusted rate, 63.5% vs 52.0%; P = .002), LIS awareness (58.3% vs 33.3%; P = .001), and LIS application (25.5% vs 12.7%; P < .001). Lower numeracy was also associated with lower rates of Part D enrollment (P = .03) and LIS application (P = .002). Reported receipt of the LIS was associated with significantly lower annual out-of-pocket drug spending (adjusted mean difference, -$256; P = .02) and premium costs (-$273; P = .02). CONCLUSIONS AND RELEVANCE: Among Medicare beneficiaries likely eligible for the Part D LIS, poorer cognition and numeracy were associated with lower reported take-up. Current educational and outreach efforts encouraging LIS applications may not be sufficient for beneficiaries with limited abilities to process and respond to information. Additional policies may be needed to extend the financial protection conferred by the LIS to all eligible seniors.
Keywords: Cognition; Comprehension; Cost Sharing; Eligibility Determination; Health Care Surveys; Humans; Medicare; Medicare Part D; Poverty; United States

Cohorts based on decade of death: no evidence for secular trends favoring later cohorts in cognitive aging and terminal decline in the AHEAD study. - Hülür, Gizem; Frank J Infurna; Ram, Nilam; Denis Gerstorf (Psychol Aging, 2013)
Studies of birth-year cohorts examined over the same age range often report secular trends favoring later-born cohorts, who are cognitively fitter and show less steep cognitive declines than earlier-born cohorts. However, there is initial evidence that those advantages of later-born cohorts do not carry into the last years of life, suggesting that pervasive mortality-related processes minimize differences that were apparent earlier in life. Elaborating this work from an alternative perspective on cohort differences, we compared rates of cognitive aging and terminal decline in episodic memory between cohorts based on the year participants had died, earlier (between 1993 and 1999) or later in historical time (between 2000 and 2010). Specifically, we compared trajectories of cognitive decline in 2 death-year cohorts of participants in the Asset and Health Dynamics Among the Oldest Old study that were matched on age at death and education and controlled for a variety of additional covariates. Results revealed little evidence of secular trends favoring later cohorts. To the contrary, the cohort that died in the 2000s showed a less favorable trajectory of age-related memory decline than the cohort that died in the 1990s. In examinations of change in relation to time to death, the cohort dying in the 2000s experienced even steeper terminal declines than the cohort dying in the 1990s. We suggest that secular increases in "manufacturing" survival may exacerbate age- and mortality-related cognitive declines among the oldest old.
Keywords: Aged; Aged, 80 and over; Aging; Death; Epidemiologic Research Design; Female; Health Surveys; Humans; Longitudinal Studies; Male; Memory Disorders; Memory, Episodic; Time Factors; United States

Disability during the last two years of life. - Alexander K Smith; Louise C Walter; Yinghui Miao; W John Boscardin; Kenneth E Covinsky (JAMA Intern Med, 2013)
IMPORTANCE: Whereas many persons at advanced ages live independently and are free of disability, we know little about how likely older people are to be disabled in the basic activities of daily living that are necessary for independent living as they enter the last years of life. OBJECTIVE: To determine national estimates of disability during the last 2 years of life. DESIGN: Prospective cohort study. SETTING: A nationally representative study of older adults in the United States. PARTICIPANTS: Participants 50 years and older who died while enrolled in the Health and Retirement Study between 1995 and 2010. Each participant was interviewed once at a varying time point in the last 24 months of life. We used these interviews to calculate national estimates of the prevalence of disability across the 2 years prior to death. We modeled the prevalence of disability in the 2 years prior to death for groups defined by age at death and sex. MAIN OUTCOMES AND MEASURES: Disability was defined as need for help with at least 1 of the following activities of daily living: dressing, bathing, eating, transferring, walking across the room, and using the toilet. RESULTS: There were 8232 decedents (mean [SD] age at death, 79 [11] years; 52% women). The prevalence of disability increased from 28% (95% CI, 24%-31%) 2 years before death to 56% (95% CI, 52%-60%) in the last month of life. Those who died at the oldest ages were much more likely to have disability 2 years before death (ages 50-69 years, 14%; 70-79 years, 21%; 80-89 years, 32%; 90 years or more, 50%; P for trend, <.001). Disability was more common in women 2 years before death (32% [95% CI, 28%-36%]) than men (21% [95% CI, 18%-25%]; P < .001), even after adjustment for older age at death. CONCLUSIONS AND RELEVANCE: Those who live to an older age are likely to be disabled, and thus in need of caregiving assistance, many months or years prior to death. Women have a substantially longer period of end-of-life disability than men.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Disability Evaluation; Disabled Persons; Educational Status; Female; Frail Elderly; Humans; Income; Longitudinal Studies; Male; Marital Status; Middle Aged; Prospective Studies; Sex Distribution; Socioeconomic factors; United States

Fall-associated difficulty with activities of daily living in functionally independent individuals aged 65 to 69 in the United States: a cohort study. - Nishant K. Sekaran; Choi, Hwajung; Rodney A. Hayward; Kenneth M. Langa (J Am Geriatr Soc, 2013)
OBJECTIVES: To determine whether falling would be a marker for future difficulty with activities of daily (ADLs) that would vary according to fall frequency and associated injury. DESIGN: Longitudinal analysis. SETTING: Community. PARTICIPANTS: Nationally representative cohort of 2,020 community-living, functionally independent older adults aged 65 to 69 at baseline followed from 1998 to 2008. MEASUREMENTS: ADL difficulty. RESULTS: Experiencing one fall with injury (odds ratio (OR) = 1.78, 95% confidence interval (CI) = 1.29-2.48), at least two falls without injury (OR = 2.36, 95% CI = 1.80-3.09), or at least two falls with at least one injury (OR = 3.75, 95% CI = 2.55-5.53) in the prior 2 years was independently associated with higher rates of ADL difficulty after adjustment for sociodemographic, behavioral, and clinical covariates. CONCLUSION: Falling is an important marker for future ADL difficulty in younger, functionally independent older adults. Individuals who fall frequently or report injury are at highest risk.
Keywords: Accidental Falls; Activities of Daily Living; Aged; Aging; Disability Evaluation; Disabled Persons; Female; Follow-Up Studies; Geriatric Assessment; Health Status; Humans; Male; Odds Ratio; Retrospective Studies; Risk Factors; United States; Wounds and Injuries

Health status and behavioral risk factors in older adult Mexicans and Mexican immigrants to the United States. - Emma Aguila; José J Escarce; Leng, Mei; Morales, Leo (J Aging Health, 2013)
OBJECTIVE: Investigate the "salmon-bias" hypothesis, which posits that Mexicans in the U.S. return to Mexico due to poor health, as an explanation for the Hispanic health paradox in which Hispanics in the United States are healthier than might be expected from their socioeconomic status. METHOD: Sample includes Mexicans age 50 years or above living in the United States and Mexico from the 2003 Mexican Health and Aging Study and the 2004 Health and Retirement Study. Logistic regressions examine whether nonmigrants or return migrants have different odds than immigrants of reporting a health outcome. RESULTS: The salmon-bias hypothesis holds for select health outcomes. However, nonmigrants and return migrants have better health outcomes than immigrants on a variety of indicators. DISCUSSION: Overall, the results of this study do not support the salmon-bias hypothesis; other explanations for the paradox could be explored.
Keywords: Aged; Emigrants and Immigrants; Emigration and Immigration; Female; Health Status; Health Surveys; Humans; Male; Mexican Americans; Mexico; Middle Aged; Risk Factors; Risk-Taking; Social Class; United States

Hospital and nursing home use from 2002 to 2008 among U.S. older adults with cognitive impairment, not dementia in 2002. - Daniel O. Clark; Timothy E. Stump; Tu, Wanzhu; Douglas K Miller; Kenneth M. Langa; Frederick W Unverzagt; Christopher M. Callahan (Alzheimer Dis Assoc Disord, 2013)
Little is known about health care use in the cognitive impairment, not dementia (CIND) subpopulation. Using a cohort of 7130 persons aged 71 years or over from the Health and Retirement Survey, we compared mean and total health care use from 2002 to 2008 for those with no cognitive impairment, CIND, or dementia in 2002. Cognitive status was determined using a validated method based on self or proxy interview measures. Health care use was also based on self or proxy reports. On the basis of the Health and Retirement Survey, the CIND subpopulation in 2002 was 5.3 million or 23% of the total population 71 years of age or over. Mean hospital nights was similar and mean nursing home nights was less in persons with CIND compared with persons with dementia. The CIND subpopulation, however, had more total hospital and nursing home nights--71,000 total hospital nights and 223,000 total nursing home nights versus 32,000 hospital nights and 138,000 nursing home nights in the dementia subpopulation. A relatively large population and high health care use result in a large health care impact of the CIND subpopulation.
Keywords: Aged; Aged, 80 and over; Aging; Cognition Disorders; Dementia; Female; Homes for the Aged; Hospitalization; Humans; Male; Nursing homes; United States

Impact of cigarette smoking on utilization of nursing home services. - Kenneth E. Warner; Ryan J McCammon; Brant E Fries; Kenneth M. Langa (Nicotine Tob Res, 2013)
INTRODUCTION: Few studies have examined the effects of smoking on nursing home utilization, generally using poor data on smoking status. No previous study has distinguished utilization for recent from long-term quitters. METHODS: Using the Health and Retirement Study, we assessed nursing home utilization by never-smokers, long-term quitters (quit >3 years), recent quitters (quit ≤3 years), and current smokers. We used logistic regression to evaluate the likelihood of a nursing home admission. For those with an admission, we used negative binomial regression on the number of nursing home nights. Finally, we employed zero-inflated negative binomial regression to estimate nights for the full sample. RESULTS: Controlling for other variables, compared with never-smokers, long-term quitters have an odds ratio (OR) for nursing home admission of 1.18 (95% CI: 1.07-1.2), current smokers 1.39 (1.23-1.57), and recent quitters 1.55 (1.29-1.87). The probability of admission rises rapidly with age and is lower for African Americans and Hispanics, more affluent respondents, respondents with a spouse present in the home, and respondents with a living child. Given admission, smoking status is not associated with length of stay (LOS). LOS is longer for older respondents and women and shorter for more affluent respondents and those with spouses present. CONCLUSIONS: Compared with otherwise identical never-smokers, former and current smokers have a significantly increased risk of nursing home admission. That recent quitters are at greatest risk of admission is consistent with evidence that many stop smoking because they are sick, often due to smoking.
Keywords: Age Factors; Aged; Aged, 80 and over; Black or African American; Cross-Sectional Studies; Female; Hispanic or Latino; Humans; Length of Stay; Logistic Models; Longitudinal Studies; Male; Middle Aged; Nursing homes; Risk; Self Report; Smoking; Socioeconomic factors; United States; White People

Latent heterogeneity in long-term trajectories of body mass index in older adults. - Anda Botoseneanu; Jersey Liang (J Aging Health, 2013)
OBJECTIVE: To evaluate latent heterogeneity in long-term trajectories of body weight in older adults. METHODS: We analyzed 14-year longitudinal data on 10,314 older adults from the Health and Retirement Study. Semiparametric mixture models identified latent subgroups of similar trajectories of body mass index (BMI). RESULTS: Five distinct trajectory subgroups emerged: normal starting-BMI with accelerated increase over time (trajectory #1), overweight and increasing (trajectory #2), borderline-obese and increasing (trajectory #3), obese and increasing (trajectory #4), and morbidly obese with decelerating gain (trajectory #5). Blacks and Hispanics had greater risk of membership in ascending high-BMI trajectory groups. Females had approximately half the risk of following overweight and obese increasing BMI trajectories compared with males. DISCUSSION: Distinct latent subgroups of BMI trajectories and significant racial/ethnic and gender trajectory heterogeneity exist in the older adult population. The propensity of men and minorities to experience high-risk BMI trajectories may exacerbate existing disparities in morbidity/ mortality in older age.
Keywords: Aging; Black or African American; Body Mass Index; Female; Hispanic or Latino; Humans; Longitudinal Studies; Male; Middle Aged; Obesity; Obesity, Morbid; Overweight; Risk Factors; Sex Distribution; United States

Monetary costs of dementia in the United States. - Michael D Hurd; Martorell, Paco; Delavande, Adeline; Kathleen J Mullen; Kenneth M. Langa (N Engl J Med, 2013)
BACKGROUND: Dementia affects a large and growing number of older adults in the United States. The monetary costs attributable to dementia are likely to be similarly large and to continue to increase. METHODS: In a subsample (856 persons) of the population in the Health and Retirement Study (HRS), a nationally representative longitudinal study of older adults, the diagnosis of dementia was determined with the use of a detailed in-home cognitive assessment that was 3 to 4 hours in duration and a review by an expert panel. We then imputed cognitive status to the full HRS sample (10,903 persons, 31,936 person-years) on the basis of measures of cognitive and functional status available for all HRS respondents, thereby identifying persons in the larger sample with a high probability of dementia. The market costs associated with care for persons with dementia were determined on the basis of self-reported out-of-pocket spending and the utilization of nursing home care; Medicare claims data were used to identify costs paid by Medicare. Hours of informal (unpaid) care were valued either as the cost of equivalent formal (paid) care or as the estimated wages forgone by informal caregivers. RESULTS: The estimated prevalence of dementia among persons older than 70 years of age in the United States in 2010 was 14.7%. The yearly monetary cost per person that was attributable to dementia was either $56,290 (95% confidence interval [CI], $42,746 to $69,834) or $41,689 (95% CI, $31,017 to $52,362), depending on the method used to value informal care. These individual costs suggest that the total monetary cost of dementia in 2010 was between $157 billion and $215 billion. Medicare paid approximately $11 billion of this cost. CONCLUSIONS: Dementia represents a substantial financial burden on society, one that is similar to the financial burden of heart disease and cancer. (Funded by the National Institute on Aging.).
Keywords: Aged; Aged, 80 and over; Cost of Illness; Dementia; Female; Health Care Costs; Home Care Services; Home Nursing; Humans; Longitudinal Studies; Male; Medicare; Middle Aged; Nursing homes; United States

Out-of-pocket spending in the last five years of life. - Amy Kelley; Kathleen McGarry; Sean Fahle; Samuel M Marshall; Qingling Du; Jonathan S Skinner (J Gen Intern Med, 2013)
BACKGROUND: A key objective of the Medicare program is to reduce risk of financial catastrophe due to out-of-pocket healthcare expenditures. Yet little is known about cumulative financial risks arising from out-of-pocket healthcare expenditures faced by older adults, particularly near the end of life. DESIGN: Using the nationally representative Health and Retirement Study (HRS) cohort, we conducted retrospective analyses of Medicare beneficiaries' total out-of-pocket healthcare expenditures over the last 5 years of life. PARTICIPANTS: We identified HRS decedents between 2002 and 2008; defined a 5 year study period using each subject's date of death; and excluded those without Medicare coverage at the beginning of this period (n = 3,209). MAIN MEASURES: We examined total out-of-pocket healthcare expenditures in the last 5 years of life and expenditures as a percentage of baseline household assets. We then stratified results by marital status and cause of death. All measurements were adjusted for inflation to 2008 US dollars. RESULTS: Average out-of-pocket expenditures in the 5 years prior to death were $38,688 (95 % Confidence Interval $36,868, $40,508) for individuals, and $51,030 (95 % CI $47,649, $54,412) for couples in which one spouse dies. Spending was highly skewed, with the median and 90th percentile equal to $22,885 and $89,106, respectively, for individuals, and $39,759 and $94,823, respectively, for couples. Overall, 25 % of subjects' expenditures exceeded baseline total household assets, and 43 % of subjects' spending surpassed their non-housing assets. Among those survived by a spouse, 10 % exceeded total baseline assets and 24 % exceeded non-housing assets. By cause of death, average spending ranged from $31,069 for gastrointestinal disease to $66,155 for Alzheimer's disease. CONCLUSION: Despite Medicare coverage, elderly households face considerable financial risk from out-of-pocket healthcare expenses at the end of life. Disease-related differences in this risk complicate efforts to anticipate or plan for health-related expenditures in the last 5 years of life.
Keywords: Aged; Cause of Death; Female; Health Expenditures; Health Services for the Aged; Humans; Male; Marital Status; Medicare; Retrospective Studies; Socioeconomic factors; Terminal Care; United States

Pain among older Hispanics in the United States: is acculturation associated with pain? - Jimenez, Nathalia; Dansie, Elizabeth; Buchwald, Dedra; Goldberg, Jack (Pain Med, 2013)
BACKGROUND: Previous studies suggest that acculturation may influence the experience of pain. STUDY DESIGN: We conducted a cross-sectional study to estimate the association between acculturation and the prevalence, intensity, and functional limitations of pain in older Hispanic adults in the United States. METHODS SUBJECTS: Participants were English- (HE) and Spanish-speaking (HS) Hispanic and non-Hispanic White (NHW) individuals aged 50 years and older who were interviewed for the Health and Retirement Study during 1998-2008. MEASURES: We measured: 1) acculturation as defined by language used in interviews, and 2) the presence, intensity, and functional limitations of pain. ANALYSIS: We applied logistic regression using generalized estimating equations, with NHW as the reference category. RESULTS: Among 18,593 participants (16,733 NHW, 824 HE, and 1,036 HS), HS had the highest prevalence (odds ratio [OR] = 1.3; 95% confidence interval [CI  = 1.1-1.4) and intensity (OR = 1.6; 95% CI = 1.4-1.9) of pain, but these differences were not significant after adjusting for age, sex, years of education, immigration status (U.S.- vs non-U.S-born), and health status (number of health conditions). Even after adjustment, HS reported the lowest levels of functional limitation (OR = 0.7; 95% CI 0.6-0.9). CONCLUSION: Pain prevalence and intensity were not related to acculturation after adjusting for sociodemographic factors, while functional limitation was significantly lower among HS even after adjusting for known risk factors. Future studies should explore the reasons for this difference.
Keywords: Acculturation; Aged; Confidence Intervals; Cross-Sectional Studies; Female; Health Status; Hispanic or Latino; Humans; Language; Logistic Models; Male; Middle Aged; Odds Ratio; pain; Pain Measurement; Prevalence; Socioeconomic factors; United States

Pain as a risk factor for disability or death. - James S Andrews; Irena Cenzer; Yelin, Edward; Kenneth E Covinsky (J Am Geriatr Soc, 2013)
OBJECTIVES: To determine whether pain predicts future activity of daily living (ADL) disability or death in individuals aged 60 and older. DESIGN: Prospective cohort study. SETTING: The 1998 to 2008 Health and Retirement Study (HRS), a nationally representative study of older community-living individuals. PARTICIPANTS: Twelve thousand six hundred thirty-one participants in the 1998 HRS aged 60 and older who did not need help in any ADL. MEASUREMENTS: Participants reporting that they had moderate or severe pain most of the time were defined as having significant pain. The primary outcome was time to development of ADL disability or death over 10 yrs, assessed at five successive 2-year intervals. ADL disability was defined as needing help performing any ADL: bathing, dressing, transferring, toileting, eating, or walking across a room. A discrete hazards survival model was used to examine the relationship between pain and incident disability over each 2-year interval using only participants who started the interval with no ADL disability. Several potential confounders were adjusted for at the start of each interval: demographic factors, seven chronic health conditions, and functional limitations (ADL difficulty and difficulty with five measures of mobility). RESULTS: At baseline, 2,283 (18%) participants had significant pain. Participants with pain were more likely (all P < .001) to be female (65% vs 54%), have ADL difficulty (e.g., transferring 12% vs 2%, toileting 11% vs 2%), have difficulty walking several blocks (60% vs 21%), and have difficulty climbing one flight of stairs (40% vs 12%). Over 10 years, participants with pain were more likely to develop ADL disability or death (58% vs 43%, unadjusted hazard ratio (HR) = 1.67, 95% confidence interval (CI) = 1.57-1.79), although after adjustment for confounders, participants with pain were not at greater risk for ADL disability or death (HR = 0.98, 95% CI = 0.91-1.07). Adjustment for functional status almost entirely explained the difference between the unadjusted and adjusted results. CONCLUSION: Although there are strong cross-sectional relationships between pain and functional limitations, individuals with pain are not at higher risk of subsequent disability or death after accounting for functional limitations. Like many geriatric syndromes, pain and disability may represent interrelated phenomena that occur simultaneously and require unified treatment paradigms.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cohort Studies; Disabled Persons; Female; Geriatric Assessment; Health Status; Humans; Life Style; Male; Middle Aged; pain; Prevalence; Prognosis; Prospective Studies; Severity of Illness Index; Sex Distribution; Sex Factors; United States

Patterns of older Americans' health care utilization over time. - Richard J. Manski; John F Moeller; Haiyan Chen; Jody Schimmel; Patricia A St Clair; John V Pepper (Am J Public Health, 2013)
OBJECTIVES: We analyzed correlates of older Americans' continuous and transitional health care utilization over 4 years. METHODS: We analyzed data for civilian, noninstitutionalized US individuals older than 50 years from the 2006 and 2008 waves of the Health and Retirement Study. We estimated multinomial logistic models of persistent and intermittent use of physician, inpatient hospital, home health, and outpatient surgery over the 2004-2008 survey periods. RESULTS: Individuals with worse or worsening health were more likely to persistently use medical care and transition into care and not transition out of care over time. Financial variables were less often significant and, when significant, were often in an unexpected direction. CONCLUSIONS: Older individuals' health and changes in health are more strongly correlated with persistence of and changes in care-seeking behavior over time than are financial status and changes in financial status. The more pronounced sensitivity to health status and changes in health are important considerations in insurance and retirement policy reforms.
Keywords: Aged; Aged, 80 and over; Ambulatory Surgical Procedures; Delivery of Health Care; Female; Health Services; Health Status; Health Surveys; Home Care Services; Hospitalization; Humans; Income; Insurance Coverage; Logistic Models; Longitudinal Studies; Male; Middle Aged; Office Visits; Patient Acceptance of Health Care; Time Factors; United States

Predicting 10-year mortality for older adults. - Cruz, Marisa; Kenneth E Covinsky; Eric W Widera; Stijacic-Cenzer, Irena; Sei J. Lee (JAMA, 2013)
Keywords: Aged; Aged, 80 and over; Cohort Studies; Female; Forecasting; Humans; Kaplan-Meier Estimate; Life Expectancy; Male; Middle Aged; Mortality; Risk Assessment; United States

Race differences in the relationship between formal volunteering and hypertension. - Jane Tavares; Jeffrey A Burr; Jan E Mutchler (J Gerontol B Psychol Sci Soc Sci, 2013)
OBJECTIVES: This study investigated race differences in the relationship between formal volunteering and hypertension prevalence among middle-aged and older adults. METHOD: Using data from the 2004 and 2006 Health and Retirement Study (N = 5,666; 677 African Americans and 4,989 whites), we examined regression models stratified by race to estimate relationships among hypertension prevalence, systolic and diastolic blood pressure, and volunteer status and hours spent volunteering among persons aged 51 years old and older. RESULTS: White volunteers had a lower risk of hypertension than white nonvolunteers. A threshold effect was also present; compared with nonvolunteers, volunteering a moderate number of hours was associated with lowest risk of hypertension for whites. Results for hypertension were consistent with results from alternative models of systolic and diastolic blood pressure. We found no statistically significant relationship between volunteering activity and hypertension/blood pressure for African Americans. DISCUSSION: There may be unmeasured cultural differences related to the meaning of volunteering and contextual differences in volunteering that account for the race differences we observed. Research is needed to determine the pathways through which volunteering is related to hypertension risk and that may help explain race differences identified here.
Keywords: Black or African American; Blood pressure; Female; Humans; Hypertension; Logistic Models; Male; Middle Aged; Prevalence; Risk Factors; United States; Volunteers; White People

The role of pain in understanding racial/ethnic differences in the frequency of physical activity among older adults. - Grubert, Elizabeth; Tamara A. Baker; McGeever, Kelly; Benjamin A Shaw (J Aging Health, 2013)
OBJECTIVE: To evaluate racial/ethnic differences in physical activity among white, black, and Hispanic adults aged 65 years and older, and to assess the potential role of pain as a mediator. METHODS: Analyses were based on data from the 2008 Health and Retirement Study. Logistic regression was used to evaluate associations between race/ethnicity and pain and the odds of regular physical activity. RESULTS: Compared to Whites, the odds of both light physical activity and moderate/vigorous physical activity were lower among Blacks, but not Hispanics. A graded inverse association between levels of pain severity and the odds of physical activity was found, but pain did not mediate racial/ethnic differences in physical activity. DISCUSSION: When compared to Whites, older Blacks appear to have relatively low rates of physical activity even without comparatively high levels of pain, while older Hispanics experience relatively high rates of pain, but are perhaps more resilient to the effects of pain on physical activity.
Keywords: Aged; Aged, 80 and over; Black or African American; Female; Health Surveys; Hispanic or Latino; Humans; Male; Motor Activity; pain; Severity of Illness Index; United States; White People

Self-rated health and morbidity onset among late midlife U.S. adults. - Kenzie Latham; Chuck W Peek (J Gerontol B Psychol Sci Soc Sci, 2013)
OBJECTIVES: Although self-rated health (SRH) is recognized as a strong and consistent predictor of mortality and functional health decline, there are relatively few studies examining SRH as a predictor of morbidity. This study examines the capacity of SRH to predict the onset of chronic disease among the late midlife population (ages 51-61 years). METHOD: Utilizing the first 9 waves (1992-2008) of the Health and Retirement Study, event history analysis was used to estimate the effect of SRH on incidence of 6 major chronic diseases (coronary heart disease, diabetes, stroke, lung disease, arthritis, and cancer) among those who reported none of these conditions at baseline (N = 4,770). RESULTS: SRH was a significant predictor of onset of any chronic condition and all specific chronic conditions excluding cancer. The effect was particularly pronounced for stroke. DISCUSSION: This research provides the strongest and most comprehensive evidence to date of the relationship between SRH and incident morbidity.
Keywords: Chronic disease; Cohort Studies; Female; Health Status; Humans; Male; Middle Aged; Morbidity; Predictive Value of Tests; Self Concept; Self Report; United States

The socioeconomic origins of physical functioning among older U.S. adults. - Jennifer Karas Montez (Adv Life Course Res, 2013)
Mounting evidence finds that adult health reflects socioeconomic circumstances (SES) in early life and adulthood. However, it is unclear how the health consequences of SES in early life and adulthood accumulate-for example, additively, synergistically. This study tests four hypotheses about how the health effects of early-life SES (measured by parental education) and adult SES (measured by own education) accumulate to shape functional limitations, whether the accumulation differs between men and women, and the extent to which key mechanisms explain the accumulation. It uses data from the 1994-2010 Health and Retirement Study on U.S. adults 50-100 years of age (N=24,026). The physical functioning benefits of parental and own education accumulated additively among men. While the physical functioning benefits generally accumulated among women, the functioning benefits from one's own education were dampened among women with low-educated mothers. The dampening partly reflected a strong tie between mothers' education level and women's obesity risk. Taken together, the findings reveal subtle differences between men and women in the life course origins of physical functioning. They also shed light on a key mechanism-obesity-that may help explain why a growing number of studies find that early-life SES is especially important for women's health.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Educational Status; Female; Health Behavior; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Obesity; Sex Factors; Socioeconomic factors; United States

Spouses of stroke survivors may be at risk for poor cognitive functioning: a cross-sectional population-based study. - Peii Chen; Amanda L. Botticello (Top Stroke Rehabil, 2013)
BACKGROUND: Stroke often results in chronic disability and the need for long-term assistance, which is provided in large part by spouses. Stroke caregivers experience poorer health and well-being compared with non-caregivers, but less is known about the specific toll that caregiving may exact on cognitive functioning. OBJECTIVE: To investigate whether persons caring for a spouse who experienced a recent stroke may be at risk for poor cognitive functioning compared with non-caregivers. METHODS: Existing data from the United States' Health and Retirement Study (HRS) were used to identify 146 caregivers from among couples in which 1 individual reported surviving a recent stroke and experiencing functional limitations. This cross-sectional population-based analysis compared the stroke caregivers with 3,416 non-caregivers in time orientation, working memory, semantic memory, learning, and episodic memory. RESULTS: Overall, the caregiver group was considerably more disadvantaged than the non-caregiver group in terms of background characteristics, socioeconomic status, health, and well-being. Results of weighted Poisson regression models indicated that stroke caregivers were at risk for poorer performance than non-caregivers in working memory, semantic memory, learning, and episodic memory. The gap between stroke caregivers and non-caregivers in episodic memory remained after adjusting for systematic differences between the 2 groups across an array of risk factors. CONCLUSIONS: Spousal caregivers of stroke survivors may be at risk for poor cognitive functioning. More work is needed to identify the processes that may contribute to the diminished cognitive capacity among these adults so that interventions may be developed to reduce caregiver burden and promote cognitive health.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Community Health Planning; Cross-Sectional Studies; Female; Humans; Male; Neuropsychological tests; Retrospective Studies; Spouses; Stroke; Survivors; United States

Stroke-associated differences in rates of activity of daily living loss emerge years before stroke onset. - Benjamin D Capistrant; Qianyi Wang; Sze Y Liu; M. Maria Glymour (J Am Geriatr Soc, 2013)
OBJECTIVES: To compare typical age-related changes in activities of daily living (ADLs) independence in stroke-free adults with long-term ADL trajectories before and after stroke. DESIGN: Prospective, observational study. SETTING: Community-dwelling Health and Retirement Study (HRS) cohort. PARTICIPANTS: HRS participants who were stroke free in 1998 and were followed through 2008 (average follow-up 7.9 years) (N = 18,441). MEASUREMENTS: Strokes were assessed using self- or proxy-report of a doctor's diagnosis and month and year of event. Logistic regression was used to compare within-person changes in odds of self-reported independence in five ADLs in those who remained stroke free throughout follow-up (n = 16,816), those who survived a stroke (n = 1,208), and those who had a stroke and did not survive to participate in another interview (n = 417). Models were adjusted for demographic and socioeconomic covariates. RESULTS: Even before stroke, those who later developed stroke had significantly lower ADL independence and were experiencing faster independence losses than similar-aged individuals who remained stroke free. Of those who developed a stroke, survivors experienced slower pre-stroke loss of ADL independence than those who died. ADL independence declined at the time of stroke and decline continued afterwards. CONCLUSION: In adults at risk of stroke, disproportionate ADL limitations emerge well before stroke onset. Excess disability in stroke survivors should not be entirely attributed to effects of acute stroke or quality of acute stroke care. Although there are many possible causal pathways between ADL and stroke, the association may be noncausal. For example, ADL limitations may be a consequence of stroke risk factors (e.g., diabetes mellitus) or early cerebrovascular ischemia.
Keywords: Activities of Daily Living; Age of Onset; Aged; Aged, 80 and over; Bayes Theorem; Disability Evaluation; Disabled Persons; Female; Follow-Up Studies; Geriatric Assessment; Humans; Male; Middle Aged; Morbidity; Prospective Studies; Risk Assessment; Risk Factors; Socioeconomic factors; Stroke; Stroke Rehabilitation; Survival Rate; Survivors; Time Factors; United States

Symptoms of depression in survivors of severe sepsis: a prospective cohort study of older Americans. - Dimitry S Davydow; Catherine L Hough; Kenneth M. Langa; Theodore J Iwashyna (Am J Geriatr Psychiatry, 2013)
OBJECTIVES: To examine if incident severe sepsis is associated with increased risk of subsequent depressive symptoms and to assess which patient characteristics are associated with increased risk of depressive symptoms. DESIGN: Prospective longitudinal cohort study. SETTING: Population-based cohort of older U.S. adults interviewed as part of the Health and Retirement Study (1998-2006). PARTICIPANTS: A total of 439 patients who survived 471 hospitalizations for severe sepsis and completed at least one follow-up interview. MEASUREMENTS: Depressive symptoms were assessed with a modified version of the Center for Epidemiologic Studies Depression Scale. Severe sepsis was identified using a validated algorithm in Medicare claims. RESULTS: The point prevalence of substantial depressive symptoms was 28% at a median of 1.2 years before sepsis, and remained 28% at a median of 0.9 years after sepsis. Neither incident severe sepsis (relative risk [RR]: 1.00; 95% confidence interval [CI]: 0.73, 1.34) nor severe sepsis-related clinical characteristics were significantly associated with subsequent depressive symptoms. These results were robust to potential threats from missing data or alternative outcome definitions. After adjustment, presepsis substantial depressive symptoms (RR: 2.20; 95% CI: 1.66, 2.90) and worse postsepsis functional impairment (RR: 1.08 per new limitation; 95% CI: 1.03, 1.13) were independently associated with substantial depressive symptoms after sepsis. CONCLUSIONS: The prevalence of substantial depressive symptoms in severe sepsis survivors is high but is not increased relative to their presepsis levels. Identifying this large subset of severe sepsis survivors at increased risk for major depression, and beginning interventions before hospital discharge, may improve outcomes.
Keywords: Aged; Aged, 80 and over; Cohort Studies; depression; Female; Hospitalization; Humans; Longitudinal Studies; Male; Poisson Distribution; Prospective Studies; Regression Analysis; Risk Factors; Sepsis; Severity of Illness Index; Survivors; United States

Trends in depressive symptom burden among older adults in the United States from 1998 to 2008. - Zivin, Kara; Paul A Pirraglia; Ryan J McCammon; Kenneth M. Langa; Sandeep Vijan (J Gen Intern Med, 2013)
CONTEXT: Diagnosis and treatment of depression has increased over the past decade in the United States. Whether self-reported depressive symptoms among older adults have concomitantly declined is unknown. OBJECTIVE: To examine trends in depressive symptoms among older adults in the US between 1998 and 2008. DESIGN: Serial cross-sectional analysis of six biennial assessments. SETTING: Health and Retirement Study (HRS), a nationally-representative survey. PATIENTS OR OTHER PARTICIPANTS Adults aged 55 and older (N = 16,184 in 1998). MAIN OUTCOME MEASURE: The eight-item Center for Epidemiologic Studies Depression scale (CES-D8) assessed three levels of depressive symptoms (none = 0, elevated = 4+, severe = 6+), adjusting for demographic and clinical characteristics. RESULTS: Having no depressive symptoms increased over the 10-year period from 40.9 % to 47.4 % (prevalence ratio [PR]: 1.16, 95 % CI: 1.13-1.19), with significant increases in those aged ≥ 60 relative to those aged 55-59. There was a 7 % prevalence reduction of elevated symptoms from 15.5 % to 14.2 % (PR: 0.93, 95 % CI: 0.88-0.98), which was most pronounced among those aged 80-84 in whom the prevalence of elevated symptoms declined from 14.3 % to 9.6 %. Prevalence of having severe depressive symptoms increased from 5.8 % to 6.8 % (PR: 1.17, 95 % CI: 1.06-1.28); however, this increase was limited to those aged 55-59, with the probability of severe symptoms increasing from 8.7 % to 11.8 %. No significant changes in severe symptoms were observed for those aged ≥ 60. CONCLUSIONS: Overall late-life depressive symptom burden declined significantly from 1998 to 2008. This decrease appeared to be driven primarily by greater reductions in depressive symptoms in the oldest-old, and by an increase in those with no depressive symptoms. These changes in symptom burden were robust to physical, functional, demographic, and economic factors. Future research should examine whether this decrease in depressive symptoms is associated with improved treatment outcomes, and if there have been changes in the treatment received for the various age cohorts.
Keywords: Age Factors; Aged; Aged, 80 and over; Cohort Studies; Cost of Illness; Cross-Sectional Studies; depression; Female; Humans; Male; Middle Aged; United States

Trends in late-life activity limitations in the United States: an update from five national surveys. - Vicki A Freedman; Brenda C Spillman; Patricia Andreski; Jennifer C. Cornman; Eileen M. Crimmins; Kramarow, Ellen; Lubitz, James; Linda G Martin; Sharon S. Merkin; Robert F. Schoeni; Teresa Seeman; Timothy A Waidmann (Demography, 2013)
This article updates trends from five national U.S. surveys to determine whether the prevalence of activity limitations among the older population continued to decline in the first decade of the twenty-first century. Findings across studies suggest that personal care and domestic activity limitations may have continued to decline for those ages 85 and older from 2000 to 2008, but generally were flat since 2000 for those ages 65-84. Modest increases were observed for the 55- to 64-year-old group approaching late life, although prevalence remained low for this age group. Inclusion of the institutional population is important for assessing trends among those ages 85 and older in particular.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Disabled Persons; Female; Health Surveys; Humans; Male; Mobility Limitation; Models, Statistical; United States

Type of high-school credentials and older age ADL and IADL limitations: is the GED credential equivalent to a diploma? - Sze Y Liu; Chavan, Niraj R.; M. Maria Glymour (Gerontologist, 2013)
PURPOSE: Educational attainment is a robust predictor of disability in elderly Americans: older adults with high-school (HS) diplomas have substantially lower disability than individuals who did not complete HS. General Educational Development (GED) diplomas now comprise almost 20% of new HS credentials issued annually in the United States but it is unknown whether the apparent health advantages of HS diplomas extend to GED credentials. This study examines whether adults older than 50 years with GEDs have higher odds of incident instrumental or basic activities of daily living (IADLs) limitations compared with HS degree holders. METHODS: We compared odds of incident IADL limitations by HS credential type using discrete-time survival models among 9,426 Health and Retirement Study participants followed from 1998 through 2008. RESULTS: HS degree holders had lower odds of incident IADLs than GED holders (OR = 0.72, 95% CI = 0.58, 0.90 and OR = 0.69, 95% CI = 0.56, 0.86 for ADLs and IADLs, respectively). There was no significant difference in odds of incident IADL limitations between GED holders and respondents without HS credentials (OR = 0.89, 95% CI = 0.71, 1.11 for ADLs; OR = 0.88, 95% CI = 0.70, 1.12 for IADLs). IMPLICATIONS: Although GEDs are widely accepted as equivalent to high school diplomas, they are not associated with comparable health advantages for physical limitations in older age.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Aging; Disabled Persons; Educational Status; Female; Follow-Up Studies; Humans; Kaplan-Meier Estimate; Logistic Models; Male; Socioeconomic factors; United States

Understanding heterogeneity in price elasticities in the demand for alcohol for older individuals. - Padmaja Ayyagari; Deb, Partha; Jason M. Fletcher; William T Gallo; Jody L Sindelar (Health Econ, 2013)
This paper estimates the price elasticity of demand for alcohol using Health and Retirement Study data. To account for unobserved heterogeneity in price responsiveness, we use finite mixture models. We recover two latent groups, one is significantly responsive to price, but the other is unresponsive. The group with greater responsiveness is disadvantaged in multiple domains, including health, financial resources, education and perhaps even planning abilities. These results have policy implications. The unresponsive group drinks more heavily, suggesting that a higher tax would fail to curb the negative alcohol-related externalities. In contrast, the more disadvantaged group is more responsive to price, thus suffering greater deadweight loss, yet this group consumes fewer drinks per day and might be less likely to impose negative externalities.
Keywords: Adult; Aged; Aged, 80 and over; Alcohol Drinking; Alcoholic Beverages; Behavior; Body Height; Costs and Cost Analysis; Female; Health Status; Humans; Male; Middle Aged; Models, Econometric; Socioeconomic factors; Taxes; United States

Urban neighbourhood unemployment history and depressive symptoms over time among late middle age and older adults. - Richard G Wight; Carol S Aneshensel; Barrett, Christopher; Michelle J Ko; Joshua Chodosh; Arun S Karlamangla (J Epidemiol Community Health, 2013)
BACKGROUND: Little is known about how a neighbourhood's unemployment history may set the stage for depressive symptomatology. This study examines the effects of urban neighbourhood unemployment history on current depressive symptoms and subsequent symptom trajectories among residentially stable late middle age and older adults. Contingent effects between neighbourhood unemployment and individual-level employment status (ie, cross-level interactions) are also assessed. METHODS: Individual-level survey data are from four waves (2000, 2002, 2004 and 2006) of the original cohort of the nationally representative US Health and Retirement Study. Neighbourhoods are operationalised with US Census tracts for which historical average proportion unemployed between 1990 and 2000 and change in proportion unemployed between 1990 and 2000 are used to characterise the neighbourhood's unemployment history. Hierarchical linear regressions estimate three-level (time, individual and neighbourhood) growth models. RESULTS: Symptoms in 2000 are highest among those residing in neighbourhoods characterised by high historical average unemployment beginning in 1990 and increasing unemployment between 1990 and 2000, net of a wide range of socio-demographic controls including individual-level employment status. These neighbourhood unemployment effects are not contingent upon individual-level employment status in 2000. 6-year trajectories of depressive symptoms decrease over time on average but are not significantly influenced by the neighbourhood's unemployment history. CONCLUSIONS: Given the current US recession, future studies that do not consider historical employment conditions may underestimate the mental health impact of urban neighbourhood context. The findings suggest that exposure to neighbourhood unemployment earlier in life may be consequential to mental health later in life.
Keywords: Age Factors; depression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Middle Aged; Multilevel Analysis; Residence Characteristics; Retirement; Risk Factors; Socioeconomic factors; Stress, Psychological; Surveys and Questionnaires; Time Factors; Unemployment; United States; Urban Population

Vascular depression: an early warning sign of frailty. - Daniel Paulson; Peter A Lichtenberg (Aging Ment Health, 2013)
OBJECTIVES: Frailty is a common geriatric disorder associated with activities of daily living (ADL) impairment, hospitalization, and death. Phenomenological evidence suggests that late-life depression (Katz, 2004 ), particularly vascular depression, may be a risk factor for frailty. This study tests that hypothesis. METHODS: We identified a sample of stroke-free women over the age of 80 from the Health and Retirement Survey. The sample included 984 respondents in 2000 (incidence sample). Of these, 459 were non-frail at baseline and still alive in 2004 (prevalence sample). Frail respondents experienced at least three of the following: wasting, exhaustion, weakness, slowness, and falls. Vascular depression was represented using two dummy variables. The first represented respondents with either high cerebrovascular burden (CVB; at least two cerebrovascular risk factors) or probable depression (score ≥3 on the 8-item Center for Epidemiological Studies Depression Scale (CES-D)), and the second represented respondents with both high CVB and probable depression. RESULTS: At baseline, the prevalence of frailty was 31.5%. Over four years the incidence of frailty was 31.8%. After controlling for age, education, ADL and IADL disability, arthritis, pulmonary disorders, cancer, and self-rated health, respondents with either high CVB or probable depression were more likely to be frail at baseline, and those with both were at even higher risk. Of those who were not frail at the 2000 wave, respondents who reported both high CVB and probable depression were more likely to become frail by 2004. DISCUSSION: These findings suggest that vascular depression is a prodrome for frailty.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cerebrovascular Disorders; depression; Disabled Persons; Female; Follow-Up Studies; Frail Elderly; Geriatric Assessment; Health Status; Humans; Incidence; Logistic Models; Male; Prevalence; Psychiatric Status Rating Scales; Risk Factors; Socioeconomic factors; United States

What do parents have to do with my cognitive reserve? Life course perspectives on twelve-year cognitive decline. - Hector M González; Wassim Tarraf; Mary E Bowen; Michelle D Johnson-Jennings; Gwenith G Fisher (Neuroepidemiology, 2013)
BACKGROUND/AIMS: To examine the cognitive reserve hypothesis by comparing the contribution of early childhood and life course factors related to cognitive functioning in a nationally representative sample of older Americans. METHODS: We examined a prospective, national probability cohort study (Health and Retirement Study; 1998-2010) of older adults (n=8,833) in the contiguous 48 United States. The main cognitive functioning outcome was a 35-point composite of memory (recall), mental status, and working memory tests. The main predictors were childhood socioeconomic position (SEP) and health, and individual-level adult achievement and health. RESULTS: Individual-level achievement indicators (i.e., education, income, and wealth) were positively and significantly associated with baseline cognitive function, while adult health was negatively associated with cognitive function. Controlling for individual-level adult achievement and other model covariates, childhood health presented a relatively small negative, but statistically significant association with initial cognitive function. Neither individual achievement nor childhood SEP was statistically linked to decline over time. CONCLUSIONS: Cognitive reserve purportedly acquired through learning and mental stimulation across the life course was associated with higher initial global cognitive functioning over the 12-year period in this nationally representative study of older Americans. We found little supporting evidence that childhood economic conditions were negatively associated with cognitive function and change, particularly when individual-level achievement is considered.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Cognitive Reserve; Cohort Studies; Female; Humans; Longevity; Longitudinal Studies; Male; Parents; Prospective Studies; Socioeconomic factors; United States

Women's receipt of Social Security retirement benefits: expectations compared to elections. - Gillen, Martie; Claudia J Heath (J Women Aging, 2013)
This research contributes knowledge regarding the options of early, normal, or delayed receipt of Social Security retirement benefits and research-based findings regarding women's expected and actual timing of election of Social Security retirement benefits. First, descriptive analyses of alternative retirement options, based on Social Security retirement benefit rules, are provided. Second, the 2000, 2002, 2004, and 2006 waves of Health and Retirement Study (HRS) data are used to analyze women's anticipated and actual election of Social Security retirement benefits. Third, based on these considerations, recommendations are made regarding Social Security retirement benefit receipt alternatives.
Keywords: Age Factors; Aged; Decision making; Female; Humans; Longitudinal Studies; Middle Aged; Pensions; Retirement; Social Security; Socioeconomic factors; Time Factors; United States

Antigenic challenge in the etiology of autoimmune disease in women. - Mary A M Rogers; Deborah A Levine; Neil Blumberg; Gwenith G Fisher; Mohammed U Kabeto; Kenneth M. Langa (J Autoimmun, 2012)
Infection has long been implicated as a trigger for autoimmune disease. Other antigenic challenges include receipt of allogeneic tissue or blood resulting in immunomodulation. We investigated antigenic challenges as possible risk factors for autoimmune disease in women using the Health and Retirement Study, a nationally representative longitudinal study, linked to Medicare files, years 1991-2007. The prevalence of autoimmune disease (rheumatoid arthritis, Hashimoto's disease, Graves' disease, systemic lupus erythematosus, celiac disease, systemic sclerosis, Sjögren syndrome and multiple sclerosis) was 1.4% in older women (95% CI: 1.3%, 1.5%) with significant variation across regions of the United States. The risk of autoimmune disease increased by 41% (95% CI of incidence rate ratio (IRR): 1.10, 1.81) with a prior infection-related medical visit. The risk of autoimmune disease increased by 90% (95% CI of IRR: 1.36, 2.66) with a prior transfusion without infection. Parity was not associated with autoimmune disease. Women less than 65 years of age and Jewish women had significantly elevated risk of developing autoimmune disease, as did individuals with a history of heart disease or end-stage renal disease. Antigenic challenges, such as infection and allogeneic blood transfusion, are significant risk factors for the development of autoimmune disease in older women.
Keywords: Aged; Aged, 80 and over; Antigens; Autoimmune Diseases; Female; Humans; Incidence; Middle Aged; Prevalence; Risk Factors; United States

Association of chronic diseases and impairments with disability in older adults: a decade of change? - William W. Hung; Joseph S. Ross; Boockvar, Kenneth S; Albert L Siu (Med Care, 2012)
BACKGROUND: Little is known about how the relationship between chronic disease, impairment, and disability has changed over time among older adults. OBJECTIVE: To examine how the associations of chronic disease and impairment with specific disability have changed over time. RESEARCH DESIGN: Repeated cross-sectional analysis, followed by examining the collated sample using time interaction variables, of 3 recent waves of the Health and Retirement Study. SUBJECTS: The subjects included 10,390, 10,621 and 10,557 community-dwelling adults aged 65 years and above in 1998, 2004, and 2008. MEASUREMENTS: : Survey-based history of chronic diseases including hypertension, heart disease, heart failure, stroke, diabetes, cancer, chronic lung disease, and arthritis; impairments, including cognition, vision, and hearing; and disability, including mobility, complex activities of daily living (ADL), and self-care ADL. RESULTS: Over time, the relationship of chronic diseases and impairments with disability was largely unchanged; however, the association between hypertension and complex ADL disability weakened from 1998 to 2004 and 2008 [odds ratio (OR) = 1.24; 99% confidence interval (CI), 1.06-1.46; OR = 1.07; 99% CI, 0.90-1.27; OR = 1.00; 99% CI, 0.83-1.19, respectively], as it did for hypertension and self-care disability (OR = 1.32; 99% CI, 1.13-1.54; OR=0.97; 99% CI, 0.82-1.14; OR = 0.99; 99% CI, 0.83-1.17). The association between diabetes and self-care disability strengthened from 1998 to 2004 and 2008 (OR = 1.21; 99% CI, 1.01-1.46; OR = 1.37; 99% CI, 1.15-1.64; OR = 1.52; 99% CI, 1.29-1.79), as it also did for lung disease and self-care disability (OR = 1.64; 99% CI, 1.33-2.03; OR = 1.63; 99% CI, 1.32-2.01; OR = 2.11; 99% CI, 1.73-2.57). CONCLUSIONS: Although relationships between diseases, impairments, and disability were largely unchanged, disability became less associated with hypertension and more with diabetes and lung disease.
Keywords: Activities of Daily Living; Aged; Aging; Cardiovascular Diseases; Chronic disease; Cognition Disorders; Cross-Sectional Studies; Diabetes Mellitus; Disabled Persons; Female; Health Surveys; Hearing loss; Humans; Hypertension; Male; Mobility Limitation; Residence Characteristics; Respiratory Tract Diseases; Self Care; Socioeconomic factors; United States; Vision Disorders

Beware of being unaware: racial/ethnic disparities in chronic illness in the USA. - Chatterji, Pinka; Heesoo Joo; Kajal Chatterji Lahiri (Health Econ, 2012)
We study racial/ethnic disparities in awareness of chronic diseases using biomarker data from the 2006 Health and Retirement Study. We explore two alternative definitions of awareness and estimate a trivariate probit model with selection, which accounts for common, unmeasured factors underlying the following: (1) self-reporting chronic disease; (2) participating in biomarker collection; and (3) having disease, conditional on participating in biomarker collection. Our findings suggest that current estimates of racial/ethnic disparities in chronic disease are sensitive to selection, and also to the definition of disease awareness used. We find that African-Americans are less likely to be unaware of having hypertension than non-Latino whites, but the magnitude of this effect falls appreciably after we account for selection. Accounting for selection, we find that African-Americans and Latinos are more likely to be unaware of having diabetes compared to non-Latino whites. These findings are based on a widely used definition of awareness - the likelihood of self-reporting disease among those who have disease. When we use an alternative definition of awareness, which considers an individual to be unaware if he or she actually has the disease conditional on self-reporting not having it, we find higher levels of unawareness among racial/ethnic minorities versus non-Latino whites for both hypertension and diabetes.
Keywords: Aged; Biomarkers; Black People; Chronic disease; Data collection; Diabetes Mellitus; ethnicity; Female; Health Knowledge, Attitudes, Practice; Health Status Disparities; Hispanic or Latino; Humans; Hypertension; Male; Racial Groups; Self Report; United States; White People

Burden of cirrhosis on older Americans and their families: analysis of the health and retirement study. - M. O. Rakoski; Ryan J McCammon; John D Piette; Theodore J Iwashyna; J. A. Marrero; Lok, Anna S; Kenneth M. Langa; Volk, Michael L (Hepatology, 2012)
UNLABELLED: Prevalence of cirrhosis among older adults is expected to increase; therefore, we studied the health status, functional disability, and need for supportive care in a large national sample of individuals with cirrhosis. A prospective cohort of individuals with cirrhosis was identified within the longitudinal, nationally representative Health and Retirement Study. Cirrhosis cases were identified in linked Medicare data via ICD-9-CM (International Classification of Diseases, Ninth Revision, Clinical Modification) codes and compared to an age-matched cohort without cirrhosis. Two primary outcome domains were assessed: (1) patients' health status (perceived health status, comorbidities, health care utilization, and functional disability as determined by activities of daily living and instrumental activities of daily living), and (2) informal caregiving (hours of caregiving provided by a primary informal caregiver and associated cost). Adjusted negative binomial regression was used to assess the association between cirrhosis and functional disability. A total of 317 individuals with cirrhosis and 951 age-matched comparators were identified. Relative to the comparison group, individuals with cirrhosis had worse self-reported health status, more comorbidities, and used significantly more health care services (hospitalizations, nursing home stays, physician visits; P < 0.001 for all bivariable comparisons). They also had greater functional disability (P < 0.001 for activities of daily living and instrumental activities of daily living), despite adjustment for covariates such as comorbidities and health care utilization. Individuals with cirrhosis received more than twice the number of informal caregiving hours per week (P < 0.001), at an annual cost of US $4700 per person. CONCLUSION: Older Americans with cirrhosis have high rates of disability, health care utilization, and need for informal caregiving. Improved care coordination and caregiver support is necessary to optimize management of this frail population.
Keywords: Aged; Black People; Caregivers; Comorbidity; Cost of Illness; Databases, Factual; Disability Evaluation; Female; Health Care Costs; Health Status; Hispanic or Latino; Humans; Incidence; Liver Cirrhosis; Male; Medicaid; Medicare; Prevalence; Prospective Studies; Retirement; United States; White People

Chiropractic episodes and the co-occurrence of chiropractic and health services use among older Medicare beneficiaries. - Paula A Weigel; Jason Hockenberry; Suzanne E Bentler; Kaskie, Brian; Frederic D Wolinsky (Journal of Manipulative & Physiological Therapeutics, 2012)
OBJECTIVE: The purpose of this study was to define and characterize episodes of chiropractic care among older Medicare beneficiaries and to evaluate the extent to which chiropractic services were used in tandem with conventional medicine. METHODS: Medicare Part B claims histories for 1991 to 2007 were linked to the nationally representative survey on Assets and Health Dynamics among the Oldest Old baseline interviews (1993-1994) to define episodes of chiropractic sensitive care using 4 approaches. Chiropractic and nonchiropractic patterns of service use were examined within these episodes of care. Of the 7447 Assets and Health Dynamics among the Oldest Old participants, 971 used chiropractic services and constituted the analytic sample. RESULTS: There were substantial variations in the number and duration of episodes and the type and volume of services used across the 4 definitions. Depending on how the episode was constructed, the mean number of episodes per chiropractic user ranged from 3.74 to 23.12, the mean episode duration ranged from 4.7 to 28.8 days, the mean number of chiropractic visits per episode ranged from 0.88 to 2.8, and the percentage of episodes with co-occurrent use of chiropractic and nonchiropractic providers ranged from 4.9% to 10.9% over the 17-year period. CONCLUSION: Treatment for back-related musculoskeletal conditions was sought from a variety of providers, but there was little co-occurrent service use or coordinated care across provider types within care episodes. Chiropractic treatment dosing patterns in everyday practice were much lower than that used in clinical trial protocols designed to establish chiropractic efficacy for back-related conditions.
Keywords: Age Factors; Aged; Aged, 80 and over; Chiropractic; Combined Modality Therapy; Episode of Care; Female; Geriatric Assessment; Health Care Surveys; Health Services; Humans; Incidence; Insurance Claim Reporting; Low Back Pain; Medicare Part B; Musculoskeletal Diseases; Primary Health Care; Retrospective Studies; Sex Factors; Treatment Outcome; United States

Chronic back pain among older construction workers in the United States: a longitudinal study. - Xiuwen S Dong; Wang, Xuanwen; Fujimoto, Alissa; Dobbin, Ronald (Int J Occup Environ Health, 2012)
This study assessed chronic back pain among older construction workers in the United States by analyzing data from the 1992-2008 Health and Retirement Study (HRS), a large-scale longitudinal survey. Fixed-effects methods were applied in the multiple logistic regression model to explore the association between back pain and time-varying factors (e.g., employment, job characteristics, general health status) while controlling for stable variables (e.g., gender, race, ethnicity). Results showed that about 40% of older construction workers over the age of 50 suffered from persistent back pain or problems. Jobs involving a great deal of stress or physical effort significantly increased the risk of back disorders and longest-held jobs in construction increased the odds of back disorders by 32% (95% CI: 1·04-1·67). Furthermore, poor physical and mental health were strongly correlated with back problems. Enhanced interventions for construction workers are urgently needed given the aging workforce and high prevalence of back disorders in this industry.
Keywords: Back Pain; Employment; Humans; Longitudinal Studies; Occupational Diseases; Occupations; United States

Coverage or costs: the role of health insurance in labor market reentry among early retirees. - Ben Lennox Kail (J Gerontol B Psychol Sci Soc Sci, 2012)
OBJECTIVES: This study evaluated the impact of insurance coverage on the odds of returning to work after early retirement and the change in insurance coverage after returning to work. METHOD: The Health and Retirement Study was used to estimate hierarchical linear models of transitions to full-time work and part-time work relative to remaining retired. A chi-square test was also used to assess change in insurance coverage after returning to work. RESULTS: Insurance coverage was unrelated to the odds of transitioning to full-time work. However, relative to employer-provided insurance, private nongroup insurance increased the odds of transitioning to part-time work, whereas public insurance reduced the odds of making this transition. Additionally, after returning to work, insurance coverage increased among those who were without employer-provided insurance in retirement. DISCUSSION: Results indicated that source of coverage may be more useful in explaining returns to part-time work than simply whether people have coverage at all. In other words, the mechanism underlying the positive relationship between insurance and returning to work appeared to be limited to those who return to work because of the cost of private nongroup insurance. Among these people, however, there was some evidence that they are able to secure new coverage once they return to work.
Keywords: Employment; Female; Health Benefit Plans, Employee; Health Surveys; Humans; Insurance Coverage; Insurance, Health; Male; Middle Aged; Retirement; United States

The cumulative effect of unemployment on risks for acute myocardial infarction. - Matthew E Dupre; Linda K George; Liu, Guangya; Eric D Peterson (Arch Intern Med, 2012)
BACKGROUND: Employment instability is a major source of strain affecting an increasing number of adults in the United States. Little is known about the cumulative effect of multiple job losses and unemployment on the risks for acute myocardial infarction (AMI). METHODS: We investigated the associations between different dimensions of unemployment and the risks for AMI in US adults in a prospective cohort study of adults (N = 13,451) aged 51 to 75 years in the Health and Retirement Study with biennial follow-up interviews from 1992 to 2010. Unadjusted rates of age-specific AMI were used to demonstrate observed differences by employment status, cumulative number of job losses, and cumulative time unemployed. Cox proportional hazards models were used to examine the multivariate effects of cumulative work histories on AMI while adjusting for sociodemographic background and confounding risk factors. RESULTS: The median age of the study cohort was 62 years, and 1061 AMI events (7.9%) occurred during the 165,169 person-years of observation. Among the sample, 14.0% of subjects were unemployed at baseline, 69.7% had 1 or more cumulative job losses, and 35.1% had spent time unemployed. Unadjusted plots showed that age-specific rates of AMI differed significantly for each dimension of work history. Multivariate models showed that AMI risks were significantly higher among the unemployed (hazard ratio, 1.35 [95% CI, 1.10-1.66]) and that risks increased incrementally from 1 job loss (1.22 [1.04-1.42]) to 4 or more cumulative job losses (1.63 [1.29-2.07]) compared with no job loss. Risks for AMI were particularly elevated within the first year of unemployment (hazard ratio, 1.27 [95% CI, 1.01-1.60]) but not thereafter. Results were robust after adjustments for multiple clinical, socioeconomic, and behavioral risk factors. CONCLUSIONS: Unemployment status, multiple job losses, and short periods without work are all significant risk factors for acute cardiovascular events.
Keywords: Female; Humans; Incidence; Male; Middle Aged; Myocardial Infarction; Prognosis; Proportional Hazards Models; Retrospective Studies; Risk Factors; Stress, Psychological; Survival Rate; Unemployment; United States

Current and long-term spousal caregiving and onset of cardiovascular disease. - Benjamin D Capistrant; J Robin Moon; Lisa F Berkman; M. Maria Glymour (J Epidemiol Community Health, 2012)
BACKGROUND: Prior evidence suggests that caregiving may increase risk of cardiovascular disease (CVD) onset. This association has never been examined in a nationally (USA) representative sample, and prior studies could not fully control for socioeconomic confounders. This paper seeks to estimate the association between spousal caregiving and incident CVD in older Americans. METHODS: Married, CVD-free Health and Retirement Study respondents aged 50+ years (n=8472) were followed up to 8 years (1669 new stroke or heart disease diagnoses). Current caregiving exposure was defined as assisting a spouse with basic or instrumental activities of daily living ≥14 h/week according to the care recipients' report in the most recent prior biennial survey; we define providing ≥14 h/week of care at two consecutive biennial surveys as 'long-term caregiving'. Inverse probability weighted discrete-time hazard models with time-updated exposure and covariate information (including socioeconomic and cardiovascular risk factors) were used to estimate the effect of caregiving on incident CVD. RESULTS: Caregiving significantly predicted CVD incidence (HR=1.35, 95% CI 1.06 to 1.68) in the population overall. Long-term caregiving was associated with double the risk of CVD onset (HR=1.95, 95% CI 1.19 to 3.18). This association for long-term care givers varied significantly by race (p<0.01): caregiving predicted CVD onset for white (HR=2.37, 95% CI 1.43 to 3.92) but not for non-white (HR=0.28, 95% CI 0.06 to 1.28). CONCLUSIONS: Spousal caregiving independently predicted risk of CVD in a large sample of US adults. There was significant evidence that the effect for long-term care givers differs for non-whites and white.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Caregivers; Female; Follow-Up Studies; Humans; Incidence; Interviews as Topic; Long-term Care; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Self Report; Socioeconomic factors; Spouses; Stress, Psychological; United States

Depressive symptoms in spouses of older patients with severe sepsis. - Dimitry S Davydow; Catherine L Hough; Kenneth M. Langa; Theodore J Iwashyna (Crit Care Med, 2012)
OBJECTIVE: To examine whether spouses of patients with severe sepsis are at increased risk for depression independent of the spouse's presepsis history, whether this risk differs by sex, and is associated with a sepsis patient's disability after hospitalization. DESIGN: Prospective longitudinal cohort study. SETTING: Population-based cohort of U.S. adults over 50 yrs old interviewed as part of the Health and Retirement Study (1993-2008). PATIENTS: Nine hundred twenty-nine patient-spouse dyads comprising 1,212 hospitalizations for severe sepsis. MEASUREMENTS AND MAIN RESULTS: Severe sepsis was identified using a validated algorithm in Medicare claims. Depression was assessed with a modified version of the Center for Epidemiologic Studies Depression Scale. All analyses were stratified by gender. The prevalence of substantial depressive symptoms in wives of patients with severe sepsis increased by 14 percentage points at the time of severe sepsis (from 20% at a median of 1.1 yrs presepsis to 34% at a median of 1 yr postsepsis) with an odds ratio of 3.74 (95% confidence interval: 2.20, 6.37), in multivariable regression. Husbands had an 8 percentage point increase in the prevalence of substantial depressive symptoms, which was not significant in multivariable regression (odds ratio 1.90, 95% confidence interval 0.75, 4.71). The increase in depression was not explained by bereavement; women had greater odds of substantial depressive symptoms even when their spouse survived a severe sepsis hospitalization (odds ratio 2.86, 95% confidence interval 1.06, 7.73). Wives of sepsis survivors who were disabled were more likely to be depressed (odds ratio 1.35 per activities of daily living limitation of sepsis survivor, 95% confidence interval 1.12, 1.64); however, controlling for patient disability only slightly attenuated the association between sepsis and wives' depression (odds ratio 2.61, 95% confidence interval 0.93, 7.38). CONCLUSIONS: Older women may be at greater risk for depression if their spouse is hospitalized for severe sepsis. Spouses of patients with severe sepsis may benefit from greater support and depression screening, both when their loved one dies and when their loved one survives.
Keywords: Age Factors; Aged; depression; Female; Hospitalization; Humans; Male; Multivariate Analysis; Prospective Studies; Psychiatric Status Rating Scales; Sepsis; Sex Factors; Spouses; Time Factors; United States

Despite 'welcome to Medicare' benefit, one in eight enrollees delay first use of part B services for at least two years. - Frank A Sloan; Kofi F Acquah; Paul P Lee; Devdutta G. Sangvai (Health Aff (Millwood), 2012)
Much research has focused on the possible overuse of health care services within Medicare, but there is also substantial evidence of underuse. In recent years, Congress has added a "welcome to Medicare" physician visit and a number of preventive services with no cost sharing to the Medicare benefit package to encourage early and appropriate use of services. We examined national longitudinal data on first claims for Part B services-the portion of Medicare that covers physician visits-to learn how people used these benefits. We found that 12 percent of people, or about one in eight, who enrolled in Medicare at age sixty-five waited more than two years before making their first use of care covered by Part B. In part, this delay reflected patterns of use before enrollment, in that people who sought preventive care before turning sixty-five continued to do so after enrolling in Medicare. Enrollees with Medigap coverage, higher household wealth, and a higher level of education typically received care under Part B sooner than others, whereas having greater tolerance for risk was more likely to lead enrollees to delay use of Part B services. Men had a lower probability of using Part B services early than women; blacks and members of other minority groups were less likely to use services early than whites. Although the "welcome to Medicare" checkup does not appear to have had a positive effect on use of services soon after enrollment, the percentage of beneficiaries receiving Part B services in the first two years after enrollment has steadily increased over time. Whether or not delays in receipt of care should be a considerable public policy concern may depend on what factors are leading specific categories of enrollees to delay care and how such delays affect health.
Keywords: Aged; Female; Humans; Insurance Claim Review; Male; Medicare Part B; Time Factors; United States

Determinants of retirement timing expectations in the United States and Australia: a cross-national comparison of the effects of health and retirement benefit policies on retirement timing decisions. - K. A. Sargent-Cox; Kaarin J. Anstey; Kendig, H.; Skladzien, E. (J Aging Soc Policy, 2012)
Data from the U.S. Health and Retirement Study (N = 2,589) and the Australian Household Income and Labour Dynamics survey (N = 1,760) were used to compare the macro-level policy frameworks on individual retirement timing expectations for pre-baby boomers (61+ years) and early baby boomers (45 to 60 years). Australian workers reported younger expected age of retirement compared to the U.S. sample. Reporting poor health was more strongly associated with younger expected retirement age in the United States than in Australia. Cohort and gender differences in the United States were found for the effect of private health insurance on younger expected age at retirement. Our results draw attention to how cross-national comparisons can inform us on the effects of policies on retirement expectations among older workers.
Keywords: Activities of Daily Living; Age Factors; Australia; Cross-Cultural Comparison; Florida; Health Benefit Plans, Employee; Health Status; Humans; Job Satisfaction; Middle Aged; Pensions; Public Policy; Retirement; Sex Factors; Socioeconomic factors; Time Factors; United States

Disability and decline in physical function associated with hospital use at end of life. - Amy Kelley; Susan L Ettner; R Sean Morrison; Qingling Du; Catherine A Sarkisian (J Gen Intern Med, 2012)
BACKGROUND: Hospital use near the end of life is often undesirable to patients, represents considerable Medicare cost, and varies widely across regions. OBJECTIVE: To concurrently examine regional and patient factors, including disability and functional decline, associated with end-of-life hospital use. DESIGN/PARTICIPANTS: We sampled decedents aged 65 and older (n = 2,493) from the Health and Retirement Study (2000-2006), and linked data from individual Medicare claims and the Dartmouth Atlas of Health Care. Two-part regression models estimated the relationship between total hospital days in the last 6 months and patient characteristics including physical function, while adjusting for regional resources and hospital care intensity (HCI). KEY RESULTS: Median hospital days was 7 (range = 0-183). 53% of respondents had functional decline. Compared with decedents without functional decline, those with severe disability or decline had more regression-adjusted hospital days (range 3.47-9.05, depending on category). Dementia was associated with fewer days (-3.02); while chronic kidney disease (2.37), diabetes (2.40), stroke or transient ischemic attack (2.11), and congestive heart failure (1.74) were associated with more days. African Americans and Hispanics had more days (5.91 and 4.61, respectively). Those with family nearby had 1.62 fewer days and hospice enrollees had 1.88 fewer days. Additional hospital days were associated with urban residence (1.74) and residence in a region with more specialists (1.97) and higher HCI (2.27). CONCLUSIONS: Functional decline is significantly associated with end-of-life hospital use among older adults. To improve care and reduce costs, health care programs and policies should address specific needs of patients with functional decline and disability.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic disease; Dementia; Disability Evaluation; Disabled Persons; Female; Frail Elderly; Geriatric Assessment; Hospitalization; Humans; Length of Stay; Longitudinal Studies; Male; Medicare; Socioeconomic factors; Terminal Care; United States

The Disability burden of COPD. - Thornton Snider, Julia; J. A. Romley; Ken S Wong; Zhang, Jie; Eber, Michael; Dana P Goldman (COPD, 2012)
Affecting an estimated 12.6 million people and causing over 100,000 deaths per year, chronic obstructive pulmonary disease (COPD) exacts a heavy burden on American society. Despite knowledge of the impact of COPD on morbidity, mortality, and health care costs, little is known about the association of the disease with economic outcomes such as employment and the collection of disability. We quantify the impact of COPD on Americans aged 51 and older-in particular, their employment prospects and their likelihood of collecting federal disability benefits-by conducting longitudinal regression analysis using the Health and Retirement Study. Controlling for initial health status and a variety of sociodemographic factors, we find that COPD is associated with a decrease in the likelihood of employment of 8.6 percentage points (OR = 0.58, 95% CI 0.50-0.67), from 44% to 35%. This association rivals that of stroke and is larger than those of heart disease, cancer, hypertension, and diabetes. Furthermore, COPD is associated with a 3.9 percentage point (OR 2.52, 95% CI 2.00-3.17) increase in the likelihood of collecting Social Security Disability Insurance (SSDI), from 3.2% to 7.1%, as well as a 1.7 percentage point (OR 2.87, 95% CI 2.02-4.08) increase in the likelihood of collecting Supplemental Security Income (SSI), from 1.0% to 2.7%. The associations of COPD with SSDI and SSI are the largest of any of the conditions studied. Our results are consistent with the hypothesis that COPD imposes a substantial burden on American society by inhibiting employment and creating disability.
Keywords: Aged; Cost of Illness; Disabled Persons; Employment; Female; Humans; Income; Insurance, Disability; Likelihood Functions; Logistic Models; Male; Middle Aged; Pulmonary Disease, Chronic Obstructive; Social Security; United States

Effect of obesity on falls, injury, and disability. - Christine L Himes; Sandra L Reynolds (J Am Geriatr Soc, 2012)
OBJECTIVES: To examine the effect of obesity on the propensity of older adults to fall, sustain a fall-related injury, and develop disability in activities of daily living (ADLs) after a fall. DESIGN: Longitudinal population-based survey. SETTING: Five waves of the Health and Retirement Study (HRS), 1998-2006. PARTICIPANTS: Ten thousand seven hundred fifty-five respondents aged 65 and older in 31,602 person-intervals. MEASUREMENTS: Falls within any 2-year interval (9,621 falls). Injuries requiring medical attention (3,130 injuries). Increased ADL disability after a fall within any 2-year interval (2,162 events). Underweight and three classes of obesity (body mass index (BMI) 30.0-34.9 kg/m(2) , Class 1) 35.0-39.9 kg/m(2) , Class 2; ≥40.0 kg/m(2) , Class 3), calculated from self-reported height and weight. Self-reported presence of lower body limitation, pain, dizziness, or vision problems. Self-reported doctor's diagnosis of diabetes mellitus, stroke, or arthritis. RESULTS: Compared with normal-weight respondents, the odds ratios (OR) for risk of falling were 1.12 (95% confidence interval (CI) = 1.01-1.24) for obesity Class 1, 1.26 (95% CI = 1.05-1.51) for obesity Class 2, and 1.50 (95% CI = 1.21-1.86) for obesity Class 3. Conditional on falling, only obesity Class 3 was related to a lower propensity for a fall-related injury (OR = 0.62, 95% CI = 0.44-0.87). Obesity Classes 1 and 2 were associated with a higher risk of greater ADL disability after a fall than normal-weight respondents (OR = 1.17, 95% CI = 1.02-1.34; OR = 1.39, 95% CI = 1.10-1.75, respectively). Being underweight was not related to risk of falling or to reported injury or greater ADL limitation after a fall. The presence of measured health problems and chronic conditions was associated with greater risk of falling and, of those who fell, greater ADL limitation but not serious injury. CONCLUSION: Obesity appears to be associated with greater risk of falling in older adults, as well as a higher risk of greater ADL disability after a fall. Obesity (BMI ≥ 40 kg/m(2) ) may reduce the risk of injury from a fall. Further investigation of the mechanisms of obesity on falls and related health outcomes is warranted.
Keywords: Accidental Falls; Activities of Daily Living; Aged; Body Mass Index; Disability Evaluation; Disabled Persons; Female; Follow-Up Studies; Humans; Incidence; Male; Obesity; Odds Ratio; Prevalence; Retrospective Studies; Risk Factors; United States; Wounds and Injuries

The effect of stability and change in health behaviors on trajectories of body mass index in older Americans: a 14-year longitudinal study. - Anda Botoseneanu; Jersey Liang (J Gerontol A Biol Sci Med Sci, 2012)
BACKGROUND: Obesity is increasingly prevalent among older adults, yet little is known about the impact of health behaviors on the trajectories of body weight in this age group. METHODS: We examined the effect of time-varying smoking, physical activity (PA), alcohol use, and changes thereof, on the 14-year (1992-2006) trajectory of body- mass index (BMI) in a cohort of 10,314 older adults from the Health and Retirements Study, aged 51-61 years at baseline. Hierarchical linear modeling (HLM) quantifies the effect of smoking, PA, and alcohol use (user status, initiation and cessation) on intercept and rate-of-change in BMI trajectory, and tests for variations in the strength of association between each behavior and BMI. RESULTS: Over 14 years (82,512 observations), BMI increased approximated by a quadratic function. Smoking and PA (user status and initiation) were associated with significantly lower BMI trajectories over time. Cessation of smoking and PA resulted in higher BMI trajectories over time. The weight-gaining effect of smoking cessation increased, while the strength of association between BMI trajectories and PA or alcohol use were constant over time. Socio-economic and health status differences explained the effects of alcohol use on BMI trajectory. CONCLUSIONS: In older adults, smoking and PA, and changes thereof, vary in their long-term effect on trajectories of BMI. Barring increases in PA levels, older smokers who quit today are expected to gain significantly more weight than two decades ago. This knowledge is essential for the design of smoking cessation, physical activityPA, and weight-control interventions in older adults.
Keywords: Aged; Aging; Alcohol Drinking; Body Mass Index; Cohort Studies; Female; Health Behavior; Health Status; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; Motor Activity; Smoking; Socioeconomic factors; United States

Elevated depressive symptoms and incident stroke in Hispanic, African-American, and White older Americans. - M. Maria Glymour; Jessica J. Yen; Anna Kosheleva; J Robin Moon; Benjamin D Capistrant; Kristen K Patton (J Behav Med, 2012)
Although depressive symptoms have been linked to stroke, most research has been in relatively ethnically homogeneous, predominantly white, samples. Using the United States based Health and Retirement Study, we compared the relationships between elevated depressive symptoms and incident first stroke for Hispanic, black, or white/other participants (N = 18,648) and estimated the corresponding Population Attributable Fractions. The prevalence of elevated depressive symptoms was higher in blacks (27%) and Hispanics (33%) than whites/others (18%). Elevated depressive symptoms prospectively predicted stroke risk in the whites/other group (HR = 1.53; 95% CI: 1.36-1.73) and among blacks (HR = 1.31; 95% CI: 1.05-1.65). The HR was similar but only marginally statistically significant among Hispanics (HR = 1.33; 95% CI: 0.92-1.91). The Population Attributable Fraction, indicating the percent of first strokes that would be prevented if the incident stroke rate in those with elevated depressive symptoms was the same as the rate for those without depressive symptoms, was 8.3% for whites/others, 7.8% for blacks, and 10.3% for Hispanics.
Keywords: Age Factors; Aged; Black or African American; depression; Female; Health Surveys; Hispanic or Latino; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Predictive Value of Tests; Prevalence; Risk Factors; Stroke; United States; White People

Ethnic/race differences in the attrition of older American survey respondents: implications for health-related research. - Natalia A. Zhivan; Alfonso Ang; Hortensia Amaro; William A. Vega; Kyriakos S Markides (Health Serv Res, 2012)
OBJECTIVE: To compare models of attrition across race/ethnic groups of aging populations and discuss implications for health-related research. DATA SOURCES: The Health and Retirement Study (1992-2008). STUDY DESIGN: A competing risks model was estimated using a multinomial logit model when respondents faced competing types of risks, such as dying, being lost from the study, and nonresponse in some years for different groups of elderly. Key explanatory variables were foreign birth, health insurance, and health status. PRINCIPAL FINDINGS: Variables describing foreign birth, health insurance, and health status differed in their prediction of attrition across ethnic groups of aging populations. CONCLUSIONS: Differences in the predictors of attrition across ethnic groups of elderly could potentially lead to biased estimates in health-related research using longitudinal data sources.
Keywords: Bias; ethnicity; Female; Health Care Surveys; Health Services Research; Health Surveys; Hispanic or Latino; Humans; Male; Mexican Americans; Middle Aged; Racial Groups; Risk; Socioeconomic factors; United States

The growth in Social Security benefits among the retirement-age population from increases in the cap on covered earnings. - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (Soc Secur Bull, 2012)
Analysts have proposed raising the maximum level of earnings subject to the Social Security payroll tax (the "tax max") to improve long-term Social Security Trust Fund solvency. This article investigates how raising the tax max leads to the "leakage" of portions of the additional revenue into higher benefit payments. Using Health and Retirement Study data matched to Social Security earnings records, we compare historical payroll tax payments and benefit amounts for Early Boomers (born 1948-1953) with tax and benefit simulations had they been subject to the tax max (adjusted for wage growth) faced by cohorts 12 and 24 years older. We find that 43.2 percent of the additional payroll tax revenue attributable to tax max increases affecting Early Boomers relative to taxes paid by the cohort 12 years older leaked into higher benefits. For Early Boomers relative to those 24 years older, we find 53.5 percent leakage.
Keywords: Aged; Cohort Studies; Female; Humans; Insurance Benefits; Male; Middle Aged; Models, Econometric; Public Policy; Salaries and Fringe Benefits; Social Security; Taxes; United States

Half of older Americans seen in emergency department in last month of life; most admitted to hospital, and many die there. - Alexander K Smith; Ellen P McCarthy; Ellen Weber; Irena Cenzer; W John Boscardin; Jonathan Fisher; Kenneth E Covinsky (Health Aff (Millwood), 2012)
Emergency department use contributes to high end-of-life costs and is potentially burdensome for patients and family members. We examined emergency department use in the last months of life for patients age sixty-five or older who died while enrolled in a longitudinal study of older adults in the period 1992-2006. We found that 51 percent of the 4,158 [corrected] decedents visited the emergency department in the last month of life, and 75 percent in the last six months of life. Repeat visits were common. A total of 77 percent of the patients seen in the emergency department in the last month of life were admitted to the hospital, and 68 percent of those who were admitted died there. In contrast, patients who enrolled in hospice at least one month before death rarely visited the emergency department in the last month of life. Policies that encourage the preparation of patients and families for death and early enrollment in hospice may prevent emergency department visits at the end of life.
Keywords: Aged; Aged, 80 and over; Emergency Service, Hospital; Female; Hospital Mortality; Hospitalization; Humans; Insurance Claim Review; Male; Terminal Care; Terminally Ill; United States

Health investment decisions in response to diabetes information in older Americans. - Alexander N Slade (J Health Econ, 2012)
Diabetes is a very common and serious chronic disease, and one of the fastest growing disease burdens in the United States. Further, health behaviors, such as exercise, smoking, drinking, as well as weight status, are instrumental to diabetes management and the reduction of its medical consequences. Nine waves of the Health and Retirement Study are used to model the role of a recent diabetes diagnosis and medication on present and subsequent weight status, exercise, drinking and smoking activity. Several non-linear dynamic population average probit models are estimated. Results suggest that compared to non-diagnosed individuals at risk for high blood sugar, diagnosed diabetics respond initially in terms of increasing exercise, losing weight, and curbing smoking and drinking behavior, but the effect diminishes after diagnosis. Evidence of recidivism is also found in these outcomes, especially weight status and physical activity, suggesting that some behavioral responses to diabetes may be short-lived.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alcohol Drinking; Body Weight; Decision making; Diabetes Mellitus; Empirical Research; Exercise; Female; Health Behavior; Health Surveys; Humans; Male; Middle Aged; Models, Psychological; Smoking; United States

Health service use among the previously uninsured: is subsidized health insurance enough? - Decker, Sandra L; Jalpa A Doshi; Amy E. Knaup; Daniel Polsky (Health Econ, 2012)
Although it has been shown that gaining Medicare coverage at age 65 years increases health service use among the uninsured, difficulty in changing habits or differences in the characteristics of previously uninsured compared with insured individuals may mean that the previously uninsured continue to use the healthcare system differently from others. This study uses Medicare claims data linked to two different surveys--the National Health Interview Survey and the Health and Retirement Study--to describe the relationship between insurance status before age 65 years and the use of Medicare-covered services beginning at age 65 years. Although we do not find statistically significant differences in Medicare expenditures or in the number of hospitalizations by previous insurance status, we do find that individuals who were uninsured before age 65 years continue to use the healthcare system differently from those who were privately insured. Specifically, they have 16% fewer visits to office-based physicians but make 18% and 43% more visits to hospital emergency and outpatient departments, respectively. A key question for the future may be why the previously uninsured seem to continue to use the healthcare system differently from the previously insured. This question may be important to consider as health coverage expansions are implemented.
Keywords: Aged; Female; Health Care Surveys; Health Services; Health Status; Humans; Insurance Coverage; Insurance, Health; Male; Medically Uninsured; Medicare; Middle Aged; Socioeconomic factors; United States

Higher rates of Clostridium difficile infection among smokers. - Mary A M Rogers; M. Todd Greene; Sanjay Saint; Carol E Chenoweth; Preeti N Malani; Itishree Trivedi; David M. Aronoff (PLoS One, 2012)
OBJECTIVES: Cigarette smoking has been shown to be related to inflammatory bowel disease. We investigated whether smoking affected the probability of developing Clostridium difficile infection (CDI). METHODS: We conducted a longitudinal study of 16,781 older individuals from the nationally representative Health and Retirement Study. Data were linked to files from the Centers for Medicare and Medicaid Services. RESULTS: Overall, the rate of CDI in older individuals was 220.6 per 100,000 person-years (95% CI 193.3, 248.0). Rates of CDI were 281.6/100,000 person-years in current smokers, 229.0/100,000 in former smokers and 189.1/100,000 person-years in never smokers. The odds of CDI were 33% greater in former smokers (95% CI: 8%, 65%) and 80% greater in current smokers (95% CI: 33%, 145%) when compared to never smokers. When the number of CDI-related visits was evaluated, current smokers had a 75% increased rate of CDI compared to never smokers (95% CI: 15%, 167%). CONCLUSIONS: Smoking is associated with developing a Clostridium difficile infection. Current smokers have the highest risk, followed by former smokers, when compared to rates of infection in never smokers.
Keywords: Clostridioides difficile; Enterocolitis, Pseudomembranous; Female; Humans; Male; Middle Aged; Smoking; United States

The impact of socioeconomic inequalities and lack of health insurance on physical functioning among middle-aged and older adults in the United States. - Kim, Jinhyun; Virginia E. Richardson (Health Soc Care Community, 2012)
Socioeconomic inequalities and lack of private health insurance have been viewed as significant contributors to health disparities in the United States. However, few studies have examined their impact on physical functioning over time, especially in later life. The current study investigated the impact of socioeconomic inequalities and lack of private health insurance on individuals' growth trajectories in physical functioning, as measured by activities of daily living. Data from the Health and Retirement Study (1994-2006) were used for this study, 6519 black and white adults who provided in-depth information about health, socioeconomic, financial and health insurance information were analysed. Latent growth curve modelling was used to estimate the initial level of physical functioning and its rate of change over time. Results showed that higher level of income and assets and having private health insurance significantly predicted better physical functioning. In particular, decline in physical functioning was slower among those who had private health insurance. Interestingly, changes in economic status, such as decreases in income and assets, had a greater impact on women's physical functioning than on men's. Black adults did not suffer more rapid declines in physical functioning than white adults after controlling for socioeconomic status. The current longitudinal study suggested that anti-poverty and health insurance policies should be enhanced to reduce the negative impact of socioeconomic inequalities on physical functioning throughout an individual's life course.
Keywords: Activities of Daily Living; Aged; Black or African American; Female; Health Status; Healthcare Disparities; Humans; Longitudinal Studies; Male; Medically Uninsured; Middle Aged; Poverty; Sex Factors; Socioeconomic factors; Time Factors; United States; White People

Limited lung function: impact of reduced peak expiratory flow on health status, health-care utilization, and expected survival in older adults. - Melissa H. Roberts; Douglas W Mapel (Am J Epidemiol, 2012)
The authors examined whether peak expiratory flow (PEF) is a valid measure of health status in older adults. Survey and test data from the 2006 and 2008 cycles of the Health and Retirement Study, a longitudinal study of US adults over age 50 years (with biennial surveys initiated in 1992), were used to develop predicted PEF regression models and to examine relations between low PEF values and other clinical factors. Low PEF (<80% of predicted value) was prevalent among persons with chronic conditions, including frequent pain, obstructive lung disease, heart disease, diabetes, and psychological distress. Persons with higher physical disability scores had substantially higher adjusted odds of having low PEF, on par with those for conditions known to be associated with poor health (cancer, heart disease, and stroke). In a multivariate regression model for difficulty with mobility, PEF remained an independent factor (odds ratio (OR) = 1.69, 95% confidence interval (CI): 1.53, 1.86). Persons with low PEF in 2006 were more likely to be hospitalized (OR = 1.26, 95% CI: 1.10, 1.43) within the subsequent 2 years and to estimate their chances of surviving for 10 or more years at less than 50% (OR = 1.69, 95% CI: 1.24, 2.30). PEF is a valid measure of health status in older persons, and low PEF is an independent predictor of hospitalization and poor subjective mortality assessment.
Keywords: Activities of Daily Living; Aged; Chronic disease; Cohort Studies; Comorbidity; Diabetes Mellitus; Female; Health Services; Health Status; Heart Diseases; Hospitalization; Humans; Incidence; Logistic Models; Longitudinal Studies; Lung Diseases; Male; Middle Aged; Neoplasms; Odds Ratio; Peak Expiratory Flow Rate; Population Surveillance; Stroke; United States

Loneliness, health, and mortality in old age: a national longitudinal study. - Ye Luo; Louise C Hawkley; Linda J. Waite; John T. Cacioppo (Soc Sci Med, 2012)
This study examined the relationship between loneliness, health, and mortality using a U.S. nationally representative sample of 2101 adults aged 50 years and over from the 2002 to 2008 waves of the Health and Retirement Study. We estimated the effect of loneliness at one point on mortality over the subsequent six years, and investigated social relationships, health behaviors, and health outcomes as potential mechanisms through which loneliness affects mortality risk among older Americans. We operationalized health outcomes as depressive symptoms, self-rated health, and functional limitations, and we conceptualized the relationships between loneliness and each health outcome as reciprocal and dynamic. We found that feelings of loneliness were associated with increased mortality risk over a 6-year period, and that this effect was not explained by social relationships or health behaviors but was modestly explained by health outcomes. In cross-lagged panel models that tested the reciprocal prospective effects of loneliness and health, loneliness both affected and was affected by depressive symptoms and functional limitations over time, and had marginal effects on later self-rated health. These population-based data contribute to a growing literature indicating that loneliness is a risk factor for morbidity and mortality and point to potential mechanisms through which this process works.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Studies; depression; Female; Health Behavior; Health Status; Humans; Interpersonal Relations; Loneliness; Longitudinal Studies; Male; Middle Aged; Mortality; Social Support; Socioeconomic factors; United States

Loneliness in older persons: a predictor of functional decline and death. - Perissinotto, Carla M; Irena Cenzer; Kenneth E Covinsky (Arch Intern Med, 2012)
BACKGROUND: Loneliness is a common source of distress, suffering, and impaired quality of life in older persons. We examined the relationship between loneliness, functional decline, and death in adults older than 60 years in the United States. METHODS: This is a longitudinal cohort study of 1604 participants in the psychosocial module of the Health and Retirement Study, a nationally representative study of older persons. Baseline assessment was in 2002 and follow-up assessments occurred every 2 years until 2008. Subjects were asked if they (1) feel left out, (2) feel isolated, or (3) lack companionship. Subjects were categorized as not lonely if they responded hardly ever to all 3 questions and lonely if they responded some of the time or often to any of the 3 questions. The primary outcomes were time to death over 6 years and functional decline over 6 years on the following 4 measures: difficulty on an increased number of activities of daily living (ADL), difficulty in an increased number of upper extremity tasks, decline in mobility, or increased difficulty in stair climbing. Multivariate analyses adjusted for demographic variables, socioeconomic status, living situation, depression, and various medical conditions. RESULTS: The mean age of subjects was 71 years. Fifty-nine percent were women; 81% were white, 11%, black, and 6%, Hispanic; and 18% lived alone. Among the elderly participants, 43% reported feeling lonely. Loneliness was associated with all outcome measures. Lonely subjects were more likely to experience decline in ADL (24.8% vs 12.5%; adjusted risk ratio [RR], 1.59; 95% CI, 1.23-2.07); develop difficulties with upper extremity tasks (41.5% vs 28.3%; adjusted RR, 1.28; 95% CI, 1.08-1.52); experience decline in mobility (38.1% vs 29.4%; adjusted RR, 1.18; 95% CI, 0.99-1.41); or experience difficulty in climbing (40.8% vs 27.9%; adjusted RR, 1.31; 95% CI, 1.10-1.57). Loneliness was associated with an increased risk of death (22.8% vs 14.2%; adjusted HR, 1.45; 95% CI, 1.11-1.88). CONCLUSION: Among participants who were older than 60 years, loneliness was a predictor of functional decline and death.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Female; Humans; Loneliness; Longitudinal Studies; Male; Middle Aged; Mortality; United States; Upper Extremity; Walking

Marriage, gender and obesity in later life. - Sven E. Wilson (Econ Hum Biol, 2012)
A large body of literature argues that marriage promotes health and increases longevity. But do these benefits extend to maintaining a healthy body weight, as the economic theory of health investment suggests they should? They do not. Using the Health and Retirement Study (HRS), I find that entry into marriage among both men and women aged 51-70 is associated with weight gain and exit from marriage with weight loss. I evaluate three additional theories with respect to the cross-sectional and longitudinal variation in the data. First, it may be that a broader set of shared risk factors (such as social obligations regarding meals) raises body mass for married couples. However, the shared risk factor model predicts that the intra-couple correlation should increase with respect to marital duration. Instead, it declines. Second, scholars have recently promoted a "crisis" model of marriage in which marital transitions, not marital status, determine differences in body mass. The crisis model is consistent with short-term effects seen for divorce, but not for the persistent weight gains associated with marriage or the persistent weight loss following widowhood. And transition models, in general, cannot explain significant cross-sectional differences across marital states in a population that is no longer experiencing many transitions, nor can it account for the prominent gender differences (in late middle-age, the heaviest group is unmarried women and the lightest are unmarried men). Third, I argue that pressures of the marriage market, in combination with gendered preferences regarding partner BMI, can account for all the longitudinal and cross-sectional patterns found in the data.
Keywords: Age Factors; Aged; Body Mass Index; Female; Humans; Male; Marital Status; Middle Aged; Models, Statistical; Obesity; Sex Factors; United States; Weight Gain; Weight Loss

Measurement equivalence in ADL and IADL difficulty across international surveys of aging: findings from the HRS, SHARE, and ELSA. - Kitty S. Chan; Judith D Kasper; Jason Brandt; Liliana E Pezzin (J Gerontol B Psychol Sci Soc Sci, 2012)
OBJECTIVE: To examine the measurement equivalence of items on disability across three international surveys of aging. METHOD: Data for persons aged 65 and older were drawn from the Health and Retirement Survey (HRS, n = 10,905), English Longitudinal Study of Aging (ELSA, n = 5,437), and Survey of Health, Ageing and Retirement in Europe (SHARE, n = 13,408). Differential item functioning (DIF) was assessed using item response theory (IRT) methods for activities of daily living (ADL) and instrumental activities of daily living (IADL) items. RESULTS: HRS and SHARE exhibited measurement equivalence, but 6 of 11 items in ELSA demonstrated meaningful DIF. At the scale level, this item-level DIF affected scores reflecting greater disability. IRT methods also spread out score distributions and shifted scores higher (toward greater disability). Results for mean disability differences by demographic characteristics, using original and DIF-adjusted scores, were the same overall but differed for some subgroup comparisons involving ELSA. DISCUSSION: Testing and adjusting for DIF is one means of minimizing measurement error in cross-national survey comparisons. IRT methods were used to evaluate potential measurement bias in disability comparisons across three international surveys of aging. The analysis also suggested DIF was mitigated for scales including both ADL and IADL and that summary indexes (counts of limitations) likely underestimate mean disability in these international populations.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Bias; Europe; Female; Health Surveys; Humans; Internationality; Longitudinal Studies; Male; United States

Overestimation of physical activity among a nationally representative sample of underactive individuals with diabetes. - Mary R Janevic; Sara J McLaughlin; Cathleen M. Connell (Med Care, 2012)
OBJECTIVES: Using data from the national Health and Retirement Study, we sought to: (a) estimate the proportion of the US adults with diabetes above the age of 50 who do not meet physical activity guidelines but believe they are sufficiently active; and (b) examine demographic and health-related correlates of such "overestimation." RESEARCH DESIGN: Respondents who were classified as underactive according to a detailed activity inventory but reported exercising at least the "right amount," were designated as overestimating their physical activity. Multiple logistic regression was used to examine the association of demographic and health-related correlates with the odds of overestimation. RESULTS: Fifty-four percent of the survey sample did not meet physical activity guidelines, and one quarter of this underactive group overestimated their physical activity. The adjusted odds of overestimation were higher among respondents who held the perception that they were about the right weight or underweight [odds ratio (OR)=2.42; 95% confidence interval (CI), 1.49-3.94), who had good or better self-assessed diabetes control (OR=1.84; 95% CI, 1.12-3.04), and who were Black or Hispanic (OR=1.89; 95% CI, 1.13-3.16). Experiencing shortness of breath reduced the odds of overestimation (OR=0.34; 95% CI, 0.19-0.61). CONCLUSIONS: Overestimation of physical activity is common among adults with diabetes, and is associated with the perceptions that one is about the right weight and that one has good control of diabetes, and with being Black or Hispanic. Clinicians should be aware that these factors may affect their patients' beliefs about how much physical activity is adequate.
Keywords: Age Factors; Data collection; Diabetes Mellitus; Disclosure; Dyspnea; Exercise; Female; Guideline Adherence; Guidelines as Topic; Health Status; Humans; Male; Middle Aged; Sedentary Behavior; Sex Factors; Socioeconomic factors; United States

Predictors of self-report of heart failure in a population-based survey of older adults. - Tanya R Gure; Ryan J McCammon; Christine T Cigolle; Todd M Koelling; Caroline S Blaum; Kenneth M. Langa (Circ Cardiovasc Qual Outcomes, 2012)
BACKGROUND: Little research has been conducted on the predictors of self-report or patient awareness of heart failure (HF) in a population-based survey. The objective of this study was to (1) test the agreement between Medicare administrative and Health and Retirement Study (HRS) survey data and (2) determine predictors associated with self-report of HF, using a validated Medicare claims algorithm as the reference standard. We hypothesized that those who self-reported HF were more likely to have a higher number of HF-related claims. METHODS AND RESULTS: Secondary data analysis was conducted using the 2004 wave of the HRS linked to 2002 to 2004 Medicare claims (n=5573 respondents aged ≥ 67 years). Concordance between self-report of HF in the HRS and Medicare claims was calculated. Logistic regression was performed to identify predictors associated with self-report HF. HF prevalence by self-report was 4.6%. Self-report of HF and claims agreement was 87% (κ=0.34). The presence of >1 HF inpatient claims was associated with greater odds of self-report (odds ratio [OR], 1.92; 95% CI, 1.23-3.00). Greater odds of self-reporting HF was also associated with ≥ 4 HF claims (OR, 2.74; 95% CI, 1.36-5.52). Blacks (OR, 0.28; 95% CI, 0.14-0.55) and Hispanics (OR, 0.30; 95% CI, 0.11-0.83) were less likely to self-report HF compared with whites in the final model. CONCLUSIONS: Self-report of HF is an insensitive method for accurately identifying HF cases, especially in those with less-severe disease and who are nonwhite. There may be limited awareness of HF among older minority patients despite having clinical encounters during which HF is coded as a diagnosis.
Keywords: Age Factors; Aged; Aged, 80 and over; Algorithms; Awareness; Chi-Square Distribution; Comorbidity; Female; Health Knowledge, Attitudes, Practice; Health Status; Health Surveys; Heart Failure; Humans; Insurance Claim Review; Logistic Models; Male; Medicare; Odds Ratio; Patients; Predictive Value of Tests; Self Report; Socioeconomic factors; United States

Prevalence of cognitive impairment in older adults with heart failure. - Tanya R Gure; Caroline S Blaum; Bruno J Giordani; Todd M Koelling; Andrzej T Galecki; Susan J Pressler; Scott L Hummel; Kenneth M. Langa (J Am Geriatr Soc, 2012)
OBJECTIVES: To determine the prevalence of cognitive impairment in older adults with heart failure (HF). DESIGN: Cross-sectional analysis of the 2004 wave of the nationally representative Health and Retirement Study linked to 2002 to 2004 Medicare administrative claims. SETTING: United States, community. PARTICIPANTS: Six thousand one hundred eighty-nine individuals aged 67 and older. MEASUREMENTS: An algorithm was developed using a combination of self- and proxy report of a heart problem and the presence of one or more Medicare claims in administrative files using standard HF diagnostic codes. On the basis of the algorithm, three categories were created to characterize the likelihood of a HF diagnosis: high or moderate probability of HF, low probability of HF, and no HF. Cognitive function was assessed using a screening measure of cognitive function or according to proxy rating. Age-adjusted prevalence estimates of cognitive impairment were calculated for the three groups. RESULTS: The prevalence of cognitive impairment consistent with dementia in older adults with HF was 15%, and the prevalence of mild cognitive impairment was 24%. The odds of dementia in those with HF were significantly higher, even after adjustment for age, education level, net worth, and prior stroke (odds ratio = 1.52, 95% confidence interval = 1.14-2.02). CONCLUSION: Cognitive impairment is common in older adults with HF and is independently associated with risk of dementia. A cognitive assessment should be routinely incorporated into HF-focused models of care.
Keywords: Aged; Aged, 80 and over; Algorithms; Chi-Square Distribution; Cognition Disorders; Cross-Sectional Studies; Demography; Female; Heart Failure; Humans; Logistic Models; Male; Medicare; Prevalence; United States

Progressive and accelerated disability onset by race/ethnicity and education among late midlife and older adults. - Kenzie Latham (J Aging Health, 2012)
OBJECTIVE: This study explores the pace of severe disability onset with an emphasis on the role of race/ethnicity and education. More specifically, this research examines whether race/ethnicity and educational attainment are independent predictors of progressive and accelerated disability onset. METHOD: Using the Health and Retirement Study (HRS) Waves 2 to 10 (1994-2010), a series of discrete-time Cox proportional hazards models with multiple competing events were created to ascertain whether respondents developed progressive or accelerated disability in subsequent waves. RESULTS: Black and Hispanic respondents were at an increased risk of developing progressive disability. Respondents without a high school degree were more likely to experience progressive or accelerated disability. DISCUSSION: Low educational attainment was a particularly strong predictor of accelerated disability onset and may represent an acute lack of resources over the life course. Race and ethnicity were important predictors of progressive disability onset, which may reflect racial/ethnic variations in the disabling process.
Keywords: Black or African American; Disabled Persons; disease progression; Educational Status; Female; Follow-Up Studies; Health Status Disparities; Hispanic or Latino; Humans; Male; Middle Aged; Qualitative Research; Risk Assessment; Risk Factors; Severity of Illness Index; Time Factors; United States; White People

A prospective cohort study of health behavior profiles after age 50 and mortality risk. - Benjamin A Shaw; Agahi, Neda (BMC Public Health, 2012)
BACKGROUND: This study examines the mortality risk associated with distinct combinations of multiple risk behaviors in middle-aged and older adults, and assesses whether the mortality risks of certain health behaviors are moderated by the presence of other risk behaviors. METHODS: Data for this prospective cohort study are from the Health and Retirement Study (HRS), a nationwide sample of adults older than 50 years. Baseline data are from respondents (n = 19,662) to the 1998 wave of the HRS. Twelve distinct health behavior profiles were created, based on each respondent's smoking, physical activity, and alcohol use status in 1998. Mortality risk was estimated through 2008 using Cox regression. RESULTS: Smoking was associated with elevated risk for mortality within all behavioral profiles, but risk was greatest when combined with heavy drinking, both for middle-aged (ages 51-65) and older (ages 66+) adults. Profiles that included physical inactivity were also associated with increased mortality risk in both age groups. However, the impact of inactivity was clearly evident only among non-smokers; among smokers, the risk of inactivity was less evident, and seemingly overshadowed by the risk of smoking. Moderate drinking was protective relative to abstinence among non-smokers, and relative to heavy drinking among smokers. CONCLUSIONS: In both middle-aged and older adults, multiple unhealthy behaviors increase mortality risk. However, the level of risk varies across unique combinations of unhealthy behaviors. These findings highlight the role that lifestyle improvements could play in promoting healthy aging, and provide insight into which behavioral combinations should receive top priority for intervention.
Keywords: Aged; Alcohol-Related Disorders; Female; Follow-Up Studies; Humans; Male; Middle Aged; Prospective Studies; Regression Analysis; Risk Assessment; Risk-Taking; Sedentary Behavior; Smoking; United States

A prospective examination of the relationship between physical activity and dementia risk in later life. - Mary E Bowen (Am J Health Promot, 2012)
PURPOSE: To examine the relationship between vigorous physical activity and dementia risk. DESIGN: Prospective study design utilizing physical activity data from the Health and Retirement Study and cognitive outcome data from the Aging, Demographics, and Memory Study. SETTING: Community-based. SUBJECTS: Adults age 71 and over (N  =  808) with 3 to 7 years of physical activity information prior to dementia/no dementia diagnosis. MEASURES: Physical activity was measured by participation in vigorous activities such as aerobics, sports, running, bicycling, and heavy housework three or more times per week (yes/no). Dementia diagnosis was based on an expert panel (e.g., neuropsychologists, neurologists, geropsychiatrists) who performed and reviewed a battery of neuropsychological tests. ANALYSIS: Binary logistic regression models were used to account for demographic characteristics, genetic risk factors (one or two apolipoprotein E ε4 alleles), health behaviors (e.g., smoking, drinking alcohol), health indicators (body mass index), and health conditions (e.g., diabetes, heart disease) in a sequential model-building process. RESULTS: The relationship between vigorous physical activity and dementia risk remained robust across models. In the final model, older adults who were physically active were 21% (p ≤ .05) less likely than their counterparts to be diagnosed with dementia. CONCLUSION: Vigorous physical activity may reduce the risk for dementia independently of the factors examined here. This study's findings are important given that few preventative strategies for dementia have been explored beyond hormonal therapy and anti-inflammatory drugs.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Body Mass Index; Confidence Intervals; Dementia; disease progression; Exercise; Female; Health Promotion; Health Status Indicators; Health Surveys; Humans; Logistic Models; Male; Motor Activity; Multivariate Analysis; Odds Ratio; Prospective Studies; Psychometrics; Risk Factors; United States

Race/ethnic and nativity disparities in later life physical performance: the role of health and socioeconomic status over the life course. - Steven A Haas; Patrick M. Krueger; Leah Rohlfsen (J Gerontol B Psychol Sci Soc Sci, 2012)
OBJECTIVES: We examine race/ethnic and nativity differences in objective measures of physical performance (i.e., peak expiratory flow, grip strength, and gait speed) in a nationally representative sample of older Whites, Blacks, and Hispanics. We also examine whether detailed measures of childhood and adult health and socioeconomic status (SES) mediate race/ethnic differences in physical performance. METHOD: We use data from the Health and Retirement Study, a population-based sample of older Americans born before 1947, and 3 measures of physical performance. Nested ordinary least squares models examine whether childhood and adult health and SES mediate race/ethnic differences in performance. RESULTS: We find large and significant race/ethnic and nativity differences in lung function, grip strength, and gait speed. Adjusting for childhood and current adult health and SES reduces race/ethnic differences in physical performance but does not eliminate them entirely. Childhood health and SES as well as more proximal levels of SES are important determinants of race/ethnic disparities in later life physical performance. DISCUSSION: The analysis highlights that a large proportion of race/ethnic and nativity disparities result from health and socioeconomic disadvantages in both early life and adulthood and thus suggests multiple intervention points at which disparities can be reduced.
Keywords: Aged; Aged, 80 and over; Aging; ethnicity; Female; Gait; Hand Strength; Health Status; Health Status Disparities; Health Surveys; Humans; Male; Middle Aged; Racial Groups; Respiratory Function Tests; Social Class; United States

The relationship between body weight, frailty, and the disablement process. - Mary E Bowen (J Gerontol B Psychol Sci Soc Sci, 2012)
OBJECTIVES: To prospectively examine the relationship between body weight, frailty, and the disablement process. METHOD: Longitudinal data from the Health and Retirement Study (1998-2006) were used to examine the relationship between being underweight, overweight, or obese (compared with normal weight) and the onset and progression of functional limitations and disabilities in instrumental activities of daily living (IADL) and activities of daily living (ADL) among a nationally representative sample of community-dwelling older adults (aged 50 and older) with characteristics of frailty (n= 11,491). Nonlinear multilevel models additionally adjusted for demographic characteristics and intra-individual changes in body weight, socioeconomic status, health behaviors, and health conditions over the course of 8 years. RESULTS: Compared with their nonfrail normal weight counterparts, prefrail obese respondents have a 16% (p ≤ 0.001) reduction in the expected functional limitations rate and frail overweight and obese respondents have a 10% (p ≤ 0.01) and 36% (p ≤ 0.001) reduction in the expected functional limitations rate, respectively. In addition, frail obese respondents have a 27% (p ≤ 0.05) reduction in the expected ADL disability rate. DISCUSSION: This study's findings suggest that underweight, overweight, and obese status differentially affect the risk for functional limitations and disabilities in IADL and ADL. Among prefrail and frail adults, some excess body weight in later life may be beneficial, reducing the rate of functional limitations and disability.
Keywords: Activities of Daily Living; Aged; Body Weight; Cross-Sectional Studies; Disability Evaluation; Disabled Persons; Female; Frail Elderly; Geriatric Assessment; Health Behavior; Health Surveys; Humans; Life Style; Longitudinal Studies; Male; Middle Aged; Overweight; Physical Fitness; Prospective Studies; sarcopenia; Socioeconomic factors; Thinness; United States

Restless legs syndrome and functional limitations among American elders in the Health and Retirement Study. - Dominic J Cirillo; Robert B Wallace (BMC Geriatr, 2012)
BACKGROUND: Restless legs syndrome (RLS) is a common condition associated with decreased quality of life in older adults. This study estimates the prevalence, risk factors, and functional correlates of among U.S. elders. METHODS: Subjects (n = 1,008) were sub-sampled from the 2002 cross-sectional interview survey of the Health and Retirement Study (HRS), a nationally representative study of U.S. elders. Symptoms and sleep disturbances consistent with RLS were identified. Activities of daily living (ADL), instrumental activities of daily living (IADL), and limitations for mobility, large muscle groups, gross and fine motor function were measured using standardized questions. Incident functional limitations were detected over six years of observation. RESULTS: The prevalence of RLS among U.S. elders born before 1947 was 10.6%. Factors associated with increased prevalence RLS at baseline included: overweight body mass index (multivariate adjusted prevalence ratio = 1.77; 95% confidence interval (CI) 1.05-2.99); mild-to-moderate pain (2.67, 1.47-4.84) or pain inferring with activity (3.44, 2.00-5.93); three or more chronic medications (2.54, 1.26-5.12), highest quartile of out-of-pocket medical expenses (2.12, 1.17-3.86), frequent falls (2.63, 1.49-4.66), health limiting ability to work (2.91, 1.75-4.85), or problems with early waking or frequent wakening (1.69, 1.09-2.62 and 1.55, 1.00-2.41, respectively). Current alcohol consumption (0.59, 0.37-0.92) and frequent healthcare provider visits (0.49, 0.27-0.90) were associated with decreased RLS prevalence. RLS did not predict incident disability for aggregate measures but was associated with increased risk for specific limitations, including: difficulty climbing several stair flights (multivariate-adjusted hazard ratio = 2.38, 95% CI 1.39-4.06), prolonged sitting (2.17, 1.25-3.75), rising from a chair (2.54, 1.62-3.99), stooping (2.66, 1.71-4.15), moving heavy objects (1.79, 1.08-2.99), carrying ten pounds (1.61, 1.05-2.97), raising arms (1.76, 1.05-2.97), or picking up a dime (1.97, 1.12-3.46). CONCLUSIONS: RLS sufferers are more likely to have functional disability, even after adjusting for health status and pain syndrome correlates.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Body Mass Index; Cross-Sectional Studies; Disabled Persons; Female; Humans; Male; Middle Aged; Prevalence; Restless Legs Syndrome; Risk Factors; United States

Risk factors of falls in community-dwelling older adults: logistic regression tree analysis. - Takashi Yamashita; Noe, Douglas A.; John A. Bailer (Gerontologist, 2012)
PURPOSE OF THE STUDY: A novel logistic regression tree-based method was applied to identify fall risk factors and possible interaction effects of those risk factors. DESIGN AND METHODS: A nationally representative sample of American older adults aged 65 years and older (N = 9,592) in the Health and Retirement Study 2004 and 2006 modules was used. Logistic Tree with Unbiased Selection, a computer algorithm for tree-based modeling, recursively split the entire group in the data set into mutually exclusive subgroups and fit a logistic regression model in each subgroup to generate an easily interpreted tree diagram. RESULTS: A subgroup of older adults with a fall history and either no activities of daily living (ADL) limitation and at least one instrumental activity of daily living or at least one ADL limitation was classified as at high risk of falling. Additionally, within each identified subgroup, the best predictor of falls varied over subgroups and was also evaluated. IMPLICATIONS: Application of tree-based methods may provide useful information for intervention program design and resource allocation planning targeting subpopulations of older adults at risk of falls.
Keywords: Accidental Falls; Activities of Daily Living; Aged; Aged, 80 and over; Decision Trees; Female; Geriatric Assessment; Health Surveys; Humans; Logistic Models; Male; Predictive Value of Tests; Residence Characteristics; Risk Assessment; Socioeconomic factors; United States

Self-reported and measured hypertension among older US- and foreign-born adults. - White, Kellee; Mauricio Avendano; Benjamin D Capistrant; J Robin Moon; Sze Y Liu; M. Maria Glymour (J Immigr Minor Health, 2012)
Self-reported hypertension is frequently used for health surveillance. However, little is known about the validity of self-reported hypertension among older Americans by nativity status. This study compared self-reported and measured hypertension among older black, white, and Hispanic Americans by nativity using the 2006 and 2008 Health and Retirement Study (n = 13,451). Sensitivity and specificity of self-reported hypertension were calculated using the Seventh report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure definition. Sensitivity was high among older blacks (88.9%), whites (82.8%), and Hispanics (84.0%), and both foreign-born (83.2%) and US-born (84.0%). Specificity was above 90% for both US-born and foreign-born, but higher for whites (92.8%) than blacks (86.0%). Despite the potential vulnerability of older foreign-born Americans, self-reported hypertension may be considered a reasonable estimate of hypertension status. Future research should confirm these findings in samples with a larger and more ethnically diverse foreign-born population.
Keywords: Aged; Black or African American; Blood Pressure Determination; Emigrants and Immigrants; Female; Hispanic or Latino; Humans; Hypertension; Male; Middle Aged; Nutrition Surveys; Reproducibility of Results; Self Report; United States; White People

The significance of education for mortality compression in the United States. - Dustin C. Brown; Mark D Hayward; Jennifer Karas Montez; Robert A Hummer; Chi-Tsun Chiu; Mira M Hidajat (Demography, 2012)
Recent studies of old-age mortality trends assess whether longevity improvements over time are linked to increasing compression of mortality at advanced ages. The historical backdrop of these studies is the long-term improvement in a population's socioeconomic resources that fueled longevity gains. We extend this line of inquiry by examining whether socioeconomic differences in longevity within a population are accompanied by old-age mortality compression. Specifically, we document educational differences in longevity and mortality compression for older men and women in the United States. Drawing on the fundamental cause of disease framework, we hypothesize that both longevity and compression increase with higher levels of education and that women with the highest levels of education will exhibit the greatest degree of longevity and compression. Results based on the Health and Retirement Study and the National Health Interview Survey Linked Mortality File confirm a strong educational gradient in both longevity and mortality compression. We also find that mortality is more compressed within educational groups among women than men. The results suggest that educational attainment in the United States maximizes life chances by delaying the biological aging process.
Keywords: Aged; Aged, 80 and over; Aging; Educational Status; Female; Health Status Disparities; Humans; Life Expectancy; Male; Middle Aged; Mortality; Mortality, Premature; Sex Distribution; Socioeconomic factors; United States

Spurring enrollment in Medicare savings programs through a substitute for the asset test focused on investment income. - Dorn, Stan; Shang, Baoping (Health Aff (Millwood), 2012)
Fewer than one-third of eligible Medicare beneficiaries enroll in Medicare savings programs, which pay premiums and, in some cases, eliminate out-of-pocket cost sharing for poor and near-poor enrollees. Many beneficiaries don't participate in savings programs because they must complete a cumbersome application process, including a burdensome asset test. We demonstrate that a streamlined alternative to the asset test-allowing seniors to qualify for Medicare savings programs by providing evidence of limited assets or showing a lack of investment income-would permit 78 percent of currently eligible seniors to bypass the asset test entirely. This simplified approach would increase the number of beneficiaries who qualify for Medicare savings programs from the current 3.6 million seniors to 4.6 million. Such an alternative would keep benefits targeted to people with low assets, eliminate costly administrative expenses and obstacles to enrollment associated with the asset test, and avoid the much larger influx of seniors that would occur if the asset test were eliminated entirely.
Keywords: Cost Savings; Eligibility Determination; Financing, Personal; Humans; Medicare; Poverty; United States

Stroke incidence in older US Hispanics: is foreign birth protective? - J Robin Moon; Benjamin D Capistrant; Ichiro Kawachi; Mauricio Avendano; Subramanian, S V; Lisa M. Bates; M. Maria Glymour (Stroke, 2012)
BACKGROUND AND PURPOSE: Although Hispanics are the fastest growing ethnic group in the United States, relatively little is known about stroke risk in US Hispanics. We compare stroke incidence and socioeconomic predictors in US- and foreign-born Hispanics with patterns among non-Hispanic whites. METHODS: Health and Retirement Study participants aged 50+ years free of stroke in 1998 (mean baseline age, 66.3 years) were followed through 2008 for self- or proxy-reported first stroke (n=15 784; 1388 events). We used discrete-time survival analysis to compare stroke incidence among US-born (including those who immigrated before age 7 years) and foreign-born Hispanics with incidence in non-Hispanic whites. We also examined childhood and adult socioeconomic characteristics as predictors of stroke among Hispanics, comparing effect estimates with those for non-Hispanic whites. RESULTS: In age- and sex-adjusted models, US-born Hispanics had higher odds of stroke onset than non-Hispanic whites (OR, 1.44; 95% CI, 1.08-1.90), but these differences were attenuated and nonsignificant in models that controlled for childhood and adulthood socioeconomic factors (OR, 1.07; 95% CI, 0.80-1.42). In contrast, in models adjusted for all demographic and socioeconomic factors, foreign-born Hispanics had significantly lower stroke risk than non-Hispanic whites (OR, 0.58; 95% CI, 0.41-0.81). The impact of socioeconomic predictors on stroke did not differ between Hispanics and whites. CONCLUSIONS: In this longitudinal national cohort, foreign-born Hispanics had lower incidence of stroke incidence than non-Hispanic whites and US-born Hispanics. Findings suggest that foreign-born Hispanics may have a risk factor profile that protects them from stroke as compared with other Americans.
Keywords: Age Factors; Aged; Cohort Studies; Emigration and Immigration; Female; Hispanic or Latino; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Retrospective Studies; Risk Factors; Socioeconomic factors; Stroke; United States; White People

Tests and expenditures in the initial evaluation of peripheral neuropathy. - Brian C. Callaghan; Ryan J McCammon; Kevin Kerber; Xiao Xu; Kenneth M. Langa; Eva L Feldman (Arch Intern Med, 2012)
BACKGROUND: Peripheral neuropathy is a common disorder in which an extensive evaluation is often unrevealing. METHODS: We sought to define diagnostic practice patterns as an early step in identifying opportunities to improve efficiency of care. The 1996-2007 Health and Retirement Study Medicare claims-linked database was used to identify individuals with an incident diagnosis of peripheral neuropathy using International Classification of Diseases, Ninth Revision, codes and required no previous neuropathy diagnosis during the preceding 30 months. Focusing on 15 relevant tests, we examined the number and patterns of tests and specific test utilization 6 months before and after the incident neuropathy diagnosis. Medicare expenditures were assessed during the baseline, diagnostic, and follow-up periods. RESULTS: Of the 12, 673 patients, 1031 (8.1%) received a new International Classification of Diseases, Ninth Revision, diagnosis of neuropathy and met the study inclusion criteria. Of the 15 tests considered, a median of 4 (interquartile range, 2-5) tests were performed, with more than 400 patterns of testing. Magnetic resonance imaging of the brain or spine was ordered in 23.2% of patients, whereas a glucose tolerance test was rarely obtained (1.0%). Mean Medicare expenditures were significantly higher in the diagnostic period than in the baseline period ($14,362 vs $8067, P < .001). CONCLUSIONS: Patients diagnosed as having peripheral neuropathy typically undergo many tests, but testing patterns are highly variable. Almost one-quarter of patients receiving neuropathy diagnoses undergo high-cost, low-yield magnetic resonance imaging, whereas few receive low-cost, high-yield glucose tolerance tests. Expenditures increase substantially in the diagnostic period. More research is needed to define effective and efficient strategies for the diagnostic evaluation of peripheral neuropathy.
Keywords: Aged; Antibodies, Antinuclear; Blood Cell Count; Blood Protein Electrophoresis; Blood Sedimentation; Brain; Diagnostic Tests, Routine; Electromyography; Female; Glucose Tolerance Test; Glycated Hemoglobin; Health Expenditures; Humans; International Classification of Diseases; Magnetic Resonance Imaging; Male; Medicare; Neural Conduction; Peripheral Nervous System Diseases; Quality Assurance, Health Care; Spine; Thyrotropin; United States; Vitamin B 12

Transition to retirement and risk of cardiovascular disease: prospective analysis of the US health and retirement study. - J Robin Moon; M. Maria Glymour; Subramanian, S V; Mauricio Avendano; Ichiro Kawachi (Soc Sci Med, 2012)
Transitioning from work to retirement could be either beneficial or harmful for health. We investigated the association between transition to retirement and risk of stroke and myocardial infarction (MI). We followed US Health and Retirement Study participants age 50+ working full-time for pay and free of major cardiovascular disease (n = 5422) in 1998 up to 10 years for transition to full retirement and self- or proxy-report of either stroke or MI (CVD; 665 events). We used discrete-time survival analysis to compare the CVD incidence for the fully retired versus the full-time working population. To distinguish short-term from long-term risks, we compared the association in the first year after retirement to estimates 2+ years after retirement. In the full model adjusting for age, sex, childhood and adult SES, behavior, and co-morbidities, being retired was associated with elevated odds of CVD onset (OR = 1.40, 95% CI: 1.04, 1.90) compared to those remaining in the full-time labor force. The odds ratio for CVD incidence within the first year of retirement was 1.55 (95% CI: 1.03, 2.33). From the second year post-retirement and thereafter, the retired had marginally elevated risk of CVD compared to those still working (OR = 1.35; 95% CI: 0.96, 1.91). Although confidence intervals were wide for some sub-groups, there were no significant interactions by sex or socioeconomic status. Results suggest that CVD risk is increased after retirement.
Keywords: Age Factors; Aged; Cardiovascular Diseases; Female; Health Behavior; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; Prospective Studies; Retirement; Risk Factors; Sex Factors; Socioeconomic factors; Survival Analysis; Time Factors; United States

Triggers of hospitalization for venous thromboembolism. - Mary A M Rogers; Deborah A Levine; Neil Blumberg; Scott A Flanders; Vineet Chopra; Kenneth M. Langa (Circulation, 2012)
BACKGROUND: The rate of hospitalization for venous thromboembolism (VTE) is increasing in the United States. Although predictors of hospital-acquired VTE are well-known, triggers of VTE before hospitalization are not as clearly defined. The objective of this study was to evaluate triggers of hospitalization for VTE. METHODS AND RESULTS: A case-crossover study was conducted. Subjects were participants in the Health and Retirement Study, a nationally representative sample of older Americans. Data were linked to Medicare files for hospital and nursing home stays, emergency department visits, outpatient visits including physician visits, and home health visits from years 1991 to 2007 (n=16 781). The outcome was hospitalization for venous thromboembolism (n=399). Exposures during the 90-day period before hospitalization for VTE were compared with exposures occurring in 4 comparison periods. Infection was the most common trigger of hospitalization for VTE, occurring in 52.4% of the risk periods before hospitalization. The adjusted incidence rate ratios (IRRs; 95% confidence interval) were 2.90 (2.13, 3.94) for all infection, 2.63 (1.90, 3.63) for infection without a previous hospital or skilled nursing facility stay, and 6.92 (4.46, 10.72) for infection with a previous hospital or skilled nursing facility stay. Erythropoiesis-stimulating agents and blood transfusion were also associated with VTE hospitalization (IRR=9.33, 95% confidence interval: 1.19, 73.42; IRR=2.57, 95% confidence interval: 1.17, 5.64; respectively). Other predictors included major surgeries, fractures (IRR=2.81), immobility (IRR=4.23), and chemotherapy (IRR=5.70). These predictors, combined, accounted for a large proportion (69.7%) of exposures before VTE hospitalization as opposed to 35.3% in the comparison periods. CONCLUSIONS: Risk prediction algorithms for VTE should be reevaluated to include infection, erythropoiesis-stimulating agents, and blood transfusion.
Keywords: Aged; Ambulatory Care Facilities; Comorbidity; Cross-Over Studies; Emergency Service, Hospital; Female; Hematinics; Home Care Services; Hospitalization; Humans; Immobilization; Incidence; Infections; Male; Medicare; Middle Aged; Office Visits; Postoperative Complications; Pulmonary Embolism; Risk Factors; Skilled Nursing Facilities; Transfusion Reaction; United States; Venous Thrombosis

Using marginal structural models to estimate the direct effect of adverse childhood social conditions on onset of heart disease, diabetes, and stroke. - Nandi, Arijit; M. Maria Glymour; Ichiro Kawachi; Tyler J VanderWeele (Epidemiology, 2012)
BACKGROUND: Early-life socioeconomic status (SES) is associated with adult chronic disease, but it is unclear whether this effect is mediated entirely via adult SES or whether there is a direct effect of adverse early-life SES on adult disease. Major challenges in evaluating these alternatives include imprecise measurement of early-life SES and bias in conventional regression methods to assess mediation. In particular, conventional regression approaches to direct effect estimation are biased when there is time-varying confounding of the association between adult SES and chronic disease by chronic disease risk factors. METHODS: First-reported heart disease, diabetes, and stroke diagnoses were assessed in a national sample of 9760 Health and Retirement Study participants followed biennially from 1992 through 2006. Early-life and adult SES measures were derived using exploratory and confirmatory factor analysis. Early-life SES was measured by parental education, father's occupation, region of birth, and childhood rural residence. Adult SES was measured by respondent's education, occupation, labor force status, household income, and household wealth. Using marginal structural models, we estimated the direct effect of early-life SES on chronic disease onset that was not mediated by adult SES. Marginal structural models were estimated with stabilized inverse probability-weighted log-linear models to adjust for risk factors that may have confounded associations between adult SES and chronic disease. RESULTS: During follow-up, 24%, 18%, and 9% of participants experienced first onset of heart disease, diabetes, and stroke, respectively. Comparing those in the most disadvantaged with the least disadvantaged quartile, early-life SES was associated with coronary heart disease (risk ratio = 1.30 [95% confidence interval = 1.12-1.51]) and diabetes (1.23 [1.02-1.48]) and marginally associated with stroke via pathways not mediated by adult SES. CONCLUSIONS: Our results suggest that early-life socioeconomic experiences directly influence adult chronic disease outcomes.
Keywords: Age Factors; Age of Onset; Child; Diabetes Mellitus; Educational Status; Female; Heart Diseases; Humans; Income; Linear Models; Male; Middle Aged; Models, Statistical; Risk Factors; Social Class; Social Conditions; Socioeconomic factors; Stroke; United States

Aging in a cultural context: cross-national differences in disability and the moderating role of personal control among older adults in the United States and England. - Philippa J Clarke; Jacqui Smith (J Gerontol B Psychol Sci Soc Sci, 2011)
OBJECTIVES: We investigate cross-national differences in late-life health outcomes and focus on an intriguing difference in beliefs about personal control found between older adult populations in the U.K. and United States. We examine the moderating role of control beliefs in the relationship between physical function and self-reported difficulty with daily activities. METHOD: Using national data from the United States (Health and Retirement Study) and England (English Longitudinal Study on Ageing), we examine the prevalence in disability across the two countries and show how it varies according to the sense of control. Poisson regression was used to examine the relationship between objective measures of physical function (gait speed) and disability and the modifying effects of control. RESULTS: Older Americans have a higher sense of personal control than the British, which operates as a psychological resource to reduce disability among older Americans. However, the benefits of control are attenuated as physical impairments become more severe. DISCUSSION: These results emphasize the importance of carefully considering cross-national differences in the disablement process as a result of cultural variation in underlying psychosocial resources. This paper highlights the role of culture in shaping health across adults aging in different sociopolitical contexts.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cross-Cultural Comparison; Culture; Disabled Persons; England; Female; Gait; Health Status; Humans; Internal-External Control; Longitudinal Studies; Male; Mobility Limitation; Politics; Social Values; Socioeconomic factors; United States

Anticipatory ex ante moral hazard and the effect of Medicare on prevention. - de Preux, Laure B (Health Econ, 2011)
This paper extends the ex ante moral hazard model to allow healthy lifestyles to reduce the probability of illness in future periods, so that current preventive behaviour may be affected by anticipated changes in future insurance coverage. In the United States, Medicare is offered to almost all the population at the age of 65. We use nine waves of the US Health and Retirement Study to compare lifestyles before and after 65 of those insured and not insured pre 65. The double-robust approach, which combines propensity score and regression, is used to compare trends in lifestyle (physical activity, smoking, drinking) of the two groups before and after receiving Medicare, using both difference-in-differences and difference-in-differences-in-differences. There is no clear effect of the receipt of Medicare or its anticipation on alcohol consumption nor smoking behaviour, but the previously uninsured do reduce physical activity just before receiving Medicare.
Keywords: Age Factors; Aged; Alcohol Drinking; Female; Health Behavior; Health Services; Humans; Insurance Coverage; Male; Medically Uninsured; Medicare; Middle Aged; Morals; Motor Activity; Proportional Hazards Models; Regression Analysis; Smoking; United States

Is the apolipoprotein e genotype a biomarker for mild cognitive impairment? Findings from a nationally representative study. - Brainerd, Charles J; V. F. Reyna; Ronald C Petersen; Glenn E Smith; Taub, Emily S (Neuropsychology, 2011)
OBJECTIVE: Although the ε4 allele of the apolipoprotein E (APOE) genotype is a known risk factor for Alzheimer's dementia (AD), prior findings on whether it is also a risk factor for mild cognitive impairment (MCI) have been inconsistent. We tested two contrasting explanations: (a) an ε4-AD specificity hypothesis, and (b) a measurement insensitivity hypothesis. METHOD: The frequency of the ε4 allele was investigated in older adults (mean age > 70) with various types of cognitive impairment (including MCI) and various types of dementia (including AD) with the aging, demographics, and memory study (ADAMS) of the National Institute on Aging's Health and Retirement Study (HRS). The ADAMS controls sources of Type I and Type II error that are posited in the ε4-AD specificity hypothesis and the measurement insensitivity hypothesis, and it is the only nationally representative data set on aging and cognitive impairment. RESULTS: ε4 was a reliable predictor of MCI, with a frequency of 32% in MCI subjects versus 20% in healthy control subjects. This link was specific to MCI because ε4 was not a risk factor for other forms of cognitive impairment without dementia. CONCLUSIONS: The results support the measurement insensitivity hypothesis rather than the ε4-AD specificity hypothesis and are consistent with recent research showing modest reductions in cognitive performance among normal functioning ε4 carriers.
Keywords: Aged; Aged, 80 and over; Aging; Analysis of Variance; Apolipoprotein E4; Cognitive Dysfunction; Dementia; Female; Gene Frequency; Genetic Markers; Genetic Testing; Genotype; Humans; Male; National Institute on Aging (U.S.); Neuropsychological tests; Reference Values; Reproducibility of Results; Risk Factors; United States

Assessment of cognition using surveys and neuropsychological assessment: the Health and Retirement Study and the Aging, Demographics, and Memory Study. - Eileen M. Crimmins; Jung K Kim; Kenneth M. Langa; David R Weir (J Gerontol B Psychol Sci Soc Sci, 2011)
OBJECTIVES: This study examines the similarity of cognitive assessments using 1 interview in a large population study, the Health and Retirement Study (HRS), and a subsample in which a detailed neuropsychiatric assessment has been performed (Aging, Demographics, and Memory Study [ADAMS]). METHODS: Respondents are diagnosed in ADAMS as demented, cognitively impaired without dementia (CIND), or as having normal cognitive function. Multinomial logistic analysis is used to predict diagnosis using a variety of cognitive and noncognitive measures from the HRS and additional measures and information from ADAMS. RESULTS: The cognitive tests in HRS predict the ADAMS diagnosis in 74% of the sample able to complete the HRS survey on their own. Proxy respondents answer for a large proportion of HRS respondents who are diagnosed as demented in ADAMS. Classification of proxy respondents with some cognitive impairment can be predicted in 86% of the sample. Adding a small number of additional tests from ADAMS can increase each of these percentages to 84% and 93%, respectively. DISCUSSION: Cognitive assessment appropriate for diagnosis of dementia and CIND in large population surveys could be improved with more targeted information from informants and additional cognitive tests targeting other areas of brain function.
Keywords: Age Factors; Aged; Aged, 80 and over; Cognition; Cognition Disorders; Dementia; Educational Status; Female; Humans; Interviews as Topic; Logistic Models; Longitudinal Studies; Male; Multivariate Analysis; Neuropsychological tests; Odds Ratio; Prevalence; Sex Factors; United States

Can Food Stamps help to reduce Medicare spending on diabetes? - Lauren Hersch Nicholas (Econ Hum Biol, 2011)
Diabetes is rapidly escalating amongst low-income, older adults at great cost to the Medicare program. We use longitudinal survey data from the Health and Retirement Study linked to administrative Medicare records and biomarker data to assess the relationship between Food Stamp receipt and diabetes health outcomes. We find no significant difference in Medicare spending, outpatient utilization, diabetes hospitalizations and blood sugar (HbA1c) levels between recipients and income-eligible non-recipients after controlling for a detailed set of covariates including individual fixed effects and measures of diabetes treatment compliance. As one-third of elderly Food Stamp recipients are currently diabetic, greater coordination between the Food Stamp, Medicare, and Medicaid programs may improve health outcomes for this group.
Keywords: Aged; Aged, 80 and over; Biomarkers; Confidence Intervals; Cross-Sectional Studies; Diabetes Mellitus; Female; Glycated Hemoglobin; Health Care Costs; Humans; Longitudinal Studies; Male; Medicare; Middle Aged; Odds Ratio; Outpatients; Poverty; Prevalence; Public Assistance; Regression Analysis; Social Welfare; Treatment Outcome; United States

Caring for individuals with dementia and cognitive impairment, not dementia: findings from the aging, demographics, and memory study. - Gwenith G Fisher; Melissa M Franks; Brenda L Plassman; Stephanie Brown; Guy G Potter; David J Llewellyn; Mary A M Rogers; Kenneth M. Langa (J Am Geriatr Soc, 2011)
OBJECTIVES: To compare the characteristics and outcomes of caregivers of adults with dementia with those of caregivers of adults with cognitive impairment, not dementia (CIND). DESIGN: Cross-sectional. SETTING: In-home assessment for cognitive impairment and self-administered caregiving questionnaire. PARTICIPANTS: One hundred sixty-nine primary family caregivers of participants in the Aging, Demographics, and Memory Study (ADAMS). ADAMS participants were aged 71 and older drawn from the nationally representative Health and Retirement Study. MEASUREMENTS: Neuropsychological testing, neurological examination, clinical assessment, and medical history were used to assign a diagnosis of normal cognition, CIND, or dementia. Caregiving measures included caregiving time, functional limitations, depressive symptoms, physical and emotional strain, caregiving rewards, caregiver health, and demographic characteristics. RESULTS: Dementia caregivers spent approximately 9 hours per day providing care, compared with 4 hours per day for CIND caregivers (P=.001). Forty-four percent of dementia caregivers exhibited depressive symptoms, compared with 26.5% of CIND caregivers (P=.03). Physical and emotional strains were similar in both groups of caregivers. Regardless of the strains, nearly all caregivers reported some benefits from providing care. Behavioral problems (P=.01) and difficulty with instrumental activities of daily living (P=.01) in persons with CIND partially explained emotional strain experienced by CIND caregivers. For those with dementia, behavioral problems predicted caregiver emotional strain (P<.001) and depressive symptoms (P=.01). CONCLUSION: Although support services are available to dementia caregivers, CIND caregivers also expend considerable time and experience strains. The real caregiver burden of cognitive impairment in the U.S. population may therefore be greatly underestimated if people who have reached the diagnostic threshold for dementia are focused on exclusively.
Keywords: Activities of Daily Living; Aged; Analysis of Variance; Caregivers; Cognition Disorders; Cross-Sectional Studies; Dementia; Female; Humans; Linear Models; Male; Neuropsychological tests; Time Factors; United States

Changes in the prevalence of cognitive impairment among older Americans, 1993-2004: overall trends and differences by race/ethnicity. - Sheffield, Kristin M; M. Kristen Peek (Am J Epidemiol, 2011)
The authors used data from 6 waves of the Health and Retirement Study to evaluate changes in the prevalence of cognitive impairment among adults 70 years of age or older from 1993 to 2004. Having sampling weights for each wave enabled the authors to create merged waves that represented cross-sections of the community-dwelling older population for that year. Logistic regression analyses with year as the predictor were used to estimate trends and determine the contribution of sociodemographic and health status variables to decreasing trends in the prevalence of cognitive impairment over time (score ≤8 on a modified Telephone Interview Cognitive Screen). Results showed an annual decline in the prevalence of cognitive impairment of 3.4% after adjustment for age, gender, and prior test exposure (odds ratio (OR) = 0.966, 95% confidence interval (CI): 0.941, 0.992). The addition of socioeconomic variables to the model attenuated the trend by 72.1%. The annual percentage of decline in impairment was larger for blacks (OR = 0.943, 95% CI: 0.914, 0.973) and Hispanics (OR = 0.954, 95% CI: 0.912, 0.997) than for whites (OR = 0.971, 95% CI: 0.936, 1.006), although the differences were not statistically significant. Linear probability models used in secondary analyses showed larger percentage-point declines for blacks and Hispanics. Improvements in educational level contributed to declines in cognitive impairment among older adults-particularly blacks and Hispanics-in the United States.
Keywords: Age Factors; Aged; Black People; Chi-Square Distribution; Cognition Disorders; Confidence Intervals; ethnicity; Female; Health Behavior; Health Status; Hispanic or Latino; Humans; Logistic Models; Longitudinal Studies; Male; Odds Ratio; Prevalence; Racial Groups; Socioeconomic factors; United States; White People

Childhood health and labor market inequality over the life course. - Steven A Haas; M. Maria Glymour; Lisa F Berkman (J Health Soc Behav, 2011)
The authors use data from the Health and Retirement Study's Earnings Benefit File, which links Health and Retirement Study to Social Security Administration records, to estimate the impact of childhood health on earnings curves between the ages of 25 and 50 years. They also investigate the extent to which diminished educational attainment, earlier onset of chronic health conditions, and labor force participation mediate this relationship. Those who experience poor childhood health have substantially diminished labor market earnings over the work career. For men, earnings differentials grow larger over the early to middle career and then slow down and begin to converge as they near 50 years of age. For women, earnings differentials emerge later in the career and show no evidence of convergence. Part of the child health earnings differential is accounted for by selection into diminished educational attainment, the earlier onset of chronic disease in adulthood, and, particularly for men, labor force participation.
Keywords: Child; Employment; Female; Health Status; Humans; Income; Male; Middle Aged; Models, Econometric; Retirement; Social Class; Social Security; Socioeconomic factors; United States

Chronic diseases and functional limitations among older construction workers in the United States: a 10-year follow-up study. - Xiuwen S Dong; Wang, Xuanwen; Daw, Christina; Ringen, Knut (J Occup Environ Med, 2011)
OBJECTIVES: To examine the health status of older construction workers in the United States, and how occupation and the aging process affect health in workers' later years. METHODS: We analyzed six waves (1998 to 2008) of the Health and Retirement Study, a longitudinal survey of US residents age 50+. The study sample totaled 7200 male workers (510 in construction trades) in the baseline. Multiple logistic regression and paired t tests were conducted to compare health outcomes across occupations and within individuals over time. RESULTS: Compared with white-collar workers, construction workers had increased odds of arthritis, back problems, chronic lung disease, functional limitations, work disability, and work-related injuries after controlling for possible confounders. CONCLUSIONS: Safety and health interventions, as well as retirement and pension policy, should meet the needs of older construction workers, who face increasingly chronic health conditions over time.
Keywords: Aged; Aging; Arthritis; Chronic disease; Disabled Persons; Facility Design and Construction; Follow-Up Studies; Humans; Lung Diseases; Male; Middle Aged; Occupational Diseases; Occupations; United States

Depression and the onset of chronic illness in older adults: a 12-year prospective study. - Mustafa C. Karakus; Lisa C Patton (J Behav Health Serv Res, 2011)
The relationship between depression and development of chronic illness among older adults is not well understood. This study uses data from the Health and Retirement Study to evaluate the relationship between depression at baseline and new onset of chronic illnesses including cancer, heart problems, arthritis, and diabetes. Analysis controlling for demographics (age, gender, race, education), health risk indicators (BMI and smoking), functional limitations (gross motor index, health limitations for work), and income show that working-age older people (ages 50-62) with depression at baseline are at significantly higher risk to develop diabetes, heart problems, and arthritis during the 12-year follow-up. No significant association was found between depression and cancer. Prevention efforts aimed at chronic illnesses among the elderly should recognize the mind-body interaction and focus on preventing or alleviating depression.
Keywords: Activities of Daily Living; Age Distribution; Aged; Chronic disease; depression; Female; Follow-Up Studies; Humans; Male; Middle Aged; Prospective Studies; Psychiatric Status Rating Scales; Risk Factors; Sex Distribution; Socioeconomic factors; United States

Determinants of medical expenditures in the last 6 months of life. - Amy Kelley; Susan L Ettner; R Sean Morrison; Qingling Du; Neil S. Wenger; Catherine A Sarkisian (Annals of Internal Medicine, 2011)
BACKGROUND: End-of-life medical expenditures exceed costs of care during other years, vary across regions, and are likely to be unsustainable. Identifying determinants of expenditure variation may reveal opportunities for reducing costs. OBJECTIVE: To identify patient-level determinants of Medicare expenditures at the end of life and to determine the contributions of these factors to expenditure variation while accounting for regional characteristics. It was hypothesized that race or ethnicity, social support, and functional status are independently associated with treatment intensity and controlling for regional characteristics, and that individual characteristics account for a substantial proportion of expenditure variation. DESIGN: Using data from the Health and Retirement Study, Medicare claims, and The Dartmouth Atlas of Health Care, relationships were modeled between expenditures and patient and regional characteristics. SETTING: United States, 2000 to 2006. PARTICIPANTS: 2394 Health and Retirement Study decedents aged 65.5 years or older. MEASUREMENTS: Medicare expenditures in the last 6 months of life were estimated in a series of 2-level multivariable regression models that included patient, regional, and patient and regional characteristics. RESULTS: Decline in function (rate ratio [RR], 1.64 [95% CI, 1.46 to 1.83]); Hispanic ethnicity (RR, 1.50 [CI, 1.22 to 1.85]); black race (RR, 1.43 [CI, 1.25 to 1.64]); and certain chronic diseases, including diabetes (RR, 1.16 [CI, 1.06 to 1.27]), were associated with higher expenditures. Nearby family (RR, 0.90 [CI, 0.82 to 0.98]) and dementia (RR, 0.78 CI, 0.71 to 0.87]) were associated with lower expenditures, and advance care planning had no association. Regional characteristics, including end-of-life practice patterns (RR, 1.09 [CI, 1.06 to 1.14]) and hospital beds per capita (RR, 1.01 [CI, 1.00 to 1.02]), were associated with higher expenditures. Patient characteristics explained 10% of overall variance and retained statistically significant relationships with expenditures after regional characteristics were controlled for. LIMITATION: The study limitations include the decedent sample, proxy informants, and a large proportion of unexplained variation. CONCLUSION: Patient characteristics, such as functional decline, race or ethnicity, chronic disease, and nearby family, are important determinants of expenditures at the end of life, independent of regional characteristics. PRIMARY FUNDING SOURCE: The Brookdale Foundation.
Keywords: Aged; Aged, 80 and over; Chronic disease; Ethnic Groups; Female; Health Expenditures; Humans; Income; Independent Living; Male; Medicare; Regression Analysis; Social Support; Socioeconomic factors; Terminal Care; United States

Is diabetes-specific health literacy associated with diabetes-related outcomes in older adults? - Takashi Yamashita; Cary S Kart (J Diabetes, 2011)
BACKGROUND:  The present study examined the association between a measure of diabetes-specific health literacy and three different Type 2 diabetes outcome indicators in a national sample of older adults. METHODS: Data were taken from the Health and Retirement Study (HRS) 2003 Diabetes module and the HRS 2002 core wave. Analysis was performed on data from 1318 respondents aged 42-96 years [mean (±SD) 67.96 ± 8.65 years] who submitted responses on all relevant independent variable measures along with an HbA1c test kit. The index of diabetes-specific health literacy was constructed from responses to 10 diabetes self-care regimen items (α = 0.927). RESULTS: Using a multivariate regression strategy to analyze weighted data, the diabetes-specific health literacy index was significantly and positively associated with self-graded assessment of diabetes self-care (R2 = 0.231). However, diabetes-specific health literacy was not independently associated with the HbA1c level or the average number of days five recommended self-management behaviors were practiced each week. CONCLUSIONS:  No previous single study has focused on the relationship between diabetes-specific health literacy and multiple diabetes-related outcomes. The direct association of diabetes-specific health literacy with patients' assessment of their self-care practice acumen is useful information for the design of effective patient intervention and/or communication strategies. Health literacy is a broad, multidimensional construct that bridges basic literacy skills and various health and illness contexts. Because it is so important to adults engaged in the self-management of chronic illness, indicators of disease-specific knowledge and/or understanding should be included in efforts to measure health literacy.
Keywords: Adult; Aged; Aged, 80 and over; Blood Glucose; Diabetes Mellitus, Type 2; Glycated Hemoglobin; Health Literacy; Humans; Logistic Models; Middle Aged; Multivariate Analysis; Self Care; Socioeconomic factors; Surveys and Questionnaires; United States

Differences in health between Americans and Western Europeans: Effects on longevity and public finance. - Pierre-Carl Michaud; Dana P Goldman; Darius Lakdawalla; Adam Gailey; Yuhui Zheng (Soc Sci Med, 2011)
In 1975, 50-year-old Americans could expect to live slightly longer than most of their Western European counterparts. By 2005, American life expectancy had fallen behind that of most Western European countries. We find that this growing longevity gap is primarily due to real declines in the health of near-elderly Americans, relative to their Western European peers. We use a microsimulation approach to project what US longevity would look like, if US health trends approximated those in Western Europe. The model implies that differences in health can explain most of the growing gap in remaining life expectancy. In addition, we quantify the public finance consequences of this deterioration in health. The model predicts that gradually moving American cohorts to the health status enjoyed by Western Europeans could save up to $1.1 trillion in discounted total health expenditures from 2004 to 2050.
Keywords: Activities of Daily Living; Adult; Aged; Body Mass Index; Cross-Cultural Comparison; Disabled Persons; Europe; Female; Health Expenditures; health policy; Health Status Disparities; Health Surveys; Humans; Internationality; Life Expectancy; Male; Middle Aged; Models, Economic; Models, Statistical; Mortality; Public Health; United States

Do biological measures mediate the relationship between education and health: A comparative study. - Goldman, Noreen; Cassio M. Turra; Rosero-Bixby, Luis; David R Weir; Eileen M. Crimmins (Soc Sci Med, 2011)
Despite a myriad of studies examining the relationship between socioeconomic status and health outcomes, few have assessed the extent to which biological markers of chronic disease account for social disparities in health. Studies that have examined this issue have generally been based on surveys in wealthy countries that include a small set of clinical markers of cardiovascular disease. The availability of recent data from nationally representative surveys of older adults in Costa Rica and Taiwan that collected a rich set of biomarkers comparable to those in a recent US survey permits us to explore these associations across diverse populations. Similar regression models were estimated on three data sets - the Social Environment and Biomarkers of Aging Study in Taiwan, the Costa Rican Study on Longevity and Healthy Aging, and the Health and Retirement Study in the USA - in order to assess (1) the strength of the associations between educational attainment and a broad range of biomarkers; and (2) the extent to which these biomarkers account for the relationships between education and two measures of health status (self-rated health, functional limitations) in older populations. The estimates suggest non-systematic and weak associations between education and high risk biomarker values in Taiwan and Costa Rica, in contrast to generally negative and significant associations in the US, especially among women. The results also reveal negligible or modest contributions of the biomarkers to educational disparities in the health outcomes. The findings are generally consistent with previous research suggesting stronger associations between socioeconomic status and health in wealthy countries than in middle-income countries and may reflect higher levels of social stratification in the US. With access to an increasing number of longitudinal biosocial surveys, researchers may be better able to distinguish true variations in the relationship between socioeconomic status and health across different settings from methodological differences.
Keywords: Biomarkers; Blood pressure; Body Mass Index; Cholesterol; Costa Rica; Educational Status; Female; Health Status Disparities; Health Status Indicators; Health Surveys; Humans; Male; Middle Aged; Qualitative Research; Taiwan; United States

Does informal care attenuate the cycle of ADL/IADL disability and depressive symptoms in late life? - Lin, I-Fen; Wu, Hsueh-Sheng (J Gerontol B Psychol Sci Soc Sci, 2011)
OBJECTIVE: Prior studies have extensively examined the reciprocal relation between disability and depressive symptoms in late life, but little is known about whether informal care attenuates the reciprocal relation over time. This study examined whether disability and depressive symptoms mobilize informal care and whether informal care, once mobilized, protects older adults against the progression of disability and depressive symptoms. METHODS: The analysis was based on 6,454 community-dwelling older adults who were interviewed in one or more waves of the Health and Retirement Study between 1998 and 2006. Extending an autoregressive cross-lagged model, we constructed 3 cycles of the relations among disability, depressive symptoms, and informal care. Comparing the relations across 3 cycles informs us about the attenuating effect of informal care on the relation between disability and depressive symptoms over time. RESULTS: Although older adults' disability and depressive symptoms mobilized informal care initially, worsening disability and depressive symptoms often exhausted support. Receipt of care generally increased, rather than decreased, disability and depressive symptoms, and the detrimental effects remained the same over time. DISCUSSION: We need to better understand the linkage between disability and depressive symptoms and seek effective interventions to reduce caregiver strain and enhance care receivers' well-being.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Cohort Studies; Cost of Illness; depression; Disability Evaluation; Female; Humans; Longitudinal Studies; Male; Models, Psychological; United States

Does self-reported health bias the measurement of health inequalities in U.S. adults? Evidence using anchoring vignettes from the Health and Retirement Study. - Jennifer B Dowd; Todd, Megan (J Gerontol B Psychol Sci Soc Sci, 2011)
OBJECTIVES: Measurement of health inequalities based on self-reports may be biased if individuals use response scales in systematically different ways. We use anchoring vignettes to test and adjust for reporting differences by education, race/ethnicity, and gender in self-reported health in 6 domains (pain, sleep, mobility, memory, shortness of breath, and depression). METHOD: Using data from the 2006 U.S. Health and Retirement Study (HRS) and the 2007 Disability Vignette Survey, we estimated generalized ordered probit models of the respondent's rating of each vignette character's health problem, allowing cut-points to vary by age, gender, education, and race/ethnicity. We then used one-step hierarchical ordered probit (HOPIT) models to jointly estimate the respondent's cut-points from the vignettes and the severity of the respondent's own health problems based on these vignette cut-points. RESULTS: We found strong evidence of reporting differences by age, gender, education, and race/ethnicity, with the magnitude depending on the specific health domain. Overall, traditional models not accounting for reporting differences underestimated the magnitude of health inequalities by education and race/ethnicity. DISCUSSION: These results suggest caution in relying on self-reported health measures to quantify and explain health disparities by socioeconomic status and race/ethnicity/ethnicity in the United States. The findings support expansion of the use of anchoring vignettes to properly account for reporting differences in self-reports of health.
Keywords: Adult; Aged; Aged, 80 and over; Attitude to Health; Bias; Black People; Disability Evaluation; Educational Status; Female; Geriatric Assessment; Health Status Indicators; Health Surveys; Hispanic or Latino; Humans; Longitudinal Studies; Male; Middle Aged; Socioeconomic factors; United States; White People

Dynamic Inefficiencies in an Employment-Based Health Insurance System: Theory and Evidence. - Fang, H.; Alessandro Gavazza (Am Econ Rev, 2011)
We investigate the effects of the institutional settings of the US health care system on individuals' life-cycle medical expenditures. Health is a form of general human capital; labor turnover and labor-market frictions prevent an employer-employee pair from capturing the entire surplus from investment in an employee’s health. Thus, the pair underinvests in health during working years, thereby increasing medical expenditures during retirement. We provide empirical evidence consistent with the comparative statics predictions of our model using the Medical Expenditure Panel Survey (MEPS) and the Health and Retirement Study (HRS). Our estimates suggest significant inefficiencies in health investment in the United States.
Keywords: Employment; Health Benefit Plans, Employee; Health Expenditures; Health Status; Humans; Income; Personnel Turnover; Retirement; United States

The effect of job loss on overweight and drinking. - Deb, Partha; William T Gallo; Padmaja Ayyagari; Jason M. Fletcher; Jody L Sindelar (J Health Econ, 2011)
This paper examines the impact of job loss due to business closings on body mass index (BMI) and alcohol consumption. We suggest that the ambiguous findings in the extant literature may be due in part to unobserved heterogeneity in response and in part due to an overly broad measure of job loss that is partially endogenous (e.g., layoffs). We improve upon this literature using: exogenously determined business closings, a sophisticated estimation approach (finite mixture models) to deal with complex heterogeneity, and national, longitudinal data from the Health and Retirement Study. For both alcohol consumption and BMI, we find evidence that individuals who are more likely to respond to job loss by increasing unhealthy behaviors are already in the problematic range for these behaviors before losing their jobs. These results suggest the health effects of job loss could be concentrated among "at risk" individuals and could lead to negative outcomes for the individuals, their families, and society at large.
Keywords: Alcohol Drinking; Body Mass Index; Female; Humans; Longitudinal Studies; Male; Middle Aged; Overweight; Unemployment; United States

The evolution of advance directives. - Douglas B. White; Robert M. Arnold (JAMA, 2011)
Keywords: Advance directives; Cost Savings; Decision making; Health Expenditures; Humans; Medicare; Palliative care; Terminal Care; United States

Gender differences in functional limitations in adults living with type 2 diabetes: biobehavioral and psychosocial mediators. - Chiu, Ching-Ju; Linda A. Wray (Ann Behav Med, 2011)
BACKGROUND: Differences in functional limitations between adults with and without diabetes are more evident in women than they are in men. PURPOSE: This study aims to investigate if there are gender differences in biological, behavioral, and psychosocial variables, and how these gender-related variables explain the gender-functional limitations relationship in adults with type 2 diabetes. METHODS: We drew data on 1,619 adults with type 2 diabetes from the Health and Retirement Study and its diabetes-specific mail survey. The fit of a series of mediation models to the data was assessed by structural equation modeling. RESULTS: Although women had better diet and blood glucose self-monitoring behaviors than did men, they reported less favorable body mass index, glycosylated hemoglobin (HbA1c) value, blood pressure, early complications, exercise behaviors, perceived control, self-efficacy, coping, depressive symptoms, and family support than did men. Psychosocial factors made an indirect contribution in the gender-functional limitations relationship by way of their strong association with biological and behavioral factors, two factors that directly and completely mediated the gender-functional limitations relationship. CONCLUSIONS: Interventions promoting psychosocial well-being and empowering perceived diabetes control, coping, and self-efficacy in women with type 2 diabetes may help improve biological and behavioral determinants, and further, their long-term functional health.
Keywords: Adult; Aged; Aged, 80 and over; Biomarkers; Blood Glucose Self-Monitoring; Body Mass Index; Diabetes Mellitus, Type 2; Exercise; Female; Health Behavior; Humans; Male; Middle Aged; Models, Psychological; Prospective Studies; Risk Factors; Self Report; Sex Characteristics; Socioeconomic factors; United States

Gender, marital power, and marital quality in later life. - Jennifer R. Bulanda (J Women Aging, 2011)
This study uses data from the 1992 Health and Retirement Study to examine gender differences in marital power and marital quality among older adults and to assess whether there are gender differences in the correlates of marital quality and marital power in later life. Results show that women report lower marital happiness, marital interaction, and marital power than do men, on average. These differences persist even after controlling for a number of life-course events and transitions. Further, results show that gender differences are also evident in the relationship of employment, childrearing, caregiving, and health factors with marital quality and power.
Keywords: Female; Health Status; Health Surveys; Humans; Interpersonal Relations; Male; Marriage; Middle Aged; Power, Psychological; Quality of Life; Regression Analysis; Sex Distribution; Socioeconomic factors; United States; Women, Working

Higher education delays and shortens cognitive impairment: a multistate life table analysis of the US Health and Retirement Study. - Mieke Reuser; Frans J Willekens; Luc G Bonneux (Eur J Epidemiol, 2011)
Improved health may extend or shorten the duration of cognitive impairment by postponing incidence or death. We assess the duration of cognitive impairment in the US Health and Retirement Study (1992-2004) by self reported BMI, smoking and levels of education in men and women and three ethnic groups. We define multistate life tables by the transition rates to cognitive impairment, recovery and death and estimate Cox proportional hazard ratios for the studied determinants. 95% confidence intervals are obtained by bootstrapping. 55 year old white men and women expect to live 25.4 and 30.0 years, of which 1.7 [95% confidence intervals 1.5; 1.9] years and 2.7 [2.4; 2.9] years with cognitive impairment. Both black men and women live 3.7 [2.9; 4.5] years longer with cognitive impairment than whites, Hispanic men and women 3.2 [1.9; 4.6] and 5.8 [4.2; 7.5] years. BMI makes no difference. Smoking decreases the duration of cognitive impairment with 0.8 [0.4; 1.3] years by high mortality. Highly educated men and women live longer, but 1.6 years [1.1; 2.2] and 1.9 years [1.6; 2.6] shorter with cognitive impairment than lowly educated men and women. The effect of education is more pronounced among ethnic minorities. Higher life expectancy goes together with a longer period of cognitive impairment, but not for higher levels of education: that extends life in good cognitive health but shortens the period of cognitive impairment. The increased duration of cognitive impairment in minority ethnic groups needs further study, also in Europe.
Keywords: Age Factors; Aged; Aged, 80 and over; Body Mass Index; Cognition Disorders; Educational Status; Female; Health Surveys; Humans; Incidence; Life Expectancy; Life Tables; Male; Middle Aged; Prevalence; Proportional Hazards Models; Retirement; Sex Factors; Smoking; Time Factors; United States

How does health insurance affect the retirement behavior of women? - Kanika Kapur; Jeannette Rogowski (Inquiry, 2011)
The availability of health insurance is a crucial factor in the retirement decision. Women are substantially less likely to have health insurance from their own employment. Using the Health and Retirement Study, we examine the role of employer-provided retiree health insurance in the retirement decisions of single women, and women in single-earner and dual-earner couples. We compare the effect of health insurance on female and male retirement. Our results show that retiree health insurance increases retirement for all groups except single men. We find suggestive evidence that the role of health insurance for women hinges on their husbands' labor force status.
Keywords: Decision making; Female; Health Benefit Plans, Employee; Humans; Male; Models, Econometric; Multivariate Analysis; Pensions; Retirement; Spouses; United States; Women, Working

How does the trajectory of multimorbidity vary across Black, White, and Mexican Americans in middle and old age? - Ana R Quiñones; Jersey Liang; Joan M. Bennett; Xiao Xu; Wen Ye (J Gerontol B Psychol Sci Soc Sci, 2011)
OBJECTIVES: This research examines intra- and interpersonal differences in multiple chronic conditions reported by Americans aged 51 and older for a period up to 11 years. It focuses on how changes in multimorbidity vary across White, Black, and Mexican Americans. METHODS: Data came from 17,517 respondents of the Health and Retirement Study (1995-2006) with up to 5 repeated observations. Hierarchical linear models were employed to analyze ethnic variations in temporal changes of reported comorbidities. FINDINGS: Middle-aged and older Americans have on average nearly 2 chronic diseases at the baseline, which increased to almost 3 conditions in 11 years. White Americans differ from Black and Mexican Americans in terms of level and rate of change of multimorbidity. Mexican Americans demonstrate lower initial levels and slower accumulation of comorbidities relative to Whites. In contrast, Blacks showed an elevated level of multimorbidity throughout the 11-year period of observation, although their rate of change slowed relative to Whites. DISCUSSION: These results suggest that health differences between Black Americans and other ethnic groups including White and Mexican Americans persist in the trajectory of multimorbidity even when population heterogeneity is adjusted. Further research is needed concerning the impact of health disadvantages and differential mortality that may have occurred before middle age as well as exploring the role of nativity, the nature of self-reported diseases, and heterogeneity underlying the average trajectory of multimorbidity for ethnic elders.
Keywords: Aged; Aged, 80 and over; Aging; Black or African American; Chronic disease; Female; Follow-Up Studies; Health Behavior; Health Status Disparities; Hispanic or Latino; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; United States; White People

The impact of private long-term care insurance on the use of long-term care. - Yong Li; Gail A Jensen (Inquiry, 2011)
This paper investigates the effects of privately purchased long-term care insurance (LTCI) on three major types of long-term care services: nursing home care, paid home care, and informal care received from Family and friends. Using 2002-2008 data from the ongoing Health and Retirement Study, we analyze the determinants of long-term care utilization simultaneously with the determinants of holding LTCI. We find that LTCI has modest effects on the likelihood of using long-term care services. For the very frail elderly, private LTCI enhances their access to nursing home care. For those with moderate disability, LTCI makes it more likely that they can remain at home and receive home care services, instead of going to a nursing home. We find no evidence that formal care substitutes for informal care in the presence of LTCI. These findings suggest that if LTCI becomes much more prevalent in the future, many older adults will be able to choose the type of long-term care arrangement that best suits their needs.
Keywords: Aged; Aged, 80 and over; Decision making; Female; Health Services Accessibility; Home Care Services; Home Nursing; Humans; Insurance, Long-Term Care; Likelihood Functions; Long-term Care; Male; Models, Econometric; Nursing homes; Private Sector; Regression Analysis; United States

Implementation of Medicare Part D and nondrug medical spending for elderly adults with limited prior drug coverage. - J. Michael McWilliams; Alan M. Zaslavsky; Haiden A. Huskamp (JAMA, 2011)
CONTEXT: Implementation of Medicare Part D was followed by increased use of prescription medications, reduced out-of-pocket costs, and improved medication adherence. Its effects on nondrug medical spending remain unclear. OBJECTIVE: To assess differential changes in nondrug medical spending following the implementation of Part D for traditional Medicare beneficiaries with limited prior drug coverage. DESIGN, SETTING, AND PARTICIPANTS: Nationally representative longitudinal survey data and linked Medicare claims from 2004-2007 were used to compare nondrug medical spending before and after the implementation of Part D by self-reported generosity of prescription drug coverage before 2006. Participants included 6001 elderly Medicare beneficiaries from the Health and Retirement Study, including 2538 with generous and 3463 with limited drug coverage before 2006. Comparisons were adjusted for sociodemographic and health characteristics and checked for residual confounding by conducting similar comparisons for a control cohort from 2002-2005. MAIN OUTCOME MEASURE: Nondrug medical spending assessed from claims, in total and by type of service (inpatient and skilled nursing facility vs physician services). RESULTS: Total nondrug medical spending was differentially reduced after January 1, 2006, for beneficiaries with limited prior drug coverage (-$306/quarter [95% confidence interval CI, -$586 to -$51]; P = .02), relative to beneficiaries with generous prior drug coverage. This differential reduction was explained mostly by differential changes in spending on inpatient and skilled nursing facility care (-$204/quarter [95% CI, -$447 to $2]; P = .05). Differential reductions in spending on physician services (-$67/quarter [95% CI, -$134 to -$5]; P = .03) were not associated with differential changes in outpatient visits (-0.06 visits/quarter [95% CI, -0.21 to 0.08]; P = .37), suggesting reduced spending on inpatient physician services for beneficiaries with limited prior drug coverage. In contrast, nondrug medical spending in the control cohort did not differentially change after January 1, 2004, for beneficiaries with limited prior drug coverage in 2002 ($14/quarter [95% CI, -$338 to $324]; P = .93), relative to beneficiaries with generous prior coverage. CONCLUSION: Implementation of Part D was associated with significant differential reductions in nondrug medical spending for Medicare beneficiaries with limited prior drug coverage.
Keywords: Aged; Aged, 80 and over; Cost Control; Costs and Cost Analysis; Data collection; Female; Health Expenditures; Health Services; Humans; Insurance Claim Review; Longitudinal Studies; Male; Medicare Part D; Patient Care; Physicians; Skilled Nursing Facilities; United States

Incidence of dementia and cognitive impairment, not dementia in the United States. - Brenda L Plassman; Kenneth M. Langa; Ryan J McCammon; Gwenith G Fisher; Guy G Potter; James R Burke; David C Steffens; Norman L Foster; Bruno J Giordani; Frederick W Unverzagt; Kathleen A Welsh-Bohmer; Steven G Heeringa; et al. (Ann Neurol, 2011)
OBJECTIVE: Estimates of incident dementia, and cognitive impairment, not dementia (CIND) (or the related mild cognitive impairment) are important for public health and clinical care policy. In this paper, we report US national incidence rates for dementia and CIND. METHODS: Participants in the Aging, Demographic, and Memory Study (ADAMS) were evaluated for cognitive impairment using a comprehensive in-home assessment. A total of 456 individuals aged 72 years and older, who were not demented at baseline, were followed longitudinally from August 2001 to December 2009. An expert consensus panel assigned a diagnosis of normal cognition, CIND, or dementia and its subtypes. Using a population-weighted sample, we estimated the incidence of dementia, Alzheimer disease (AD), vascular dementia (VaD), and CIND by age. We also estimated the incidence of progression from CIND to dementia. RESULTS: The incidence of dementia was 33.3 (standard error [SE], 4.2) per 1,000 person-years and 22.9 (SE, 2.9) per 1,000 person-years for AD. The incidence of CIND was 60.4 (SE, 7.2) cases per 1,000 person-years. An estimated 120.3 (SE, 16.9) individuals per 1,000 person-years progressed from CIND to dementia. Over a 5.9-year period, about 3.4 million individuals aged 72 and older in the United States developed incident dementia, of whom approximately 2.3 million developed AD, and about 637,000 developed VaD. Over this same period, almost 4.8 million individuals developed incident CIND. INTERPRETATION: The incidence of CIND is greater than the incidence of dementia, and those with CIND are at high risk of progressing to dementia, making CIND a potentially valuable target for treatments aimed at slowing cognitive decline.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Cognition Disorders; Cohort Studies; Dementia; Diagnostic and Statistical Manual of Mental Disorders; disease progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Models, Statistical; United States

Increasing and decreasing alcohol use trajectories among older women in the U.S. across a 10-year interval. - Janet Kay Bobo; April A Greek (Int J Environ Res Public Health, 2011)
Older women who routinely drink alcohol may experience health benefits, but they are also at risk for adverse effects. Despite the importance of their drinking patterns, few studies have analyzed longitudinal data on changes in drinking among community-based samples of women ages 50 and older. Reported here are findings from a semi-parametric group-based model that used data from 4,439 randomly sampled U.S. women who enrolled in the Health and Retirement Study (HRS) and completed ≥ 3 biannual alcohol assessments during 1998-2008. The best-fitting model based on the drinks per day data had four trajectories labeled as "Increasing Drinkers" (5.3% of sample), "Decreasing Drinkers" (5.9%), "Stable Drinkers" (24.2%), and "Non/Infrequent Drinkers" (64.6%). Using group assignments generated by the trajectory model, one adjusted logistic regression analysis contrasted the groups with low alcohol intake in 1998 (Increasing Drinkers and Non/Infrequent Drinkers). In this model, baseline education, physical activity, cigarette smoking, and binge drinking were significant factors. Another analysis compared the groups with higher intake in 1998 (Decreasing Drinkers versus Stable Drinkers). In this comparison, baseline depression, cigarette smoking, binge drinking, and retirement status were significant. Findings underscore the need to periodically counsel all older women on the risks and benefits of alcohol use.
Keywords: Aged; Alcohol Drinking; Alcoholic Intoxication; Alcoholism; Cohort Studies; depression; Ethanol; Female; Follow-Up Studies; Humans; Longitudinal Studies; Middle Aged; Retirement; Risk Factors; Smoking; Surveys and Questionnaires; United States

The influence of changes in dental care coverage on dental care utilization among retirees and near-retirees in the United States, 2004-2006. - Richard J. Manski; John F Moeller; Patricia A St Clair; Jody Schimmel; Haiyan Chen; John V Pepper (Am J Public Health, 2011)
OBJECTIVES: We examined dental care utilization transition dynamics between 2004 and 2006 in the context of changing dental coverage status. METHODS: We used data from the Health and Retirement Study for persons aged 51 years and older to estimate a multivariable model of dental care use transitions with controls for dental coverage and retirement transitions and other potentially confounding covariates. RESULTS: We found that Americans aged 51 years and older who lost dental coverage between the 2004 and 2006 survey periods were more likely to stop dental care use between periods, and those who gained coverage were more likely to start dental care use between periods, than those without coverage in both periods. CONCLUSIONS: Dental coverage transitions and status have a strong effect on transitions in dental care use. Given that retirement is a time when many experience a loss of dental coverage, older adults may be at risk for sporadic dental care and even stopping use, leading to worse dental and potentially overall health.
Keywords: Age Factors; Aged; Dental Care; Employment; Female; Health Care Surveys; Humans; Insurance, Dental; Male; Medically Uninsured; Middle Aged; Retirement; Socioeconomic factors; United States

Job loss and depression: the role of subjective expectations. - Mandal, Bidisha; Padmaja Ayyagari; William T Gallo (Soc Sci Med, 2011)
Although the importance of expectations is well documented in the decision-making literature, a key shortcoming of the empirical research into effects of involuntary job loss on depression is perhaps its neglect of the subjective expectations of job loss. Using data from the US Health and Retirement Study surveys we examine whether the impact of job loss on mental health is influenced by an individual's subjective expectations regarding future displacement. Our results imply that, among older workers in the age range of 55-65 year, subjective expectations are as significant predictors of depression as job loss itself, and ignoring them can bias the estimate of the impact of job loss on mental health.
Keywords: Adaptation, Psychological; Aged; Bias; depression; Empirical Research; Health Surveys; Humans; Mental Health; Middle Aged; Stress, Psychological; Unemployment; United States

Job strain, depressive symptoms, and drinking behavior among older adults: results from the health and retirement study. - Briana Mezuk; Amy S B Bohnert; Scott M Ratliff; Zivin, Kara (J Gerontol B Psychol Sci Soc Sci, 2011)
OBJECTIVE: To examine the relationship between job strain and two indicators of mental health, depression and alcohol misuse, among currently employed older adults. METHOD: Data come from the 2004 and 2006 waves of the Health and Retirement Study (N = 2,902). Multivariable logistic regression modeling was used to determine the association between job strain, indicated by the imbalance of job stress and job satisfaction, with depression and alcohol misuse. RESULTS: High job strain (indicated by high job stress combined with low job satisfaction) was associated with elevated depressive symptoms (odds ratio [OR] = 2.98, 95% confidence interval [CI]: 1.99-4.45) relative to low job strain after adjusting for sociodemographic characteristics, labor force status, and occupation. High job stress combined with high job satisfaction (OR = 1.93) and low job stress combined with low job satisfaction (OR = 1.94) were also associated with depressive symptoms to a lesser degree. Job strain was unrelated to either moderate or heavy drinking. These associations did not vary by gender or age. DISCUSSION: Job strain is associated with elevated depressive symptoms among older workers. In contrast to results from investigations of younger workers, job strain was unrelated to alcohol misuse. These findings can inform the development and implementation of workplace health promotion programs that reflect the mental health needs of the aging workforce.
Keywords: Age Factors; Aged; Alcoholism; Cohort Studies; Depressive Disorder; Female; Health Behavior; Health Surveys; Humans; Job Satisfaction; Logistic Models; Male; Middle Aged; Multivariate Analysis; Prospective Studies; Retirement; Sex Factors; Statistics as Topic; Stress, Psychological; United States

Lifecourse socioeconomic circumstances and multimorbidity among older adults. - Reginald D. Tucker-Seeley; Li, Yi; Sorensen, Glorian; Subramanian, S V (BMC Public Health, 2011)
BACKGROUND: Many older adults manage multiple chronic conditions (i.e. multimorbidity); and many of these chronic conditions share common risk factors such as low socioeconomic status (SES) in adulthood and low SES across the lifecourse. To better capture socioeconomic condition in childhood, recent research in lifecourse epidemiology has broadened the notion of SES to include the experience of specific hardships. In this study we investigate the association among childhood financial hardship, lifetime earnings, and multimorbidity. METHODS: Cross-sectional analysis of 7,305 participants age 50 and older from the 2004 Health and Retirement Study (HRS) who also gave permission for their HRS records to be linked to their Social Security Records in the United States. Zero-inflated Poisson regression models were used to simultaneously model the likelihood of the absence of morbidity and the expected number of chronic conditions. RESULTS: Childhood financial hardship and lifetime earnings were not associated with the absence of morbidity. However, childhood financial hardship was associated with an 8% higher number of chronic conditions; and, an increase in lifetime earnings, operationalized as average annual earnings during young and middle adulthood, was associated with a 5% lower number of chronic conditions reported. We also found a significant interaction between childhood financial hardship and lifetime earnings on multimorbidity. CONCLUSIONS: This study shows that childhood financial hardship and lifetime earnings are associated with multimorbidity, but not associated with the absence of morbidity. Lifetime earnings modified the association between childhood financial hardship and multimorbidity suggesting that this association is differentially influential depending on earnings across young and middle adulthood. Further research is needed to elucidate lifecourse socioeconomic pathways associated with the absence of morbidity and the presence of multimorbidity among older adults.
Keywords: Aged; Chronic disease; Comorbidity; Cross-Sectional Studies; Female; Humans; Male; Middle Aged; Social Class; United States

Long-term declines in ADLs, IADLs, and mobility among older Medicare beneficiaries. - Frederic D Wolinsky; Suzanne E Bentler; Jason Hockenberry; Michael P Jones; Maksym Obrizan; Paula A Weigel; Kaskie, Brian; Robert B Wallace (BMC Geriatr, 2011)
BACKGROUND: Most prior studies have focused on short-term (≤ 2 years) functional declines. But those studies cannot address aging effects inasmuch as all participants have aged the same amount. Therefore, the authors studied the extent of long-term functional decline in older Medicare beneficiaries who were followed for varying time lengths, and the authors also identified the risk factors associated with those declines. METHODS: The analytic sample included 5,871 self- or proxy-respondents who had complete baseline and follow-up survey data that could be linked to their Medicare claims for 1993-2007. Functional status was assessed using activities of daily living (ADLs), instrumental ADLs (IADLs), and mobility limitations, with declines defined as the development of two of more new difficulties. Multiple logistic regression analysis was used to focus on the associations involving respondent status, health lifestyle, continuity of care, managed care status, health shocks, and terminal drop. RESULTS: The average amount of time between the first and final interviews was 8.0 years. Declines were observed for 36.6% on ADL abilities, 32.3% on IADL abilities, and 30.9% on mobility abilities. Functional decline was more likely to occur when proxy-reports were used, and the effects of baseline function on decline were reduced when proxy-reports were used. Engaging in vigorous physical activity consistently and substantially protected against functional decline, whereas obesity, cigarette smoking, and alcohol consumption were only associated with mobility declines. Post-baseline hospitalizations were the most robust predictors of functional decline, exhibiting a dose-response effect such that the greater the average annual number of hospital episodes, the greater the likelihood of functional status decline. Participants whose final interview preceded their death by one year or less had substantially greater odds of functional status decline. CONCLUSIONS: Both the additive and interactive (with functional status) effects of respondent status should be taken into consideration whenever proxy-reports are used. Encouraging exercise could broadly reduce the risk of functional decline across all three outcomes, although interventions encouraging weight reduction and smoking cessation would only affect mobility declines. Reducing hospitalization and re-hospitalization rates could also broadly reduce the risk of functional decline across all three outcomes.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Cohort Studies; Disabled Persons; Female; Follow-Up Studies; Geriatric Assessment; Health Surveys; Humans; Insurance Benefits; Longitudinal Studies; Male; Medicare; Mobility Limitation; Prospective Studies; Time Factors; United States

Memory predicts changes in depressive symptoms in older adults: a bidirectional longitudinal analysis. - Jajodia, Archana; Borders, Ashley (J Gerontol B Psychol Sci Soc Sci, 2011)
OBJECTIVES: Although research indicates that depressive symptoms and memory performance are related in older adults, the temporal associations between these variables remain unclear. This study examined whether depressive symptoms predicted later memory change and whether memory predicted later change in depressive symptoms. METHODS: The sample consisted of more than 14,000 adults from the Health and Retirement Study, a biannual longitudinal study of health and retirement in Americans older than age 50 years. Measures of delayed recall and depressive symptoms served as the main study variables. We included age, sex, education, and history of vascular diseases as covariates. RESULTS: Using dynamic change models with latent difference scores, we found that memory performance predicted change in depressive symptoms 2 years later. Depressive symptoms did not predict later change in memory. The inclusion of vascular health variables diminished the size of the observed relationship, suggesting that biological processes may partially explain the effect of memory on depressive symptoms. IMPLICATIONS: Future research should explore both biological and psychological processes that may explain the association between worse memory performance and subsequent increases in depressive symptoms.
Keywords: Aged; Aged, 80 and over; Comorbidity; Dementia, Vascular; depression; Female; Geriatric Assessment; Humans; Longitudinal Studies; Male; Mental Recall; Middle Aged; Models, Psychological; Retirement; Statistics as Topic; United States

Mortgage delinquency and changes in access to health resources and depressive symptoms in a nationally representative cohort of Americans older than 50 years. - Dawn E Alley; Jennifer Lloyd; José A Pagán; Craig E Pollack; Michelle Shardell; Carolyn Cannuscio (Am J Public Health, 2011)
OBJECTIVES: We evaluated associations between mortgage delinquency and changes in health and health-relevant resources over 2 years, with data from the Health and Retirement Study, a longitudinal survey representative of US adults older than 50 years. METHODS: In 2008, participants reported whether they had fallen behind on mortgage payments since 2006 (n = 2474). We used logistic regression to compare changes in health (incidence of elevated depressive symptoms, major declines in self-rated health) and access to health-relevant resources (food, prescription medications) between participants who fell behind on their mortgage payments and those who did not. RESULTS: Compared with nondelinquent participants, the mortgage-delinquent group had worse health status and less access to health-relevant resources at baseline. They were also significantly more likely to develop incident depressive symptoms (odds ratio [OR] = 8.60; 95% confidence interval [CI] = 3.38, 21.85), food insecurity (OR = 7.53; 95% CI = 3.01, 18.84), and cost-related medication nonadherence (OR = 8.66; 95% CI = 3.72, 20.16) during follow-up. CONCLUSIONS: Mortgage delinquency was associated with significant elevations in the incidence of mental health impairments and health-relevant material disadvantage. Widespread mortgage default may have important public health implications.
Keywords: depression; Drug Costs; Economic Recession; Female; Health Services Accessibility; Health Status; Housing; Humans; Male; Medication Adherence; Middle Aged; Socioeconomic factors; Stress, Psychological; United States

Multiple trajectories of depressive symptoms in middle and late life: racial/ethnic variations. - Jersey Liang; Xiao Xu; Ana R Quiñones; Joan M. Bennett; Wen Ye (Psychol Aging, 2011)
This research aims to identify distinct courses of depressive symptoms among middle-aged and older Americans and to ascertain how these courses vary by race/ethnicity. Data came from the 1995-2006 Health and Retirement Study which involved a national sample of 17,196 Americans over 50 years of age with up to six repeated observations. Depressive symptoms were measured by an abbreviated version of the Center for Epidemiologic Studies Depression scale. Semiparametric group based mixture models (Proc Traj) were used for data analysis. Six major trajectories were identified: (a) minimal depressive symptoms (15.9%), (b) low depressive symptoms (36.3%), (c) moderate and stable depressive symptoms (29.2%), (d) high but decreasing depressive symptoms (6.6%), (e) moderate but increasing depressive symptoms (8.3%), and (f) persistently high depressive symptoms (3.6%). Adjustment of time-varying covariates (e.g., income and health conditions) resulted in a similar set of distinct trajectories. Relative to White Americans, Black and Hispanic Americans were significantly more likely to be in trajectories of more elevated depressive symptoms. In addition, they were more likely to experience increasing and decreasing depressive symptoms. Racial and ethnic variations in trajectory groups were partially mediated by SES, marital status, and health conditions, particularly when both interpersonal and intrapersonal differences in these variables were taken into account.
Keywords: Age Factors; Aged; Black or African American; depression; disease progression; Female; Health Status Disparities; Hispanic or Latino; Humans; Longitudinal Studies; Male; Middle Aged; Models, Statistical; Socioeconomic factors; Time Factors; United States; White People

National estimates of the prevalence of Alzheimer's disease in the United States. - Brookmeyer, Ron; Denis A Evans; Liesi Hebert; Kenneth M. Langa; Steven G Heeringa; Brenda L Plassman; Walter Kukull (Alzheimers Dement, 2011)
Several methods of estimating prevalence of dementia are presented in this article. For both Brookmeyer and the Chicago Health and Aging project (CHAP), the estimates of prevalence are derived statistically, forward calculating from incidence and survival figures. The choice of incidence rates on which to build the estimates may be critical. Brookmeyer used incidence rates from several published studies, whereas the CHAP investigators applied the incidence rates observed in their own cohort. The Aging, Demographics, and Memory Study (ADAMS) and the East Boston Senior Health Project (EBSHP) were sample surveys designed to ascertain the prevalence of Alzheimer's disease and dementia. ADAMS obtained direct estimates by relying on probability sampling nationwide. EBSHP relied on projection of localized prevalence estimates to the national population. The sampling techniques of ADAMS and EBSHP were rather similar, whereas their disease definitions were not. By contrast, EBSPH and CHAP have similar disease definitions internally, but use different calculation techniques, and yet arrive at similar prevalence estimates, which are considerably greater than those obtained by either Brookmeyer or ADAMS. Choice of disease definition may play the larger role in explaining differences in observed prevalence between these studies.
Keywords: Age Factors; Alzheimer disease; Community Health Planning; Data collection; Humans; Incidence; Models, Statistical; Prevalence; Sampling Studies; United States

Neighborhoods and chronic disease onset in later life. - Vicki A Freedman; Irina B Grafova; Jeannette Rogowski (Am J Public Health, 2011)
OBJECTIVES: To strengthen existing evidence on the role of neighborhoods in chronic disease onset in later life, we investigated associations between multiple neighborhood features and 2-year onset of 6 common conditions using a national sample of older adults. METHODS: Neighborhood features for adults aged 55 years or older in the 2002 Health and Retirement Study were measured by use of previously validated scales reflecting the built, social, and economic environment. Two-level random-intercept logistic models predicting the onset of heart problems, hypertension, stroke, diabetes, cancer, and arthritis by 2004 were estimated. RESULTS: In adjusted models, living in more economically disadvantaged areas predicted the onset of heart problems for women (odds ratio [OR] = 1.20; P < .05). Living in more highly segregated, higher-crime areas was associated with greater chances of developing cancer for men (OR = 1.31; P < .05) and women (OR = 1.25; P < .05). CONCLUSIONS: The neighborhood economic environment is associated with heart disease onset for women, and neighborhood-level social stressors are associated with cancer onset for men and women. The social and biological mechanisms that underlie these associations require further investigation.
Keywords: Aged; Chronic disease; Environment Design; Factor Analysis, Statistical; Female; Health Resources; Health Status Disparities; Humans; Logistic Models; Male; Middle Aged; Poverty Areas; Residence Characteristics; Risk Factors; Small-Area Analysis; Social Environment; Social Problems; Socioeconomic factors; United States

Operationalizing diagnostic criteria for Alzheimer's disease and other age-related cognitive impairment-Part 2. - Seshadri, Sudha; Alexa S. Beiser; Au, Rhoda; Philip A Wolf; Robert S Wilson; Ronald C Petersen; David S Knopman; Walter A Rocca; Claudia H Kawas; Maria M Corrada; Brenda L Plassman; Kenneth M. Langa; et al. (Alzheimers Dement, 2011)
This article focuses on the effects of operational differences in case ascertainment on estimates of prevalence and incidence of cognitive impairment and/or dementia of the Alzheimer type. Experience and insights are discussed by investigators from the Framingham Heart Study, the East Boston Senior Health Project, the Chicago Health and Aging Project, the Mayo Clinic Study of Aging, the Baltimore Longitudinal Study of Aging, and the Aging, Demographics, and Memory Study. There is a general consensus that the single most important factor determining prevalence estimates of Alzheimer's disease (AD) is the severity of cognitive impairment used as a threshold to define cases. Studies that require a level of cognitive impairment in which persons are unable to provide self-care will have much lower estimates than the studies aimed at identifying persons in the earliest stages of AD. There are limited autopsy data from the aforementioned epidemiological studies to address accuracy in the diagnosis of etiological subtype, namely the specification of AD alone or in combination with other types of pathology. However, other community-based cohort studies show that many persons with mild cognitive impairment and also some persons without dementia or mild cognitive impairment meet pathological criteria for AD, thereby suggesting that the number of persons who would benefit from an effective secondary prevention intervention is probably higher than the published prevalence estimates. Improved accuracy in the clinical diagnosis of AD is anticipated with the addition of molecular and structural biomarkers in the next generation of epidemiological studies.
Keywords: Age Factors; Aging; Alzheimer disease; Cognition Disorders; Community Health Planning; Humans; Incidence; Longitudinal Studies; Neuropsychological tests; Prevalence; United States

Physical disability trajectories in older Americans with and without diabetes: the role of age, gender, race or ethnicity, and education. - Chiu, Ching-Ju; Linda A. Wray (Gerontologist, 2011)
PURPOSE: This research combined cross-sectional and longitudinal data to characterize age-related trajectories in physical disability for adults with and without diabetes in the United States and to investigate if those patterns differ by age, gender, race or ethnicity, and education. DESIGN AND METHODS: Data were examined on 20,433 adults aged 51 and older from the 1998 to 2006 Health and Retirement Study. Multilevel models and a cohort-sequential design were applied to quantitatively depict the age norm of physical disability after age 50. RESULTS: Adults with diabetes not only experience greater levels of physical disability but also faster rates of deterioration over time. This pattern is net of attrition, time-invariant sociodemographic factors, and time-varying chronic disease conditions. Differences in physical disability between adults with and without diabetes were more pronounced in women, non-White, and those of lower education. The moderating effects of gender and education remained robust even after controlling for selected covariates in the model. IMPLICATIONS: This study highlighted the consistently greater development of disability over time in adults with diabetes and particularly in those who are women, non-White, or adults of lower education. Future studies are recommended to examine the mechanisms underlying the differential effects of diabetes on physical disability by gender and education.
Keywords: Activities of Daily Living; Age Distribution; Aged; Aged, 80 and over; Cross-Sectional Studies; Diabetes Mellitus; Disabled Persons; Educational Status; ethnicity; Female; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Models, Theoretical; Racial Groups; Sex Distribution; Time Factors; United States

A prospective cohort study of long-term cognitive changes in older Medicare beneficiaries. - Frederic D Wolinsky; Suzanne E Bentler; Jason Hockenberry; Michael P Jones; Paula A Weigel; Kaskie, Brian; Robert B Wallace (BMC Public Health, 2011)
BACKGROUND: Promoting cognitive health and preventing its decline are longstanding public health goals, but long-term changes in cognitive function are not well-documented. Therefore, we first examined long-term changes in cognitive function among older Medicare beneficiaries in the Survey on Assets and Health Dynamics among the Oldest Old (AHEAD), and then we identified the risk factors associated with those changes in cognitive function. METHODS: We conducted a secondary analysis of a prospective, population-based cohort using baseline (1993-1994) interview data linked to 1993-2007 Medicare claims to examine cognitive function at the final follow-up interview which occurred between 1995-1996 and 2006-2007. Besides traditional risk factors (i.e., aging, age, race, and education) and adjustment for baseline cognitive function, we considered the reason for censoring (entrance into managed care or death), and post-baseline continuity of care and major health shocks (hospital episodes). Residual change score multiple linear regression analysis was used to predict cognitive function at the final follow-up using data from telephone interviews among 3,021 to 4,251 (sample size varied by cognitive outcome) baseline community-dwelling self-respondents that were ≥ 70 years old, not in managed Medicare, and had at least one follow-up interview as self-respondents. Cognitive function was assessed using the 7-item Telephone Interview for Cognitive Status (TICS-7; general mental status), and the 10-item immediate and delayed (episodic memory) word recall tests. RESULTS: Mean changes in the number of correct responses on the TICS-7, and 10-item immediate and delayed word recall tests were -0.33, -0.75, and -0.78, with 43.6%, 54.9%, and 52.3% declining and 25.4%, 20.8%, and 22.9% unchanged. The main and most consistent risks for declining cognitive function were the baseline values of cognitive function (reflecting substantial regression to the mean), aging (a strong linear pattern of increased decline associated with greater aging, but with diminishing marginal returns), older age at baseline, dying before the end of the study period, lower education, and minority status. CONCLUSIONS: In addition to aging, age, minority status, and low education, substantial and differential risks for cognitive change were associated with sooner vs. later subsequent death that help to clarify the terminal drop hypothesis. No readily modifiable protective factors were identified.
Keywords: Aged; Aged, 80 and over; Aging; Cognition; Cognition Disorders; Cohort Studies; Female; Humans; Interviews as Topic; Male; Medicare; Mental Health; Outcome Assessment, Health Care; Prospective Studies; Regression Analysis; Risk Factors; United States

Recent trends in chronic disease, impairment and disability among older adults in the United States. - William W. Hung; Joseph S. Ross; Boockvar, Kenneth S; Albert L Siu (BMC Geriatr, 2011)
BACKGROUND: To examine concurrent prevalence trends of chronic disease, impairment and disability among older adults. METHODS: We analyzed the 1998, 2004 and 2008 waves of the Health and Retirement Study, a nationally representative survey of older adults in the United States, and included 31,568 community dwelling adults aged 65 and over. Measurements include: prevalence of chronic diseases including hypertension, heart disease, stroke, diabetes, cancer, chronic lung disease and arthritis; prevalence of impairments, including impairments of cognition, vision, hearing, mobility, and urinary incontinence; prevalence of disability, including activities of daily living (ADLs) and instrumental activities of daily living (IADLs). RESULTS: The proportion of older adults reporting no chronic disease decreased from 13.1% (95% Confidence Interval [CI], 12.4%-13.8%) in 1998 to 7.8% (95% CI, 7.2%-8.4%) in 2008, whereas the proportion reporting 1 or more chronic diseases increased from 86.9% (95% CI, 86.2%-89.6%) in 1998 to 92.2% (95% CI, 91.6%-92.8%) in 2008. In addition, the proportion reporting 4 or more diseases increased from 11.7% (95% CI, 11.0%-12.4%) in 1998 to 17.4% (95% CI, 16.6%-18.2%) in 2008. The proportion of older adults reporting no impairments was 47.3% (95% CI, 46.3%-48.4%) in 1998 and 44.4% (95% CI, 43.3%-45.5%) in 2008, whereas the proportion of respondents reporting 3 or more was 7.2% (95% CI, 6.7%-7.7%) in 1998 and 7.3% (95% CI, 6.8%-7.9%) in 2008. The proportion of older adults reporting any ADL or IADL disability was 26.3% (95% CI, 25.4%-27.2%) in 1998 and 25.4% (95% CI, 24.5%-26.3%) in 2008. CONCLUSIONS: Multiple chronic disease is increasingly prevalent among older U.S. adults, whereas the prevalence of impairment and disability, while substantial, remain stable.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic disease; Disabled Persons; Female; Health Surveys; Humans; Longitudinal Studies; Male; United States; Visually Impaired Persons

Recruitment and retention of minority participants in the health and retirement study. - Mary Beth Ofstedal; David R Weir (Gerontologist, 2011)
PURPOSE: Minority oversamples of African Americans and Hispanics have been a key feature of the Health and Retirement Study (HRS) design from its origins in 1992. The objective of this article was to assess the quality of the HRS with respect to the recruitment and retention of minority respondents. DESIGN AND METHODS: To evaluate minority recruitment efforts, we examine baseline response rates for the early baby boom cohort that was added in the 2004 wave and the representativeness of this cohort with regard to demographic, socioeconomic, and health characteristics. To evaluate retention, we focus on minority differentials in 2008 interview, nonresponse and mortality outcomes for the full HRS sample. We also examine minority differentials in participation in supplemental components of the HRS. RESULTS: Minority response rates at baseline and in longitudinal follow-ups for the main HRS interview have been equal to or better than that of majority Whites. Conversely, response rates to some specific supplemental components have been lower for minority sample members. IMPLICATIONS: The oversample strategies that the HRS has employed have been successful at identifying and recruiting minority participants at response rates very comparable with that of Whites and others. Minority differentials in participation in supplemental components have been overcome to some extent through interviewer training and targeted follow-up strategies. The HRS experience suggests that well-trained interviewers can overcome most if not all of whatever race and ethnic differentials exist in willingness to participate in surveys, including those involving biological data collection.
Keywords: Aged; Biomarkers; Black or African American; Female; Health Promotion; Health Surveys; Hispanic or Latino; Humans; Male; Middle Aged; Minority Groups; Minority health; National Health Programs; Patient Dropouts; Patient Selection; Retirement; Sampling Studies; Surveys and Questionnaires; United States

Reducing case ascertainment costs in U.S. population studies of Alzheimer's disease, dementia, and cognitive impairment-Part 1. - David R Weir; Robert B Wallace; Kenneth M. Langa; Brenda L Plassman; Robert S Wilson; David A Bennett; Duara, Ranjan; Loewenstein, David; Ganguli, Mary; Sano, Mary (Alzheimers Dement, 2011)
Establishing methods for ascertainment of dementia and cognitive impairment that are accurate and also cost-effective is a challenging enterprise. Large population-based studies often using administrative data sets offer relatively inexpensive and reliable estimates of severe conditions including moderate to advanced dementia that are useful for public health planning, but they can miss less severe cognitive impairment which may be the most effective point for intervention. Clinical and epidemiological cohorts, intensively assessed, provide more sensitive detection of less severe cognitive impairment but are often costly. In this article, several approaches to ascertainment are evaluated for validity, reliability, and cost. In particular, the methods of ascertainment from the Health and Retirement Study are described briefly, along with those of the Aging, Demographics, and Memory Study (ADAMS). ADAMS, a resource-intense sub-study of the Health and Retirement Study, was designed to provide diagnostic accuracy among persons with more advanced dementia. A proposal to streamline future ADAMS assessments is offered. Also considered are algorithmic and Web-based approaches to diagnosis that can reduce the expense of clinical expertise and, in some contexts, can reduce the extent of data collection. These approaches are intended for intensively assessed epidemiological cohorts where goal is valid and reliable case detection with efficient and cost-effective tools.
Keywords: Aging; Algorithms; Alzheimer disease; Cognition Disorders; Community Health Planning; Cost-Benefit Analysis; Dementia; Health Surveys; Humans; Internet; Reproducibility of Results; United States

Regional variation in the association between advance directives and end-of-life Medicare expenditures. - Lauren Hersch Nicholas; Kenneth M. Langa; Theodore J Iwashyna; David R Weir (JAMA, 2011)
CONTEXT: It is unclear if advance directives (living wills) are associated with end-of-life expenditures and treatments. OBJECTIVE: To examine regional variation in the associations between treatment-limiting advance directive use, end-of-life Medicare expenditures, and use of palliative and intensive treatments. DESIGN, SETTING, AND PATIENTS: Prospectively collected survey data from the Health and Retirement Study for 3302 Medicare beneficiaries who died between 1998 and 2007 linked to Medicare claims and the National Death Index. Multivariable regression models examined associations between advance directives, end-of-life Medicare expenditures, and treatments by level of Medicare spending in the decedent's hospital referral region. MAIN OUTCOME MEASURES: Medicare expenditures, life-sustaining treatments, hospice care, and in-hospital death over the last 6 months of life. RESULTS: Advance directives specifying limits in care were associated with lower spending in hospital referral regions with high average levels of end-of-life expenditures (-$5585 per decedent; 95% CI, -$10,903 to -$267), but there was no difference in spending in hospital referral regions with low or medium levels of end-of-life expenditures. Directives were associated with lower adjusted probabilities of in-hospital death in high- and medium-spending regions (-9.8%; 95% CI, -16% to -3% in high-spending regions; -5.3%; 95% CI, -10% to -0.4% in medium-spending regions). Advance directives were associated with higher adjusted probabilities of hospice use in high- and medium-spending regions (17%; 95% CI, 11% to 23% in high-spending regions, 11%; 95% CI, 6% to 16% in medium-spending regions), but not in low-spending regions. CONCLUSION: Advance directives specifying limitations in end-of-life care were associated with significantly lower levels of Medicare spending, lower likelihood of in-hospital death, and higher use of hospice care in regions characterized by higher levels of end-of-life spending.
Keywords: Advance directives; Aged; Aged, 80 and over; Data collection; Female; Health Expenditures; Hospice Care; Hospital Mortality; Hospitals; Humans; Kidney Failure, Chronic; Male; Medicare; Palliative care; Prospective Studies; Regression Analysis; Terminal Care; United States

The relationships between major lifetime discrimination, everyday discrimination, and mental health in three racial and ethnic groups of older adults. - Liat Ayalon; Amber M Gum (Aging Ment Health, 2011)
OBJECTIVES: To evaluate the relationships between perceived exposure to major lifetime discrimination, everyday discrimination, and mental health in three racial/ethnic groups of older adults. DESIGN: The Health and Retirement Study is a nationally representative sample of individuals 50 years and older living in the United States. A total of 6455 Whites, 716 Latinos, and 1214 Blacks were eligible to complete a self-report psychosocial questionnaire in the year 2006. RESULTS: Whereas 30% of the general population reported at least one type of major lifetime discrimination, almost 45% of Black older adults reported such discrimination. Relative to the other two racial/ethnic groups (82% Whites, 82.6% Blacks), Latinos were significantly less likely to report any everyday discrimination (64.2%), whereas Blacks reported the greatest frequency of everyday discrimination. Whites reported the highest levels of life satisfaction and the lowest levels of depressive symptoms. Relative to major lifetime discrimination, everyday discrimination had a somewhat stronger correlation with mental health indicators. The relationships between discrimination and mental health outcomes were stronger for White compared to Black older adults, although everyday discrimination was still significantly associated with outcomes for Black older adults. CONCLUSIONS: Black older adults experience the greatest number of discriminative events, but weaker associated mental health outcomes. This could be because they have become accustomed to these experiences, benefit from social or cultural resources that serve as buffers, or selective survival, with the present sample capturing only the most resilient older adults who have learned to cope with the deleterious effects of discrimination.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Asian; Black or African American; Cross-Cultural Comparison; depression; Discrimination, Psychological; ethnicity; Hispanic or Latino; Humans; Longitudinal Studies; Mental Health; Middle Aged; Personal Satisfaction; Prejudice; Prevalence; Social Perception; Socioeconomic factors; Surveys and Questionnaires; United States; White People

Social characteristics and health status of exceptionally long-lived Americans in the Health and Retirement Study. - Jennifer A Ailshire; Hiram Beltrán-Sánchez; Eileen M. Crimmins (J Am Geriatr Soc, 2011)
OBJECTIVES: To characterize the social characteristics and physical, functional, mental, and cognitive health of exceptional survivors in the United States and how the experience of exceptional longevity differs according to social status. DESIGN: Nationally representative longitudinal study of older Americans. SETTING: United States. PARTICIPANTS: One thousand six hundred forty-nine men and women born from 1900 to 1911 from the Health and Retirement Study: 1,424 nonsurvivors who died before reaching the age of 97 and 225 exceptional survivors who survived to age 97 and older. MEASUREMENTS: Self-reported data on sociodemographic characteristics, social environment, physical and mental health, and physical and cognitive function. RESULTS: At baseline, exceptional survivors were more likely to live independently and had fewer diseases, better mental health, and better physical and cognitive function than those who did not survive to age 97. Exceptional survivors experienced declines from baseline in all health domains upon reaching 97 years of age, but between one-fifth and one-third of exceptional survivors remained disease free, with no functional limitations or depressive symptoms, and one-fifth retained high cognitive function. Of exceptional survivors, men were healthier than women, and whites were generally healthier than nonwhites. Highly educated exceptional survivors had better cognitive function than their less-educated counterparts. CONCLUSION: On average, exceptional survivors are relatively healthy and high functioning for most of their lives and experience health declines only upon reaching maximum longevity. Heterogeneity in the population of exceptionally old adults indicates that, although many individuals reach maximum longevity in a state of poor health and functioning, a considerable portion of exceptional survivors remain healthy and high-functioning even in very old age.
Keywords: Age Factors; Aged, 80 and over; Female; Geriatric Assessment; Health Status; Humans; Longevity; Longitudinal Studies; Male; Social Class; Sociology; United States

Social stratification of body weight trajectory in middle-age and older americans: results from a 14-year longitudinal study. - Anda Botoseneanu; Jersey Liang (J Aging Health, 2011)
OBJECTIVE: To depict the trajectory of BMI from middle to late adulthood and to examine social variations in BMI trajectories. METHOD: Eight waves (1992-2006) of the Health and Retirement Study involving a nationally representative sample of Americans aged 51 to 61 years at baseline were used. Changes in BMI were analyzed using hierarchical linear modeling with time-constant and time-varying covariates. RESULTS: BMI increased linearly over time. Compared with Caucasians, African-Americans had higher BMI levels, while Hispanics had similar BMI levels, but lower rates of increase over time. Higher education predicted lower BMI levels and was not associated with the rate of change. Younger age-at-baseline predicted lower BMI level and lower rate of increase. No gender differences were found. DISCUSSION: Observed racial/ethnic and educational differences in BMI trajectory from middle to old age inform policies and interventions aimed at modifying health risks and reducing health disparities in old age.
Keywords: Age Factors; Aged; Aging; Body Mass Index; ethnicity; Female; Health Status Disparities; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; Multivariate Analysis; Obesity; Psychometrics; Risk Assessment; Self Report; Social Class; Socioeconomic factors; Time Factors; United States

Socioeconomic inequalities in old-age mortality: a comparison of Denmark and the USA. - Rasmus Hoffmann (Soc Sci Med, 2011)
Previous studies have reported important variations in the magnitude of health inequalities between countries that belong to different welfare systems. This suggests that there is scope for reducing health inequalities by means of country-level interventions. The present study adds to this literature by exploring whether the magnitude of socioeconomic inequalities in mortality is associated with social inequality levels. Denmark and the USA belong to fundamentally different welfare systems (social democratic and liberal) and our study thereby contributes to the ongoing debate on whether welfare systems are linked to health inequalities. We analyze Denmark and the USA in terms of socioeconomic differences in mortality above age 58. The data sources were Danish register data from 1980 to 2002 (n = 2,029,324), and survey data from the US Health and Retirement Study (HRS) from 1992 to 2006 (n = 9374). Survival analysis was used to study the impact of socioeconomic status on mortality and the magnitude of mortality differences between the two countries was compared. The results showed surprisingly that mortality differentials were larger in Denmark than in the USA even after controlling for a number of covariates: The poorest 10 percent of the Danish elderly population have a mortality rate ratio of 3.32 (men) and 3.70 (women) compared to the richest 25 percent. In the USA the corresponding rate ratios are 1.67 and 1.56. Low income seems to be a more powerful risk factor for mortality than low education. A number of possible explanations for higher mortality differences in Denmark are discussed: unintended positive correlation between generous health services and health inequality, early life influences, mortality selection, and relative deprivation.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Cross-Cultural Comparison; Denmark; Educational Status; Female; Health Expenditures; Humans; Income; Life Expectancy; Male; Middle Aged; Mortality; Political Systems; Social Class; Social Welfare; United States

Socioeconomic status and race/ethnicity independently predict health decline among older diabetics. - Emily J Nicklett (BMC Public Health, 2011)
BACKGROUND: There are pervasive racial and socioeconomic differences in health status among older adults with type 2 diabetes. The extent to which racial/ethnic and socioeconomic disparities unfold to differential health outcomes has yet to be investigated among older adults with diabetes. This study examines whether or not race/ethnicity and SES are independent predictors of steeper rates of decline in self-rated health among older adults in the U.S. with type 2 diabetes. METHODS: The study population was a subset of diabetic adults aged 65 and older from the Health and Retirement Study. Respondents were followed up to 16 years. Multilevel cumulative logit regression models were used to examine the contributions of socioeconomic indicators, race/ethnicity, and covariates over time. Health decline was measured as a change in self-reported health status over the follow-up period. RESULTS: Relative to whites, blacks had a significantly lower cumulative odds of better health status over time (OR: 0.61, p < .0001). Hispanics reported significantly lower cumulative odds better health over time relative to whites (OR: 0.59, p < .05). Although these disparities narrowed when socioeconomic characteristics were added to the model, significant differences remained. Including socioeconomic status did not remove the health effects of race/ethnicity among blacks and Hispanics. CONCLUSIONS: The author found that race/ethnicity and some socioeconomic indicators were independent predictors of health decline among older adults with diabetes.
Keywords: Aged; Aged, 80 and over; Black People; Diabetes Mellitus, Type 2; Diagnostic Self Evaluation; Female; Follow-Up Studies; Health Status Disparities; Hispanic or Latino; Humans; Male; Social Class; United States; White People

Sources of variability in estimates of the prevalence of Alzheimer's disease in the United States. - Robert S Wilson; David R Weir; Sue E Leurgans; Denis A Evans; Liesi Hebert; Kenneth M. Langa; Brenda L Plassman; Brent J. Small; David A Bennett (Alzheimers Dement, 2011)
BACKGROUND: The prevalence of Alzheimer's disease (AD) in the United States was estimated at 2.3 million in 2002 by the Aging, Demographics, and Memory Study (ADAMS), which is almost 50% less than the estimate of 4.5 million in 2000 derived from the Chicago Health and Aging Project. METHODS: We considered how differences in diagnostic criteria may have contributed to these differences in AD prevalence. RESULTS: We identified several important differences in diagnostic criteria that may have contributed to the differing estimates of AD prevalence. Two factors were especially noteworthy. First, the Diagnostic and Statistical Manual of Mental Disorders III-R and IV criteria of functional limitation documented by an informant used in ADAMS effectively concentrated the diagnosis of dementia toward a relatively higher level of cognitive impairment. ADAMS separately identified a category of cognitive impairment not dementia and within that group there were a substantial number of cases with "prodromal" AD (a maximum of 1.95 million with upweighting). Second, a substantial proportion of dementia in ADAMS was attributed to either vascular disease (representing a maximum of 0.59 million with upweighting) or undetermined etiology (a maximum of 0.34 million), whereas most dementia, including mixed dementia, was attributed to AD in the Chicago Health and Aging Project. CONCLUSION: The diagnosis of AD in population studies is a complex process. When a diagnosis of AD excludes persons meeting criteria for vascular dementia, when not all persons with dementia are assigned an etiology, and when a diagnosis of dementia requires an informant report of functional limitations, the prevalence is substantially lower and the diagnosed cases most likely have a relatively higher level of impairment.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Community Health Planning; Comorbidity; Dementia; Diagnosis, Differential; Female; Humans; Incidence; Male; Prevalence; United States

Spousal associations between functional limitation and depressive symptom trajectories: Longitudinal findings from the study of Asset and Health Dynamics Among the Oldest Old (AHEAD). - Christiane A Hoppmann; Denis Gerstorf; Anita Hibbert (Health Psychol, 2011)
OBJECTIVE: To examine spousal associations between functional limitation and depressive symptom trajectories in a national sample of older long-term married couples. DESIGN: We used 14.5-year longitudinal data on functional limitations and depressive symptoms from 1,704 couples participating in the Study of Asset and Health Dynamics Among the Oldest Old (AHEAD). MAIN OUTCOME MEASURES: Activities of daily living and a short version of the Center for Epidemiologic Studies Depression scale were used. RESULTS: Between-person difference findings corroborate previous research by showing that levels and changes in functional limitations and depressive symptoms are closely interrelated among wives and husbands. Our results further demonstrate sizable associations in levels and changes in functional limitations and depressive symptoms between spouses. For example, functional limitation levels in one spouse were associated with depressive symptom levels in the other spouse. Spousal associations remained after controlling for individual (age, education, cognition) and spousal covariates (marriage duration, number of children) and did not differ between women and men. CONCLUSION: Our findings highlight the important role of marital relationships in shaping health trajectories in old age because they show that some of the well-documented between-person differences in functional limitations and depressive symptoms are in fact related to spouses.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; depression; Female; Humans; Longitudinal Studies; Male; Psychometrics; Spouses; United States

Subsidized housing not subsidized health: health status and fatigue among elders in public housing and other community settings. - Parsons, Pamela L; Briana Mezuk; Scott M Ratliff; Kate L Lapane (Ethn Dis, 2011)
OBJECTIVES: To estimate trends in the prevalence of fatigue among elders living in public housing or in the community; to compare health status of elders living in public housing to their community-dwelling counterparts. DESIGN: Cross-sectional study. SETTING: Community-dwelling elders who reported ever residing in public housing were compared to those living in other community settings. PARTICIPANTS: Participants of the Health and Retirement Study (seven waves of interviews conducted from 1995 through 2006) interviewed in 2006 with complete data on housing status, self-report measures of health status and measures of functioning (n = 16,191). MEASUREMENTS: Self-reported fatigue, functioning, and other health conditions. We also evaluated four functional indices: overall mobility, large muscle functioning, gross motor functioning, and fine motor functioning. RESULTS: Those reporting having lived in public housing were twice as likely to rate their health as fair or poor relative to those with no public housing experience (57.3% vs 26.9%, respectively). Cardiac conditions, stroke, hypertension, diabetes, arthritis and psychiatric problems were all more prevalent in those living in public housing relative to community-dwelling elders not living in public housing. Fatigue was more prevalent in persons residing in public housing (26.7%) as compared to other community-dwelling elders (17.8%). CONCLUSION: The health status of persons residing in public housing is poor. Fatigue and comorbid conditions are highly prevalent and more common in those living in public housing. Developing care models that meet the needs of this oft-neglected population is warranted.
Keywords: Aged; Chronic disease; Comorbidity; Cross-Sectional Studies; Fatigue; Female; Health Status Disparities; Humans; Male; Poverty; Prevalence; Public Housing; United States

Trends in the incidence and prevalence of Alzheimer's disease, dementia, and cognitive impairment in the United States. - Walter A Rocca; Ronald C Petersen; David S Knopman; Liesi Hebert; Denis A Evans; Kathleen S Hall; Gao, Sujuan; Frederick W Unverzagt; Kenneth M. Langa; Eric B Larson; Lon R White (Alzheimers Dement, 2011)
Declines in heart disease and stroke mortality rates are conventionally attributed to reductions in cigarette smoking, recognition and treatment of hypertension and diabetes, effective medications to improve serum lipid levels and to reduce clot formation, and general lifestyle improvements. Recent evidence implicates these and other cerebrovascular factors in the development of a substantial proportion of dementia cases. Analyses were undertaken to determine whether corresponding declines in age-specific prevalence and incidence rates for dementia and cognitive impairment have occurred in recent years. Data spanning 1 or 2 decades were examined from community-based epidemiological studies in Minnesota, Illinois, and Indiana, and from the Health and Retirement Study, which is a national survey. Although some decline was observed in the Minnesota cohort, no statistically significant trends were apparent in the community studies. A significant reduction in cognitive impairment measured by neuropsychological testing was identified in the national survey. Cautious optimism appears justified.
Keywords: Age Factors; Alzheimer disease; Cognition Disorders; Cohort Studies; Community Health Planning; Dementia; Humans; Incidence; Prevalence; Residence Characteristics; Retrospective Studies; Time Factors; United States

Understanding how race/ethnicity and gender define age-trajectories of disability: an intersectionality approach. - David F Warner; Tyson H Brown (Soc Sci Med, 2011)
A number of studies have demonstrated wide disparities in health among racial/ethnic groups and by gender, yet few have examined how race/ethnicity and gender intersect or combine to affect the health of older adults. The tendency of prior research to treat race/ethnicity and gender separately has potentially obscured important differences in how health is produced and maintained, undermining efforts to eliminate health disparities. The current study extends previous research by taking an intersectionality approach (Mullings & Schulz, 2006), grounded in life course theory, conceptualizing and modeling trajectories of functional limitations as dynamic life course processes that are jointly and simultaneously defined by race/ethnicity and gender. Data from the nationally representative 1994-2006 US Health and Retirement Study and growth curve models are utilized to examine racial/ethnic/gender differences in intra-individual change in functional limitations among White, Black and Mexican American Men and Women, and the extent to which differences in life course capital account for group disparities in initial health status and rates of change with age. Results support an intersectionality approach, with all demographic groups exhibiting worse functional limitation trajectories than White Men. Whereas White Men had the lowest disability levels at baseline, White Women and racial/ethnic minority Men had intermediate disability levels and Black and Hispanic Women had the highest disability levels. These health disparities remained stable with age-except among Black Women who experience a trajectory of accelerated disablement. Dissimilar early life social origins, adult socioeconomic status, marital status, and health behaviors explain the racial/ethnic disparities in functional limitations among Men but only partially explain the disparities among Women. Net of controls for life course capital, Women of all racial/ethnic groups have higher levels of functional limitations relative to White Men and Men of the same race/ethnicity. Findings highlight the utility of an intersectionality approach to understanding health disparities.
Keywords: Age Factors; Black or African American; Disability Evaluation; Disabled Persons; Female; Health Status Disparities; Health Surveys; Hispanic or Latino; Humans; Male; Middle Aged; Models, Statistical; Models, Theoretical; Sex Factors; Social Class; United States; White People

The urban neighborhood and cognitive functioning in late middle age. - Carol S Aneshensel; Michelle J Ko; Joshua Chodosh; Richard G Wight (J Health Soc Behav, 2011)
This study examines the association of cognitive functioning with urban neighborhood socioeconomic disadvantage and racial/ethnic segregation for a U.S. national sample of persons in late middle age, a time in the life course when cognitive deficits begin to emerge. The key hypothesis is that effects of neighborhood on cognitive functioning are not uniform but are most pronounced among subgroups of the population defined by socioeconomic status and race/ethnicity. Data are from the third wave of the Health and Retirement Survey for the birth cohort of 1931 to 1941, which was 55 to 65 years of age in 1996 (analytic N = 4,525), and the 1990 U.S. Census. Neighborhood socioeconomic disadvantage has an especially large negative impact on cognitive functioning among persons who are themselves poor, an instance of compound disadvantage. These findings have policy implications supporting "upstream" interventions to enhance cognitive functioning, especially among those most adversely affected by neighborhood socioeconomic disadvantage.
Keywords: Activities of Daily Living; Age Factors; Aged; Aging; Chi-Square Distribution; Cognition; Cognition Disorders; ethnicity; Female; Health Status Disparities; Humans; Male; Middle Aged; Psychometrics; Residence Characteristics; Risk Factors; Socioeconomic factors; United States; Urban Population

Utilization of blood transfusion among older adults in the United States. - Mary A M Rogers; Neil Blumberg; Heal, Joanna M; Kenneth M. Langa (Transfusion, 2011)
BACKGROUND: While there have been epidemiologic studies of blood donors, the characteristics of individuals who receive transfusions have not been well described for the US population. STUDY DESIGN AND METHODS: Subjects were from the nationally representative Health and Retirement Study whose data were linked to Medicare files from 1991 through 2007 (n = 16,377). A cohort study was conducted to assess the frequency of transfusion in older Americans over time and to describe the characteristics of blood recipients. RESULTS: Thirty-one percent (95% confidence interval [CI], 30%-33%) of older Americans received at least one transfusion within a 10-year period and 5.8% (95% CI, 5.4%-6.2%) experienced repeated transfusion-related visits within 30 days. The mean number of transfusion-related visits was 2.3 over a 10-year period (95% CI, 2.2-2.4). Older Americans who lived in the South were most likely to receive a transfusion (34%), independent of demographic and health-related factors, while those who lived in the western United States were the least likely (26%). Predictors of transfusion included smoking, low body mass index, and a history of cancer, diabetes mellitus, end-stage renal disease, and heart disease. African-Americans and Mexican-Americans had greater rates of blood utilization than other races and other Hispanics (respectively). There were also differences in transfusion utilization by education, marital status, religion, and alcohol use. CONCLUSIONS: Transfusion is common in older Americans. Regional variations in blood use are not explained by patient characteristics alone.
Keywords: Age Distribution; Aged; Aged, 80 and over; Black or African American; Blood Transfusion; Female; Humans; Male; United States; White People

Volunteer transitions among older adults: the role of human, social, and cultural capital in later life. - Tay K. McNamara; Guillermo Ernest Gonzales (J Gerontol B Psychol Sci Soc Sci, 2011)
OBJECTIVES: We aim to understand how human, social, and cultural capitals are associated with the volunteer process, that is, engagement (starting), intensity (number of hours), and cessation (stopping), among older adults. METHOD: Data from the 2000 through 2008 Health and Retirement Study and the 2001 through 2009 Consumption and Activity Mail Survey provide a sample of 4,526 respondents. Random-effects pooled time series analyses incorporate not only the presence of various types of capital but also the quality of that capital. RESULTS: Human and cultural capitals were positively associated with increased volunteer involvement. Effects of social capital (relationships in the family, employment status, and the community) depended on the quality of the relationships, not necessarily on their presence alone. DISCUSSION: Results suggest that bolstering older adults' capitals, particularly among lower socioeconomic status groups, can increase volunteer engagement and intensity and reduce cessation. Additionally, a variety of organizational policies including respite programs for caregivers and employer policies allowing employees to reduce their work hours might indirectly affect participation rates and commitment. Potential pools of volunteers exist in families, workplaces, and religious organizations, but more research is necessary to identify how to recruit and retain individuals in social networks where volunteer participatory rates are low.
Keywords: Aged; Aging; Caregivers; Community Participation; Cost of Illness; Educational Status; Employment; Female; Health Status; Health Surveys; Humans; Likelihood Functions; Longitudinal Studies; Male; Middle Aged; Multivariate Analysis; Religion and Psychology; Social Environment; Social Identification; Social Support; Socioeconomic factors; United States; Volunteers

Volunteering, driving status, and mortality in U.S. retirees. - Sei J. Lee; Michael A Steinman; Erwin J Tan (J Am Geriatr Soc, 2011)
OBJECTIVES: To evaluate how accounting for driving status altered the relationship between volunteering and mortality in U.S. retirees. DESIGN: Observational prospective cohort. SETTING: Nationally representative sample from the Health and Retirement Study in 2000 and 2002 followed to 2006. PARTICIPANTS: Retirees aged 65 and older (N=6,408). MEASUREMENTS: Participants self-reported their volunteering, driving status, age, sex, race or ethnicity, presence of chronic conditions, geriatric syndromes, socioeconomic factors, functional limitations, and psychosocial factors. Death by December 31, 2006, was the outcome. RESULTS: For drivers, mortality in volunteers (9%) and nonvolunteers (12%) was similar; for limited or non-drivers, mortality for volunteers (15%) was markedly lower than for nonvolunteers (32%). Adjusted results showed that, for drivers, the volunteering-mortality odds ratio (OR) was 0.90 (95% confidence interval (CI)=0.66-1.22), whereas for limited or nondrivers, the OR was 0.62 (95% CI=0.49-0.78) (interaction P=.05). The effect of driving status was greater for rural participants, with greater differences between rural drivers and rural limited or nondrivers (interaction P=.02) and between urban drivers and urban limited or nondrivers (interaction P=.81). CONCLUSION: The influence of volunteering in decreasing mortality seems to be stronger in rural retirees who are limited or nondrivers. This may be because rural or nondriving retirees are more likely to be socially isolated and thus receive more benefit from the greater social integration from volunteering.
Keywords: Activities of Daily Living; Aged; Automobile Driving; Female; Health Status; Humans; Male; Prospective Studies; Retirement; Risk Factors; Social Behavior; Survival Rate; United States; Volunteers

Who pays for obesity? - Bhattacharya, Jay; Sood, Neeraj (J Econ Perspect, 2011)
Adult obesity is a growing problem. From 1962 to 2006, obesity prevalence nearly tripled to 35.1 percent of adults. The rising prevalence of obesity is not limited to a particular socioeconomic group and is not unique to the United States. Should this widespread obesity epidemic be a cause for alarm? From a personal health perspective, the answer is an emphatic "yes." But when it comes to justifications of public policy for reducing obesity, the analysis becomes more complex. A common starting point is the assertion that those who are obese impose higher health costs on the rest of the population—a statement which is then taken to justify public policy interventions. But the question of who pays for obesity is an empirical one, and it involves analysis of how obese people fare in labor markets and health insurance markets. We will argue that the existing literature on these topics suggests that obese people on average do bear the costs and benefits of their eating and exercise habits. We begin by estimating the lifetime costs of obesity. We then discuss the extent to which private health insurance pools together obese and thin, whether health insurance causes obesity, and whether being fat might actually cause positive externalities for those who are not obese. If public policy to reduce obesity is not justified on the grounds of external costs imposed on others, then the remaining potential justification would need to be on the basis of helping people to address problems of ignorance or self-control that lead to obesity. In the conclusion, we offer a few thoughts about some complexities of such a justification.
Keywords: Adult; Cost of Illness; Financing, Personal; Health Benefit Plans, Employee; Health Care Costs; health policy; Humans; Income; Insurance Coverage; Insurance Pools; Insurance, Health; Life Expectancy; Models, Econometric; Obesity; Prevalence; Private Sector; Public Sector; Risk Adjustment; Social Control Policies; United States

Advance directives and outcomes of surrogate decision making before death. - Maria J Silveira; Scott Y H Kim; Kenneth M. Langa (N Engl J Med, 2010)
BACKGROUND: Recent discussions about health care reform have raised questions regarding the value of advance directives. METHODS: We used data from survey proxies in the Health and Retirement Study involving adults 60 years of age or older who had died between 2000 and 2006 to determine the prevalence of the need for decision making and lost decision-making capacity and to test the association between preferences documented in advance directives and outcomes of surrogate decision making. RESULTS: Of 3746 subjects, 42.5% required decision making, of whom 70.3% lacked decision-making capacity and 67.6% of those subjects, in turn, had advance directives. Subjects who had living wills were more likely to want limited care (92.7%) or comfort care (96.2%) than all care possible (1.9%); 83.2% of subjects who requested limited care and 97.1% of subjects who requested comfort care received care consistent with their preferences. Among the 10 subjects who requested all care possible, only 5 received it; however, subjects who requested all care possible were far more likely to receive aggressive care as compared with those who did not request it (adjusted odds ratio, 22.62; 95% confidence interval [CI], 4.45 to 115.00). Subjects with living wills were less likely to receive all care possible (adjusted odds ratio, 0.33; 95% CI, 0.19 to 0.56) than were subjects without living wills. Subjects who had assigned a durable power of attorney for health care were less likely to die in a hospital (adjusted odds ratio, 0.72; 95% CI, 0.55 to 0.93) or receive all care possible (adjusted odds ratio, 0.54; 95% CI, 0.34 to 0.86) than were subjects who had not assigned a durable power of attorney for health care. CONCLUSIONS: Between 2000 and 2006, many elderly Americans needed decision making near the end of life at a time when most lacked the capacity to make decisions. Patients who had prepared advance directives received care that was strongly associated with their preferences. These findings support the continued use of advance directives.
Keywords: Advance directives; Aged; Aged, 80 and over; Decision making; Female; Humans; Living Wills; Logistic Models; Male; Mental Competency; Middle Aged; Proxy; Terminal Care; United States

Alcohol use trajectories in two cohorts of U.S. women aged 50 to 65 at baseline. - Janet Kay Bobo; April A Greek; Daniel H. Klepinger; Jerald R Herting (J Am Geriatr Soc, 2010)
OBJECTIVES: To examine drinking trajectories followed by two cohorts of older women over 8 to 10 years of follow-up. DESIGN: Longitudinal analyses of two nationally representative cohorts using semiparametric group-based models weighted and adjusted for baseline age. SETTING: Study data were obtained from detailed interviews conducted in the home or by telephone. PARTICIPANTS: One cohort included 5,231 women in the Health and Retirement Study (HRS) aged 50 to 65 in 1996; the other included 1,658 women in the National Longitudinal Survey (NLS) aged 50 to 65 in 1995. MEASUREMENTS: Both cohorts reported any recent drinking and average number of drinks per drinking day using similar but not identical questions. HRS women completed six interviews (one every other year) from 1996 to 2006. NLS women completed five interviews from 1995 to 2003. RESULTS: All trajectory models yielded similar results. For HRS women, four trajectory groups were observed in the model based on drinks per day: increasing drinkers (4.9% of cohort), infrequent and nondrinkers (61.8%), consistent drinkers (25.9%), and decreasing drinkers (7.4%). Corresponding NLS values from the drinks per day model were 8.8%, 61.4%, 21.2%, and 8.6%, respectively. In 2006, the average number of drinks per day for HRS women in the increasing drinker and consistent drinker trajectories was 1.31 and 1.59, respectively. In 2003, these values for NLS women were 0.99 and 1.38, respectively. CONCLUSION: Most women do not markedly change their drinking behavior after age 50, but some increase their alcohol use substantially, whereas others continue to exceed current recommendations. These findings underscore the importance of periodically asking older women about their drinking to assess, advise, and assist those who may be at risk for developing alcohol-related problems.
Keywords: Aged; Aging; Alcohol Drinking; Alcoholism; Cohort Studies; Female; Follow-Up Studies; Humans; Life Change Events; Middle Aged; Retirement; Risk Factors; Surveys and Questionnaires; United States

Can racial disparity in health between black and white Americans be attributed to racial disparities in body weight and socioeconomic status? - Kahng, Sang Kyoung (Health Soc Work, 2010)
Few studies have examined to what extent racial disparities in chronic health conditions (CHCs) are attributable to racial differences in body weight (measured as body mass index [BMI]) and socioeconomic status (SES) among older adults. To address this gap, using longitudinal data from the Health and Retirement Study, the current study examined risk factors of CHC trajectory including race, BMI, and SES. The sample consists of 22,560 in 1998, 20,825 in 2000, and 19,004 in 2002. Data analysis was done through latent growth curve modeling. As expected, older adults presented an increasing trajectory of CHCs over time. Black Americans presented a significantly more negative CHC trajectory than did their white counterparts, confirming racial disparity in health over time. Consequent hierarchical analyses revealed that racial disparity in CHC trajectory can be explained by racial disparity in BMI and that racial disparity in BMI can be attributed to racial disparity in SES. Because low SES is closely related to unhealthy diet and negative health behaviors that may subsequently lead to obesity and chronic health conditions, the findings suggest that to address racial disparity in CHCs, it is important for social workers to continuously try to mitigate racial inequality in SES.
Keywords: Aged; Black or African American; Body Mass Index; Body Weight; Female; Health Surveys; Healthcare Disparities; Humans; Male; Middle Aged; Social Class; United States; White People

Clinical complexity in middle-aged and older adults with diabetes: the Health and Retirement Study. - Caroline S Blaum; Christine T Cigolle; Cynthia Boyd; Jennifer L. Wolff; Zhiyi Tian; Kenneth M. Langa; David R Weir (Med Care, 2010)
BACKGROUND: Some patients with diabetes may have health status characteristics that could make diabetes self-management (DSM) difficult and lead to inadequate glycemic control, or limit the benefit of some diabetes management interventions. OBJECTIVE: To investigate how many older and middle-aged adults with diabetes have such health status characteristics. DESIGN: Secondary data analysis of a nationally representative health interview survey, the Health and Retirement Study, and its diabetes mail-out survey. SETTING/PARTICIPANTS: Americans aged 51 and older with diabetes (n = 3506 representing 13.6 million people); aged 56 and older in diabetes survey (n = 1132, representing 9.9 million). MEASUREMENTS: Number of adults with diabetes and (a) relatively good health; (b) health status that could make DSM difficult (eg, comorbidities, impaired instrumental activities of daily living; and (c) characteristics like advanced dementia and activities of daily living dependency that could limit benefit of some diabetes management. Health and Retirement Study measures included demographics. Diabetes Survey included self-measured HbA1c. RESULTS: Nearly 22% of adults > or =51 with diabetes (about 3 million people) have health characteristics that could make DSM difficult. Another 10% (1.4 million) may receive limited benefit from some diabetes management. Mail-out respondents with health characteristics that could make DSM difficult had significantly higher mean HbA1c compared with people with relatively good health (7.6% vs. 7.3%, P < 0.04.). CONCLUSIONS: Some middle-aged as well as older adults with diabetes have health status characteristics that might make DSM difficult or of limited benefit. Current diabetes quality measures, including measures of glycemic control, may not reflect what is possible or optimal for all patient groups.
Keywords: Aged; Cross-Sectional Studies; Diabetes Complications; Diabetes Mellitus, Type 2; Female; Glycemic Index; Health Status; Health Surveys; Humans; Male; Middle Aged; Quality of Health Care; Self Care; Severity of Illness Index; Treatment Failure; United States

Coronary heart disease from a life-course approach: findings from the health and retirement study, 1998-2004. - Mary E Bowen (J Aging Health, 2010)
OBJECTIVE: Guided by a life-course approach to chronic disease, this study examined the ways in which childhood deprivation (low parental education and father's manual occupation) may be associated with coronary heart disease (CHD). METHOD: Multilevel modeling techniques and a nationally representative sample of Americans above age 50 from the Health and Retirement Study (HRS; N = 18,465) were used to examine childhood and CHD relationships over the course of 6 years (1998-2004). RESULTS: Having a father with </=8 years of education was associated with 11% higher odds of CHD, accounting for demographic characteristics, adult socioeconomic status (SES; education, income, and wealth), CHD risks (diabetes, hypertension, cigarette smoking, and obesity), and other factors (childhood health, exercise, stroke, and marital status). DISCUSSION: Policies and programs aimed at improving the conditions of poor children and their families may effectively reduce the prevalence of CHD in later life.
Keywords: Age Factors; Aged; Aging; Coronary Artery Disease; Educational Status; Female; Health Status Disparities; Health Surveys; Humans; Income; Male; Middle Aged; Multivariate Analysis; Odds Ratio; Poverty; Prevalence; Retirement; Risk Assessment; Risk Factors; Self Report; Social Class; Socioeconomic factors; United States

Cross-national comparison of sex differences in health and mortality in Denmark, Japan and the US. - Oksuzyan, Anna; Eileen M. Crimmins; Saito, Yasuhiko; Angela M O'Rand; James W Vaupel; Christensen, Kaare (Eur J Epidemiol, 2010)
The present study aims to compare the direction and magnitude of sex differences in mortality and major health dimensions across Denmark, Japan and the US. The Human Mortality Database was used to examine sex differences in age-specific mortality rates. The Danish twin surveys, the Danish 1905-Cohort Study, the Health and Retirement Study, and the Nihon University Japanese Longitudinal Study of Aging were used to examine sex differences in health. Men had consistently higher mortality rates at all ages in all three countries, but they also had a substantial advantage in handgrip strength compared with the same-aged women. Sex differences in activities of daily living (ADL) became pronounced among individuals aged 85+ in all three countries. Depression levels tended to be higher in women, particularly, in Denmark and the HRS, and only small sex differences were observed in the immediate recall test and Mini-Mental State Exam. The present study revealed consistent sex differentials in survival and physical health, self-rated health and cognition at older ages, whereas the pattern of sex differences in depressive symptoms was country-specific.
Keywords: Aged; Aged, 80 and over; Denmark; Disability Evaluation; Female; Health Status; Humans; Japan; Male; Middle Aged; Mortality; Sex Distribution; United States

Defining emergency department episodes by severity and intensity: A 15-year study of Medicare beneficiaries. - Kaskie, Brian; Maksym Obrizan; Elizabeth A Cook; Michael P Jones; Li Liu; Suzanne E Bentler; Robert B Wallace; John F Geweke; Kara B Wright; Elizabeth A Chrischilles; Claire E Pavlik; Robert L. Ohsfeldt; et al. (BMC Health Serv Res, 2010)
BACKGROUND: Episodes of Emergency Department (ED) service use among older adults previously have not been constructed, or evaluated as multi-dimensional phenomena. In this study, we constructed episodes of ED service use among a cohort of older adults over a 15-year observation period, measured the episodes by severity and intensity, and compared these measures in predicting subsequent hospitalization. METHODS: We conducted a secondary analysis of the prospective cohort study entitled the Survey on Assets and Health Dynamics among the Oldest Old (AHEAD). Baseline (1993) data on 5,511 self-respondents >or=70 years old were linked to their Medicare claims for 1991-2005. Claims then were organized into episodes of ED care according to Medicare guidelines. The severity of ED episodes was measured with a modified-NYU algorithm using ICD9-CM diagnoses, and the intensity of the episodes was measured using CPT codes. Measures were evaluated against subsequent hospitalization to estimate comparative predictive validity. RESULTS: Over 15 years, three-fourths (4,171) of the 5,511 AHEAD participants had at least 1 ED episode, with a mean of 4.5 episodes. Cross-classification indicated the modified-NYU severity measure and the CPT-based intensity measure captured different aspects of ED episodes (kappa = 0.18). While both measures were significant independent predictors of hospital admission from ED episodes, the CPT measure had substantially higher predictive validity than the modified-NYU measure (AORs 5.70 vs. 3.31; p < .001). CONCLUSIONS: We demonstrated an innovative approach for how claims data can be used to construct episodes of ED care among a sample of older adults. We also determined that the modified-NYU measure of severity and the CPT measure of intensity tap different aspects of ED episodes, and that both measures were predictive of subsequent hospitalization.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Emergency Service, Hospital; Humans; Insurance Claim Review; Medicare; Prospective Studies; Severity of Illness Index; United States

Dental care coverage and retirement. - Richard J. Manski; John F Moeller; Jody Schimmel; Patricia A St Clair; Haiyan Chen; Larry S. Magder; John V Pepper (J Public Health Dent, 2010)
OBJECTIVES: To examine the convergence of an aging population and a decreased availability of dental care coverage using data from the Health and Retirement Study (HRS). METHODS: We calculate national estimates of the number and characteristics of those persons age 51 years and above covered by dental insurance by labor force, retirement status, and source of coverage. We also estimate a multivariate model controlling for potentially confounding variables. RESULTS: We show that being in the labor force is a strong predictor of having dental coverage. For older retired adults not in the labor force, the only source for dental coverage is either a postretirement health benefit or spousal coverage. CONCLUSIONS: Dental care, generally not covered in Medicare, is an important factor in the decision to seek dental care. It is important to understand the relationship between retirement and dental coverage in order to identify the best ways of improving oral health and access to care among older Americans.
Keywords: Aged; Employment; ethnicity; Female; Humans; Income; Insurance, Dental; Male; Middle Aged; Models, Statistical; Multivariate Analysis; Retirement; United States

Dental care expenditures and retirement. - Richard J. Manski; John F Moeller; Haiyan Chen; Patricia A St Clair; Jody Schimmel; Larry S. Magder; John V Pepper (J Public Health Dent, 2010)
OBJECTIVES: To examine the relationship of dental care coverage, retirement, and out-of-pocket (OOP) dental expenditures in an aging population, using data from the Health and Retirement Study (HRS). METHODS: We estimate OOP dental expenditures among individuals who have dental utilization as a function of dental care coverage status, retirement, and individual and household characteristics. We also estimate a multivariate model controlling for potentially confounding variables. RESULTS: Overall, mean OOP dental expenditures among those with any spending were substantially larger for those without coverage than for those with coverage. However, controlling for coverage shows that there is little difference in spending by retirement status. CONCLUSIONS: Although having dental coverage is a key determinant of the level of OOP expenditures on dental care; spending is higher among those without coverage than those who have dental insurance. We also found that while retirement has no independent effect on OOP dental expenditures once controlling for coverage, dental coverage rates are much lower among retirees.
Keywords: Age Factors; Aged; Dental Care; Educational Status; ethnicity; Female; Financing, Personal; Humans; Income; Insurance Coverage; Insurance, Dental; Male; Marital Status; Middle Aged; Mouth, Edentulous; Retirement; United States

Dental care utilization and retirement. - Richard J. Manski; John F Moeller; Haiyan Chen; Patricia A St Clair; Jody Schimmel; Larry S. Magder; John V Pepper (J Public Health Dent, 2010)
OBJECTIVE: The authors examine the relationship of dental care coverage, retirement, and utilization in an aging population using data from the Health and Retirement Study (HRS). METHODS: The authors estimate dental care use as a function of dental care coverage status, retirement, and individual and household characteristics. They also estimate a multivariate model controlling for potentially confounding variables. RESULTS: The authors show that that the loss of income and dental coverage associated with retirement may lead to lower use rates but this effect may be offset by other unobserved aspects of retirement including more available free time leading to an overall higher use rate. CONCLUSIONS: The authors conclude from this study that full retirement accompanied by reduced income and dental insurance coverage produces lower utilization of dental services. However, they also show that retirement acts as an independent variable, whereas income, coverage, and free time (unobserved) act as intervening variables.
Keywords: Aged; Confounding Factors, Epidemiologic; Dental Care; Employment; ethnicity; Female; health policy; Humans; Income; Insurance, Dental; Leisure activities; Logistic Models; Male; Middle Aged; Multivariate Analysis; Odds Ratio; Retirement; Socioeconomic factors; United States

Depression among older adults in the United States and England. - Zivin, Kara; David J Llewellyn; Iain A Lang; Sandeep Vijan; Mohammed U Kabeto; Erin M Miller; Kenneth M. Langa (Am J Geriatr Psychiatry, 2010)
CONTEXT: Depression negatively affects health and well being among older adults, but there have been no nationally representative comparisons of depression prevalence among older adults in England and the United States. OBJECTIVE: The authors sought to compare depressive symptoms among older adults in these countries and identify sociodemographic and clinical correlates of depression in these countries. DESIGN AND SETTING: The authors assessed depressive symptoms in non-Hispanic whites aged 65 years and older in 2002 in two nationally representative, population-based studies: the U.S. Health and Retirement Study and English Longitudinal Study of Ageing. PARTICIPANTS: A total of 8,295 Health and Retirement Study respondents and 5,208 English Longitudinal Study of Ageing respondents. MAIN OUTCOME MEASURES: The authors measured depressive symptoms using the eight-item Center for Epidemiologic Studies Depression Scale. The authors determined whether depressive symptom differences between the United States and England were associated with sociodemographic characteristics, chronic health conditions, and health behaviors. RESULTS: Significant depressive symptoms (Center for Epidemiologic Studies Depression Scale score ≥4) were more prevalent in English than U.S. adults (17.6% versus 14.6%, adjusted Wald test F([1, 1593]) = 11.4, p < 0.001). Adjusted rates of depressive symptoms in England were 19% higher compared with the United States (odds ratio: 1.19, 95% confidence interval: 1.01-1.40). U.S. adults had higher levels of education, and net worth, but lower levels of activities of daily living/instrumental activities of daily living impairments, tobacco use, and cognitive impairment, which may have contributed to relatively lower levels of depressive symptoms in the United States. CONCLUSIONS: Older adults in the United States had lower rates of depressive symptoms than their English counterparts despite having more chronic health conditions. Future cross-national studies should identify how depression treatment influences outcomes in these populations.
Keywords: Aged; Aged, 80 and over; depression; England; Female; Health Behavior; Health Status; Health Surveys; Humans; Male; Prevalence; Risk Factors; United States; White People

Depressive symptoms in middle age and the development of later-life functional limitations: the long-term effect of depressive symptoms. - Kenneth E Covinsky; Kristine Yaffe; Lindquist, Karla; Cherkasova, Elena; Yelin, Edward; Dan G. Blazer (J Am Geriatr Soc, 2010)
OBJECTIVES: To determine whether middle-aged persons with depressive symptoms are at higher risk for developing activity of daily living (ADL) and mobility limitations as they advance into older age than those without. DESIGN: Prospective cohort study. SETTING: The Health and Retirement Study (HRS), a nationally representative sample of people aged 50 to 61. PARTICIPANTS: Seven thousand two hundred seven community living participants in the 1992 wave of the HRS. MEASUREMENTS: Depressive symptoms were measured using the 11-item Center for Epidemiologic Studies Depression Scale (CES-D 11), with scores of 9 or more (out of 33) classified as significant depressive symptoms. Difficulty with five ADLs and basic mobility tasks (walking several blocks or up one flight of stairs) was measured every 2 years through 2006. The primary outcome was persistent difficulty with ADLs or mobility, defined as difficulty in two consecutive waves. RESULTS: Eight hundred eighty-seven (12%) subjects scored 9 or higher on the CES-D 11 and were classified as having significant depressive symptoms. Over 12 years of follow-up, subjects with depressive symptoms were more likely to reach the primary outcome measure of persistent difficulty with mobility or difficulty with ADL function (45% vs 23%, Cox hazard ratio (HR)=2.33, 95% confidence interval (CI)=2.06-2.63). After adjusting for age, sex, measures of socioeconomic status, comorbid conditions, high body mass index, smoking, exercise, difficulty jogging 1 mile, and difficulty climbing several flights of stairs, the risk was attenuated but still statistically significant (Cox HR=1.44, 95% CI=1.25-1.66). CONCLUSION: Depressive symptoms independently predict the development of persistent limitations in ADLs and mobility as middle-aged persons advance into later life. Middle-aged persons with depressive symptoms may be at greater risk for losing their functional independence as they age.
Keywords: Activities of Daily Living; depression; Female; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Mobility Limitation; Proportional Hazards Models; Prospective Studies; Risk Factors; United States

Depressive symptoms predict incident stroke independently of memory impairments. - M. Maria Glymour; J Maselko; Gilman, S E; Kristen K Patton; Mauricio Avendano (Neurology, 2010)
BACKGROUND: We evaluated whether depressive symptoms predict the onset of first stroke independently of memory impairment. We conceptualized memory impairment as a marker of preexisting cerebrovascular disease. We hypothesized that if depressive symptoms are causally related to stroke through mechanisms unrelated to cerebrovascular disease, depressive symptoms should predict stroke independently of memory impairment. METHODS: Incidence of first stroke was assessed with self or proxy reports from 19,087 participants in the Health and Retirement Study cohort (1,864 events). Elevated depressive symptoms (3+ on an 8-item Centers for the Epidemiologic Study of Depression scale) and memory impairment (score of ≤6 on a combined immediate and delayed recall of a 10-word list) were used as predictors of incident stroke in Cox survival models with adjustment for sociodemographic and cardiovascular risk factors. RESULTS: After adjustment for sociodemographic and cardiovascular risk factors, elevated depressive symptoms (hazard ratio = 1.25; 95% confidence interval 1.12-1.39) and memory impairment (hazard ratio = 1.26; 95% confidence interval 1.13-1.41) each predicted stroke incidence in separate models. Hazard ratios were nearly unchanged and remained significant (1.23 for elevated depressive symptoms and 1.25 for memory impairment) when models were simultaneously adjusted for both elevated depressive symptoms and memory impairment. Elevated depressive symptoms also predicted stroke when restricting analyses to individuals with median memory score or better. CONCLUSIONS: Memory impairments and depressive symptoms independently predict stroke incidence. Memory impairment may reflect undiagnosed cerebrovascular disease. These results suggest that depressive symptoms might be directly related to stroke rather than merely indicating preexisting cerebrovascular disease.
Keywords: Aged; Aged, 80 and over; depression; Female; Health Surveys; Humans; Incidence; Kaplan-Meier Estimate; Longitudinal Studies; Male; Memory Disorders; Middle Aged; Neuropsychological tests; Predictive Value of Tests; Risk Factors; Statistics, Nonparametric; Stroke; United States

Diabetes-related support, regimen adherence, and health decline among older adults. - Emily J Nicklett; Jersey Liang (J Gerontol B Psychol Sci Soc Sci, 2010)
UNLABELLED: OBJECTIVES. Social support is generally conceptualized as health promoting; however, there is little consensus regarding the mechanisms through which support is protective. Illness support has been proposed to promote regimen adherence and subsequent prevention of health decline. We hypothesize that (a) support for regimen adherence is negatively associated with self-reported health decline among older diabetic adults and that (b) regimen adherence is negatively associated with health decline among older diabetic adults. METHODS: We used the Health and Retirement Study data on individuals over the age of 60 years with type 2 diabetes mellitus (n = 1,788), examining change in self-reported health status over a 2-year period using binomial and cumulative ordinal logistic regression models. RESULTS: Diabetic support is not significantly associated with health decline, but it is strongly associated with adherence to health-promoting activities consisting of a diabetic regimen. Therefore, the extent to which one receives illness support for a given regimen component is highly positively associated with adhering to that component, although this adherence does not necessarily translate into protection against perceived decline in health. CONCLUSIONS: Illness-related support appears to be a mechanism through which social support matters in the diabetic population. Although this relationship did not extend to prevention of health status decline among diabetics, the relationship between support and illness management is promising.
Keywords: Activities of Daily Living; Aged; Diabetes Mellitus, Type 2; Disability Evaluation; Female; Health Behavior; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Patient Compliance; Quality of Life; Social Support; Surveys and Questionnaires; United States

Direct and indirect effects of obesity on U.S. labor market outcomes of older working age adults. - F. Renna; Thakur, Nidhi (Soc Sci Med, 2010)
In this paper, we study the impact of obesity on labor market decisions of older working age adults in USA. Labor market outcomes are defined as any one of three: working; not working due to a disability; or not working due to an early retirement. Based on existing medical literature, we deduce that obesity can largely impact labor market decisions directly through impairment of bodily functions and indirectly by being a risk factor for various diseases like hypertension, arthritis, etc. We use data from the US Health and Retirement Study on older adults who were no more than 64 years of age in 2002. In our modeling effort, we employ two estimation strategies. We first estimate a model in which employment outcome in 2002 is a function of weight status in 1992. In the second strategy, controlling for time-invariant individual heterogeneity, we first consider the impact of obesity on bodily impairments and chronic illnesses; then, we consider the impact of such impairments and illnesses on labor market outcomes. Our results indicate that, for men, obesity class 2 and 3 increases both the probability of taking an early retirement and the incidence of disability by 1.5 percentage points. For women, we find that obesity class 2 and 3 increases the probability of taking an early retirement by 2.5 percentage points and the incidence of disability by 1.7 percentage points.
Keywords: Chronic disease; Disabled Persons; Employment; Female; Humans; Male; Middle Aged; Obesity; Retirement; Risk Factors; Sex Factors; United States

Disease prevalence, disease incidence, and mortality in the United States and in England. - James Banks; Muriel, Alastair; James P Smith (Demography, 2010)
We find that both disease incidence and disease prevalence are higher among Americans in age groups 55-64 and 70-80, indicating that Americans suffer from higher past cumulative disease risk and experience higher immediate risk of new disease onset compared with the English. In contrast, age-specific mortality rates are similar in the two countries, with an even higher risk among the English after age 65. We also examine reasons for the large financial gradients in mortality in the two countries. Among 55- to 64-year-olds, we estimate similar health gradients in income and wealth in both countries, but for 70- to 80-year-olds, we find no income gradient in the United Kingdom. Standard behavioral risk factors (work, marriage, obesity, exercise, and smoking) almost fully explain income gradients among those aged 55-64 in both countries and a significant part among Americans 70-80 years old. The most likely explanation of the absence of an English income gradient relates to the English income benefit system: below the median, retirement benefits are largely flat and independent of past income, and hence past health, during the working years. Finally, we report evidence using a long panel of American respondents that their subsequent mortality is not related to large changes in wealth experienced during the prior 10-year period.
Keywords: Aged; Aged, 80 and over; England; Health Status; Health Status Disparities; Humans; Incidence; Life Tables; Middle Aged; Morbidity; Mortality; Prevalence; Socioeconomic factors; United States

Dynamics and heterogeneity in the process of human frailty and aging: evidence from the U.S. older adult population. - Yang, Yang; Lee, Linda C (J Gerontol B Psychol Sci Soc Sci, 2010)
OBJECTIVES: This study investigated the dynamics and heterogeneity of the frailty index (FI) conceived as a systemic indicator of biological aging in the community-dwelling older adult population in the United States. METHODS: We used panel data on multiple birth cohorts from the Health and Retirement Survey 1993-2006 and growth curve models to estimate age trajectories of the FI and their differences by sex, race, and socioeconomic status (SES) within cohorts. RESULTS: The FI for cohorts born before 1942 exhibit quadratic increases with age and accelerated increases in the accumulation of health deficits. More recent cohorts exhibit higher average levels of and rates of increment in the FI than their predecessors do at the same ages. Females, non-Whites, and individuals with low education and income exhibit greater degrees of physiological deregulation than their male, White, and high-SES counterparts at any age. Patterns of sex, race, and SES differentials in rates of aging vary across cohorts. DISCUSSION: Adjusting for social behavioral factors, the analysis provides evidence for physiological differences in the aging process among recent cohorts of older adults, points to the need for biological explanations of female excess in general system damage, and reveals the insufficiency of any single mechanism for depicting the racial and SES differences in the process of physiological deterioration.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Frail Elderly; Humans; Male; Surveys and Questionnaires; United States

Education and physical activity mediate the relationship between ethnicity and cognitive function in late middle-aged adults. - Meredith C. Masel; Raji, Mukaila; M. Kristen Peek (Ethn Health, 2010)
OBJECTIVE: Minority status has been implicated as a risk factor for disparate scores on cognitive function tests in older adults. Research on ethnicity and cognitive function has yielded socioeconomic status, particularly education, as a primary reason for the discrepancy. Other factors, such as physical activity may provide insight into the relationship. Despite this knowledge, few studies have thoroughly examined the mediating characteristics of education or physical activity in the relationship between ethnicity and cognitive function in younger aged groups. Most research conducted focuses only on older adults during a time when degeneration of brain tissue may complicate the exploration of the relationships among ethnicity and cognitive function. The current research will expand existing knowledge about education, physical activity, and cognitive function in minority groups. DESIGN: The study presents data from the Health and Retirement Study, a nationally representative sample of late middle-aged White, Black, and Hispanic adults (n=9204, mean age+/-SD = 55.8+/-3.1). Regression and mediation testing determined the mediating effects of education and physical activity in the relationship between ethnicity and cognitive function. RESULTS: Significant association between White ethnicity and higher scores on cognitive tests was evident as early as late middle age. The magnitude of the association significantly diminished on adjusting for education and leisure time physical activity. CONCLUSION: Our data suggest a potential mediating role of education and physical activity on the ethnic differences in cognitive tests in late middle-aged White, Black, and Hispanic adults. Our findings suggest a need for studies to understand if adult education and culturally appropriate physical activity interventions in middle age influence ethnic disparities in prevalence of cognitive impairment in old age.
Keywords: Black People; Body Mass Index; Brief Psychiatric Rating Scale; Cognition Disorders; Educational Status; Exercise; Female; Health Status; Hispanic or Latino; Humans; Longitudinal Studies; Male; Memory Disorders; Middle Aged; United States; White People

Ethnicity and changing functional health in middle and late life: a person-centered approach. - Jersey Liang; Xiao Xu; Joan M. Bennett; Wen Ye; Ana R Quiñones (J Gerontol B Psychol Sci Soc Sci, 2010)
OBJECTIVES: Following a person-centered approach, this research aims to depict distinct courses of disability and to ascertain how the probabilities of experiencing these trajectories vary across Black, Hispanic, and White middle-aged and older Americans. METHODS: Data came from the 1995-2006 Health and Retirement Study, which involved a national sample of 18,486 Americans older than 50 years of age. Group-based semiparametric mixture models (Proc Traj) were used for data analysis. RESULTS: Five trajectories were identified: (a) excellent functional health (61%), (b) good functional health with small increasing disability (25%), (c) accelerated increase in disability (7%), (d) high but stable disability (4%), and (e) persistent severe impairment (3%). However, when time-varying covariates (e.g., martial status and health conditions) were controlled, only 3 trajectories emerged: (a) healthy functioning (53%), moderate functional decrement (40%), and (c) large functional decrement (8%). Black and Hispanic Americans had significantly higher probabilities than White Americans in experiencing poor functional health trajectories, with Blacks at greater risks than Hispanics. CONCLUSIONS: Parallel to the concepts of successful aging, usual aging, and pathological aging, there exist distinct courses of changing functional health over time. The mechanisms underlying changes in disability may vary between Black and Hispanic Americans.
Keywords: Age Factors; Aged; Black or African American; Disabled Persons; disease progression; ethnicity; Female; Health Status; Health Status Disparities; Health Surveys; Hispanic or Latino; Humans; Likelihood Functions; Male; Marital Status; Middle Aged; Time Factors; United States; White People

Evolving self-rated health in middle and old age: how does it differ across Black, Hispanic, and White Americans? - Jersey Liang; A. R. Quinones; Joan M. Bennett; Wen Ye; Xiao Xu; Benjamin A Shaw; Mary Beth Ofstedal (J Aging Health, 2010)
OBJECTIVE: This research focuses on ethnic variations in the intraindividual changes in self-rated health. METHOD: Data came from the Health and Retirement Study involving up to 6 repeated observations between 1995 and 2006 of a national sample of 18,486 Americans above 50 years of age. Hierarchical linear models were employed in depicting variations in self-rated health across White, Black, and Hispanic Americans. RESULTS: Subjective health worsened over time albeit moderately. Relative to younger persons, older individuals rated their health poorer with a greater rate of deteriorating health. With reference to ethnic variations in the intercept and slope of perceived health, White Americans rated their health most positively, followed by Black Americans, with Hispanics rating their health least positively. This pattern held even when socioeconomic status, social networks, and prior health were adjusted. DISCUSSION: Significant ethnic differences exist in the evolvement of self-rated health in middle and late life. Further inquiries may include analyzing ethnic heterogeneities from a person-centered perspective, health disparities across subgroups of Hispanics, effects of neighborhood attributes, and implications of left truncation.
Keywords: Age Factors; Aged; Aging; Black or African American; Diagnostic Self Evaluation; Female; Health Status Disparities; Hispanic or Latino; Humans; Linear Models; Male; Middle Aged; United States; White People

An examination of older immigrants' use of dental services in the United States. - Christina N Anderson; Hyungsoo Kim (J Aging Soc Policy, 2010)
The recent influx of immigrants aged 65 and older in the United States triggers an increasing need to understand older immigrants' dental services use. This paper uses data (n = 9,617) from the 2004 and 2006 waves of the Health and Retirement Study to examine the dental services use of older Americans. In particular, this study focuses on differences in dental services use between immigrants and natives and potential contributing factors. Multivariate logistic regression analyses showed, contrary to expectation, that older immigrants were more likely to use dental services than older natives despite numerous barriers (odds ratio = 1.30 in 2004). The results in 2006 confirmed these findings. The results from 2004 and 2006 analyses showed dental insurance coverage, sex, and marital status were associated differently with dental services use for immigrants and natives. Implications for current oral health policies and future research of older Americans are discussed, as well as methods for meeting older immigrants' growing dental services needs.
Keywords: Age Factors; Aged; Dental Care for Aged; Educational Status; Emigrants and Immigrants; Female; Health Services Accessibility; Humans; Insurance, Dental; Logistic Models; Longitudinal Studies; Male; Marital Status; Middle Aged; Multivariate Analysis; Sex Factors; Socioeconomic factors; United States

Factors influencing cost-related nonadherence to medication in older adults: a conceptually based approach. - Zivin, Kara; Scott M Ratliff; Michele M Heisler; Kenneth M. Langa; John D Piette (Value Health, 2010)
OBJECTIVE: Although multiple noncost factors likely influence a patient's propensity to forego treatment in the face of cost pressures, little is known about how patients' sociodemographic characteristics, physical and behavioral health comorbidities, and prescription regimens influence cost-related nonadherence (CRN) to medications. We sought to determine both financial and nonfinancial factors associated with CRN in a nationally representative sample of older adults. METHODS: We used a conceptual model developed by Piette and colleagues that describes financial and nonfinancial factors that could increase someone's risk of CRN, including income, comorbidities, and medication regimen complexity. We used data from the 2004 wave of the Health and Retirement Study and the 2005 HRS Prescription Drug Study to examine the influence of factors within each of these domains on measures of CRN (including not filling, stopping, or skipping doses) in a nationally representative sample of Americans age 65+ in 2005. RESULTS: Of the 3071 respondents who met study criteria, 20% reported some form of CRN in 2005. As in prior studies, indicators of financial stress such as higher out-of-pocket payments for medications and lower net worth were significantly associated with CRN in multivariable analyses. Controlling for these economic pressures, relatively younger respondents (ages 65-74) and depressive symptoms were consistent independent risk factors for CRN. CONCLUSIONS: Noncost factors influenced patients' propensity to forego treatment even in the context of cost concerns. Future research encompassing clinician and health system factors should identify additional determinants of CRN beyond patients' cost pressures.
Keywords: Aged; Aged, 80 and over; Chronic disease; Female; Financing, Personal; Health Status; Humans; Logistic Models; Male; Medication Adherence; Models, Econometric; Multivariate Analysis; Prescription Fees; Risk Factors; Socioeconomic factors; United States

Functional declines, social support, and mental health in the elderly: does living in a state supportive of home and community-based services make a difference? - Muramatsu, Naoko; yin, Hongjun; Hedeker, Donald (Soc Sci Med, 2010)
This study examines how acute and chronic stresses associated with functional declines in seniors and their spouses are moderated by their informal and formal support contexts. In the United States, states vary greatly in their support for home and community-based services (HCBS) for seniors with disabilities. This state-to-state variation allowed us to examine mental health effects of living in a society supportive of HCBS for the oldest old, who are at high risk for low or declining functions in daily activities and cognitive abilities. Using a ten-year panel study of a nationally representative sample of the oldest old (>or=70 years old) covering the period 1993-2002, we conducted mixed-effects logistic regression analysis to incorporate time-varying characteristics of persons and states. As expected, low and declining functions in daily living and cognition constituted significant stressors among seniors and their spouse. Results demonstrated the important role of informal support available from non-spouse family/friends in lowering depression. Living in a state supportive of HCBS was associated with lower depression among seniors experiencing consistently low levels of function or recent functional declines, especially among those without informal support. Our findings were consistent with moderating or buffering models of formal support, suggesting that state HCBS support is effective mainly under conditions of high levels of stressors. Political will is needed to prepare US society to collectively support community-based long-term needs, given the difficulty of preparing ourselves fully for common, but often unexpected, functional declines in later life.
Keywords: Activities of Daily Living; Aged; Cognition; Community Health Services; depression; Disabled Persons; Female; Home Care Services; Humans; Logistic Models; Male; Mental Health; Multilevel Analysis; Risk Factors; Social Support; Spouses; State Government; Stress, Psychological; United States

Hospitalizations and deaths among adults with cardiovascular disease who underuse medications because of cost: a longitudinal analysis. - Michele M Heisler; Choi, Hwajung; Allison B Rosen; Sandeep Vijan; Mohammed U Kabeto; Kenneth M. Langa; John D Piette (Med Care, 2010)
CONTEXT: It is well-documented that the financial burden of out-of-pocket expenditures for prescription drugs often leads people with medication-sensitive chronic illnesses to restrict their use of these medications. Less is known about the extent to which such cost-related medication underuse is associated with increases in subsequent hospitalizations and deaths. OBJECTIVE: We compared the risk of hospitalizations among 5401 and of death among 6135 middle-aged and elderly adults with one or more cardiovascular diseases (diabetes, coronary artery disease, heart failure, and history of stroke) according to whether participants did or did not report restricting prescription medications because of cost. DESIGN AND SETTING: A retrospective biannual cohort study across 4 cross-sectional waves of the Health and Retirement Study, a nationally representative survey of adults older than age 50. Using multivariate logistic regression to adjust for baseline differences in sociodemographic and health characteristics, we assessed subsequent hospitalizations and deaths between 1998 and 2006 for respondents who reported that they had or had not taken less medicine than prescribed because of cost. RESULTS: Respondents with cardiovascular disease who reported underusing medications due to cost were significantly more likely to be hospitalized in the next 2 years, even after adjusting for other patient characteristics (adjusted predicted probability of 47% compared with 38%, P < 0.001). The more survey waves respondents reported cost-related medication underuse during 1998 to 2004, the higher the probability of being hospitalized in 2006 (adjusted predicted probability of 54% among respondents reporting cost-related medication underuse in all 4 survey waves compared with 42% among respondents reporting no underuse, P < 0.001). There was no independent association of cost-related medication underuse with death. CONCLUSIONS: In this nationally representative cohort, middle-aged and elderly adults with cardiovascular disease who reported cutting back on medication use because of cost were more likely to report being hospitalized over a subsequent 2-year period after they had reported medication underuse. The more extensively respondents reported cost-related underuse over time, the higher their adjusted predicted probability of subsequent hospitalization.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Financing, Personal; Health Care Costs; Health Services Accessibility; Health Status Disparities; Hospitalization; Humans; Logistic Models; Longitudinal Studies; Male; Medication Adherence; Middle Aged; Multivariate Analysis; Risk Factors; United States

Impact of cognitive impairment on screening mammography use in older US women. - Kala M. Mehta; Kathy Z Fung; Christine E Kistler; Chang, Anna; Louise C Walter (Am J Public Health, 2010)
OBJECTIVES: We evaluated mammography rates for cognitively impaired women in the context of their life expectancies, given that guidelines do not recommend screening mammography in women with limited life expectancies because harms outweigh benefits. METHODS: We evaluated Medicare claims for women aged 70 years or older from the 2002 wave of the Health and Retirement Study to determine which women had screening mammography. We calculated population-based estimates of 2-year screening mammography prevalence and 4-year survival by cognitive status and age. RESULTS: Women with severe cognitive impairment had lower rates of mammography (18%) compared with women with normal cognition (45%). Nationally, an estimated 120,000 screening mammograms were performed among women with severe cognitive impairment despite this group's median survival of 3.3 years (95% confidence interval = 2.8, 3.7). Cognitively impaired women who had high net worth and were married had screening rates approaching 50%. CONCLUSIONS: Although severe cognitive impairment is associated with lower screening mammography rates, certain subgroups with cognitive impairment are often screened despite lack of probable benefit. Given the limited life expectancy of women with severe cognitive impairment, guidelines should explicitly recommend against screening these women.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Female; Humans; Incidence; Longitudinal Studies; Mammography; Medicare; Patient Acceptance of Health Care; Social Class; United States

Length of stay for older adults residing in nursing homes at the end of life. - Kelly, Anne; Conell-Price, Jessamyn; Kenneth E Covinsky; Irena Cenzer; Chang, Anna; W John Boscardin; Alexander K Smith (J Am Geriatr Soc, 2010)
OBJECTIVES: To describe lengths of stay of nursing home decedents. DESIGN: Retrospective cohort study. SETTING: The Health and Retirement Study (HRS), a nationally representative survey of U.S. adults aged 50 and older. PARTICIPANTS: One thousand eight hundred seventeen nursing home residents who died between 1992 and 2006. MEASUREMENTS: The primary outcome was length of stay, defined as the number of months between nursing home admission and date of death. Covariates were demographic, social, and clinical factors drawn from the HRS interview conducted closest to the date of nursing home admission. RESULTS: The mean age of decedents was 83.3 ± 9.0; 59.1% were female, and 81.5% were white. Median and mean length of stay before death were 5 months (interquartile range 1-20) and 13.7 ± 18.4 months, respectively. Fifty-three percent died within 6 months of placement. Large differences in median length of stay were observed according to sex (men, 3 months vs women, 8 months) and net worth (highest quartile, 3 months vs lowest quartile, 9 months) (all P <.001). These differences persisted after adjustment for age, sex, marital status, net worth, geographic region, and diagnosed chronic conditions (cancer, hypertension, diabetes mellitus, lung disease, heart disease, and stroke). CONCLUSION: Nursing home lengths of stay are brief for the majority of decedents. Lengths of stay varied markedly according to factors related to social support.
Keywords: Advance care planning; Aged; Aged, 80 and over; Female; Follow-Up Studies; Humans; Length of Stay; Male; Middle Aged; Nursing homes; Palliative care; Retrospective Studies; United States

Lifetime marital history and mortality after age 50. - John C Henretta (J Aging Health, 2010)
OBJECTIVES: This article examines the relationship between lifetime marital history and mortality after age 50. METHOD: Data are drawn from the Health and Retirement Study birth cohort of 1931 to 1941. The analysis utilizes three measures of marital history: number of marriages, proportion time married, and age at first marriage. RESULTS: Three or more marriages and a lower proportion of adult life spent married are each associated with a higher hazard of dying after age 50 for both men and women even after controlling for current marital status and socioeconomic status. Smoking behavior accounts for part of the relationship of marital history and status with mortality. DISCUSSION: Research on marital status and health should consider marital history as well as current status. Two topics are particularly important: examining the relationship in different cohorts and disentangling the potentially causal role of health behaviors such as smoking.
Keywords: Age Factors; Aging; Cohort Studies; Female; Health Status; Humans; Interpersonal Relations; Male; Marital Status; Middle Aged; Mortality; Multivariate Analysis; Proportional Hazards Models; Residence Characteristics; Risk Assessment; Risk-Taking; Smoking; Time Factors; United States

The longevity gap between Black and White men in the United States at the beginning and end of the 20th century. - Frank A Sloan; Padmaja Ayyagari; Salm, Martin; Grossman, Daniel (Am J Public Health, 2010)
OBJECTIVES: We sought to assess whether the disparity in mortality rates between Black and White men decreased from the beginning to the end of the 20th century. METHODS: We used Cox proportional hazard models for mortality to estimate differences in longevity between Black and White Civil War veterans from 1900 to 1914 (using data from a pension program) and a later cohort of male participants (using data from the 1992 to 2006 Health and Retirement Study). In sensitivity analysis, we compared relative survival of veterans for alternative baseline years through 1914. RESULTS: In our survival analysis, the Black-White male difference in mortality, both unadjusted and adjusted for other influences, did not decrease from the beginning to the end of the 20th century. A 17% difference in Black-White mortality remained for the later cohort even after we controlled for other influences. Although we could control for fewer other influences on longevity, the Black-White differences in mortality for the earlier cohort was 18%. CONCLUSIONS: In spite of overall improvements in longevity, a major difference in Black-White male mortality persists.
Keywords: Aged; Black or African American; Health Status Disparities; Humans; Longevity; Longitudinal Studies; Male; Men's health; Middle Aged; Mortality; Proportional Hazards Models; Survival Analysis; United States; Veterans; White People

Long-term cognitive impairment and functional disability among survivors of severe sepsis. - Theodore J Iwashyna; E Wesley Ely; Dylan M Smith; Kenneth M. Langa (JAMA, 2010)
CONTEXT: Cognitive impairment and functional disability are major determinants of caregiving needs and societal health care costs. Although the incidence of severe sepsis is high and increasing, the magnitude of patients' long-term cognitive and functional limitations after sepsis is unknown. OBJECTIVE: To determine the change in cognitive impairment and physical functioning among patients who survive severe sepsis, controlling for their presepsis functioning. DESIGN, SETTING, AND PATIENTS: A prospective cohort involving 1194 patients with 1520 hospitalizations for severe sepsis drawn from the Health and Retirement Study, a nationally representative survey of US residents (1998-2006). A total of 9223 respondents had a baseline cognitive and functional assessment and had linked Medicare claims; 516 survived severe sepsis and 4517 survived a nonsepsis hospitalization to at least 1 follow-up survey and are included in the analysis. MAIN OUTCOME MEASURES: Personal interviews were conducted with respondents or proxies using validated surveys to assess the presence of cognitive impairment and to determine the number of activities of daily living (ADLs) and instrumental ADLs (IADLs) for which patients needed assistance. RESULTS: Survivors' mean age at hospitalization was 76.9 years. The prevalence of moderate to severe cognitive impairment increased 10.6 percentage points among patients who survived severe sepsis, an odds ratio (OR) of 3.34 (95% confidence interval [CI], 1.53-7.25) in multivariable regression. Likewise, a high rate of new functional limitations was seen following sepsis: in those with no limits before sepsis, a mean 1.57 new limitations (95% CI, 0.99-2.15); and for those with mild to moderate limitations before sepsis, a mean of 1.50 new limitations (95% CI, 0.87-2.12). In contrast, nonsepsis general hospitalizations were associated with no change in moderate to severe cognitive impairment (OR, 1.15; 95% CI, 0.80-1.67; P for difference vs sepsis = .01) and with the development of fewer new limitations (mean among those with no limits before hospitalization, 0.48; 95% CI, 0.39-0.57; P for difference vs sepsis <.001 and mean among those with mild to moderate limits, 0.43; 95% CI, 0.23-0.63; P for difference = .001). The declines in cognitive and physical function persisted for at least 8 years. CONCLUSIONS: Severe sepsis in this older population was independently associated with substantial and persistent new cognitive impairment and functional disability among survivors. The magnitude of these new deficits was large, likely resulting in a pivotal downturn in patients' ability to live independently.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Case-Control Studies; Cognition Disorders; Disabled Persons; Female; Health Status; Hospitalization; Humans; Male; Prospective Studies; Sepsis; Severity of Illness Index; Survivors; United States

Modifiable risk factors for incidence of pain in older adults. - Yu Shi; Hooten, W Michael; Rosebud O. Roberts; David O. Warner (Pain, 2010)
Pain symptoms in aging populations have significant public health impact. The aim of this study was to determine risk factors for the incidence of pain in older adults, focusing on those factors that can be modified. Secondary analyses were performed of survey data from the nationally representative Health and Retirement Study of US adults older than 50 years. Generalized estimating equations logistic regressions were used to evaluate the effect of selected variables on the incidence of pain using biennial (1992 through 2006) data, determining the relationship between the incidence of pain and the potential risk factors. Of the 18,439 survey respondents in 2006, 34.1% (95% CI: 33.2%, 35.0%) reported that they were often troubled by pain; 24.3% reported having moderate to severe pain; and 22.3% reported that their daily life was affected by pain. Between 1992 and 2006, 7967 individuals reported new onset of pain in 169,762 person-years of follow-up, an incidence of 4.69 (4.59, 4.80) per 100 person-years. Depression and being overweight were independent predictors associated with an increased likelihood of incident pain. Current smoking increased the likelihood of incident pain only in those subjects who also reported depression. In conclusion, pain is a common symptom in older adults. Depression, smoking, and overweight are potentially modifiable risk factors and could be considered in the prevention and management of pain in older adults.
Keywords: Age Factors; Aged; Aged, 80 and over; Cross-Sectional Studies; Demography; depression; Female; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Overweight; pain; Prevalence; Retrospective Studies; Risk Assessment; Risk Factors; Smoking; United States

Obesity and excess mortality among the elderly in the United States and Mexico. - Monteverde, Malena; Noronha, Kenya; Alberto Palloni; Beatriz Novak (Demography, 2010)
Increasing levels of obesity could compromise future gains in life expectancy in low- and high-income countries. Although excess mortality associated with obesity and, more generally, higher levels of body mass index (BAI) have been investigated in the United States, there is little research about the impact of obesity on mortality in Latin American countries, where very the rapid rate of growth of prevalence of obesity and overweight occur jointly with poor socioeconomic conditions. The aim of this article is to assess the magnitude of excess mortality due to obesity and overweight in Mexico and the United States. For this purpose, we take advantage of two comparable data sets: the Health and Retirement Study 2000 and 2004 for the United States, and the Mexican Health and Aging Study 2001 and 2003 for Mexico. We find higher excess mortality risks among obese and overweight individuals aged 60 and older in Mexico than in the United States. Yet, when analyzing excess mortality among different socioeconomic strata, we observe greater gaps by education in the United States than in Mexico. We also find that although the probability of experiencing obesity-related chronic diseases among individuals with high BMI is larger for the U.S. elderly, the relative risk of dying conditional on experiencing these diseases is higher in Mexico.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Chronic disease; Female; Humans; Logistic Models; Male; Mexico; Middle Aged; Mortality; Multivariate Analysis; Obesity; Risk Factors; Socioeconomic factors; United States

Obesity, physical activity, and depressive symptoms in a cohort of adults aged 51 to 61. - Dianna D Carroll; Heidi M Blanck; Mary K. Serdula; David R Brown (J Aging Health, 2010)
OBJECTIVE: To determine associations between changes in obesity and vigorous physical activity (PA) status and depressive symptoms in a cohort aged 51 to 61 years at baseline. METHOD: Two waves (1992, 1998) of Health and Retirement Study data were used to divide participants into four obesity and four vigorous PA status categories based on change in or maintenance of their 1992 status in 1998. Depressive symptoms were defined as the upper quintile score (women >/= 4, men >/= 3) on the eight-item Center for Epidemiologic Studies-Depression Scale. Logistic regression determined adjusted odds ratios for depressive symptoms associated with obesity and vigorous PA status. RESULTS: Among men, no significant associations were found. Among women, decreasing from high vigorous PA status and maintenance of obese status were independently associated with increased odds for depressive symptoms in 1998. DISCUSSION: The findings illustrate the importance of examining gender differences in studies of risk factors for depression.
Keywords: Activities of Daily Living; Age Factors; Aging; Chi-Square Distribution; Cohort Studies; Confidence Intervals; depression; Female; Health Status; Humans; Logistic Models; Male; Middle Aged; Motor Activity; Multivariate Analysis; Obesity; Odds Ratio; Psychometrics; Self Report; Sex Factors; United States

Out-of-pocket burden of health care spending and the adequacy of the Medicare Part D low-income subsidy. - Becky A. Briesacher; Ross-Degnan, Dennis; Anita K Wagner; Hassan Fouayzi; Fang Zhang; Jerry Gurwitz; Soumerai, Stephen B (Med Care, 2010)
BACKGROUND: Evaluating the adequacy of Medicare prescription drug program (Part D) and its low-income subsidy (LIS) requires a comprehensive understanding of drug spending in relation to household resources. OBJECTIVE: : To estimate out-of-pocket health care costs in the year before Part D, in context of total household spending, health status, and LIS eligibility. RESEARCH DESIGN: Nationally representative cross-sectional study. SUBJECTS: Two thousand two hundred thirty-one Medicare families in the 2005/2006 Health and Retirement Study. METHODS: We assessed health care costs as a share of household resources remaining after spending on essential housing, food, personal care, and transportation. Burdensome health care costs were defined as exceeding 40% of nonessential resources. We used logistic regressions to assess the probability of incurring burdensome health expenditures, controlling for LIS eligibility. RESULTS: In the year before Part D, more than half of Medicare families [56.0%; 95% confidence interval (CI): 55.3-59.9] experienced burdensome health care costs. Families in poor health allocated a median of 68.1% [interquartile range (IQR): 35.1-82.9] of nonessential resources to health care (compared with 34.0% median; IQR 11.9-52.2 among families in excellent health, P < 0.011). Most (64%) out-of-pocket health care spending was allocated to health insurance premiums and medications. As many as 26% of Medicare families had burdensome health care costs but were not eligible for LIS assistance. CONCLUSIONS: Before Part D, burdensome health care expenditures were common in Medicare families. Our estimates of Part D and LIS benefits indicate a limited scope of relief.
Keywords: Adult; Aged; Confidence Intervals; Cost of Illness; Deductibles and Coinsurance; Drug Prescriptions; Female; Financing, Personal; Health Expenditures; Humans; Income; Male; Medicare Part D; Middle Aged; Odds Ratio; Poverty; Socioeconomic factors; United States

Prevalence and predictors of fatigue in middle-aged and older adults: evidence from the health and retirement study. - Meng, Hongdao; Hale, Lauren; Friedberg, Fred (J Am Geriatr Soc, 2010)
Keywords: Aged; Aged, 80 and over; Fatigue; Female; Health Surveys; Humans; Male; Middle Aged; Prevalence; Retirement; Retrospective Studies; Survival Rate; United States

Prevalence of neuropsychiatric symptoms and their association with functional limitations in older adults in the United States: the aging, demographics, and memory study. - Okura, Toru; Brenda L Plassman; David C Steffens; David J Llewellyn; Guy G Potter; Kenneth M. Langa (J Am Geriatr Soc, 2010)
OBJECTIVES: To estimate the prevalence of neuropsychiatric symptoms and examine their association with functional limitations. DESIGN: Cross-sectional analysis. SETTING: The Aging, Demographics, and Memory Study (ADAMS). PARTICIPANTS: A sample of adults aged 71 and older (N=856) drawn from Health and Retirement Study (HRS), a nationally representative cohort of U.S. adults aged 51 and older. MEASUREMENTS: The presence of neuropsychiatric symptoms (delusions, hallucinations, agitation, depression, apathy, elation, anxiety, disinhibition, irritation, and aberrant motor behaviors) was identified using the Neuropsychiatric Inventory. A consensus panel in the ADAMS assigned a cognitive category (normal cognition; cognitive impairment, no dementia (CIND); mild, moderate, or severe dementia). Functional limitations, chronic medical conditions, and sociodemographic information were obtained from the HRS and ADAMS. RESULTS: Forty-three percent of individuals with CIND and 58% of those with dementia exhibited at least one neuropsychiatric symptom. Depression was the most common individual symptom in those with normal cognition (12%), CIND (30%), and mild dementia (25%), whereas apathy (42%) and agitation (41%) were most common in those with severe dementia. Individuals with three or more symptoms and one or more clinically significant symptoms had significantly higher odds of having functional limitations. Those with clinically significant depression had higher odds of activity of daily living limitations, and those with clinically significant depression, anxiety, or aberrant motor behaviors had significantly higher odds of instrumental activity of daily living limitations. CONCLUSION: Neuropsychiatric symptoms are highly prevalent in older adults with CIND and dementia. Of those with cognitive impairment, a greater number of total neuropsychiatric symptoms and some specific individual symptoms are strongly associated with functional limitations.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Behavioral Symptoms; Cognition Disorders; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Disorders; Prevalence; United States

Prior hospitalization and the risk of heart attack in older adults: a 12-year prospective study of Medicare beneficiaries. - Frederic D Wolinsky; Suzanne E Bentler; Li Liu; Michael P Jones; Kaskie, Brian; Jason Hockenberry; Elizabeth A Chrischilles; Kara B Wright; John F Geweke; Maksym Obrizan; Robert L. Ohsfeldt; Gary E Rosenthal; et al. (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: We investigated whether prior hospitalization was a risk factor for heart attacks among older adults in the survey on Assets and Health Dynamics among the Oldest Old. METHODS: Baseline (1993-1994) interview data were linked to 1993-2005 Medicare claims for 5,511 self-respondents aged 70 years and older and not enrolled in managed Medicare. Primary hospital International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) 410.xx discharge codes identified postbaseline hospitalizations for acute myocardial infarctions (AMIs). Participants were censored at death or postbaseline managed Medicare enrollment. Traditional risk factors and other covariates were included. Recent postbaseline non-AMI hospitalizations (ie, prior hospitalizations) were indicated by a time-dependent marker, and sensitivity analyses identified their peak effect. RESULTS: The total number of person-years of surveillance was 44,740 with a mean of 8.1 (median = 9.1) per person. Overall, 483 participants (8.8%) suffered postbaseline heart attacks, with 423 participants (7.7%) having their first-ever AMI. As expected, significant traditional risk factors were sex (men); race (whites); marital status (never being married); education (noncollege); geography (living in the South); and reporting a baseline history of angina, arthritis, diabetes, and heart disease. Risk factors were similar for both any postbaseline and first-ever postbaseline AMI analyses. The time-dependent recent non-AMI hospitalization marker did not alter the effects of the traditional risk factors but increased AMI risk by 366% (adjusted hazards ratio = 4.66, p < .0001). Discussion. Our results suggest that some small percentage (<3%) of heart attacks among older adults might be prevented if effective short-term postdischarge planning and monitoring interventions were developed and implemented.
Keywords: Aged; Educational Status; Female; Hospitalization; Humans; Male; Marital Status; Medicare; Myocardial Infarction; Patient Discharge; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Factors; United States

Recent developments in longitudinal studies of aging in the United States. - Hauser, Robert M.; David R Weir (Demography, 2010)
We review recent developments in longitudinal studies of aging, focusing on the Wisconsin Longitudinal Study (WLS) and the Health and Retirement Study (HRS). Both studies are part of a trend toward biosocial surveys in which biological measurement is joined with traditional survey techniques, and a related trend toward greater harmonization across studies. Both studies have collected DNA samples and are working toward genotyping that would allow broadly based association studies. Increased attention to psychological measurement of personality and of cognitive ability using adaptive testing structures has also been shared across the studies. The HRS has expanded its economic measurement to longitudinal studies of consumption and to broader-based measurement of pension and Social Security wealth. It has added biomarkers of cardiovascular risk. The WLS has developed an integrated approach to the study of death and bereavement and an innovative use of high school yearbook photographs to capture information about health in early life of its participants.
Keywords: Aging; Data collection; Demography; Genome-Wide Association Study; Health Status Indicators; Health Surveys; Humans; Longitudinal Studies; Research Design; Socioeconomic factors; United States

Reforming beneficiary cost sharing to improve Medicare performance. - Zuckerman, Stephen; Shang, Baoping; Timothy A Waidmann (Inquiry, 2010)
This paper explores options for reforming Medicare cost sharing in an effort to provide better financial protection for those beneficiaries with the greatest health care needs. Using data from the Health and Retirement Study (HRS) and the Medicare Current Beneficiary Survey (MCBS), we consider how unified annual deductibles, alternative coinsurance rates, and a limit on out-of-pocket spending would alter program spending, beneficiary cost sharing, and premiums for supplemental coverage. We show that adding an out-of-pocket limit and raising deductibles and coinsurance slightly would provide better safeguards to beneficiaries with high costs than the current Medicare benefit structure. Our estimates also suggest that policies protecting these beneficiaries could be structured in a way that would add little to overall program costs.
Keywords: Aged; Aged, 80 and over; Cost Sharing; Health Expenditures; Humans; Medicare; Middle Aged; Models, Economic; United States

The role of health behaviors in mediating the relationship between depressive symptoms and glycemic control in type 2 diabetes: a structural equation modeling approach. - Chiu, Ching-Ju; Linda A. Wray; Elizabeth A Beverly; Oralia G Dominic (Soc Psychiatry Psychiatr Epidemiol, 2010)
OBJECTIVES: We investigated the longitudinal association between depressive symptoms and glycemic control (HbA1c) in adults with type 2 diabetes, and the extent to which that association was explained by health behaviors. METHODS: This study assessed data on 998 adults (aged 51 and above) with type 2 diabetes in the US nationally representative Health and Retirement Study and its diabetes-specific mail survey. Participants' depressive symptoms and baseline health behaviors (exercise, body weight control, and smoking status) were collected in 1998. Follow-up health behaviors and the glycemic control outcome were measured at a 2- and 5-year intervals, respectively. RESULTS: Nearly one in four of participants (23%) reported moderate or high levels of depressive symptoms at baseline (CES-D score >or=3). Adults with higher levels of depressive symptoms at baseline showed lower scores on baseline and follow-up health behaviors as well as higher HbA1c levels at a 5-year follow-up. Structural equation models (SEM) reveal that health behaviors accounted for 13% of the link between depressive symptoms and glycemic control. CONCLUSIONS: The long-term relationship between depressive symptoms and glycemic control was supported in the present study. Health behaviors, including exercise, body weight control, and smoking status, explained a sizable amount of the association between depressive symptoms and glycemic control. More comprehensive diabetes self-care behaviors should be examined with available data. Other competing explicators for the link, such as endocrinological process and antidepressant effects, also warrant further examination.
Keywords: Adult; Aged; Blood Glucose; Body Weight; Comorbidity; depression; Diabetes Mellitus, Type 2; Female; Follow-Up Studies; Glycated Hemoglobin; Glycemic Index; Health Behavior; Health Surveys; Humans; Life Style; Longitudinal Studies; Male; Middle Aged; Models, Statistical; Self Care; Smoking; United States

Self-reported versus measured height and weight in the health and retirement study. - Meng, Hongdao; Xiaoxing He; Dixon, Denise (J Am Geriatr Soc, 2010)
Keywords: Aged; Body Height; Body Weight; Female; Humans; Male; Middle Aged; Obesity; Population Surveillance; Prevalence; Reproducibility of Results; Sensitivity and Specificity; United States

Sociodemographic and health-related risks for loneliness and outcome differences by loneliness status in a sample of U.S. older adults. - Laurie A. Theeke (Res Gerontol Nurs, 2010)
This study assesses sociodemographic and health-related factors associated with loneliness and outcome differences between loneliness groups using a sample of 13,812 older adults from the U.S Health and Retirement Study. Descriptive and bivariate analyses were followed by logistic regression to evaluate risks and analysis of covariance testing to determine outcome differences. Overall, prevalence of loneliness was 16.9%. Nonmarried status, poorer self-report of health, lower educational level, functional impairment, increasing number of chronic illnesses, younger age, lower income, and less people living in the household were all associated with loneliness. The chronically lonely group reported less exercise, more tobacco use, less alcohol use, a greater number of chronic illnesses, higher depression scores, and greater average number of nursing home stays. Future research evaluating the effectiveness of both prevention and treatment interventions for loneliness in older adults would provide empirical data to further guide gerontological nursing practice.
Keywords: Aged; Aged, 80 and over; Female; Health Status; Humans; Logistic Models; Loneliness; Male; Middle Aged; Multivariate Analysis; Risk Factors; Socioeconomic factors; United States

Stability and changes in living arrangements: relationship to nursing home admission and timing of placement. - Judith D Kasper; Liliana E Pezzin; Rice, J Bradford (J Gerontol B Psychol Sci Soc Sci, 2010)
OBJECTIVES: To examine whether stability of living arrangements and changes in household composition-both types and frequency-influence nursing home placement or timing to entry among older people. METHODS: Data from the first 5 waves of the Assets and Health Dynamics of the Elderly (1993-2002) on 8,093 persons aged 70 years or older at baseline are used in probit and hazard models to predict nursing home entry and time to entry. RESULTS: Stable living arrangements carry different risks of institutionalization. Those living continuously alone or with others were at highest risk; at lowest risk were those living continuously with a spouse or the same child (lowest overall). Changes in household composition were protective against nursing home entry and slowed time to entry; types of change were not influential when number of changes was taken into account. DISCUSSION: Results suggest that stability of living arrangements in and of itself is not protective against institutionalization. Having options that allow one to change living arrangements over time in response to changing needs for assistance is of importance if the goal is to avoid institutional care or extend community residence prior to entry.
Keywords: Aged; Aged, 80 and over; Family Characteristics; Female; Health Status; Homes for the Aged; Humans; Institutionalization; Male; Marital Status; Multivariate Analysis; Nursing homes; Risk Factors; Single Person; Socioeconomic factors; Time Factors; United States

Successful aging in the United States: prevalence estimates from a national sample of older adults. - Sara J McLaughlin; Cathleen M. Connell; Steven G Heeringa; Lydia W Li; J Scott Roberts (J Gerontol B Psychol Sci Soc Sci, 2010)
OBJECTIVES: To estimate the prevalence of successful aging in the United States, with the broad aim of contributing to the dialogue on Rowe and Kahn's concept of successful aging. METHODS: Using data from the Health and Retirement Study, the prevalence of successful aging was calculated for adults aged 65 years and older at four time points: 1998, 2000, 2002, and 2004. Successful aging was operationalized in accordance with Rowe and Kahn's definition, which encompasses disease and disability, cognitive and physical functioning, social connections, and productive activities. RESULTS: No greater than 11.9% of older adults were aging "successfully" in any year. The adjusted odds of successful aging were generally lower for those of advanced age, male gender, and lower socioeconomic status. Between 1998 and 2004, the odds of successful aging declined by 25%, after accounting for demographic changes in the older population. DISCUSSION: Few older adults meet the criteria put forth in Rowe and Kahn's definition of successful aging, suggesting the need for modification if the concept is to be used for broad public health purposes. Disparities in successful aging were evident for socially defined subgroups, highlighting the importance of structural factors in enabling successful aging.
Keywords: Affect; Aged; Aging; Female; Health Status; Humans; Male; Middle Aged; Prevalence; United States

Surgery as a teachable moment for smoking cessation. - Yu Shi; David O. Warner (Anesthesiology, 2010)
BACKGROUND: A "teachable moment" is an event that motivates spontaneous behavior change. Some evidence suggests that major surgery for a smoking-related illness can serve as a teachable moment for smoking cessation. This study tested the hypotheses that surgery increases the likelihood of smoking cessation and that cessation is more likely after major surgical procedures compared with outpatient surgery. METHODS: Secondary analyses were performed of longitudinal biennial survey data (1992-2004) from the nationally representative Health and Retirement Study of U.S. adults older than 50 yr, determining the relationship between the incidence of smoking cessation and the occurrence of surgery. RESULTS: Five thousand four hundred ninety-eight individuals reported current smoking at enrollment, and 2,444 of them (44.5%) quit smoking during the period of examination. The incidence of quitting in smokers undergoing major surgery was 20.6/100 person-years of follow-up and 10.2/100 person-years in those undergoing outpatient surgery. In a multivariate negative binomial regression model, the incidence rate ratio of quitting associated with major surgery was 2.02 (95% CI: 1.67-2.44) and that of those associated with outpatient surgery was 1.28 (95% CI: 1.09-1.50). Estimates derived from national surgical utilization data show that approximately 8% of all quit events in the United States annually can be attributed to the surgical procedures analyzed. CONCLUSIONS: Undergoing surgery is associated with an increased likelihood of smoking cessation in the older U.S. population. Cessation is more likely in association with major procedures compared with outpatient surgery. These data support the concept that surgery is a teachable moment for smoking cessation.
Keywords: Aged; Aged, 80 and over; Ambulatory Surgical Procedures; Analysis of Variance; Cohort Studies; Female; Follow-Up Studies; General Surgery; Humans; Longitudinal Studies; Male; Middle Aged; Patient Education as Topic; Regression Analysis; Smoking cessation; Treatment Outcome; United States

Take-up of Medicare Part D: results from the Health and Retirement Study. - Helen G Levy; David R Weir (J Gerontol B Psychol Sci Soc Sci, 2010)
OBJECTIVES: To estimate the impact of Medicare Part D on prescription drug coverage among elderly Medicare beneficiaries and to analyze the predictors of program enrollment ("take-up") among those with no prior drug coverage. METHODS: Multivariate analyses of data from the 2002, 2004, and 2006 waves of the Health and Retirement Study. RESULTS: Take-up of Part D among those without drug coverage in 2004 was high; about 50%-60% of this group had Part D coverage in 2006. Only 7% of senior citizens lacked drug coverage in 2006 compared with 24% in 2004. Demand for prescription drugs was the most important determinant of the decision to enroll in Part D among those with no prior coverage. Many of those who remained without coverage in 2006 reported that they do not use prescribed medicines, and the majority had relatively low out-of-pocket spending. CONCLUSION: For the most part, Medicare beneficiaries seem to have been able to make economically rational decisions about Part D enrollment despite the complexity of the program.
Keywords: Aged; ethnicity; Humans; Longitudinal Studies; Medically Uninsured; Medicare Part D; Multivariate Analysis; Poverty; prescription drugs; Prescription Fees; United States

Untreated poor vision: a contributing factor to late-life dementia. - Mary A M Rogers; Kenneth M. Langa (Am J Epidemiol, 2010)
Ophthalmologic abnormalities have been described in patients with dementia, but the extent to which poor vision and treatment for visual disorders affect cognitive decline is not well defined. Linked data from the Health and Retirement Study and Medicare files (1992-2005) were used to follow the experiences of 625 elderly US study participants with normal cognition at baseline. The outcome was a diagnosis of dementia, cognitively impaired but no dementia, or normal cognition. Poor vision was associated with development of dementia (P = 0.0048); individuals with very good or excellent vision at baseline had a 63% reduced risk of dementia (95% confidence interval (CI): 20, 82) over a mean follow-up period of 8.5 years. Participants with poorer vision who did not visit an ophthalmologist had a 9.5-fold increased risk of Alzheimer disease (95% CI: 2.3, 39.5) and a 5-fold increased risk of cognitively impaired but no dementia (95% CI: 1.6, 15.9). Poorer vision without a previous eye procedure increased the risk of Alzheimer disease 5-fold (95% CI: 1.5, 18.8). For Americans aged 90 years or older, 77.9% who maintained normal cognition had received at least one previous eye procedure compared with 51.7% of those with Alzheimer disease. Untreated poor vision is associated with cognitive decline, particularly Alzheimer disease.
Keywords: Aged, 80 and over; Cognition Disorders; Dementia; Female; Humans; Logistic Models; Male; Medicare; Ophthalmology; Patient Acceptance of Health Care; Risk Factors; United States; Vision Disorders

A 12-year prospective study of stroke risk in older Medicare beneficiaries. - Frederic D Wolinsky; Suzanne E Bentler; Elizabeth A Cook; Elizabeth A Chrischilles; Li Liu; Kara B Wright; John F Geweke; Maksym Obrizan; Claire E Pavlik; Robert L. Ohsfeldt; Michael P Jones; Robert B Wallace; et al. (BMC Geriatr, 2009)
BACKGROUND: 5.8 M living Americans have experienced a stroke at some time in their lives, 780K had either their first or a recurrent stroke this year, and 150K died from strokes this year. Stroke costs about $66B annually in the US, and also results in serious, long-term disability. Therefore, it is prudent to identify all possible risk factors and their effects so that appropriate intervention points may be targeted. METHODS: Baseline (1993-1994) interview data from the nationally representative Survey on Assets and Health Dynamics among the Oldest Old (AHEAD) were linked to 1993-2005 Medicare claims. Participants were 5,511 self-respondents >or= 70 years old. Two ICD9-CM case-identification approaches were used. Two approaches to stroke case-identification based on ICD9-CM codes were used, one emphasized sensitivity and the other emphasized specificity. Participants were censored at death or enrollment into managed Medicare. Baseline risk factors included sociodemographic, socioeconomic, place of residence, health behavior, disease history, and functional and cognitive status measures. A time-dependent marker reflecting post-baseline non-stroke hospitalizations was included to reflect health shocks, and sensitivity analyses were conducted to identify its peak effect. Competing risk, proportional hazards regression was used. RESULTS: Post-baseline strokes occurred for 545 (9.9%; high sensitivity approach) and 374 (6.8%; high specificity approach) participants. The greatest static risks involved increased age, being widowed or never married, living in multi-story buildings, reporting a baseline history of diabetes, hypertension, or stroke, and reporting difficulty picking up a dime, refusing to answer the delayed word recall test, or having poor cognition. Risks were similar for both case-identification approaches and for recurrent and first-ever vs. only first-ever strokes. The time-dependent health shock (recent hospitalization) marker did not alter the static model effect estimates, but increased stroke risk by 200% or more. CONCLUSION: The effect of our health shock marker (a time-dependent recent hospitalization indicator) was large and did not mediate the effects of the traditional risk factors. This suggests an especially vulnerable post-hospital transition period from adverse effects associated with both their underlying health shock (the reasons for the recent hospital admission) and the consequences of their treatments.
Keywords: Aged; Aged, 80 and over; Female; Humans; Insurance Benefits; Male; Medicare; Prospective Studies; Risk Factors; Socioeconomic factors; Stroke; United States

The accuracy of Medicare claims as an epidemiological tool: the case of dementia revisited. - Donald H. Taylor Jr.; Østbye, Truls; Kenneth M. Langa; David R Weir; Brenda L Plassman (J Alzheimers Dis, 2009)
Our study estimates the sensitivity and specificity of Medicare claims to identify clinically-diagnosed dementia, and documents how errors in dementia assessment affect dementia cost estimates. We compared Medicare claims from 1993-2005 to clinical dementia assessments carried out in 2001-2003 for the Aging Demographics and Memory Study (ADAMS) cohort (n = 758) of the Health and Retirement Study. The sensitivity and specificity of Medicare claims was 0.85 and 0.89 for dementia (0.64 and 0.95 for AD). Persons with dementia cost the Medicare program (in 2003) $7,135 more than controls (P < 0.001) when using claims to identify dementia, compared to $5,684 more when using ADAMS (P < 0.001). Using Medicare claims to identify dementia results in a 110% increase in costs for those with dementia as compared to a 68% increase when using ADAMS to identify disease, net of other variables. Persons with false positive Medicare claims notations of dementia were the most expensive group of subjects ($11,294 versus $4,065, for true negatives P < 0.001). Medicare claims overcount the true prevalence of dementia, but there are both false positive and negative assessments of disease. The use of Medicare claims to identify dementia results in an overstatement of the increase in Medicare costs that are due to dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Cohort Studies; Dementia; Female; Health Care Costs; Humans; Insurance Claim Reporting; Male; Medicare; Prevalence; Sensitivity and Specificity; United States

The aftermath of hip fracture: discharge placement, functional status change, and mortality. - Suzanne E Bentler; Li Liu; Maksym Obrizan; Elizabeth A Cook; Kara B Wright; John F Geweke; Elizabeth A Chrischilles; Claire E Pavlik; Robert B Wallace; Robert L. Ohsfeldt; Michael P Jones; Gary E Rosenthal; et al. (Am J Epidemiol, 2009)
The authors prospectively explored the consequences of hip fracture with regard to discharge placement, functional status, and mortality using the Survey on Assets and Health Dynamics Among the Oldest Old (AHEAD). Data from baseline (1993) AHEAD interviews and biennial follow-up interviews were linked to Medicare claims data from 1993-2005. There were 495 postbaseline hip fractures among 5,511 respondents aged >or=69 years. Mean age at hip fracture was 85 years; 73% of fracture patients were white women, 45% had pertrochanteric fractures, and 55% underwent surgical pinning. Most patients (58%) were discharged to a nursing facility, with 14% being discharged to their homes. In-hospital, 6-month, and 1-year mortality were 2.7%, 19%, and 26%, respectively. Declines in functional-status-scale scores ranged from 29% on the fine motor skills scale to 56% on the mobility index. Mean scale score declines were 1.9 for activities of daily living, 1.7 for instrumental activities of daily living, and 2.2 for depressive symptoms; scores on mobility, large muscle, gross motor, and cognitive status scales worsened by 2.3, 1.6, 2.2, and 2.5 points, respectively. Hip fracture characteristics, socioeconomic status, and year of fracture were significantly associated with discharge placement. Sex, age, dementia, and frailty were significantly associated with mortality. This is one of the few studies to prospectively capture these declines in functional status after hip fracture.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; depression; Female; Health Status; Health Status Indicators; Hip Fractures; Humans; Interviews as Topic; Iowa; Length of Stay; Logistic Models; Medicare; Patient Discharge; Prospective Studies; Psychometrics; Socioeconomic factors; Time Factors; Treatment Outcome; United States

Are mature smokers misinformed? - Ahmed Khwaja; Daniel S. Silverman; Frank A Sloan; Wang, Yang (J Health Econ, 2009)
While there are many reasons to continue to smoke in spite of its consequences for health, the concern that many smoke because they misperceive the risks of smoking remains a focus of public discussion and motivates tobacco control policies and litigation. In this paper we investigate the relative accuracy of mature smokers' risk perceptions about future survival, and a range of morbidities and disabilities. Using data from the survey on smoking (SOS) conducted for this research, we compare subjective beliefs elicited from the SOS with corresponding individual-specific objective probabilities estimated from the health and retirement study. Overall, consumers in the age group studied, 50-70, are not overly optimistic in their perceptions of health risk. If anything, smokers tend to be relatively pessimistic about these risks. The finding that smokers are either well informed or pessimistic regarding a broad range of health risks suggests that these beliefs are not pivotal in the decision to continue smoking. Although statements by the tobacco companies may have been misleading and thus encouraged some to start smoking, we find no evidence that systematic misinformation about the health consequences of smoking inhibits quitting.
Keywords: Aged; Deception; Female; Health Knowledge, Attitudes, Practice; Health Surveys; Humans; Male; Middle Aged; Risk Assessment; Smoking; United States

The benefits of risk factor prevention in Americans aged 51 years and older. - Dana P Goldman; Yuhui Zheng; Girosi, Federico; Pierre-Carl Michaud; S Jay Olshansky; David M Cutler; John W Rowe (Am J Public Health, 2009)
OBJECTIVES: We assessed the potential health and economic benefits of reducing common risk factors in older Americans. METHODS: A dynamic simulation model tracked a national cohort of persons 51 and 52 years of age to project their health and medical spending in prevention scenarios for diabetes, hypertension, obesity, and smoking. RESULTS: The gain in life span from successful treatment of a person aged 51 or 52 years for obesity would be 0.85 years; for hypertension, 2.05 years; and for diabetes, 3.17 years. A 51- or 52-year-old person who quit smoking would gain 3.44 years. Despite living longer, those successfully treated for obesity, hypertension, or diabetes would have lower lifetime medical spending, exclusive of prevention costs. Smoking cessation would lead to increased lifetime spending. We used traditional valuations for a life-year to calculate that successful treatments would be worth, per capita, $198,018 (diabetes), $137,964 (hypertension), $118,946 (smoking), and $51,750 (obesity). CONCLUSIONS: Effective prevention could substantially improve the health of older Americans, and--despite increases in longevity--such benefits could be achieved with little or no additional lifetime medical spending.
Keywords: Diabetes Mellitus; Health Care Costs; health policy; Health Promotion; Humans; Hypertension; Middle Aged; Models, Biological; Models, Economic; Obesity; Quality-Adjusted Life Years; Risk Reduction Behavior; Smoking; Smoking Prevention; United States

Bridge employment and retirees' health: a longitudinal investigation. - Zhan, Yujie; Wang, Mo; Liu, Songqi; Kenneth S. Shultz (J Occup Health Psychol, 2009)
The present study examined the relationship between bridge employment and retirees' health outcomes (i.e., major diseases, functional limitations, and mental health). We used a nationally representative sample of 12,189 retirees from the first 4 waves of the Health and Retirement Study. Hierarchical regression analyses showed that compared with full retirement, engaging in bridge employment either in a career field or in a different field was associated with fewer major diseases and functional limitations, whereas engaging in career bridge employment was associated with better mental health. The findings highlight the health benefits of engaging in bridge employment for retirees. The practical implications of this study are discussed at both the individual and policy levels. Limitations of the current findings are also noted in conjunction with future research directions.
Keywords: Employment; Female; Health Status; Humans; Interviews as Topic; Longitudinal Studies; Male; Middle Aged; Retirement; United States

Can self-reported strokes be used to study stroke incidence and risk factors?: evidence from the health and retirement study. - M. Maria Glymour; Mauricio Avendano (Stroke, 2009)
BACKGROUND AND PURPOSE: Most stroke incidence studies use geographically localized (community) samples with few national data sources available. Such samples preclude research on contextual risk factors, but national samples frequently collect only self-reported stroke. We examine whether incidence estimates from clinically verified studies are consistent with estimates from a nationally representative US sample assessing self-reported stroke. METHODS: Health and Retirement Study (HRS) participants (n=17 056) age 50+ years were followed for self- or proxy-reported first stroke (1293 events) from 1998 to 2006 (average, 6.8 years). We compared incidence rates by race, sex, and age strata with those previously documented in leading geographically localized studies with medically verified stroke. We also examined whether cardiovascular risk factor effect estimates in HRS are comparable to those reported in studies with clinically verified strokes. RESULTS: The weighted first-stroke incidence rate was 10.0 events/1000 person-years. Total age-stratified incidence rates in whites were mostly comparable with those reported elsewhere and were not systematically higher or lower. However, among blacks in HRS, incidence rates generally appeared higher than those previously reported. HRS estimates were most comparable with those reported in the Cardiovascular Health Study. Incidence rates approximately doubled per decade of age and were higher in men and blacks. After demographic adjustment, all risk factors predicted stroke incidence in whites. Smoking, hypertension, diabetes, and heart disease predicted incident stroke in blacks. CONCLUSIONS: Associations between known risk factors and stroke incidence were verified in HRS, suggesting that misreporting is nonsystematic. HRS may provide valuable data for stroke surveillance and examination of classical and contextual risk factors.
Keywords: Age Factors; Aged; Aged, 80 and over; Algorithms; Epidemiologic Methods; ethnicity; Female; Humans; Longitudinal Studies; Male; Middle Aged; Retirement; Risk Factors; Sex Factors; Stroke; Treatment Outcome; United States

Cancer survivorship, health insurance, and employment transitions among older workers. - Tunceli, Kaan; Pamela F. Short; John R. Moran; Tunceli, Ozgur (Inquiry, 2009)
This study examined the effect of job-related health insurance on employment transitions (labor force exits, reductions in hours, and job changes) of older working cancer survivors. Using multivariate models, we compared longitudinal data for the period 1997-2002 from the Penn State Cancer Survivor Study to similar data for workers with no cancer history in the Health and Retirement Study, who were also ages 55 to 64 at follow-up. The interaction of cancer survivorship with health insurance at diagnosis was negative and significant in predicting labor force exits, job changes, and transitions to part-time employment for both genders. The differential effect of job-related health insurance on the labor market dynamics of cancer survivors represents an additional component of the economic and psychosocial burden of cancer on survivors.
Keywords: Career Mobility; Cohort Studies; Female; Health Benefit Plans, Employee; Health Insurance Portability and Accountability Act; Humans; Longitudinal Studies; Male; Middle Aged; Models, Statistical; Neoplasms; Retirement; Survivors; United States

Changes in functional status among persons over age sixty-five undergoing total knee arthroplasty. - Frank A Sloan; Ruiz, David; Alyssa C Platt (Med Care, 2009)
BACKGROUND: This study assessed changes in physical functional status following receipt of total knee arthroplasty (TKA) for patients diagnosed with osteoarthritis (OA) of the knee in a national sample of persons aged 65+ in the United States relative to a sample of similar OA patients who did not receive TKA. METHODS: Data from the Health Retirement Survey (HRS) and linked Medicare claims from 1994 to 2006 were used to identify persons with diagnoses of OA of the lower leg who received a TKA (n = 516) and those who did not receive TKA (n = 1756). Predicted probabilities of receiving total knee arthroplasty from logit analysis were used for matching TKA and comparison groups on demographic, socioeconomic, and baseline functional status factors. Functional status measures were: mobility, gross motor function, large muscle, and limitations in activities of daily living (ADL). Average treatment effects of the treated (ATT), which compares changes in functional status between those who received TKA with similar individuals who did not receive TKA, were computed using propensity score matching. RESULTS: Mobility (average treatment effect of the treated (ATT = 0.315; 95% CI: 0.118-0.512), gross motor function (ATT = 0.314; 95% CI: 0.156-0.472), and ADL limitations (ATT = 0.174; 95% CI: 0.055-0.293), improved among persons receiving TKA relative to the comparison group. Relative to the mean values of the physical function at baseline, mobility, gross motor function, and ADL limitations persons receiving TKA had better functional outcomes than the comparison group by 17.5, 39.3, and 46.9 percent, respectively. CONCLUSIONS: TKA is effective in improving functional status in elderly persons.
Keywords: Activities of Daily Living; Aged; Arthroplasty, Replacement, Knee; Attitude to Health; Geriatric Assessment; Health Care Surveys; Health Status; Health Surveys; Humans; Insurance Claim Reporting; Logistic Models; Longitudinal Studies; Medicare; Mobility Limitation; Multivariate Analysis; Muscle Weakness; Osteoarthritis, Knee; pain; Sensitivity and Specificity; Surveys and Questionnaires; Treatment Outcome; United States

Childhood socioeconomic status and racial differences in disability: evidence from the Health and Retirement Study (1998-2006). - Mary E Bowen (Soc Sci Med, 2009)
This study used a life course approach to examine the ways in which childhood socioeconomic status (SES) may account for some of the racial differences in disability in later life. Eight years (5 waves) of longitudinal data from the US Health and Retirement Study (HRS; 1998-2006), a nationally representative sample of community-dwelling Black and White Americans over age 50 (N=14,588), were used in nonlinear multilevel models. Parental education and father's occupation were used to predict racial differences in activities of daily living (ADL) and instrumental activities of daily living (IADL). The role of adult SES (education, income, and wealth) and health behaviors (smoking, drinking alcohol, exercising, and being obese) were also examined and models were adjusted for health conditions (heart problems, diabetes, stroke, hypertension, cancer, lung disease, and arthritis). With the inclusion of childhood SES indicators, racial differences in ADL and IADL disability were reduced. Adult SES and health behaviors mediated some of the relationship between low childhood SES and disability, though low childhood SES continued to be associated with disability net of these. In support of a life course approach, these findings suggest that socioeconomic conditions in early life may have implications for racial differences in disability between older Black and older White adults.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Black or African American; Disabled Persons; Female; Health Behavior; Humans; Male; Middle Aged; Models, Statistical; Prejudice; Prospective Studies; Racial Groups; Social Justice; Socioeconomic factors; Statistics as Topic; United States; White People

Cognitive decline among patients with chronic obstructive pulmonary disease. - William W. Hung; Juan P. Wisnivesky; Albert L Siu; Joseph S. Ross (Am J Respir Crit Care Med, 2009)
RATIONALE: Prior research has suggested an association between chronic obstructive pulmonary disease (COPD) and the development of cognitive decline; however, these studies have been cross-sectional or small case series. OBJECTIVES: To determine whether COPD increases the risk of cognitive decline among older adults surveyed in a large, population-based longitudinal cohort. METHODS: We included data from the 1996 to 2002 waves of the Health and Retirement Study, a biennial nationally representative survey. We studied respondents who completed cognitive testing in 1996 and at least one subsequent survey, and excluded those with unknown history of COPD. Clinical history of COPD was based on self-report; severity was categorized based on use of oxygen or disease-related activity limitations. Our primary outcome was cognitive performance, measured using a validated 35-point scale. We examined the effect of COPD on cognition using multivariable mixed linear models accounting for repeated measurements, adjusted for sociodemographic and clinical characteristics. MEASUREMENTS AND MAIN RESULTS: A total of 4,150 adults were included in our study. Among them, 12% reported a history of COPD (29% severe, 71% nonsevere disease). On repeated measurement, mean cognition scores of older adults with both severe and nonsevere COPD were significantly lower when compared with adults without COPD (2.6 points [P < 0.001] and 0.9 points [P < 0.001], respectively). After multivariable adjustment, mean scores of adults with severe COPD remained lower (0.9 point [P < 0.001]), whereas mean score of adults with nonsevere COPD was no longer different (P = 0.39) when compared with adults without COPD. CONCLUSIONS: Severe COPD was associated with lower cognitive performance on standardized measurement over time.
Keywords: Aged; Case-Control Studies; Cognition Disorders; Female; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; Pulmonary Disease, Chronic Obstructive; Pulmonary Ventilation; Risk Factors; Severity of Illness Index; Socioeconomic factors; United States

Cognitive health among older adults in the United States and in England. - Kenneth M. Langa; David J Llewellyn; Iain A Lang; David R Weir; Robert B Wallace; Mohammed U Kabeto; Felicia A Huppert (BMC Geriatr, 2009)
BACKGROUND: Cognitive function is a key determinant of independence and quality of life among older adults. Compared to adults in England, US adults have a greater prevalence of cardiovascular risk factors and disease that may lead to poorer cognitive function. We compared cognitive performance of older adults in the US and England, and sought to identify sociodemographic and medical factors associated with differences in cognitive function between the two countries. METHODS: Data were from the 2002 waves of the US Health and Retirement Study (HRS) (n = 8,299) and the English Longitudinal Study of Ageing (ELSA) (n = 5,276), nationally representative population-based studies designed to facilitate direct comparisons of health, wealth, and well-being. There were differences in the administration of the HRS and ELSA surveys, including use of both telephone and in-person administration of the HRS compared to only in-person administration of the ELSA, and a significantly higher response rate for the HRS (87% for the HRS vs. 67% for the ELSA). In each country, we assessed cognitive performance in non-hispanic whites aged 65 and over using the same tests of memory and orientation (0 to 24 point scale). RESULTS: US adults scored significantly better than English adults on the 24-point cognitive scale (unadjusted mean: 12.8 vs. 11.4, P < .001; age- and sex-adjusted: 13.2 vs. 11.7, P < .001). The US cognitive advantage was apparent even though US adults had a significantly higher prevalence of cardiovascular risk factors and disease. In a series of OLS regression analyses that controlled for a range of sociodemographic and medical factors, higher levels of education and wealth, and lower levels of depressive symptoms, accounted for some of the US cognitive advantage. US adults were also more likely to be taking medications for hypertension, and hypertension treatment was associated with significantly better cognitive function in the US, but not in England (P = .014 for treatment x country interaction). CONCLUSION: Despite methodological differences in the administration of the surveys in the two countries, US adults aged >/= 65 appeared to be cognitively healthier than English adults, even though they had a higher burden of cardiovascular risk factors and disease. Given the growing number of older adults worldwide, future cross-national studies aimed at identifying the medical and social factors that might prevent or delay cognitive decline in older adults would make important and valuable contributions to public health.
Keywords: Aged; Aged, 80 and over; Aging; Cognition; Cognition Disorders; Cohort Studies; Cross-Sectional Studies; England; Female; Health Status; Humans; Longitudinal Studies; Male; Neuropsychological tests; United States

Comparing models of frailty: the Health and Retirement Study. - Christine T Cigolle; Mary Beth Ofstedal; Zhiyi Tian; Caroline S Blaum (J Am Geriatr Soc, 2009)
OBJECTIVES: To operationalize and compare three models of frailty, each representing a distinct theoretical view of frailty: as deficiencies in function (Functional Domains model), as an index of health burden (Burden model), and as a biological syndrome (Biologic Syndrome model). DESIGN: Cross-sectional analysis. SETTING: 2004 wave of the Health and Retirement Study, a nationally representative, longitudinal health interview survey. PARTICIPANTS: Adults aged 65 and older (N=11,113) living in the community and in nursing homes in the United States. MEASUREMENTS: The outcome measure was the presence of frailty, as defined according to each frailty model. Covariates included chronic diseases and sociodemographic characteristics. RESULTS: Almost one-third (30.2%) of respondents were frail according to at least one model; 3.1% were frail according to all three models. The Functional Domains model showed the least overlap with the other models. In contrast, 76.1% of those classified as frail according to the Biologic Syndrome model and 72.1% of those according to the Burden model were also frail according to at least one other model. Older adults identified as frail according to the different models differed in sociodemographic and chronic disease characteristics. For example, the Biologic Syndrome model demonstrated substantial associations with older age (adjusted odds ratio (OR)=10.6, 95% confidence interval (CI)=6.1-18.5), female sex (OR=1.7, 95% CI=1.2-2.5), and African-American ethnicity (OR=2.1, % CI=1.0-4.4). CONCLUSION: Different models of frailty, based on different theoretical constructs, capture different groups of older adults. The different models may represent different frailty pathways or trajectories to adverse outcomes such as disability and death.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic disease; Cross-Sectional Studies; Demography; Disability Evaluation; Frail Elderly; Geriatric Assessment; Health Surveys; Humans; Interviews as Topic; Logistic Models; Models, Theoretical; United States

The co-occurrence of chronic diseases and geriatric syndromes: the health and retirement study. - Pearl G. Lee; Christine T Cigolle; Caroline S Blaum (J Am Geriatr Soc, 2009)
OBJECTIVES: To analyze the co-occurrence, in adults aged 65 and older, of five conditions that are highly prevalent, lead to substantial morbidity, and have evidence-based guidelines for management and well-developed measures of medical care quality. DESIGN: Secondary data analysis of the 2004 wave of the Health and Retirement Study (HRS). SETTING: Nationally representative health interview survey. PARTICIPANTS: Respondents in the 2004 wave of the HRS aged 65 and older. MEASUREMENTS: Self-reported presence of five index conditions (three chronic diseases (coronary artery disease, congestive heart failure, and diabetes mellitus) and two geriatric syndromes (urinary incontinence and injurious falls)) and demographic information (age, sex, race, living situation, net worth, and education). RESULTS: Eleven thousand one hundred thirteen adults, representing 37.1 million Americans aged 65 and older, were interviewed. Forty-five percent were aged 76 and older, 58% were female, 8% were African American, and 4% resided in a nursing home. Respondents with more conditions were older and more likely to be female, single, and residing in a nursing home (all P<.001). Fifty-six percent had at least one of the five index conditions, and 23% had two or more. Of respondents with one condition, 20% to 55% (depending on the index condition) had two or more additional conditions. CONCLUSION: Five common conditions (3 chronic diseases, 2 geriatric syndromes) often co-occur in older adults, suggesting that coordinated management of comorbid conditions, both diseases and geriatric syndromes, is important. Care guidelines and quality indicators, rather than considering one condition at a time, should be developed to address comprehensive and coordinated management of co-occurring diseases and geriatric syndromes.
Keywords: Accidental Falls; Activities of Daily Living; Aged; Aged, 80 and over; Angina Pectoris; Comorbidity; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Female; Geriatric Assessment; Health Surveys; Heart Failure; Humans; Male; Myocardial Infarction; Sick Role; Syndrome; United States; Urinary incontinence

Correlates of improvement in walking ability in older persons in the United States. - Joseph Feinglass; Song, Jing; Larry M Manheim; Semanik, Pamela; Rowland W Chang; Dorothy D Dunlop (Am J Public Health, 2009)
OBJECTIVES: We analyzed factors associated with improvement in walking ability among respondents to the nationally representative Health and Retirement Study. METHODS: We analyzed data from 6574 respondents aged 53 years or older who reported difficulty walking several blocks, 1 block, or across the room in 2000 or 2002. We examined associations between improvement (versus no change, deterioration, or death) and baseline health status, chronic conditions, baseline walking difficulty, demographic characteristics, socioeconomic status, and behavioral risk factors. RESULTS: Among the 25% of the study population with baseline walking limitations, 29% experienced improved walking ability, 40% experienced no change in walking ability, and 31% experienced deteriorated walking ability or died. In a multivariate analysis, we found positive associations between walking improvement and more recent onset and more severe walking difficulty, being overweight, and engaging in vigorous physical activity. A history of diabetes, having any difficulty with activities of daily living, and being a current smoker were all negatively associated with improvement in walking ability. After we controlled for baseline health, improvement in walking ability was equally likely among racial and ethnic minorities and those with lower socioeconomic status. CONCLUSIONS: Interventions to reduce smoking and to increase physical activity may help improve walking ability in older Americans.
Keywords: Age Factors; Aged; Aged, 80 and over; Confidence Intervals; Female; Health Promotion; Humans; Male; Middle Aged; Motor Activity; Multivariate Analysis; Odds Ratio; Overweight; Smoking Prevention; Social Marketing; Socioeconomic factors; United States; Walking

Dental care coverage transitions. - Richard J. Manski; John F Moeller; Haiyan Chen; Patricia A St Clair; Jody Schimmel; Larry S. Magder; John V Pepper (Am J Manag Care, 2009)
OBJECTIVE: To examine dental insurance transition dynamics in the context of changing employment and retirement status. STUDY DESIGN: Data from the Health and Retirement Study (HRS) were analyzed for individuals 51 years and older between the 2004 and 2006 waves of the HRS. METHODS: The primary focus of the analysis is the relationship between retirement and transitions in dental care coverage. We calculate and present bivariate relationships between dental coverage and retirement status transitions over time and estimate a multivariable model of dental coverage controlling for retirement and other potentially confounding covariates. RESULTS: Older adults are likely to lose their dental coverage on entering retirement compared with those who remain in the labor force between waves of the HRS. While more than half of those persons in the youngest group (51-64 years) were covered over this entire period, two-thirds of those in the oldest group (>or=75 years) were without coverage over the same period. We observe a high percentage of older persons flowing into and out of dental coverage over the period of our study, similar to flows into and out of poverty. CONCLUSIONS: Dental insurance is an important factor in the decision to seek dental care. Yet, no dental coverage is provided by Medicare, which provides medical insurance for almost all Americans 65 years and older. This loss of coverage could lead to distortions in the timing of when to seek care, ultimately leading to worse oral and overall health.
Keywords: Aged; Career Mobility; Female; Health Benefit Plans, Employee; Humans; Insurance Coverage; Insurance, Dental; Interviews as Topic; Male; Middle Aged; United States

Doing well: a SEM analysis of the relationships between various activities of daily living and geriatric well-being. - James A Katt; Speranza, Linda; Shore, Wendy; Karen H. Saenz; E. Lea Witta (J Genet Psychol, 2009)
An existing large data set, the Health and Retirement Study (HRS) with the subsequent addition of the Consumption and Activities Mail Survey (CAMS) data, provides a rich data set for the examination of the activities of older adults. In this study HRS and CAMS data are used to examine relationships between various activities of daily living (ADLs) and well-being in older adults. Using structural equation modeling, influences of direct and indirect factors that affect older individuals' cognitive and emotional well-being are analyzed. The data suggest ability to perform ADLs has little to do with cognitive well-being, but is an influential factor in determining emotional well-being.
Keywords: Activities of Daily Living; Adaptation, Psychological; Aged; Cognition; depression; Humans; Models, Psychological; Socioeconomic factors; United States

Early Life Health and Cognitive Function in Old Age. - Case, Anne; Paxson, Christina (Am Econ Rev, 2009)
Keywords: Adult; Aged; Child; Cognition Disorders; Communicable Diseases; Health Status; Humans; Infant; Infant Mortality; United States

The effect of depression and cognitive impairment on enrollment in Medicare Part D. - Zivin, Kara; Mohammed U Kabeto; Helen C Kales; Kenneth M. Langa (J Am Geriatr Soc, 2009)
OBJECTIVES: To examine concerns that vulnerable populations, such as depressed or cognitively impaired beneficiaries would have challenges accessing Part D coverage. DESIGN: Logistic regression analysis was used to assess whether elderly Medicare beneficiaries with depression or cognitive impairment differentially planned to and actually signed up for Part D. SETTING: 2004 and 2006 data from the Health and Retirement Study (HRS) were used, including a subsample that completed the Prescription Drug Study (PDS) in 2005. PARTICIPANTS: Nine thousand five hundred ninety-three HRS respondents and 3,567 PDS respondents. MEASUREMENTS: The outcome variables of interest were planned and actual enrollment in Part D. The independent variables were depression and cognitive impairment status. The analyses were adjusted using clinical and demographic predictors including age, sex, race or ethnicity, educational attainment, net worth, marital status, health status, number of health conditions being treated with prescription medications, and presence of a caregiver. RESULTS: Although having depression or cognitive impairment was associated with a higher likelihood of planning to and actually signing up for Part D in unadjusted analyses, in adjusted analyses, having depression or cognitive impairment was not significantly associated with whether Medicare beneficiaries planned to enroll in or actually enrolled in Part D. CONCLUSION: Vulnerable Medicare beneficiaries with depression or cognitive impairment were able to access Part D benefits to the same extent as nonvulnerable beneficiaries. More research is needed to determine how well Part D meets the needs of these populations.
Keywords: Aged; Aged, 80 and over; Chi-Square Distribution; Cognition Disorders; depression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Medicare Part D; Middle Aged; Patient Participation; Risk Factors; United States

Effect of Medicare home health care payment on informal care. - Ezra Golberstein; David C Grabowski; Kenneth M. Langa; M.E. Chernew (Inquiry, 2009)
This paper assesses the effect of payment caps for Medicare home health care on the use of informal care by older adults with functional limitations. We find that individuals exposed to more restrictive payment caps offset reductions in Medicare home health care with increased informal care, although we only observe this effect for lower-income individuals. This suggests that home care payment restrictions may have increased the caregiving burden on some low-income families, but that many higher-income families were able to either forgo the care or finance it privately. Home care payment policies should recognize these effects, balancing costs of the program with the desire to protect families from the burdens associated with providing informal home care.
Keywords: Caregivers; Confidence Intervals; Female; Health Care Surveys; Home Care Services; Humans; Male; Medicare; Organizational Policy; Reimbursement Mechanisms; United States

Is the effect of reported physical activity on disability mediated by cognitive performance in white and african american older adults? - Mihaela A. Popa; Sandra L Reynolds; Brent J. Small (J Gerontol B Psychol Sci Soc Sci, 2009)
This study examined if reported physical activity has beneficial outcomes on disability through cognitive performance-mediated effects and if these mediation effects are comparable for White and African American elders. Longitudinal data from the Assets and Health Dynamics among the Oldest Old study (N = 4,472) are used to test mediation in multilevel models. During the 7-year follow-up, cognitive performance mediated the effects of reported physical activity on disability in the entire sample and in Whites but not in African Americans. Our results indicate that reported physical activity may delay the disability development through improvement in cognitive performance. Unmeasured education and comorbidity influences may have obscured the mediation effects in African Americans. Reported physical activity plays a key role in the independence of older adults and should be particularly promoted in African Americans and during the entire life course.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Black or African American; Cognition Disorders; Cohort Studies; Disability Evaluation; Exercise; Female; Follow-Up Studies; Health Status Disparities; Humans; Male; Motor Activity; Neuropsychological tests; Socioeconomic factors; United States; White People

The effect of retirement on weight. - Chung, Sukyung; Marisa E Domino; Sally C. Stearns (J Gerontol B Psychol Sci Soc Sci, 2009)
OBJECTIVES: People who are close to retirement age show the highest rates of weight gain and obesity. We investigate the effect of retirement on the change in body mass index (BMI) in diverse groups varying by wealth status and occupation type. METHODS: Six panels of the Health and Retirement Study (1992-2002) on individuals aged 50-71 were used (N = 37,807). We used fixed-effects regression models with instrumental variables method to estimate the causal effect of retirement on change in the BMI. RESULTS: Retirement leads to modest weight gain, 0.24 BMI on average. Weight gain with retirement was found among people who were already overweight and those with lower wealth retiring from physically demanding occupations. The cumulative effect of aging among people in their 50s, however, outweighs the effect of retirement; the average BMI gain between ages 50 and 60 is 1.30, 5 times the effect of retirement. CONCLUSIONS: Given the increasing number of people approaching retirement age, the population level impact of the weight gain ascribed to retirement on health outcomes and health care system might be significant. Future research should evaluate programs targeted to older adults who are most likely to gain weight with retirement.
Keywords: Aged; Aging; Body Mass Index; Cohort Studies; Cross-Sectional Studies; Female; Geriatric Assessment; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Models, Statistical; Motor Activity; Obesity; Overweight; Pensions; Retirement; Social Security; Socioeconomic factors; United States; Weight Gain

The effects of developing a dual sensory loss on depression in older adults: a longitudinal study. - Michele Capella McDonnall (J Aging Health, 2009)
OBJECTIVE: To determine the effect of developing a dual sensory loss (DSL) on depression over time and evaluate the impact of preexisting single sensory loss on this effect. METHOD: Multilevel modeling was used to analyze data (N = 2,689) from the Health and Retirement Study. RESULTS: A significant increase in depression at the first report of DSL occurred, and depression increased at a significantly faster rate following DSL, in a curvilinear pattern. In addition, persons who eventually developed DSL began the study with a depression score significantly higher than persons who did not experience sensory loss. A preexisting single sensory loss did not alter the effect of DSL on depression. DISCUSSION: Two sources of disparity in depression between persons with and without DSL were identified: preexisting differences and differences that occurred due to the DSL. The relationship exhibited between depression and developing a DSL indicated an adjustment process.
Keywords: Adaptation, Psychological; Adult; Aged; Aged, 80 and over; Black or African American; depression; Depressive Disorder; Female; Health Surveys; Hearing loss; Hispanic or Latino; Humans; Longitudinal Studies; Male; Middle Aged; Models, Statistical; Multivariate Analysis; Rehabilitation; Retirement; Risk Factors; Sensation Disorders; United States; Vision Disorders; White People

Estimating the quantity and economic value of family caregiving for community-dwelling older persons in the last year of life. - Rhee, YongJoo; Howard B Degenholtz; Anthony T. Lo Sasso; Linda L Emanuel (J Am Geriatr Soc, 2009)
OBJECTIVES: To estimate the quantity and economic value of informal care provided to older persons during their final year of life in the community. DESIGN: Retrospective analysis of publicly available nationally representative survey data. SETTING: This retrospective study used data from the Health and Retirement Study, a nationally representative, longitudinal study of community-dwelling older people. PARTICIPANTS: Older people who died between 2000 and 2002. MEASUREMENTS: Data were extracted from the 2002 "exit survey" and linked with characteristics of caregivers from the helper file. Ordinary least squares regression was used to estimate hours of informal caregiving for community-dwelling older people (N=990). Adjusted hours were multiplied by the 2002 national average home aide wage (9.16 USD per hour). Sensitivity tests were performed using the 10th percentile wage rate (6.56 USD) and 90th percentile wage rate (12.34 USD). RESULTS: Older people who died in the community received on average 65.8 hours per week of informal care in the last year of life. The estimated economic value ranges from 22,514 USD to 42,351 USD, which is equivalent to the annual direct replacement cost with a home aide in 2002. CONCLUSION: Family members provide substantial assistance during the last year of life for older people who die in the community. If the informal care provided in the last year of life is replaced with a home aide, the total economic value for the United States would be approximately 1.4 billion USD (in 2002).
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Caregivers; Costs and Cost Analysis; Disability Evaluation; Female; Health Surveys; Home Health Aides; Home Nursing; Humans; Independent Living; Male; Middle Aged; Retrospective Studies; Terminal Care; United States

Factors associated with long-stay nursing home admissions among the U.S. elderly population: comparison of logistic regression and the Cox proportional hazards model with policy implications for social work. - Cai, Qian; J. Warren Salmon; Mark E. Rodgers (Soc Work Health Care, 2009)
Two statistical methods were compared to identify key factors associated with long-stay nursing home (LSNH) admission among the U.S. elderly population. Social Work's interest in services to the elderly makes this research critical to the profession. Effectively transitioning the "baby boomer" population into appropriate long-term care will be a great societal challenge. It remains a challenge paramount to the practice of social work. Secondary data analyses using four waves (1995, 1998, 2000, and 2002) of the Health Retirement Study (HRS) coupled with the Assets and Health Dynamics among the Oldest Old (AHEAD) surveys were conducted. Multivariable logistic regression and Cox proportional hazards model were performed and compared. Older age, lower self-perceived health, worse instrumental activities of daily living (IADL), psychiatric problems, and living alone were found significantly associated with increased risk of LSNH admission. In contrast, being female, African American, or Hispanic; owning a home; and having lower level of cognitive impairment reduced the admission risk. Home ownership showed a significant effect in logistic regression, but a marginal effect in the Cox model. The Cox model generally provided more precise parameter estimates than logistic regression. Logistic regression, used frequently in analyses, can provide a good approximation to the Cox model in identifying factors of LSNH admission. However, the Cox model gives more information on how soon the LSNH admission may happen. Our analyses, based on two models, dually identified the factors associated with LSNH admission; therefore, results discussed confidently provide implications for both public and private long-term care policies, as well as improving the assessment capabilities of social work practitioners for development of screening programs among at-risk elderly. Given the predicted surge in this population, significant factors found from this study can be utilized in a strengths-based empowerment approach by social workers to aid in avoiding LSNH utilization.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Female; Geriatric Assessment; Health Status; Homes for the Aged; Humans; Logistic Models; Male; Mental Health; Nursing homes; Proportional Hazards Models; Risk Factors; Sex Factors; Social work; Socioeconomic factors; United States

Financial hardship and mortality among older adults using the 1996-2004 Health and Retirement Study. - Reginald D. Tucker-Seeley; Li, Yi; Subramanian, S V; Sorensen, Glorian (Ann Epidemiol, 2009)
PURPOSE: We investigated the effect of financial hardship on mortality risk in a community-dwelling sample of adults 50 years of age and olderin the United States. METHOD: The 1996 Health and Retirement Study cohorts were followed prospectively to 2004 (N = 8,377). Gender-stratified grouped Cox models were used to estimate the difference in the relative risk (RR) of mortality between a specific number of financial hardships (one, two, or three or more) and no hardships; and the predictive utility of each individual financial hardship for mortality during the follow-up period. RESULTS: Gender-stratified models adjusted for demographics, socioeconomic characteristics, and functional limitations in 1996 showed that women reporting one (hazard ratio [HR] = 1.42; 95% confidence interval [CI]: 1.05-1.92) or three or more (HR = 1.60; 95% CI: 1.05-2.46) and men reporting two (HR = 1.80; 95% CI: 1.21-2.69) financial hardships had a substantially higher probability of mortality compared to those reporting no financial hardships. Individual financial hardships that predicted mortality in fully adjusted models for women included receiving Medicaid (HR = 2.23; 95% CI: 1.68-2.98) and for men receiving Medicaid (HR = 2.11; 95% CI: 1.57-2.84) and receiving food stamps (HR = 1.59; 95% CI: 1.09-2.33). CONCLUSIONS: These findings suggest that over and above the influence of traditional measures of socioeconomic status, financial hardship exerts an influence on the risk of mortality among older adults and that the number and type of hardships important in predicting mortality may differ for men and women.
Keywords: Aged; Female; Geriatric Assessment; Health Surveys; Humans; Male; Medicaid; Middle Aged; Mortality; Poverty; Proportional Hazards Models; Prospective Studies; Retirement; Risk; Sex Factors; United States

Health and well-being in older married female cancer survivors. - Aloen L. Townsend; Karen J Ishler; Karen F Bowman; Rose, Julia Hannum; Peak, Nicole Juszczak (J Am Geriatr Soc, 2009)
OBJECTIVES: To investigate differences between older married female cancer survivors and a matched comparison sample on physical health and on effects of health on depressive symptomatology. DESIGN AND SETTING: National survey data from the 1992 Health and Retirement Study. PARTICIPANTS: Married women who reported having been diagnosed with cancer (N=245) and married women who did not report a cancer diagnosis but who matched the survivors on age, race, and ethnicity (N=245). MEASUREMENTS: Outcome measure was depressive symptomatology (modified CES-D). Predictors were multiple indicators of health and demographic characteristics. RESULTS: Cancer survivors reported significantly worse health on all indicators but not higher depressive symptomatology after health and demographics were controlled. Predictors of higher depression were fatigue, pain, and lower education. These effects did not differ between groups. CONCLUSION: Health impairment in cancer survivors highlights the need for ongoing follow-up care. Survivorship was associated indirectly with higher depressive symptomatology through its relationship with health impairment.
Keywords: Age Factors; Case-Control Studies; Depressive Disorder; Female; Health Status; Health Status Indicators; Health Surveys; Humans; Marriage; Middle Aged; Neoplasms; Predictive Value of Tests; Risk Factors; Survivors; United States

Health disadvantage in US adults aged 50 to 74 years: a comparison of the health of rich and poor Americans with that of Europeans. - Mauricio Avendano; M. Maria Glymour; James Banks; Johan P Mackenbach (Am J Public Health, 2009)
OBJECTIVES: We compared the health of older US, English, and other European adults, stratified by wealth. METHODS: Representative samples of adults aged 50 to 74 years were interviewed in 2004 in 10 European countries (n = 17,481), England (n = 6527), and the United States (n = 9940). We calculated prevalence rates of 6 chronic diseases and functional limitations. RESULTS: American adults reported worse health than did English or European adults. Eighteen percent of Americans reported heart disease, compared with 12% of English and 11% of Europeans. At all wealth levels, Americans were less healthy than were Europeans, but differences were more marked among the poor. Health disparities by wealth were significantly smaller in Europe than in the United States and England. Odds ratios of heart disease in a comparison of the top and bottom wealth tertiles were 1.94 (95% confidence interval [CI] = 1.69, 2.24) in the United States, 2.13 (95% CI = 1.73, 2.62) in England, and 1.38 (95% CI = 1.23, 1.56) in Europe. Smoking, obesity, physical activity levels, and alcohol consumption explained a fraction of health variations. CONCLUSIONS: American adults are less healthy than Europeans at all wealth levels. The poorest Americans experience the greatest disadvantage relative to Europeans.
Keywords: Age Factors; Aged; Chronic disease; Confidence Intervals; Disabled Persons; Europe; Female; Health Status Disparities; Heart Diseases; Humans; Male; Middle Aged; Odds Ratio; Poverty; Prevalence; Risk Factors; Socioeconomic factors; United States

The health effects of Medicare for the near-elderly uninsured. - Daniel Polsky; Jalpa A Doshi; José J Escarce; Manning, Willard; Susan M Paddock; Cen, Liyi; Jeannette Rogowski (Health Serv Res, 2009)
OBJECTIVE: To determine whether Medicare enrollment at age 65 has an effect on the health trajectory of the near-elderly uninsured. DATA SOURCES: Eight biennial waves (1992-2006) of the Health and Retirement Study, a nationally representative panel survey of noninstitutionalized 51-61 year olds and their spouses. STUDY DESIGN: We use a quasi-experimental approach to compare the health effects of insurance for the near-elderly uninsured with previously insured contemporaneous controls. The primary outcome measure is overall self-reported health status combined with mortality (i.e., excellent to very good, good, fair to poor, dead). RESULTS: The change in the trajectory of overall health status for the previously uninsured that can be attributed to Medicare is small and not statistically significant. For every 100 persons in the previously uninsured group, joining Medicare is associated with 0.6 fewer in excellent or very good health (95 percent CI: -4.8, 3.3), 0.3 more in good health (95 percent CI: -3.8, 4.1), 2.5 fewer in fair or poor health (95 percent CI: -7.4, 2.3), and 2.8 more dead (-4.0, 10.0) by age 73. The health trajectory patterns from physician objective health measures are similarly small and not statistically significant. CONCLUSIONS: Medicare coverage at age 65 for the previously uninsured is not linked to improvements in overall health status.
Keywords: Aged; Attitude to Health; Female; Follow-Up Studies; Health Services Accessibility; Health Services Research; Health Status; Health Surveys; Humans; Insurance Coverage; Logistic Models; Male; Medically Uninsured; Medicare; Mortality; Multivariate Analysis; Program Evaluation; Retirement; Socioeconomic factors; Statistics, Nonparametric; United States

The health impact of remarriage behavior on chronic obstructive pulmonary disease: findings from the US longitudinal survey. - Noda, Tatsuya; Ojima, Toshiyuki; Hayasaka, Shinya; Hagihara, Okihito; Takayanagi, Ryoichi; Nobutomo, Koichi (BMC Public Health, 2009)
BACKGROUND: Chronic obstructive pulmonary disease (COPD) is a major disease among adults, and its deterioration was reported to be associated with psychological imbalance. Meanwhile, bereavement and divorce have proven harmful to the health status of a surviving spouse. But few studies have been conducted to evaluate the remedial effect on survivors' health outcome by remarriage after bereavement. The present study thus examined the associations between remarriage and the onset of COPD. METHODS: Our cohort was drawn from Health and Retirement Study participants in the United States, and consisted of 2676 subjects who were divorced or bereaved from 1992 to 2002. We then followed them for up to 11 years and assessed the incidence rate of COPD using a Cox proportional hazard model after adjusting for marital status, age, gender, education and the number of cigarettes smoked. RESULTS: Among all subjects, 224 who remarried after bereavement or divorce tended to be younger and more male dominated. Remarriage after bereavement/divorce was associated with significantly decreased risk of COPD onset for overall subjects [hazard ratio (HR): 0.51, 95% confidence interval (95% CI): 0.28-0.94], female subjects [HR: 0.36, 95% CI: 0.13-0.98], and for those under 70 years old [HR: 0.36, 95% CI: 0.17-0.79]. CONCLUSION: This study investigates the impact of remarriage on health outcome based on a large-scale population survey and indicates that remarriage significantly correlates with reduced risk of COPD incidence, even after adjusting smoking habit.
Keywords: Aged; Bereavement; Educational Status; Female; Follow-Up Studies; Health Status; Health Surveys; Humans; Lung Diseases, Obstructive; Male; Marriage; Middle Aged; Outcome Assessment, Health Care; Proportional Hazards Models; Smoking; United States

The impact of occupation on self-rated health: cross-sectional and longitudinal evidence from the health and retirement survey. - Ralitza Gueorguieva; Jody L Sindelar; Tracy Falba; Jason M. Fletcher; Patricia S Keenan; Wu, Ran; William T Gallo (J Gerontol B Psychol Sci Soc Sci, 2009)
BACKGROUND: The objective of this study is to estimate occupational differences in self-rated health, both in cross-section and over time, among older individuals. METHODS: We use hierarchical linear models to estimate self-reported health as a function of 8 occupational categories and key covariates. We examine self-reported health status over 7 waves (12 years) of the Health and Retirement Study. Our study sample includes 9,586 individuals with 55,389 observations. Longest occupation is used to measure the cumulative impact of occupation, address the potential for reverse causality, and allow the inclusion of all older individuals, including those no longer working. RESULTS: Significant baseline differences in self-reported health by occupation are found even after accounting for demographics, health habits, economic attributes, and employment characteristics. But contrary to our hypothesis, there is no support for significant differences in slopes of health trajectories even after accounting for dropout. CONCLUSIONS: Our findings suggest that occupation-related differences found at baseline are durable and persist as individuals age.
Keywords: Aged; Attitude to Health; Cohort Studies; Cross-Sectional Studies; Educational Status; Female; Health Status Indicators; Health Surveys; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; Mortality; Occupations; Odds Ratio; Retirement; Social Class; Socioeconomic factors; United States

Incidence and remission of urinary incontinence in a community-based population of women ≥ 50 years. - Yuko M Komesu; Rebecca G Rogers; Ronald M Schrader; Cynthia M. Lewis (Int Urogynecol J Pelvic Floor Dysfunct, 2009)
INTRODUCTION AND HYPOTHESIS: The objective of the study was to determine incidence, remission, and predictors of change in urinary incontinence in women ≥ 50 in a racially diverse population. METHODS: Subjects were women ≥ 50 with 4-year follow-up incontinence information in the Health and Retirement Study. Women with Any UI (AUI) and Severe UI (SVUI) were evaluated. Repeated measures logistic regression determined predictors of progression to and improvement of SVUI. RESULTS: Women (11,591) were evaluated. AUI 4-year cumulative incidence was 12.7-33.8% (fifth vs. ninth decades). SVUI incidence was lower but also increased with age. Among the predictors of improvement in SVUI were age (ninth vs. fifth decade odds ratios (OR) = 6.06) and ethnicity (Black vs. White OR = 0.57). Improvement of SVUI (45.8% overall) decreased with age (ninth vs. fifth decade OR = 0.12). CONCLUSIONS: SVUI incidence increased and remission decreased with age. Ethnicity and age predicted SVUI progression while age predicted improvement. Rates of the latter were high, particularly in younger patients.
Keywords: Age Factors; Black People; disease progression; Female; Hispanic or Latino; Humans; Incidence; Logistic Models; Longitudinal Studies; Middle Aged; Odds Ratio; Prevalence; Remission, Spontaneous; Severity of Illness Index; United States; Urinary incontinence; White People

Level and change in cognitive test scores predict risk of first stroke. - Triveni DeFries; Mauricio Avendano; M. Maria Glymour (J Am Geriatr Soc, 2009)
OBJECTIVES: To determine whether cognitive test scores and cognitive decline predict incidence of first diagnosed stroke. DESIGN: Stroke-free Health and Retirement Study participants were followed on average 7.6 years for self- or proxy-reported first stroke (1,483 events). Predictors included baseline performance on a modified Telephone Interview for Cognitive Status (Mental Status) and Word Recall test and decline between baseline and second assessment in either measure. Hazard ratios (HRs) were estimated using Cox proportional hazards models for the whole sample and stratified according to five major cardiovascular risk factors. SETTING: National cohort study of noninstitutionalized adults with a mean baseline age of 64+/-9.9. PARTICIPANTS: Health and Retirement Study participants (n=19,699) aged 50 and older. RESULTS: Word Recall (HR for 1 standard deviation difference=0.92, 95% confidence interval (CI)=0.86-0.97)) and Mental Status (HR=0.89, 95% CI=0.84-0.95) predicted incident stroke. Mental Status predicted stroke risk in those with (HR=0.93, 95%=0.87-0.99) and without (HR=0.81, 95% CI=0.72-.91) one or more vascular risk factors. Word Recall declines predicted a 16% elevation in subsequent stroke risk (95% CI=1.01-1.34). Declines in Mental Status predicted a 37% elevation in stroke risk (95% CI=1.11-1.70). CONCLUSION: Cognitive test scores predict future stroke risk, independent of other major vascular risk factors.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Cohort Studies; Dementia, Vascular; Female; Follow-Up Studies; Humans; Interviews as Topic; Kaplan-Meier Estimate; Male; Mental Status Schedule; Middle Aged; Predictive Value of Tests; Psychometrics; Risk; Stroke; United States

Marital biography and health at mid-life. - Mary Elizabeth Hughes; Linda J. Waite (J Health Soc Behav, 2009)
This article develops a series of hypotheses about the long-term effects of one's history of marriage, divorce, and widowhood on health, and it tests those hypotheses using data from the Health and Retirement Study. We examine four dimensions of health at mid-life: chronic conditions, mobility limitations, self-rated health, and depressive symptoms. We find that the experience of marital disruption damages health, with the effects still evident years later; among the currently married, those who have ever been divorced show worse health on all dimensions. Both the divorced and widowed who do not remarry show worse health than the currently married on all dimensions. Dimensions of health that seem to develop slowly, such as chronic conditions and mobility limitations, show strong effects of past marital disruption, whereas others, such as depressive symptoms, seem more sensitive to current marital status. Those who spent more years divorced or widowed show more chronic conditions and mobility limitations.
Keywords: Female; Health Status; Humans; Interviews as Topic; Longitudinal Studies; Male; Marital Status; Middle Aged; United States

Marital trajectories and mortality among US adults. - Matthew E Dupre; Audrey N Beck; Sarah O. Meadows (Am J Epidemiol, 2009)
More than a century of empirical evidence links marital status to mortality. However, the hazards of dying associated with long-term marital trajectories and contributing risk factors are largely unknown. The authors used 1992-2006 prospective data from a cohort of US adults to investigate the impact of current marital status, marriage timing, divorce and widow transitions, and marital durations on mortality. Multivariate hazard ratios were significantly higher for adults currently divorced and widowed, married at young ages (< or =18 years), who accumulated divorce and widow transitions (among women), and who were divorced for 1-4 years. Results also showed significantly lower risks of mortality for men married after age 25 years compared with on time (ages 19-25 years) and among women experiencing > or =10 years of divorce and > or =5 years of widowhood relative to those without exposure to these statuses. For both sexes, accumulation of marriage duration was the most robust predictor of survival. Results from risk-adjusted models indicated that socioeconomic resources, health behaviors, and health status attenuated the associations in different ways for men and women. The study demonstrates that traditional measures oversimplify the relation between marital status and mortality and that sex differences are related to a nexus of marital experiences and associated health risks.
Keywords: Age Factors; Cohort Studies; Female; Health Behavior; Humans; Male; Marital Status; Middle Aged; Mortality; Retirement; Retrospective Studies; Risk Factors; Sex Factors; Time Factors; United States

Material resources and population health: disadvantages in health care, housing, and food among adults over 50 years of age. - Dawn E Alley; Beth J Soldo; José A Pagán; John McCabe; deBlois, Madeleine; Samuel H Field; David A Asch; Carolyn Cannuscio (Am J Public Health, 2009)
OBJECTIVES: We examined associations between material resources and late-life declines in health. METHODS: We used logistic regression to estimate the odds of declines in self-rated health and incident walking limitations associated with material disadvantages in a prospective panel representative of US adults aged 51 years and older (N = 15,441). RESULTS: Disadvantages in health care (odds ratio [OR] = 1.39; 95% confidence interval [CI] = 1.23, 1.58), food (OR = 1.69; 95% CI = 1.29, 2.22), and housing (OR = 1.20; 95% CI = 1.07, 1.35) were independently associated with declines in self-rated health, whereas only health care (OR = 1.43; 95% CI = 1.29, 1.58) and food (OR = 1.64; 95% CI = 1.31, 2.05) disadvantage predicted incident walking limitations. Participants experiencing multiple material disadvantages were particularly susceptible to worsening health and functional decline. These effects were sustained after we controlled for numerous covariates, including baseline health status and comorbidities. The relations between health declines and non-Hispanic Black race/ethnicity, poverty, marital status, and education were attenuated or eliminated after we controlled for material disadvantage. CONCLUSIONS: Material disadvantages, which are highly policy relevant, appear related to health in ways not captured by education and poverty. Policies to improve health should address a range of basic human needs, rather than health care alone.
Keywords: Aged; Female; Food Supply; Health Status Disparities; Health Surveys; Healthcare Disparities; Housing; Humans; Logistic Models; Male; Middle Aged; Poverty; United States

Medicare savings programs: analyzing options for expanding eligibility. - Zuckerman, Stephen; Shang, Baoping; Timothy A Waidmann (Inquiry, 2009)
The Medicare Savings Programs (MSPs) are designed to provide financial assistance to Medicare beneficiaries who do not qualify for full Medicaid coverage. This paper considers changes in eligibility that would better align MSP program rules with those related to receiving low-income subsidies for the Medicare Part D drug benefit. These changes would make more people eligible for the MSPs and could encourage greater participation; similar changes were incorporated in recently passed legislation. Our analysis, based on 2006 data from the Health and Retirement Study, shows there is a trade-off between making larger numbers of beneficiaries eligible by eliminating resource requirements and better targeting of individuals with greater health care needs by expanding income standards.
Keywords: Aged; Demography; Disabled Persons; Eligibility Determination; Female; Health Status; Humans; Income; Male; Medical Assistance; Medicare; Medicare Part D; Public Policy; United States

Mortality attributable to obesity among middle-aged adults in the United States. - Neil K Mehta; Virginia W Chang (Demography, 2009)
Obesity is considered a major cause of premature mortality and a potential threat to the longstanding secular decline in mortality in the United States. We measure relative and attributable risks associated with obesity among middle-aged adults using data from the Health and Retirement Study (1992-2004). Although class II/III obesity (BMI > or = or = 35.0 kg/m2) increases mortality by 40% in females and 62% in males compared with normal BMI (BMI = 18.5-24.9), class I obesity (BMI = 30.0-34.9) and being overweight (BMI = 25.0-29.9) are not associated with excess mortality. With respect to attributable mortality, class II/III obesity (BMI > or = 35.0) is responsible for approximately 4% of deaths among females and 3% of deaths among males. Obesity is often compared with cigarette smoking as a major source of avoidable mortality. Smoking-attributable mortality is much larger in this cohort: about 36% in females and 50% in males. Results are robust to confounding by preexisting diseases, multiple dimensions of socioeconomic status (SES), smoking, and other correlates. These findings challenge the viewpoint that obesity will stem the long-term secular decline in U.S. mortality.
Keywords: Body Mass Index; Confidence Intervals; Confounding Factors, Epidemiologic; Female; Humans; Male; Middle Aged; Multivariate Analysis; Obesity; Proportional Hazards Models; Risk; Socioeconomic factors; United States

A new measure of medication affordability. - Becky A. Briesacher; Ross-Degnan, Dennis; Adams, Alyce; Anita K Wagner; Jerry Gurwitz; Soumerai, Stephan (Soc Work Public Health, 2009)
This study developed a new measure of medication affordability that examines out-of-pocket drug expenses relative to available household resources. The authors assessed the spending patterns of approximately 2.1 million poor households (< or =100% federal poverty level) of adults aged 51 and older by Medicaid status. The data were drawn from the 2000-2001 Health and Retirement Study. Household spending was categorized into three broad types: basic living, health care, and discretionary. Older (aged 51 or older) poor households without Medicaid allocated about 72% of their total resources ($17,421, SE $783) to basic living needs. In comparison, those with Medicaid had scarcer total resources ($12,498, SE $423) and allocated 85% to basic living needs. Medication costs consumed the largest proportion of health care expenses for both types of poor households (Medicaid: $463, SE $67; non-Medicaid: $970, SE $102). After paying for basic living needs and health care costs, these families had, on average, only $16 left each week. Poor families have very few resources available for anything beyond basic living needs, even when they have Medicaid coverage. There is no great reservoir of discretionary funds to pay for increases in cost-sharing under Medicaid and Medicare Part D.
Keywords: Aged; Data collection; Female; Financing, Personal; Humans; Male; Medicaid; Middle Aged; Poverty; Prescription Fees; United States

Parental education and late-life dementia in the United States. - Mary A M Rogers; Brenda L Plassman; Mohammed U Kabeto; Gwenith G Fisher; John J McArdle; David J Llewellyn; Guy G Potter; Kenneth M. Langa (J Geriatr Psychiatry Neurol, 2009)
We investigated the relation between parental education and dementia in the United States. Participants in the Aging, Demographics, and Memory Study were included, with information regarding parental education obtained from the Health and Retirement Study. The odds of dementia in elderly Americans whose mothers had less then 8 years of schooling were twice (95% CI, 1.1-3.8) that of individuals with higher maternal education, when adjusted for paternal education. Of elderly Americans with less educated mothers, 45.4% (95% CI, 37.4-53.4%) were diagnosed with dementia or ;;cognitive impairment, no dementia'' compared to 31.2% (95% CI, 25.0-37.4%) of elderly Americans whose mothers had at least an 8th grade education. The population attributable risk of dementia due to low maternal education was 18.8% (95% CI, 9.4-28.2%). The education of girls in a population may be protective of dementia in the next generation.
Keywords: Age Distribution; Aged; Aged, 80 and over; Apolipoproteins E; Biomarkers; Cognition Disorders; Dementia; Educational Status; Fathers; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Male; Mothers; Odds Ratio; Parents; Prevalence; Prospective Studies; Racial Groups; Risk Factors; Sex Distribution; United States

Patterns of food insecurity and participation in food assistance programmes over time in the elderly. - Kim, Kirang; Edward A Frongillo (Public Health Nutr, 2009)
OBJECTIVE: The present study aimed to understand the relationship between need and help-seeking behaviour in older adults by examining the patterns of food insecurity and participation in food assistance programmes (FAP), i.e. the Food Stamp Program and home-delivered meals. DESIGN: Data from two longitudinal studies were used. The studies were designed to obtain nationally representative information on health, insurance coverage, financial status, family support systems, labour market status and retirement planning, every two years: the Health and Retirement Study (HRS, 1996-2002) and Asset and Health Dynamics Among the Oldest Old (AHEAD, 1995-2002). SETTING: USA. SUBJECTS: There were 7623 participants for HRS and 3378 for AHEAD. RESULTS: The older adults appeared to have persistent patterns between food insecurity and participation in FAP, especially in the Food Stamp Program. More persistently food-insecure older adults had higher participation in FAP (P < 0.001). Food-insecure older adults at one time were more likely to shift from non-participation to participation in FAP the next time than food-secure older adults (P < 0.001). Regardless of previous food insecurity status, previous participants in FAP were more likely to participate subsequently. CONCLUSIONS: The relationship between need and help-seeking behaviour in older adults was found to follow a persistent positive pattern, determined by looking at the patterns of food insecurity and participation in FAP. Although food insecurity as a need is a good predictor of participation in FAP, it is not enough to fully predict participation in FAP. Help-seeking behaviour (i.e. previous programme participation) is also important in predicting participation in FAP.
Keywords: Aged; diet; Food Supply; Humans; Longitudinal Studies; Malnutrition; National Health Programs; Patient Acceptance of Health Care; Prevalence; Public Assistance; United States

Predictors of loneliness in U.S. adults over age sixty-five. - Laurie A. Theeke (Arch Psychiatr Nurs, 2009)
The purpose of this study was to examine sociodemographic and health-related risks for loneliness among older adults using Health and Retirement Study Data. Overall prevalence of loneliness was 19.3%. Marital status, self-report of health, number of chronic illnesses, gross motor impairment, fine motor impairment, and living alone were predictors of loneliness. Age, female gender, use of home care, and frequency of healthcare visits were not predictive. Loneliness is a prevalent problem for older adults in the United States with its own health-related risks. Future research of interventions targeting identified risks would enhance the evidence base for nursing and the problem of loneliness.
Keywords: Aged; Aged, 80 and over; Female; Health Status; Humans; Likelihood Functions; Logistic Models; Loneliness; Male; Prevalence; Risk Factors; Single Person; Socioeconomic factors; United States

Prevalence of depression among older Americans: the Aging, Demographics and Memory Study. - David C Steffens; Gwenith G Fisher; Kenneth M. Langa; Guy G Potter; Brenda L Plassman (Int Psychogeriatr, 2009)
BACKGROUND: Previous studies have attempted to provide estimates of depression prevalence in older adults. The Aging, Demographics and Memory Study (ADAMS) is a population-representative study that included a depression assessment, providing an opportunity to estimate the prevalence of depression in late life in the U.S.A. METHODS: The ADAMS sample was drawn from the larger Health and Retirement Study. A total of 851 of 856 ADAMS participants aged 71 and older had available depression data. Depression was measured using the Composite International Diagnostic Interview - Short Form (CIDI-SF) and the informant depression section of the Neuropsychiatric Inventory (NPI). We estimated the national prevalence of depression, stratified by age, race, sex, and cognitive status. Logistic regression analyses were performed to examine the association of depression and previously reported risk factors for the condition. RESULTS: When combining symptoms of major or minor depression with reported treatment for depression, we found an overall depression prevalence of 11.19%. Prevalence was similar for men (10.19%) and women (11.44%). Whites and Hispanics had nearly three times the prevalence of depression found in African-Americans. Dementia diagnosis and pain severity were associated with increased depression prevalence, while black race was associated with lower rates of depression. CONCLUSIONS: The finding of similar prevalence estimates for depression in men and women was not consistent with prior research that has shown a female predominance. Given the population-representativeness of our sample, similar depression rates between the sexes in ADAMS may result from racial, ethnic and socioeconomic diversity.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Black People; Cohort Studies; Comorbidity; Cross-Sectional Studies; Depressive Disorder; Female; Health Status; Hispanic or Latino; Humans; Male; Neuropsychological tests; Personality Assessment; Sex Factors; Socioeconomic factors; United States; White People

Proximity to death and participation in the long-term care market. - Weaver, France; Sally C. Stearns; Edward C Norton; Spector, William (Health Econ, 2009)
The extent to which increasing longevity increases per capita demand for long-term care depends on the degree to which utilization is concentrated at the end of life. We estimate the marginal effect of proximity to death, measured by being within 2 years of death, on the probabilities of nursing home and formal home care use, and we determine whether this effect differs by availability of informal care--i.e. marital status and co-residence with an adult child. The analysis uses a sample of elderly aged 70+ from the 1993-2002 Health and Retirement Study. Simultaneous probit models address the joint decisions to use long-term care and co-reside with an adult child. Overall, proximity to death significantly increases the probability of nursing home use by 50.0% and of formal home care use by 12.4%. Availability of informal support significantly reduces the effect of proximity to death. Among married elderly, proximity to death has no effect on institutionalization. In conclusion, proximity to death is one of the main drivers of long-term care use, but changes in sources of informal support, such as an increase in the proportion of married elderly, may lessen its importance in shaping the demand for long-term care.
Keywords: Aged; Aged, 80 and over; Caregivers; Female; Health Services Needs and Demand; Home Care Services; Humans; Interviews as Topic; Longevity; Male; Models, Statistical; Nursing homes; Terminal Care; United States

Recent hospitalization and the risk of hip fracture among older Americans. - Frederic D Wolinsky; Suzanne E Bentler; Li Liu; Maksym Obrizan; Elizabeth A Cook; Kara B Wright; John F Geweke; Elizabeth A Chrischilles; Claire E Pavlik; Robert L. Ohsfeldt; Michael P Jones; Kelly K Richardson; et al. (J Gerontol A Biol Sci Med Sci, 2009)
BACKGROUND: We identified hip fracture risks in a prospective national study. METHODS: Baseline (1993-1994) interview data were linked to Medicare claims for 1993-2005. Participants were 5,511 self-respondents aged 70 years and older and not in managed Medicare. ICD9-CM 820.xx (International Classification of Diseases, 9th Edition, Clinical Modification) codes identified hip fracture. Participants were censored at death or enrollment into managed Medicare. Static risk factors included sociodemographic, socioeconomic, place of residence, health behavior, disease history, and functional and cognitive status measures. A time-dependent marker reflecting postbaseline hospitalizations was included. RESULTS: A total of 495 (8.9%) participants suffered a postbaseline hip fracture. In the static proportional hazards model, the greatest risks involved age (adjusted hazard ratios [AHRs] of 2.01, 2.82, and 4.91 for 75-79, 80-84, and > or =85 year age groups vs those aged 70-74 years; p values <.001), sex (AHR = 0.45 for men vs women; p < .001), race (AHRs of 0.37 and 0.46 for African Americans and Hispanics vs whites; p values <.001 and <.01), body mass (AHRs of 0.40, 0.77, and 1.73 for obese, overweight, and underweight vs normal weight; p values <.001, <.05, and <.01), smoking status (AHRs = 1.49 and 1.52 for current and former smokers vs nonsmokers; p values <.05 and <.001), and diabetes (AHR = 1.99; p < .001). The time-dependent recent hospitalization marker did not alter the static model effect estimates, but it did substantially increase the risk of hip fracture (AHR = 2.51; p < .001). CONCLUSIONS: Enhanced discharge planning and home care for non-hip fracture hospitalizations could reduce subsequent hip fracture rates.
Keywords: Accidental Falls; Age Distribution; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Follow-Up Studies; Geriatric Assessment; Hip Fractures; Hospitalization; Humans; Logistic Models; Male; Multivariate Analysis; Probability; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Distribution; Survival Analysis; United States

Retirement and physical activity: analyses by occupation and wealth. - Chung, Sukyung; Marisa E Domino; Sally C. Stearns; Barry M Popkin (Am J Prev Med, 2009)
BACKGROUND: Older adults close to retirement age show the lowest level of physical activity. Changes in lifestyle with retirement may alter physical activity levels. This study investigated whether retirement changes physical activity and how the effect differs by occupation type and wealth level. METHODS: This longitudinal study used the Health and Retirement Study (1996-2002), U.S. population-based data. Analyses were conducted in 2007 and 2008. Physical activity was measured by a composite indicator of participation in either work-related or leisure-time physical activity. Fixed-effects regression models were used to account for confounders and unobserved heterogeneity. The dependent variable was a composite indicator of participation in regular physical activity either at work or during nonworking hours. RESULTS: Physical activity decreased with retirement from a physically demanding job but increased with retirement from a sedentary job. Occupation type interacted with wealth level, with the negative impact on physical activity of retirement exacerbated by lack of wealth and the positive effect of retirement on physical activity enhanced by wealth. CONCLUSIONS: Substantial differences in the effect of retirement on physical activity occurred across subgroups. As the number of people approaching retirement age rapidly increases, findings suggest that a growing segment of the nation's population may not sustain an adequate level of physical activity.
Keywords: Cohort Studies; Female; Humans; Income; Life Style; Longitudinal Studies; Male; Middle Aged; Motor Activity; Occupations; Retirement; United States

Risk perception and preference for prevention of Alzheimer's disease. - Chung, Sukyung; Kala M. Mehta; Shumway, Martha; Alvidrez, Jennifer; Eliseo J Perez-Stable (Value Health, 2009)
OBJECTIVES: To understand how older adults perceive their risk of Alzheimer's Disease (AD) and how this may shape their medical care decisions, we examined whether presence of established risk factors of AD is associated with individuals' perceived risk of AD, and with preference for preventing AD. PARTICIPANTS: Data came from the US Health and Retirement Study participants who were asked questions on AD risk perception (N = 778). MEASUREMENTS: Perceived risk of AD was measured by respondents' estimate of their percent chance (0-100) developing AD in the next 10 years. Preference for AD prevention was measured with questions eliciting willingness to pay for a drug to prevent AD. ANALYSIS: Multivariate linear regressions were used to estimate correlates of perceived risk and preference for prevention. RESULTS: Better cognitive functioning and physical activity are associated with decreased perceived risk. Neither age nor cardiovascular disease is associated with perceived risk. African Americans have lower perceived risk than non-Latino whites; the difference is wider among people age 65 and above. Only 4% to 7% of the variation in perceived risk was explained by the model. Preference for prevention is stronger with increased perceived risk, but not with the presence of risk factors. Persons with better cognitive functioning, physical functioning, or wealth status have a stronger preference for prevention. CONCLUSION: Some known risk factors appear to inform, but only modestly, individuals' perceived risk of AD. Furthermore, decisions about AD prevention may not be determined by objective needs alone, suggesting a potential discrepancy between need and demand for AD preventive care.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer disease; Cognition; Female; Health education; Health Knowledge, Attitudes, Practice; Health Surveys; Humans; Linear Models; Male; Multivariate Analysis; Psychometrics; Risk Assessment; Risk Factors; Social Perception; Statistics as Topic; United States

Smoking and weight change after new health diagnoses in older adults. - Patricia S Keenan (Arch Intern Med, 2009)
BACKGROUND: Smoking and patterns of diet and activity are the 2 leading underlying causes of death in the United States, yet the factors that prompt individuals to adopt healthier habits are not well understood. METHODS: This study was undertaken to determine whether individuals who have experienced recent adverse health events are more likely to quit smoking or to lose weight than those without recent events using Health and Retirement Study panel survey data for 20 221 overweight or obese individuals younger than 75 years and 7764 smokers from 1992 to 2000. RESULTS: In multivariate analyses, adults with recent diagnoses of stroke, cancer, lung disease, heart disease, or diabetes mellitus were 3.2 times more likely to quit smoking than were individuals without new diagnoses (P < .001). Among overweight or obese individuals younger than 75 years, those with recent diagnoses of lung disease, heart disease, or diabetes mellitus lost -0.35 U of body mass index (calculated as weight in kilograms divided by height in meters squared) compared with those without these new diagnoses (P < .001). Smokers with multiple new diagnoses were 6 times more likely to quit smoking compared with those with no new diagnoses. The odds of quitting smoking were 5 times greater in individuals with a new diagnosis of heart disease, and body mass index declined by 0.6 U in overweight or obese individuals with a new diagnosis of diabetes mellitus (P < .001). CONCLUSIONS: Across a range of health conditions, new diagnoses can serve as a window of opportunity that prompts older adults to change health habits, in particular, to quit smoking. Quality improvement efforts targeting secondary as well as primary prevention through the health care system are likely well founded.
Keywords: Age Factors; Aged; Aged, 80 and over; Body Mass Index; Diabetes Mellitus, Type 2; Health Behavior; Health Surveys; Heart Diseases; Humans; Longitudinal Studies; Lung Diseases; Middle Aged; Multivariate Analysis; Neoplasms; Overweight; Racial Groups; Smoking; Smoking cessation; Stroke; United States; Weight Loss

Smoking kills, obesity disables: a multistate approach of the US Health and Retirement Survey. - Mieke Reuser; Luc G Bonneux; Frans J Willekens (Obesity (Silver Spring), 2009)
Increasing BMI causes concerns about the consequences for health care. Decreasing cardiovascular mortality has lowered obesity-related mortality, extending duration of disability. We hypothesized increased duration of disability among overweight and obese individuals. We estimated age-, risk-, and state-dependent probabilities of activities of daily living (ADL) disability and death and calculated multistate life tables, resulting in the comprehensive measure of life years with and without ADL disability. We used prospective data of 16,176 white adults of the Health and Retirement Survey (HRS). Exposures were self-reported BMI and for comparison smoking status and levels of education. Outcomes were years to live with and without ADL disability at age 55. The reference categories were high normal weight (BMI: 23-24.9), nonsmoking and high education. Mild obesity (BMI: 30-34.9) did not change total life expectancy (LE) but exchanged disabled for disability-free years. Mild obesity decreased disability-free LE with 2.7 (95% confidence limits 1.2; 3.2) year but increased LE with disability with 2.0 (0.6; 3.4) years among men. Among women, BMI of 30 to 34.9 decreased disability-free LE with 3.6 (2.1; 5.1) year but increased LE with disability with 3.2 (1.6;4.8) years. Overweight (BMI: 25-29.9) increases LE with disability for women only, by 2.1 (0.8; 3.3) years). Smoking compressed disability by high mortality. Smoking decreased LE with 7.2 years, and LE with disability with 1.3 (0.5; 2.5) years (men) and 1.4 (0.3; 2.6) years (women). A lower education decreased disability-free life, but not duration of ADL disability. In the aging baby boom, higher BMI will further increase care dependence.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Body Mass Index; Disability Evaluation; Educational Status; Female; Health Surveys; Humans; Life Expectancy; Life Tables; Male; Middle Aged; Obesity; Proportional Hazards Models; Prospective Studies; Smoking; United States; White People

Socioeconomic differentials in immune response. - Jennifer B Dowd; Allison E Aiello (Epidemiology, 2009)
BACKGROUND: Lower socioeconomic status (SES) is strongly linked to health outcomes, though the mechanisms are poorly understood. Little is known about the role of the immune system in creating and sustaining health disparities. Here we test whether SES is related to cell-mediated immunity, as measured by the host's ability to keep persistent cytomegalovirus (CMV) antibody levels in a quiescent state. METHODS: Censored regression models were used to test the cross-sectional relationship of education, income, and race/ethnicity with antibody response to CMV, using a nationally representative sample of 9721 respondents aged 25 years and older in the Third National Health and Nutrition Examination Survey (NHANES III, 1988-1994). RESULTS: Among CMV-seropositive respondents, those with less education, lower income, and nonwhite race/ethnicity had higher levels of CMV antibodies at all ages. On average, each additional year of age was associated with CMV antibody levels that were 0.03 units higher (95% confidence interval = 0.03 to 0.04), whereas each additional year of education was associated with antibody levels that were 0.05 units lower (0.02 to 0.09). A doubling of family income was associated with antibody levels that were 0.25 units lower (0.11 to 0.39), the equivalent of 8 fewer years of age-related CMV antibody response. These relationships remained strong after controlling for baseline health conditions, smoking status, and BMI. CONCLUSIONS: SES is associated with an indirect marker of cell-mediated immunity in a nationally representative sample. SES differences in immune control over CMV may have fundamental implications for health disparities over the life course.
Keywords: Adult; Aged; Cytomegalovirus; Cytomegalovirus Infections; Female; Health Status Disparities; Humans; Male; Middle Aged; Nutrition Surveys; Regression Analysis; Social Class; United States

Statistical design and estimation for the national social life, health, and aging project. - O'Muircheartaigh, Colm; Eckman, Stephanie; Smith, Stephen (J Gerontol B Psychol Sci Soc Sci, 2009)
OBJECTIVES: The paper discusses the sample design of the National Social Life, Health, and Aging Project (NSHAP) and how the design affects how estimates should be calculated from the survey data. The NSHAP study allows researchers to study the links between sexuality and health in older adults. The goal of the design was to represent adults aged 57-85 years in six demographic domains. METHODS: The sample design begins with a national area probability sample of households, carried out jointly with the 2004 round of the Health and Retirement Study. Selection of respondents for NSHAP balanced age and gender subgroups and oversampled African Americans and Latinos. Data collection was carried out from July 2005 to March 2006. RESULTS: The survey obtained an overall response rate of 75.5%. DISCUSSION: The complex sample design requires that the selection probabilities and the field implementation be accounted for in estimating population parameters. The data set contains weights to compensate for differential probabilities of selection and response rates among demographic groups. Analysts should use weights in constructing estimates from the survey and account for the complex sample design in estimating standard errors for survey estimates.
Keywords: Aged; Aged, 80 and over; Aging; Bias; Data collection; Data Interpretation, Statistical; Female; Health Status; Health Surveys; Humans; Longitudinal Studies; Male; Mass Screening; Middle Aged; Research Design; Sampling Studies; Sexual Behavior; Social Behavior; United States

Trajectories of cognitive function in late life in the United States: demographic and socioeconomic predictors. - Arun S Karlamangla; Miller-Martinez, Dana; Carol S Aneshensel; Teresa Seeman; Richard G Wight; Joshua Chodosh (Am J Epidemiol, 2009)
This study used mixed-effects modeling of data from a national sample of 6,476 US adults born before 1924, who were tested 5 times between 1993 and 2002 on word recall, serial 7's, and other mental status items to determine demographic and socioeconomic predictors of trajectories of cognitive function in older Americans. Mean decline with aging in total cognition score (range, 0-35; standard deviation, 6.00) was 4.1 (0.68 standard deviations) per decade (95% confidence interval: 3.8, 4.4) and in recall score (range, 0-20; standard deviation, 3.84) was 2.3 (0.60 standard deviations) per decade (95% confidence interval: 2.1, 2.5). Older cohorts (compared with younger cohorts), women (compared with men), widows/widowers, and those never married (both compared with married individuals) declined faster, and non-Hispanic blacks (compared with non-Hispanic whites) and those in the bottom income quintile (compared with the top quintile) declined slower. Race and income differences in rates of decline were not sufficient to offset larger differences in baseline cognition scores. Educational level was not associated with rate of decline in cognition scores. The authors concluded that ethnic and socioeconomic disparities in cognitive function in older Americans arise primarily from differences in peak cognitive performance achieved earlier in the life course and less from declines in later life.
Keywords: Aged; Aged, 80 and over; Aging; Black or African American; Cognition; Confidence Intervals; Education; Female; Geriatric Assessment; Hispanic or Latino; Humans; Income; Male; Marital Status; Mexican Americans; Poverty; Sampling Studies; Socioeconomic factors; Surveys and Questionnaires; United States; White People

Volunteer dynamics of older Americans. - Barbara A Butrica; Richard W. Johnson; Sheila R Zedlewski (J Gerontol B Psychol Sci Soc Sci, 2009)
OBJECTIVES: The impending retirement of boomers has spurred interest in tapping their productive energies to benefit society. This study examined volunteer transitions among older adults to understand the factors that affect volunteer dynamics. METHODS: Using data from the Health and Retirement Study, the analysis examined entries into and exits from formal volunteer activities between 1996 and 2004 by adults aged 55-65 at study baseline. The study showed the duration of volunteer activities, the probability that older adults start and stop volunteering, and the factors that significantly predict volunteer transitions. RESULTS: The findings reveal considerable stability among both volunteers and nonvolunteers; however, older adults are more likely to stop volunteering than to start. Volunteers who contribute intensely and for many years and who are married to volunteers are the least likely to quit. And nonvolunteers are more likely to start volunteering if they have been uninvolved for few years and their spouses volunteer. CONCLUSIONS: The results point to the need to focus efforts on retaining older volunteers to maximize volunteer engagement during later years. Recruiting older adults in volunteer activities early on, ideally before they retire, could also help meet volunteer needs.
Keywords: Aged; Aging; Cross-Sectional Studies; Female; Humans; Life Change Events; Male; Middle Aged; Probability; Retirement; United States; Volunteers

Weight change, initial BMI, and mortality among middle- and older-aged adults. - Mikko Myrskylä; Virginia W Chang (Epidemiology, 2009)
BACKGROUND: It is not known how the relationship between weight change and mortality is influenced by initial body mass index (BMI) or the magnitude of weight change. METHODS: We use the nationally representative Health and Retirement Study (n = 13,104; follow-up 1992-2006) and Cox regression analysis to estimate relative mortality risks for 2-year weight change by initial BMI among 50- to-70-year-old Americans. We defined small weight loss or gain as a change of 1-2.9 BMI units and large weight loss or gain as a change of 3-5 BMI units. RESULTS: Large and small weight losses were associated with excess mortality for all initial BMI levels below 32 kg/m (eg, hazard ratio [HR] for large weight loss from BMI of 30 = 1.61 [95% confidence interval = 1.31-1.98]; HR for small weight loss from BMI of 30 = 1.19 [1.06-1.28]). Large weight gains were associated with excess mortality only at high BMIs (eg, HR for large weight gain from BMI of 35 = 1.33 [1.00-1.77]). Small weight gains were not associated with excess mortality for any initial BMI level. The weight loss-mortality association was robust to adjustments for health status and to sensitivity analyses considering unobserved confounders. CONCLUSIONS: Weight loss is associated with excess mortality among normal, overweight, and mildly obese middle- and older-aged adults. The excess risk increases for larger losses and lower initial BMI. These results suggest that the potential benefits of a lower BMI may be offset by the negative effects associated with weight loss. Weight gain may be associated with excess mortality only among obese people with an initial BMI over 35.
Keywords: Aged; Body Mass Index; Humans; Middle Aged; Mortality; Proportional Hazards Models; Prospective Studies; United States; Weight Gain; Weight Loss

Actuation of mobility intentions among the young-old: an event-history analysis. - Don E Bradley; Charles F Longino; Eleanor P. Stoller; William H Haas (Gerontologist, 2008)
PURPOSE: Although migration decision making is central to understanding later-life migration, the critical step between migration intentions and mobility outcomes has received only limited empirical attention. We address two questions: How often are intended moves actuated? What factors condition the likelihood that mobility intentions will be actuated? DESIGN AND METHODS: We employ data from the 1994-2002 Health and Retirement Study, which is a nationally representative panel targeting households containing persons aged 53 to 63 years at baseline. Event-history techniques are used to examine the link between reported mobility intentions at baseline and mobility outcomes across the study period, net of relevant controls. We conduct separate household-level analyses for couple and noncouple households and recognize three types of moves: local, family oriented, and nonlocal. RESULTS: Findings confirm the utility of mobility expectations as a predictor of future mobility. More importantly, results highlight the complex nature of later-life mobility. The actuation of mobility intentions appears to operate differently in couple than in noncouple households. Moreover, our findings suggest that the role of several key variables depends on the type of move under consideration. IMPLICATIONS: The ability to identify potential "retirement migrants" may be of practical importance for state and local government officials as well as developers interested in recruiting or retaining young-old residents. Our study offers insight on the interpretation of stated mobility intentions. Moreover, consistent with early theoretical work in the field, our analysis suggests that empirical studies must account for heterogeneity among older movers in order to avoid misleading results.
Keywords: Aged; Databases as Topic; Emigration and Immigration; Humans; Intention; Middle Aged; Population Dynamics; Retirement; United States

Age and racial/ethnic disparities in arthritis-related hip and knee surgeries. - Dorothy D Dunlop; Larry M Manheim; Song, Jing; Sohn, Min-Woong; Joseph Feinglass; Huan J. Chang; Rowland W Chang (Med Care, 2008)
BACKGROUND: Nearly 18 million Americans experience limitations due to their arthritis. Documented disparities according to racial/ethnic groups in the use of surgical interventions such as knee and hip arthroplasty are largely based on data from Medicare beneficiaries age 65 or older. Whether there are disparities among younger adults has not been previously addressed. OBJECTIVE: This study assesses age-specific racial/ethnic differences in arthritis-related knee and hip surgeries. DESIGN: Longitudinal (1998-2004) Health and Retirement Study. SETTING: National probability sample of US community-dwelling adults. SAMPLE: A total of 2262 black, 1292 Hispanic, and 13,159 white adults age 51 and older. MEASUREMENTS: The outcome is self-reported 2-year use of arthritis-related hip or knee surgery. Independent variables are demographic (race/ethnicity, age, gender), health needs (arthritis, chronic diseases, obesity, physical activity, and functional limitations), and medical access (income, wealth, education, and health insurance). Longitudinal data methods using discrete survival analysis are used to validly account for repeated (biennial) observations over time. Analyses use person-weights, stratum, and sampling error codes to provide valid inferences to the US population. RESULTS: Black adults under the age of 65 years report similar age/gender adjusted rates of hip/knee arthritis surgeries [hazard ratio (HR) = 1.43, 95% confidence interval (CI) = 0.87-2.38] whereas older blacks (age 65+) have significantly lower rates (HR = 0.38, CI = 0.16-0.55) compared with whites. These relationships hold controlling for health and economic differences. Both under age 65 years (HR = 0.64, CI = 0.12-1.44) and older (age 65+) Hispanic adults (HR = 0.60, CI = 0.32-1.10) report lower utilization rates, although not statistically different than whites. A large portion of the Hispanic disparity is explained by economic differences. CONCLUSIONS: These national data document lower rates of arthritis-related hip/knee surgeries for older black versus white adults age 65 or above, consistent with other national studies. However, utilization rates for black versus white under age 65 do not differ. Lower utilization among Hispanics versus whites in both age groups is largely explained by medical access factors. National utilization patterns may vary by age and merit further investigation.
Keywords: Age Distribution; Aged; Arthritis; Arthroplasty, Replacement, Hip; Arthroplasty, Replacement, Knee; Black or African American; Female; Health Services Accessibility; Healthcare Disparities; Hispanic or Latino; Humans; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; United States; Utilization Review; White People

The burden of mortality of obesity at middle and old age is small. A life table analysis of the US Health and Retirement Survey. - Mieke Reuser; Luc G Bonneux; Frans J Willekens (Eur J Epidemiol, 2008)
The evidence of effect of overweight and obesity on mortality at middle and old age is conflicting. The increased relative risk of cardiovascular disease and diabetes for overweight and obese individuals compared to normal weight is well documented, but the absolute risk of cardiovascular death has decreased spectacularly since the 1980s. We estimate the burden of mortality of obesity among middle and old aged adults in the Health and Retirement Survey (HRS), a US prospective longitudinal study. We calculate univariate and multivariate age-specific probabilities and proportional hazard ratios of death in relation to self-reported body mass index (BMI), smoking and education. The life table translates age specific adjusted event rates in survival times, dependent on risk factor distributions (smoking, levels of education and self reported BMI). 95% confidence intervals are calculated by bootstrapping. The highest life expectancy at age 55 was found in overweight (BMI 25-29.9), highly educated non smokers: 30.7 (29.5-31.9) years (men) and 33.2 (32.1-34.3) (women), slightly higher than a BMI 23-24.9 in both sexes. Smoking decreased the population life expectancy with 3.5 (2.7-4.4) years (men) and 1.8 (1.0-2.5) years (women). Less than optimal education cost men and women respectively 2.8 (2.1-3.6) and 2.6 (1.6-3.6) years. Obesity and low normal weight decreased population life expectancy respectively by 0.8 (0.2-1.3) and 0.8 (0.0-1.5) years for men and women in a contemporary, US population. The burden of mortality of obesity is limited, compared to smoking and low education.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Educational Status; Female; Health Surveys; Humans; Life Expectancy; Life Tables; Male; Middle Aged; Multivariate Analysis; Obesity; Proportional Hazards Models; Smoking; United States; Weight Gain; Weight Loss

Changes in weight among U.S. adults aged 70 and over, 1993 to 2002. - Xiaoxing He; Meng, Hongdao (Prev Med, 2008)
OBJECTIVE: To describe the patterns and predictors of weight change among U.S. adults aged 70 and over. METHOD: The study is a retrospective cohort study of 7441 community-dwelling U.S. adults aged 70 years and over during 1993-2002. We examined changes in weight for men and women, and by race/ethnicity groups. We used multivariate linear regression analysis to determine predictors of weight change while controlling for key covariates at baseline. RESULTS: The mean body weight decreased in both genders and all ethnic groups. Unadjusted average weight loss was 3.41 kg for men and 3.29 kg for women over nine years. Black women had higher mean body weight at baseline and were more likely to report weight gains of 5 kg or more. Multivariate analysis showed that age and baseline weight were major predictors of weight loss. Physical activity was associated with less weight loss among men. CONCLUSION: The trends of weight change among U.S. adults aged 70 and over were more prone to weight loss than weight gain, with substantial variations. Public health messages regarding weight control should take into account the heterogeneity of this population and target weight loss as well as weight gain to meet diverse needs of the population.
Keywords: Aged; Aged, 80 and over; Aging; Female; Humans; Interviews as Topic; Linear Models; Male; Multivariate Analysis; Population Growth; Retrospective Studies; United States; Weight Gain; Weight Loss

Chronic conditions and mortality among the oldest old. - Sei J. Lee; Alan S Go; Lindquist, Karla; Bertenthal, Daniel; Kenneth E Covinsky (Am J Public Health, 2008)
OBJECTIVES: We sought to determine whether chronic conditions and functional limitations are equally predictive of mortality among older adults. METHODS: Participants in the 1998 wave of the Health and Retirement Study (N=19430) were divided into groups by decades of age, and their vital status in 2004 was determined. We used multivariate Cox regression to determine the ability of chronic conditions and functional limitations to predict mortality. RESULTS: As age increased, the ability of chronic conditions to predict mortality declined rapidly, whereas the ability of functional limitations to predict mortality declined more slowly. In younger participants (aged 50-59 years), chronic conditions were stronger predictors of death than were functional limitations (Harrell C statistic 0.78 vs. 0.73; P=.001). In older participants (aged 90-99 years), functional limitations were stronger predictors of death than were chronic conditions (Harrell C statistic 0.67 vs. 0.61; P=.004). CONCLUSIONS: The importance of chronic conditions as a predictor of death declined rapidly with increasing age. Therefore, risk-adjustment models that only consider comorbidities when comparing mortality rates across providers may be inadequate for adults older than 80 years.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic disease; Female; Health Behavior; Health Status; Humans; Male; Middle Aged; Models, Statistical; Predictive Value of Tests; Proportional Hazards Models; Reproducibility of Results; Risk Adjustment; Severity of Illness Index; Socioeconomic factors; Survival Analysis; United States

Cohort differences in wealth and pension participation of near-retirees. - Irena Dushi; Howard M Iams (Soc Secur Bull, 2008)
The approaching retirement of the baby-boom generation has attracted both research and public policy attention. Many social and economic changes occurred during the second half of the twentieth century, changes that are likely to affect the retirement economic security of recent cohorts in many ways. In this article, using data from the Health and Retirement Study (HRS), a longitudinal, nationally representative survey of older Americans, we compare potential retirement economic resources-pension participation and nonpension net worth-of two cohorts of near-retirees. Particularly we look at individuals born from 1933 through 1939, often referred to as depression babies, who were ages 55-61 in 1994 and the more recent cohort consisting of individuals of the same ages (55-61) in 2004, who were born from 1943 through 1949. Our findings indicate that the more recent cohort of near-retirees has a significantly higher pension participation rate over their working life, and therefore greater opportunity to establish pension income through their working life, compared with the earlier cohort (82 percent versus 64 percent). The increase in pension participation was more pronounced among the recent cohort of women, an expected outcome given the increase in labor force participation of women over the past half century. As a result, although differences by sex in pension participation remained significant, the gap has narrowed for the recent cohort of near-retirees. In addition, we find that the gap in participation rate between those in the highest and the lowest wealth quintiles has widened over time (from 22 percent in 1994 to 26 percent in 2004). For both cohorts of near-retirees, the evidence indicates that those without a pension have much lower levels of net total worth than those who report having a pension. The pattern that emerges for both cohorts is that about one-fifth of individuals aged 55-61 hold little or no wealth at all, whereas about two-fifths hold a substantial amount of wealth. In addition, housing equity, which rarely is used to finance consumption in retirement, comprises more than one-half of total nonpension net worth for about 60 percent of all households, leaving--on average less than $45,000 jointly in nonhousing wealth and IRA/Keogh assets--a much smaller amount of wealth that is readily accessible if the need arises. The fact that many near-retirees (about 40 percent) in the lowest-two wealth quintiles have no pension to potentially draw income from, coupled with the very low level of total nonpension wealth raises concern about their income security in retirement; they may be likely to rely heavily on Social Security, rely on welfare programs, or continue work in retirement.
Keywords: Female; Humans; Income; Longitudinal Studies; Male; Middle Aged; Pensions; Population Growth; Retirement; United States

Declines in late-life disability: the role of early- and mid-life factors. - Vicki A Freedman; Linda G Martin; Robert F. Schoeni; Jennifer C. Cornman (Soc Sci Med, 2008)
Investigations into the reasons for declines in late-life disability have largely focused on the role of contemporaneous factors. Adopting a life-course perspective as a backdrop, in this paper we ask whether there also has been a role for selected early- and mid-life factors in the decline, and if so whether these factors have been operating through changes in the risks of disability onset or recovery. Drawing on five waves from 1995 to 2004 of the U.S. Health and Retirement Study, we found for the 75 years and older population in the United States that the prevalence of difficulty with activities of daily living (ADL) declined from 30.2% in 1995 to 26.0% in 2004, whereas the trend in difficulty with instrumental activities of daily living (IADL) was flat. Onset of ADL limitations also was reduced during this period while recovery increased. Changes in the educational composition of the older population were linked to declines in the prevalence of ADL limitations, but there were also modest contributions of changes in mother's education, self-rated childhood health, and lifetime occupation. Declines in late-life vision impairments and increases in wealth also contributed substantially to the downward trend, and had chronic conditions not increased, it would have been even larger. Reductions in the onset of ADL limitations were partly driven by changes in educational attainment of respondents and their mothers and, in late-life, better vision and wealth. In contrast, the recovery trend was not accounted for by changes in early- or mid-life factors. We conclude that early- and mid-life factors have contributed along with late-life factors to U.S. late-life disability trends mainly through their influence on the onset of, rather than recovery from, limitations.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; Chronic disease; Cross-Sectional Studies; Disabled Persons; Female; Frail Elderly; Health Behavior; Health Status; Health Surveys; Humans; Life Style; Logistic Models; Male; Morbidity; Population Surveillance; Socioeconomic factors; United States

Degree of disability and patterns of caregiving among older Americans with congestive heart failure. - Tanya R Gure; Mohammed U Kabeto; Caroline S Blaum; Kenneth M. Langa (J Gen Intern Med, 2008)
OBJECTIVES: Although congestive heart failure (CHF) is a common condition, the extent of disability and caregiving needs for those with CHF are unclear. We sought to determine: (1) prevalence of physical disability and geriatric conditions, (2) whether CHF is independently associated with disability, (3) rates of nursing home admission, and (4) formal and informal in-home care received in the older CHF population. METHODS: We used cross-sectional data from the 2000 wave of the Health and Retirement Study. We compared outcomes among three categories of older adults: (1) no coronary heart disease (CHD), (2) CHD, without CHF, and (3) CHF. Compared to those without CHF, respondents reporting CHF were more likely to be disabled (P < 0.001) and to have geriatric conditions (P < 0.001). Respondents reporting CHF were more likely to have been admitted to a nursing home (P < 0.05). CHF respondents were more functionally impaired than respondents without CHF. RESULTS: The adjusted average weekly informal care hours for respondents reporting CHF was higher than for those reporting CHD but without CHF and those reporting no CHD (6.7 vs 4.1 vs 5.1, respectively; P < 0.05). Average weekly formal caregiving hours also differed among the three groups (1.3 CHF vs 0.9 CHD without CHF vs 0.7 no CHD; P > 0.05). CONCLUSIONS: CHF imposes a significant burden on patients, families, and the long-term care system. Older adults with CHF have higher rates of disability, geriatric conditions, and nursing home admission.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Coronary Disease; Cross-Sectional Studies; Disabled Persons; Female; Health Surveys; Heart Failure; Hospitalization; Humans; Male; Nursing homes; United States

Depression and retirement in late middle-aged U.S. workers. - Jalpa A Doshi; Cen, Liyi; Daniel Polsky (Health Serv Res, 2008)
OBJECTIVE: To determine whether late middle-aged U.S. workers with depression are at an increased risk for retirement. DATA SOURCE: Six biennial waves (1992-2002) of the Health and Retirement Study, a nationally representative panel survey of noninstitutionalized 51-61-year-olds and their spouses started in 1992. STUDY DESIGN: Workers aged 53-58 years in 1994 were followed every 2 years thereafter, through 2002. Depression was coded as lagged time-dependent variables measuring active depression and severity of depression. The main outcome variable was a transition to retirement which was measured using two distinct definitions to capture different stages in the retirement process: (1) Retirement was defined as a transition out of the labor force in the sample of all labor force participants (N=2,853); (2) In addition a transition out of full time work was used as the retirement definition in the subset of labor force participants who were full time workers (N=2,288). PRINCIPAL FINDINGS: In the sample of all labor force participants, the presence of active depression significantly increased the hazard of retirement in both late middle-aged men (adjusted OR: 1.37 [95 percent CI 1.05, 1.80]) and women (adjusted OR: 1.40 [95 percent CI 1.10, 1.78]). For women, subthreshold depression was also a significant predictor of retirement. In the sample of full time workers, the relationship between depression and retirement was considerably weaker for women yet remained strong for men. CONCLUSIONS: Depression and depressive symptoms were significantly associated with retirement in late middle-aged U.S. workers. Policymakers must consider the potentially adverse impact of these labor market outcomes when estimating the cost of untreated depression and evaluating the value of interventions to improve the diagnosis and treatment of depression.
Keywords: Activities of Daily Living; Comorbidity; depression; Employment; Female; Humans; Male; Middle Aged; Retirement; Severity of Illness Index; Sex Factors; Socioeconomic factors; United States

Divergent pathways? Racial/ethnic differences in older women's labor force withdrawal. - Tyson H Brown; David F Warner (J Gerontol B Psychol Sci Soc Sci, 2008)
OBJECTIVES: The purpose of this study was to investigate how women's labor force withdrawal behavior varies across race/ethnicity and to identify life course factors that generate these differences. METHODS: Using a sample of 7,235 women from the 1992-2004 Health and Retirement Study, we estimated cross-sectional multinomial logit models to explore racial/ethnic differences in labor force status at first interview. We then examined the prospective risk of exiting the labor force via retirement, work disability, or death using discrete-time hazard models. RESULTS: Black and Hispanic women had twice the odds of Whites of being work-disabled at first interview. Whereas younger minorities had lower odds of being retired at first interview, older minorities had higher odds. The prospective results showed that both Blacks and Hispanics had higher risks of work disability but not of retirement or of dying in the labor force. Overall, racial/ethnic differences in mid- and later life work behavior stemmed primarily from disparities in life course capital. DISCUSSION: This study shows that substantial racial/ethnic disparities in labor force exit behavior have already emerged by midlife. It is important to note that distinguishing between alternative pathways out of the labor force demonstrates that work disability is a more common experience for Black and Hispanic women than for Whites.
Keywords: Aged; Black People; Demography; Disability Evaluation; Disabled Persons; Employment; ethnicity; Hispanic or Latino; Humans; Middle Aged; Retirement; United States

Dynamics of work disability and pain. - Arie Kapteyn; James P Smith; Arthur H.O. vanSoest (J Health Econ, 2008)
This paper investigates the role of pain dynamics in subsequently affecting dynamics in self-reported work disability and the dynamics of employment patterns of older workers in the US. Not only is pain prevalence quite high, there also are many transitions in and out of pain at these ages. We investigate pain and its relationship to health (work disability) and work in a dynamic panel data model, using six biennial waves from the Health and Retirement Study. We find that the dynamics of the presence of pain are central to understanding the dynamics of self-reported work disability and through this pathway, pain dynamics are also a significant factor in the dynamic patterns of employment.
Keywords: Aged; Disabled Persons; Employment; Female; Humans; Male; Middle Aged; Models, Statistical; pain; United States

Early motherhood and mental health in midlife: a study of British and American cohorts. - John C Henretta; Emily M D Grundy; Lucy C Okell; Michael E J Wadsworth (Aging Ment Health, 2008)
OBJECTIVES: Examine the relationship between early age at first birth and mental health among women in their fifties. METHODS: Analysis of data on women from a British 1946 birth cohort study and the U.S. Health and Retirement Study birth cohort of 1931-1941. RESULTS: In both samples a first birth before 21 years, compared to a later first birth, is associated with poorer mental health. The association between early first birth and poorer mental health persists in the British study even after controlling for early socioeconomic status, midlife socioeconomic status and midlife health. In the U.S. sample, the association becomes non-significant after controlling for educational attainment. CONCLUSIONS: Early age at first birth is associated with poorer mental health among women in their fifties in both studies, though the pattern of associations differs.
Keywords: Adolescent; Birth Order; Cohort Studies; England; Female; Humans; Interviews as Topic; Maternal Age; Mental Health; Middle Aged; Mothers; Pregnancy; Pregnancy in Adolescence; United States

Educational differentials in life expectancy with cognitive impairment among the elderly in the United States. - Agnès Lièvre; Dawn E Alley; Eileen M. Crimmins (J Aging Health, 2008)
OBJECTIVE: This article provides estimates of education differentials in life expectancy with and without cognitive impairment for the noninstitutionalized population aged 70 years and older in the United States. METHOD: Life expectancy with cognitive impairment was calculated using multistate models, allowing transitions between cognitively intact and cognitively impaired states and from each of these states to death and allowing transition rates to vary across age and education. Four waves of the Assets and Health Dynamics of the Oldest Old survey were used. RESULTS: Those with low levels of education are more likely to become cognitively impaired and do so at an earlier age. After age 70, persons with low educational levels can expect to live 11.6 years, and persons with high education 14.1 years, without cognitive impairment. Length of life with cognitive impairment differs by education (1.6 years and 1.0 years at age 70, respectively) but differs little by age. DISCUSSION: Although those with higher education have lower rates of both cognitive impairment and mortality, those who do become cognitively impaired appear to be in poorer health, leading to a reduced probability of improved cognition and increased probability of mortality relative to those with lower educational levels.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Educational Status; Female; Humans; Life Expectancy; Male; United States

Effects of social integration on preserving memory function in a nationally representative US elderly population. - Karen A Ertel; M. Maria Glymour; Lisa F Berkman (Am J Public Health, 2008)
OBJECTIVES: We tested whether social integration protects against memory loss and other cognitive disorders in late life in a nationally representative US sample of elderly adults, whether effects were stronger among disadvantaged individuals, and whether earlier cognitive losses explained the association (reverse causation). METHODS: Using data from the Health and Retirement Study (N = 16,638), we examined whether social integration predicted memory change over 6 years. Memory was measured by immediate and delayed recall of a 10-word list. Social integration was assessed by marital status, volunteer activity, and frequency of contact with children, parents, and neighbors. We examined growth-curve models for the whole sample and within subgroups. RESULTS: The mean memory score declined from 11.0 in 1998 to 10.0 in 2004. Higher baseline social integration predicted slower memory decline in fully adjusted models (P<.01). Memory among the least integrated declined at twice the rate as among the most integrated. This association was largest for respondents with fewer than 12 years of education. There was no evidence of reverse causation. CONCLUSIONS: Our study provides evidence that social integration delays memory loss among elderly Americans. Future research should focus on identifying the specific aspects of social integration most important for preserving memory.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Female; Health Behavior; Health Status; Humans; Interpersonal Relations; Male; Mental Health; Mental Recall; Predictive Value of Tests; Reproducibility of Results; Severity of Illness Index; social isolation; Social Support; Socioeconomic factors; United States

Emergency department utilization patterns among older adults. - Frederic D Wolinsky; Li Liu; Thomas R Miller; An, Hyonggin; John F Geweke; Kaskie, Brian; Kara B Wright; Elizabeth A Chrischilles; Claire E Pavlik; Elizabeth A Cook; Robert L. Ohsfeldt; Kelly K Richardson; et al. (J Gerontol A Biol Sci Med Sci, 2008)
BACKGROUND: We identified 4-year (2 years before and 2 years after the index [baseline] interview) ED use patterns in older adults and the factors associated with them. METHODS: A secondary analysis of baseline interview data from the nationally representative Survey on Assets and Health Dynamics Among the Oldest Old linked to Medicare claims data. Participants were 4310 self-respondents 70 years old or older. Current Procedural Terminology (CPT) codes 99281 and 99282 identified low-intensity use, and CPT codes 99283-99285 identified high-intensity use. Exploratory factor analysis and multivariable multinomial logistic regression were used. RESULTS: The majority (56.6%) of participants had no ED visits during the 4-year period. Just 5.7% had only low-intensity ED use patterns, whereas 28.9% used the ED only for high-intensity visits, and 8.7% had a mixture of low-intensity and high-intensity use. Participants with lower immediate word recall scores and those who did not live in major metropolitan areas were more likely to be low-intensity-only ED users. Older individuals, those who did not live in rural counties, had greater morbidity and functional status burdens, and lower immediate word recall scores were more likely to be high-intensity-only ED users. Participants who were older, did not live in major cities, had lower education levels, had greater morbidity and functional status burdens, and lower immediate word recall scores were more likely to have mixed ED use patterns. CONCLUSIONS: Nearly half of these older adults used the ED at least once over a 4-year period, with a mean annual ED use percentage of 18.4. Few, however, used the ED only for visits that may have been avoidable. This finding suggests that triaging Medicare patients would not decrease ED overcrowding, although continued surveillance is necessary to detect potential changes in ED use patterns among older adults.
Keywords: Aged; Emergency Service, Hospital; Factor Analysis, Statistical; Female; Humans; Logistic Models; Male; Medicare; Risk Factors; United States

End-of-life medical treatment choices: do survival chances and out-of-pocket costs matter? - Chao, Li-Wei; José A Pagán; Beth J Soldo (Med Decis Making, 2008)
BACKGROUND: Out-of-pocket medical expenditures incurred prior to the death of a spouse could deplete savings and impoverish the surviving spouse. Little is known about the public's opinion as to whether spouses should forego such end-of-life (EOL) medical care to prevent asset depletion. OBJECTIVES: To analyze how elderly and near elderly adults assess hypothetical EOL medical treatment choices under different survival probabilities and out-of-pocket treatment costs. METHODS: Survey data on a total of 1143 adults, with 589 from the Asset and Health Dynamics Among the Oldest Old (AHEAD) and 554 from the Health and Retirement Study (HRS), were used to study EOL cancer treatment recommendations for a hypothetical anonymous married woman in her 80s. RESULTS: Respondents were more likely to recommend treatment when it was financed by Medicare than by the patient's own savings and when it had 60% rather than 20% survival probability. Black and male respondents were more likely to recommend treatment regardless of survival probability or payment source. Treatment uptake was related to the order of presentation of treatment options, consistent with starting point bias and framing effects. CONCLUSIONS: Elderly and near elderly adults would recommend that the hypothetical married woman should forego costly EOL treatment when the costs of the treatment would deplete savings. When treatment costs are covered by Medicare, respondents would make the recommendation to opt for care even if the probability of survival is low, which is consistent with moral hazard. The sequence of presentation of treatment options seems to affect patient treatment choice.
Keywords: Aged; Choice Behavior; Female; Financing, Personal; Health Care Costs; Humans; Life Expectancy; Male; Medicare; Neoplasms; Socioeconomic factors; Terminal Care; United States

Exploring the determinants of racial and ethnic disparities in total knee arthroplasty: health insurance, income, and assets. - Amresh D Hanchate; Zhang, Yuqing; David T Felson; Arlene S Ash (Med Care, 2008)
OBJECTIVE: To estimate national total knee arthroplasty (TKA) rates by economic factors, and the extent to which differences in insurance coverage, income, and assets contribute to racial and ethnic disparities in TKA use. DATA SOURCE: US longitudinal Health and Retirement Study survey data for the elderly and near-elderly (biennial rounds 1994-2004) from the Institute of Social Research, University of Michigan. STUDY DESIGN: The outcome is dichotomous, whether the respondent received first TKA in the previous 2 years. Longitudinal, random-effects logistic regression models are used to assess associations with lagged economic indicators. SAMPLE: Sample was 55,469 person-year observations from 18,439 persons; 663, with first TKA. RESULTS: Racial/ethnic disparities in TKA were more prominent among men than women. For example, relative to white women, odds ratios (ORs) were 0.94, 0.46, and 0.79, for white, black, and Hispanic men, respectively (P < 0.05 for black men). After adjusting for economic factors, racial/ethnic differences in TKA rates for women essentially disappeared, while the deficit for black men remained large. Among Medicare-enrolled elderly, those with supplemental insurance may be more likely to have first TKA compared with those without it, whether the supplemental coverage was private [OR: 1.27; 95% confidence interval (CI): 0.82-1.96] or Medicaid (OR: 1.18; 95% CI: 0.93-1.49). Among the near-elderly (age 47-64), compared with the privately insured, the uninsured were less likely (OR: 0.61; 95% CI: 0.40-0.92) and those with Medicaid more likely (OR: 1.53; 95% CI: 1.03-2.26) to have first TKA. CONCLUSIONS: Limited insurance coverage and financial constraints explain some of the racial/ethnic disparities in TKA rates.
Keywords: Aged; Aged, 80 and over; Arthroplasty, Replacement, Knee; Comorbidity; ethnicity; Female; Healthcare Disparities; Humans; Income; Insurance, Health; Logistic Models; Longitudinal Studies; Male; Middle Aged; Sex Distribution; Socioeconomic factors; United States

Gender differences in functional status in middle and older age: are there any age variations? - Jersey Liang; Joan M. Bennett; Benjamin A Shaw; Ana R Quiñones; Wen Ye; Xiao Xu; Mary Beth Ofstedal (J Gerontol B Psychol Sci Soc Sci, 2008)
OBJECTIVES: The present study examines gender differences in changes in functional status after age 50 and how such differences vary across different age groups. METHODS: Data came from the Health and Retirement Study, involving up to six repeated observations of a national sample of Americans older than 50 years of age between 1995 and 2006. We employed hierarchical linear models with time-varying covariates in depicting temporal variations in functional status between men and women. RESULTS: As a quadratic function, the worsening of functional status was more accelerated in terms of the intercept and rate of change among women and those in older age groups. In addition, gender differences in the level of functional impairment were more substantial in older persons than in younger individuals, although differences in the rate of change between men and women remained constant across age groups. DISCUSSION: A life course perspective can lead to new insights regarding gender variations in health within the context of intrapersonal and interpersonal differences. Smaller gender differences in the level of functional impairment in the younger groups may reflect improvement of women's socioeconomic status, greater rate of increase in chronic diseases among men, and less debilitating effects of diseases.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Disabled Persons; Female; Health Status; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; Sex Factors; United States

Health and wealth of elderly couples: causality tests using dynamic panel data models. - Pierre-Carl Michaud; Arthur H.O. vanSoest (J Health Econ, 2008)
A positive relationship between socio-economic status (SES) and health, the "health-wealth gradient", is repeatedly found in many industrialized countries. This study analyzes competing explanations for this gradient: causal effects from health to wealth (health causation) and causal effects from wealth to health (wealth or social causation). Using six biennial waves of couples aged 51-61 in 1992 from the US Health and Retirement Study, we test for causality in panel data models incorporating unobserved heterogeneity and a lag structure supported by specification tests. In contrast to tests relying on models with only first order lags or without unobserved heterogeneity, these tests provide no evidence of causal wealth health effects. On the other hand, we find strong evidence of causal effects from both spouses' health on household wealth. We also find an effect of the husband's health on the wife's mental health, but no other effects from one spouse's health to health of the other spouse.
Keywords: Aged; Causality; Family Characteristics; Female; Health Status Indicators; Humans; Income; Longitudinal Studies; Male; Middle Aged; Models, Econometric; Retirement; Social Class; Spouses; United States

Health insurance coverage as people approach and pass age-eligibility for Medicare. - Caffrey, Christine; Christine L Himes (J Aging Soc Policy, 2008)
This study uses six waves of the Health and Retirement Study (HRS) to measure dynamics of health insurance coverage as people approach and pass age-eligibility for Medicare. Thirteen percent of 59- to 64-year-olds were uninsured and 13% of 65- to 70-year-olds relied solely on Medicare. Those unmarried, in good health, and in poor health had an increased likelihood of being uninsured before age-eligibility for Medicare, while non-whites and those in good health had an increased likelihood of having Medicare-only coverage after age-eligibility for Medicare. Although only a small percentage was continually without coverage or with Medicare-only coverage, a substantial percentage had these coverage types at some point. Limitations and policy implications are included.
Keywords: Aged; Eligibility Determination; Female; Humans; Insurance Coverage; Insurance, Health; Male; Medicare; Middle Aged; United States

[The health status of the elderly population: what do we need to know?]. - Reboucas, Monica; Siulmara Cristina Galera; Pereira, Silvia Regina Mendes; Pereira, Mauricio Gomes (Cien Saude Colet, 2008)
The objective of this research was to evaluate the data on the health of the elderly population available in the Brazilian information system and their correspondence with the North American statistics using the Internet. The North American publication "Older Americans 2000: Key Indicators of Well-Being" was used as a standard. The databases and instruments used in the North American and Brazilian surveys are presented. The North American data are based on the Supplement on Aging and Second Supplement on Aging; Health and Retirement Study; National Health Interview Survey and National Long Term Care Survey. The Brazilian data were collected from the Mortality Information System; Information System of the National Program of Immunizations; National Household Sample Survey conducted in 1998 and 2003 and from the Household Survey on Risk Behavior and Morbidity from Not Transmissible Diseases of 2002-2003. There is a great number of Brazilian information about the aged population of the Country available in the Internet and with few exceptions the information on aged Brazilians corresponds to the information available about aged North Americans.
Keywords: Aged; Brazil; Cross-Sectional Studies; Geriatric Assessment; Health Status Indicators; Humans; Middle Aged; United States

Identification of dementia: agreement among national survey data, medicare claims, and death certificates. - Truls Ostbye; Donald H. Taylor Jr.; Elizabeth C. Clipp; Lynn Van Scoyoc; Brenda L Plassman (Health Serv Res, 2008)
OBJECTIVE: To estimate the proportion of seniors with dementia from three independent data sources and their agreement. DATA SOURCES: The longitudinal Asset and Health Dynamics among the Oldest Old (AHEAD) study (n=7,974), Medicare claims, and death certificate data. STUDY DESIGN: Estimates of the proportion of individuals with dementia from: (1) self- or proxy-reported cognitive status measures from surveys, (2) Medicare claims, and (3) death certificates. Agreement using Cohen's kappa; multivariate logistic regression. PRINCIPAL FINDINGS: The proportion varied substantially among the data sources. Agreement was poor (kappa: 0.14-0.46 depending upon comparison assessed); the individuals identified had relatively modest overlap. CONCLUSIONS: Estimates of dementia occurrence based on cognitive status measures from three independent data sources were not interchangeable. Further validation of these sources is needed. Caution should be used if policy is based on only one data source.
Keywords: Aged; Consensus; Data Interpretation, Statistical; Death Certificates; Dementia; Female; Health Surveys; Humans; Incidence; Insurance Claim Review; Male; Mass Screening; Medicare; Research Design; United States

Impact of functional limitations and medical comorbidity on subsequent weight changes and increased depressive symptoms in older adults. - Valerie L Forman-Hoffman; Kelly K Richardson; Jon W. Yankey; Stephen L Hillis; Robert B Wallace; Frederic D Wolinsky (J Aging Health, 2008)
OBJECTIVE: The primary goal of this study was to determine the effect of the onset of major medical comorbidity and functional decline on subsequent weight change and increased depressive symptoms. METHODS: The sample included a prospective cohort of 53 to 63 year olds (n = 10,150) enrolled in the Health and Retirement Study. Separate lagged covariate models for men and women were used to study the impact of functional decline and medical comorbidity on subsequent increases in depressive symptoms and weight change 2 years later. RESULTS: Functional decline and medical comorbidity were individual predictors of subsequent weight changes but not increased depressive symptoms. Most specific incident medical comorbidities or subtypes of functional decline predicted weight changes in both directions. DISCUSSION: The elevated risk of weight gain subsequent to functional decline or onset of medical comorbidities may require the receipt of preventive measures to reduce further weight-related complications.
Keywords: Activities of Daily Living; Age Factors; Arthritis; Comorbidity; depression; Depressive Disorder; Diabetes Complications; Diabetes Mellitus; Disabled Persons; Female; Health Surveys; Heart Diseases; Humans; Hypertension; Lung Diseases; Male; Mental Disorders; Middle Aged; Neoplasms; Obesity; Risk Factors; Sex Factors; Stroke; United States; Weight Gain

Informal care and Medicare expenditures: testing for heterogeneous treatment effects. - Courtney Harold Van Houtven; Edward C Norton (J Health Econ, 2008)
We estimate the effect of informal care on Medicare expenditures not only for care provided by children but also by the source of informal care (sons versus daughters, children versus others) and recipient characteristics (marital status). Our conceptual framework predicts heterogeneous effectiveness by source and recipient of informal care. We estimate two-part expenditure models as a function of informal care, controlling for endogeneity. We find that informal care by children reduces Medicare long-term care and inpatient expenditures of single elderly. We find that children are less effective caregivers among recipients who are married. For single elderly, child caregivers are more effective than other types. Gender of a child caregiver does not matter.
Keywords: Adult; Aged; Caregivers; Health Expenditures; Humans; Medicare; Models, Econometric; United States

Job loss, retirement and the mental health of older Americans. - Mandal, Bidisha; Roe, Brian (J Ment Health Policy Econ, 2008)
BACKGROUND: Millions of older individuals cope with physical limitations, cognitive changes, and various losses such as bereavement that are commonly associated with aging. Given increased vulnerability to various health problems during aging, work displacement might exacerbate these due to additional distress and to possible changes in medical coverage. Older Americans are of increasing interest to researchers and policymakers due to the sheer size of the Baby Boom cohort, which is approaching retirement age, and due to the general decline in job security in the U.S. labor market. AIMS OF THE STUDY: This research compares and contrasts the effect of involuntary job loss and retirement on the mental health of older Americans. Furthermore, it examines the impact of re-employment on the depressive symptoms. METHODS: There are two fundamental empirical challenges in isolating the effect of employment status on mental health. The first is to control for unobserved heterogeneity--all latent factors that could impact mental health so as to establish the correct magnitude of the effect of employment status. The second challenge is to verify the direction of causality. First difference models are used to control for latent effects and a two-stage least squares regression is used to account for reverse causality. RESULTS: We find that involuntary job loss worsens mental health, and re-employment recaptures the past mental health status. Retirement is found to improve mental health of older Americans. DISCUSSION: With the use of longitudinal data from the Health and Retirement Study surveys and the adoption of proper measures to control for the possibility of reverse causality, this study provides strong evidence of elevating depressive symptoms with involuntary job displacement even after controlling for other late-life events. Women suffer from greater distress levels than men after job loss due to business closure or lay-off. However, women also exhibit better psychological well-being than men following retirement. The present study is the first to report that the re-employment of involuntary job-loss sufferers leads to a recapturing of past mental health status. Additionally, we find that re-entering the labor force is psychologically beneficial to retirees as well. IMPLICATIONS FOR HEALTH CARE PROVISION: It is well established that out-of-pocket expenditures on all forms of health care for seniors with self-diagnosed depression significantly exceeds expenditures for seniors with other common ailments such as hypertension and arthritis in the U.S. Thus, our research suggests that re-employment of older Americans displaced from the labor force will be cost-effective with regard to personal mental health outcomes. IMPLICATIONS FOR HEALTH POLICIES: That re-employment of involuntary job loss sufferers leads to a recapturing of past mental health status illuminates one potential policy trade off - increased resources dedicated to job training and placement for older U.S. workers could reap benefits with regard to reduced private and public mental health expenditures. IMPLICATIONS FOR FURTHER RESEARCH: Further research could more clearly assess the degree to which the mental health benefits of employment among older Americans would warrant the expansion of job training and employment programs aimed at this group.
Keywords: depression; Female; Health Status; Humans; Insurance Coverage; Insurance, Health; Life Change Events; Longitudinal Studies; Male; Mental Health; Middle Aged; Retirement; Socioeconomic factors; Stress, Psychological; Unemployment; United States

Life with and without heart disease among women and men over 50. - Eileen M. Crimmins; Mark D Hayward; Ueda, Hiroshi; Saito, Yasuhiko; Jung K Kim (J Women Aging, 2008)
This article uses a demographic approach and data from the Health and Retirement Survey, a nationally representative sample of the U.S. population, to investigate sex differences in the length of life lived with heart disease and after a heart attack for persons in the United States age 50 and older. On average, women live longer than men with heart disease. At age 50 women can expect to live 7.9 years and men 6.7 years with heart disease. The average woman experiences heart disease onset three years older and heart attacks 4.4 years older than men.
Keywords: Activities of Daily Living; Aged; Female; Health Status; Heart Diseases; Humans; Life Expectancy; Male; Middle Aged; Myocardial Infarction; Patient Education as Topic; Prejudice; Risk Factors; United States; Women's Health; Women's Health Services

Lifecourse social conditions and racial disparities in incidence of first stroke. - M. Maria Glymour; Mauricio Avendano; Steven A Haas; Lisa F Berkman (Ann Epidemiol, 2008)
PURPOSE: Some previous studies found excess stroke rates among black subjects persisted after adjustment for socioeconomic status (SES), fueling speculation regarding racially patterned genetic predispositions to stroke. Previous research was hampered by incomplete SES assessments, without measures of childhood conditions or adult wealth. We assess the role of lifecourse SES in explaining stroke risk and stroke disparities. METHODS: Health and Retirement Study participants age 50+ (n = 20,661) were followed on average 9.9 years for self- or proxy-reported first stroke (2175 events). Childhood social conditions (southern state of birth, parental SES, self-reported fair/poor childhood health, and attained height), adult SES (education, income, wealth, and occupational status) and traditional cardiovascular risk factors were used to predict first stroke onset using Cox proportional hazards models. RESULTS: Black subjects had a 48% greater risk of first stroke incidence than whites (95% confidence interval, 1.33-1.65). Childhood conditions predicted stroke risk in both blacks and whites, independently of adult SES. Adjustment for both childhood social conditions and adult SES measures attenuated racial differences to marginal significance (hazard ratio, 1.13; 95% CI, 1.00-1.28). CONCLUSIONS: Childhood social conditions predict stroke risk in black and White American adults. Additional adjustment for adult SES, in particular wealth, nearly eliminated the disparity in stroke risk between black and white subjects.
Keywords: Aged; Aged, 80 and over; Black or African American; Cardiovascular Diseases; ethnicity; Female; Health Status Disparities; Humans; Incidence; Interviews as Topic; Life Style; Longitudinal Studies; Male; Middle Aged; Models, Statistical; Risk Factors; Social Environment; Socioeconomic factors; Stroke; United States; White People

Measurement differences in depression: chronic health-related and sociodemographic effects in older Americans. - Frances Margaret Yang; Richard N Jones (Psychosom Med, 2008)
OBJECTIVE: To evaluate the influence of five chronic health conditions (high blood pressure, heart conditions, stroke, diabetes, and lung diseases) and four sociodemographic characteristics (age, gender, education, and race/ethnicity) on the endorsement patterns of depressive symptoms in a sample of community-dwelling older adults. METHOD: Participants were adults aged >or=65 years from the 2004 Health and Retirement Study (n = 9448). Depressive symptoms were measured with a nine-item Center for Epidemiologic Studies-Depression scale. Measurement differences attributable to health and sociodemographic factors were assessed with a multidimensional model based on item response theory. RESULTS: Evidence for unidimensionality was equivocal. We used a bifactor model to express symptom endorsement patterns as resulting from a general factor and three specific factors ("dysphoria," "psychosomatic," and "lack of positive affect"). Even after controlling for the effects of health on the psychosomatic factor, heart conditions, stroke, diabetes, and lung diseases had significant positive effects on the general factor. Significant effects due to gender and educational levels were observed on the "lack of positive affect" factor. Older adults self-identifying as Latinos had higher levels of general depression. On the symptom level, meaningful measurement noninvariance due to race/ethnic differences were found in the following five items: depressed, effort, energy, happy, and enjoy life. CONCLUSIONS: The increased tendency to endorse depressive symptoms among persons with specific health conditions is, in part, explained by specific associations among symptoms belonging to the psychosomatic domain. Differences attributable to the effects of health conditions may reflect distinct phenomenological features of depression. The bifactor model serves as a vehicle for testing such hypotheses.
Keywords: Aged; Aged, 80 and over; Chronic disease; Cohort Studies; Comorbidity; Confounding Factors, Epidemiologic; Culture; depression; Diabetes Mellitus; Educational Status; ethnicity; Factor Analysis, Statistical; Female; Heart Diseases; Humans; Hypertension; Interviews as Topic; Lung Diseases; Male; Self-Assessment; Sex Factors; Stroke; United States

Memory decline and depressive symptoms in a nationally representative sample of older adults: the Health and Retirement Study (1998-2004). - Hector M González; Mary E Bowen; Gwenith G Fisher (Dement Geriatr Cogn Disord, 2008)
BACKGROUND/AIMS: Inconsistencies in the relationship between depression and cognitive decline may exist because the expected cognitive domains at risk have not been specified in previous study designs. We aimed to examine the relationship between depressive symptoms and verbal episodic memory functioning over time. METHODS: Data from a prospective cohort study (Health and Retirement Study; 1998-2004; n = 18,465), a multistage national probability sample of older adults in the United States, were analyzed. Verbal learning and memory of a 10-word list learning task were the main outcomes. Depressive symptoms (Center for Epidemiologic Studies - Depression Scale) constituted the main predictor. RESULTS: Depressive symptoms were associated with significantly lower immediate (-0.05; p < 0.001) and delayed (-0.06; p < 0.001) word list recall scores after controlling for demographics and baseline and time-varying cardiovascular disease risks and diseases. CONCLUSIONS: In this US national study of older adults, elevated depressive symptoms were associated with declines in episodic learning and memory over time. These associations were little affected by the demographic or medical conditions considered in this study. The results suggest that learning and memory decline may be a long-term feature associated with depressive symptoms among the nation's older adult population.
Keywords: Aged; Aged, 80 and over; depression; Female; Health Status; Humans; Incidence; Male; Memory Disorders; Neuropsychological tests; Prevalence; Retirement; United States

A multilevel analysis of urban neighborhood socioeconomic disadvantage and health in late life. - Richard G Wight; Janet R. Cummings; Miller-Martinez, Dana; Arun S Karlamangla; Teresa Seeman; Carol S Aneshensel (Soc Sci Med, 2008)
The associations between neighborhood context and various indicators of health are receiving growing empirical attention, but much of this research is regionally circumscribed or assumes similar effects across the life course. This study utilizes a U.S. national sample to investigate the association between urban neighborhood socioeconomic disadvantage and health specifically among older adults. Data are from 3442 participants aged 70 years and older in the 1993 Asset and Health Dynamics Among the Oldest Old (AHEAD) Study, and the 1990 U.S. Census. Our approach underscores the importance of multiple dimensions of health (self-reported physician-diagnosed cardiovascular disease [CVD], functional status, and self-rated health) as well as multiple dimensions of neighborhood disadvantage, which are conceptualized as environmental hazards that may lead to a physiologically consequential stress response. We find that individual-level factors attenuate the association between neighborhood disadvantage and both CVD and functional status, but not self-rated health. Net of covariates, high neighborhood socioeconomic disadvantage is significantly associated with reporting poor health. In late life, neighborhood socioeconomic disadvantage is more consequential to subjective appraisals of health than diagnosed CVD or functional limitations.
Keywords: Aged; Female; Health Behavior; Health Status Disparities; Humans; Male; Poverty; Small-Area Analysis; Socioeconomic factors; United States; Urban Population

Neighborhoods and disability in later life. - Vicki A Freedman; Irina B Grafova; Robert F. Schoeni; Jeannette Rogowski (Soc Sci Med, 2008)
This paper uses the US Health and Retirement Study to explore linkages between neighborhood conditions and stages of the disablement process among adults aged 55 years and older in the United States. We consider multiple dimensions of the neighborhood including the built environment as well as social and economic conditions. In doing so, we use factor analysis to reduce indicators into eight neighborhood scales, which we incorporate into two-level logistic regression models along with controls for individual-level factors. We find evidence that economic conditions and the built environment, but not social conditions, matter. Neighborhood economic advantage is associated with a reduced risk of lower body limitations for both men and women. We also find for men that neighborhood economic disadvantage is linked to increased chances of reporting personal care limitations, particularly for those aged 55-64 years, and that high connectivity of the built environment is associated with reduced risk of limitations in instrumental activities. Our findings highlight the distinctive benefits of neighborhood economic advantage early in the disablement process. In addition, findings underscore the need for attention in the design and evaluation of disability-prevention efforts to the benefits that accrue from more physically connected communities and to the potential harm that may arise in later life from living in economically disadvantaged areas.
Keywords: Aging; Disabled Persons; Factor Analysis, Statistical; Female; Health Status Disparities; Humans; Male; Middle Aged; Residence Characteristics; Social Conditions; Socioeconomic factors; United States

Neighborhoods and obesity in later life. - Irina B Grafova; Vicki A Freedman; Kumar, Rizie; Jeannette Rogowski (Am J Public Health, 2008)
OBJECTIVES: We examined the influence of neighborhood environment on the weight status of adults 55 years and older. METHODS: We conducted a 2-level logistic regression analysis of data from the 2002 wave of the Health and Retirement Study. We included 8 neighborhood scales: economic advantage, economic disadvantage, air pollution, crime and segregation, street connectivity, density, immigrant concentration, and residential stability. RESULTS: When we controlled for individual- and family-level confounders, living in a neighborhood with a high level of economic advantage was associated with a lower likelihood of being obese for both men (odds ratio [OR] = 0.86; 95% confidence interval [CI] = 0.80, 0.94) and women (OR = 0.83; 95% CI = 0.77, 0.89). Men living in areas with a high concentration of immigrants and women living in areas of high residential stability were more likely to be obese. Women living in areas of high street connectivity were less likely to be overweight or obese. CONCLUSIONS: The mechanisms by which neighborhood environment and weight status are linked in later life differ by gender, with economic and social environment aspects being important for men and built environment aspects being salient for women.
Keywords: Aged; Air Pollution; Crime; Emigrants and Immigrants; Environment Design; Female; Health Status Indicators; Humans; Income; Logistic Models; Male; Middle Aged; Obesity; Odds Ratio; Overweight; Population Density; Residence Characteristics; Retirement; Social Class; Social Conditions; Social Environment; Socioeconomic factors; United States

Parent caregiving choices of middle-generation Blacks and Whites in the United States. - Shelley I. White-Means; Rose M. Rubin (J Aging Health, 2008)
OBJECTIVE: This study compares how middle-generation caregivers and non-caregivers differ by race and explores racial differences in activities of daily living (ADL), instrumental activities of daily living (IADL), and financial assistance that middle-generation caregivers provide for their parents. METHOD: Using 2000 Health and Retirement Study data, racially stratified descriptive analyses and logistic regression models for ADL, IADL, and financial assistance are presented. RESULTS: Parental need and race influence support, with similar patterns of Black and White ADL support, but racial differences in IADL and financial support. Having more children motivates Whites to increase IADL support and reduce financial support; more children decreases Blacks' IADL support. Sibling caregiver networks influence IADL and financial support in ways that vary by race. The number employed is a key determinant for Blacks for all support, but only influences White ADL support. DISCUSSION: The findings of this article indicate the importance of sample stratification by race and that employment or other subsidies may aid the expansion of caregiving by middle-generation adults.
Keywords: Activities of Daily Living; Black People; Caregivers; Employment; Family Characteristics; Financial Support; Humans; Intergenerational Relations; Logistic Models; Parent-Child Relations; Parents; Siblings; Socioeconomic factors; United States; White People

Parental marital disruption, family type, and transfers to disabled elderly parents. - Liliana E Pezzin; Robert A. Pollak; Barbara Steinberg Schone (J Gerontol B Psychol Sci Soc Sci, 2008)
OBJECTIVE: The objective of this study was to investigate the effect of parental marital status, marital history, and family type on intergenerational living arrangements and adult children's time and cash transfers to their unpartnered disabled elderly parents. METHODS: We used data from the Asset and Health Dynamics Among the Oldest Old survey to estimate the joint probabilities that an adult child provides time and/or cash transfers to a parent and to analyze a five-level categorical variable capturing parent-child living arrangements. RESULT: The estimates suggest significant detrimental effects of parental divorce and step relationship on time transfers and on the probability of coresidence with the index child. Family type, as captured by the composition of the index child's sibling network according to kin relationship to the parent, also affected transfers and living arrangement choices of adult children. DISCUSSION: The findings that transfers from adult children to their unpartnered disabled elderly parents depend on parental marital status and kin relationship suggest that changing family patterns are altering the traditional role of the family as a support network. These findings raise concerns about the care likely to be available to future cohorts of elderly persons who will have experienced substantially higher rates of divorce, remarriage, and step parenthood than the cohort considered in this study.
Keywords: Adult; Aged; Altruism; Divorce; Family Characteristics; Female; Frail Elderly; Gift Giving; Humans; Likelihood Functions; Longitudinal Studies; Male; Multivariate Analysis; Parent-Child Relations; Residence Characteristics; Siblings; United States

Prevalence of cognitive impairment without dementia in the United States. - Brenda L Plassman; Kenneth M. Langa; Gwenith G Fisher; Steven G Heeringa; David R Weir; Mary Beth Ofstedal; James R Burke; Michael D Hurd; Guy G Potter; Willard L Rodgers; David C Steffens; John J McArdle; et al. (Ann Intern Med, 2008)
BACKGROUND: Cognitive impairment without dementia is associated with increased risk for disability, increased health care costs, and progression to dementia. There are no population-based prevalence estimates of this condition in the United States. OBJECTIVE: To estimate the prevalence of cognitive impairment without dementia in the United States and determine longitudinal cognitive and mortality outcomes. DESIGN: Longitudinal study from July 2001 to March 2005. SETTING: In-home assessment for cognitive impairment. PARTICIPANTS: Participants in ADAMS (Aging, Demographics, and Memory Study) who were age 71 years or older drawn from the nationally representative HRS (Health and Retirement Study). Of 1770 selected individuals, 856 completed initial assessment, and of 241 selected individuals, 180 completed 16- to 18-month follow-up assessment. MEASUREMENTS: Assessments, including neuropsychological testing, neurologic examination, and clinical and medical history, were used to assign a diagnosis of normal cognition, cognitive impairment without dementia, or dementia. National prevalence rates were estimated by using a population-weighted sample. RESULTS: In 2002, an estimated 5.4 million people (22.2%) in the United States age 71 years or older had cognitive impairment without dementia. Prominent subtypes included prodromal Alzheimer disease (8.2%) and cerebrovascular disease (5.7%). Among participants who completed follow-up assessments, 11.7% with cognitive impairment without dementia progressed to dementia annually, whereas those with subtypes of prodromal Alzheimer disease and stroke progressed at annual rates of 17% to 20%. The annual death rate was 8% among those with cognitive impairment without dementia and almost 15% among those with cognitive impairment due to medical conditions. LIMITATIONS: Only 56% of the nondeceased target sample completed the initial assessment. Population sampling weights were derived to adjust for at least some of the potential bias due to nonresponse and attrition. CONCLUSION: Cognitive impairment without dementia is more prevalent in the United States than dementia, and its subtypes vary in prevalence and outcomes.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Dementia; disease progression; Humans; Longitudinal Studies; Prevalence; United States

Preventive health behaviors among grandmothers raising grandchildren. - Lindsey A Baker; Merril Silverstein (J Gerontol B Psychol Sci Soc Sci, 2008)
OBJECTIVES: We examined differential preventive health behavior among grandmothers who recently began raising a grandchild, grandmothers raising a grandchild for at least 2 years, and grandmothers not raising a grandchild. METHODS: Data came from the 2000, 2002, and 2004 waves of the Health and Retirement Study. We ran multivariate logistic regression models to assess receipt of influenza vaccination, cholesterol screening, monthly breast self-exam, mammography, and Papanicolaou (Pap) tests among grandmothers aged 50 to 75. RESULTS: Grandmothers who recently began raising a grandchild were significantly less likely to report influenza vaccination and cholesterol screening than grandmothers not raising grandchildren, even after we controlled for increased emotional and financial strains within the household. We also observed this association for Pap tests, although this finding was only marginally significant. Grandmothers who had been raising a grandchild for at least 2 years were significantly more likely to report influenza vaccination and monthly breast self-exam than grandmothers not raising grandchildren. DISCUSSION: The enhancement of preventive behavior seen among long-term grandparent caregivers does not fully offset the suppression of preventive behavior during the transition into care; support groups should target a range of interventions toward the promotion of healthy behavior among new grandparent caregivers.
Keywords: Aged; Breast Self-Examination; Caregivers; Female; Health Behavior; Humans; Hypercholesterolemia; Influenza, Human; Intergenerational Relations; Logistic Models; Mass Screening; Middle Aged; Papanicolaou Test; Preventive Health Services; United States; Vaccination; Vaginal Smears

Racial disparities in receipt of hip and knee joint replacements are not explained by need: the Health and Retirement Study 1998-2004. - Steel, Nicholas; Clark, Allan; Iain A Lang; Robert B Wallace; David Melzer (J Gerontol A Biol Sci Med Sci, 2008)
BACKGROUND: Hip and knee joint replacement rates vary by demographic group. This article describes the epidemiology of need for joint replacement, and of subsequent receipt of a joint replacement by those in need. METHODS: Data from the Health and Retirement Study were used to assess need for hip or knee joint replacement in a total of 14,807 adults aged 60 years or older in 1998, 2000, and 2002 and receipt of needed surgery 2 years later. "Need" classification was based on difficulty walking, joint pain, stiffness, or swelling and receipt of treatment for arthritis, without contraindications to surgery. RESULTS: Need in 2002 was greater in participants who were older than 74 years (vs 60-64: adjusted odds ratio 2.06; 95% confidence interval, 1.68-2.53), women (vs men: 1.81; 1.53-2.14), less educated (vs college educated: 1.27; 1.06-1.52), in the poorest third (vs richest: 2.20; 1.78-2.72), or obese (vs nonobese: 2.39; 2.02-2.81). One hundred sixty-eight participants in need received a joint replacement, with lower receipt in black or African American participants (vs white: 0.47; 0.26-0.83) or less educated (vs college educated: 0.65; 0.44-0.96). These differences were not explained by current employment, access to medical care, family responsibilities, disability, living alone, comorbidity, or exclusion of those younger than Medicare eligibility age. CONCLUSIONS: After taking variations in need into consideration, being black or African American or lacking a college education appears to be a barrier to receiving surgery, whereas age, sex, relative poverty, and obesity do not. These disparities maintain disproportionately high levels of pain and disability in disadvantaged groups.
Keywords: Aged; Arthroplasty, Replacement, Hip; Arthroplasty, Replacement, Knee; Black or African American; Educational Status; Female; Health Services Needs and Demand; Humans; Male; Middle Aged; United States

Spousal caregiving in late midlife versus older ages: implications of work and family obligations. - Julie C Lima; Susan M Allen; Goldscheider, Frances; Intrator, Orna (J Gerontol B Psychol Sci Soc Sci, 2008)
OBJECTIVES: This study examined life-stage differences in the provision of care to spouses with functional impairment. METHODS: We examined 1,218 married adults aged 52 and older from the 2000 wave of the Health and Retirement Study who received impairment-related help with at least one activity of daily living. We examined the differential likelihood that spouses served as primary caregiver and the hours of care provided by spousal primary caregivers by life stage. RESULTS: We found that late middle-aged care recipients were more likely than their older counterparts to receive the majority of their care from their spouse but received fewer hours of spousal care, mostly when spouses worked full time. Competing demands of caring for children or parents did not affect the amount of care provided by a spouse. DISCUSSION: Late middle-aged adults with functional limitations are more likely than older groups to be married and cared for primarily by spouses; however, they may be particularly vulnerable to unmet need for care. As the baby boom generation ages, retirement ages increase, and federal safety nets weaken, people with health problems at older ages may soon find themselves in the same caregiving predicament as those in late middle age.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Caregivers; Employment; Family Relations; Female; Gender Identity; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; Mobility Limitation; Spouses; Time Factors; United States

Spousal concordance in health behavior change. - Tracy Falba; Jody L Sindelar (Health Serv Res, 2008)
OBJECTIVE: This study examines the degree to which a married individual's health habits and use of preventive medical care are influenced by his or her spouse's behaviors. STUDY DESIGN: Using longitudinal data on individuals and their spouses, we examine changes over time in the health habits of each person as a function of changes in his or her spouse's health habits. Specifically, we analyze changes in smoking, drinking, exercising, cholesterol screening, and obtaining a flu shot. DATA SOURCE: This study uses data from the Health and Retirement Study (HRS), a nationally representative sample of individuals born between 1931 and 1941 and their spouses. Beginning in 1992, 12,652 persons (age-eligible individuals as well as their spouses) from 7,702 households were surveyed about many aspects of their life, including health behaviors, use of preventive services, and disease diagnosis. SAMPLE: The analytic sample includes 6,072 individuals who are married at the time of the initial HRS survey and who remain married and in the sample at the time of the 1996 and 2000 waves. PRINCIPAL FINDINGS: We consistently find that when one spouse improves his or her behavior, the other spouse is likely to do so as well. This is found across all the behaviors analyzed, and persists despite controlling for many other factors. CONCLUSIONS: Simultaneous changes occur in a number of health behaviors. This conclusion has prescriptive implications for developing interventions, treatments, and policies to improve health habits and for evaluating the impact of such measures.
Keywords: Attitude to Health; Cross-Sectional Studies; Exercise; Family Characteristics; Female; Health Behavior; Health Care Surveys; Health Promotion; Health Status; Humans; Interpersonal Relations; Life Style; Male; Marriage; Middle Aged; Preventive Health Services; Prospective Studies; Risk-Taking; Smoking; Spouses; United States

Spousal smoking and incidence of first stroke: the Health and Retirement Study. - M. Maria Glymour; Triveni DeFries; Ichiro Kawachi; Mauricio Avendano (Am J Prev Med, 2008)
BACKGROUND: Few prospective studies have investigated the relationship between spousal cigarette smoking and the risk of incident stroke. METHODS: Stroke-free participants in the U.S.-based Health and Retirement Study (HRS) aged >or=50 years and married at baseline (n=16,225) were followed, on average, 9.1 years between 1992 and 2006) for proxy or self-report of first stroke (1,130 events). Participants were stratified by gender and own smoking status (never-smokers, former smokers, or current smokers), and the relationship assessed between the spouse's smoking status and the risk of incident stroke. Analyses were conducted in 2007 with Cox proportional hazards models. All models were adjusted for age; race; Hispanic ethnicity; Southern birthstate; parental education; paternal occupation class; years of education; baseline income; baseline wealth; obesity; overweight; alcohol use; and diagnosed hypertension, diabetes, or heart disease. RESULTS: Having a spouse who currently smoked was associated with an increased risk of first stroke among never-smokers (hazard ratio=1.42, 95% CI=1.05, 1.93) and former smokers (hazard ratio=1.72, 95% CI=1.33, 2.22). Former smokers married to current smokers had a stroke risk similar to respondents who themselves smoked. CONCLUSIONS: Spousal smoking poses important stroke risks for never-smokers and former smokers. The health benefits of quitting smoking likely extend to both the individual smoker and his or her spouse.
Keywords: Age Factors; Confidence Intervals; Female; Humans; Incidence; Male; Middle Aged; Prospective Studies; Risk Factors; Smoking; Spouses; Stroke; Time Factors; Tobacco Smoke Pollution; United States

Stroke disparities in older Americans: is wealth a more powerful indicator of risk than income and education? - Mauricio Avendano; M. Maria Glymour (Stroke, 2008)
BACKGROUND AND PURPOSE: This study examines the independent effect of wealth, income, and education on stroke and how these disparities evolve throughout middle and old age in a representative cohort of older Americans. METHODS: Stroke-free participants in the Health and Retirement Study (n=19,565) were followed for an average of 8.5 years. Total wealth, income, and education assessed at baseline were used in Cox proportional hazards models to predict time to stroke. Separate models were estimated for 3 age-strata (50 to 64, 65 to 74, and >or=75), and incorporating risk factor measures (smoking, physical activity, body mass index, hypertension, diabetes, and heart disease). RESULTS: 1542 subjects developed incident stroke. Higher education predicted reduced stroke risk at ages 50 to 64, but not after adjustment for wealth and income. Wealth and income were independent risk factors for stroke at ages 50 to 64. Adjusted hazard ratios comparing the lowest decile with the 75th-90th percentiles were 2.3 (95% CI 1.6, 3.4) for wealth and 1.8 (95% CI 1.3, 2.6) for income. Risk factor adjustment attenuated these effects by 30% to 50%, but coefficients for both wealth (HR=1.7, 95% CI 1.2, 2.5) and income (HR=1.6, 95% CI 1.2, 2.3) remained significant. Wealth, income, and education did not consistently predict stroke beyond age 65. CONCLUSIONS: Wealth and income are independent predictors of stroke at ages 50 to 64 but do not predict stroke among the elderly. This age patterning might reflect buffering of the negative effect of low socioeconomic status by improved access to social and health care programs at old ages, but may also be an artifact of selective survival.
Keywords: Age Distribution; Age Factors; Aged; Cohort Studies; Educational Status; Female; Humans; Incidence; Income; Life Style; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Socioeconomic factors; Stroke; United States

Trends in the prevalence and mortality of cognitive impairment in the United States: is there evidence of a compression of cognitive morbidity? - Kenneth M. Langa; Eric B Larson; Jason H. Karlawish; David M Cutler; Mohammed U Kabeto; Scott Y H Kim; Allison B Rosen (Alzheimers Dement, 2008)
BACKGROUND: Recent medical, demographic, and social trends might have had an important impact on the cognitive health of older adults. To assess the impact of these multiple trends, we compared the prevalence and 2-year mortality of cognitive impairment (CI) consistent with dementia in the United States in 1993 to 1995 and 2002 to 2004. METHODS: We used data from the Health and Retirement Study (HRS), a nationally representative population-based longitudinal survey of U.S. adults. Individuals aged 70 years or older from the 1993 (N = 7,406) and 2002 (N = 7,104) waves of the HRS were included. CI was determined by using a 35-point cognitive scale for self-respondents and assessments of memory and judgment for respondents represented by a proxy. Mortality was ascertained with HRS data verified by the National Death Index. RESULTS: In 1993, 12.2% of those aged 70 or older had CI compared with 8.7% in 2002 (P < .001). CI was associated with a significantly higher risk of 2-year mortality in both years. The risk of death for those with moderate/severe CI was greater in 2002 compared with 1993 (unadjusted hazard ratio, 4.12 in 2002 vs 3.36 in 1993; P = .08; age- and sex-adjusted hazard ratio, 3.11 in 2002 vs 2.53 in 1993; P = .09). Education was protective against CI, but among those with CI, more education was associated with higher 2-year mortality. CONCLUSIONS: These findings support the hypothesis of a compression of cognitive morbidity between 1993 and 2004, with fewer older Americans reaching a threshold of significant CI and a more rapid decline to death among those who did. Societal investment in building and maintaining cognitive reserve through formal education in childhood and continued cognitive stimulation during work and leisure in adulthood might help limit the burden of dementia among the growing number of older adults worldwide.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Female; Humans; Male; Neurology; Prevalence; Quality of Life; Socioeconomic factors; United States

Using subjective expectations to forecast longevity: do survey respondents know something we don't know? - Maria Perozek (Demography, 2008)
Old-age mortality is notoriously difficult to predict because it requires not only an understanding of the process of senescence-which is influenced by genetic, environmental, and behavioral factors-but also a prediction of how these factors will evolve. In this paper I argue that individuals are uniquely qualified to predict their own mortality based on their own genetic background, as well as environmental and behavioral risk factors that are often known only to the individual. Given this private information, individuals form expectations about survival probabilities that may provide additional information to demographers and policymakers in their challenge to predict mortality. From expectations data from the 1992 Health and Retirement Study (HRS), I construct subjective, cohort life tables that are shown to predict the unusual direction of revisions to U.S. life expectancy by gender between 1992 and 2004: that is, for these cohorts, the Social Security Actuary (SSA) raised male life expectancy in 2004 and at the same lowered female life expectancy, narrowing the gender gap in longevity by 25% over this period. Further, although the subjective life expectancies for men appear to be roughly in line with the 2004 life tables, the subjective expectations of women suggest that female life expectancies estimated by the SSA might still be on the high side.
Keywords: Aged; Aged, 80 and over; Aging; Data collection; Demography; Female; health policy; Humans; Life Expectancy; Life Tables; Longevity; Male; Middle Aged; Mortality; Risk Factors; Sex Factors; United States

Within-group differences in depression among older Hispanics living in the United States. - Frances Margaret Yang; Cazorla-Lancaster, Yamileth; Richard N Jones (J Gerontol B Psychol Sci Soc Sci, 2008)
Using the Health and Retirement Study, we examine the prevalence of depression in different groups of Hispanic older adults. Respondents (n = 759) were aged 59 and older and identified themselves as Mexican American (56%), Cuban American (13%), Puerto Rican (8%), other (8%), or not specified (15%). We used a modified version of the Center for Epidemiologic Studies-Depression scale and the Composite International Diagnostic Interview to assess depressive symptoms and the presence of major depression. Relative to Puerto Ricans, each Hispanic group had significantly lower levels of depressive symptoms, except for Cuban Americans; and each Hispanic group had lower prevalence rates for major depression, except for other Hispanics, even after we adjusted for sociodemographic, cultural factors, socioeconomic, functional limitations, and chronic health conditions.
Keywords: Aged; Culture; Depressive Disorder, Major; Female; Hispanic or Latino; Humans; Insurance, Health; Male; Middle Aged; Prevalence; Severity of Illness Index; Socioeconomic factors; United States

Age group differences in depressive symptoms among older adults with functional impairments. - Namkee G Choi; Kim, Johnny S. (Health Soc Work, 2007)
This study used data from the 2000 interview wave of the Health and Retirement Study to examine age group differences in the likelihood of self-reported depressive symptomatology among a nationally representative sample of 3,035 adults age 55 years or older who had at least one activities of daily living (ADL) or instrumental activities of daily living (IADL) limitation. Depression was defined as scoring three points or higher on the eight-point Center for Epidemiological Studies Depression Scale. The results show that respondents age 75 years or older with one ADL/IADL impairment or more were significantly less likely to be depressed than were those between ages 55 and 64 with the same degree of functional impairment. It is recommended that doctors, social workers, and other health care and social services providers pay special attention to younger old adults with health problems and functional limitations because they have a greater risk of being depressed.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Demography; depression; Disabled Persons; Female; Health Status; Humans; Interviews as Topic; Logistic Models; Male; Middle Aged; United States

Baseline health, socioeconomic status, and 10-year mortality among older middle-aged Americans: findings from the Health and Retirement Study, 1992 2002. - Joseph Feinglass; Lin, Suru; Jason A. Thompson; Joseph J Sudano; Dorothy D Dunlop; Song, Jing; David W. Baker (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVE: This study analyzed whether socioeconomic status in older middle age continues to be associated with 10-year survival after data are controlled for baseline health status. METHODS: We confirmed deaths through 2002 for 9,759 participants in the Health and Retirement Study, aged 51 to 61 in 1992. We used discrete time survival models to examine hazard ratios over 10 years of follow-up. We examined associations of demographic characteristics and socioeconomic status measures before and after adjustment by health status and behavioral risk factors. RESULT: The 10-year mortality rate was 10.9%, ranging from 4.7% for respondents reporting excellent health to 35.8% for those reporting poor health at baseline. Lower levels of education, income, and wealth were strongly associated with higher mortality risk after we controlled for just demographic characteristics. After further adjustment for health status and behavioral risk factors, only household income remained significant. DISCUSSION: Baseline health by age 50 is an important pathway in the association between midlife socioeconomic status and mortality risk to age 70. The continuing effect of low household income on mortality risk was concentrated among respondents reporting excellent to good health at baseline. Socioeconomic disparities in middle-age health continue to limit disability-free life expectancy at older ages.
Keywords: Adult; Aged; Aged, 80 and over; Economics; Education; Follow-Up Studies; Health Status; Humans; Income; Middle Aged; Mortality; Motor Activity; Pilot Projects; Proportional Hazards Models; Retirement; Risk Factors; Risk-Taking; Smoking; Social Class; Thinness; United States

Beyond comorbidity counts: how do comorbidity type and severity influence diabetes patients' treatment priorities and self-management? - Eve A Kerr; Michele M Heisler; Sarah L. Krein; Mohammed U Kabeto; Kenneth M. Langa; David R Weir; John D Piette (J Gen Intern Med, 2007)
BACKGROUND: The majority of older adults have 2 or more chronic conditions and among patients with diabetes, 40% have at least three. OBJECTIVE: We sought to understand how the number, type, and severity of comorbidities influence diabetes patients' self-management and treatment priorities. DESIGN: Cross-sectional observation study. PATIENTS: A total of 1,901 diabetes patients who responded to the 2003 Health and Retirement Study (HRS) diabetes survey. MEASUREMENTS: We constructed multivariate models to assess the association between presence of comorbidities and each of 2 self-reported outcomes, diabetes prioritization and self-management ability, controlling for patient demographics. Comorbidity was characterized first by a count of all comorbid conditions, then by the presence of specific comorbidity subtypes (microvascular, macrovascular, and non-diabetes related), and finally by severity of 1 serious comorbidity: heart failure (HF). RESULTS: 40% of respondents had at least 1 microvascular comorbidity, 79% at least 1 macrovascular comorbidity, and 61% at least 1 non-diabetes-related comorbidity. Patients with a greater overall number of comorbidities placed lower priority on diabetes and had worse diabetes self-management ability scores. However, only macrovascular and non-diabetes-related comorbidities, but not microvascular comorbidities, were associated with lower diabetes prioritization, whereas higher numbers of microvascular, macrovascular, and non-diabetes-related conditions were all associated with lower diabetes self-management ability scores. Severe, but not mild, HF was associated with lower diabetes prioritization and self-management scores. CONCLUSIONS: The type and severity of comorbid conditions, and not just the comorbidity count, influence diabetes patients' self-management. Patients with severely symptomatic comorbidities and those with conditions they consider to be unrelated to diabetes may need additional support in making decisions about care priorities and self-management activities.
Keywords: Aged; Attitude to Health; Cohort Studies; Comorbidity; Cross-Sectional Studies; Diabetes Mellitus; Female; Health Priorities; Heart Failure; Humans; Male; Middle Aged; Self Care; Severity of Illness Index; United States

Burden of common multiple-morbidity constellations on out-of-pocket medical expenditures among older adults. - Schoenberg, Nancy E.; Hyungsoo Kim; Edwards, William; Fleming, Steven T. (Gerontologist, 2007)
PURPOSE: On average, adults aged 60 years or older have 2.2 chronic diseases, contributing to the over 60 million Americans with multiple morbidities. We aimed to understand the financial implications of the most frequent multiple morbidities among older adults. DESIGN AND METHODS: We analyzed Health and Retirement Study data, determining out-of-pocket medical expenses from 1998 and 2002 separately and examining differences in the impact of multiple-morbidity constellations on these expenses. We paid particular attention to the most common disease constellations - hypertension, arthritis, and heart disease. RESULTS: An increasing prevalence of multiple morbidity (58% compared with 70% of adults had two or more chronic conditions in 1998 and 2002, respectively) was accompanied by escalating out-of-pocket expenditures (2,164 dollars in 1998, increasing by 104% to 3,748 dollars in 2002). Individuals with two, three, and four chronic conditions had health care expenditure increases of 41%, 85%, and 100%, respectively, over 4 years. Such patterns were particularly noticeable among the oldest old, those with higher educational attainment, and women, although having supplementary health insurance or Medicaid mitigated these expenses. Finally, there were significant differences in out-of-pocket expenditure levels among the multiple-morbidity combinations. IMPLICATIONS: Increasing rates of multiple morbidities in conjunction with escalating health care costs and stable or declining incomes among elders warrant creative attention from providers, researchers, and policy makers. Further understanding how specific multiple-morbidity constellations impact out-of-pocket spending moves us closer to effective interventions to support vulnerable elders.
Keywords: Aged; Arthritis; Chronic disease; Comorbidity; Cost of Illness; Female; Financing, Personal; Health Expenditures; Health Surveys; Heart Diseases; Humans; Hypertension; Interviews as Topic; Male; Middle Aged; United States

Change in depression of spousal caregivers of dementia patients following patient's death. - Tweedy, Maureen P.; Charles A Guarnaccia (Omega (Westport), 2007)
Caring for an elderly spouse with dementia places a heavy burden on spousal caregivers and often results in chronic depression. Little has been written about change in depression caregivers experience from before to after the death of the spouse with dementia. This longitudinal study examines change in depression of spousal caregivers that occurs following death of the dementia patient. Two theoretical models, the Relief and Stress Models, are discussed in terms of caregiver depression after the death of the dementia-patient care-recipient spouse. These two theoretical models were tested using longitudinal data from the National Institute on Aging sponsored Health and Retirement Study. Both male and female spousal caregivers report an increase in depression after the death of the dementia-patient care-recipient spouse. As time passed following the spouse's death, the conjugally bereaved husbands showed a decrease in depression while the conjugally bereaved wives continued to report increased depression.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Bereavement; Caregivers; Dementia; depression; Female; Humans; Life Change Events; Long-term Care; Longitudinal Studies; Male; Sex Factors; Spouses; Surveys and Questionnaires; United States

Do panel surveys really make people sick? A commentary on Wilson and Howell (60:11, 2005, 2623-2627). - David R Weir; James P Smith (Soc Sci Med, 2007)
In a recent article in this journal, Wilson and Howell [2005. Do panel surveys make people sick? US arthritis trends in the Health and Retirement Survey. Social Science & Medicine, 60(11), 2623-2627.] argue that the sharp trend of rising age-specific arthritis prevalence from 1992 to 2000 in the USA among those in their 50s based on the original Health and Retirement Study (HRS) cohort of respondents is "almost surely spurious." Their reasons are that no such trend is found in the National Health Interview Study (NHIS) over this same time period, and that an introduction of a new birth cohort into HRS in 1998 also indicates no trend. They also claim that there may be an inherent bias in panel surveys leading respondents to report greater levels of disease as the duration of their participation in the panel increases. This bias, which they call "panel conditioning," suggests a tendency for participants in a longitudinal survey to seek out medical care and diagnosis of symptoms asked about in previous waves. In this paper, we show that the evidence presented and the conclusions reached by Wilson and Howell are incorrect. Properly analyzed, three national health surveys--the NHIS, National Health and Nutrition Examination Survey (NHANES), and HRS--all show increases in age-specific arthritis prevalence during the 1990s. Since the new HRS sample cohort introduced in 1998 represents only a part of that birth cohort, we also demonstrate that Wilson and Howell's evidence in favor of panel conditioning was flawed. We find little indication of panel conditioning among existing participants in a panel survey.
Keywords: Arthritis; Female; Health Surveys; Humans; Male; Middle Aged; Prevalence; United States

Does money buy better health? Unpacking the income to health association after midlife. - Berry, Brent M. (Health (London), 2007)
This article estimates the effect of household financial resources on health after midlife using models that minimize health-related selectivity and unobserved heterogeneity bias. I focus on the self-rated health and mobility limitations of adults transitioning into retirement over six panels of the Health and Retirement Study (1992-2002; age 51-61 at wave one; N = 7602). Standard regression models that adjust for health-related selection with prospective and retrospective controls suggest a significant influence of long-term income on health, but an insignificant influence of short-term income. Further adjustment for unobserved fixed effects also suggests that short-term income is insignificant. Sizable recent and long-term health feedbacks to income for a portion of the HRS respondents underscore the need to control for the confounding influence of health over the lifecourse. Together these results suggest that adults after midlife are heterogeneous with respect to the causal and selective processes generating the observed association between income and health.
Keywords: Aged; Attitude to Health; Employment; Health Status Indicators; Humans; Income; Middle Aged; Mobility Limitation; Models, Econometric; Retirement; Self Concept; Sociology, Medical; United States

Does more health care improve health among older adults? A longitudinal analysis. - Ezra Golberstein; Jersey Liang; A. R. Quinones; Frederic D Wolinsky (J Aging Health, 2007)
OBJECTIVE: This research assesses the association of health services use with subsequent physical health among older Americans, adjusting for the confounding between health care use and prior health. METHOD: Longitudinal data are from the Survey on Assets and Health Dynamics Among the Oldest Old (AHEAD). Linear and logistic regressions are used to model the linkages between medical care use and health outcomes, including self-rated health, functional limitations, and mortality. RESULTS: There is limited evidence that increased health care use is correlated with improved subsequent health. Increased use of medical care is largely associated with poorer health outcomes. Moreover, there are no significant interaction effects of health care use and baseline health on Activities of Daily Living and Instrumental Activities of Daily Living, despite the existence of a significant but very small interaction effect on self-rated health. CONCLUSIONS: The findings have implications for the quality of care delivered by the American health care system.
Keywords: Activities of Daily Living; Aged; Health Services; Health Services for the Aged; Health Status; Humans; Longitudinal Studies; United States

Early childbearing, marital status, and women's health and mortality after age 50. - John C Henretta (J Health Soc Behav, 2007)
This article examines the relationship between a woman's childbearing history and her later health and mortality, with primary focus on whether the association between them is due to early and later socioeconomic status. Data are drawn from the Health and Retirement Study birth cohort of 1931-1941. Results indicate that, conditional on reaching midlife and controlling for early and later socioeconomic status, a first birth before age 20 is associated with a higher hazard of dying. In addition, having an early birth is associated with a higher prevalence of reported heart disease, lung disease, and cancer in 1994. Being unmarried at the time of the first birth is associated with earlier mortality, but this association disappears when midlife socioeconomic status is controlled. The number of children ever born does not significantly affect mortality but is associated with prevalence of diabetes.
Keywords: Adolescent; Cohort Studies; Female; Humans; Marital Status; Maternal Age; Middle Aged; Mortality; Parity; Pregnancy; Pregnancy in Adolescence; Prevalence; Proportional Hazards Models; Social Class; United States; Women's Health

The economic consequences of widowhood for older minority women. - Jacqueline L. Angel; Maren A. Jimenez; Ronald J. Angel (Gerontologist, 2007)
PURPOSE: We compare the economic consequences of widowhood for pre-retirement age and early-retirement age Black, Hispanic, and non-Hispanic White women. METHODS: We use the 1992 and 2000 waves of the Health and Retirement Study to assess the effects of widowhood on the household incomes and assets of non-Hispanic White, Black, and Hispanic women who were 51 years of age or older at baseline (N = 4,544). RESULTS: For women of all racial and ethnic groups, marital disruption, including widowhood, results in a substantial decline in household income and assets. Net of demographic controls, the relative loss is far greater for Black and Hispanic widows than for non-Hispanic White widows. IMPLICATIONS: The data reveal a substantial widowhood penalty for total household income and net worth for women in each racial and ethnic group. However, the findings suggest that minority widows are at a particularly high risk of poverty in late life, given that they have lower incomes and fewer assets to begin with. Implications of the results for the financial security of women approaching retirement are discussed.
Keywords: Aged; Black or African American; Female; Hispanic or Latino; Humans; Longitudinal Studies; Middle Aged; United States; White People; Widowhood

Educational disparities in the prevalence and consequence of physical vulnerability. - Daniel O. Clark; Timothy E. Stump; Douglas K Miller; Long, J. Scott (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVES: The purpose of this study was to estimate educational differences in the prevalence and mortality consequence of physical vulnerability among older adults in the United States. METHODS: Data came from the 1998 and 2000 waves of the Health and Retirement Study, a nationally representative cross-sectional and prospective cohort study of community-based adults aged 65 and older. We created a physical vulnerability score from age, gender, and self-reported disability measures and measured socioeconomic status via educational attainment. Mortality data came from the National Death Index. RESULTS: In the 1998 cohort, high physical vulnerability was more than 3 times more prevalent in individuals with less than 12 years of education compared to those with 16 or more years of education. Although less educated older adults had a higher probability of death overall, evidence of educational differences in the mortality consequence of high physical vulnerability was limited. In 2000, 2.16 million older adults had high physical vulnerability, and more than one half (53%) of these adults had less than 12 years of education. DISCUSSION: In persons 65 years of age or older, educational differences are more apparent in the prevalence of physical vulnerability than in the mortality consequence of that vulnerability.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic disease; Cohort Studies; Cross-Sectional Studies; Educational Status; Female; Geriatric Assessment; Health Surveys; Humans; Male; Mobility Limitation; Risk Factors; Socioeconomic factors; Survival Analysis; United States

Evidence on early-life income and late-life health from America's Dust Bowl era. - David M Cutler; Grant Miller; Douglas M Norton (Proceedings of the National Academy of Sciences, 2007)
In recent decades, elderly Americans have enjoyed enormous gains in longevity and reductions in disability. The causes of this progress remain unclear, however. This paper investigates the role of fetal programming, exploring how economic progress early in the 20th century might be related to declining disability today. Specifically, we match sudden unexpected economic changes experienced in utero in America's Dust Bowl during the Great Depression to unusually detailed individual-level information about old-age disability and chronic disease. We are unable to detect any meaningful relationship between early life factors and outcomes in later life. We conclude that, if such a relationship exists in the United States, it is most likely not a quantitatively important explanation for declining disability today.
Keywords: Aged; Data collection; Female; Health Status; History, 20th Century; Humans; Income; Male; Middle Aged; Retirement; Socioeconomic factors; United States

Exploring the association of dual use of the VHA and Medicare with mortality: separating the contributions of inpatient and outpatient services. - Frederic D Wolinsky; An, Hyonggin; Li Liu; Thomas R Miller; Gary E Rosenthal (BMC Health Serv Res, 2007)
BACKGROUND: Older veterans may use both the Veterans Health Administration (VHA) and Medicare, but the association of dual use with health outcomes is unclear. We examined the association of indirect measures of dual use with mortality. METHODS: Our secondary analysis used survey, claims, and National Death Index data from the Survey on Assets and Health Dynamics among the Oldest Old. The analytic sample included 1,521 men who were Medicare beneficiaries. Veterans were classified as dual users when their self-reported number of hospital episodes or physician visits exceeded that in their Medicare claims. Veterans reporting inpatient or outpatient visits but having no Medicare claims were classified as VHA-only users. Proportional hazards regression was used. RESULTS: 897 (59%) of the men were veterans, of whom 134 (15%) were dual users. Among dual users, 60 (45%) met the criterion based on inpatient services, 54 (40%) based on outpatient services, and 20 (15%) based on both. 766 men (50%) died. Adjusting for covariates, the independent effect of any dual use was a 38% increased mortality risk (AHR = 1.38; p = .02). Dual use based on outpatient services marginally increased mortality risk by 45% (AHR = 1.45; p = .06), and dual use based on both inpatient and outpatient services increased the risk by 98% (AHR = 1.98; p = .02). CONCLUSION: Indirect measures of dual use were associated with increased mortality risk. New strategies to better coordinate care, such as shared medical records, should be considered.
Keywords: Aged; Aged, 80 and over; Ambulatory Care; Cluster Analysis; Continuity of Patient Care; Emergency Service, Hospital; Episode of Care; Hospital Mortality; Hospitals, Veterans; Humans; Male; Medicare; Proportional Hazards Models; United States; Veterans

Health of previously uninsured adults after acquiring Medicare coverage. - J. Michael McWilliams; Meara, Ellen; Alan M. Zaslavsky; John Z. Ayanian (JAMA, 2007)
CONTEXT: Uninsured near-elderly adults, particularly those with cardiovascular disease or diabetes, experience worse health outcomes than insured adults. However, the health benefits of providing insurance coverage for uninsured adults have not been clearly demonstrated. OBJECTIVE: To assess the effect of acquiring Medicare coverage on the health of previously uninsured adults. DESIGN AND SETTING: We conducted quasi-experimental analyses of longitudinal survey data from 1992 through 2004 from the nationally representative Health and Retirement Study. We compared changes in health trends reported by previously uninsured and insured adults after they acquired Medicare coverage at age 65 years. PARTICIPANTS: Five thousand six adults who were continuously insured and 2227 adults who were persistently or intermittently uninsured from ages 55 to 64 years. MAIN OUTCOME MEASURES: Differential changes in self-reported trends after age 65 years in general health, change in general health, mobility, agility, pain, depressive symptoms, and a summary measure of these 6 domains; and adverse cardiovascular outcomes (all trend changes reported in health scores per year). RESULTS: Compared with previously insured adults, previously uninsured adults reported significantly improved health trends after age 65 years for the summary measure (differential change in annual trend, +0.20; P = .002) and several component measures. Relative to previously insured adults with cardiovascular disease or diabetes, previously uninsured adults with these conditions reported significantly improved trends in summary health (differential change in annual trend, +0.26; P = .006), change in general health (+0.02; P = .03), mobility (+0.04; P = .05), agility (+0.08; P = .003), and adverse cardiovascular outcomes (-0.015; P = .02) but not in depressive symptoms (+0.04; P = .32). Previously uninsured adults without these conditions reported differential improvement in depressive symptoms (+0.08; P = .002) but not in summary health (+0.10; P = .17) or any other measure. By age 70 years, the expected difference in summary health between previously uninsured and insured adults with cardiovascular disease or diabetes was reduced by 50%. CONCLUSION: In this study, acquisition of Medicare coverage was associated with improved trends in self-reported health for previously uninsured adults, particularly those with cardiovascular disease or diabetes.
Keywords: Aged; Cardiovascular Diseases; depression; Diabetes Mellitus; Female; Health Status; Health Surveys; Humans; Longitudinal Studies; Male; Medically Uninsured; Medicare; Middle Aged; Outcome Assessment, Health Care; United States

Hospital episodes and physician visits: the concordance between self-reports and medicare claims. - Frederic D Wolinsky; Thomas R Miller; An, Hyonggin; John F Geweke; Robert B Wallace; Kara B Wright; Elizabeth A Chrischilles; Li Liu; Claire E Pavlik; Elizabeth A Cook; Robert L. Ohsfeldt; Kelly K Richardson; et al. (Med Care, 2007)
BACKGROUND: Health services use typically is examined using either self-reports or administrative data, but the concordance between the 2 is not well established. OBJECTIVE: We evaluated the concordance of hospital and physician utilization data from self-reports and claims data, and identified factors associated with disagreement. METHODS: We performed a secondary analysis on linked observational and administrative data. A national sample of 4310 respondents who were 70 years old or older at their baseline interviews was used. Self-reported and Medicare claims-based hospital episodes and physician visits for 12 months before baseline were examined. Kappa statistics were used to evaluate concordance, and multivariable multinomial logistic regression was used to identify factors associated with overreporting (self-reports > claims), underreporting (self-reports < claims), and concordant-reporting (self-reports approximately claims). RESULTS: The concordance of hospital episodes was high (kappa = 0.767 for the 2 x 2 comparison of none vs. some and kappa = 0.671 for the 6 x 6 comparison of none, 1, ..., 4, or 5 or more), but concordance for physician visits was low (kappa = 0.255 for the 2 x 2 comparison of none versus some and kappa = 0.351 for the 14 x 14 comparison of none, 1, ..., 12, and 13 or more). Multivariable multinomial logistic regression indicated that over-, under-, and concordant-reporting of hospital episodes was significantly associated with gender, alcohol consumption, arthritis, cancer, heart disease, psychologic problems, lower body functional limitations, self-rated health, and depressive symptoms. Over-, under-, and concordant-reporting of physician visits were significantly associated with age, gender, race, living alone, veteran status, private health insurance, arthritis, cancer, diabetes, hypertension, heart disease, lower body functional limitations, and poor memory. CONCLUSIONS: Concordance between self-reported and claims-based hospital episodes was high, but concordance for physician visits was low. Factors significantly associated with bidirectional (over- and underreporting) and unidirectional (over- or underreporting) error patterns were detected. Therefore, caution is advised when drawing conclusions based on just one physician visit data source.
Keywords: Aged; Centers for Medicare and Medicaid Services, U.S.; Episode of Care; Female; Hospitalization; Humans; Insurance Claim Review; Interviews as Topic; Male; Physicians; Quality Assurance, Health Care; Self Disclosure; United States

An interpersonal continuity of care measure for Medicare Part B claims analyses. - Frederic D Wolinsky; Thomas R Miller; John F Geweke; Elizabeth A Chrischilles; An, Hyonggin; Robert B Wallace; Claire E Pavlik; Kara B Wright; Robert L. Ohsfeldt; Gary E Rosenthal (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVES: This article presents an interpersonal continuity of care measure. METHODS: We operationalized continuity of care as no more than an 8-month interval between any two visits during a 2-year period to either (a) the same primary care physician or (b) the same physician regardless of specialty. Sensitivity analyses evaluated two interval censoring algorithms and two alternative intervals. We linked Medicare Part A and B claims to baseline survey data for 4,596 respondents to the Survey on Asset and Health Dynamics Among the Oldest Old. We addressed the potential for selection bias by using propensity score methods, and we explored construct validity. RESULTS: Interpersonal continuity with a primary care physician was 17.3%, and interpersonal continuity of care with any physician was 26.1%. Older participants; men; individuals who lived alone; people who had difficulty walking; and respondents with medical histories of arthritis, cancer, diabetes, heart conditions, hypertension, and stroke were most likely to have continuity. Individuals who had never married, were widowed, were working, or had low subjective life expectancy were least likely to have continuity. DISCUSSION: Researchers can measure interpersonal continuity of care using Medicare Part B claims. Replication of these findings and further construct validation, however, are needed prior to widespread adoption of this method.
Keywords: Aged; Aged, 80 and over; Continuity of Patient Care; Disability Evaluation; Female; Health Services Accessibility; Health Surveys; Humans; Insurance Claim Review; Male; Medicare Part B; Mobility Limitation; Physician-Patient Relations; Primary Health Care; United States

Latent variable analyses of age trends of cognition in the Health and Retirement Study, 1992-2004. - John J McArdle; Gwenith G Fisher; Kelly M Kadlec (Psychol Aging, 2007)
The present study was conducted to better describe age trends in cognition among older adults in the longitudinal Health and Retirement Study (HRS) from 1992 to 2004 (N = 17,000). The authors used contemporary latent variable models to organize this information in terms of both cross-sectional and longitudinal inferences about age and cognition. Common factor analysis results yielded evidence for at least 2 common factors, labeled Episodic Memory and Mental Status, largely separable from vocabulary. Latent path models with these common factors were based on demographic characteristics. Multilevel models of factorial invariance over age indicated that at least 2 common factors were needed. Latent curve models of episodic memory were based on age at testing and showed substantial age differences and age changes, including impacts due to retesting as well as several time-invariant and time-varying predictors.
Keywords: Aged; Aged, 80 and over; Aging; Cognition; Female; Health Surveys; Humans; Individuality; Longitudinal Studies; Male; Mental Recall; Mental Status Schedule; Middle Aged; Models, Statistical; Neuropsychological tests; Psychometrics; Retention, Psychology; Sex Factors; United States

The long-term effects of poor childhood health: an assessment and application of retrospective reports. - Steven A Haas (Demography, 2007)
This study assesses retrospective childhood health reports and examines childhood health as a predictor of adult health. The results suggest that such reports are of reasonable reliability as to warrant their judicious use in population research. They also demonstrate a large positive relationship between childhood and adult health. Compared with excellent, very good, or good childhood health, poor childhood health is associated with more than three times greater odds of having poor adult self-rated health and twice the risk of a work-limiting disability or a chronic health condition. These associations are independent of childhood and current socioeconomic position and health-related risk behaviors.
Keywords: Adolescent; Adult; Age Factors; Aged; Child; Child Welfare; Child, Preschool; Chronic disease; Disabled Persons; Female; Health Status; Humans; Infant; Infant, Newborn; Male; Middle Aged; Reproducibility of Results; Retrospective Studies; Risk Assessment; Risk Factors; Socioeconomic factors; Time; United States

Mechanisms for racial and ethnic disparities in glycemic control in middle-aged and older Americans in the health and retirement study. - Michele M Heisler; Jessica Faul; Rodney A. Hayward; Kenneth M. Langa; Caroline S Blaum; David R Weir (Arch Intern Med, 2007)
BACKGROUND: Mechanisms for racial/ethnic disparities in glycemic control are poorly understood. METHODS: A nationally representative sample of 1901 respondents 55 years or older with diabetes mellitus completed a mailed survey in 2003; 1233 respondents completed valid at-home hemoglobin A(1c) (HbA(1c)) kits. We constructed multivariate regression models with survey weights to examine racial/ethnic differences in HbA(1c) control and to explore the association of HbA(1c) level with sociodemographic and clinical factors, access to and quality of diabetes health care, and self-management behaviors and attitudes. RESULTS: There were no significant racial/ethnic differences in HbA(1c) levels in respondents not taking antihyperglycemic medications. In 1034 respondents taking medications, the mean HbA(1c) value (expressed as percentage of total hemoglobin) was 8.07% in black respondents and 8.14% in Latino respondents compared with 7.22% in white respondents (P < .001). Black respondents had worse medication adherence than white respondents, and Latino respondents had more diabetes-specific emotional distress (P < .001). Adjusting for hypothesized mechanisms accounted for 14.0% of the higher HbA(1c) levels in black respondents and 19.0% in Latinos, with the full model explaining 22.0% of the variance. Besides black and Latino ethnicity, only insulin use (P < .001), age younger than 65 years (P = .007), longer diabetes duration (P = .004), and lower self-reported medication adherence (P = .04) were independently associated with higher HbA(1c) levels. CONCLUSIONS: Latino and African American respondents had worse glycemic control than white respondents. Socioeconomic, clinical, health care, and self-management measures explained approximately a fifth of the HbA(1c) differences. One potentially modifiable factor for which there were racial disparities--medication adherence--was among the most significant independent predictors of glycemic control.
Keywords: Aged; Aged, 80 and over; Black People; Diabetes Mellitus; Female; Glycated Hemoglobin; Health Services Accessibility; Hispanic or Latino; Humans; Longitudinal Studies; Male; Middle Aged; Patient Compliance; Socioeconomic factors; Treatment Refusal; United States; White People

Pain in aging community-dwelling adults in the United States: non-Hispanic whites, non-Hispanic blacks, and Hispanics. - Reyes-Gibby, Cielito C.; Aday, Lu Ann; Todd, Knox H.; Cleeland, Charles S.; Anderson, Karen O. (J Pain, 2007)
UNLABELLED: Racial and ethnic disparities in healthcare persist in the U.S. Although pain is one of the most prevalent and disabling symptoms of disease, only a few studies have assessed disparities in pain in large racially and ethnically diverse, middle- to late aged community samples, thus limiting the generalizability of study findings in broader populations. With data from the 2000 Health and Retirement Study, we assessed the prevalence and impact of pain in a community sample of aging (> or =51 years old) non-Hispanic whites (n = 11,021), non-Hispanic blacks (n = 1,804), and Hispanics (n = 952) in the U.S. Pain, pain severity, activity limitation as a result of pain, comorbid conditions, and sociodemographic variables were assessed. Results showed that pain prevalence was 28%, and 17% of the sample reported activity limitation as a result of pain. Non-Hispanic blacks (odds ratio [OR], 1.78; 99% confidence interval [CI], 1.33-2.37) and Hispanics (OR, 1.80; 99% CI, 1.26-2.56) had higher risk for severe pain compared with non-Hispanic whites. Analyses of respondents with pain (n = 3,811) showed that having chronic diseases (2 comorbid conditions, OR, 1.5; 99% CI, 1.09-2.17), psychological distress (OR, 1.99; 99% CI, 1.54-2.43), being a Medicaid recipient (OR, 1.63; 99% CI, 1.17-2.25), and lower educational level (OR, 1.45; 99% CI, 1.14-1.85) were significant predictors for severe pain and helped to explain racial/ethnic differences in pain severity. PERSPECTIVE: This study, which used a large racially and ethnically diverse community sample, provided empirical evidence that racial/ethnic difference in pain severity in aging community adults in the U.S. can be accounted for by differential vulnerability in terms of chronic disease, socioeconomic conditions, and access to care.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Aging; Black People; Chronic disease; Data collection; ethnicity; Female; Hispanic or Latino; Humans; Insurance, Health; Logistic Models; Male; Middle Aged; pain; Pain Measurement; Population; Socioeconomic factors; United States; White People

Participation in food assistance programs modifies the relation of food insecurity with weight and depression in elders. - Kim, Kirang; Edward A Frongillo (J Nutr, 2007)
The relation of food insecurity in elders with outcomes such as overweight and depression, and the influence of participation in food assistance programs on these relations, has not been established. The aim of this study was to examine the relation between food insecurity and weight and depression in elders, and determine whether participation in food assistance programs modifies the effect of food insecurity on weight and depression. Two longitudinal data sets were used: the Health and Retirement Study (1996-2002) and the Asset and Health Dynamics Among the Oldest Old (1995-2002). The relation of food insecurity and participation in food assistance programs was assessed by multilevel linear regression analysis. Food insecurity was positively related to weight and depression among elders. Some analyses supported that food-insecure elders who participated in food assistance programs were less likely to be overweight and depressed than those who did not participate in food assistance programs. This finding implies that food assistance programs can have both nutritional and non-nutritional impacts. The positive impact of participation in food assistance programs of reducing or preventing poor outcomes resulting from food insecurity will improve elders' quality of life, save on their healthcare expenses, and help to meet their nutritional needs.
Keywords: Aged; depression; Female; Food Services; Food Supply; Health Surveys; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; Models, Theoretical; Overweight; Public Assistance; United States

Predicting the changes in depressive symptomatology in later life: how much do changes in health status, marital and caregiving status, work and volunteering, and health-related behaviors contribute? - Namkee G Choi; Bohman, Thomas M. (J Aging Health, 2007)
This study examined the unique effects of four variable groups on changes in older adults' depressive symptoms for a 2-year period: (1) baseline health and disability status, (2) changes in health and disability since baseline, (3) stability and changes in marital and caregiving status and in work and volunteering, and (4) stability and changes in health-related behaviors. With data from the 1998 and 2000 interview waves of the Health and Retirement Study, the authors used gender-separate multistep (hierarchical) residualized regression analyses in which the Center for Epidemiological Studies Depression scale (CES-D) score at follow-up is modeled as a function of the effect of each group of independent variables. As hypothesized, changes in health, disability, marital, and caregiving status explained a larger amount of variance than the existing and stable conditions, although each group of variables explained a relatively small amount (0.3-3.4%) of variance in the follow-up CES-D score.
Keywords: Aged; Caregivers; depression; Employment; Female; Forecasting; Health Behavior; Health Status; Humans; Male; Marital Status; Middle Aged; Netherlands; Regression Analysis; Sweden; United States; Volunteers

Prevalence of dementia in the United States: the aging, demographics, and memory study. - Brenda L Plassman; Kenneth M. Langa; Gwenith G Fisher; Steven G Heeringa; David R Weir; Mary Beth Ofstedal; James R Burke; Michael D Hurd; Guy G Potter; Willard L Rodgers; David C Steffens; Robert J. Willis; et al. (Neuroepidemiology, 2007)
AIM: To estimate the prevalence of Alzheimer's disease (AD) and other dementias in the USA using a nationally representative sample. METHODS: The Aging, Demographics, and Memory Study sample was composed of 856 individuals aged 71 years and older from the nationally representative Health and Retirement Study (HRS) who were evaluated for dementia using a comprehensive in-home assessment. An expert consensus panel used this information to assign a diagnosis of normal cognition, cognitive impairment but not demented, or dementia (and dementia subtype). Using sampling weights derived from the HRS, we estimated the national prevalence of dementia, AD and vascular dementia by age and gender. RESULTS: The prevalence of dementia among individuals aged 71 and older was 13.9%, comprising about 3.4 million individuals in the USA in 2002. The corresponding values for AD were 9.7% and 2.4 million individuals. Dementia prevalence increased with age, from 5.0% of those aged 71-79 years to 37.4% of those aged 90 and older. CONCLUSIONS: Dementia prevalence estimates from this first nationally representative population-based study of dementia in the USA to include subjects from all regions of the country can provide essential information for effective planning for the impending healthcare needs of the large and increasing number of individuals at risk for dementia as our population ages.
Keywords: Age Distribution; Aged; Aged, 80 and over; Cohort Studies; Dementia; Female; Geriatric Assessment; Health Surveys; Humans; Logistic Models; Male; Prevalence; Sex Distribution; United States

Racial/ethnic differences in the development of disability among older adults. - Dorothy D Dunlop; Song, Jing; Larry M Manheim; Daviglus, Martha L.; Rowland W Chang (Am J Public Health, 2007)
OBJECTIVES: We investigated differences in the development of disability in activities of daily living among non-Hispanic Whites, African Americans, Hispanics interviewed in Spanish, and Hispanics interviewed in English. METHODS: We estimated 6-year risk for disability development among 8161 participants 65 years or older and free of baseline disability. We evaluated mediating factors amenable to clinical and public health intervention on racial/ethnic difference. RESULTS: The risk for developing disability among Hispanics interviewed in English was similar to that among Whites (hazard ratio [HR]=0.99; 95% confidence interval [CI] = 0.6, 1.4) but was substantially higher among African Americans (HR=1.6; 95% CI=1.3, 1.9) and Hispanics interviewed in Spanish (HR=1.8; 95% CI=1.4, 2.1). Adjustment for demographics, health, and socioeconomic status reduced a large portion of those disparities (African American adjusted HR=1.1, Spanish-interviewed Hispanic adjusted HR=1.2). CONCLUSIONS: Higher risks for developing disability among older African Americans, and Hispanics interviewed in Spanish compared with Whites were largely attenuated by health and socioeconomic differences. Language- and culture-specific programs to increase physical activity and promote weight maintenance may reduce rates of disability in activities of daily living and reduce racial/ethnic disparities in disability.
Keywords: Activities of Daily Living; Aged; Black or African American; Disabled Persons; Female; Health Behavior; Health Status Disparities; Health Surveys; Hispanic or Latino; Humans; Male; Prevalence; Proportional Hazards Models; Prospective Studies; Risk; Socioeconomic factors; Survival Analysis; United States; White People

The relationship between self-rated health and mortality in older black and white Americans. - Sei J. Lee; Sandra Y. Moody-Ayers; C. Seth Landefeld; Louise C Walter; Lindquist, Karla; Mark Segal; Kenneth E Covinsky (J Am Geriatr Soc, 2007)
OBJECTIVES: To determine whether the association between self-rated health (SRH) and 4-year mortality differs between black and white Americans and whether education affects this relationship. DESIGN: Prospective cohort. SETTING: Communities in the United States. PARTICIPANTS: Sixteen thousand four hundred thirty-two subjects (14,004 white, 2,428 black) enrolled in the 1998 wave of the Health and Retirement Study (HRS), a population-based study of community-dwelling U.S. adults aged 50 and older. MEASUREMENTS: Subjects were asked to self-identify their race and their overall health by answering the question, "Would you say your health is excellent, very good, good, fair, or poor?" Death was determined according to the National Death Index. RESULTS: SRH is a much stronger predictor of mortality in whites than blacks (c-statistic 0.71 vs 0.62). In whites, poor SRH resulted in a markedly higher risk of mortality than excellent SRH (odds ratio (OR)=10.4, 95% confidence interval (CI)=8.0-13.6). In blacks, poor RSH resulted in a much smaller increased risk of mortality (OR=2.9, 95% CI=1.5-5.5). SRH was a stronger predictor of death in white and black subjects with higher levels of education, but differences in education could not account for the observed race differences in the prognostic effect of SRH. CONCLUSION: This population-based study found that the relationship between SRH and mortality is stronger in white Americans and in subjects with higher levels of education. Because the association between SRH and mortality appears weakest in traditionally disadvantaged groups, SRH may not be the best measure to identify vulnerable older subjects.
Keywords: Age Distribution; Aged; Aged, 80 and over; Black People; Educational Status; Female; Health Status; Humans; Male; Middle Aged; Mortality; Population Surveillance; Prognosis; Self Disclosure; Sex Distribution; United States; White People

Risk of nursing home admission among older americans: does states' spending on home- and community-based services matter? - Muramatsu, Naoko; yin, Hongjun; Richard T. Campbell; Ruby L Hoyem; Martha A. Jacob; Christopher Ross (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVE: States vary greatly in their support for home- and community-based services (HCBS) that are intended to help disabled seniors live in the community. This article examines how states' generosity in providing HCBS affects the risk of nursing home admission among older Americans and how family availability moderates such effects. METHODS: We conducted discrete time survival analysis of first long-term (90 or more days) nursing home admissions that occurred between 1995 and 2002, using Health and Retirement Study panel data from respondents born in 1923 or earlier. RESULT: State HCBS effects were conditional on child availability among older Americans. Living in a state with higher HCBS expenditures was associated with lower risk of nursing home admission among childless seniors (p <.001). However, the association was not statistically significant among seniors with living children. Doubling state HCBS expenditures per person aged 65 or older would reduce the risk of nursing home admission among childless seniors by 35%. DISCUSSION: Results provided modest but important evidence supportive of increasing state investment in HCBS. Within-state allocation of HCBS resources, however, requires further research and careful consideration about fairness for individual seniors and their families as well as cost effectiveness.
Keywords: Aged; Aged, 80 and over; Caregivers; Cohort Studies; Cost Savings; Cost-Benefit Analysis; Female; Financing, Government; Health Expenditures; Home Care Services; Homes for the Aged; Humans; Insurance Coverage; Long-term Care; Male; Medicaid; Medicare; Nursing homes; Patient Admission; Patient Readmission; Risk Assessment; Risk Factors; State Health Plans; United States

Self-rated health trajectories and mortality among older adults. - Thomas R Miller; Frederic D Wolinsky (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVES: For this article, we evaluated whether measures of prior self-rated health (SRH) trajectories had associations with subsequent mortality that were independent of current SRH assessment and other covariates. METHODS: We used multivariable logistic regression that incorporated four waves of interview data (1993, 1995, 1998, and 2000) from the Asset and Health Dynamics Among the Oldest Old Survey in order to predict mortality during 2000-2002. We defined prior SRH trajectories for each individual based on the slope estimated from a simple linear regression of their own SRH between 1993 and 1998 and the variance around that slope. In addition to SRH reported in 2000, other covariates included in the mortality models reflected health status, health-related behaviors, and individual resources. RESULTS: Among the 3,129 respondents in the analytic sample, SRH in 2000 was significantly (p <.0001) associated with mortality, but the measures of prior SRH trajectories were not. Prior SRH trajectory was, however, a significant determinant of current SRH. We observed significant independent associations with mortality for age, sex, education, lung disease, and having ever smoked. DISCUSSION: Although measures of prior SRH trajectories did not have significant direct associations with mortality, they did have important indirect effects via their influence on current SRH.
Keywords: Age Factors; Aged; Aged, 80 and over; Attitude to Health; Cardiovascular Diseases; Cause of Death; Female; Follow-Up Studies; Health Status; Health Status Indicators; Humans; Logistic Models; Longitudinal Studies; Lung Diseases; Male; Mortality; Multivariate Analysis; Risk Factors; Sex Factors; Smoking; Socioeconomic factors; Survival Analysis; United States

Urban neighborhoods and depressive symptoms among older adults. - Carol S Aneshensel; Richard G Wight; Miller-Martinez, Dana; Amanda L. Botticello; Arun S Karlamangla; Teresa Seeman (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVE: This study seeks to determine whether depressive symptoms among older persons systematically vary across urban neighborhoods such that experiencing more symptoms is associated with low socioeconomic status (SES), high concentrations of ethnic minorities, low residential stability and low proportion aged 65 years and older. METHODS: Survey data are from the Study of Assets and Health Dynamics Among the Oldest Old (AHEAD), a 1993 U.S. national probability sample of noninstitutionalized persons born in 1923 or earlier (i.e. people aged 70 or older). Neighborhood data are from the 1990 Census at the tract level. Hierarchical linear regression is used to estimate multilevel models. RESULT: The average number of depressive symptoms varies across Census tracts independent of individual-level characteristics. Symptoms are not significantly associated with neighborhood SES, ethnic composition, or age structure when individual-level characteristics are controlled statistically. However, net of individual-level characteristics, symptoms are positively associated with neighborhood residential stability, pointing to a complex meaning of residential stability for the older population. DISCUSSION: This study shows that apparent neighborhood-level socioeconomic effects on depressive symptoms among urban-dwelling older adults are largely if not entirely compositional in nature. Further, residential stability in the urban neighborhood may not be emotionally beneficial to its aged residents.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Comorbidity; Cross-Sectional Studies; Depressive Disorder; Female; Health Status Indicators; Health Surveys; Humans; Incidence; Male; Minority Groups; Peer Group; Population Dynamics; Risk Factors; Social Environment; United States; Urban Population

Use of health services by previously uninsured Medicare beneficiaries. - J. Michael McWilliams; Meara, Ellen; Alan M. Zaslavsky; John Z. Ayanian (N Engl J Med, 2007)
BACKGROUND: Previously uninsured adults who enroll in the Medicare program at the age of 65 years may have greater morbidity, requiring more intensive and costlier care over subsequent years, than they would if they had been previously insured. METHODS: We used longitudinal data from the nationally representative Health and Retirement Study to assess self-reported health care use and expenditures from 1992 through 2004 among 5158 adults who were privately insured or uninsured before Medicare coverage began at the age of 65 years. We used propensity-score methods to compare health care use and expenditures for previously insured and uninsured beneficiaries who were similar across numerous characteristics at 59 to 60 years of age and adjusted for differences in supplemental and prescription-drug coverage after 65 years of age. RESULTS: Among 2951 adults with hypertension, diabetes, heart disease, or stroke diagnosed before 65 years of age, previously uninsured adults who acquired Medicare coverage at the age of 65 reported significantly greater increases in the numbers of doctor visits (P<0.001) and hospitalizations (P=0.001) and in total medical expenditures (P=0.02) than did previously insured adults. Significant differential increases were not evident among the 2207 adults without these conditions (P>0.12 for all comparisons). In analyses adjusted for supplemental and prescription-drug coverage, previously uninsured adults with these conditions reported more doctor visits (13% relative difference, P=0.04), more hospitalizations (20% relative difference, P=0.04), and higher total medical expenditures (51% relative difference, P=0.09) from ages 65 to 72 years than did previously insured adults. CONCLUSIONS: The costs of expanding health insurance coverage for uninsured adults before they reach the age of 65 years may be partially offset by subsequent reductions in health care use and spending for these adults after the age of 65, particularly if they have cardiovascular disease or diabetes before the age of 65 years.
Keywords: Aged; Cardiovascular Diseases; Diabetes Mellitus; Female; Health Expenditures; Health Services; Hospitalization; Humans; Insurance, Health; Logistic Models; Longitudinal Studies; Male; Medically Uninsured; Medicare; Middle Aged; Socioeconomic factors; United States

Use of preventive care by the working poor in the United States. - Joseph S. Ross; Bernheim, Susannah M.; Elizabeth H Bradley; Teng, Hsun-Mei; William T Gallo (Prev Med, 2007)
OBJECTIVE: Examine the association between poverty and preventive care use among older working adults. METHOD: Cross-sectional analysis of the pooled 1996, 1998 and 2000 waves of the Health and Retirement Study, a nationally representative sample of older community-dwelling adults, studying self-reported use of cervical, breast, and prostate cancer screening, as well as serum cholesterol screening and influenza vaccination. Adults with incomes within 200% of the federal poverty level were defined as poor. RESULTS: Among 10,088 older working adults, overall preventive care use ranged from 38% (influenza vaccination) to 76% (breast cancer screening). In unadjusted analyses, the working poor were significantly less likely to receive preventive care. After adjustment for insurance coverage, education, and other socio-demographic characteristics, the working poor remained significantly less likely to receive breast cancer (RR 0.92, 95% CI, 0.86-0.96), prostate cancer (RR 0.89, 95% CI, 0.81-0.97), and cholesterol screening (RR 0.91, 95% CI, 0.86-0.96) than the working non-poor, but were not significantly less likely to receive cervical cancer screening (RR 0.96, 95% CI, 0.90-1.01) or influenza vaccination (RR 0.92, 95% CI, 0.84-1.01). CONCLUSION: The older working poor are at modestly increased risk for not receiving preventive care.
Keywords: Cost of Illness; Cross-Sectional Studies; Employment; Female; Health Promotion; Health Services Accessibility; Health Services Needs and Demand; Humans; Male; Mass Screening; Middle Aged; Patient Acceptance of Health Care; Poverty; Preventive Health Services; Risk Assessment; Socioeconomic factors; United States; Vulnerable Populations

Weight and depressive symptoms in older adults: direction of influence? - Valerie L Forman-Hoffman; Jon W. Yankey; Stephen L Hillis; Robert B Wallace (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVE: . The purpose of this study was to clarify the direction of the relationship between changes in depressive symptoms and changes in weight in older adults. Methods. The sample included a prospective cohort of individuals aged 53-63 (n = 9,130) enrolled in the Health and Retirement Study. We used separate cross-lagged models for men and women in order to study the impact of weight change on subsequent increases in depressive symptoms 2 years later and vice versa. RESULT: . Weight gain did not lead to increased depressive symptoms, and weight loss preceded increased depressive symptoms only in unadjusted models among men (odds ratio [OR] = 1.26, 95% confidence interval [CI] = 1.04-1.53). Increased depressive symptoms were not predictive of subsequent weight loss, but they were predictive of subsequent weight gain in unadjusted models only (men: OR = 1.24, 95% CI = 1.00-1.54; women: OR = 1.12, 95% CI = 1.00-1.26). In adjusted models, baseline depressive symptoms predicted both weight loss and weight gain among both men and women. Increase in functional limitations and medical conditions were significant predictors of both weight loss and weight gain. Baseline functional limitations also predicted increased depressive symptoms. Discussion. Based on our findings, it is apparent that researchers need to examine the pathways between changes in weight and increases in depressive symptoms in the context of functional limitations and medical comorbidity.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Comorbidity; Depressive Disorder; Female; Health Status Indicators; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; Models, Statistical; Odds Ratio; Prospective Studies; Sex Factors; Statistics as Topic; United States; Weight Gain; Weight Loss

Changes in health for the uninsured after reaching age-eligibility for Medicare. - David W. Baker; Joseph Feinglass; Durazo-Arvizu, Ramon; Whitney P. Witt; Joseph J Sudano; Jason A. Thompson (J Gen Intern Med, 2006)
BACKGROUND: Uninsured adults in late middle age are more likely to have a health decline than individuals with private insurance. OBJECTIVE: To determine how health and the risk of future adverse health outcomes changes after the uninsured gain Medicare. DESIGN: Prospective cohort study. PARTICIPANTS: Participants (N=3,419) in the Health and Retirement Study who transitioned from private insurance or being uninsured to having Medicare coverage at the 1996, 1998, 2000, or 2002 interview. MEASUREMENTS: We analyzed risk-adjusted changes in self-reported overall health and physical functioning during the transition period to Medicare (t(-2) to t(0)) and the following 2 years (t(0) to t(2)). RESULTS: Between the interview before age 65 (t(-2)) and the first interview after reaching age 65 (t(0)), previously uninsured individuals were more likely than those who had private insurance to have a major decline in overall health (adjusted relative risk [ARR] 1.46; 95% confidence interval [CI] 1.03 to 2.04) and to develop a new physical difficulty affecting mobility (ARR 1.24; 95% CI 0.96 to 1.56) or agility (ARR 1.33; 95% CI 1.12 to 1.54). Rates of improvement were similar between the 2 groups. During the next 2 years (t(0) to t(2)), adjusted rates of declines in overall health and physical functioning were similar for individuals who were uninsured and those who had private insurance before gaining Medicare. CONCLUSIONS: Gaining Medicare does not lead to immediate health benefits for individuals who were uninsured before age 65. However, after 2 or more years of continuous coverage, the uninsured no longer have a higher risk of adverse health outcomes.
Keywords: Age Factors; Aged; Cohort Studies; Eligibility Determination; Female; Health Status; Humans; Male; Medically Uninsured; Medicare; Middle Aged; Prospective Studies; United States

Cohabitation among older adults: a national portrait. - Susan L. Brown; Lee, Gary R.; Jennifer R. Bulanda (J Gerontol B Psychol Sci Soc Sci, 2006)
OBJECTIVE: Older adults are increasingly likely to experience cohabitation, or living together unmarried in an intimate, heterosexual union. In order to begin building a conceptual framework, we provide a descriptive portrait of older adult cohabitors, emphasizing how they compare to older remarrieds and unpartnereds. METHODS: We used data from both Census 2000 and the 1998 Health and Retirement Study ( HRS; Health and Retirement Study, 1998) to estimate the size and composition of the cohabiting population aged 51 and older. Also, using HRS data, we estimated multinomial logistic regression models to identify the correlates associated with cohabitation and remarriage (vs being unpartnered) among women and men who were previously married. RESULT: More than 1 million older adults, composing 4% of the unmarried population, currently cohabit. About 90% of these individuals were previously married. We identify significant differences among cohabitors, remarrieds, and unpartnereds across several dimensions, including sociodemographic characteristics, economic resources, physical health, and social relationships. Cohabitors appear to be more disadvantaged than remarrieds, and this is especially evident for women. DISCUSSION: Older cohabitors differ from individuals of other marital statuses, and therefore future work on marital status should explicitly incorporate cohabitation.
Keywords: Activities of Daily Living; Demography; Female; Health Status; Humans; Interpersonal Relations; Male; Marriage; Middle Aged; Residence Characteristics; Sexual Partners; Surveys and Questionnaires; United States

Crediting care or marriage? Reforming Social Security family benefits. - Herd, Pamela (J Gerontol B Psychol Sci Soc Sci, 2006)
OBJECTIVE: For more than 20 years policy advocates and policymakers have argued that Social Security should reward women for raising children. Current family benefits, which only benefit women who marry, are thought to be outdated and unable to protect the neediest women. Thus, would Black and poor women fare better if family benefits were linked to parenthood, as opposed to marriage? I examined three care credit proposals that reflect the most common proposals put forth in the United States and the most common designs in other countries. METHODS: I used the 1992 Health and Retirement Study and the Current Population Survey to create a policy simulation that estimates how women reaching age 62 from 2020 to 2030 would be affected by care credits. RESULT: Black and poor women fared best with benefits linked to parenthood. The specific proposal allowed parents, from the 35 earnings years used to calculate their benefit, to substitute $15,000 for up to 9 earnings' years that fell below this level. DISCUSSION: The poorest women fare better with family benefits linked to parenthood instead of marital status. Moreover, they fare best when working women can benefit from care credits, but the care credit's value is not linked to earnings.
Keywords: Family; Female; Humans; Insurance Benefits; Marital Status; Mothers; Social Security; United States

Dual use of Medicare and the Veterans Health Administration: are there adverse health outcomes? - Frederic D Wolinsky; Thomas R Miller; An, Hyonggin; Paul R Brezinski; Thomas E Vaughn; Gary E Rosenthal (BMC Health Serv Res, 2006)
BACKGROUND: Millions of veterans are eligible to use the Veterans Health Administration (VHA) and Medicare because of their military service and age. This article examines whether an indirect measure of dual use based on inpatient services is associated with increased mortality risk. METHODS: Data on 1,566 self-responding men (weighted N = 1,522) from the Survey of Assets and Health Dynamics among the Oldest Old (AHEAD) were linked to Medicare claims and the National Death Index. Dual use was indirectly indicated when the self-reported number of hospital episodes in the 12 months prior to baseline was greater than that observed in the Medicare claims. The independent association of dual use with mortality was estimated using proportional hazards regression. RESULTS: 96 (11%) of the veterans were classified as dual users. 766 men (50.3%) had died by December 31, 2002, including 64.9% of the dual users and 49.3% of all others, for an attributable mortality risk of 15.6% (p < .003). Adjusting for demographics, socioeconomics, comorbidity, hospitalization status, and selection bias at baseline, as well as subsequent hospitalization for ambulatory care sensitive conditions, the independent effect of dual use was a 56.1% increased relative risk of mortality (AHR = 1.561; p = .009). CONCLUSION: An indirect measure of veterans' dual use of the VHA and Medicare systems, based on inpatient services, was associated with an increased risk of death. Further examination of dual use, especially in the outpatient setting, is needed, because dual inpatient and dual outpatient use may be different phenomena.
Keywords: Aged; Aged, 80 and over; Deductibles and Coinsurance; Episode of Care; Health Services Research; Hospitals, Veterans; Humans; Male; Medicare; Mortality; Outcome Assessment, Health Care; Proportional Hazards Models; Quality Indicators, Health Care; Risk Assessment; Selection Bias; Surveys and Questionnaires; United States; United States Department of Veterans Affairs; Veterans

The effect of private insurance on the health of older, working age adults: evidence from the health and retirement study. - Avi Dor; Joseph J Sudano; David W. Baker (Health Serv Res, 2006)
OBJECTIVE: Primarily, to determine if the presence of private insurance leads to improved health status, as measured by a survey-based health score. Secondarily, to explore sensitivity of estimates to adjustments for endogeneity. The study focuses on adults in late middle age who are nearing entry into Medicare. DATA SOURCES: The analysis file is drawn from the Health and Retirement Study, a national survey of relatively older adults in the labor force. The dependent variable, an index of 5 health outcome items, was obtained from the 1996 survey. Independent variables were obtained from the 1992 survey. State-level instrumental variables were obtained from the Area Resources File and the TAXSIM file. The final sample consists of 9,034 individuals of which 1,540 were uninsured. STUDY DESIGN: Estimation addresses endogeneity of the insurance participation decision in health score regressions. In addition to ordinary least squares (OLS), two models are tested: an instrumental variables (IV) model, and a model with endogenous treatment effects due to Heckman (1978). Insurance participation and health behaviors enter with a lag to allow their effects to dissipate over time. Separate regressions were run for groupings of chronic conditions. PRINCIPAL FINDINGS: The OLS model results in statistically significant albeit small effects of insurance on the computed health score, but the results may be downward biased. Adjusting for endogeneity using state-level instrumental variables yields up to a six-fold increase in the insurance effect. Results are consistent across IV and treatment effects models, and for major groupings of medical conditions. The insurance effect appears to be in the range of about 2-11 percent. There appear to be no significant differences in the insurance effect for subgroups with and without major chronic conditions. CONCLUSIONS: Extending insurance coverage to working age adults may result in improved health. By conjecture, policies aimed at expanding coverage to this population may lead to improved health at retirement and entry to Medicare, potentially leading to savings. However, further research is needed to determine whether similar results are found when alternative measures of overall health or health scores are used. Future research should also explore the use of alternative instrumental variables. Preliminary results provide no justification for targeting certain subgroups with susceptibility to certain chronic conditions rather than broad policy interventions.
Keywords: Chronic disease; Data collection; Female; Health Status; Humans; Insurance, Health; Male; Medically Uninsured; Middle Aged; Private Sector; United States

The effect of recurrent involuntary job loss on the depressive symptoms of older US workers. - William T Gallo; Elizabeth H Bradley; Teng, Hsun-Mei; Stanislav V Kasl (Int Arch Occup Environ Health, 2006)
OBJECTIVES: The objective of this study was to assess whether recurrent involuntary job loss among US workers nearing retirement resulted in increasingly less severe changes in depressive symptoms with successive job losses. METHODS: With data drawn from the US Health and Retirement Survey (HRS), we used repeated measures longitudinal analysis to investigate the effect of recurrent job loss on follow-up depressive symptoms, measured up to 2 years following job loss. Study participants include 617 individuals, aged 51-61 years at the 1992 study baseline, who had at least one job loss between 1990 and 2000. Our primary outcome variable was a continuous measure of depressive symptoms, constructed from the 8-item Center for Epidemiologic Studies-Depression (CES-D) battery administered at every HRS wave. A second, dichotomous outcome, derived from the continuous measure, measured clinically relevant depressive symptoms. The exposure (recurrent job loss) was defined by binary dummy variables representing two and three/four job losses. All job losses were the result of either plant closing or layoff. RESULTS: Our main finding indicates that, after relevant covariates are controlled, compared to one job loss, two job losses result in a modest increase in the level depressive symptoms (not significant) at two-year follow-up. Three or more job losses result, on average, in a decline in depressive symptoms to a level near pre-displacement assessment (not significant). Somewhat in contrast, two job losses were found to be associated with increased risk of clinically relevant depressive symptoms. CONCLUSIONS: The principal finding confirms our hypothesis that, among US workers nearing retirement, repeated exposure to job separation results in diminished effects on mental health. Adaptation to the job loss stressor may underlie the observed response, although other explanations, including macroeconomic developments, are possible.
Keywords: Adaptation, Physiological; depression; Employment; Female; Humans; Life Change Events; Longitudinal Studies; Male; Middle Aged; Retirement; Stress, Psychological; United States

Effects of retirement and grandchild care on depressive symptoms. - Maximiliane E Szinovacz; Adam Davey (Int J Aging Hum Dev, 2006)
This study explores how grandchild care in conjunction with grandparents' retirement affects depressive symptoms, using data from the Health and Retirement Survey. The findings demonstrate that retirement moderates the influence of grandchild care obligations on well-being, measured by depressive symptoms. For retired men, freedom from grandchild care obligations is associated with heightened well-being. Among women, continued employment seems to protect against potential negative effects of extensive grandchild care obligations on well-being. The results for men seem most in line with the argument that family care obligations spoil retirement, whereas the results for women suggest a scenario that is most compatible with the role enhancement thesis.
Keywords: Aged; Aging; Child; Child Rearing; depression; Family Characteristics; Female; Holistic health; Humans; Intergenerational Relations; Leisure activities; Longitudinal Studies; Male; Middle Aged; Retirement; Sex Factors; Social Responsibility; Surveys and Questionnaires; United States

Explaining US racial/ethnic disparities in health declines and mortality in late middle age: the roles of socioeconomic status, health behaviors, and health insurance. - Joseph J Sudano; David W. Baker (Soc Sci Med, 2006)
Pervasive health disparities continue to exist among racial/ethnic minority groups, but the factors related to these disparities have not been fully elucidated. We undertook this prospective cohort study to determine the independent contributions of socioeconomic status (SES), health behaviors, and health insurance in explaining racial/ethnic disparities in mortality and health declines. Our study period was 1992-1998, and our study population consists of a US nationally representative sample of 6286 non-Hispanic whites (W), 1391 non-Hispanic blacks (B), 405 Hispanics interviewed in English (H/E), and 318 Hispanics interviewed in Spanish (H/S), ages 51-61 in 1992 in the Health and Retirement Study. The main outcome measures were death; major decline in self-reported overall health (SROH); and combined outcome of death or major decline in SROH. Crude mortality rates over the 6-year study period for W, B, H/E and H/S were 5.8%, 10.6%, 5.8%, and 4.4%, respectively. Rates of major decline in SROH were 14.6%, 23.2%, 22.1% and 39.4%, for W, B, H/E and H/S, respectively. Higher mortality rates for B versus W were mostly explained by worse baseline health. For major decline in SROH, education, income, and net worth independently explained more of the disparities for all three minority groups as compared to health behaviors and insurance, reducing the effect for B and H/E to non-significance, while leaving a significant elevated odds ratio for H/S. Without addressing the as-yet undetermined and pernicious effects of lower SES, public health initiatives that promote changing individual health behaviors and increasing rates of insurance coverage among blacks and Hispanics will not eliminate racial/ethnic health disparities.
Keywords: Black or African American; Cohort Studies; Female; Health Behavior; Health Status Disparities; Hispanic or Latino; Humans; Insurance, Health; Logistic Models; Male; Medically Uninsured; Middle Aged; Mortality; Poverty; Risk Assessment; Social Class; Sociology, Medical; United States; White People

Increased wealth and income as correlates of self-assessed retirement. - Caputo, Richard K. (J Gerontol Soc Work, 2006)
This study examined whether retirement implies complete withdrawal from the labor force and the role that increased wealth and income play in regard to the nature of retirement. Data came from the Health & Retirement Study, Waves 1-5. Findings indicated that most study sample pre-retirees remained in the labor force as they moved into what are considered the normal retirement years. As they moved on average from 50+ years of age to 60+ years of age, increasing percentages of study sample pre-retirees reported themselves as completely retired. Those who viewed themselves as completely retired were far less likely to work than those who did not view themselves as completely retired. Of particular importance was the finding that increased income in 2000 decreased the likelihood of self-reported complete retirement. Equally important was the finding that increased assets had no effect on retirement status with the exception of survey year 1998 when increased assets decreased the likelihood of viewing oneself as completely retired. Findings suggested that pro-work retirement policies aimed at increasing labor force participation among pre-retirees and increasing the normal retirement age can be effective. Five pro-work policies were discussed.
Keywords: Aged; Data collection; Employment; Female; Financing, Personal; Humans; Income; Interviews as Topic; Male; Middle Aged; Motivation; Organizational Policy; Pensions; Retirement; Self-Assessment; Social Security; Socioeconomic factors; United States

Insurance coverage and health care use among near-elderly women. - Xiao Xu; Patel, Divya A.; Vahratian, Anjel; Ransom, Scott B. (Womens Health Issues, 2006)
OBJECTIVES: Data on near-elderly (ages 55-64) women's access to and use of health care have been limited. In this study, we sought to examine the status of near-elderly women's health insurance coverage in the United States and how it may influence their use of health care services. METHODS: A nationwide random sample of women aged 55-64 was drawn from the 2002 wave of the Health and Retirement Study. Descriptive statistics were calculated and multivariable regression analyses were performed to quantify the impact of insurance coverage on near-elderly women's use of outpatient services, inpatient services, and prescription medication over a 2-year period. RESULTS: In 2002, 9.4% of near-elderly women in the United States were uninsured and 15.4% had public coverage. Those who had coverage for a particular service were significantly more likely to use that service compared to women without coverage, with odds ratios ranging from 2.0-6.7 for services such as a physician visit, hospital stay, dental visit, and use of prescription medication. Among those who had at least one physician visit, near-elderly women who had some of the cost covered by insurance reported significantly more visits than women without coverage. Likewise, for near-elderly women regularly taking prescription medications, having more extensive coverage significantly increased their likelihood of medication adherence. The frequency of hospitalization was also higher for women who had complete coverage for the cost. CONCLUSIONS: The nature of a near-elderly woman's insurance coverage significantly affects her use of health care services. More attention is needed to improve the health care of near-elderly women with inadequate insurance coverage.
Keywords: Attitude to Health; Female; Health Services Accessibility; Health Services Needs and Demand; Health Status; Humans; Insurance Coverage; Insurance, Health; Medically Uninsured; Middle Aged; Patient Acceptance of Health Care; Socioeconomic factors; United States; Women's Health; Women's Health Services

A longitudinal study of the relationship between health behavior risk factors and dependence in activities of daily living. - Sang-Hyuk Jung; Truls Ostbye; Kyoung-Ok Park (J Prev Med Public Health, 2006)
OBJECTIVES: The purpose of this study was to shed further light on the effect of modifiable health behavior risk factors on dependence in activities of daily living, defined in a multidimensional fashion. METHODS: The study participants were 10,278 middle aged Americans in a longitudinal health study, the Health and Retirement Survey (HRS). A multi-stage probability sampling design incorporating the effect of population sizes (Metropolitan and non-metropolitan), ethnicity (the non-Hispanic White, the Hispanic, and the Black), and age (age 51-61) was utilized. Basic Activities of Daily Living (ADL) were measured using five activities necessary for survival (impairment in dressing, eating, bathing, sleeping, and moving across indoor spaces). Explanatory variables were four health behavior risk factors included smoking, exercise, Body Mass Index (BMI), and alcohol consumption. RESULTS: Most participants at baseline were ADL independent (1992). 97.8% of participants were independent in all ADL's at baseline and 78.2% were married. Approximately 27.5% were current smokers at baseline, and the subjects reported moderate or heavy exercise were 74.8%. All demographic characteristics and behavioral risk factors were significantly associated with the ADL status at Wave 4 except alcohol consumption. Risk behaviors such as current smoking, sedentary life style and high BMI at Wave 1 were associated with ADL status deterioration; however, moderate alcohol consumption tended to be more related to better ADL status than abstaining at Wave 4. ADL status at Wave 1 was the strongest factor and the next was exercise and smoking affecting ADL status at Wave 4. People who were in ADL dependent at Wave 1 were 15.17 times more likely to be ADL dependent at Wave 4 than people who were in ADL independent at Wave 1. Concerning smoking cigarettes, people who kept only light exercise or sedentary life style at Wave 1 were 1.70 times more likely to be died at Wave 4 than the people who did not smoke at Wave 1. CONCLUSIONS: All demographics and health behaviors at wave 1 had consistently similar OR trends for ADL status to each other except alcohol consumption. Smoking and exercise in health behaviors, and age and gender in demographics at Wave 1 were significant factors associated with ADL group separation at Wave 4.
Keywords: Activities of Daily Living; Alcohol Drinking; Body Mass Index; ethnicity; Exercise; Female; Health Behavior; Humans; Longitudinal Studies; Male; Middle Aged; Risk Factors; Smoking; United States

Postretirement earnings relative to preretirement earnings: gender and racial differences. - Martha N. Ozawa; Hong, Baeg-Eui (J Gerontol Soc Work, 2006)
As the social security program comes under increasing financial pressure in the coming decades, the federal government will encourage elderly people to continue to work. Data from the Social Security Administration indicate that earnings are already a sizable component of retirement income. But there is public concern about how women and minorities will fare economically in this changing policy environment. To what extent can women and minorities keep earning money after they reach retirement age? This article presents the results of a study that investigated the postretirement earnings, relative to the preretirement earnings, of women and minorities, and compared the results with those for men and whites. The major finding, based on regression analyses, was that women's postretirement earnings, relative to their preretirement earnings, were greater than those of men. Furthermore, the regression results indicate that nonwhites' postretirement earnings could not be predicted by their preretirement earnings or by any of the independent variables used in the study, including age, gender, education, marital status, number of children, occupation, and preretirement earnings.
Keywords: Age Factors; Aged; Aged, 80 and over; Data collection; Employment; Female; Humans; Income; Male; Men; Minority Groups; Pensions; Retirement; Salaries and Fringe Benefits; Sex Factors; Social Security; Time Factors; United States; White People; women

Religious influences on preventive health care use in a nationally representative sample of middle-age women. - Benjamins, Maureen Reindl (J Behav Med, 2006)
Despite the many benefits of preventive services, they are often underutilized. Social factors, such as religion, can figure prominently in these discrepancies by either creating barriers or facilitating use. Using data from the Health and Retirement Survey (HRS, 1992-1996), the current study examines the relationship between religious attendance, religious salience, and denomination and three types of female preventive services in a sample of middle-age women (N = 4253). Findings indicate that women who attend religious services more frequently use more mammograms, Pap smears, and self-breast exams. In addition, women belonging to Mainline Protestant or Jewish denominations use certain preventive services more than Evangelical Protestants. Finally, women with higher levels of religious salience are more likely to conduct self-breast exams. These findings add important information to the public health literature concerning factors that influence preventive service use. They also add to the growing field of religion and health research where preventive health care use is emerging as a possible mechanism linking religion to a wide variety of physical health outcomes.
Keywords: Aged; Breast Self-Examination; Female; Health Behavior; Health Status Indicators; Health Surveys; Humans; Mammography; Mass Screening; Middle Aged; Papanicolaou Test; Preventive Health Services; Religion and Medicine; Religion and Psychology; Social Support; Socioeconomic factors; United States; Utilization Review; Vaginal Smears

Retirement patterns from career employment. - Kevin E. Cahill; Michael D. Giandrea; Joseph F. Quinn (Gerontologist, 2006)
PURPOSE: This article investigates how older Americans leave their career jobs and estimates the extent of intermediate labor force activity (bridge jobs) between full-time work on a career job and complete labor-force withdrawal. DESIGN AND METHODS: Using data from the Health and Retirement Study, we explored the work histories and retirement patterns of a cohort of retirees aged 51 to 61 in 1992 during a 10-year period in both cross-sectional and longitudinal contexts. We examined determinants of retirement patterns in a multinomial logistic regression model. RESULTS: We found that a majority of older Americans with career jobs retire gradually, in stages, rather than all at once. We also found that the utilization of bridge jobs was more common among younger respondents, respondents without defined-benefit pension plans, and respondents at both the lower and upper ends of the wage distribution. IMPLICATIONS: Older Americans are now working longer than pre-1980s trends would have predicted. Given concerns about the traditional sources of retirement income (Social Security, employer pensions, and prior savings), older Americans may have to rely more on earnings. This article suggests that many are already doing so by moving to bridge jobs after leaving their career employment.
Keywords: Aged; Aged, 80 and over; Aging; Career Choice; Employment; Female; Health Status; Humans; Income; Male; Middle Aged; Pensions; Retirement; Social Security; United States

The tide to come: elderly health in Latin America and the Caribbean. - Alberto Palloni; Mary McEniry; Rebeca Wong; Pelaez, M. (J Aging Health, 2006)
This article introduces a conjecture and reviews partial evidence about peculiarities in the aging of populations in Latin America and the Caribbean (LAC) that may impact future elderly health status. Using Survey on Health and Well-Being of Elders data (SABE; n = 10,902), the authors estimated effects of early childhood conditions on adult diabetes and heart disease. Using Waaler-type surfaces, the authors obtained expected mortality risks for SABE and also U.S. elderly (Health and Retirement System, n = 12,527). Expected mortality risks using Waaler-type surfaces among elderly in LAC reflected excesses supporting our conjecture. There was partial evidence of a relation between various indicators of early childhood nutritional status (knee height, waist-to-hip ratio) and diabetes and even stronger evidence of a relation between rheumatic fever and adult heart disease. There is some evidence, albeit weak, to suggest that the conjecture regarding elderly health status' connection to early conditions has some merit.
Keywords: Aged; Aged, 80 and over; Caribbean Region; Child; Diabetes Mellitus; Forecasting; Health Status; Heart Diseases; Humans; Latin America; Malnutrition; Middle Aged; Mortality; Nutritional Status; United States

Urban neighborhood context, educational attainment, and cognitive function among older adults. - Richard G Wight; Carol S Aneshensel; Miller-Martinez, Dana; Amanda L. Botticello; Janet R. Cummings; Arun S Karlamangla; Teresa Seeman (Am J Epidemiol, 2006)
Existing research has not addressed the potential impact of neighborhood context--educational attainment of neighbors in particular--on individual-level cognition among older adults. Using hierarchical linear modeling, the authors analyzed data from the 1993 Study of Assets and Health Dynamics Among the Oldest Old (AHEAD), a large, nationally representative sample of US adults born before 1924. Data from participants residing in urban neighborhoods (n = 3,442) were linked with 1990 US Census tract data. Findings indicate that 1) average cognitive function varies significantly across US Census tracts; 2) older adults living in low-education areas fare less well cognitively than those living in high-education areas, net of individual characteristics, including their own education; 3) this association is sustained when controlling for contextual-level median household income; and 4) the effect of individual-level educational attainment differs across neighborhoods of varying educational profiles. Promoting educational attainment among the general population living in disadvantaged neighborhoods may prove cognitively beneficial to its aging residents because it may lead to meliorations in stressful life conditions and coping deficiencies.
Keywords: Aged; Aged, 80 and over; Chi-Square Distribution; Cognition Disorders; Educational Status; Female; Humans; Linear Models; Male; Residence Characteristics; Risk Factors; Socioeconomic factors; United States; Urban Population

Why don't people buy long-term-care insurance? - Cramer, Anne Theisen; Gail A Jensen (J Gerontol B Psychol Sci Soc Sci, 2006)
OBJECTIVES: The objective of this article was to assess the determinants of an individual's decision to purchase long-term-care (LTC) insurance. This article focuses on the decision to purchase a new policy as opposed to renewing an existing policy. This study gave special consideration to the role of policy price, the savings associated with buying a policy now as opposed to later, the purchaser's education, and the purchaser's income. METHODS: Using data from the 2002 Health and Retirement Survey, we estimated logistic regressions to model consumer decisions to purchase LTC insurance. We explored several alternative measures of the price of a policy. RESULTS: Price was a significant determinant in decisions to purchase coverage. The demand for coverage, however, was price inelastic, with elasticities ranging from -0.23 to -0.87, depending on the specification of the model. The education level and income of the purchaser were also important. DISCUSSION: This analysis provides the first estimates of price elasticity of demand for LTC insurance. The finding that demand is very price inelastic suggests that state initiatives that effectively subsidize premiums as a way of stimulating purchases are likely to meet with very limited success in the present environment.
Keywords: Aged; Choice Behavior; Commerce; Decision making; Demography; Female; Humans; Insurance, Health; Long-term Care; Male; Middle Aged; United States

Disparities among older adults in measures of cognitive function by race or ethnicity. - Frank A Sloan; Wang, Jingshu (J Gerontol B Psychol Sci Soc Sci, 2005)
This study examined racial or ethnic differences in cognitive function, cross-sectionally and longitudinally, using survey data from the Asset and Health Dynamics Among the Oldest Old. A version of the Telephone Interview for Cognitive Status (TICS), proxy assessments of cognition, and difficulties in performing daily tasks were assessed. Blacks performed below Whites on the TICS at baseline and on proxy assessments of cognition. TICS score declined with age for Whites and Blacks, with some relative gains for Blacks. At baseline, Blacks more often had difficulties in performing daily tasks, with some increase in difficulties relative to Whites with age. Differences between other groups and Whites were smaller than those between Blacks and Whites.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Black or African American; Case-Control Studies; Cognition; Cognition Disorders; Cross-Sectional Studies; Female; Hispanic or Latino; Humans; Linear Models; Longitudinal Studies; Male; Racial Groups; United States

Health and living arrangements among older Americans: does marriage matter? - Jersey Liang; Brown, Joseph W.; Krause, Neal M.; Mary Beth Ofstedal; Joan M. Bennett (J Aging Health, 2005)
OBJECTIVE: This research examines how physical and mental health influence living arrangements among older Americans and whether these effects differ for married and unmarried persons. METHODS: Data came from the Asset and Health Dynamics Among the Oldest Old study. These two intervals were pooled, and hierarchical multinomial logistic regressions were used to analyze pooled time lags. RESULTS: Functional status and cognitive functioning are significantly associated with living arrangements among those not married. Health conditions exert no significant effects among those married. Given the same functional status, unmarried elders are significantly more likely than their married counterparts to reside with their children or with others. DISCUSSION: These results underscore the critical role of the spouse in influencing living arrangements, providing new evidence supporting the assertion that a spouse is the greatest guarantee of support in old age and the importance of the marriage institution.
Keywords: Adult children; Aged; Demography; Health Status; Humans; Institutionalization; Marital Status; Marriage; Mental Health; Parents; Residence Characteristics; Social Support; Socioeconomic factors; Spouses; United States

Health events and the smoking cessation of middle aged Americans. - Tracy Falba (J Behav Med, 2005)
This study investigates the effect of serious health events including new diagnoses of heart attacks, strokes, cancers, chronic lung disease, chronic heart failure, diabetes, and heart disease on future smoking status up to 6 years postevent. Data come from the Health and Retirement Study, a nationally representative longitudinal survey of Americans aged 51-61 in 1991, followed every 2 years from 1992 to 1998. Smoking status is evaluated at each of three follow-ups, (1994, 1996, and 1998) as a function of health events between each of the four waves. Acute and chronic health events are associated with much lower likelihood of smoking both in the wave immediately following the event and up to 6 years later. However, future events do not retrospectively predict past cessation. In sum, serious health events have substantial impacts on cessation rates of older smokers. Notably, these effects persist for as much as 6 years after a health event.
Keywords: Diabetes Mellitus; Female; Health Behavior; Health Status; Heart Failure; Humans; Logistic Models; Longitudinal Studies; Male; Middle Aged; Smoking; Smoking cessation; Social Environment; Socioeconomic factors; United States

Health insurance coverage during the years preceding medicare eligibility. - David W. Baker; Joseph J Sudano (Arch Intern Med, 2005)
BACKGROUND: Adults in late middle age who lack health insurance are more likely to die or experience a decline in their overall health. Because most estimates of the uninsured are cross-sectional, the true number of individuals whose health is at risk from being uninsured is unclear. METHODS: We analyzed a nationally representative sample of 6065 US adults 51 to 57 years old who were interviewed in 1992, 1994, 1996, 1998, and 2000 as part of the Health and Retirement Study. Insurance coverage was determined at the time of each interview and classified as private, public, or uninsured. Longitudinal data were used to determine the proportion of individuals who were uninsured at any interview during the 8-year study period. RESULTS: The proportion of participants who were uninsured at the time of the 1992, 1994, 1996, 1998, and 2000 interviews was 14.3%, 10.8%, 9.7%, 8.8%, and 8.2%, respectively. People frequently transitioned between having insurance and being uninsured. As a result, despite the declining prevalence of being uninsured, the percentage who were uninsured at least once during the 8-year period rose to 23.3% by 2000; few participants (2.6%) were continuously uninsured. Only 60.1% of participants were continuously enrolled in private insurance across all 5 interviews. CONCLUSIONS: The proportion of US adults in late middle age at risk from being uninsured over a 10-year follow-up period was 2 to 3 times higher than cross-sectional estimates. At least one quarter of older adults will be uninsured at some point during the years preceding eligibility for Medicare.
Keywords: Age Factors; Black or African American; Cohort Studies; Female; Health Status; Hispanic or Latino; Humans; Insurance Coverage; Insurance, Health; Male; Medically Uninsured; Middle Aged; Sex Factors; Socioeconomic factors; United States; White People

Heavy alcohol use and marital dissolution in the USA. - Ostermann, Jan; Frank A Sloan; Donald H. Taylor Jr. (Soc Sci Med, 2005)
Using the first five waves of the US Health and Retirement Study, a nationally representative survey of middle-aged persons in the USA conducted between 1992 and 2000, we assessed the association between alcohol consumption and separation and divorce (combined as divorced in the analysis) for 4589 married couples during up to four repeated 2-yr follow-up periods. We found that drinking status was positively correlated between spouses. The correlations did not increase over the follow-up period. Discrepancies in alcohol consumption between spouses were more closely related to the probability of subsequent divorce than consumption levels per se. Couples with two abstainers and couples with two heavy drinkers had the lowest rates of divorce. Couples with one heavy drinker were most likely to divorce. Controlling for current consumption levels, a history of problem drinking by either spouse was not significantly associated with an increased probability of divorce. Our findings on alcohol use and marital dissolution were highly robust in alternative specifications.
Keywords: Alcohol Drinking; Alcohol-Related Disorders; Divorce; Female; Health Status; Humans; Male; Middle Aged; Social Class; United States

The impact of diabetes on employment and work productivity. - Tunceli, Kaan; Cathy J. Bradley; Nerenz, David; L Keoki Williams; Pladevall, Manel; Elston, Lafata J. (Diabetes Care, 2005)
OBJECTIVE: The purpose of this study was to longitudinally examine the effect of diabetes on labor market outcomes. RESEARCH DESIGN AND METHODS: Using secondary data from the first two waves (1992 and 1994) of the Health and Retirement Study, we identified 7,055 employed respondents (51-61 years of age), 490 of whom reported having diabetes in wave 1. We estimated the effect of diabetes in wave 1 on the probability of working in wave 2 using probit regression. For those working in wave 2, we modeled the relationships between diabetic status in wave 1 and the change in hours worked and work-loss days using ordinary least-squares regressions and modeled the presence of health-related work limitations using probit regression. All models control for health status and job characteristics and are estimated separately by sex. RESULTS: Among individuals with diabetes, the absolute probability of working was 4.4 percentage points less for women and 7.1 percentage points less for men relative to that of their counterparts without diabetes. Change in weekly hours worked was not statistically significantly associated with diabetes. Women with diabetes had 2 more work-loss days per year compared with women without diabetes. Compared with individuals without diabetes, men and women with diabetes were 5.4 and 6 percentage points (absolute increase), respectively, more likely to have work limitations. CONCLUSIONS: This article provides evidence that diabetes affects patients, employers, and society not only by reducing employment but also by contributing to work loss and health-related work limitations for those who remain employed.
Keywords: Diabetes Mellitus; Efficiency; Employment; Female; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Multivariate Analysis; Odds Ratio; United States; Work

The impact of obesity on active life expectancy in older American men and women. - Sandra L Reynolds; Saito, Yasuhiko; Eileen M. Crimmins (Gerontologist, 2005)
PURPOSE: The purpose of this article is to estimate the effect of obesity on both the length of life and length of nondisabled life for older Americans. DESIGN AND METHODS: Using data from the first 3 waves of the Asset and Health Dynamics Among the Oldest Old (AHEAD) survey, this article develops estimates of total, active, and disabled life expectancy for obese and nonobese older men and women. We used the Interpolation of Markov Chains (IMaCh) method to estimate the average number of years obese and nonobese older persons can expect to live with and without activity of daily living (ADL) disability. RESULTS: Our findings indicate that obesity has little effect on life expectancy in adults aged 70 years and older. However, the obese are more likely to become disabled. This means that obese older adults live both more years and a higher proportion of their remaining lives disabled. IMPLICATIONS: The lack of significant differences in life expectancy by obesity status among the old suggests that obesity-related death is less of a concern than disability in this age range. Given steady increases in obesity among Americans at all ages, future disability rates may be higher than anticipated among older U.S. adults. In order to reduce disability among future cohorts of older adults, more research is needed on the causes and treatment of obesity and evaluations done on interventions to accomplish and maintain weight loss.
Keywords: Activities of Daily Living; Aged; Female; Health Status; Health Surveys; Humans; Life Expectancy; Life Tables; Logistic Models; Male; Markov chains; Obesity; Risk Factors; United States

The impact of own and spouse's urinary incontinence on depressive symptoms. - Fultz, Nancy H.; Kristi Rahrig Jenkins; Truls Ostbye; Donald H. Taylor Jr.; Mohammed U Kabeto; Kenneth M. Langa (Soc Sci Med, 2005)
This study investigated the impact of own and spouse's urinary incontinence on depressive symptoms. Attention was paid to the possibility that gender and caregiving might be important factors in understanding significant effects. We used negative binomial regression to analyze survey data for 9974 middle-aged and older respondents to the Health and Retirement Study in the USA. Results supported the hypothesis that the respondents' own urinary incontinence was associated with depressive symptoms (unadj. IRR = 1.73, 95% CIs = 1.53, 1.95 for men; unadj. IRR = 1.50, 95% CIs = 1.38, 1.63 for women). Controlling sociodemographic and health variables reduced this relationship, but it remained statistically significant for both men and women. Having an incontinent wife put men at greater risk for depressive symptoms (unadj. IRR = 1.13, 95% CIs = 1.02, 1.25), although this relation became nonsignificant with the addition of control variables. No relation between women's depressive symptoms and husbands' (in)continence status was found. Caregiving was not a significant variable in the adjusted analyses, but spouses' depressive symptoms emerged as a significant predictor of the respondents' own depressive symptoms. Health care providers must be sensitive to the emotional impact of urinary incontinence. Our findings also suggest the importance of considering the patient's mental health within a wider context, particularly including the physical and mental health of the patient's spouse.
Keywords: Aged; Caregivers; Cohort Studies; depression; Female; Humans; Male; Middle Aged; United States; Urinary incontinence

Labor market, financial, insurance and disability outcomes among near elderly Americans with depression and pain. - Tian, Haijun; Robinson, Rebecca L.; Sturm, Roland (J Ment Health Policy Econ, 2005)
BACKGROUND: The economic burden of depression has been documented, but the role of comorbid conditions is unclear. Depression and comorbid pain are particularly common, are associated with worse clinical outcomes and require different care than "pure'' depression. Does this comorbidity account for a large share of the adverse social outcomes attributed to depression? AIMS OF STUDY: We analyzed the relationship between depression and comorbid pain, and labor market, financial, insurance and disability outcomes among Americans aged 55-65. METHODS: Cross-sectional data were used from Wave 3 of the Health and Retirement Survey, a nationally representative sample of individuals aged 55-65 surveyed in 1996. Multivariate regression analyses, controlling for socio-demographics and chronic health conditions, estimated the associations between depression and pain, and economic outcomes. Outcomes included: employment and retirement status, household income, total medical expenditures, government health insurance, social security, limitations in activities of daily living (ADLs), and health limitations affecting work. Primary explanatory variables included the presence of severe pain, mild/moderate pain, or absence of pain, with or without depression. RESULTS: Compared to depression alone, depression and comorbid pain was associated with worse labor market (non-employment, retirement), financial (total medical expenditures), insurance (government insurance, social security) and disability outcomes (limitations in ADLs, health limitations affecting work), after covariate adjustment (p <or= 0.01, except retirement with p < 0.1). Findings were even more disparate as level of pain severity increased. The simulated results showed that the magnitudes of the adverse effects were attributed disproportionally to individuals with comorbid pain and depression versus "pure'' depression. Of those with depression, 51% had comorbid pain. Yet, this subgroup of depressed individuals accounted for 59% of those not employed, 61% of those with government health insurance, 79% of those with limitations in ADLs, and 72% of those with health limitations affecting work. DISCUSSION AND LIMITATION: Depression with comorbid pain, not depression alone was responsible for a large part of the higher economic burden associated with depression. The study is limited by self-reported measures of pain, depression, and outcomes. It is cross-sectional and cannot identify causal effects of depression with pain. These findings may not be generalizable to other age groups. IMPLICATIONS FOR HEALTH CARE PROVISION AND USE: The depressed with comorbid pain appear to experience greater burden through increased costs and worse functioning and may require different management than those with depression alone. The depressed with comorbid pain may benefit from treatment practices and guidelines that address the duality of these conditions throughout the process of care. IMPLICATION FOR HEALTH POLICIES: The depressed with comorbid pain were more likely to receive government support than depression alone. Given the central role of employer-sponsored health insurance in the U.S., they may have worse access to health care because they leave employment or retire earlier. With the evolving state of Medicare, broad formulary access to mental health treatments might be considered. IMPLICATIONS FOR FURTHER RESEARCH: Further research should focus on causality of depression and comorbid pain on economic outcomes. Depression research should consider the heterogeneity of this disorder in outcomes assessment.
Keywords: Aged; Cost of Illness; Cross-Sectional Studies; depression; Employment; Female; Humans; Male; Middle Aged; pain; United States

Life course pathways to adult-onset diabetes. - Best, Latrica E.; Mark D Hayward; Mira M Hidajat (Soc Biol, 2005)
Early life conditions, such as socioeconomic status (SES) and health, have the potential to set in motion multiple and reinforcing pathways that shape both the prevalence and onset of diabetes among older adults. Using data from the Health and Retirement Study (1998-2002) for persons age 51 years and older, we investigated the core mediating mechanisms linking early life conditions with diabetes prevalence in 1998 and onset over a 4-year follow-up period, focusing on adult achievement processes and obesity as key mechanisms. We found that father's education is negatively associated with diabetes prevalence for older men and women. However, no markers of early life SES are directly associated with older men's and women's onset of diabetes, and the negative effects of adult SES on diabetes onset pertain only to women. Early life health affects the onset of diabetes among women--but not the prevalence--and no evidence of this association was found for men. We found no evidence that obesity is an important mechanism connecting either early life or adult SES with diabetes development in men or women. We speculate that early life SES may accelerate the development of diabetes at younger ages, and that the pathways linking life course SES, early life health, and diabetes are partly gender-specific and biological in nature.
Keywords: Aged; Child; Diabetes Mellitus, Type 2; Family Health; Female; Follow-Up Studies; Humans; Life Style; Likelihood Functions; Logistic Models; Male; Middle Aged; Obesity; Poverty; Risk Factors; Social Class; United States

Lifetime earnings, social security benefits, and the adequacy of retirement wealth accumulation. - Engen, Eric M.; William G. Gale; Cori E. Uccello (Soc Secur Bull, 2005)
Keywords: Adult; Humans; Income; Middle Aged; Models, Econometric; Pensions; Retirement; Social Security; United States

Men who work at age 70 or older. - Martha N. Ozawa; Terry Y S Lum (J Gerontol Soc Work, 2005)
The federal policy on older workers has shifted from the encouragement of early withdrawal from the labor force to the encouragement of continuous participation in the labor force. In this light, it is instructive to investigate the backgrounds of elderly people who work at age 70 or older. This article presents the findings of a study, using data from the 1993 Asset and Health Dynamics of the Oldest Old Study, that investigated the effects of health, economic conditions (net worth, employer-provided pensions, and supplemental medical insurance coverage), education, and spouse's work status on the probability of working among men aged 70 or older. The study addressed the probability of working, the probability of working fulltime and of working part-time, and the probability of being self-employed and of being employed by others. Implications for policy are discussed.
Keywords: Aged; Employment; Health Status; Humans; Logistic Models; Male; Multivariate Analysis; Public Policy; Socioeconomic factors; United States

Net worth predicts symptom burden at the end of life. - Maria J Silveira; Mohammed U Kabeto; Kenneth M. Langa (J Palliat Med, 2005)
OBJECTIVES: To explore the predictors of symptom burden at the end of life. DESIGN: Observational, secondary analysis of Health and Retirement Study (HRS) data. SETTING: USA. PARTICIPANTS: Two thousand six hundred four deceased, older adults. METHODS: Multivariate Poisson and logistic regression to explore the relationship between sociodemographic and clinical factors with symptoms. RESULTS: Fatigue, pain, dyspnea, depression, and anorexia were common and severe; 58% of participants experienced more than 3 of these during their last year of life. Sociodemographic and clinical factors were associated with the number of symptoms as well as the presence of pain, depression, and dyspnea alone. Decedents in the highest quartile of net worth had fewer symptoms (incident rate ratio [IRR] 0.90, confidence interval [CI] 0.85-0.96) and less pain (odds ratio [OR] 0.66, CI 0.51-0.85) than comparisons did. Patients with cancer experienced more pain (OR 2.02, CI 1.62-2.53) and depression (OR 1.31, CI 1.07-1.61). Patients experienced more depression (OR 2.37, CI 1.85-3.03) and dyspnea (OR 1.40, CI 1.09-1.78). LIMITATION: Use of proxy reports for primary data. CONCLUSION: Older Americans experience a large symptom burden in the last year of life, largely with treatable symptoms such as pain, dyspnea, and depression. The adequacy of symptom control relates to clinical factors as well as net worth. This association between symptoms and wealth suggests that access to health care and other social services beyond those covered by Medicare may be important in decreasing symptom burden at the end of life.
Keywords: Aged; Aged, 80 and over; Data collection; Female; Humans; Logistic Models; Male; Severity of Illness Index; Social Class; Terminally Ill; United States

Physical and mental health status of older long-term cancer survivors. - Nancy L. Keating; Norredam, Marie; Landrum, Mary Beth; Haiden A. Huskamp; Meara, Ellen (J Am Geriatr Soc, 2005)
OBJECTIVES: To assess the physical and mental health status of older long-term cancer survivors. DESIGN: Cohort study using propensity score methods to control for baseline differences between cancer survivors and controls. SETTING: General community population in the United States. PARTICIPANTS: Nine hundred sixty-four cancer patients who had survived for more than 4 years and 14,333 control patients who had never had cancer from a population-based sample of Americans aged 55 and older responding to the 2002 Health and Retirement Study. MEASUREMENTS: Medical conditions, symptoms, health behaviors, health status, mobility, activities of daily living, mental health diagnoses, self-rated memory, depressive symptoms, cognitive function, and self-reported life expectancy. RESULTS: Cancer survivors reported higher rates of lung disease (13.9% vs 9.6%; P=.001), heart condition (29.3% vs 22.9%; P<.001), arthritis (69.4% vs 59.4%; P<.001), incontinence (26.6% vs 19.7%; P=.001), frequent pain (36.4% vs 29.4%; P=.005), and obesity (27.0% vs 24.2%; P=.001) than individuals without cancer but lower rates of smoking (12.0% vs 14.8%; P=.03). Cancer survivors were less likely than persons without cancer to report excellent or very good health status (37.2% vs 44.6%; P<.001) and had more mobility (P<.001) and activity of daily living (P=.01) limitations. Cancer survivors did not differ from persons without cancer in rates of depression or cognitive function (both P>.2) but were less optimistic about their life expectancy (P=.004). CONCLUSION: The physical health status of older long-term cancer survivors is somewhat worse than that of comparable persons who have never had cancer, but they have surprisingly similar mental health status. Future research is needed to understand factors contributing to poorer health status and identify patients at highest risk of long-term cancer-related problems.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Chronic disease; Cohort Studies; Female; Health Behavior; Health Status; Humans; Logistic Models; Male; Mental Health; Middle Aged; Neoplasms; Survivors; United States

Predictors of perceptions of involuntary retirement. - Maximiliane E Szinovacz; Adam Davey (Gerontologist, 2005)
PURPOSE: Retirement is often treated as a voluntary transition, yet selected circumstances can restrict choice in retirement decision processes. We investigated conditions under which retirees perceive their retirement as "forced" rather than "wanted." METHODS: Analyses relied on Waves 1-4 of the Health and Retirement Survey (N=1,160; 572 men and 588 women). Logistic regression models estimated the effects of background factors, choice and restricted choice conditions, and retirement contexts on perceptions of forced retirement. RESULTS: Nearly one third of older workers perceived their retirement as forced. Such forced retirement reflects restricted choice through health limitations, job displacement, and care obligations. Other predictors include marital status, race, assets, benefits, job tenure, and off-time retirement. IMPLICATIONS: Future research should establish personal and policy implications of forced retirement. Programs are needed to help older workers forced into retirement find alternative employment opportunities and to reduce the conditions leading to forced retirement.
Keywords: Activities of Daily Living; Choice Behavior; Demography; Humans; Retirement; Social Perception; Socioeconomic factors; United States

Processes of cumulative adversity: childhood disadvantage and increased risk of heart attack across the life course. - Angela M O'Rand; Jenifer Hamil-Luker (J Gerontol B Psychol Sci Soc Sci, 2005)
OBJECTIVES: This article examines how processes of cumulative adversity shape heart attack risk trajectories across the life course. METHODS: Our sample includes 9,760 Health and Retirement Study respondents born between 1931 and 1941. Using self-reported retrospective measures of respondents' early background, we first identify three latent classes with differential exposure to childhood disadvantage. Intervening covariates associated with educational attainment, employment status, income attainment, marital history, and health behaviors are added to capture sequential processes of adversity. Final latent-class cluster models estimate the cumulative impact of these covariates on three different heart attack risk trajectories between 1992 and 2002: high, increasing, and low. RESULTS: Early disadvantage and childhood illness have severe enduring effects and increase the risk for heart attack. Adult pathways, however, differentially influence trajectories of heart attack risk and mediate the effects of early disadvantage. DISCUSSION: Findings suggest that future research should consider how processes of cumulative adversity initiated in childhood influence health outcomes in older ages.
Keywords: Child; Cluster Analysis; Family Characteristics; Female; Human Development; Humans; Likelihood Functions; Male; Middle Aged; Myocardial Infarction; Psychosocial Deprivation; Regression Analysis; Risk Factors; Social Environment; Socioeconomic factors; United States

Racial differences in activities of daily living limitation onset in older adults with arthritis: a national cohort study. - Shih, Vivian C.; Song, Jing; Rowland W Chang; Dorothy D Dunlop (Arch Phys Med Rehabil, 2005)
OBJECTIVE: To investigate factors that predict the onset of limitations in activities of daily living (ADLs) in adults 65 years old or older who have arthritis, in order to develop public health programs for minorities (African and Hispanic Americans) and white Americans. DESIGN: Longitudinal cohort study. SETTING: National probability sample. PARTICIPANTS: Older adults with arthritis (N=3541) who participated in the 1998 and 2000 Health and Retirement Study interviews and who had no baseline ADL limitations. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURE: Onset of ADL limitations was identified from reports of 1 or more ADL task limitations at 2-year follow-up. RESULTS: Onset is most frequent among African Americans (24.4%), followed by Hispanics (22.2%), and whites (16.9%). Race specific multivariate analysis showed that the strongest risk factor predicting onset of limitations across all racial and ethnic groups is physical limitations. Low household income was significant for older minorities but not for whites. Comorbid cardiovascular disease was a unique multivariate risk factor among African Americans. CONCLUSIONS: Physical limitation is a strong risk factor for ADL limitation onset that is shared by all racial and ethnic groups. Early identification and treatment of physical limitations may prevent the onset of ADL limitations and thus improve quality of life. Race specific public health interventions should be considered to reduce the development of ADL limitations among older adults with arthritis.
Keywords: Activities of Daily Living; Aged; Arthritis; Black or African American; Female; Geriatric Assessment; Health Behavior; Health Services Needs and Demand; Hispanic or Latino; Humans; Longitudinal Studies; Male; Predictive Value of Tests; Prospective Studies; Risk Factors; United States; White People

Setting eligibility criteria for a care-coordination benefit. - Christine T Cigolle; Kenneth M. Langa; Mohammed U Kabeto; Caroline S Blaum (J Am Geriatr Soc, 2005)
OBJECTIVES: To examine different clinically relevant eligibility criteria sets to determine how they differ in numbers and characteristics of individuals served. DESIGN: Cross-sectional analysis of the 2000 wave of the Health and Retirement Study (HRS), a nationally representative longitudinal health interview survey of adults aged 50 and older. SETTING: Population-based cohort of community-dwelling older adults, subset of an ongoing longitudinal health interview survey. PARTICIPANTS: Adults aged 65 and older who were respondents in the 2000 wave of the HRS (n=10,640, representing approximately 33.6 million Medicare beneficiaries). MEASUREMENTS: Three clinical criteria sets were examined that included different combinations of medical conditions, cognitive impairment, and activity of daily living/instrumental activity of daily living (ADL/IADL) dependency. RESULTS: A small portion of Medicare beneficiaries (1.3-5.8%) would be eligible for care coordination, depending on the criteria set chosen. A criteria set recently proposed by Congress (at least four severe complex medical conditions and one ADL or IADL dependency) would apply to 427,000 adults aged 65 and older in the United States. Criteria emphasizing cognitive impairment would serve an older population. CONCLUSION: Several criteria sets for a Medicare care-coordination benefit are clinically reasonable, but different definitions of eligibility would serve different numbers and population groups of older adults.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Case Management; Chronic disease; Cognition Disorders; Comorbidity; Cross-Sectional Studies; Disability Evaluation; Disease Management; Eligibility Determination; Female; Geriatric Assessment; Health Surveys; Humans; Longitudinal Studies; Male; Medicare; Middle Aged; Retirement; United States

The significance of nonmarital cohabitation: marital status and mental health benefits among middle-aged and older adults. - Susan L. Brown; Jennifer R. Bulanda; Lee, Gary R. (J Gerontol B Psychol Sci Soc Sci, 2005)
OBJECTIVES: According to the 2000 Census, about 1.2 million persons over age 50 are currently cohabiting. Do these unmarried cohabiting partnerships provide adults with mental health benefits that are similar to those enjoyed by marrieds? We extended prior work on marital status and depression by including cohabitation in our conceptualization of marital status. METHODS: We used data from the 1998 Health and Retirement Study (N = 18,598) to examine the relationship between marital status and depressive symptoms among adults over age 50. We also examined gender differences in this association. RESULTS: We found that cohabitors report more depressive symptoms, on average, than do marrieds, net of economic resources, social support, and physical health. Additional analyses revealed that only among men do cohabitors report significantly higher depression scores. Cohabiting and married women as well as cohabiting men experience similar levels of depression, and all of these groups report levels that are significantly higher than married men's. DISCUSSION: Our findings demonstrate the importance of accounting for nontraditional living arrangements among persons aged 50 and older. Cohabitation appears to be more consequential for men's than women's depressive symptoms.
Keywords: Aged; depression; Female; Humans; Insurance Benefits; Male; Marital Status; Mental Health Services; Middle Aged; Sexual Partners; Social Support; United States

Social status and risky health behaviors: results from the health and retirement study. - Linda A. Wray; Duane F. Alwin; Ryan J McCammon (J Gerontol B Psychol Sci Soc Sci, 2005)
OBJECTIVES: We focus on a hypothesized mechanism that may underlie the well-documented link between social status and health-behavioral health risks. METHODS: We use longitudinal data from representative samples of 6,106 middle-aged and 3,636 older adults from the Health and Retirement Study to examine the relationships between social status-including early life social status (e.g., parental schooling), ascribed social status (e.g., sex, race-ethnicity), and achieved social status (e.g., schooling, economic resources)-and behavioral health risks (e.g., weight, smoking, drinking, physical activity) to (1) assess how early life and ascribed social statuses are linked to behavioral health risks, (2) investigate the role of achieved factors in behavioral health risks, (3) test whether achieved status explains the contributions of early life and ascribed status, and (4) examine whether the social status and health risk relationships differ at midlife and older age. RESULTS: We find that early life, achieved, and ascribed social statuses strongly predict behavioral health risks, although the effects are stronger in midlife than they are in older age. DISCUSSION: Ascribed social statuses (and interactions of sex and race-ethnicity), which are important predictors of behavioral health risks even net of early life and achieved social status, should be explored in future research.
Keywords: Aged; Aging; Alcohol Drinking; Body Weight; Exercise; Female; Health Behavior; Humans; Life Style; Likelihood Functions; Logistic Models; Longitudinal Studies; Male; Middle Aged; Smoking; Social Class; United States

Supplemental private health insurance and depressive symptoms in older married couples. - Min, Meeyoung O.; Aloen L. Townsend; Baila Miller; Rovine, Michael J. (Int J Aging Hum Dev, 2005)
Stress process theory is applied to examine lack of supplemental private health insurance as a risk factor for depressive symptomatology among older married couples covered by Medicare. Dyadic data from 130 African-American couples and 1,429 White couples in the 1993 Asset and Health Dynamics Among the Oldest-Old Survey were analyzed using hierarchical generalized linear modeling. Lack of supplemental insurance is operationalized at the household level in terms of neither spouse covered, one spouse covered, or both spouses covered. Controlling for covariates at both individual and couple levels, supplemental insurance has significant impact on depression, but the pattern differs by race. White couples report the highest depression when neither spouse is covered by private health insurance; African-American couples report the highest depression when only one spouse is covered. Results suggest lack of supplemental private health insurance coverage is a stressor that significantly affects depressive symptoms.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Black People; Chi-Square Distribution; depression; Female; Humans; Insurance Coverage; Insurance, Health; Linear Models; Male; Risk Factors; Spouses; United States; White People

Understanding the racial and ethnic differences in caregiving arrangements. - Terry Y S Lum (J Gerontol Soc Work, 2005)
In this study, the relative importance of family/household structure, socioeconomic status, and culture is examined, and their connection to racial and ethnic variations in caregiving networks is explored. Each of these three domains is seen as contributing to the race/ethnic variations in caregiving arrangements.
Keywords: Aged; Caregivers; ethnicity; Family Characteristics; Female; Frail Elderly; Humans; Logistic Models; Male; Multivariate Analysis; Social work; Socioeconomic factors; United States

Use of complementary medicine in older Americans: results from the Health and Retirement Study. - Ness, Jose; Dominic J Cirillo; David R Weir; Nisly, Nicole L.; Robert B Wallace (Gerontologist, 2005)
PURPOSE: The correlates of complementary and alternative medicine (CAM) utilization among elders have not been fully investigated. This study was designed to identify such correlates in a large sample of older adults, thus generating new data relevant to consumer education, medical training, and health practice and policy. DESIGN AND METHODS: A subsample from the 2000 Wave of the Health and Retirement Study (n = 1,099) aged 52 or older were surveyed regarding use of CAM (chiropractic, alternative practitioners, dietary and herbal supplements, and personal practices). RESULTS: Of respondents over 65 years of age, 88% used CAM, with dietary supplements and chiropractic most commonly reported (65% and 46%, respectively). Users of alternate practitioners and dietary supplements reported having more out-of-pocket expenses on health than nonusers of these modalities. Age correlated positively with use of dietary supplements and personal practices and inversely with alternative practitioner use. Men reported less CAM use than women, except for chiropractic and personal practices. Blacks and Hispanics used fewer dietary supplements and less chiropractic, but they reported more personal practices than Whites. Advanced education correlated with fewer chiropractic visits and more dietary and herbal supplement and personal practices use. Higher income, functional impairment, alcohol use, and frequent physician visits correlated with more alternative practitioner use. There was no association between CAM and number of chronic diseases. IMPLICATIONS: The magnitude and patterns of CAM use among elders lend considerable importance to this field in public health policy making and suggest a need for further epidemiological research and ongoing awareness efforts for both patients and providers.
Keywords: Activities of Daily Living; Aged; Chi-Square Distribution; Complementary Therapies; Female; Humans; Male; Middle Aged; Regression Analysis; Surveys and Questionnaires; United States

A variables associated with occupational and physical therapy stroke rehabilitation utilization and outcomes. - Chad Cook; Stickley, Lois; Ramey, Kevin; Knotts, Valerie J. (J Allied Health, 2005)
Many studies have reported the benefits of a comprehensive stroke team including occupational therapy/physical therapy (OT/PT) services; however, factors associated with access to these services are less known. This study used a subsample of the Health and Retirement Study database, a cross-sectional survey of more than 11,126 Americans aged 65 to 106 years within the contiguous United States. The purposes of this study were to determine the associational factors that contribute to attending OT/PT and determine if attending OT/PT leads to a reduced report of stroke-related problems. The findings indicated that fewer than 10% of stroke survivors in a noninstitutionalized, community-based setting were currently accessing OT/PT. Additionally, access to OT/PT services was highly associated with report of having an attending physician, report of stroke-related weakness, higher monthly income, and older age. The increased odds of reported continued problems associated with a past stroke were associated with failure to access OT/PT services, lower monthly income, Hispanic culture, and age. OT/PT services were typically provided to patients who reported a higher level of physical dysfunction. Despite the greater degree of severity, OT/PT intervention led to reports of lower levels of disability and problems over time.
Keywords: Aged; Aged, 80 and over; Cross-Sectional Studies; Disability Evaluation; Female; Health Services Accessibility; Humans; Male; Occupational therapy; Physical Therapy Modalities; Risk Factors; Socioeconomic factors; Stroke Rehabilitation; United States

When is baseline adjustment useful in analyses of change? An example with education and cognitive change. - M. Maria Glymour; Weuve, Jennifer; Lisa F Berkman; Ichiro Kawachi; Robins, James M. (Am J Epidemiol, 2005)
In research on the determinants of change in health status, a crucial analytic decision is whether to adjust for baseline health status. In this paper, the authors examine the consequences of baseline adjustment, using for illustration the question of the effect of educational attainment on change in cognitive function in old age. With data from the US-based Assets and Health Dynamics Among the Oldest Old survey (n = 5,726; born before 1924), they show that adjustment for baseline cognitive test score substantially inflates regression coefficient estimates for the effect of schooling on change in cognitive test scores compared with models without baseline adjustment. To explain this finding, they consider various plausible assumptions about relations among variables. Each set of assumptions is represented by a causal diagram. The authors apply simple rules for assessing causal diagrams to demonstrate that, in many plausible situations, baseline adjustment induces a spurious statistical association between education and change in cognitive score. More generally, when exposures are associated with baseline health status, this bias can arise if change in health status preceded baseline assessment or if the dependent variable measurement is unreliable or unstable. In some cases, change-score analyses without baseline adjustment provide unbiased causal effect estimates when baseline-adjusted estimates are biased.
Keywords: Age Factors; Aged; Bias; Cognition Disorders; Educational Status; Epidemiologic Methods; Female; Health Status; Humans; Longitudinal Studies; Male; Models, Statistical; Neuropsychological tests; Regression Analysis; United States

Who foregoes survivor protection in employer-sponsored pension annuities? - Richard W. Johnson; Cori E. Uccello; Joshua H. Goldwyn (Gerontologist, 2005)
PURPOSE: Retirees in traditional pension plans must generally choose between single life annuities, which provide regular payments until death, and joint and survivor annuities, which pay less each month but continue to make payments to the spouse after the death of the retired worker. This article examines the payout decision and measures the share of married retirees with pension annuities who forego survivor protection. DESIGN AND METHODS: The analysis consists of a probit model of the pension payout decision, based on data from the 1992-2000 waves of the Health and Retirement Study. RESULTS: More than one quarter (28%) of married men and two thirds of married women receiving employer-sponsored retirement annuities declined survivor protection. Men with small pensions and limited household wealth, men in better health than their spouses, and men whose spouses have pension coverage from their own employers are more likely than other men to reject survivor protection. IMPLICATIONS: Most workers appear to make payout decisions by rationally balancing the costs and benefits of each type of annuity, suggesting that existing measures to encourage joint and survivor annuities are adequate. However, the growth in 401(k) plans, which are generally not covered by existing laws protecting spousal pension rights, may leave widows vulnerable.
Keywords: Female; Humans; Male; Multivariate Analysis; Pensions; Socioeconomic factors; Spouses; United States

Body mass index, physical activity, and the risk of decline in overall health and physical functioning in late middle age. - Xiaoxing He; David W. Baker (Am J Public Health, 2004)
OBJECTIVES: We examined the relation between body mass index, exercise, overall health, and physical functioning. METHODS: We studied 7867 adults aged 51 to 61 years in 1992 to 1996. Adjusted relative risks for health decline and new physical difficulties were determined with logistic regression. RESULTS: Overweight and obesity were independently associated with health decline (adjusted relative risk [ARR] = 1.29 and 1.36) and development of a new physical difficulty (ARR = 1.27 and 1.45). Regular exercise significantly reduced the risk of health decline and development of a new physical difficulty, even among obese individuals. CONCLUSIONS: Maintaining ideal body weight is important in preventing decline in overall health and physical functioning. However, regular exercise can reduce the risk of health decline even among individuals who cannot achieve ideal weight.
Keywords: Attitude to Health; Body Mass Index; Female; Health Status; Humans; Logistic Models; Male; Middle Aged; Motor Activity; Obesity; Quality of Life; Risk Assessment; Risk Factors; Risk Reduction Behavior; Self Care; United States

Changes in weight among a nationally representative cohort of adults aged 51 to 61, 1992 to 2000. - Xiaoxing He; David W. Baker (Am J Prev Med, 2004)
BACKGROUND: Few studies have examined patterns and predictors of changes in body weight among adults in late middle age. METHODS: Prospective cohort study of 7391 community-dwelling U.S. adults aged 51 to 61 years at baseline (1992), using publicly available data files from the 1992, 1994, 1996, 1998, and 2000 Health and Retirement Survey interviews. Changes in weight and body mass index (BMI) were examined for different racial/ethnic groups of men and women. The predictors of changes in body weight and BMI were determined using gender-specific linear regression. RESULTS: Mean body weight and BMI increased in both genders and all ethnic groups. The mean weight gain was higher for women (1.67 kg, 95% confidence interval [CI]=1.34-1.99) than for men (1.43 kg, 95% CI=1.17-1.68). White men and women had the lowest baseline BMI but tended to gain more weight than other racial/ethnic groups. In multivariate analyses, individuals who were older or had higher baseline weight showed less weight gain. Men were less likely to gain weight if their self-reported overall health at baseline was poor compared to those in excellent health. Regular light or vigorous recreational activities and work-related activities were not associated with less weight gain. Race, education, and income were not associated with weight gain in multivariate analyses. CONCLUSIONS: All population subgroups are at risk for weight gain. Public health messages should target diverse populations. The current levels of physical activity attained by this population do not appear to protect against weight gain.
Keywords: Body Mass Index; Body Weight; Female; Health Surveys; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; Motor Activity; Multivariate Analysis; Prospective Studies; Racial Groups; Sex Factors; United States

Cognitive deficits and the course of major depression in a cohort of middle-aged and older community-dwelling adults. - Ramin Mojtabai; Mark Olfson (J Am Geriatr Soc, 2004)
OBJECTIVES: To examine associations between cognitive deficits and persistent significant depressive symptoms at baseline and 2- and 4-year follow-ups in a sample of community-dwelling middle-aged and older adults. DESIGN: Prospective cohort study. SETTING: A U.S. national prospective cohort study of middle-aged and older adults, the Health and Retirement Study. PARTICIPANTS: A sample of 661 participants of the 1996 wave of the Health and Retirement Study who met criteria for 12-month Diagnostic and Statistical Manual of Mental Disorders, Third Edition, Revised major depression (MD). MEASUREMENTS: MD was assessed using the World Health Organization Composite International Diagnostic Interview-Short Form. Persistent significant depressive symptoms were assessed using an eight-item version of the Center for Epidemiological Studies Depression scale. RESULTS: Cognitive deficits were associated with persistent significant depressive symptoms at follow-up. In a latent state-trait analysis, two stable and strongly correlated traits best explained variations in cognitive functioning and depressive symptoms across assessment points. CONCLUSION: Trait-like cognitive deficits commonly complicate the course of MD in community-dwelling middle-aged and older adults and may help to explain the persistent course of depressive symptoms in a large subgroup of adults with MD in this age range.
Keywords: Aged; Chi-Square Distribution; Cognition Disorders; Depressive Disorder, Major; Female; Geriatric Assessment; Humans; Interviews as Topic; Logistic Models; Male; Middle Aged; Prospective Studies; Psychiatric Status Rating Scales; Residence Characteristics; Risk Factors; United States

The effect of heavy drinking on social security old-age and survivors insurance contributions and benefits. - Ostermann, Jan; Frank A Sloan (Milbank Q, 2004)
This article estimates the effects of heavy alcohol consumption on Social Security Old-Age and Survivor Insurance (OASI) contributions and benefits. The analysis accounts for differential earnings and mortality experiences of individuals with different alcohol consumption patterns and controls for other characteristics, including smoking. Relative to moderate drinkers, heavy drinkers receive fewer OASI benefits relative to their contributions. Ironically, for each cohort of 25-year-olds, eliminating heavy drinking costs the program an additional $3 billion over the cohort's lifetime. Public health campaigns are designed to improve individual health-relevant behaviors and, in the long run, increase longevity. Therefore, if programs for the elderly are structured as longevity-independent defined benefit programs, their success will reward healthier behaviors but increase these programs' outlays and worsen their financial condition.
Keywords: Accidents, Traffic; Adolescent; Adult; Aged; Aged, 80 and over; Alcoholism; Cost Sharing; Female; Health Behavior; Humans; Insurance Coverage; Life Expectancy; Male; Middle Aged; Old Age Assistance; Social Security; United States

The effect of smoking on years of healthy life (YHL) lost among middle-aged and older Americans. - Truls Ostbye; Donald H. Taylor Jr. (Health Serv Res, 2004)
OBJECTIVE: To estimate the effects of smoking on quality of life over time, using the Years of Healthy Life (YHL) construct. DATA SOURCES/STUDY SETTING: The Health and Retirement Study (HRS) survey (N=12,652) of persons 50 to 60 years old and the Asset and Health Dynamics Among the Oldest Old (AHEAD) survey (N=8,124) of persons > or =70 years old, plus spouses regardless of age, followed from 1992/1993 to 2000. STUDY DESIGN: Years of healthy life from baseline to death were estimated. Regression models were developed with smoking as the main explanatory variable and with both YHL and years of life remaining as the outcome variables. PRINCIPAL FINDINGS: Smoking was strongly and consistently related to YHL lost. In HRS, individuals who had quit smoking at least 15 years prior to baseline had a similar number of YHL left as never smokers. CONCLUSIONS: Efforts to encourage smoking cessation should emphasize the impact of these factors on quality of life.
Keywords: Age Distribution; Aged; Aged, 80 and over; Female; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; Quality of Life; Quality-Adjusted Life Years; Regression Analysis; Sex Distribution; Smoking; Smoking cessation; United States

The effect of spousal mental and physical health on husbands' and wives' depressive symptoms, among older adults: longitudinal evidence from the Health and Retirement Survey. - Michele J. Siegel; Elizabeth H Bradley; William T Gallo; Stanislav V Kasl (J Aging Health, 2004)
OBJECTIVE: To estimate the effect of spousal depressive symptoms and physical health on respondents' depressive symptoms in a national sample of older married couples. METHOD: We used data on 5,035 respondent husbands and wives from the 1992 and 1994 waves of the Health and Retirement Survey. Multivariate regression models were estimated to examine the impact of spousal depressive symptoms and physical health on respondents' depressive symptoms. RESULTS: Adjusting for respondent mental and physical health and sociodemographic traits, having a spouse with more depressive symptoms was associated with significantly higher follow-up depressive symptoms in the respondent (p < .001). Controlling for spousal depressive symptoms, a decline in the spouses' physical health was associated with a significant reduction in respondent depressive symptoms (p < .05). DISCUSSION: Our findings suggest that health care providers treating older adults should be sensitive to the possibility that spouses may be affected when clients suffer poor mental or physical health.
Keywords: Aged; Caregivers; depression; Female; Health Status; Humans; Male; Mental Health; Models, Theoretical; Spouses; United States

The effect of the tobacco settlement and smoking bans on alcohol consumption. - Gabriel A. Picone; Frank A Sloan; Justin G Trogdon (Health Econ, 2004)
In the last few years, the price of cigarettes has increased considerably in the USA. In addition, a number of states have also imposed smoking bans. These increases in the cost and barriers to smoking have created a natural experiment to study relationships between smoking and drinking behaviors. In this study, we employ data from the first six waves of the Health and Retirement Survey (HRS) to analyze the effects of smoking bans and cigarette prices on alcohol consumption. We also test if past cigarette and alcohol consumption affect current alcohol consumption as predicted by co-addiction models. We estimate dynamic panel models using GMM estimators. Our approach allows us to obtain consistent estimates irrespective of the number of time periods. The three main findings of this study are: (1) there is positive reinforcement effect of past cigarette consumption on current alcohol consumption, (2) smoking bans reduce alcohol consumption and (3) there is a positive effect of cigarette prices on alcohol consumption.
Keywords: Aged; Alcohol Drinking; Behavior, Addictive; Data collection; Female; Humans; Male; Middle Aged; Models, Econometric; Smoking; United States

Elders who delay medication because of cost: health insurance, demographic, health, and financial correlates. - Klein, Dawn; Carolyn L. Turvey; Robert B Wallace (Gerontologist, 2004)
PURPOSE: Prescription medication use is essential to the health and well-being of many elderly persons. However, the cost of medications may be prohibitive and contribute to noncompliance with medical recommendations. This study identifies community-dwelling elders who reported a delay in medication use because of prescription medication cost. DESIGN AND METHODS: This was a cross-sectional study of a nationwide sample of 6,535 elders participating in the Asset and Health Dynamics Among the Oldest Old (AHEAD) study. Participants reported if they had taken less medication than prescribed or if they had not filled prescriptions because of cost in the past 2 years. This response was then compared with the self-report of multiple variables, including demographic, health status, health insurance coverage, and financial variables. RESULTS: Elders who were most vulnerable to medication delay as a result of cost included those with Medicare coverage only, low income, high out-of-pocket prescription costs, and poor health as well as African American elders and those aged 65-80 years. IMPLICATIONS: This study provides important information about community-dwelling elders that reported a delay in medication use because of cost. As a Medicare prescription benefit has been passed, it will be important to monitor how these changes affect the elders identified at risk for medication delay.
Keywords: Aged; Aged, 80 and over; Cross-Sectional Studies; Drug Therapy; Fees, Pharmaceutical; Female; Health Status; Humans; Insurance, Pharmaceutical Services; Logistic Models; Male; Medicare; Multivariate Analysis; Patient Compliance; Self Administration; Socioeconomic factors; United States

Elevated depressive symptoms among caregiving grandparents. - Blustein, J.; Sewin Chan; Guanais, F.C. (Health Serv Res, 2004)
OBJECTIVE: To determine whether caregiving grandparents are at an increased risk for depressive symptoms. DATA SOURCE: National sample (n=10,293) of grandparents aged 53-63 years in 1994, and their spouse/partners, who took part in the Health and Retirement Study (HRS). STUDY DESIGN: Grandparents were surveyed in 1994 and resurveyed every two years thereafter, through 2000. Over that period, 977 had a grandchild move in or out of their home. These grandparents served as their own controls to assess the impact of having a grandchild in the home. Data Extraction. Depressive symptoms were measured using an abbreviated form of the Center for Epidemiologic Studies-Depression (CES-D) scale, scored 1-8, with a score > or =4 associated with depression "caseness". PRINCIPAL FINDINGS: At the time of the 1994 interview, 8.2 percent of grandparents had a grandchild in their home. However, there was substantial variation across demographic groups (e.g., 29.4 percent of single nonwhite grandmothers, but only 2.0 percent of single white grandfathers had a grandchild in residence). The impact of having a grandchild in the home varied by grandparent demographic group, with single grandparents and those without coresident adult children experiencing the greatest probability of elevation in depressive symptoms when a grandchild was in residence. For example, single nonwhite grandmothers experienced an 8 percentage point increase in the probability of having a CES-D score > or =4 when a grandchild was in their home, compared to when a grandchild was not in their home, controlling for changes in health care, income, and household composition over time (95 percent CI=0.1 to 15.0 percentage points). CONCLUSIONS: Grandparents have a greater probability of elevated depressive symptoms when a grandchild is in their home, versus when a grandchild is not in their home. Single women of color bear a disproportionate burden of the depression associated with caring for grandchildren. Since an increasing number of grandparents function as a de facto safety net keeping their grandchildren out of formal foster care, identifying strategies to support the health and well-being of caregiving grandparents is an emerging priority.
Keywords: Child; Data collection; depression; Family; Humans; Intergenerational Relations; Interviews as Topic; Middle Aged; Socioeconomic factors; United States

The health effects of restricting prescription medication use because of cost. - Michele M Heisler; Kenneth M. Langa; Eby, Elizabeth L.; A. Mark Fendrick; Mohammed U Kabeto; John D Piette (Med Care, 2004)
BACKGROUND: High out-of-pocket expenditures for prescription medications could lead people with chronic illnesses to restrict their use of these medications. Whether adults experience adverse health outcomes after having restricted medication use because of cost is not known. METHODS: We analyzed data from 2 prospective cohort studies of adults who reported regularly taking prescription medications using 2 waves of the Health and Retirement Study (HRS), a national survey of adults aged 51 to 61 in 1992, and the Asset and Health Dynamics Among the Oldest Old (AHEAD) Study, a national survey of adults aged 70 or older in 1993 (n = 7991). We used multivariable logistic and Poisson regression models to assess the independent effect on health outcomes over 2 to 3 years of follow up of reporting in 1995-1996 having taken less medicine than prescribed because of cost during the prior 2 years. After adjusting for differences in sociodemographic characteristics, health status, smoking, alcohol consumption, body mass index (BMI), and comorbid chronic conditions, we determined the risk of a significant decline in overall health among respondents in good to excellent health at baseline and of developing new disease-related adverse outcomes among respondents with cardiovascular disease, diabetes, arthritis, and depression. RESULTS: In adjusted analyses, 32.1% of those who had restricted medications because of cost reported a significant decline in their health status compared with 21.2% of those who had not (adjusted odds ratio [AOR], 1.76; confidence interval [CI], 1.27-2.44). Respondents with cardiovascular disease who restricted medications reported higher rates of angina (11.9% vs. 8.2%; AOR, 1.50; CI, 1.09-2.07) and experienced higher rates of nonfatal heart attacks or strokes (7.8% vs. 5.3%; AOR, 1.51; CI, 1.02-2.25). After adjusting for potential confounders, we found no differences in disease-specific complications among respondents with arthritis and diabetes, and increased rates of depression only among the older cohort. CONCLUSIONS: Cost-related medication restriction among middle-aged and elderly Americans is associated with an increased risk of a subsequent decline in their self-reported health status, and among those with preexisting cardiovascular disease with higher rates of angina and nonfatal heart attacks or strokes. Such cost-related medication restriction could be a mechanism for worse health outcomes among low-income and other vulnerable populations who lack adequate insurance coverage.
Keywords: Aged; Chronic disease; Female; Financing, Personal; Health Services Accessibility; Health Status; Humans; Male; Middle Aged; Multivariate Analysis; Patient Compliance; Prospective Studies; Risk; United States

Health insurance coverage and mortality among the near-elderly. - J. Michael McWilliams; Alan M. Zaslavsky; Meara, Ellen; John Z. Ayanian (Health Aff (Millwood), 2004)
Uninsured near-elderly people may be particularly at risk for adverse health outcomes. We compared mortality of a nationally representative cohort of insured and uninsured near-elderly people with stratification by race; income; and the presence of diabetes, hypertension, or heart disease, using propensity-score methods to adjust for numerous characteristics. Lacking health insurance was associated with substantially higher adjusted mortality among adults who were white; had low incomes; or had diabetes, hypertension, or heart disease. Expanding coverage to the near-elderly uninsured may greatly improve health outcomes for these groups.
Keywords: Cohort Studies; Female; health policy; Humans; Insurance Coverage; Insurance, Health; Longitudinal Studies; Male; Medically Uninsured; Middle Aged; Mortality; United States

The impact of diabetes on workforce participation: results from a national household sample. - Sandeep Vijan; Rodney A. Hayward; Kenneth M. Langa (Health Serv Res, 2004)
OBJECTIVE: Diabetes is a highly prevalent condition that results in substantial morbidity and premature mortality. We investigated how diabetes-associated mortality, disability, early retirement, and work absenteeism impacts workforce participation. DATA SOURCE: We used the Health and Retirement Study (HRS), a national household sample of adults aged 51-61 in 1992, as a data source. STUDY DESIGN: We conducted cross-sectional analyses on the baseline HRS data, and longitudinal analyses using data from eight years of follow-up. We used two-part regression models to estimate the adjusted impact of diabetes on workforce participation, and then estimated the economic impact of diabetes-related losses in productivity. PRINCIPAL FINDINGS: Diabetes is a significant predictor of lost productivity. The incremental lost income due to diabetes by 1992 was 60.0 billion US dollars over an average diabetes duration of 9.7 years. From 1992 to 2000, diabetes was responsible for 4.4 billion US dollars in lost income due to early retirement, 0.5 billion US dollars due to increased sick days, 31.7 billion US dollars due to disability, and 22.0 US dollars billion in lost income due to premature mortality, for a total of 58.6 billion dollars in lost productivity, or 7.3 billion US dollars per year. CONCLUSIONS: In the U.S. population of adults born between 1931 and 1941, diabetes is associated with a profound negative impact on economic productivity. By 1992, an estimated 60 billion US dollars in lost productivity was associated with diabetes; additional annual losses averaged 7.3 billion US dollars over the next eight years, totaling about 120 billion US dollars by the year 2000. Given the rising prevalence of diabetes, these costs are likely to increase substantially unless countered by better public health or medical interventions.
Keywords: Chronic disease; Cohort Studies; Cost of Illness; Cross-Sectional Studies; Diabetes Mellitus; Disabled Persons; Efficiency; Employment; Female; Health Services Research; Health Status Indicators; Humans; Longitudinal Studies; Male; Middle Aged; United States

Increasing obesity rates and disability trends. - Sturm, Roland; Ringel, Jeanne S.; Andreyeva, Tatiana (Health Aff (Millwood), 2004)
Are older Americans becoming more or less disabled? Unhealthy body weight has increased dramatically, but other data show that disability rates have declined. We use data from the Health and Retirement Study to estimate the association between obesity and disability, and we combine these data with trend estimates of obesity rates from the Behavioral Risk Factor Surveillance Survey. If current trends in obesity continue, disability rates will increase by 1 percent per year more in the 50-69 age group than if there were no further weight gain.
Keywords: Aged; Disabled Persons; Female; Humans; Male; Middle Aged; Obesity; Population Surveillance; United States

Informal care and health care use of older adults. - Courtney Harold Van Houtven; Edward C Norton (J Health Econ, 2004)
Informal care by adult children is a common form of long-term care for older adults and can reduce medical expenditures if it substitutes for formal care. We address how informal care by all children affects formal care, which is critically important given demographic trends and the many policies proposed to promote informal care. We examine the 1998 Health and Retirement Survey (HRS) and 1995 Asset and Health Dynamics Among the Oldest-Old Panel Survey (AHEAD) using two-part utilization models. Instrumental variables (IV) estimation controls for the simultaneity of informal and formal care. Informal care reduces home health care use and delays nursing home entry.
Keywords: Aged; Female; Health Care Surveys; health policy; Health Services for the Aged; Home Care Services; Home Nursing; Homes for the Aged; Humans; Male; Nursing homes; United States

Involuntary job loss as a risk factor for subsequent myocardial infarction and stroke: findings from the Health and Retirement Survey. - William T Gallo; Elizabeth H Bradley; Tracy Falba; J. A. Dubin; Cramer, L.; Stanislav V Kasl (Am J Ind Med, 2004)
BACKGROUND: The role of stress in the development of cardiovascular disease is well established. Previous research has demonstrated that involuntary job loss in the years immediately preceding retirement can be a stressful life event shown to produce adverse changes in physical and affective health. The objective of this study was to estimate the risk of myocardial infarction (MI) and stroke associated with involuntary job loss among workers nearing retirement in the United States. METHODS: We used multivariable survival analysis to analyze data from the first four waves of the Health and Retirement Survey (HRS), a nationally representative sample of older individuals in the US. The analytic sample includes 457 workers who experienced job loss and a comparison group of 3,763 employed individuals. RESULTS: The results indicate that involuntary job loss is not associated with subsequent risk of MI (adjusted HR = 1.89; 95% CI = 0.91, 3.93); the risk of subsequent stroke associated with involuntary job loss is more than double (adjusted HR = 2.64; 95% CI = 1.01, 6.94). CONCLUSIONS: Our findings present new data to suggest that involuntary job loss should be considered as a plausible risk factor for subsequent cardiovascular and cerebrovascular illness among older workers.
Keywords: Female; Humans; Male; Middle Aged; Myocardial Infarction; Prospective Studies; Retirement; Risk Factors; Stress, Psychological; Stroke; Unemployment; United States

Major depression in community-dwelling middle-aged and older adults: prevalence and 2- and 4-year follow-up symptoms. - Ramin Mojtabai; Mark Olfson (Psychol Med, 2004)
BACKGROUND: Although major depression is a common condition across the age range, there is some evidence from clinical studies that it may be more persistent and disabling in older adults. This study examined the demographic, socio-economic and clinical factors associated with major depression and with persistence of depressive symptoms at 2- and 4-year follow-ups in a large population sample of middle-aged and older adults. METHOD: In a sample of 9747 participants aged over 50 in the 1996 wave of the US Health and Retirement Study, the authors assessed the 12-month prevalence of major depression using the Composite International Diagnostic Interview-Short Form (CIDI-SF). Significant depressive symptoms at the time of 1996, 1998 and 2000 interviews were assessed using a short form of the Center for Epidemiological Studies Depression Scale (CES-D). RESULTS: The 12-month prevalence of CIDI-SF major depression was 6.6%. With age, prevalence declined, but the likelihood of significant depressive symptoms at follow-ups increased. Both prevalence and persistence of significant depressive symptoms at follow-ups were associated with socio-economic disadvantage and physical illness. Persistence of depressive symptoms at follow-ups was also associated with symptoms of anhedonia, feelings of worthlessness, and thoughts of death at baseline. CONCLUSIONS: Sociodemographic, physical health and a specific profile of depressive symptoms are associated with a poorer course of major depression in the middle-aged and older adults. These indicators may identify a subgroup of patients in need of more careful follow-up and intensive treatment.
Keywords: Age Factors; Aged; Depressive Disorder, Major; Female; Follow-Up Studies; Health Status; Humans; Logistic Models; Male; Middle Aged; Prevalence; Residence Characteristics; Sex Factors; Socioeconomic factors; Time Factors; United States

Nonmetro residence and impaired vision among elderly Americans. - Nan E. Johnson (J Rural Health, 2004)
PURPOSE: Nonmetro and metro elderly people are contrasted in their risk of having (relative to lacking) an impairment in distance vision and in near vision. METHODS: Using the 1995-1996 panel (Wave 2) of the Asset and Health Dynamics Among the Oldest Old (AHEAD) Survey, the prevalence of 5 eye-threatening conditions (cardiovascular disease, cataract, diabetes, glaucoma, and hypertension), a variety of medical treatments for these conditions, the number of talks/visits with doctors in the 2 years before Wave 2, and several relevant demographic characteristics of the 6,817 respondents were controlled. FINDINGS: Nonmetro and metro elders have the same risk of impairment in distance vision. After controlling for other factors, nonmetro elders have a higher risk than their metro peers of an uncorrected impairment in near vision (probably presbyopia). CONCLUSIONS: Nonmetro elders may confront more impediments to updating their corrective lenses for presbyopia. Implications for public health policy are discussed.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cataract; Chronic disease; Comorbidity; Diabetes Mellitus; Humans; Hypertension; Prevalence; Risk Assessment; Rural Health; United States; Urban Health; Vision Disorders

Nonmetro residence, hearing loss, and its accommodation among elderly people. - Nan E. Johnson (J Rural Health, 2004)
BACKGROUND: No previous studies compare the prevalence of physiological hearing loss among older adults by nonmetro/metro residence. Also, there is little information on their relative successes in accommodating hearing loss with a hearing aid. PURPOSE: This study sought to bridge these gaps by analyzing the 8,222 respondents to Wave 1 (1993-1994) of the national Asset and Health Dynamics Among the Oldest Old (AHEAD) Survey. METHODS: Respondents were classified into 4 categories of hearing status: (1) physiologically normal hearing; and physiologically abnormal hearing with (2) full accommodation of lost hearing with a hearing aid, (3) partial accommodation, and (4) no hearing aid. A multinomial logistic regression was used to predict the odds of having any of the 3 statuses of physiologically abnormal hearing rather than normal hearing. FINDINGS: Nonmetro residents had the same odds as metro residents of having no residual hearing loss when a hearing aid was worn (versus having physiologically normal hearing). But nonmetro residents had a much greater risk than their metro counterparts of having a hearing loss but no hearing aid or a residual hearing loss even when wearing an aid. The association of nonmetro residence with either of these latter hearing-loss statuses was greater than that of age, a more traditionally acknowledged hearing-risk factor. CONCLUSION: Future studies should add nonmetro residence to the list of risk factors for negative hearing outcomes, especially since the percentage of elderly nonmetro residents is expected to grow over the next 2 decades.
Keywords: Aged; Aged, 80 and over; Comorbidity; Female; Health Surveys; Hearing aids; Hearing loss; Humans; Male; Memory Disorders; Odds Ratio; Rural Health; United States; Urban Population

Number of children associated with obesity in middle-aged women and men: results from the health and retirement study. - Weng, Haoling H.; Bastian, Lori A.; Donald H. Taylor Jr.; Truls Ostbye (J Womens Health (Larchmt), 2004)
OBJECTIVE: To study associations between number of children and obesity in middle-aged women and men. METHODS: In the Health and Retirement Study, a national survey of households, we tested the association between increasing number of children and obesity (body mass index [BMI] >or= 30) in 9046 middle-aged women and men (4523 couples). RESULTS: Women (n = 4523) who were obese were more frequently nonwhite, reported lower household income, were more frequently employed outside the home, were less frequently covered by health insurance, and were more frequently less educated compared with nonobese women. Men (n = 4523) who were obese were younger, were more frequently African American, and were more frequently less educated and poorer compared with nonobese men. Among women, a 7% increase in risk of obesity was noted for each additional child, adjusting for age, race, household income, work status, physical activity, tobacco use, and alcohol use. Among men, a 4% increase in risk of obesity was noted for each additional child, adjusting for the same covariates. These sex differences were not significantly different. CONCLUSIONS: Previous research has demonstrated an association between number of children and obesity among women. These results suggest a similar association among men. Public health interventions focused on obesity prevention should target both parents, especially those parents with several children.
Keywords: Adult; Aged; Body Mass Index; Family Characteristics; Female; Health Behavior; Health Surveys; Humans; Male; Middle Aged; Obesity; Parity; Risk Assessment; United States

Obesity's effects on the onset of functional impairment among older adults. - Kristi Rahrig Jenkins (Gerontologist, 2004)
PURPOSE: This study has two purposes. First, it determines if there is a relationship between body weight and the onset of functional impairment across time among this sample of older adults. More specifically, it examines if obese older adults are more likely to experience the onset of functional impairment. Second, it explores how health behaviors and health conditions may explain the relationship between body weight and the onset of functional impairment. DESIGN AND METHODS: With the use of longitudinal data from the Asset and Health Dynamics Among the Oldest Old (AHEAD) survey, logistic regression models on the onset of functional impairment over two time points are estimated for older adults. RESULTS: Results indicate that body weight (more specifically being overweight or obese) makes one more likely to experience the onset of functional impairment across various domains of impairment. Outside of health behaviors and health conditions, obesity has an independent effect on the onset of impairment in strength, lower body mobility, and activities of daily living. IMPLICATIONS: Study findings support the active treatment of weight problems in older adults. Future directions for research in this area should address effective weight management interventions targeting issues related to older individuals.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Body Weight; Chronic disease; Disabled Persons; Exercise; Female; Humans; Longitudinal Studies; Male; Motor Activity; Movement; Obesity; Risk-Taking; United States

Physical activity and mortality across cardiovascular disease risk groups. - Richardson, Caroline R.; Kriska, Andrea M.; Lantz, Paula M.; Rodney A. Hayward (Med Sci Sports Exerc, 2004)
PURPOSE: Several cohort studies suggest that sedentary individuals have an increased risk of death compared with individuals who are physically active. Most of these studies have been conducted in highly selected patient populations who tend to be healthier and are from higher socioeconomic status (SES) groups. We examined the impact of a sedentary lifestyle on mortality by cardiovascular disease (CVD) risk group in a national sample of U.S. adults who represent a wide range of activity levels, health conditions, and SES groups. METHODS: Using data from the HRS, a nationally representative, observational study of 9824 U.S. adults aged 51-61 yr in 1992, we estimated the relative risk of death comparing sedentary individuals with those who are physically active by CVD risk group in a multivariate logistic regression model. RESULTS: Even after adjusting for confounders, regular moderate to vigorous physical activity was associated with substantially lower overall mortality (odds ratio (OR) = 0.62 (95% CI 0.44-0.86)) compared with sedentary individuals. High CVD risk individuals (21% of the population) accounted for 64% of deaths attributable to a sedentary lifestyle. Those with high CVD risk had the most significant benefit from being active (regular moderate to vigorous exercisers OR = 0.55 (95% CI 0.31-0.97) and occasional or light exercisers OR 0.55 (95% CI 0.41-0.74)) compared with high CVD risk individuals who were sedentary. CONCLUSION: A sedentary lifestyle is associated with a higher risk of death in preretirement-aged U.S. adults. Individuals with high CVD risk appear to get the largest benefit from being physically active. Physical activity interventions targeting high CVD risk individuals should be a medical and public health priority.
Keywords: Cardiovascular Diseases; Cohort Studies; Female; Follow-Up Studies; Humans; Life Style; Logistic Models; Male; Middle Aged; Motor Activity; Multivariate Analysis; Odds Ratio; Prospective Studies; Risk Assessment; Risk Factors; Socioeconomic factors; Survival Analysis; United States

Quality of preventive clinical services among caregivers in the health and retirement study. - Kim, Catherine; Mohammed U Kabeto; Robert B Wallace; Kenneth M. Langa (J Gen Intern Med, 2004)
We examined the association between caregiving for a spouse and preventive clinical services (self-reported influenza vaccination, cholesterol screening, mammography, Pap smear, and prostate cancer screening over 2 years and monthly self-breast exam) for the caregiver in a cross-sectional analysis of the Health and Retirement Study, a nationally representative sample of U.S. adults aged > or = 50 years (N = 11,394). Spouses engaged in 0, 1-14, or > or = 14 hours per week of caregiving. Each service was examined in logistic regression models adjusting for caregiver characteristics. After adjustment for covariates, there were no significant associations between spousal caregiving and likelihood of caregiver receipt of preventive services.
Keywords: Aged; Caregivers; Cohort Studies; Cross-Sectional Studies; Female; Health Care Surveys; Humans; Male; Middle Aged; Patient Acceptance of Health Care; Preventive Health Services; Quality of Health Care; Time Factors; United States

Religion and functional health among the elderly: is there a relationship and is it constant? - Benjamins, Maureen Reindl (J Aging Health, 2004)
OBJECTIVES: Religion significantly influences a variety of health outcomes, especially among the elderly. Few studies have examined how the relationship may differ by age within this age group. It is possible that increasing levels of religiosity within the elderly, or other age-related differences, may strengthen the influence of religion on functional limitations. METHOD: This study used the Assets and Health Dynamics Among the Oldest Old Survey, a nationally representative, longitudinal data set, to estimate the effects of religious attendance and salience on functional ability. RESULTS: More frequent attendance is associated with fewer functional limitations, whereas higher levels of salience are associated with more limitations. No significant age interactions were found. DISCUSSION: Attendance and salience predict the number of functional limitations in the elderly but in different directions. These effects tend to be stable within the elderly population, indicating that further age divisions may not be necessary when examining this relationship in future studies.
Keywords: Activities of Daily Living; Age Factors; Aging; Demography; Health Behavior; Health Status; Humans; Mental Health; Religion and Psychology; Socioeconomic factors; United States

Religion and preventative health care utilization among the elderly. - Benjamins, Maureen Reindl; Brown, Carolyn (Soc Sci Med, 2004)
Evidence supporting a relationship between religion and physical health has increased substantially in the recent past. One possible explanation for this relationship that has not received much attention in the literature is that health care utilization may differ by religious involvement or religious denomination. A nationally representative sample of older adults was used to estimate the effects of religious salience and denomination on six different types of preventative health care (i.e. flu shots, cholesterol screening, breast self-exams, mammograms, pap smears, and prostate screening). Findings show that both men and women who report high levels of religiosity are more likely to use preventative services. Denominational differences show that affiliated individuals, especially those who are Jewish, are significantly more likely to use each type of preventative care than non-affiliated individuals. The results of this study open the door to further exploration of this potentially important, but relatively neglected, link between religion and health.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Catholicism; Diagnostic Tests, Routine; Female; Health Services for the Aged; Health Status; Humans; Interviews as Topic; Jews; Logistic Models; Longitudinal Studies; Male; Patient Acceptance of Health Care; Preventive Health Services; Primary Health Care; Protestantism; Religion and Psychology; Socioeconomic factors; United States

Resolving inconsistencies in trends in old-age disability: report from a technical working group. - Vicki A Freedman; Eileen M. Crimmins; Robert F. Schoeni; Brenda C Spillman; Aykan, Hakan; Kramarow, Ellen; Land, Kenneth; Lubitz, James; Kenneth G. Manton; Linda G Martin; Shinberg, Diane; Timothy A Waidmann (Demography, 2004)
In September 2002, a technical working group met to resolve previously published inconsistencies across national surveys in trends in activity limitations among the older population. The 12-person panel prepared estimates from five national data sets and investigated methodological sources of the inconsistencies among the population aged 70 and older from the early 1980s to 2001. Although the evidence was mixed for the 1980s and it is difficult to pinpoint when in the 1990s the decline began, during the mid- and late 1990s, the panel found consistent declines on the order of 1%-2.5% per year for two commonly used measures in the disability literature: difficulty with daily activities and help with daily activities. Mixed evidence was found for a third measure: the use of help or equipment with daily activities. The panel also found agreement across surveys that the proportion of older persons who receive help with bathing has declined at the same time as the proportion who use only equipment (but not personal care) to bathe has increased. In comparing findings across surveys, the panel found that the period, definition of disability, treatment of the institutionalized population, and age standardizing of results were important to consider. The implications of the findings for policy, national survey efforts, and further research are discussed.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Chronic disease; Disabled Persons; Female; Health Surveys; Homemaker Services; Humans; Male; Models, Statistical; Self-Help Devices; United States

Use of an IRT-based latent variable model to link different forms of the CES-D from the Health and Retirement Study. - Richard N Jones; Stephanie J. Fonda (Soc Psychiatry Psychiatr Epidemiol, 2004)
BACKGROUND: The goal of this study was to calibrate depressive symptoms collected using different versions of the Centers for Epidemiologic Studies - Depression (CES-D) instrument in different waves of the Health and Retirement Study (HRS). METHOD: The HRS is a prospective and nationally representative cohort study. This analysis included a sample of HRS participants, adults aged 23-85 years in 1992 who had complete data on depressive symptoms at initial 2- and 4-year follow-up interviews (N= 5,734). Depressive symptoms were assessed with the CES-D. Symptom coverage and response categories varied across study wave. The first wave (1992) used a four-category response, whereas subsequent waves (1994 and 1996) used a two-category response. A structural equations model (SEM) based in Item Response Theory (IRT) was used to calibrate symptoms and generate linked depressive symptom burden scores. RESULTS: Linked depressive symptom burden scores, derived from calibrated symptoms, were distributed similarly across HRS wave. CONCLUSION: Our results demonstrate the applicability of an IRT-based SEM to address a common challenge in prospective studies: changes in the content and context of symptom assessment. Future investigations may make use of our linked syndrome scores to further explore other aspects of depression from a longitudinal perspective.
Keywords: Adult; Aged; Aging; Calibration; Depressive Disorder; Female; Humans; Longitudinal Studies; Male; Middle Aged; Models, Psychological; Psychological Tests; Psychometrics; United States

Workplace characteristics and work disability onset for men and women. - Eileen M. Crimmins; Mark D Hayward (Soz Praventivmed, 2004)
OBJECTIVES: This paper investigates the association between job characteristics and work disability among men and women in older working ages in the United States. We examine whether the association persists when controlling for major chronic disease experience. We also address whether job characteristics are ultimately associated with the receipt of disability benefits. METHODS: Data are from the Health and Retirement Survey and are nationally representative of noninstitutionalized persons 51-61 in 1992. Disability onset is estimated using a hazard modeling approach for those working at wave 1 (N = 5,999). A logistic regression analysis of disability benefits is based on a risk set of 525 persons who become work-disabled before the second interview. RESULTS: Women's disability onset and health problems appear less related to job characteristics than men's. For men, work disability is associated with stressful jobs, lack of job control, and environmentally hazardous conditions but is not associated with physical demands. Participation in disability benefit programs among those with work disability is unrelated to most job characteristics or health conditions. CONCLUSIONS: Understanding of the differing process to work disability for men and women and the relationship between work and health by gender is important for current policy development.
Keywords: Disabled Persons; Female; Humans; Logistic Models; Male; Middle Aged; Occupational Diseases; Proportional Hazards Models; Retirement; Risk; Sex Factors; Sick Leave; Stress, Psychological; United States; Workers' compensation; Workload; Workplace

Additive and interactive effects of comorbid physical and mental conditions on functional health. - Fultz, Nancy H.; Mary Beth Ofstedal; A. Regula Herzog; Robert B Wallace (J Aging Health, 2003)
OBJECTIVE: To understand the role of cognitive impairment and depressive symptoms on functional outcomes of stroke and diabetes. Evaluation approaches to functional outcomes have rarely focused on the presence of specific comorbidities, particularly those involving mental health disorders. METHODS: Data are from the AHEAD cohort of the Health and Retirement Study (HRS), a nationally representative panel of persons 70+ years of age in 1993. Analyses are limited to 5,646 self-respondents for whom functional outcome data are available in 1995. Additive and interactive multiple regression models are compared for each outcome and focal condition combination. RESULTS: The additive model is sufficient for the majority of outcome and focal condition combinations. The interaction term is significant in 4 of 12 comparisons. DISCUSSION: Stroke, diabetes, cognitive impairment, and depressive symptoms exhibit strong independent effects on physical functioning. Support for the hypothesis that cognitive impairment and depression exacerbate the impact of stroke and diabetes is more limited.
Keywords: Activities of Daily Living; Aged; Aging; Black or African American; Cognition Disorders; depression; Diabetes Complications; Educational Status; Health Surveys; Hispanic or Latino; Humans; Stroke; United States; White People

Asking neutral versus leading questions: implications for functional limitation measurement. - Vicki A Freedman; Aykan, Hakan; Kleban, Morton H. (J Aging Health, 2003)
UNLABELLED: National surveys of older Americans routinely have included functional limitation items using either a leading approach ("how much difficulty do you have...") or a neutral approach ("do you have any difficulty..."). This article evaluates the performance of scales based on these two approaches. METHODS: Using responses from 595 randomly selected participants to the 1994 Health and Retirement Study, the authors compared prevalences and evaluated scales based on each approach with respect to the extent of missing data, face validity, reliability, predictive validity, convergent validity, and robustness of odds ratios in predictive models. RESULTS: The authors found that leading questions provided higher estimates of functional limitations than neutral questions, but both approaches yielded scales with similar validity and reliability. However, for both approaches, scales incorporating degree of difficulty had better validity and reliability than those based on counts of tasks. All four approaches yielded substantially similar coefficients in a model predicting disability onset. DISCUSSION: The authors conclude that, because they minimize survey time without compromising validity and reliability, items that explicitly capture degree of difficulty by asking "How much difficulty do you have..." may be the optimal approach for survey designers.
Keywords: Activities of Daily Living; Aged; Factor Analysis, Statistical; Health Surveys; Humans; Research Design; Surveys and Questionnaires; United States

Cognitive function and acute care utilization. - Walsh, Edith G.; Bei Wu; Mitchell, Janet B.; Lisa F Berkman (J Gerontol B Psychol Sci Soc Sci, 2003)
OBJECTIVES: Little is known about variation in cognitive function across the aged population, or how use and costs of health care vary with cognitive impairment. This study was designed to create a typology of cognitive function in a nationally representative sample, and evaluate acute care use in relation to cognitive function, holding constant confounding factors. By including proxy assessments of cognitive function, this is the first study to include individuals unable to respond themselves. METHODS: We analyzed the baseline year of the Asset and Health Dynamics Among the Oldest Old (AHEAD) survey, sponsored by the National Institute on Aging, to create three levels of cognitive function, using direct measures for self-respondents (n = 6,651) and proxy evaluations for the others (n = 792). We used a two-part model to predict the likelihood of using various health services and to evaluate intensity of care among users. RESULTS: Sixteen percent, 64%, and 20% of the sample fell into the low, moderate, and high cognitive function groups, respectively, that differed significantly on almost all demographic and health status measures, and some utilization measures. Controlling for other health and functional status measures, lower cognitive function had a significant and negative effect on outpatient services, but did not affect hospital use directly. DISCUSSION: Lower cognitive function may be a barrier to outpatient care, but these analyses should be repeated using administrative use and cost data.
Keywords: Aged; Cognition Disorders; Female; Geriatric Assessment; Health Behavior; Health Status; Hospitalization; Hospitals; Humans; Length of Stay; Male; Neuropsychological tests; Outpatient Clinics, Hospital; Severity of Illness Index; United States

County-level income inequality and depression among older Americans. - Muramatsu, Naoko (Health Serv Res, 2003)
OBJECTIVES: To examine (1) whether county-level income inequality is associated with depression among Americans aged 70 and older, taking into consideration county-level mean household income and individual-level socioeconomic status (SES), demographic characteristics, and physical health, and (2) whether income inequality effects are stronger among people with lower SES and physical health. DATA SOURCES: The individual-level data from the first wave of the Assets and Health Dynamics among the Oldest Old survey (1993-1994) were linked with the county-level income inequality and mean household income data from the 1990 Census. STUDY DESIGN: Multilevel analysis was conducted to examine the association between income inequality (the Gini coefficient) and depression. PRINCIPAL FINDINGS: Income inequality was significantly associated with depression among older Americans. Those living in counties with higher income inequality were more depressed, independent of their demographic characteristics, SES, and physical health. The association was stronger among those with more illnesses. CONCLUSIONS: While previous empirical research on income inequality and physical health is equivocal, evidence for income inequality effects on mental health seems to be strong.
Keywords: Age Factors; Aged; Aged, 80 and over; depression; Female; Health Status Indicators; Humans; Income; Male; Socioeconomic factors; United States

Determinants of self-perceived changes in health status among pre- and early-retirement populations. - Namkee G Choi (Int J Aging Hum Dev, 2003)
Using data from the 1992 and 1994 waves of the Health and Retirement Study (HRS), this study described reasons reported by pre- and early-retirement populations for perceived changes in global health status over a 2-year period. It then analyzed the association between self-perceptions of change and the actual changes in objective health conditions, controlling for demographics, emotional health status, and the changes in work status and health-affecting habits. The results were compared to the determinants of self-ratings of health at wave 2. Existing or increasing impairments in functional abilities were found to contribute to self-perceptions of decline. However, a diagnosis of new chronic disease and the experience of a major medical event per se did not universally contribute to self-perception of decline. The relationship between cross-sectional self-ratings of health and objective health conditions was more straightforward. Self-perception of improvement among people with serious health problems most likely owed to medical interventions and improvement in symptoms, the most frequently mentioned reasons for perceived improvement, and reflected the subjects' selective optimization and resiliency.
Keywords: Activities of Daily Living; Age Factors; Female; Health Behavior; Health Status; Humans; Logistic Models; Male; Middle Aged; Multivariate Analysis; Retirement; Self Concept; United States

High out-of-pocket health care spending by the elderly. - Dana P Goldman; Julie M Zissimopoulos (Health Aff (Millwood), 2003)
We use data from the Health and Retirement Study to examine the elderly's out-of-pocket health care spending. We find that Medicare HMOs, employer supplements, and Medicaid effectively insulate against the risk of high expenditures. At the ninetieth percentile, Medicare beneficiaries with employer supplements or enrolled in Medicare HMOs spend 1,600 dollars less out of pocket than beneficiaries with traditional Medicare spend. For the poor elderly, Medicaid offers similar protection. Among the near-poor elderly, there is little employer coverage, so Medicare HMOs provide most of the protection against financial risk. There is evidence that Medicare HMO benefits have eroded since 1998, raising the question of whether the near-poor have lost financial protection since then.
Keywords: Aged; Drug Costs; Drug Prescriptions; Financing, Personal; Health Care Surveys; Health Expenditures; Health Maintenance Organizations; Health Services for the Aged; Humans; Insurance, Health; Medicare; Poverty; United States

Intermittent lack of health insurance coverage and use of preventive services. - Joseph J Sudano; David W. Baker (Am J Public Health, 2003)
OBJECTIVES: This study examined the association between intermittent lack of health insurance coverage and use of preventive health services. METHODS: Analyses focused on longitudinal data on insurance status and preventive service use among a national sample of US adults who participated in the Health and Retirement Study. RESULTS: Findings showed that, among individuals who obtain insurance coverage after histories of intermittent coverage, relatively long periods may be necessary to reestablish clinically appropriate care patterns. Increasing periods of noncoverage led to successively lower rates of use of most preventive services. CONCLUSIONS: Intermittent lack of insurance coverage-even across a relatively long period-results in less use of preventive services. Studies that examine only current insurance status may underestimate the population at risk from being uninsured.
Keywords: Episode of Care; Female; Health Behavior; Health Status; Humans; Insurance Coverage; Logistic Models; Longitudinal Studies; Male; Medically Uninsured; Middle Aged; Outcome Assessment, Health Care; Patient Acceptance of Health Care; Preventive Health Services; Socioeconomic factors; United States

The labor market consequences of race differences in health. - John Bound; Timothy A Waidmann; Michael Schoenbaum; Bingenheimer,Jeffrey B. (Milbank Q, 2003)
Keywords: Adult; Age Distribution; Age Factors; Attitude to Health; Black or African American; Cross-Cultural Comparison; Data Interpretation, Statistical; Employment; Female; Health Services Needs and Demand; Health Status Indicators; Humans; Indians, North American; Male; Middle Aged; Sex Distribution; Sex Factors; Socioeconomic factors; United States; White People

Life expectancy with cognitive impairment in the older population of the United States. - Suthers, Kristen; Jung K Kim; Eileen M. Crimmins (J Gerontol B Psychol Sci Soc Sci, 2003)
OBJECTIVES: This article provides estimates of the prevalence of cognitive impairment by age and sex for a nationally representative sample of the U.S. population aged 70 and over. From these estimates, years of life with and without cognitive impairment are calculated. METHODS: Using data from the Assets and Health Dynamics of the Oldest Old (AHEAD) survey, the prevalence of cognitive impairment is estimated for a sample representing both the community-dwelling and institutionalized older American population. Sullivan's method is used to calculate the average number of years an elderly person can expect to live with and without cognitive impairment. RESULTS: The prevalence of moderate to severe cognitive impairment in the total U.S. population aged 70 and over is 9.5%. At age 70, the average American can expect 1.5 years with cognitive impairment. Expected length of life with cognitive impairment is longer for women than men because of their longer life expectancy. DISCUSSION: As total life expectancy continues to increase, the length of life with cognitive impairment for the American population will increase unless age-specific prevalence is reduced. There is great potential for improvement in future early treatment and diagnosis of this condition.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Cross-Sectional Studies; Female; Humans; Life Expectancy; Male; Neuropsychological tests; Probability; Psychometrics; Sex Factors; Survival Analysis; United States

Medication costs, adherence, and health outcomes among Medicare beneficiaries. - Ramin Mojtabai; Mark Olfson (Health Aff (Millwood), 2003)
In a two-year period more than two million elderly Medicare beneficiaries did not adhere to drug treatment regimens because of cost. This poor adherence tended to be more common among beneficiaries with no or partial medication coverage and was associated with poorer health and higher rates of hospitalization. The risk for cost-related poor adherence was especially pronounced among lower-income beneficiaries with high out-of-pocket drug spending. We argue that this pattern of cost-related poor medication adherence should inform the design of Medicare prescription drug benefit legislation.
Keywords: Aged; Aged, 80 and over; Chronic disease; Continuity of Patient Care; Family Characteristics; Female; Financing, Personal; Health Services Research; Humans; Income; Insurance, Pharmaceutical Services; Longitudinal Studies; Male; Medicare; Patient Compliance; Prevalence; Probability; Self Administration; Treatment Outcome; United States

Racial disparities in joint replacement use among older adults. - Dorothy D Dunlop; Larry M Manheim; Song, Jing; Rowland W Chang (Med Care, 2003)
BACKGROUND: Although joint replacement can restore function for arthritis patients with severe joint disease, this procedure has not been used equally across racial groups. Differences in joint replacement use are assessed from a national sample. OBJECTIVE: This study evaluates the role of health conditions and economic access to explain differences in joint replacement among older black and Hispanic minorities relative to white persons. DESIGN: Longitudinal (1993-1995) Asset and Health Dynamics Among the Oldest Old (AHEAD) study. SETTING: National probability sample of US community-dwelling older adults. PATIENT POPULATION: AHEAD participants (n = 6159) aged 69 to 103 years. MEASUREMENTS: The outcome is subject-reported 2-year use of any arthritis-related joint-replacement. Independent variables are demographics, health needs (arthritis, other medical conditions, functional health), and economic access (income, assets, education, and health insurance). RESULTS: Older minorities reported arthritis-related joint replacements (black: 0.98%; Hispanic: 0.97%, annually) less frequently compared with white persons (1.48% annually). Older minorities were significantly less likely to use joint replacement compared with white persons (OR, 0.37; 95% CI, 0.20, 0.71) controlling for demographics, and arthritis and other health needs. Disparities remained significant (OR, 0.46; 95% CI, 0.22, 0.98) after additionally controlling for economic medical access. Use was lower among people who depended solely on Medicare compared with those with supplemental health insurance (OR, 0.46; 95% CI, 0.22, 0.95). CONCLUSIONS: These national data document low rates of arthritis-related joint replacement among older Hispanic persons comparable to black persons. Less use among older minorities compared with white persons is not explained by differences in health needs or economic access. Other cultural and attitudinal factors merit investigation to explain disparities.
Keywords: Aged; Aged, 80 and over; Arthroplasty, Replacement; Black or African American; Cohort Studies; Data Interpretation, Statistical; Health Services Accessibility; Health Services Needs and Demand; Health Status; Health Surveys; Hispanic or Latino; Humans; Interviews as Topic; Osteoarthritis; Sampling Studies; United States; White People

Racial/ethnic differences in rates of depression among preretirement adults. - Dorothy D Dunlop; Song, Jing; Lyons, J.S.; Larry M Manheim; Rowland W Chang (Am J Public Health, 2003)
OBJECTIVES: We estimated racial/ethnic differences in rates of major depression and investigated possible mediators. METHODS: Depression prevalence rates among African American, Hispanic, and White adults were estimated from a population-based national sample and adjusted for potential confounders. RESULTS: African Americans (odds ratio [OR] = 1.16, 95% confidence interval [CI] = 0.93, 1.44) and Hispanics (OR = 1.44, 95% CI = 1.02, 2.04) exhibited elevated rates of major depression relative to Whites. After control for confounders, Hispanics and Whites exhibited similar rates, and African Americans exhibited significantly lower rates than Whites. CONCLUSIONS: Major depression and factors associated with depression were more frequent among members of minority groups than among Whites. Elevated depression rates among minority individuals are largely associated with greater health burdens and lack of health insurance, factors amenable to public policy intervention.
Keywords: Aged; Black or African American; Cohort Studies; Comorbidity; Demography; Depressive Disorder, Major; Diagnostic and Statistical Manual of Mental Disorders; Female; Hispanic or Latino; Humans; Male; Middle Aged; Minority Groups; Probability; Risk Factors; Socioeconomic factors; United States; White People

Screening mammography and Pap tests among older American women 1996-2000: results from the Health and Retirement Study (HRS) and Asset and Health Dynamics Among the Oldest Old (AHEAD). - Truls Ostbye; Gary N. Greenberg; Donald H. Taylor Jr.; Lee, Ann Marie M. (Ann Fam Med, 2003)
BACKGROUND: We wanted to determine the frequency of self-reported receipt of screening mammography and Papanicolaou (Pap) tests in older women and investigate important predictors of utilization, based on 2 national longitudinal surveys. METHODS: This cohort study includes participants from 4 waves (1994-2000) of the Health and Retirement Study (HRS)--5,942 women aged 50 to 61 years, and 4 waves (1993-2000) of the Asset and Health Dynamics Among the Oldest Old (AHEAD) survey--4,543 women aged 70 years and older. The self-reported receipt of screening mammograms and Pap smears in the most recent 2 years were reported in 1996 and 2000 for HRS, with predictors of receipt measured in 1994 and 1998. In AHEAD, the self-reported receipt of screening mammograms and Pap smears in the most recent 2 years were reported in 1995 and 2000, with predictors of receipt measured in 1993 and 1998. RESULTS: Receipt of mammography is stable at 70% to 80% among women aged 50 to 64 years, then declines to around 40% among those aged 85 to 90 years. For Pap tests there is a decline from 75% among women aged 50 to 54 years to 25% in those aged 85 to 90 years. For both mammography and Pap tests, the rates increased in all groups from 1995/1996 to 2000. Higher education, being married, higher income, not smoking, and vigorous exercise were consistently associated with higher rates of receipt. CONCLUSIONS: Although the use of mammography and Pap tests for screening declines into old age, use has been increasing recently. The large and increasing number of tests performed might not be justified given the lack of evidence of effect in older age-groups.
Keywords: Age Factors; Aged; Aged, 80 and over; Breast Neoplasms; Cost-Benefit Analysis; Female; Health Services for the Aged; Humans; Longitudinal Studies; Mammography; Middle Aged; Multivariate Analysis; Papanicolaou Test; Patient Acceptance of Health Care; Risk; United States; Uterine Cervical Neoplasms; Vaginal Smears

Urinary incontinence and depression in middle-aged United States women. - Ingrid E Nygaard; Carolyn L. Turvey; Burns, Trudy L.; Elizabeth A Chrischilles; Robert B Wallace (Obstet Gynecol, 2003)
OBJECTIVE: To determine the correlates of incontinence in middle-aged women and to test for an association between incontinence and depression. METHODS: This was a population-based cross-sectional study of 5701 women who were residents of the United States, aged 50-69 years, and participated in the third interview of the Health and Retirement Study. The primary outcome measure was self-reported urinary incontinence. Depression was ascertained based on criteria set by the Diagnostic and Statistical Manual of Mental Disorders, using a short form of the Composite International Diagnostic Interview. In addition, depressive symptoms were assessed using the revised Center for Epidemiologic Studies Depression Scale. Multivariable logistic regression models were constructed to determine the independent association between incontinence and depression, after adjusting for confounders. RESULTS: Approximately 16% reported either mild-moderate or severe incontinence. Depression, race, age, body mass index, medical comorbidities, and limited activities of daily living were associated with incontinence. After adjusting for medical morbidity, functional status, and demographic variables, women with severe and mild-moderate incontinence were 80% (odds ratio [OR] 1.82; 95% confidence interval [CI] 1.26, 2.63) and 40% (OR 1.41; 95% CI 1.06, 1.87) more likely, respectively, to have depression than continent women. The association did not hold for depressive symptoms measured by the revised Center for Epidemiologic Studies Depression Scale after adjusting for covariates. CONCLUSION: Depression and incontinence are associated in middle-aged women. The strength of the association depends on the instrument used to classify depression. This reinforces the need to screen patients presenting for treatment of urinary incontinence for depression.
Keywords: Activities of Daily Living; Aged; Comorbidity; Cross-Sectional Studies; depression; Female; Humans; Logistic Models; Middle Aged; United States; Urinary incontinence

Body-mass index and 4-year change in health-related quality of life. - Damush, T.M.; Timothy E. Stump; Daniel O. Clark (J Aging Health, 2002)
OBJECTIVE: To determine the effect of body-mass index (BMI) categories (a proxy for adiposity) on 4-year changes in health-related quality of life (HRQL) independent of baseline disease severity. DESIGN: Secondary analyses of a prospective, longitudinal study. PARTICIPANTS: Data on 7,895 adults ages 51 to 61 years who responded to the Health and Retirement Surveys in 1992, 1994, and 1996 were included. RESULTS: Estimates of the effect of BMI on changes in HRQL were adjusted by disease severity. Each BMI category was associated with an increasing risk of decline in perceived health, with the highest risk in the higher categories. A BMI of between 30 and 35 was associated with a risk of decline in mobility. CONCLUSIONS: The findings suggest a significant impact of BMI on changes in HRQL that is independent of disease severity and baseline HRQL.
Keywords: Body Mass Index; Disabled Persons; Female; Health Status; Humans; Male; Middle Aged; Obesity; Quality of Life; United States

Breast cancer and women's labor supply. - Cathy J. Bradley; Bednarek, Heather; David Neumark (Health Serv Res, 2002)
OBJECTIVE: To investigate the effect of breast cancer on women's labor supply. DATE SOURCE/STUDY SETTING: Using the 1992 Health and Retirement Study, we estimate the probability of working using probit regression and then, for women who are employed, we estimate regressions for average weekly hours worked using ordinary least squares (OLS). We control for health status by using responses to perceived health status and comorbidities. For a sample of married women, we control for spouses' employer-based health insurance. We also perform additional analyses to detect selection bias in our sample. PRINCIPAL FINDINGS: We find that the probability of breast cancer survivors working is 10 percentage points less than that for women without breast cancer. Among women who work, breast cancer survivors work approximately three more hours per week than women who do not have cancer. Results of similar magnitude persist after health status is controlled in the analysis, and although we could not definitively rule out selection bias, we could not find evidence that our results are attributable to selection bias. CONCLUSIONS: For some women, breast cancer may impose an economic hardship because it causes them to leave theirjobs. However, for women who survive and remain working, this study failed to show a negative effect on hours worked associated with breast cancer. Perhaps the morbidity associated with certain types and stages of breast cancer and its treatment does not interfere with work.
Keywords: Breast Neoplasms; Comorbidity; Cost of Illness; Decision making; Employment; Family Characteristics; Female; Health Benefit Plans, Employee; Health Status; Humans; Marital Status; Middle Aged; Probability; Selection Bias; Survivors; United States; Women, Working

Breast cancer survival, work, and earnings. - Cathy J. Bradley; Bednarek, Heather; David Neumark (J Health Econ, 2002)
Relying on data from the Health and Retirement Study (HRS) linked to longitudinal social security earnings data, we examine differences between breast cancer survivors and a non-cancer control group in employment, hours worked, wages, and earnings. Overall, breast cancer has a negative impact on employment. However, among survivors who work, hours of work, wages, and earnings are higher compared to women in the control group. We explore possible biases underlying these estimates, focusing on selection, but cannot rule out a causal interpretation. Our research points to heterogeneous labor market responses to breast cancer, and shows that breast cancer does not appear to be debilitating for women who remain in the work force.
Keywords: Breast Neoplasms; Cohort Studies; Diagnostic Tests, Routine; Efficiency; Employment; Female; Humans; Longitudinal Studies; Mammography; Middle Aged; Models, Econometric; Probability; Research Design; Retirement; Salaries and Fringe Benefits; Social Security; Survivors; United States; Women, Working

Driving life expectancy of persons aged 70 years and older in the United States. - Foley, Daniel J.; Heimovitz, Harley K.; Jack M. Guralnik; Brock, Dwight B. (Am J Public Health, 2002)
OBJECTIVES: We estimated total life expectancy and driving life expectancy of US drivers aged 70 years and older. METHODS: Life table methods were applied to 4699 elderly persons who were driving in 1993 and reassessed in a 1995 survey. RESULTS: Drivers aged 70 to 74 years had a driving life expectancy of approximately 11 years. A higher risk of mortality among men as a cause of driving cessation offset a higher risk of driving cessation not related to mortality among women that resulted in similar driving life expectancies. CONCLUSIONS: Nationwide, many elderly drivers quit driving each year and must seek alternative sources of transportation. Because of differences in life expectancy, women require more years of support for transportation, on average, than men after age 70.
Keywords: Accidents, Traffic; Activities of Daily Living; Aged; Aged, 80 and over; Automobile Driving; Decision making; Family Characteristics; Female; Frail Elderly; Humans; Interviews as Topic; Licensure; Life Expectancy; Logistic Models; Male; Risk Factors; Transportation; United States

The health capital of families: an investigation of the inter-spousal correlation in health status. - Sven E. Wilson (Soc Sci Med, 2002)
This study documents and analyzes the inter-spousal correlation in health status (ISCIHS) among married couples in later life. A simple economic theory is developed that integrates standard theories of marriage markets and health capital formation. This theory implies that several causal factors will lead to a positive correlation in the health status of spouses. These include assortative matching in the marriage market along dimensions related to health (such as education); a tendency to share common life-style behaviors such as diet, smoking and exercise; shared environmental risk factors for disease; and a potential for direct effects of the health of one spouse on the health of the other. Empirical estimates using the 1992 Health and Retirement study in the USA demonstrate that ISCIHS is large in magnitude, highly statistically significant, and robust to alternative measures of health status. ISCIHS exists even after controlling for age, education, income, and other socioeconomic and demographic determinants of health status, including behavioral risk factors. These covariates reduce the overall correlation coefficient by 33% to 57%, depending on the health measure, which suggests both that marriage formation and decision making processes systematically affect health in later life and that heretofore unidentified risk factors for disease and disability exist at the household level.
Keywords: Activities of Daily Living; Chronic disease; Decision making; Female; Health Behavior; Health Status Indicators; Humans; Interviews as Topic; Life Style; Male; Marital Status; Middle Aged; Regression Analysis; Risk Factors; Risk-Taking; Self Efficacy; Sociology, Medical; Spouses; United States

Health in household context: living arrangements and health in late middle age. - Mary Elizabeth Hughes; Linda J. Waite (J Health Soc Behav, 2002)
People living in some arrangements show better health than persons in other living arrangements. Recent prospective studies document higher mortality among persons living in particular types of households. We extend this research by examining the influence of household structure on health using longitudinal data. We theorize that individuals experience role-based household relations as sets of resources and demands. In certain household structures, individuals are more likely to perceive that the demands made on them outweigh the resources available to them. This perceived imbalance poses a risk to individual health. We test our expectations by analyzing the relationship between living arrangements and health using data from waves 1 and 2 of the Health and Retirement Study. We focus on persons ages 51-61 and explore gender differences. We find prospective links between household structure and self-rated health, mobility limitation, and depressive symptoms. Married couples living alone or with children only are the most advantaged; single women living with children appear disadvantaged on all health outcomes. Men and women in other household types are disadvantaged on some health outcomes. Our results suggest that the social context formed by the household may be important to the social etiology of health. In addition, they qualify the well-known link between marital status and health: The effect of marital status on health depends on household context.
Keywords: Activities of Daily Living; Depressive Disorder; Family Characteristics; Family Health; Female; Health Status Indicators; Humans; Longitudinal Studies; Male; Marital Status; Middle Aged; Self Efficacy; United States

Individual consequences of volunteer and paid work in old age: health and mortality. - Luoh, M.; A. Regula Herzog (J Health Soc Behav, 2002)
The impacts of the productive social activities of volunteer and paid work on health have rarely been investigated among the oldest Americans despite a recent claim for their beneficial effect (Rowe and Kahn 1998). This paper used data from Waves 3 and 4 of the Asset and Health Dynamics among the Oldest Old (AHEAD) Study to (1) investigate the impact of these activities on health measured as self-reported health and activities of daily living (ADL) functioning limitations and to (2) explore possible causal mechanisms. Using multinomial logistic regression analysis, amounts of volunteer and paid work over a minimum of 100 annual hours self-reported at Wave 3 were related to poor health and death as competing risks measured at Wave 4, controlling for health measured at Wave 2 and for other predictors of poor health and death. Findings suggest that performing more than 100 annual hours of volunteer work and of paid work have independent and significant protective effects against subsequent poor health and death. Additional analyses suggest that the quantity of volunteer and paid work beyond 100 annual hours is not related to health outcomes and that physical exercise and mental health measured as cognitive functioning and depressive symptoms explain not entirely overlapping parts of the relationship between productive activities and health.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Employment; Female; Health Status; Humans; Male; Mortality; Multivariate Analysis; Prospective Studies; United States; Volunteers

Informal caregiving time and costs for urinary incontinence in older individuals in the United States. - Kenneth M. Langa; Fultz, Nancy H.; Sanjay Saint; Mohammed U Kabeto; A. Regula Herzog (J Am Geriatr Soc, 2002)
OBJECTIVES: To obtain nationally representative estimates of the additional time, and related cost, of informal caregiving associated with urinary incontinence in older individuals. DESIGN: Multivariate regression models using data from the 1993 Asset and Health Dynamics Study, a nationally representative survey of people aged 70 and older (N = 7,443). SETTING: Community-dwelling older people. PARTICIPANTS: National population-based sample of community-dwelling older people. MEASUREMENTS: Weekly hours of informal caregiving, and imputed cost of caregiver time, for community-dwelling older people who reported (1) no unintended urine loss, (2) incontinence that did not require the use of absorbent pads, and (3) incontinence that required the use of absorbent pads. RESULTS: Thirteen percent of men and 24% of women reported incontinence. After adjusting for sociodemographics, living situation, and comorbidities, continent men received 7.4 hours per week of care, incontinent men who did not use pads received 11.3 hours, and incontinent men who used pads received 16.6 hours (P <.001). Women in these groups received 5.9, 7.6, and 10.7 hours (P <.001), respectively. The additional yearly cost of informal care associated with incontinence was $1,700 and $4,000 for incontinent men who did not and did use pads, respectively, whereas, for women in these groups, the additional yearly cost was $700 and $2,000. Overall, this represents a national annual cost of more than $6 billion for incontinence-related informal care. CONCLUSIONS: The quantity of informal caregiving for older people with incontinence and its associated economic cost are substantial. Future analyses of the costs of incontinence, and the cost-effectiveness of interventions to prevent or treat incontinence, should consider the significant informal caregiving costs associated with this condition.
Keywords: Aged; Caregivers; Comorbidity; Confounding Factors, Epidemiologic; Female; Humans; Incontinence Pads; Male; Regression Analysis; Time Factors; United States; Urinary incontinence

A longitudinal study of the effects of tobacco smoking and other modifiable risk factors on ill health in middle-aged and old Americans: results from the Health and Retirement Study and Asset and Health Dynamics among the Oldest Old survey. - Truls Ostbye; Donald H. Taylor Jr.; Sang-Hyuk Jung (Prev Med, 2002)
BACKGROUND: While the effects of smoking and other modifiable risk factors on mortality and specific diseases are well established, their effects on ill health more generally are less known. Using two national, longitudinal surveys, the objective of this study was to analyze the effect of smoking and other modifiable risk factors on ill health, defined in a multidimensional fashion (i.e., disability, impaired mobility, health care utilization, and self-reported health). METHODS: The analyses were based on the Health and Retirement Study (HRS) (12,652 persons 50-60 years old surveyed in 1992, 1994, 1996, and 1998) and the Asset and Health Dynamics among the Oldest Old survey (8,124 persons 60-70 years old surveyed in 1993, 1996, and 1998). RESULTS: Smoking was strongly related to mortality and to ill health, with similar relative effects in the middle-aged and the elderly. There were consistent adverse dose-response relationships between smoking and ill health in the HRS. Persons who had quit smoking at least 15 years prior to the survey were no more likely than never smokers to experience ill health. A dose-response relationship was found between exercise and ill health. For body mass index and alcohol, there were U-shaped relationships with ill health. CONCLUSIONS: Public health efforts designed to encourage smoking cessation should emphasize improvements in ill health in addition to decreased mortality.
Keywords: Age Distribution; Aged; Aged, 80 and over; Alcohol Drinking; Attitude to Health; Chi-Square Distribution; Exercise; Female; Health Behavior; Health Status; Health Surveys; Humans; Life Style; Logistic Models; Longitudinal Studies; Male; Middle Aged; Risk Assessment; Risk Factors; Sex Distribution; Smoking; Socioeconomic factors; Survival Rate; United States

A national study of the quantity and cost of informal caregiving for the elderly with stroke. - Hickenbottom, S.L.; A. Mark Fendrick; Kutcher, J.S.; Mohammed U Kabeto; Steven J. Katz; Kenneth M. Langa (Neurology, 2002)
BACKGROUND: As the US population ages, increased stroke incidence will result in higher stroke-associated costs. Although estimates of direct costs exist, little information is available regarding informal caregiving costs for stroke patients. OBJECTIVE: To determine a nationally representative estimate of the quantity and cost of informal caregiving for stroke. METHODS: The authors used data from the first wave of the Asset and Health Dynamics (AHEAD) Study, a longitudinal study of people over 70, to determine average weekly hours of informal caregiving. Two-part multivariable regression analyses were used to determine the likelihood of receiving informal care and the quantity of caregiving hours for those with stroke, after adjusting for important covariates. Average annual cost for informal caregiving was calculated. RESULTS: Of 7,443 respondents, 656 (8.8%) reported a history of stroke. Of those, 375 (57%) reported stroke-related health problems (SRHP). After adjusting for cormorbid conditions, potential caregiver networks, and sociodemographics, the proportion of persons receiving informal care increased with stroke severity, and there was an association of weekly caregiving hours with stroke +/- SRHP (p < 0.01). Using the median 1999 home health aide wage (8.20 dollars/hour) as the value for family caregiver time, the expected yearly caregiving cost per stroke ranged from 3,500 dollars to 8,200 dollars. Using conservative prevalence estimates from the AHEAD sample (750,000 US elderly patients with stroke but no SRHP and 1 million with stroke and SRHP), this would result in an annual cost of up to 6.1 billion dollars for stroke-related informal caregiving in the United States. CONCLUSIONS: Informal caregiving-associated costs are substantial and should be considered when estimating the cost of stroke treatment.
Keywords: Aged; Aged, 80 and over; Caregivers; Confidence Intervals; Female; Humans; Longitudinal Studies; Male; Multivariate Analysis; Stroke; United States

Prevalence and correlates of depressive symptoms in a community sample of people suffering from heart failure. - Carolyn L. Turvey; Schultz, K.; Arndt, Stephan; Robert B Wallace; A. Regula Herzog (J Am Geriatr Soc, 2002)
OBJECTIVES: To examine the rates and correlates of depressive symptoms and syndromal depression in people with self-reported heart failure participating in a community study of people aged 70 and older. DESIGN: Cross-sectional. SETTING: Community-based epidemiological study of older people from the continental United States. PARTICIPANTS: Six thousand one hundred twenty-five older people participating in the longitudinal study of Assets and Health Dynamics. Participants had to be born in 1923 or earlier. MEASUREMENTS: The short-form Composite International Diagnostic Interview assessed syndromal depression, and a revised version of the Center for Epidemiologic Studies-Depression scale assessed depressive symptoms. Medical illness was based on self-report. The authors compared the rates of syndromal depression and individual depressive symptoms in people with self-reported heart failure (n = 199) with those in people with other heart conditions (n = 1,856) and with no heart conditions (n = 4,070). RESULTS: Eleven percent of those with heart failure met criteria for syndromal depression, compared with 4.8% of people with other heart conditions and 3.2% of those with no heart conditions. The association between heart failure and depression held even after controlling for disability, reported fatigue and breathlessness, and number of comorbid chronic illnesses. CONCLUSION: Community-living older people with self-reported heart failure were at approximately twice the risk for syndromal depression of the rest of the community. Although fatigue and functional disability were also related to depression in this sample, these variables did not account for the association between syndromal depression and self-reported heart failure.
Keywords: Aged; depression; Female; Heart Failure; Humans; Longitudinal Studies; Male; Prevalence; United States

The role of smoking and other modifiable lifestyle risk factors in maintaining and restoring lower body mobility in middle-aged and older Americans: results from the HRS and AHEAD. Health and Retirement Study. Asset and Health Dynamics Among the Oldest Ol - Truls Ostbye; Donald H. Taylor Jr.; Katrina M. Krause; Scoyoc, L.V. (J Am Geriatr Soc, 2002)
OBJECTIVES: To analyze the effect of smoking, smoking cessation, and other modifiable risk factors on mobility in middle-aged and older Americans. DESIGN: Panel study; secondary data analysis. SETTING: United States (national sample). PARTICIPANTS: The Health and Retirement Study (HRS) includes data on 12,652 Americans aged 50 to 61 in four waves (1992-1998). The Asset and Health Dynamics Among the Oldest Old (AHEAD) survey followed 8,124 community-dwelling people aged 70 years and older in three waves (1993-1998). MEASUREMENTS: The relationships between the primary outcome measure, lower body mobility (ability to walk several blocks and walk up one flight of stairs without difficulty), and smoking, exercise (HRS only), body mass index (BMI), and alcohol use were estimated in bivariate and multivariate analyses. RESULTS: Not smoking was strongly positively related to mobility, and the relative effects were similar in both panels. Among those with impaired mobility at baseline, not smoking was also strongly related to recovery. In the middle aged, there were consistent dose-response relationships between amount smoked and impaired mobility. Fifteen years after quitting, the risk of impaired mobility returned to that of never smokers. There was also a strong dose-response relationship between level of exercise and mobility. Inverted U-shaped relationships with mobility were observed for BMI and alcohol consumption. CONCLUSIONS: The relationships between not smoking and lower body mobility in middle-aged and older Americans are strong and consistent. Interventions aimed at reducing smoking have the potential to preserve mobility and thereby prolong health and independence in later life.
Keywords: Age Distribution; Aged; Aged, 80 and over; Alcohol Drinking; Body Mass Index; Exercise; Female; Humans; Leg; Logistic Models; Longitudinal Studies; Male; Marital Status; Middle Aged; Risk Factors; Sex Distribution; Smoking; Smoking cessation; United States; Walking

Caregiver report of hallucinations and paranoid delusions in elders aged 70 or older. - Carolyn L. Turvey; Schultz, Susan K.; Arndt, Stephan; Ellingrod, Vicki; Robert B Wallace; A. Regula Herzog (Int Psychogeriatr, 2001)
This study examined the demographic, medical, and psychiatric correlates of hallucinations and paranoid delusions reported by proxy informants for 822 elders aged 70 or older. This sample comprised people who were deemed unable to complete a direct interview in a large nationwide study of aging. Marital status, trouble with vision, and cognitive impairment were associated with report of both paranoid delusions and hallucinations. Depressive symptoms and stroke were associated with hallucinations only. These results suggest that inadequate external stimulation in the elderly leads to psychotic experiences.
Keywords: Aged; Aged, 80 and over; Aging; Caregivers; Cognition Disorders; Cohort Studies; Delusions; depression; Female; Follow-Up Studies; Hallucinations; Humans; Male; Marital Status; Paranoid Disorders; Risk Factors; Stroke; Surveys and Questionnaires; United States; Vision Disorders

Estimating the cost of informal caregiving for elderly patients with cancer. - Hayman, James A.; Kenneth M. Langa; Mohammed U Kabeto; Steven J. Katz; DeMonner, Sonya M.; M.E. Chernew; Slavin, Mitchell B.; A. Mark Fendrick (J Clin Oncol, 2001)
PURPOSE: As the United States population ages, the increasing prevalence of cancer is likely to result in higher direct medical and nonmedical costs. Although estimates of the associated direct medical costs exist, very little information is available regarding the prevalence, time, and cost associated with informal caregiving for elderly cancer patients. MATERIALS AND METHODS: To estimate these costs, we used data from the first wave (1993) of the Asset and Health Dynamics (AHEAD) Study, a nationally representative longitudinal survey of people aged 70 or older. Using a multivariable, two-part regression model to control for differences in health and functional status, social support, and sociodemographics, we estimated the probability of receiving informal care, the average weekly number of caregiving hours, and the average annual caregiving cost per case (assuming an average hourly wage of $8.17) for subjects who reported no history of cancer (NC), having a diagnosis of cancer but not receiving treatment for their cancer in the last year (CNT), and having a diagnosis of cancer and receiving treatment in the last year (CT). RESULTS: Of the 7,443 subjects surveyed, 6,422 (86%) reported NC, 718 (10%) reported CNT, and 303 (4%) reported CT. Whereas the adjusted probability of informal caregiving for those respondents reporting NC and CNT was 26%, it was 34% for those reporting CT (P <.05). Those subjects reporting CT received an average of 10.0 hours of informal caregiving per week, as compared with 6.9 and 6.8 hours for those who reported NC and CNT, respectively (P <.05). Accordingly, cancer treatment was associated with an incremental increase of 3.1 hours per week, which translates into an additional average yearly cost of $1,200 per patient and just over $1 billion nationally. CONCLUSION: Informal caregiving costs are substantial and should be considered when estimating the cost of cancer treatment in the elderly.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Cost of Illness; Family; Female; Home Nursing; Humans; Male; Multivariate Analysis; Neoplasms; Regression Analysis; United States

The explosion in paid home health care in the 1990s: who received the additional services? - Kenneth M. Langa; M.E. Chernew; Mohammed U Kabeto; Steven J. Katz (Med Care, 2001)
OBJECTIVE: Public expenditures for home health care grew rapidly in the 1990s, but it remains unclear to whom the additional services were targeted. This study tests whether the rapidly increasing expenditures were targeted to the elderly with high levels of disability and low levels of social support, 2 groups that have historically been higher users of paid home health and nursing home services. METHODS: The Asset and Health Dynamics Study, a nationally representative, longitudinal survey of people > or = 70 years of age (n = 7,443), was used to determine the association of level of disability and level of social support with the use of paid home care services in both 1993 and 1995. Multivariable regression models were used to adjust for sociodemographics, recent hospital or nursing home admissions, chronic medical conditions, and receipt of informal care from family members. RESULTS: Those with higher levels of disability received more adjusted weekly hours of paid home care in both 1993 and 1995. In 1993, users of paid home care with the least social support (unmarried living alone) received more adjusted weekly hours of care than the unmarried elderly living with others (24 versus 13 hours, P < 0.01) and the married (24 versus 18 hours, P = 0.06). However, by 1995, those who were unmarried and living with others were receiving the most paid home care: 40 versus 26 hours for the unmarried living alone (P < 0.05) and 24 hours for the married (P < 0.05). CONCLUSIONS: The recent large increase in formal home care services went disproportionately to those with greater social support. Home care policy changes in the early 1990s resulted in a shift in the distribution of home care services toward the elderly living with their children.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Chronic disease; Family Characteristics; Female; Financing, Government; Frail Elderly; Geriatric Assessment; Health Care Surveys; Health Expenditures; health policy; Home Care Services; Home Nursing; Humans; Longitudinal Studies; Male; Marital Status; Multivariate Analysis; Social Support; Socioeconomic factors; Surveys and Questionnaires; United States; Utilization Review

National estimates of the quantity and cost of informal caregiving for the elderly with dementia. - Kenneth M. Langa; M.E. Chernew; Mohammed U Kabeto; A. Regula Herzog; Mary Beth Ofstedal; Robert J. Willis; Robert B Wallace; Mucha, L.M.; Walter L. Straus; A. Mark Fendrick (J Gen Intern Med, 2001)
OBJECTIVE: Caring for the elderly with dementia imposes a substantial burden on family members and likely accounts for more than half of the total cost of dementia for those living in the community. However, most past estimates of this cost were derived from small, nonrepresentative samples. We sought to obtain nationally representative estimates of the time and associated cost of informal caregiving for the elderly with mild, moderate, and severe dementia. DESIGN: Multivariable regression models using data from the 1993 Asset and Health Dynamics Study, a nationally representative survey of people age 70 years or older (N = 7,443). SETTING: National population-based sample of the community-dwelling elderly. MAIN OUTCOME MEASURES: Incremental weekly hours of informal caregiving and incremental cost of caregiver time for those with mild dementia, moderate dementia, and severe dementia, as compared to elderly individuals with normal cognition. Dementia severity was defined using the Telephone Interview for Cognitive Status. RESULTS: After adjusting for sociodemographics, comorbidities, and potential caregiving network, those with normal cognition received an average of 4.6 hours per week of informal care. Those with mild dementia received an additional 8.5 hours per week of informal care compared to those with normal cognition (P < .001), while those with moderate and severe dementia received an additional 17.4 and 41.5 hours (P < .001), respectively. The associated additional yearly cost of informal care per case was 3,630 dollars for mild dementia, 7,420 dollars for moderate dementia, and 17,700 dollars for severe dementia. This represents a national annual cost of more than 18 billion dollars. CONCLUSION: The quantity and associated economic cost of informal caregiving for the elderly with dementia are substantial and increase sharply as cognitive impairment worsens. Physicians caring for elderly individuals with dementia should be mindful of the importance of informal care for the well-being of their patients, as well as the potential for significant burden on those (often elderly) individuals providing the care.
Keywords: Aged; Aged, 80 and over; Caregivers; Cost of Illness; Dementia; Female; Health Care Costs; Humans; Male; Multivariate Analysis; Regression Analysis; Severity of Illness Index; Time Factors; United States

Patterns and risk factors of change in somatic and mood symptoms among older adults. - Stephanie J. Fonda; A. Regula Herzog (Ann Epidemiol, 2001)
PURPOSE: This paper was concerned with patterns of individual-level, longitudinal change in depressive symptoms and factors related to those patterns among Americans 70+ years of age. Two types of depressive symptoms were considered, somatic and mood symptoms. The paper focused on whether the patterns of change and the risk factors for these two types of symptoms differed, as we might expect among old and oldest-old adults. METHODS: The analytic sample included self-respondents of the 1993--1995 Asset and Health Dynamics among the Oldest Old (AHEAD) study who were born in 1923 or earlier. Depressive symptoms were assessed using an abbreviated Center for Epidemiologic Studies-Depression (CES-D) Scale. The analyses involved examination of respondents' change scores in depressive symptoms and multivariate models using ordinary least squares (OLS) and seemingly unrelated regressions (SUR). RESULTS: In aggregate, somatic symptoms were more common than mood symptoms initially and over time. Despite differences in aggregate rates, AHEAD respondents' individual-level patterns of change for the two types of symptoms were similar; i.e., stability was the principal trend (53--60%), followed by improvement (21--26%). A number of factors related to change in one aspect of depressive symptoms and not the other, or had greater effects on one aspect of depressive symptoms than the other; e.g., physical health had greater effects on somatic than mood symptoms. CONCLUSIONS: This study suggests that, in investigations of the course and risk factors for depressive symptoms among people 70+ years of age, it is important to separate somatic symptoms from mood symptoms; their etiology may differ. In general, factors reflecting respondents' social milieu (e.g., bereavement, residential relocation) may have greater effects on mood than somatic symptoms, whereas certain factors representing physical health may have greater effects on somatic symptoms.
Keywords: Age Factors; Aged; Depressive Disorder; Female; Follow-Up Studies; Geriatric Assessment; Humans; Least-Squares Analysis; Longitudinal Studies; Male; Mood Disorders; Regression Analysis; Risk Factors; Severity of Illness Index; Somatoform Disorders; United States

Predictors of transitions in disease and disability in pre- and early-retirement populations. - Namkee G Choi; Schlichting-Ray, L. (J Aging Health, 2001)
OBJECTIVES: This study analyzed rates of prevalence and incidence of, and transitions in, disease and disability statuses of those aged 51 to 61 years and the predictors of the transition outcomes-remaining free of disease or disability, getting better, or getting worse-over a 2-year period. METHODS: Data from the 1992 and 1994 interview waves of the Health and Retirement Study were used for gender-separate binary and multinomial logistic regression analyses. RESULTS: Despite high prevalence and incidence rates of chronic disease and functional limitations, the improvement rates in disabilities were also high. For both genders, age, years of education, health-related behaviors, and comorbidity factors were significant predictors of the transition outcomes. DISCUSSION: The significance of health-related behaviors as predictors of transitions suggests that lifestyle factors may have a bigger influence on this age group than on older groups.
Keywords: Activities of Daily Living; Aged; Black or African American; Chronic disease; Disabled Persons; Female; Health Status; Hispanic or Latino; Humans; Male; Middle Aged; Retirement; Risk Factors; Sex Factors; Socioeconomic factors; United States; White People

Prevalence and outcomes of comorbid metabolic and cardiovascular conditions in middle- and older-age adults. - Oldrige, Neil B.; Timothy E. Stump; Nothwehr, F.; Daniel O. Clark (J Clin Epidemiol, 2001)
UNLABELLED: To estimate age group differences in the prevalence and outcomes of three common and often comorbid metabolic conditions (i.e., obesity, hypertension, and diabetes) and heart disease. DESIGN: Nationally representative prospective cohort study. SETTING: PARTICIPANTS' homes. PARTICIPANTS: 9825 adults aged 51 to 61 years (middle-age) in 1992, and 7370 adults aged 70 years and over (older-age) in 1993. MEASUREMENTS: Two-year dichotomous outcomes included: doctor visits, hospitalization, mobility difficulty, activity of daily living limitation, poor perceived health, and mortality. Odds ratios (OR) were adjusted for sociodemographic characteristics and history of cancer or lung disease. RESULTS: Those with one condition represented 80% and 70% of the middle- and older-age groups, respectively, while just 1-2% of each age group reported all three metabolic conditions. Thirteen percent and 32%, respectively, reported heart disease with or without metabolic conditions. Diabetes comorbid with other metabolic conditions, and particularly with heart disease, substantially elevated the risk of adverse outcomes such as health-related quality of life deficits, health services use, and mortality in both middle- and older-age adults. In the middle-age group, the OR was 6.81 for mortality in patients with a combination of obesity and diabetes and 6.10 in those with a combination of heart disease and diabetes. There also were significant ORs for mortality in middle-aged patients with heart disease (OR = 2.40), diabetes (OR = 2.63) and for those with a combination of obesity, hypertension, and diabetes (OR = 3.26). CONCLUSION: The impact of these often comorbid conditions underscores the importance of targeted and aggressive prevention, particularly among middle-age adults.
Keywords: Age Distribution; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; Diabetes Complications; Diabetes Mellitus; Female; Health Services for the Aged; Humans; Hypertension; Male; Middle Aged; Obesity; Odds Ratio; Outcome Assessment, Health Care; Prevalence; Prospective Studies; Quality of Life; United States

Proportional treatment effects for count response panel data: effects of binary exercise on health care demand. - Lee, Myoung Jae; Satoru Kobayashi (Health Econ, 2001)
We define conditional and marginal treatment effects appropriate for count data, and then conduct an empirical analysis for the effects of exercise on health care demand using panel data from the Health Retirement Study. The response variables are office visits to doctors and hospitalization days, and the treatments of interest are light and vigorous exercises. We found that short-run light exercise increases health care demand by 3-5%, whereas long-run light exercise decreases it by 3-6%. We also found that short-run vigorous exercise decreases health care demand by 1-2%, whereas long-run vigorous exercise decreases it by 1-3%. However, many of these numbers are not statistically significantly different from zero. These findings suggest that it will be difficult to reduce health care cost much by encouraging people to do more exercise--at least in the short-run.
Keywords: Adult; Aged; Aged, 80 and over; Bias; Cost Control; Cross-Sectional Studies; Data Interpretation, Statistical; Effect Modifier, Epidemiologic; Exercise Therapy; Female; Health Promotion; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Needs Assessment; Regression Analysis; Research Design; Treatment Outcome; United States

Self-restriction of medications due to cost in seniors without prescription coverage. - Michael A Steinman; Laura Sands; Kenneth E Covinsky (J Gen Intern Med, 2001)
OBJECTIVE: Little is known about patients who skip doses or otherwise avoid using their medications because of cost. We sought to identify which elderly patients are at highest risk of restricting their medications because of cost, and how prescription coverage modifies this risk. DESIGN AND PARTICIPANTS: Cross-sectional study from the 1995-1996 wave of the Survey of Asset and Health Dynamics Among the Oldest Old, a population-based survey of Americans age 70 years and older. MEASUREMENTS: Subjects were asked the extent of their prescription coverage, and whether they had taken less medicine than prescribed for them because of cost over the prior 2 years. We used bivariate and multivariate analyses to identify risk factors for medication restriction in subjects who lacked prescription coverage. Among these high-risk groups, we then examined the effect of prescription coverage on rates of medication restriction. MAIN RESULTS: Of 4,896 seniors who regularly used prescription medications, medication restriction because of cost was reported by 8% of subjects with no prescription coverage, 3% with partial coverage, and 2% with full coverage (P <.01 for trend). Among subjects with no prescription coverage, the strongest independent predictors of medication restriction were minority ethnicity (odds ratio [OR], 2.9 compared with white ethnicity; 95% confidence interval [95% CI], 2.0 to 4.2), annual income <$10,000 (OR, 3.8 compared with income > or =$20,000; 95% CI, 2.4 to 6.1), and out-of-pocket prescription drug costs >$100 per month (OR, 3.3 compared to costs < or =$20; 95% CI, 1.5 to 7.2). The prevalence of medication restriction in members of these 3 risk groups was 21%, 16%, and 13%, respectively. Almost half (43%) of subjects with all 3 risk factors and no prescription coverage reported restricting their use of medications. After multivariable adjustment, high-risk subjects with no coverage had 3 to 15 times higher odds of medication restriction than subjects with partial or full coverage (P <.01). CONCLUSIONS: Medication restriction is common in seniors who lack prescription coverage, particularly among certain vulnerable groups. Seniors in these high-risk groups who have prescription coverage are much less likely to restrict their use of medications.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Cross-Sectional Studies; Female; Humans; Insurance, Pharmaceutical Services; Male; Prescription Fees; Risk Factors; Socioeconomic factors; Treatment Refusal; United States

Socioeconomic status and the prevalence of health problems among married couples in late midlife. - Sven E. Wilson (Am J Public Health, 2001)
OBJECTIVES: This study analyzed the association between socioeconomic status (SES) and the prevalence of mutually occurring health problems among married couples in late midlife. METHODS: Data consisted of 4746 married couples aged 51 to 61 years from the 1992 US Health and Retirement Study. Two health measures were used: (1) self-assessed health status and (2) an index of functional limitations and activity restrictions. SES indicators were household income, education, and insurance coverage. RESULTS: In general, after adjustment for age cohort, a strong association was found between the health of a married individual and the health of his or her spouse. SES was highly associated with the joint occurrence of health problems among marriage partners. CONCLUSIONS: Public health policy should pay particular attention to the interaction between health, SES, and interpersonal relationships.
Keywords: Activities of Daily Living; Cohort Studies; Female; Health Status; Humans; Male; Marital Status; Middle Aged; Odds Ratio; Risk Factors; Socioeconomic factors; Spouses; United States

Valuation of life: a concept and a scale. - Lawton, M. Powell; Moss, Miriam; Hoffman, Christine; Kleban, Morton H.; Ruckdeschel, Katy; Winter, Laraine (J Aging Health, 2001)
OBJECTIVES: The objective was to derive and test the psychometric characteristics of a scale to measure Valuation of Life (VOL). METHODS: Four samples were used in successive phases of exploratory factor analysis, confirmatory factor analysis, reliability and validity testing, and exploration of response-error effects. Estimates of Years of Desired Life were obtained under a variety of hypothetical quality-of-life (QOL)-compromising conditions of poor health. RESULTS: Confirmed 13-item (Positive VOL) and 6-item (Negative VOL) factors were obtained. A significant relationship between VOL and most Years of Desired Life estimates remained when demographic, health, quality of life, and mental health measures were controlled. Analysis of Negative VOL revealed that some respondents misunderstand the meaning of an agree response to negatively phrased items. DISCUSSION: VOL is a cognitive-affective schema whose function as a mediator and moderator between health and end-of-life decisions deserves further research.
Keywords: Factor Analysis, Statistical; Humans; Psychometrics; Quality of Life; United States

The effect of smoking on health using a sequential self-selection model. - Kajal Chatterji Lahiri; Song, Jae G. (Health Econ, 2000)
We estimate a structural model of individual smoking behaviour emphasizing the role of individual risk belief on smoking choices. Our model consists of five equations: two selection equations for initiation and cessation decisions, and three switching outcome regressions for nonsmokers, ex-smokers, and current smokers. The presence of significant self-selectivity implies that the health effects of smoking based on sample proportions do not correctly indicate the true risk of cigarette smoking. Further, our evidence suggests that the self-selection in the cessation decision, but not in the initiation decision, is consistent with economic rationality. We estimate the model by full information maximum likelihood (FIML) with starting values from heteroskedasticity corrected Heckman-Lee two-step method using newly released Health and Retirement Study (HRS) data.
Keywords: Adult; Aged; Aged, 80 and over; Attitude to Health; Decision making; Health Behavior; Health Status; Health Surveys; Humans; Middle Aged; Models, Econometric; Predictive Value of Tests; Reproducibility of Results; Risk Factors; Risk-Taking; Selection Bias; Smoking; Smoking cessation; Surveys and Questionnaires; United States

Expectations among the elderly about nursing home entry. - Richard C Lindrooth; Hoerger, Thomas J.; Edward C Norton (Health Serv Res, 2000)
OBJECTIVE: To assess whether the covariates that explain expectations of nursing home entry are consistent with the characteristics of those who enter nursing homes. DATA SOURCES: Waves 1 and 2 of the Assets and Health Dynamics Among the Oldest Old (AHEAD) survey. STUDY DESIGN: We model expectations about nursing home entry as a function of expectations about leaving a bequest, living at least ten years, health condition, and other observed characteristics. We use an instrumental variables and generalized least squares (IV-GLS) method based on Hausman and Taylor (1981) to obtain more efficient estimates than fixed effects, without the restrictive assumptions of random effects. PRINCIPAL FINDINGS: Expectations about nursing home entry are reasonably close to the actual probability of nursing home entry. Most of the variables that affect actual entry also have significant effects on expectations about entry. Medicaid subsidies for nursing home care may have little effect on expectations about nursing home entry; individuals in the lowest asset quartile, who are most likely to receive these subsidies, report probabilities not significantly different from those in other quartiles. Application of the IV-GLS approach is supported by a series of specification tests. CONCLUSIONS: We find that expectations about future nursing home entry are consistent with the characteristics of actual entrants. Underestimation of risk of nursing home entry as a reason for low levels of long-term care insurance is not supported by this analysis.
Keywords: Activities of Daily Living; Aged; Attitude to Health; Data Interpretation, Statistical; Effect Modifier, Epidemiologic; Female; Geriatric Assessment; Health Care Surveys; Health Services Research; Health Status; Homes for the Aged; Humans; Least-Squares Analysis; Longevity; Male; Medicaid; Nursing homes; Patient Admission; Probability; Risk Factors; Surveys and Questionnaires; United States

Gender disparities in the receipt of home care for elderly people with disability in the United States. - Steven J. Katz; Mohammed U Kabeto; Kenneth M. Langa (JAMA, 2000)
CONTEXT: Projected demographic shifts in the US population over the next 50 years will cause families, health care practitioners, and policymakers to confront a marked increase in the number of people with disabilities living in the community. Concerns about the adequacy of community support are particularly salient to women, who make up a disproportionate number of disabled elderly people and who may be particularly vulnerable because they are more likely to live alone with limited financial resources. OBJECTIVE: To address gender differences in receipt of informal and formal home care. DESIGN, SETTING, AND PARTICIPANTS: Nationally representative survey conducted in 1993 among 7443 noninstitutionalized people (4538 women and 2905 men) aged 70 years or older. MAIN OUTCOME MEASURE: Number of hours per week of informal (generally unpaid) and formal (generally paid) home care received by survey participants who reported any activity of daily living (ADL) or instrumental activity of daily living (IADL) impairment (n = 3109) compared by gender and living arrangement and controlling for other factors. RESULTS: Compared with disabled men, disabled women were much more likely to be living alone (45.4% vs 16.8%, P<.001) and much less likely to be living with a spouse (27.8% vs 73.6%, P<.001). Overall, women received fewer hours of informal care per week than men (15.7 hours; 95% confidence interval [CI], 14.5-16.9 vs 21.2 hours; 95% CI, 19. 7-22.8). Married disabled women received many fewer hours per week of informal home care than married disabled men (14.8 hours; 95% CI, 13.7-15.8 vs 26.2 hours; 95% CI, 24.6-27.9). Children (>80% women) were the dominant caregivers for disabled women while wives were the dominant caregivers of disabled men. Gender differences in formal home care were small (2.8 hours for women; 95% CI, 2.5-3.1 vs 2.1 hours for men; 95% CI, 1.7-2.4). CONCLUSION: Large gender disparities appear to exist in the receipt of informal home care for disabled elderly people in the United States, even within married households. Programs providing home care support for disabled elderly people need to consider these large gender disparities and the burden they impose on families when developing intervention strategies in the community.
Keywords: Activities of Daily Living; Aged; Disabled Persons; Family; Female; Geriatrics; Home Care Services; Home Nursing; Humans; Male; Regression Analysis; Sex Distribution; United States

Health effects of involuntary job loss among older workers: findings from the health and retirement survey. - William T Gallo; Elizabeth H Bradley; Michele J. Siegel; Stanislav V Kasl (J Gerontol B Psychol Sci Soc Sci, 2000)
OBJECTIVES: To estimate the health consequences of involuntary job loss among older workers in the United States. METHODS: Using longitudinal data from the 1992 and 1994 waves of the Health and Retirement Survey, multivariate regression models were estimated to assess the impact of involuntary job loss on both physical functioning and mental health. Our analysis sample included 209 workers who experienced involuntary job loss between survey dates and a comparison group of 2,907 continuously employed workers. RESULTS: The effects of late-life involuntary job loss on both follow-up physical functioning and mental health were negative and statistically significant (p < .05), even after baseline health status and sociodemographic factors were controlled for. Among displaced workers, reemployment was positively associated with both follow-up physical functioning and mental health, whereas the duration of joblessness was not significantly associated with either outcome. DISCUSSION: The findings provide evidence of a causal relationship between job loss and morbidity among older workers. This relationship is reflected in both poorer physical functioning and mental health for workers who experience involuntary job loss. In addition to the economic consequences of worker displacement, there may be important health consequences of job loss, especially among older workers.
Keywords: Activities of Daily Living; Adaptation, Psychological; Aging; Female; Geriatric Assessment; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Retirement; Unemployment; United States

Health insurance and retirement behavior: evidence from the health and retirement survey. - Jeannette Rogowski; Lynn A Karoly (J Health Econ, 2000)
This paper studies the role of health insurance in the retirement decisions of older workers. As policymakers consider mechanisms for how to increase access to affordable health insurance for the near elderly, considerations of the potential labor force implications of such policies will be important to consider--potentially inducing retirements just at a time when the labor force is shrinking. Using data from the 1992 and 1996 waves of the Health and Retirement Survey, this study demonstrates that access to post-retirement health insurance has a large effect on retirement. Among older male workers, those with retiree health benefit offers are 68% more likely to retire (and those with non-employment based insurance are 44% more likely to retire) than their counterparts who would lose employment-based health insurance upon retirement. In addition, the study demonstrated that in retirement models, when retiree health benefits are controlled for, the effects of pension coverage are reduced, suggesting that these effects may have been overestimated in the prior literature.
Keywords: Aged; Career Mobility; Data collection; Decision making; Employment; Health Services Accessibility; Humans; Insurance, Health; Male; Retirement; Social Class; United States

HRS data set: Respondent Earnings and Social Security Benefits Files. - Unattributed (Soc Secur Bull, 2000)
Keywords: Humans; Income; Social Security; United States

Job characteristics and leisure physical activity. - Bei Wu; Frank Porell (J Aging Health, 2000)
OBJECTIVES: This study employs a sample population of older workers to estimate an empirical model of leisure exercise activity. Alternative theories relating work and leisure attitudes relevant for understanding the exercise behavior of older workers are tested empirically. METHODS: Responses of 6,433 full-time older workers (51 to 61 years old) from the 1992 Health and Retirement Study (HRS) are grouped into two white-collar and blue-collar worker categories and are analyzed to test whether self-reported levels of regular physical activity are associated with the physical demands and stress associated with one's job. RESULTS: Although the white-collar workers, whose jobs involve more physical efforts, are more likely to do light physical activity, the blue-collar workers, whose jobs are more physically demanding, tend to engage in more vigorous exercise. DISCUSSION: The empirical results are most supportive of the generalization theory, and they also illustrate the complexity of relationships between work and leisure physical activity.
Keywords: Demography; Exercise; Female; Humans; Job Description; Job Satisfaction; Leisure activities; Male; Middle Aged; Stress, Psychological; United States

Measuring morbidity: disease counts, binary variables, and statistical power. - Kenneth F Ferraro; Janet M Wilmoth (J Gerontol B Psychol Sci Soc Sci, 2000)
OBJECTIVES: This study compares the use of the binary disease variables with counts of the same conditions in models of self-rated health to better understand the advantages and disadvantages of each approach. In particular, the analysis seeks to determine if statistical power is adequate for the binary variable approach. METHODS: Morbidity measures from adults in 2 large national surveys were used in both cross-sectional and longitudinal analyses. RESULTS: Although differences across the approaches are modest, the binary variable approach offers greater explanatory power and slightly higher R2 values. Despite these advantages, statistical power is insufficient in some cases, especially for conditions that are relatively rare and/or that manifest modest differences on the outcome variable. DISCUSSION: Statistical power estimates are advisable when using the binary variable approach, especially if the list of diseases and health conditions is extensive. Although a simple count of diseases may be useful in some research applications, separate counts for serious and nonserious conditions should be more useful in many research projects while avoiding the risk of inadequate statistical power.
Keywords: Adult; Aged; Chronic disease; Cross-Sectional Studies; Female; Geriatric Assessment; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; Models, Statistical; United States

Pathways to retirement: patterns of labor force participation and labor market exit among the pre-retirement population by race, Hispanic origin, and sex. - Chenoa Flippen; Tienda, Marta (J Gerontol B Psychol Sci Soc Sci, 2000)
OBJECTIVES: This study examines the pre-retirement labor force participation behavior of Black, White, and Hispanic men and women to determine how patterns of labor market exit differ among groups. METHODS: We combine data from the first and second waves of the Health and Retirement Study and apply multinomial logit regression techniques to model labor force status in the first wave of the HRS and change over time. RESULTS: Black, Hispanic, and female elderly persons experience more involuntary job separation in the years immediately prior to retirement, and the resulting periods of joblessness often eventuate in "retirement" or labor force withdrawal. Minority disadvantage in human capital, health, and employment characteristics accounts for a large part of racial and ethnic differences in labor force withdrawal. Nevertheless, Black men and Hispanic women experience more involuntary labor market exits than Whites with similar socioeconomic and demographic characteristics. DISCUSSION: Workers most vulnerable to labor market difficulties during their youth confront formidable obstacles maintaining their desired level of labor force attachment as they approach their golden years. This has significant policy implications for the contours of gender and race/ethnic inequality among elderly persons, particularly as life expectancy and the size of the minority elderly population continue to increase.
Keywords: Aged; Black or African American; Cross-Cultural Comparison; Employment; Female; Hispanic or Latino; Humans; Logistic Models; Male; Middle Aged; Personnel Downsizing; Regression Analysis; Retirement; Sex Factors; Socioeconomic factors; United States; White People

Pension decisions in a changing economy: gender, structure, and choice. - Melissa A. Hardy; Kim Shuey (J Gerontol B Psychol Sci Soc Sci, 2000)
OBJECTIVES: As responsibility for financial security in retirement becomes more individualized, understanding the distribution and determinants of savings behavior grows in importance. Employed men and women often gain access to their pension assets when they change jobs. In this study gender differences in pre-retirement access to and disposition of accumulated pension assets are examined. METHODS: The authors used data from the Health and Retirement Study to model pension participation, disposition of pension assets, and use of cash settlements derived from a pension plan in a previous job. Logit models provided estimates of gender differences in access to pensions and the preservation of pension funds for retirement. RESULTS: Women were less likely to have participated in employer-sponsored pension plans; more likely to cash out accumulated pension assets when they changed jobs; and, when job changes occurred at relatively young ages, equally likely to spend the settlement. However, by their late 40s, women were more likely to save the settlement, a net gender difference that increased with age at which the settlement was received. DISCUSSION: The structure of employment compensation continues to place women at a disadvantage. Gender differences in earnings and fringe benefits not only affect current financial status, but also cast a shadow over future financial security. Although the gender gap in pension coverage has been reduced, women with pensions have access to lower benefits and less in accumulated assets. As these continuing deficits are addressed, enhancing women's tendency to save pension assets for retirement can help them build financial security.
Keywords: Age Factors; Choice Behavior; Decision making; Female; Humans; Male; Middle Aged; Models, Economic; Pensions; United States

Preferences for surrogate decision makers, informal communication, and advance directives among community-dwelling elders: results from a national study. - Faith P. Hopp (Gerontologist, 2000)
This study, drawing on a nationally representative sample of community-dwelling adults aged 70 and older from the second wave of the Asset and Health Dynamics Among the Oldest Old (AHEAD) survey, addresses the need for greater information on advance care planning among older adults. Older persons expect to draw on a diverse array of persons to make health care decisions for them when they are unable to do so, including spouses, when available, as well as younger generation members such as children and grandchildren. Completion of advance directives such as living wills and durable powers of attorney for health care was more common among White respondents than among African American respondents, and among high school- and college-educated respondents compared with those with less than a high school education. The results suggest the need to develop interventions aimed at strengthening knowledge and understanding of advance directives, particularly for African Americans and persons with lower levels of educational attainment. They further suggest the need for more research on the factors related to informal communication between older adults and their family members on issues related to advance care planning.
Keywords: Advance directives; Aged; Aged, 80 and over; Black or African American; Choice Behavior; Communication; Educational Status; Family; Female; Health education; Health Status; Humans; Logistic Models; Male; Needs Assessment; Surveys and Questionnaires; United States; White People

The prevalence and impact of accommodations on the employment of persons 51-61 years of age with musculoskeletal conditions. - Yelin, Edward; Sonneborn, Dean; Laura S. Trupin (Arthritis Care Res, 2000)
OBJECTIVE: To provide estimates of the frequency with which persons 51 to 61 years of age with musculoskeletal conditions receive workplace accommodations from their employers and to determine if the receipt of such accommodations is associated with higher rates of employment two years later. METHODS: The estimates derive from the Health and Retirement Survey, a national probability sample of 8,781 respondents who were interviewed both in 1992 and 1994 and who were between the ages of 51 and 61 years, of whom 5,495 reported one or more musculoskeletal conditions. We tabulated the frequency of accommodations provided in 1992 and then estimated the impact of accommodations and demographic and medical characteristics on 1994 employment status, using logistic regression. RESULTS: In 1992, about 14.40 million persons aged 51-61 years reported a musculoskeletal condition. Of these, 1.32 million (9.2%) reported a disability and were employed, the target population for accommodations. Overall, fewer than 1 in 5 persons with musculoskeletal conditions who had a disability and were employed indicated that they had received any form of accommodation on their current jobs. Although no form of accommodation was reported with great frequency, the most commonly used ones included getting someone to help do one's job (12.1%), scheduling more breaks during the work day (9.5%), changing the time that the work day started and stopped (6.3%), having a shorter work day (5.6%), getting special equipment (5.3%), and changing the work tasks (5.3%). Persons with one or more accommodations in 1992, however, were no more likely to be working in 1994 than those with none. Only one specific accommodation--getting someone to help do one's job--was associated with a higher rate of employment in 1994. CONCLUSIONS: Receipt of employment accommodations occurred infrequently, and was not generally associated with an improvement in the employment rate of persons with musculoskeletal conditions and disabilities.
Keywords: Disabled Persons; Employment, Supported; Female; Health Status; Health Surveys; Humans; Logistic Models; Longitudinal Studies; Male; Middle Aged; Morbidity; Musculoskeletal Diseases; Personnel Turnover; Program Evaluation; Surveys and Questionnaires; United States; Workload; Workplace

The racial crossover in comorbidity, disability, and mortality. - Nan E. Johnson (Demography, 2000)
This study analyzed one respondent per household who was age 70 or more at the time of the household's inclusion in Wave 1 (1993-1994) and whose survival status was determinable at Wave 2 (1995-1996) of the Survey on Asset and Health Dynamics Among the Oldest Old (AHEAD Survey). At age 76 at Wave 1, there was a racial crossover in the cumulative number of six potentially fatal diagnoses (chronic lung disease, cancer, heart disease, hypertension, diabetes, and stroke) from a higher cumulative average number for blacks to a higher average number for whites. Also, there was a racial crossover at age 86 in the cumulative average number of disabilities in the Advanced Activities of Daily Living (AADLs), from a higher average for blacks to a higher average for whites. Between Waves 1 and 2, there was a racial crossover in the odds of mortality from higher odds for blacks to higher odds for whites; this occurred at about age 81. The results are consistent with the interpretation that the racial crossover in comorbidity (but not the crossover in AADL disability) propelled the racial crossover in mortality.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Birth Certificates; Black People; Chronic disease; Comorbidity; Cross-Over Studies; Death Certificates; Disabled Persons; Female; Humans; Male; United States; White People

Racial variations in end-of-life care. - Faith P. Hopp; Sonia A. Duffy (J Am Geriatr Soc, 2000)
OBJECTIVES: To identify differences in advanced care planning and end-of-life decision-making between whites and blacks aged 70 and older. DESIGN: The Asset and Health Dynamics Among the Oldest Old (AHEAD) study is a nationally representative survey of adults who were aged 70 and older in 1993. Relatives (proxy respondents) for 540 persons who died between the first (1993) and second (1995) waves of the study were surveyed about advanced care planning and end-of-life decisions that were made for their family member who died. SETTING: Respondents were interviewed at home by telephone (n = 444) or in person (n = 95). PARTICIPANTS: The 540 proxy respondents included 454 whites and 86 blacks. MEASUREMENTS: Questions were asked about advance care planning and end-of-life decisions. RESULTS: Whites were significantly more likely than blacks to discuss treatment preferences before death (P = .002), to complete a living will (P = .001), and to designate a Durable Power of Attorney for Health Care (DPAHC) (P = .032). The treatment decisions for whites were more likely to involve limiting care in certain situations (P = .007) and withholding treatment before death (P = .034). In contrast, the treatment decisions for blacks were more likely to be based on the desire to provide all care possible in order to prolong life (P = .013). Logistic regression models revealed that race continued to be a significant predictor of advance care planning and treatment decisions even after controlling for sociodemographic factors. CONCLUSIONS: These findings suggest that there are important differences between blacks and whites regarding advanced care planning and end-of-life decision-making. Health professionals need to understand the diverse array of end-of-life preferences among various racial and ethnic groups and to develop greater awareness and sensitivity to these preferences when helping patients with end-of-life decision-making.
Keywords: Advance care planning; Advance directives; Aged; Aged, 80 and over; Attitude to Health; Black or African American; Cross-Cultural Comparison; Decision making; Female; Follow-Up Studies; Humans; Logistic Models; Male; Patient Care Planning; Terminal Care; United States; White People

Uninsured status and out-of-pocket costs at midlife. - Richard W. Johnson; Crystal, Stephen (Health Serv Res, 2000)
OBJECTIVE: To investigate how baseline health insurance coverage affects subsequent out-of-pocket costs and utilization of health services over a two-year period. DATA SOURCE: The first two waves of the Health and Retirement Study, a nationally representative survey of the noninstitutionalized population, ages 51 to 61 at baseline. Interviews were conducted in 1992 and 1994. Our sample consisted of 7,018 respondents who did not report public insurance as their sole source of coverage at baseline. STUDY DESIGN: We compared self-reports of physician visits, hospitalizations, and out-of-pocket health care costs, measured as payments to physicians, hospitals, and nursing homes, by type of insurance coverage at the beginning of the period. We estimated multivariate models of costs and service use to control for individual health, demographic, and economic characteristics and employed instrumental variable techniques to account for the endogeneity of insurance coverage. PRINCIPAL FINDINGS: Controlling for personal characteristics and accounting for the endogeneity of insurance coverage, persons at midlife with job-related health benefits went on to spend only about $50 per year less in out-of-pocket payments for health services than persons who lacked health insurance at the beginning of the period. However, they spent about $650 more per year in insurance premiums than the uninsured. The uninsured used relatively few health services, except when they were seriously ill, in which case they were likely to acquire public insurance. CONCLUSIONS: The medically uninsured appear to avoid substantial out-of-pocket health care costs by using relatively few health services when they are not seriously ill, and then relying upon health care safety nets when they experience medical problems. These results suggest that the main impact of non-insurance at midlife is not to place the locus of responsibility for costly health care upon individuals. Instead, it discourages routine care and transfers the costs of care for severe health events to other payers. Our findings on the high cost of employment-based coverage are consistent with evidence that the proportion of workers accepting health benefits from employers has been declining in recent years.
Keywords: Age Factors; Female; Financing, Personal; Health Care Surveys; Health Services; Health Status; Humans; Insurance Coverage; Insurance, Health; Longitudinal Studies; Male; Medically Uninsured; Middle Aged; Models, Econometric; Multivariate Analysis; Surveys and Questionnaires; United States

Characteristics of individuals with integrated pensions. - Bender, K A (Soc Secur Bull, 1999)
Employer pensions that integrate benefits with Social Security have been the focus of relatively little research. Since changes in Social Security benefit levels and other program characteristics can affect the benefit levels and other features of integrated pension plans, it is important to know who is covered by these plans. This article examines the characteristics of workers covered by integrated pension plans, compared to those with nonintegrated plans and those with no pension coverage. Integrated pension plans are those that explicitly adjust their benefit structure to help compensate for the employer's contributions to the Social Security program. There are two basic integration methods used by defined benefit (DB) plans. The offset method causes a reduction in employer pension benefits by up to half of the Social Security retirement benefit; the excess rate method is characterized by an accrual rate that is lower for earnings below the Social Security taxable maximum than above it. Defined contribution (DC) pension plans can be integrated along the lines of the excess rate method. To date, research on integrated pensions has focused on plan characteristics, as reported to the Bureau of Labor Statistics (BLS) through its Employee Benefits Survey (EBS). This research has examined the prevalence of integration among full-time, private sector workers by industry, firm size, and broad occupational categories. However, because the EBS provides virtually no data on worker characteristics, analyses of the effects of pension integration on retirement benefits have used hypothetical workers, varying according to assumed levels of earnings and job tenure. This kind of analysis is not particularly helpful in examining the potential effects of changes in the Social Security program on workers' pension benefits. However, data on pension integration at the individual level are available, most recently from the Health and Retirement Study (HRS), a nationally representative survey of individuals aged 51-61 in 1992. This dataset provides the basis for the analysis presented here. The following are some of the major findings from this analysis. The incidence of pension integration in the HRS sample is 32 percent of all workers with a pension (14 percent of all workers). The HRS can also identify integrated DC plans, a statistic that is not available from BLS data. The rate of integration for workers with only DC plans is 8 percent. After controlling for other variables, several socio-demographic characteristics are significantly related to the incidence of integration. The probability of having an integrated pension is 4.6 percentage points less for men compared to women. Non-Hispanic blacks are 6.4 percentage points less likely than non-Hispanic whites to have integrated pensions. Union members are 14 percentage points less likely to have integrated pensions, while workers with less than a graduate level education are at least 15 percentage points more likely to have a pension that is integrated. Some earnings and pension characteristics are also significantly correlated with pension integration. Earnings are positively related, with the probability of having an integrated pension increasing by 2 percentage points for an increase of $1,000 in annual pay. An even larger effect comes from earning at or above the Social Security taxable maximum. Workers at or above this income level are 10 percentage points more likely to have an integrated plan, but for those with more than one plan the probability of pension integration goes up by 13 percentage points.
Keywords: Bias; Data collection; Educational Status; ethnicity; Female; Humans; Income; Labor Unions; Male; Middle Aged; Occupations; Pensions; Regression Analysis; Reproducibility of Results; Retirement; Sex Factors; Social Security; Socioeconomic factors; United States

A comparison of correlates of cognitive functioning in older persons in Taiwan and the United States. - Mary Beth Ofstedal; Zachary Zimmer; Hui-Sheng Lin (J Gerontol B Psychol Sci Soc Sci, 1999)
OBJECTIVES: This article compares patterns of association between cognitive functioning and a number of sociodemographic and health correlates among older persons in Taiwan and the United States. METHODS: The study uses data from the 1993 Survey of Health and Living Status of the Elderly in Taiwan and the 1993 Study of Asset and Health Dynamics Among the Oldest Old in the United States. Separate multivariate regression models are employed for each country to examine the effects of sociodemographic and health factors on cognitive functioning, and to examine the marginal impact of cognitive functioning on activities of daily living (ADL) and instrumental ADL (IADL) functioning. RESULTS: Results of the multivariate analyses show similar patterns of association across the two countries and replicate findings from previous studies. Increasing age, female gender, lower education, depression, and selected health conditions are associated with lower cognitive functioning. In addition, although a significant predictor of both ADL and IADL impairments, cognitive functioning is more powerful with respect to explaining IADL impairments. DISCUSSION: Study findings suggest that the cognitive measures are capturing similar dimensions in Taiwan and the United States, and that factors associated with cognitive functioning and its consequences with respect to physical functioning are similar in the two countries.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Cognition; Cross-Cultural Comparison; depression; Educational Status; Female; Geriatric Assessment; Health Status; Humans; Male; Multivariate Analysis; Regression Analysis; Sex Factors; Socioeconomic factors; Surveys and Questionnaires; Taiwan; United States

Gender differences in pension wealth: estimates using provider data. - Richard W. Johnson; Sambamoorthi, Usha; Crystal, Stephen (Gerontologist, 1999)
Information from pension providers was examined to investigate gender differences in pension wealth at midlife. For full-time wage and salary workers approaching retirement age who had pension coverage, median pension wealth on the current job was 76% greater for men than women. Differences in wages, years of job tenure, and industry between men and women accounted for most of the gender gap in pension wealth on the current job. Less than one third of the wealth difference could not be explained by gender differences in education, demographics, or job characteristics. The less-advantaged employment situation of working women currently in midlife carries over into worse retirement income prospects. However, the gender gap in pensions is likely to narrow in the future as married women's employment experiences increasingly resemble those of men.
Keywords: Female; Humans; Male; Occupations; Pensions; Sex Factors; United States; Women, Working

Health problems as determinants of retirement: are self-rated measures endogenous? - Debra S. Dwyer; Olivia S. Mitchell (J Health Econ, 1999)
We explore alternative measures of unobserved health status in order to identify effects of mental and physical capacity for work on older men's retirement. Traditional self-ratings of poor health are tested against more objectively measured instruments. Using the Health and Retirement Study (HRS), we find that health problems influence retirement plans more strongly than do economic variables. Specifically, men in poor overall health expected to retire one to two years earlier, an effect that persists after correcting for potential endogeneity of self-rated health problems. The effects of detailed health problems are also examined in depth.
Keywords: Health Services Research; Health Status Indicators; Humans; Male; Models, Statistical; Retirement; Self-Assessment; United States

Healthy bodies and thick wallets: the dual relation between health and economic status. - James P Smith (J Econ Perspect, 1999)
The first section of this paper documents the size of the association between health and one prominent economic status measure--household wealth. The next section deals with how health influences economic status by sketching out reasons why health may alter household savings (and eventually wealth) and then providing estimates of the empirical magnitude of these effects. The third section shifts attention to the other pathway--the links between economic status and health--and summarizes major controversies and evidence surrounding these issues.
Keywords: Financing, Personal; Health Expenditures; Health Status; Humans; Socioeconomic factors; United States

Prevalence and severity of urinary incontinence in older African American and Caucasian women. - Fultz, Nancy H.; A. Regula Herzog; Trivellore E. Raghunathan; Robert B Wallace; Diokno, A.C. (J Gerontol A Biol Sci Med Sci, 1999)
BACKGROUND: Few studies have investigated the prevalence and severity of urinary incontinence in older African American women. Comparisons of findings with those for older Caucasian women could provide important clues to the etiology of urinary incontinence and be used in planning screening programs and treatment services. METHODS: Data are from the first wave of the Asset and Health Dynamics Among the Oldest Old (AHEAD) study. A nationally representative sample of noninstitutionalized adults 70 years of age and older was interviewed. African Americans were oversampled to ensure that there would be enough minority respondents to compare findings across racial groups. RESULTS: A statistically significant relationship was found between race and urinary incontinence in the previous year: 23.02% of the Caucasian women reported incontinence, compared with 16.17% of the African American women. Other factors that appear to increase the likelihood of incontinence include education, age, functional impairment, sensory impairment, stroke, body mass, and reporting by a proxy. Race was not related to the severity (as measured by frequency) of urine loss among incontinent older women. CONCLUSION: This study identifies or confirms important risk factors for self-reported urinary incontinence in a national context, and suggests factors leading to protection from incontinence. Race is found to relate to incontinence, with older African American women reporting a lower prevalence.
Keywords: Aged; Aged, 80 and over; Black or African American; Female; Humans; Prevalence; Risk Factors; United States; Urinary incontinence; White People

Racial differences in education, obesity, and health in later life. - Christine L Himes (Ann N Y Acad Sci, 1999)
Keywords: Age Distribution; Aged; Arthritis; Black or African American; Diabetes Mellitus; Educational Status; Female; Health Status; Health Surveys; Humans; Logistic Models; Male; Obesity; Prevalence; Social Class; United States; White People

Retirement patterns and bridge jobs in the 1990s. - Joseph F. Quinn (EBRI Issue Brief, 1999)
During most of the post-World War II period, American men have been leaving the labor force at earlier and earlier ages. Evidence suggests that this trend has been under way for more than a century. However, in the mid-1980s, this trend came to an abrupt halt. Male labor force participation rates have been flat since 1985, and have actually increased over the past several years. Understanding these issues is especially important given the looming increase in the Social Security normal retirement age to 67 and the possibility of even more increases in the ages of eligibility under Social Security and Medicare reform. Because of the influx of married women into the labor market in the post-World War II period, older women's participation rates did not decline as men's did. In contrast, their rates were relatively steady, rising or falling very slowly. Since the mid-1980s, however, older women's participation rates have increased significantly. Many more older men and women are working today than the pre-1986 trends would have suggested. Many older Americans leave the labor force gradually, utilizing "bridge jobs" between employment on a full-time career job and complete labor force withdrawal. These bridge jobs are often part-time, often in a new line of work, and sometimes involve a switch from wage and salary work to self-employment. Estimates suggest that between one-third and one-half of older Americans will work on a bridge job before retiring completely, and for these workers retirement is best viewed as a process, not as a single event. These changes in retirement behavior are consistent with societal changes that have altered the relative attractiveness of work and leisure late in life. Mandatory retirement has been outlawed for most American workers. Social Security has become more age-neutral, no longer penalizing the average worker who wants to continue working after age 65. An increasing proportion of employer pension coverage has been in defined contribution plans, which do not contain the age-specific retirement incentives that many defined benefit plans do. The composition of jobs has shifted from manufacturing to service occupations. Americans are living longer and healthier lives, and many look forward to years to productive activity after age 65. These structural changes have been accompanied by an important cyclical factor: the strength of the American economy over the past decade. This has increased the demand for all types of labor, including older workers. Evidence suggests that there is more than this cyclical factor at work, however, and that new attitudes about work late in life are developing. Labor supply decisions late in life are correlated in expected ways with the individual's health (measured in several ways), age, and pension and health insurance status. Retirement patterns in America are much richer and more varied than the stereotypical one-step view of retirement suggests. Public policy is changing in ways that make continued work late in life more likely. If employers are willing to provide flexible job opportunities to meet the needs of these potential employees, then society can tap a growing pool of older, experienced, and willing workers for years to come.
Keywords: Aged; Attitude; Career Mobility; Data collection; Employment; Female; Humans; Male; Middle Aged; Multivariate Analysis; Retirement; United States

Transitions in employment, morbidity, and disability among persons ages 51-61 with musculoskeletal and non-musculoskeletal conditions in the US, 1992-1994. - Yelin, Edward; Laura S. Trupin; Sebesta, D.S. (Arthritis Rheum, 1999)
OBJECTIVE: To provide estimates of the prevalence of musculoskeletal conditions in a sample of persons ages 51-61 living in the community in the US in 1992, to indicate the incidence of such conditions between 1992 and 1994, and to describe the proportion of individuals with these conditions who developed or recovered from disability and who left and entered employment during this time. METHODS: The estimates were derived from the Health and Retirement Survey, consisting of data on a national probability sample of 8,739 persons, ages 51-61, who were interviewed in the community in 1992 and reinterviewed in 1994. RESULTS: In 1992, 62.4% of persons (14.4 million) between the ages of 51 and 61 years reported at least 1 musculoskeletal condition; the rate increased to 70.5% by 1994. More than 40% of persons with musculoskeletal conditions reported disability, which was almost 90% of all persons with disability in this age group. Persons with musculoskeletal conditions had lower employment rates, were less likely to enter employment, and were more likely to leave employment compared with persons without these conditions. High rates of disability account for much of these differences. CONCLUSION: Musculoskeletal conditions affected more than two-thirds of persons ages 51-61 and accounted for all but 10% of those with disabilities. The prevention of disability among such persons should improve their employment prospects.
Keywords: Chronic disease; Disability Evaluation; Disabled Persons; Employment; Female; Humans; Incidence; Male; Middle Aged; Morbidity; Musculoskeletal Diseases; Prevalence; Retirement; United States

Life transitions and health insurance coverage of the near elderly. - Frank A Sloan; Conover, C.J. (Med Care, 1998)
OBJECTIVES: This study addresses three issues. (1) What are demographic wealth, employment, and health characteristics of near-elderly persons losing or acquiring health insurance coverage? Specifically, (2) what are the effects of life transitions, including changes in employment status, health, and marital status? (3) To what extent do public policies protect such persons against coverage loss, including various state policies recently implemented to increase access to insurance? METHODS: The authors used the 1992 and 1994 waves of the Health and Retirement Study to analyze coverage among adults aged 51 to 64 years. RESULTS: One in five near-elderly persons experienced a change in insurance coverage from 1992 to 1994. Yet, there was no significant change in the mix of coverage as those losing one form of coverage were replaced by others acquiring similar coverage. CONCLUSIONS: Individuals whose health deteriorated significantly were not more likely than others to suffer a subsequent loss of coverage, due to substitution of retiree or individual coverage for those losing private coverage and acquisition of Medicaid and Medicare coverage for one in five uninsured. State policies to increase access to private health insurance generally did not prevent individuals from losing coverage or allow the uninsured to gain coverage. Major determinants of the probability of being insured were education, employment status of person and spouse, and work disability status. Other measures of health and functional status did not affect the probability of being insured, but had important impacts on the probability of having public coverage, conditional on being insured.
Keywords: Death; Employment; health policy; Health Services Research; Health Status Indicators; Humans; Insurance Coverage; Life Change Events; Medicaid; Medically Uninsured; Medicare; Middle Aged; Retirement; Spouses; United States

Occupational injuries among older workers with disabilities: a prospective cohort study of the Health and Retirement Survey, 1992 to 1994. - Zwerling, Craig; Nancy L. Sprince; Charles S. Davis; Paul S. Whitten; Robert B Wallace; Steven G Heeringa (Am J Public Health, 1998)
OBJECTIVES: We tested the hypothesis that among older workers, disabilities in general, and hearing and visual impairments in particular, are risk factors for occupational injuries. METHODS: Using the first 2 interviews of the Health and Retirement Study, a nationally representative survey of Americans aged 51 to 61 years, we conducted a prospective cohort study of 5600 employed nonfarmers. RESULTS: Testing a logistic regression model developed in a previous cross-sectional study, we found that the following occupations and risk factors were associated with occupational injury as estimated by odds ratios: service personnel, odds ratio = 1.71 (95% confidence interval = 1.13, 2.57); mechanics and repairers, 3.47 (1.98, 6.10); operators and assemblers, 2.33 (1.51, 3.61); laborers, 3.16 (1.67, 5.98); jobs requiring heavy lifting, 2.05 (1.55, 2.70); self-employment, 0.50 (0.34, 0.73); and self-reported disability, 1.58 (1.14, 2.19). Replacing the general disability variable with specific hearing and visual impairment variables, we found that poor hearing (1.35 [0.95, 1.93]) and poor sight (1.45 [0.94, 2.22]) both had elevated odds ratios. CONCLUSIONS: Poor sight and poor hearing, as well as work disabilities in general, are associated with occupational injuries among older workers.
Keywords: Accidents, Occupational; Age Distribution; Aged; Aged, 80 and over; Analysis of Variance; Cross-Sectional Studies; Disabled Persons; Female; Health Surveys; Humans; Logistic Models; Male; Middle Aged; Odds Ratio; Prospective Studies; Retirement; Risk Factors; United States

A comparative analysis of ADL questions in surveys of older people. - Willard L Rodgers; Baila Miller (J Gerontol B Psychol Sci Soc Sci, 1997)
This article describes questions designed to assess limitations with respect to activities of daily living (ADLs) that were asked on the first wave of the AHEAD study, and it assesses their cross-sectional measurement properties. It also provides comparisons between those questions and parallel questions that have been asked on two other surveys of the elderly population in the United States: the 1984 Supplement on Aging (SOA) to the National Health Interview Survey and the screener for the 1982 National Long Term Care Survey (NLTCS). It also compares a single item from the 1990 Census. It then compares the ways in which the same individuals answer these different versions of ADL questions, using data from subsamples of the AHEAD respondents who were also asked the SOA, NLTCS, or Census questions. The analysis shows that there is a substantial amount of measurement error in the answers to ADL questions, and it suggests that this is a major contributor to apparent improvements and declines in functional health observed in longitudinal data.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Geriatric Assessment; Health Services; Health Status; Health Surveys; Humans; Regression Analysis; Reproducibility of Results; United States

Demographic and economic correlates of health in old age. - James P Smith; Raynard Kington (Demography, 1997)
In this paper we examine disparities in the ability to function among older Americans. We place special emphasis on two goals: (1) understanding the quantitatively large socioeconomic status-health gradient, and (2) the persistence in health outcomes over long periods. We find that there exist strong contemporaneous and long-run feedbacks from health to economic status. In light of these feedbacks, it is important to distinguish among alternative sources of income and the recipient of income in the household. This research also demonstrates that health outcomes at old age are influenced by health attributes of past, concurrent, and future generations of relatives. Finally, we find that the demographic and economic differences that exist among them explain functional health disparities by race and ethnicity, but not by gender.
Keywords: Activities of Daily Living; Aged; Cohort Studies; Demography; Disabled Persons; ethnicity; Female; Health Status; Humans; Income; Male; Models, Econometric; Racial Groups; Socioeconomic factors; United States

Employee benefits, retirement patterns, and implications for increased work life. - Fronstin, Paul (EBRI Issue Brief, 1997)
This Issue Brief examines why policymakers are concerned about the trend toward early retirement and how it relates to Social Security, Medicare, and employee health and retirement benefits. It reviews the rationale for the effects of economic incentives on early retirement decisions and includes a summary of empirical literature on the retirement process. It presents data on how employee benefits influence workers' expected retirement patterns. Finally, it examines the implications of public policies to reverse early-retirement trends and raise the eligibility age for Social Security and Medicare. An employee Benefit Research Institute/Gallup survey indicates that there is a direct link between a worker's decision to retire early and the availability of retiree health benefits. In 1993, 61 percent of workers reported that they would not retire before becoming eligible for Medicare if their employer did not provide retiree health benefits. Participation in a pension plan can be an important determinant of retirement. Twenty-one percent of pension plan participants planned to stop working before age 65, compared with 12 percent among nonparticipants. Workers whose primary pension plan was a defined benefit plan were more likely to expect to stop working before age 65 (23 percent) than workers whose primary plan was a defined contribution plan (18 percent). Expected income replacement rates effect retirement patterns, indicating that as the expected replacement increases, the probability of expecting to stop working before age 65 increases. Twenty-two percent of workers with an expected income replacement rate below 60 percent expected to stop working before age 65, compared with 29 percent for those in the 60-69 percent replacement range, and 30 percent for those in the 70-79 percent replacement range. Workers expecting to receive retiree health insurance are more likely to expect to stop working before age 65 than workers who do not expect to have retiree health insurance. Twenty-one percent of workers with retiree health insurance expected to stop working before age 65, compared with 12 percent of workers not expecting to receive retiree health insurance. The Social Security Old-Age and Survivors Insurance (OASI) program depends on obtaining sufficient revenue from active workers' payroll taxes to fund the benefits received by retired beneficiaries. Funding the program in the past was in large part effortless because of the relatively large number of workers per retiree. Today, funding the program is a greater challenge because the ratio of workers to retirees has fallen. Policymakers have been able to agree that reform of the program is necessary for its survival; however, the debate over options to reform the program is just beginning, and it is likely to be a long time before a consensus emerges.
Keywords: Age Factors; Aged; Employment; Female; Health Benefit Plans, Employee; Health Status Indicators; Humans; Male; Medicare; Middle Aged; Pensions; Private Sector; Retirement; Social Security; United States

Health insurance coverage at midlife: characteristics, costs, and dynamics. - Richard W. Johnson; Crystal, Stephen (Health Care Financ Rev, 1997)
Recent data from the first two waves of the Health and Retirement Study are analyzed to evaluate prevalence of different types of health insurance, characteristics of different plan types, and change sin coverage as individuals approach retirement age. Although overall rates of coverage are quite high among the middle-aged, the risk of noncoverage is high within many disadvantaged groups, including Hispanics, low-wage earners, and the recently disabled. Sixty percent of individuals with health benefits are enrolled in health maintenance organizations (HMOs) or preferred provider organizations (PPOs). In addition, one-fourth of enrollees in fee-for-service (FFS) plans report restrictions in their access to specialists.
Keywords: Age Factors; Costs and Cost Analysis; Demography; Female; Health Benefit Plans, Employee; Health Care Surveys; Humans; Insurance Coverage; Insurance, Health; Logistic Models; Longitudinal Studies; Male; Middle Aged; United States

Measures of cognitive functioning in the AHEAD Study. - A. Regula Herzog; Robert B Wallace (J Gerontol B Psychol Sci Soc Sci, 1997)
Decline in cognitive functioning and onset of cognitive impairment are potentially important predictors of elderly persons needing informal assistance and formal health care. This article describes the measures of cognitive functioning that were developed for the Asset and Health Dynamics Among the Oldest Old (AHEAD) study of some 6,500 Americans aged 70 years and older. The study was designed to investigate the impact of health on disbursement of family and economic resources. Evaluation of the cognitive measures in terms of psychometric properties and missing data, telephone administration, and formation of an aggregate index is encouraging. Their construct validity is evidenced by their correlations with sociodemographic characteristics and health indicators that replicate existing findings as well as by their prediction of IADL and ADL functioning that are consistent with theory.
Keywords: Aged; Aged, 80 and over; Cognition; Geriatric Assessment; Health Status; Health Surveys; Humans; Longitudinal Studies; Memory; Mental Status Schedule; Psychological Tests; Socioeconomic factors; United States

Medical insurance and the use of health care services by the elderly. - Michael D Hurd; Kathleen McGarry (J Health Econ, 1997)
The objective of this paper is to find how health insurance influences the use of health care services by the elderly. On the basis of the first wave of the Asset and Health Dynamics Survey, we find that those who are the most heavily insured use the most health care services. Because our data show little relationship between observable health measures and either the propensity to hold or to purchase private insurance, we interpret this as an effect of the incentives embodied in the insurance, rather than as the result of adverse selection in the purchase of insurance.
Keywords: Activities of Daily Living; Aged; Health Care Surveys; Health Services for the Aged; Health Status Indicators; Hospitalization; Humans; Insurance, Health; Medicare; Office Visits; Patient Acceptance of Health Care; Private Sector; Probability; United States

Patterns of in-home care among elderly black and white Americans. - Norgard, T.M.; Willard L Rodgers (J Gerontol B Psychol Sci Soc Sci, 1997)
This study examines the use of informal and formal sources of care by elderly Black and White Americans (n = 2,847) who are functionally impaired and noninstitutionalized. The data are from the Asset and Health Dynamics Among the Oldest Old (AHEAD) study. Detailed baseline characteristics are provided and logistic regressions are used to assess the likelihood of (a) receiving in-home assistance from any source, (b) using any informal sources of in-home care, (c) using any formal sources, and (d) using formal sources of in-home care with informal sources of home care. Results of the logistic regressions indicate that, compared to Whites, Black elders were less likely to receive assistance and to use informal sources of home care.
Keywords: Aged; Aged, 80 and over; Black or African American; Caregivers; Female; Home Care Services; Humans; Male; Socioeconomic factors; United States; White People

Complex marital histories and economic well-being: the continuing legacy of divorce and widowhood as the HRS cohort approaches retirement. - Karen C. Holden; Kuo, H.H. (Gerontologist, 1996)
We use data from the first wave of the Health and Retirement Survey (HRS) to examine the marital histories of this cohort of women and men on the verge of retirement. The legacy of past increases in divorce rates is evident in the complex marital histories of HRS households and the relationship between those histories and current economic status. Couples in a first marriage now make up only one-quarter of black households and fewer than half of all white and Hispanic households. In over one-third of all married-couple households, at least one spouse had a previous marriage that ended in divorce or widowhood. These couples have significantly lower incomes and assets than couples in first marriages. Contrary to the popular notion that private and public insurance better provide for the security of widows than divorced persons, currently widowed households and couples in which the prior marriage of one spouse had ended in widowhood are no better off than are their divorced peers. This holds true for both black and white households. From a single cross-section, one cannot tell what caused these differences in income and wealth across marital status groups although it is clear that women and blacks spend a higher percentage of their lifetime outside of marriage than do men and whites. We also speculate from estimates of widowhood expectations for a subset of married respondents that underestimating the chances of widowhood--because both men and women overestimate their chances of joint survival--may be a factor in the relatively low economic status of widows. Because couples in life-long marriages have been the traditional standard upon which marital property reform and the survivorship rules of private and public programs are based, their diminishing importance among all households raises concern about the protection provided by these institutions against the long-term economic consequences of past and future marital dissolution.
Keywords: Cross-Sectional Studies; Divorce; Female; Humans; Life Tables; Male; Middle Aged; Poverty; Retirement; United States; Widowhood

Disentangling the effects of disability status and gender on the labor supply of Anglo, black, and Latino older workers. - Santiago, A.M.; Clara G. Muschkin (Gerontologist, 1996)
Utilizing data from the 1991 Health and Retirement Study Early Release File, this article examines the effects of disability status on labor force participation and earnings of preretirement workers aged 50 to 64. Results from our hierarchical regression models suggest that poor health and the presence of a work disability significantly reduced the labor force participation and earnings of older men and women. These analyses also suggest that economic well-being was constrained by the costs associated with additional "minority statuses." For example, the odds of being employed were reduced by approximately 46% for black men with disabilities. Further, the earnings of black men were 17% lower than the earnings of their nondisabled counterparts.
Keywords: Black or African American; Disabled Persons; Employment; Female; Hispanic or Latino; Humans; Male; Middle Aged; Models, Theoretical; Multivariate Analysis; Sex Factors; United States; White People

The extent of private and public health insurance coverage among adult Hispanics. - Ronald J. Angel; Jacqueline L. Angel (Gerontologist, 1996)
Data from the Health and Retirement Survey reveal extremely low levels of health insurance coverage among Hispanics and, especially, among Mexican Americans. The data reveal that this lack of insurance is associated with lower rates of employer-based and privately purchased coverage. Even after controlling for a large number of insurance-related factors, Hispanics have rates of health insurance coverage that are lower than those of either non-Hispanic blacks or whites. This serious lack of health insurance coverage among preretirement-age Hispanics has serious implications both for health, because the lack of insurance represents a major barrier to health care, and for the adequacy of retirement coverage, because private insurance represents an important supplement to Medicare.
Keywords: Adult; Aged; Employment; Female; Health Services Accessibility; Hispanic or Latino; Humans; Insurance, Health; Male; Medical Assistance; Middle Aged; Multivariate Analysis; United States

The health-wealth connection: racial differences. - Dennis G. Shea; Toni Miles; Mark D Hayward (Gerontologist, 1996)
This article examines the theoretical connection between health capital and financial capital in an economic life-cycle model, exploring possible explanations for racial differences in capital accumulation behavior. Using data from the Health and Retirement Survey, detailed descriptive analysis and a comparison of regression models for health and financial capital are presented. The results, although preliminary and based on cross-section data, suggest possible racial differences in the connection between health and wealth and deserve further study.
Keywords: Black or African American; Cross-Sectional Studies; Female; Health Status; Humans; Income; Male; Middle Aged; Models, Theoretical; Regression Analysis; United States; White People

Minority perspectives from the Health and Retirement Study. Introduction: health and retirement among ethnic and racial minority groups. - James S Jackson; Lockery, Shirley A.; Juster, F. Thomas (Gerontologist, 1996)
Keywords: Aged; Health Status; Humans; Minority Groups; Prospective Studies; Quality of Life; Retirement; United States

Physical function among retirement-aged African American men and women. - Daniel O. Clark; Christopher M. Callahan; Mungai, S.M.; Frederic D Wolinsky (Gerontologist, 1996)
Prior attempts to identify factors associated with physical function (here, major lower body movements) among African Americans have been constrained by a narrow range of measures, small sample sizes, or both. The 1992 Health and Retirement Study (HRS) contains a substantial over-sample of African Americans (649 men and 957 women self-respondents aged 51 to 61 years), and detailed measures of high-risk behaviors, disease prevalence and severity, impairment, and physical function. We extend the natural history of disease to the natural history of functional status and model sociodemographic characteristics, high-risk behaviors, disease prevalence and severity, and impairments as direct and indirect influences on physical function in this African American sample. This natural history of functional status model fits the data well for both men (ROC = .88) and women (ROC = .83), although there are gender differences. Slightly over one-half of the women report some difficulty in physical function, compared with one-third of the men. Women also have a higher mean body-mass and report a greater prevalence and severity in 6 of 9 chronic diseases and more pain, but are less likely to smoke or abuse alcohol than men. Importantly, many of the factors with the largest direct and indirect associations with difficulty in physical function among these African American men (alcohol abuse, smoking, body mass, diabetes, heart disease, cerebrovascular disease, arthritis, and pain) and women (alcohol abuse, body mass, arthritis, and respiratory illness) are all potentially preventable or manageable.
Keywords: Black or African American; Female; Health Behavior; Health Status; Humans; Male; Middle Aged; Models, Theoretical; Odds Ratio; Retirement; United States

Retirement expectations: differences by race, ethnicity, and gender. - Honig, Marjorie (Gerontologist, 1996)
Analyses by race and ethnicity of several important dimensions of labor market behavior have been constrained in the past by limited samples of the African American and Hispanic populations. This article uses data from the first wave of the Health and Retirement Survey, which oversamples these populations, to compare the retirement plans of African American, Hispanic, and white married men and women. Findings suggest that retirement expectations may accurately forecast retirement behavior and that the differences by race and ethnicity, as well as by gender, that are evident in retirement plans are likely to be reflected in retirement outcomes.
Keywords: ethnicity; Female; Health Knowledge, Attitudes, Practice; Humans; Male; Middle Aged; Models, Theoretical; Pensions; Retirement; Sex Factors; Social Security; United States

Risk factors for occupational injuries among older workers: an analysis of the health and retirement study. - Zwerling, Craig; Nancy L. Sprince; Robert B Wallace; Charles S. Davis; Paul S. Whitten; Steven G Heeringa (Am J Public Health, 1996)
OBJECTIVES: This study examined risk factors for occupational injury among older workers. METHODS: We analyzed data on 6854 employed nonfarmers from the Health and Retirement Study (HRS), a population-based sample of Americans 51 through 61 years old. RESULTS: Occupational injuries were associated with the following: the occupations of mechanics and repairers (odds ratio [OR] = 2.27), service personnel (OR = 1.68), and laborers (OR = 2.18); jobs requiring heavy lifting (OR = 2.75); workers' impaired hearing (OR = 1.60) and impaired vision (OR = 1.53); and jobs requiring good vision (OR = 1.43). Self-employment was associated with fewer injuries (OR = 0.47). CONCLUSIONS: These results emphasize the importance of a good match between job demands and worker capabilities.
Keywords: Accidents, Occupational; Cross-Sectional Studies; Educational Status; Female; Health Status; Humans; Male; Middle Aged; Occupational Diseases; Regression Analysis; Retirement; Risk Factors; Sex Factors; United States; Wounds and Injuries

The role of ethnicity in the disability and work experience of preretirement-age Americans. - Linda A. Wray (Gerontologist, 1996)
Using the 1992 HRS, this study examines the effects of social and demographic risk factors, including ethnicity, as well as health and job characteristics on disability and work status among 8,701 preretirement-age Americans with work history. Analytic results indicated that non-Anglo ethnicity was not a significant predictor of disability status but that being African American was a strong significant predictor of being a past versus current worker. The primary predictors of disability and work status were health behaviors, effects of health conditions, job characteristics, and workplace adaptations, factors that lend themselves to policy manipulation.
Keywords: Activities of Daily Living; Analysis of Variance; Disabled Persons; Employment; ethnicity; Female; Humans; Male; Middle Aged; Odds Ratio; Regression Analysis; Risk Factors; United States

Who takes early Social Security benefits? The economic and health characteristics of early beneficiaries. - R.V. Burkhauser; Kenneth A. Couch; John W R Phillips (Gerontologist, 1996)
Using the 1992 and 1994 Waves of the Health and Retirement Survey, we compare individuals who first take Social Security benefits at age 62 with those who don't and find that the income and net assets of these two groups are similar in the years just prior to eligibility. However, there is great diversity within the groups, so that poor health appears to be more closely related to lower economic well-being than is early Social Security acceptance status. Our results suggest that raising the Social Security retirement age is not likely to dramatically lower the economic well-being of the typical person aged 62 since only 3% of men aged 62 are receiving Social Security retirement benefits, are in poor health, and have Social Security retirement benefits as their only source of pension income.
Keywords: Aged; Eligibility Determination; Female; Health Status; Health Surveys; Humans; Income; Male; Middle Aged; Pensions; Retirement; Social Security; United States

Effect of recall period on the reporting of occupational injuries among older workers in the Health and Retirement Study. - Zwerling, Craig; Nancy L. Sprince; Robert B Wallace; Charles S. Davis; Paul S. Whitten; Steven G Heeringa (Am J Ind Med, 1995)
Studies of injury morbidity often rely on self-reported survey data. In designing these surveys, researchers must chose between a shorter recall period to minimize recall bias and a longer period to maximize the precision of rate estimates. Using data from the Health and Retirement Study, which employed a recall period of 1 year, we examined the effect of the recall period on rates of occupational injuries among older workers as well as upon rate ratios of these injuries for nine risk factors. We fit a stochastic model to the occupational injury rates as a function of time before the interview and used this model to estimate what the injury rates would have been had we used a 4-week recall period. The adjusted occupational injury rate of 5.9 injuries per 100 workers per year was 36% higher than the rate based on a 1-year recall period. Adjustment for recall period had much less effect on rate ratios, which typically varied by < 10%. Our work suggests that self-reported surveys with longer recall periods may be used to estimate occupational injury rates and also may be useful in studying the associations between occupational injuries and a variety of risk factors.
Keywords: Accidents, Occupational; Adult; Aged; Bias; Cross-Sectional Studies; Data collection; Female; Humans; Incidence; Linear Models; Male; Mental Recall; Middle Aged; Models, Statistical; Reproducibility of Results; Retirement; Risk Factors; Time Factors; United States

Labor force dynamics of older men. - David M. Blau (Econometrica, 1994)
"This paper describes and analyzes movements of older men among labor force states [in the United States] using quarterly observations derived from the Retirement History Survey (RHS)." The results indicate "substantial undercounts in the biannual data, indicating that the prevalence of labor force movements at older ages has been underestimated previously.... The results show that labor force dynamics at older ages are important, including duration and spell occurrence dependence, and work experience effects. These effects are robust to nonparametric controls for unobserved heterogeneity. The estimates indicate that social security benefits have strong effects on the timing of labor force transitions at older ages, but that changes in social security benefit levels over time have not contributed much to the trend toward earlier labor force exit."
Keywords: Americas; Developed Countries; Economics; Employment; Financial Management; Financing, Government; Health Workforce; North America; Retirement; Social Class; Social Security; Socioeconomic factors; United States